Biallelic variation in the choline and ethanolamine transporter underlies a pleiotropic disease spectrum from adult neurodegeneration to severe developmental disorders. - Calame, Daniel G; Wong, Jovi Huixin; Panda, Puravi; Nguyen, Dat Tuan; Leong, Nancy C P; Sangermano, Riccardo; Patankar, Sohil G; Abdel-Hamid, Mohamed; Alabdi, Lama; Safwat, Sylvia; Flannery, Kyle P; Dardas, Zain; et al. (medRxiv, 2024)
encodes Feline leukemia virus subgroup C receptor 1 (FLVCR1), a solute carrier (SLC) transporter within the Major Facilitator Superfamily. FLVCR1 is a widely expressed transmembrane protein with plasma membrane and mitochondrial isoforms implicated in heme, choline, and ethanolamine transport. While knockout mice die with skeletal malformations and defective erythropoiesis reminiscent of Diamond-Blackfan anemia, rare biallelic pathogenic variants are linked to childhood or adult-onset neurodegeneration of the retina, spinal cord, and peripheral nervous system. We ascertained from research and clinical exome sequencing 27 individuals from 20 unrelated families with biallelic ultra-rare missense and predicted loss-of-function (pLoF) variant alleles. We characterize an expansive phenotypic spectrum ranging from adult-onset retinitis pigmentosa to severe developmental disorders with microcephaly, reduced brain volume, epilepsy, spasticity, and premature death. The most severely affected individuals, including three individuals with homozygous pLoF variants, share traits with knockout mice and Diamond-Blackfan anemia including macrocytic anemia and congenital skeletal malformations. Pathogenic missense variants primarily lie within transmembrane domains and reduce choline and ethanolamine transport activity compared with wild-type with minimal impact on FLVCR1 stability or subcellular localization. Several variants disrupt splicing in a mini-gene assay which may contribute to genotype-phenotype correlations. Taken together, these data support an allele-specific gene dosage model in which phenotypic severity reflects residual FLVCR1 activity. This study expands our understanding of Mendelian disorders of choline and ethanolamine transport and demonstrates the importance of choline and ethanolamine in neurodevelopment and neuronal homeostasis.

Closing the gap: Solving complex medically relevant genes at scale. - Mahmoud, Medhat; Harting, John; Corbitt, Holly; Chen, Xiao; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Meng, Qingchang; Han, Tina; Lambert, Christine; Zhang, Siyuan; Baybayan, Primo; Henno, Geoff; et al. (medRxiv, 2024)
Comprehending the mechanism behind human diseases with an established heritable component represents the forefront of personalized medicine. Nevertheless, numerous medically important genes are inaccurately represented in short-read sequencing data analysis due to their complexity and repetitiveness or the so-called 'dark regions' of the human genome. The advent of PacBio as a long-read platform has provided new insights, yet HiFi whole-genome sequencing (WGS) cost remains frequently prohibitive. We introduce a targeted sequencing and analysis framework, Twist Alliance Dark Genes Panel (TADGP), designed to offer phased variants across 389 medically important yet complex autosomal genes. We highlight TADGP accuracy across eleven control samples and compare it to WGS. This demonstrates that TADGP achieves variant calling accuracy comparable to HiFi-WGS data, but at a fraction of the cost. Thus, enabling scalability and broad applicability for studying rare diseases or complementing previously sequenced samples to gain insights into these complex genes. TADGP revealed several candidate variants across all cases and provided insight into diversity when tested on samples from rare disease and cardiovascular disease cohorts. In both cohorts, we identified novel variants affecting individual disease-associated genes (e.g., ). Nevertheless, the annotation of the variants across these 389 medically important genes remains challenging due to their underrepresentation in ClinVar and gnomAD. Consequently, we also offer an annotation resource to enhance the evaluation and prioritization of these variants. Overall, we can demonstrate that TADGP offers a cost-efficient and scalable approach to routinely assess the dark regions of the human genome with clinical relevance.

Empowering personalized pharmacogenomics with generative AI solutions. - Mullai Murugan; Bo Yuan; Eric Venner; Ballantyne, Christie M; Robinson, Katherine M; Coons, James C; Wang, Liwen; Empey, Philip E; Richard A Gibbs (J Am Med Inform Assoc, 2024)
OBJECTIVE: This study evaluates an AI assistant developed using OpenAI's GPT-4 for interpreting pharmacogenomic (PGx) testing results, aiming to improve decision-making and knowledge sharing in clinical genetics and to enhance patient care with equitable access. MATERIALS AND METHODS: The AI assistant employs retrieval-augmented generation (RAG), which combines retrieval and generative techniques, by harnessing a knowledge base (KB) that comprises data from the Clinical Pharmacogenetics Implementation Consortium (CPIC). It uses context-aware GPT-4 to generate tailored responses to user queries from this KB, further refined through prompt engineering and guardrails. RESULTS: Evaluated against a specialized PGx question catalog, the AI assistant showed high efficacy in addressing user queries. Compared with OpenAI's ChatGPT 3.5, it demonstrated better performance, especially in provider-specific queries requiring specialized data and citations. Key areas for improvement include enhancing accuracy, relevancy, and representative language in responses. DISCUSSION: The integration of context-aware GPT-4 with RAG significantly enhanced the AI assistant's utility. RAG's ability to incorporate domain-specific CPIC data, including recent literature, proved beneficial. Challenges persist, such as the need for specialized genetic/PGx models to improve accuracy and relevancy and addressing ethical, regulatory, and safety concerns. CONCLUSION: This study underscores generative AI's potential for transforming healthcare provider support and patient accessibility to complex pharmacogenomic information. While careful implementation of large language models like GPT-4 is necessary, it is clear that they can substantially improve understanding of pharmacogenomic data. With further development, these tools could augment healthcare expertise, provider productivity, and the delivery of equitable, patient-centered healthcare services.

The frequency of pathogenic variation in the All of Us cohort reveals ancestry-driven disparities. - Eric Venner; Patterson, Karynne; Kalra, Divya; Wheeler, Marsha M; Chen, Yi-Ju; Sara E Kalla; Bo Yuan; Karnes, Jason H; Kimberly Walker; Smith, Joshua D; McGee, Sean; Radhakrishnan, Aparna; et al. (Commun Biol, 2024)
Disparities in data underlying clinical genomic interpretation is an acknowledged problem, but there is a paucity of data demonstrating it. The All of Us Research Program is collecting data including whole-genome sequences, health records, and surveys for at least a million participants with diverse ancestry and access to healthcare, representing one of the largest biomedical research repositories of its kind. Here, we examine pathogenic and likely pathogenic variants that were identified in the All of Us cohort. The European ancestry subgroup showed the highest overall rate of pathogenic variation, with 2.26% of participants having a pathogenic variant. Other ancestry groups had lower rates of pathogenic variation, including 1.62% for the African ancestry group and 1.32% in the Latino/Admixed American ancestry group. Pathogenic variants were most frequently observed in genes related to Breast/Ovarian Cancer or Hypercholesterolemia. Variant frequencies in many genes were consistent with the data from the public gnomAD database, with some notable exceptions resolved using gnomAD subsets. Differences in pathogenic variant frequency observed between ancestral groups generally indicate biases of ascertainment of knowledge about those variants, but some deviations may be indicative of differences in disease prevalence. This work will allow targeted precision medicine efforts at revealed disparities.
Keywords: African People; Black People; European People; Genetic Predisposition to Disease; Genomics; Hispanic or Latino; Humans; Population Health; United States

Genetic sex validation for sample tracking in next-generation sequencing clinical testing. - Jianhong Hu; Korchina, Viktoriya; Zouk, Hana; Harden, Maegan V; Murdock, David; Macbeth, Alyssa; Harrison, Steven M; Lennon, Niall; Kovar, Christie; Balasubramanian, Adithya; Zhang, Lan; Chandanavelli, Gauthami; et al. (BMC Res Notes, 2024)
OBJECTIVE: Data from DNA genotyping via a 96-SNP panel in a study of 25,015 clinical samples were utilized for quality control and tracking of sample identity in a clinical sequencing network. The study aimed to demonstrate the value of both the precise SNP tracking and the utility of the panel for predicting the sex-by-genotype of the participants, to identify possible sample mix-ups. RESULTS: Precise SNP tracking showed no sample swap errors within the clinical testing laboratories. In contrast, when comparing predicted sex-by-genotype to the provided sex on the test requisition, we identified 110 inconsistencies from 25,015 clinical samples (0.44%), that had occurred during sample collection or accessioning. The genetic sex predictions were confirmed using additional SNP sites in the sequencing data or high-density genotyping arrays. It was determined that discrepancies resulted from clerical errors (49.09%), samples from transgender participants (3.64%) and stem cell or bone marrow transplant patients (7.27%) along with undetermined sample mix-ups (40%) for which sample swaps occurred prior to arrival at genome centers, however the exact cause of the events at the sampling sites resulting in the mix-ups were not able to be determined.
Keywords: Bone Marrow Transplantation; Clinical Laboratory Services; Genotype; High-Throughput Nucleotide Sequencing; Humans; Laboratories

Germline Genetic Testing and Survival Outcomes Among Children With Rhabdomyosarcoma: A Report From the Children's Oncology Group. - Martin-Giacalone, Bailey A; Li, He; Scheurer, Michael E; Casey, Dana L; Dugan-Perez, Shannon; Marquez-Do, Deborah A; Donna M Muzny; Richard A Gibbs; Barkauskas, Donald A; Hall, David; Stewart, Douglas R; Schiffman, Joshua D; et al. (JAMA Netw Open, 2024)
IMPORTANCE: Determining the impact of germline cancer-predisposition variants (CPVs) on outcomes could inform novel approaches to testing and treating children with rhabdomyosarcoma. OBJECTIVE: To assess whether CPVs are associated with outcome among children with rhabdomyosarcoma. DESIGN, SETTING, AND PARTICIPANTS: In this cohort study, data were obtained for individuals, aged 0.01-23.23 years, newly diagnosed with rhabdomyosarcoma who were treated across 171 Children's Oncology Group sites from March 15, 1999, to December 8, 2017. Data analysis was performed from June 16, 2021, to May 15, 2023. EXPOSURE: The presence of a CPV in 24 rhabdomyosarcoma-associated cancer-predisposition genes (CPGs) or an expanded set of 63 autosomal-dominant CPGs. MAIN OUTCOMES AND MEASURES: Overall survival (OS) and event-free survival (EFS) were the main outcomes, using the Kaplan-Meier estimator to assess survival probabilities and the Cox proportional hazards regression model to adjust for clinical covariates. Analyses were stratified by tumor histology and the fusion status of PAX3 or PAX7 to the FOXO1 gene. RESULTS: In this study of 580 individuals with rhabdomyosarcoma, the median patient age was 5.9 years (range, 0.01-23.23 years), and the male-to-female ratio was 1.5 to 1 (351 [60.5%] male). For patients with CPVs in rhabdomyosarcoma-associated CPGs, EFS was 48.4% compared with 57.8% for patients without a CPV (P = .10), and OS was 53.7% compared with 65.3% for patients without a CPV (P = .06). After adjustment, patients with CPVs had significantly worse OS (adjusted hazard ratio [AHR], 2.49 [95% CI, 1.39-4.45]; P = .002), and the outcomes were not better among patients with embryonal histology (EFS: AHR, 2.25 [95% CI, 1.25-4.06]; P = .007]; OS: AHR, 2.83 [95% CI, 1.47-5.43]; P = .002]). These associations were not due to the development of a second malignant neoplasm, and importantly, patients with fusion-negative rhabdomyosarcoma who harbored a CPV had similarly inferior outcomes as patients with fusion-positive rhabdomyosarcoma without CPVs (EFS: AHR, 1.35 [95% CI, 0.71-2.59]; P = .37; OS: AHR, 1.71 [95% CI, 0.84-3.47]; P = .14). There were no significant differences in outcome by CPV status of the 63 CPG set. CONCLUSIONS AND RELEVANCE: This cohort study identified a group of patients with embryonal rhabdomyosarcoma who had a particularly poor outcome. Other important clinical findings included that individuals with TP53 had poor outcomes independent of second malignant neoplasms and that patients with fusion-negative rhabdomyosarcoma who harbored a CPV had outcomes comparable to patients with fusion-positive rhabdomyosarcoma. These findings suggest that germline CPV testing may aid in clinical prognosis and should be considered in prospective risk-based clinical trials.
Keywords: Child; Cohort Studies; Female; Genetic Testing; Germ Cells; Humans; Male; Neoplasms, Second Primary; Prospective Studies; Rhabdomyosarcoma

Inter and intra-host diversity of RSV in hematopoietic stem cell transplant adults with normal and delayed viral clearance. - Avadhanula, Vasanthi; Agustinho, Daniel Paiva; Menon, Vipin Kumar; Chemaly, Roy F; Shah, Dimpy P; Qin, Xiang; Surathu, Anil; Harshavardhan Doddapaneni; Donna M Muzny; Ginger A Metcalf; Cregeen, Sara Javornik; Richard A Gibbs; et al. (Virus Evol, 2024)
Respiratory syncytial virus (RSV) infection in immunocompromised individuals often leads to prolonged illness, progression to severe lower respiratory tract infection, and even death. How the host immune environment of the hematopoietic stem cell transplant (HCT) adults can affect viral genetic variation during an acute infection is not understood well. In the present study, we performed whole genome sequencing of RSV/A or RSV/B from samples collected longitudinally from HCT adults with normal (<14 days) and delayed (≥14 days) RSV clearance who were enrolled in a ribavirin trial. We determined the inter-host and intra-host genetic variation of RSV and the effect of mutations on putative glycosylation sites. The inter-host variation of RSV is centered in the attachment (G) and fusion (F) glycoprotein genes followed by polymerase (L) and matrix (M) genes. Interestingly, the overall genetic variation was constant between normal and delayed clearance groups for both RSV/A and RSV/B. Intra-host variation primarily occurred in the G gene followed by non-structural protein (NS1) and L genes; however, gain or loss of stop codons and frameshift mutations appeared only in the G gene and only in the delayed viral clearance group. Potential gain or loss of O-linked glycosylation sites in the G gene occurred both in RSV/A and RSV/B isolates. For RSV F gene, loss of N-linked glycosylation site occurred in three RSV/B isolates within an antigenic epitope. Both oral and aerosolized ribavirin did not cause any mutations in the L gene. In summary, prolonged viral shedding and immune deficiency resulted in RSV variation, especially in structural mutations in the G gene, possibly associated with immune evasion. Therefore, sequencing and monitoring of RSV isolates from immunocompromised patients are crucial as they can create escape mutants that can impact the effectiveness of upcoming vaccines and treatments.

Multilocus pathogenic variants contribute to intrafamilial clinical heterogeneity: a retrospective study of sibling pairs with neurodevelopmental disorders. - Bozkurt-Yozgatli, Tugce; Pehlivan, Davut; Richard A Gibbs; Sezerman, Ugur; Posey, Jennifer E; Lupski, James R; Coban-Akdemir, Zeynep (BMC Med Genomics, 2024)
BACKGROUND: Multilocus pathogenic variants (MPVs) are genetic changes that affect multiple gene loci or regions of the genome, collectively leading to multiple molecular diagnoses. MPVs may also contribute to intrafamilial phenotypic variability between affected individuals within a nuclear family. In this study, we aim to gain further insights into the influence of MPVs on a disease manifestation in individual research subjects and explore the complexities of the human genome within a familial context. METHODS: We conducted a systematic reanalysis of exome sequencing data and runs of homozygosity (ROH) regions of 47 sibling pairs previously diagnosed with various neurodevelopmental disorders (NDD). RESULTS: We found siblings with MPVs driven by long ROH regions in 8.5% of families (4/47). The patients with MPVs exhibited significantly higher F values (p-value = 1.4e-2) and larger total ROH length (p-value = 1.8e-2). Long ROH regions mainly contribute to this pattern; the siblings with MPVs have a larger total size of long ROH regions than their siblings in all families (p-value = 6.9e-3). Whereas the short ROH regions in the siblings with MPVs are lower in total size compared to their sibling pairs with single locus pathogenic variants (p-value = 0.029), and there are no statistically significant differences in medium ROH regions between sibling pairs (p-value = 0.52). CONCLUSION: This study sheds light on the significance of considering MPVs in families with affected sibling pairs and the role of ROH as an adjuvant tool in explaining clinical variability within families. Identifying individuals carrying MPVs may have implications for disease management, identification of possible disease risks to different family members, genetic counseling and exploring personalized treatment approaches.
Keywords: Biological Variation, Population; Genome, Human; Genotype; Homozygote; Humans; Polymorphism, Single Nucleotide; Retrospective Studies; Siblings

NODAL variants are associated with a continuum of laterality defects from simple D-transposition of the great arteries to heterotaxy. - Dardas, Zain; Fatih, Jawid M; Jolly, Angad; Dawood, Moez; Du, Haowei; Grochowski, Christopher M; Jones, Edward G; Jhangiani, Shalini N; Wehrens, Xander H T; Liu, Pengfei; Bi, Weimin; Eric Boerwinkle; et al. (Genome Med, 2024)
BACKGROUND: NODAL signaling plays a critical role in embryonic patterning and heart development in vertebrates. Genetic variants resulting in perturbations of the TGF-β/NODAL signaling pathway have reproducibly been shown to cause laterality defects in humans. To further explore this association and improve genetic diagnosis, the study aims to identify and characterize a broader range of NODAL variants in a large number of individuals with laterality defects. METHODS: We re-analyzed a cohort of 321 proband-only exomes of individuals with clinically diagnosed laterality congenital heart disease (CHD) using family-based, rare variant genomic analyses. To this cohort we added 12 affected subjects with known NODAL variants and CHD from institutional research and clinical cohorts to investigate an allelic series. For those with candidate contributory variants, variant allele confirmation and segregation analysis were studied by Sanger sequencing in available family members. Array comparative genomic hybridization and droplet digital PCR were utilized for copy number variants (CNV) validation and characterization. We performed Human Phenotype Ontology (HPO)-based quantitative phenotypic analyses to dissect allele-specific phenotypic differences. RESULTS: Missense, nonsense, splice site, indels, and/or structural variants of NODAL were identified as potential causes of heterotaxy and other laterality defects in 33 CHD cases. We describe a recurrent complex indel variant for which the nucleic acid secondary structure predictions implicate secondary structure mutagenesis as a possible mechanism for formation. We identified two CNV deletion alleles spanning NODAL in two unrelated CHD cases. Furthermore, 17 CHD individuals were found (16/17 with known Hispanic ancestry) to have the c.778G > A:p.G260R NODAL missense variant which we propose reclassification from variant of uncertain significance (VUS) to likely pathogenic. Quantitative HPO-based analyses of the observed clinical phenotype for all cases with p.G260R variation, including heterozygous, homozygous, and compound heterozygous cases, reveal clustering of individuals with biallelic variation. This finding provides evidence for a genotypic-phenotypic correlation and an allele-specific gene dosage model. CONCLUSION: Our data further support a role for rare deleterious variants in NODAL as a cause for sporadic human laterality defects, expand the repertoire of observed anatomical complexity of potential cardiovascular anomalies, and implicate an allele specific gene dosage model.
Keywords: Animals; Arteries; Comparative Genomic Hybridization; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Phenotype; Transposition of Great Vessels

Somatic mutations of esophageal adenocarcinoma: a comparison between Black and White patients. - Lim, Hyeyeun; Marie-Claude Gingras; Zhao, Jing; Byun, Jinyoung; Castro, Patricia D; Tsavachidis, Spiridon; Jianhong Hu; Harshavardhan Doddapaneni; Yi Han; Donna M Muzny; Richard A Gibbs; Amos, Christopher I; et al. (Sci Rep, 2024)
Esophageal adenocarcinoma is the most common histological subtype of esophageal cancer in Western countries and shows poor prognosis with rapid growth. EAC is characterized by a strong male predominance and racial disparity. EAC is up to fivefold more common among Whites than Blacks, yet Black patients with EAC have poorer survival rates. The racial disparity remains largely unknown, and there is limited knowledge of mutations in EAC regarding racial disparities. We used whole-exome sequencing to show somatic mutation profiles derived from tumor samples from 18 EAC male patients. We identified three molecular subgroups based on the pre-defined esophageal cancer-specific mutational signatures. Group 1 is associated with age and NTHL1 deficiency-related signatures. Group 2 occurs primarily in Black patients and is associated with signatures related to DNA damage from oxidative stress and NTHL1 deficiency-related signatures. Group 3 is associated with defective homologous recombination-based DNA often caused by BRCA mutation in White patients. We observed significantly mutated race related genes (LCE2B in Black, SDR39U1 in White) were (q-value < 0.1). Our findings underscore the possibility of distinct molecular mutation patterns in EAC among different races. Further studies are needed to validate our findings, which could contribute to precision medicine in EAC.
Keywords: Adenocarcinoma; Black or African American; Esophageal Neoplasms; Exome Sequencing; Female; Humans; Male; Mutation; White

β-Actin G342D as a Cause of NK Cell Deficiency Impairing Lytic Synapse Termination. - Reed, Abigail E; Peraza, Jackeline; van den Haak, Frederique; Hernandez, Evelyn R; Richard A Gibbs; Chinn, Ivan K; Lupski, James R; Marchi, Enrica; Reshef, Ran; Alobeid, Bachir; Mace, Emily M; Orange, Jordan S (J Immunol, 2024)
NK cell deficiency (NKD) occurs when an individual's major clinical immunodeficiency derives from abnormal NK cells and is associated with several genetic etiologies. Three categories of β-actin-related diseases with over 60 ACTB (β-actin) variants have previously been identified, none with a distinct NK cell phenotype. An individual with mild developmental delay, macrothrombocytopenia, and susceptibility to infections, molluscum contagiosum virus, and EBV-associated lymphoma had functional NKD for over a decade. A de novo ACTB variant encoding G342D β-actin was identified and was consistent with the individual's developmental and platelet phenotype. This novel variant also was found to have direct impact in NK cells because its expression in the human NK cell line YTS (YTS-NKD) caused increased cell spreading in lytic immune synapses created on activating surfaces. YTS-NKD cells were able to degranulate and perform cytotoxicity, but they demonstrated defective serial killing because of prolonged conjugation to the killed target cell and thus were effectively unable to terminate lytic synapses. G342D β-actin results in a novel, to our knowledge, mechanism of functional NKD via increased synaptic spreading and defective lytic synapse termination with resulting impaired serial killing, leading to overall reductions in NK cell cytotoxicity.
Keywords: Actins; Blood Platelets; Cell Line; Humans; Immunologic Deficiency Syndromes; Killer Cells, Natural

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Eric Boerwinkle; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.
Keywords: Adult; Aged; Apolipoproteins B; Cholesterol, LDL; Coronary Disease; DNA; Female; Humans; Male; Middle Aged; Proprotein Convertase 9; Prospective Studies

A biallelic frameshift indel in PPP1R35 as a cause of primary microcephaly. - Dawood, Moez; Akay, Gulsen; Mitani, Tadahiro; Marafi, Dana; Fatih, Jawid M; Gezdirici, Alper; Najmabadi, Hossein; Kahrizi, Kimia; Punetha, Jaya; Grochowski, Christopher M; Du, Haowei; Jolly, Angad; et al. (Am J Med Genet A, 2023)
Protein phosphatase 1 regulatory subunit 35 (PPP1R35) encodes a centrosomal protein required for recruiting microtubule-binding elongation machinery. Several proteins in this centriole biogenesis pathway correspond to established primary microcephaly (MCPH) genes, and multiple model organism studies hypothesize PPP1R35 as a candidate MCPH gene. Here, using exome sequencing (ES) and family-based rare variant analyses, we report a homozygous, frameshifting indel deleting the canonical stop codon in the last exon of PPP1R35 [Chr7: c.753_*3delGGAAGCGTAGACCinsCG (p.Trp251Cysfs*22)]; the variant allele maps in a 3.7 Mb block of absence of heterozygosity (AOH) in a proband with severe MCPH (-4.3 SD at birth, -6.1 SD by 42 months), pachygyria, and global developmental delay from a consanguineous Turkish kindred. Droplet digital PCR (ddPCR) confirmed mutant mRNA expression in fibroblasts. In silico prediction of the translation of mutant PPP1R35 is expected to be elongated by 18 amino acids before encountering a downstream stop codon. This complex indel allele is absent in public databases (ClinVar, gnomAD, ARIC, 1000 genomes) and our in-house database of 14,000+ exomes including 1800+ Turkish exomes supporting predicted pathogenicity. Comprehensive literature searches for PPP1R35 variants yielded two probands affected with severe microcephaly (-15 SD and -12 SD) with the same homozygous indel from a single, consanguineous, Iranian family from a cohort of 404 predominantly Iranian families. The lack of heterozygous cases in two large cohorts representative of the genetic background of these two families decreased our suspicion of a founder allele and supports the contention of a recurrent mutation. We propose two potential secondary structure mutagenesis models for the origin of this variant allele mediated by hairpin formation between complementary GC rich segments flanking the stop codon via secondary structure mutagenesis.
Keywords: Codon, Terminator; Frameshift Mutation; Humans; Infant, Newborn; Iran; Microcephaly; Microtubule-Associated Proteins; Pedigree

Biallelic missense variants in COG3 cause a congenital disorder of glycosylation with impairment of retrograde vesicular trafficking. - Duan, Ruizhi; Marafi, Dana; Xia, Zhi-Jie; Ng, Bobby G; Maroofian, Reza; Sumya, Farhana Taher; Saad, Ahmed K; Du, Haowei; Fatih, Jawid M; Hunter, Jill V; Elbendary, Hasnaa M; Baig, Shahid M; et al. (J Inherit Metab Dis, 2023)
Biallelic variants in genes for seven out of eight subunits of the conserved oligomeric Golgi complex (COG) are known to cause recessive congenital disorders of glycosylation (CDG) with variable clinical manifestations. COG3 encodes a constituent subunit of the COG complex that has not been associated with disease traits in humans. Herein, we report two COG3 homozygous missense variants in four individuals from two unrelated consanguineous families that co-segregated with COG3-CDG presentations. Clinical phenotypes of affected individuals include global developmental delay, severe intellectual disability, microcephaly, epilepsy, facial dysmorphism, and variable neurological findings. Biochemical analysis of serum transferrin from one family showed the loss of a single sialic acid. Western blotting on patient-derived fibroblasts revealed reduced COG3 and COG4. Further experiments showed delayed retrograde vesicular recycling in patient cells. This report adds to the knowledge of the COG-CDG network by providing collective evidence for a COG3-CDG rare disease trait and implicating a likely pathology of the disorder as the perturbation of Golgi trafficking.
Keywords: Adaptor Proteins, Vesicular Transport; Congenital Disorders of Glycosylation; Fibroblasts; Glycosylation; Humans; Phenotype

Circulating tumor DNA sequencing of pediatric solid and brain tumor patients: An institutional feasibility study. - Mangum, Ross; Reuther, Jacquelyn; Sen Baksi, Koel; Gandhi, Ilavarasi; Zabriskie, Ryan C; Recinos, Alva; Raesz-Martinez, Robin; Lin, Frank Y; Potter, Samara L; Sher, Andrew C; Kralik, Stephen F; Mohila, Carrie A; et al. (Pediatr Hematol Oncol, 2023)
The potential of circulating tumor DNA (ctDNA) analysis to serve as a real-time "liquid biopsy" for children with central nervous system (CNS) and non-CNS solid tumors remains to be fully elucidated. We conducted a study to investigate the feasibility and potential clinical utility of ctDNA sequencing in pediatric patients enrolled on an institutional clinical genomics trial. A total of 240 patients had tumor DNA profiling performed during the study period. Plasma samples were collected at study enrollment from 217 patients and then longitudinally from a subset of patients. Successful cell-free DNA extraction and quantification occurred in 216 of 217 (99.5%) of these initial samples. Twenty-four patients were identified whose tumors harbored 30 unique variants that were potentially detectable on a commercially-available ctDNA panel. Twenty of these 30 mutations (67%) were successfully detected by next-generation sequencing in the ctDNA from at least one plasma sample. The rate of ctDNA mutation detection was higher in patients with non-CNS solid tumors (7/9, 78%) compared to those with CNS tumors (9/15, 60%). A higher ctDNA mutation detection rate was also observed in patients with metastatic disease (9/10, 90%) compared to non-metastatic disease (7/14, 50%), although tumor-specific variants were detected in a few patients in the absence of radiographic evidence of disease. This study illustrates the feasibility of incorporating longitudinal ctDNA analysis into the management of relapsed or refractory patients with childhood CNS or non-CNS solid tumors.
Keywords: Biomarkers, Tumor; Brain Neoplasms; Child; Circulating Tumor DNA; Feasibility Studies; High-Throughput Nucleotide Sequencing; Humans; Mutation

Deleterious heteroplasmic mitochondrial mutations are associated with an increased risk of overall and cancer-specific mortality. - Hong, Yun Soo; Battle, Stephanie L; Shi, Wen; Puiu, Daniela; Pillalamarri, Vamsee; Xie, Jiaqi; Pankratz, Nathan; Lake, Nicole J; Lek, Monkol; Rotter, Jerome I; Rich, Stephen S; Kooperberg, Charles; et al. (Nat Commun, 2023)
Mitochondria carry their own circular genome and disruption of the mitochondrial genome is associated with various aging-related diseases. Unlike the nuclear genome, mitochondrial DNA (mtDNA) can be present at 1000 s to 10,000 s copies in somatic cells and variants may exist in a state of heteroplasmy, where only a fraction of the DNA molecules harbors a particular variant. We quantify mtDNA heteroplasmy in 194,871 participants in the UK Biobank and find that heteroplasmy is associated with a 1.5-fold increased risk of all-cause mortality. Additionally, we functionally characterize mtDNA single nucleotide variants (SNVs) using a constraint-based score, mitochondrial local constraint score sum (MSS) and find it associated with all-cause mortality, and with the prevalence and incidence of cancer and cancer-related mortality, particularly leukemia. These results indicate that mitochondria may have a functional role in certain cancers, and mitochondrial heteroplasmic SNVs may serve as a prognostic marker for cancer, especially for leukemia.
Keywords: DNA, Mitochondrial; Heteroplasmy; Humans; Leukemia; Mitochondria; Mutation

Exome-wide assessment of isolated biliary atresia: A report from the National Birth Defects Prevention Study using child-parent trios and a case-control design to identify novel rare variants. - Sok, Pagna; Aniko Sabo; Almli, Lynn M; Jenkins, Mary M; Nembhard, Wendy N; Agopian, A J; Bamshad, Michael J; Blue, Elizabeth E; Brody, Lawrence C; Brown, Austin L; Browne, Marilyn L; Canfield, Mark A; et al. (Am J Med Genet A, 2023)
The etiology of biliary atresia (BA) is unknown, but recent studies suggest a role for rare protein-altering variants (PAVs). Exome sequencing data from the National Birth Defects Prevention Study on 54 child-parent trios, one child-mother duo, and 1513 parents of children with other birth defects were analyzed. Most (91%) cases were isolated BA. We performed (1) a trio-based analysis to identify rare de novo, homozygous, and compound heterozygous PAVs and (2) a case-control analysis using a sequence kernel-based association test to identify genes enriched with rare PAVs. While we replicated previous findings on PKD1L1, our results do not suggest that recurrent de novo PAVs play important roles in BA susceptibility. In fact, our finding in NOTCH2, a disease gene associated with Alagille syndrome, highlights the difficulty in BA diagnosis. Notably, IFRD2 has been implicated in other gastrointestinal conditions and warrants additional study. Overall, our findings strengthen the hypothesis that the etiology of BA is complex.
Keywords: Biliary Atresia; Case-Control Studies; Exome; Homozygote; Humans; Membrane Proteins; Parents

Familial Hypercholesterolemia in the Electronic Medical Records and Genomics Network: Prevalence, Penetrance, Cardiovascular Risk, and Outcomes After Return of Results. - Dikilitas, Ozan; Sherafati, Alborz; Saadatagah, Seyedmohammad; Satterfield, Benjamin A; Kochan, David C; Anderson, Katherine C; Chung, Wendy K; Hebbring, Scott J; Salvati, Zachary M; Sharp, Richard R; Sturm, Amy C; Richard A Gibbs; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: The implications of secondary findings detected in large-scale sequencing projects remain uncertain. We assessed prevalence and penetrance of pathogenic familial hypercholesterolemia (FH) variants, their association with coronary heart disease (CHD), and 1-year outcomes following return of results in phase III of the electronic medical records and genomics network. METHODS: Adult participants (n=18 544) at 7 sites were enrolled in a prospective cohort study to assess the clinical impact of returning results from targeted sequencing of 68 actionable genes, including , , and . FH variant prevalence and penetrance (defined as low-density lipoprotein cholesterol >155 mg/dL) were estimated after excluding participants enrolled on the basis of hypercholesterolemia. Multivariable logistic regression was used to estimate the odds of CHD compared to age- and sex-matched controls without FH-associated variants. Process (eg, referral to a specialist or ordering new tests), intermediate (eg, new diagnosis of FH), and clinical (eg, treatment modification) outcomes within 1 year after return of results were ascertained by electronic health record review. RESULTS: The prevalence of FH-associated pathogenic variants was 1 in 188 (69 of 13,019 unselected participants). Penetrance was 87.5%. The presence of an FH variant was associated with CHD (odds ratio, 3.02 [2.00-4.53]) and premature CHD (odds ratio, 3.68 [2.34-5.78]). At least 1 outcome occurred in 92% of participants; 44% received a new diagnosis of FH and 26% had treatment modified following return of results. CONCLUSIONS: In a multisite cohort of electronic health record-linked biobanks, monogenic FH was prevalent, penetrant, and associated with presence of CHD. Nearly half of participants with an FH-associated variant received a new diagnosis of FH and a quarter had treatment modified after return of results. These results highlight the potential utility of sequencing electronic health record-linked biobanks to detect FH.
Keywords: Adult; Cardiovascular Diseases; Coronary Artery Disease; Electronic Health Records; Genomics; Heart Disease Risk Factors; Humans; Hyperlipoproteinemia Type II; Penetrance; Prevalence; Proprotein Convertase 9; Prospective Studies; Risk Factors

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Eric Boerwinkle; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; Hersh, Craig P; et al. (Genetics, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-sequencing data in GTEx V8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased whole genome sequencing data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.
Keywords: Alternative Splicing; Exons; Genotype; Penetrance; RNA Splice Sites; RNA Splicing; RNA, Messenger

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Eric Boerwinkle; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; Hersh, Craig P; et al. (bioRxiv, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-seq data in GTEx v8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased WGS data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.

Genetic Sex Validation for Sample Tracking in Clinical Testing. - Jianhong Hu; Korchina, Viktoriya; Zouk, Hana; Harden, Maegan V; Murdock, David; Macbeth, Alyssa; Harrison, Steven M; Lennon, Niall; Kovar, Christie; Balasubramanian, Adithya; Zhang, Lan; Chandanavelli, Gauthami; et al. (Res Sq, 2023)
OBJECTIVE: Data from DNA genotyping via a 96-SNP panel in a study of 25,015 clinical samples were utilized for quality control and tracking of sample identity in a clinical sequencing network. The study aimed to demonstrate the value of both the precise SNP tracking and the utility of the panel for predicting the sex-by-genotype of the participants, to identify possible sample mix-ups. RESULTS: Precise SNP tracking showed no sample swap errors within the clinical testing laboratories. In contrast, when comparing predicted sex-by-genotype to the provided sex on the test requisition, we identified 110 inconsistencies from 25,015 clinical samples (0.44%), that had occurred during sample collection or accessioning. The genetic sex predictions were confirmed using additional SNP sites in the sequencing data or high-density genotyping arrays. It was determined that discrepancies resulted from clerical errors, samples from transgender participants and stem cell or bone marrow transplant patients along with undetermined sample mix-ups.

The genomic landscape of familial glioma. - Choi, Dong-Joo; Armstrong, Georgina; Lozzi, Brittney; Vijayaraghavan, Prashanth; Plon, Sharon E; Wong, Terence C; Eric Boerwinkle; Donna M Muzny; Chen, Hsiao-Chi; Richard A Gibbs; Ostrom, Quinn T; Melin, Beatrice; et al. (Sci Adv, 2023)
Glioma is a rare brain tumor with a poor prognosis. Familial glioma is a subset of glioma with a strong genetic predisposition that accounts for approximately 5% of glioma cases. We performed whole-genome sequencing on an exploratory cohort of 203 individuals from 189 families with a history of familial glioma and an additional validation cohort of 122 individuals from 115 families. We found significant enrichment of rare deleterious variants of seven genes in both cohorts, and the most significantly enriched gene was ( = 0.0006). Furthermore, we identified rare noncoding variants in both cohorts that were predicted to affect transcription factor binding sites or cause cryptic splicing. Last, we selected a subset of discovered genes for validation by CRISPR knockdown screening and found that , have profound impacts on proliferation. This study performs comprehensive surveillance of the genomic landscape of familial glioma.
Keywords: Brain Neoplasms; Calcium-Binding Proteins; DNA-Binding Proteins; Genetic Predisposition to Disease; Genomics; Glioma; Humans; Tumor Suppressor Proteins; Whole Genome Sequencing

Identification of allele-specific KIV-2 repeats and impact on Lp(a) measurements for cardiovascular disease risk. - Behera, S; Belyeu, J R; Chen, X; Paulin, L F; Nguyen, N Q H; Newman, E; Mahmoud, M; Menon, V K; Qi, Q; Joshi, P; Marcovina, S; Rossi, M; et al. (bioRxiv, 2023)
The abundance of Lp(a) protein holds significant implications for the risk of cardiovascular disease (CVD), which is directly impacted by the copy number (CN) of KIV-2, a 5.5 kbp sub-region. KIV-2 is highly polymorphic in the population and accurate analysis is challenging. In this study, we present the DRAGEN KIV-2 CN caller, which utilizes short reads. Data across 166 WGS show that the caller has high accuracy, compared to optical mapping and can further phase ~50% of the samples. We compared KIV-2 CN numbers to 24 previously postulated KIV-2 relevant SNVs, revealing that many are ineffective predictors of KIV-2 copy number. Population studies, including USA-based cohorts, showed distinct KIV-2 CN, distributions for European-, African-, and Hispanic-American populations and further underscored the limitations of SNV predictors. We demonstrate that the CN estimates correlate significantly with the available Lp(a) protein levels and that phasing is highly important.

Longitudinal host transcriptional responses to SARS-CoV-2 infection in adults with extremely high viral load. - Avadhanula, Vasanthi; Creighton, Chad J; Ferlic-Stark, Laura; Sucgang, Richard; Zhang, Yiqun; Nagaraj, Divya; Nicholson, Erin G; Rajan, Anubama; Menon, Vipin Kumar; Harshavardhan Doddapaneni; Donna M Muzny; Ginger A Metcalf; et al. (bioRxiv, 2023)
Current understanding of viral dynamics of SARS-CoV-2 and host responses driving the pathogenic mechanisms in COVID-19 is rapidly evolving. Here, we conducted a longitudinal study to investigate gene expression patterns during acute SARS-CoV-2 illness. Cases included SARS-CoV-2 infected individuals with extremely high viral loads early in their illness, individuals having low SARS-CoV-2 viral loads early in their infection, and individuals testing negative for SARS-CoV-2. We could identify widespread transcriptional host responses to SARS-CoV-2 infection that were initially most strongly manifested in patients with extremely high initial viral loads, then attenuating within the patient over time as viral loads decreased. Genes correlated with SARS-CoV-2 viral load over time were similarly differentially expressed across independent datasets of SARS-CoV-2 infected lung and upper airway cells, from both in vitro systems and patient samples. We also generated expression data on the human nose organoid model during SARS-CoV-2 infection. The human nose organoid-generated host transcriptional response captured many aspects of responses observed in the above patient samples, while suggesting the existence of distinct host responses to SARS-CoV-2 depending on the cellular context, involving both epithelial and cellular immune responses. Our findings provide a catalog of SARS-CoV-2 host response genes changing over time.

Monoallelic variation in DHX9, the gene encoding the DExH-box helicase DHX9, underlies neurodevelopment disorders and Charcot-Marie-Tooth disease. - Calame, Daniel G; Guo, Tianyu; Wang, Chen; Garrett, Lillian; Jolly, Angad; Dawood, Moez; Kurolap, Alina; Henig, Noa Zunz; Fatih, Jawid M; Herman, Isabella; Du, Haowei; Mitani, Tadahiro; et al. (Am J Hum Genet, 2023)
DExD/H-box RNA helicases (DDX/DHX) are encoded by a large paralogous gene family; in a subset of these human helicase genes, pathogenic variation causes neurodevelopmental disorder (NDD) traits and cancer. DHX9 encodes a BRCA1-interacting nuclear helicase regulating transcription, R-loops, and homologous recombination and exhibits the highest mutational constraint of all DDX/DHX paralogs but remains unassociated with disease traits in OMIM. Using exome sequencing and family-based rare-variant analyses, we identified 20 individuals with de novo, ultra-rare, heterozygous missense or loss-of-function (LoF) DHX9 variant alleles. Phenotypes ranged from NDDs to the distal symmetric polyneuropathy axonal Charcot-Marie-Tooth disease (CMT2). Quantitative Human Phenotype Ontology (HPO) analysis demonstrated genotype-phenotype correlations with LoF variants causing mild NDD phenotypes and nuclear localization signal (NLS) missense variants causing severe NDD. We investigated DHX9 variant-associated cellular phenotypes in human cell lines. Whereas wild-type DHX9 was restricted to the nucleus, NLS missense variants abnormally accumulated in the cytoplasm. Fibroblasts from an individual with an NLS variant also showed abnormal cytoplasmic DHX9 accumulation. CMT2-associated missense variants caused aberrant nucleolar DHX9 accumulation, a phenomenon previously associated with cellular stress. Two NDD-associated variants, p.Gly411Glu and p.Arg761Gln, altered DHX9 ATPase activity. The severe NDD-associated variant p.Arg141Gln did not affect DHX9 localization but instead increased R-loop levels and double-stranded DNA breaks. Dhx9 mice exhibited hypoactivity in novel environments, tremor, and sensorineural hearing loss. All together, these results establish DHX9 as a critical regulator of mammalian neurodevelopment and neuronal homeostasis.
Keywords: Animals; Cell Line; Charcot-Marie-Tooth Disease; DEAD-box RNA Helicases; Dichlorodiphenyl Dichloroethylene; DNA Helicases; Humans; Mammals; Mice; Neoplasm Proteins; Neurodevelopmental Disorders

Novel LSS variants in alopecia and intellectual disability syndrome: New case report and clinical spectrum of LSS-related rare disease traits. - Elbendary, Hasnaa M; Marafi, Dana; Saad, Ahmed K; Elhossini, Rasha; Duan, Ruizhi; Rafat, Karima; Jhangiani, Shalini N; Richard A Gibbs; Pehlivan, Davut; Calame, Daniel G; Posey, Jennifer E; James R Lupski; et al. (Clin Genet, 2023)
Pathogenic biallelic variants in LSS are associated with three Mendelian rare disease traits including congenital cataract type 44, autosomal recessive hypotrichosis type 14, and alopecia-intellectual disability syndrome type 4 (APMR4). We performed trio research exome sequencing on a family with a four-year-old male with global developmental delay, epilepsy and striking alopecia, and identified novel compound heterozygous LSS splice site (c.14+2T>C) and missense (c.1357 G>A; p.V453L) variant alleles. Rare features associated with APMR4 such as cryptorchidism, micropenis, mild cortical brain atrophy and thin corpus callosum were detected. Previously unreported APMR4 findings including cerebellar involvement in the form of unsteady ataxic gait, small vermis with prominent folia, were noted. A review of all reported variants to date in 29 families with LSS-related phenotypes showed an emerging genotype-phenotype correlation. Our report potentially expands LSS-related phenotypic spectrum and highlights the importance of performing brain imaging in LSS-related conditions.
Keywords: Alopecia; Humans; Intellectual Disability; Male; Mutation; Phenotype; Rare Diseases; Syndrome

Rare variant enrichment analysis supports as a contributory driver gene in the etiology of Mayer-Rokitansky-Küster-Hauser syndrome. - Jolly, Angad; Du, Haowei; Borel, Christelle; Chen, Na; Zhao, Sen; Grochowski, Christopher M; Duan, Ruizhi; Fatih, Jawid M; Dawood, Moez; Salvi, Sejal; Jhangiani, Shalini N; Donna M Muzny; et al. (HGG Adv, 2023)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is characterized by aplasia of the female reproductive tract; the syndrome can include renal anomalies, absence or dysgenesis, and skeletal anomalies. While functional models have elucidated several candidate genes, only (MIM: 603490) variants have been definitively associated with a subtype of MRKH with hyperandrogenism (MIM: 158330). DNA from 148 clinically diagnosed MRKH probands across 144 unrelated families and available family members from North America, Europe, and South America were exome sequenced (ES) and by family-based genomics analyzed for rare likely deleterious variants. A replication cohort consisting of 442 Han Chinese individuals with MRKH was used to further reproduce findings in diverse genetic backgrounds. Proband and OMIM phenotypes annotated using the Human Phenotype Ontology were analyzed to quantitatively delineate the phenotypic spectrum associated with variant alleles found in our MRKH cohort and those previously published. This study reports 18 novel variant alleles, 16 within a multiethnic MRKH cohort and two within a congenital scoliosis cohort. Cohort-wide analyses for a burden of rare variants within a single gene identified likely damaging variants in (MIM: 617782), a known disease gene for renal hypoplasia and uterine abnormalities (MIM: 617805), in 16 of 590 MRKH probands. variant alleles, including a CNV null allele, were found in 8 MRKH type 1 probands and 8 MRKH type II probands. This study used quantitative phenotypic analyses in a worldwide multiethnic cohort to identify and strengthen the association of to isolated uterine agenesis (MRKH type I) and syndromic MRKH type II.
Keywords: 46, XX Disorders of Sex Development; Female; Humans; Urogenital Abnormalities; Uterus

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed whole-genome sequencing study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Eric Boerwinkle; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (Am J Hum Genet, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions in lipid metabolism. Large-scale whole-genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess more associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with measurement of blood lipids and lipoproteins (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare-variant aggregate association tests using the STAAR (variant-set test for association using annotation information) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare-coding variants in nearby protein-coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500-kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variation and rare protein-coding variation at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNAs.
Keywords: Genome-Wide Association Study; Humans; Lipids; Polymorphism, Single Nucleotide; Precision Medicine; RNA, Long Noncoding; Whole Genome Sequencing

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Eric Boerwinkle; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

Type 2 Diabetes Modifies the Association of CAD Genomic Risk Variants With Subclinical Atherosclerosis. - Hasbani, Natalie R; Westerman, Kenneth E; Kwak, Soo Heon; Chen, Han; Li, Xihao; Di Corpo, Daniel; Wessel, Jennifer; Bis, Joshua C; Sarnowski, Chloe; Wu, Peitao; Bielak, Lawrence F; Guo, Xiuqing; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of coronary artery disease (CAD), but questions remain about the underlying pathology. Identifying which CAD loci are modified by T2D in the development of subclinical atherosclerosis (coronary artery calcification [CAC], carotid intima-media thickness, or carotid plaque) may improve our understanding of the mechanisms leading to the increased CAD in T2D. METHODS: We compared the common and rare variant associations of known CAD loci from the literature on CAC, carotid intima-media thickness, and carotid plaque in up to 29 670 participants, including up to 24 157 normoglycemic controls and 5513 T2D cases leveraging whole-genome sequencing data from the Trans-Omics for Precision Medicine program. We included first-order T2D interaction terms in each model to determine whether CAD loci were modified by T2D. The genetic main and interaction effects were assessed using a joint test to determine whether a CAD variant, or gene-based rare variant set, was associated with the respective subclinical atherosclerosis measures and then further determined whether these loci had a significant interaction test. RESULTS: Using a Bonferroni-corrected significance threshold of <1.6×10, we identified 3 genes (, , and ) associated with CAC and 2 genes ( and ) associated with carotid intima-media thickness and carotid plaque, respectively, through gene-based rare variant set analysis. Both and also had significantly different associations for CAC in T2D cases versus controls. No significant interaction tests were identified through the candidate single-variant analysis. CONCLUSIONS: These results highlight T2D as an important modifier of rare variant associations in CAD loci with CAC.
Keywords: Atherosclerosis; Carotid Intima-Media Thickness; Coronary Artery Disease; Diabetes Mellitus, Type 2; Genomics; Humans; Plaque, Atherosclerotic; Risk Factors

Whole Genome Analysis of Venous Thromboembolism: the Trans-Omics for Precision Medicine Program. - Seyerle, Amanda A; Laurie, Cecelia A; Coombes, Brandon J; Jain, Deepti; Conomos, Matthew P; Brody, Jennifer; Chen, Ming-Huei; Gogarten, Stephanie M; Beutel, Kathleen M; Gupta, Namrata; Heckbert, Susan R; Jackson, Rebecca D; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Risk for venous thromboembolism has a strong genetic component. Whole genome sequencing from the TOPMed program (Trans-Omics for Precision Medicine) allowed us to look for new associations, particularly rare variants missed by standard genome-wide association studies. METHODS: The 3793 cases and 7834 controls (11.6% of cases were individuals of African, Hispanic/Latino, or Asian ancestry) were analyzed using a single variant approach and an aggregate gene-based approach using our primary filter (included only loss-of-function and missense variants predicted to be deleterious) and our secondary filter (included all missense variants). RESULTS: Single variant analyses identified associations at 5 known loci. Aggregate gene-based analyses identified only (odds ratio, 6.2 for carriers of rare variants; =7.4×10) when using our primary filter. Employing our secondary variant filter led to a smaller effect size at (odds ratio, 3.8; =1.6×10), while excluding variants found only in rare isoforms led to a larger one (odds ratio, 7.5). Different filtering strategies improved the signal for 2 other known genes: became significant (minimum =1.8×10 with the secondary filter), while did not (minimum =4.4×10 with minor allele frequency <0.0005). Results were largely the same when restricting the analyses to include only unprovoked cases; however, one novel gene, , became significant (=4.4×10 using all missense variants with minor allele frequency <0.0005). CONCLUSIONS: Here, we have demonstrated the importance of using multiple variant filtering strategies, as we detected additional genes when filtering variants based on their predicted deleteriousness, frequency, and presence on the most expressed isoforms. Our primary analyses did not identify new candidate loci; thus larger follow-up studies are needed to replicate the novel locus and to identify additional rare variation associated with venous thromboembolism.
Keywords: Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Precision Medicine; Venous Thromboembolism

Whole Genome Sequencing Based Analysis of Inflammation Biomarkers in the Trans-Omics for Precision Medicine (TOPMed) Consortium. - Jiang, Min-Zhi; Gaynor, Sheila M; Li, Xihao; Van Buren, Eric; Stilp, Adrienne; Buth, Erin; Wang, Fei Fei; Manansala, Regina; Gogarten, Stephanie M; Li, Zilin; Polfus, Linda M; Salimi, Shabnam; et al. (bioRxiv, 2023)
Inflammation biomarkers can provide valuable insight into the role of inflammatory processes in many diseases and conditions. Sequencing based analyses of such biomarkers can also serve as an exemplar of the genetic architecture of quantitative traits. To evaluate the biological insight, which can be provided by a multi-ancestry, whole-genome based association study, we performed a comprehensive analysis of 21 inflammation biomarkers from up to 38,465 individuals with whole-genome sequencing from the Trans-Omics for Precision Medicine (TOPMed) program. We identified 22 distinct single-variant associations across 6 traits - E-selectin, intercellular adhesion molecule 1, interleukin-6, lipoprotein-associated phospholipase A2 activity and mass, and P-selectin - that remained significant after conditioning on previously identified associations for these inflammatory biomarkers. We further expanded upon known biomarker associations by pairing the single-variant analysis with a rare variant set-based analysis that further identified 19 significant rare variant set-based associations with 5 traits. These signals were distinct from both significant single variant association signals within TOPMed and genetic signals observed in prior studies, demonstrating the complementary value of performing both single and rare variant analyses when analyzing quantitative traits. We also confirm several previously reported signals from semi-quantitative proteomics platforms. Many of these signals demonstrate the extensive allelic heterogeneity and ancestry-differentiated variant-trait associations common for inflammation biomarkers, a characteristic we hypothesize will be increasingly observed with well-powered, large-scale analyses of complex traits.

Whole-exome sequencing study identifies four novel gene loci associated with diabetic kidney disease. - Pan, Yang; Sun, Xiao; Mi, Xuenan; Huang, Zhijie; Hsu, Yenchih; Hixson, James E; Munzy, Donna; Ginger A Metcalf; Franceschini, Nora; Tin, Adrienne; Köttgen, Anna; Francis, Michael; et al. (Hum Mol Genet, 2023)
Diabetic kidney disease (DKD) is recognized as an important public health challenge. However, its genomic mechanisms are poorly understood. To identify rare variants for DKD, we conducted a whole-exome sequencing (WES) study leveraging large cohorts well-phenotyped for chronic kidney disease and diabetes. Our two-stage WES study included 4372 European and African ancestry participants from the Chronic Renal Insufficiency Cohort and Atherosclerosis Risk in Communities studies (stage 1) and 11 487 multi-ancestry Trans-Omics for Precision Medicine participants (stage 2). Generalized linear mixed models, which accounted for genetic relatedness and adjusted for age, sex and ancestry, were used to test associations between single variants and DKD. Gene-based aggregate rare variant analyses were conducted using an optimized sequence kernel association test implemented within our mixed model framework. We identified four novel exome-wide significant DKD-related loci through initiating diabetes. In single-variant analyses, participants carrying a rare, in-frame insertion in the DIS3L2 gene (rs141560952) exhibited a 193-fold increased odds [95% confidence interval (CI): 33.6, 1105] of DKD compared with noncarriers (P = 3.59 × 10-9). Likewise, each copy of a low-frequency KRT6B splice-site variant (rs425827) conferred a 5.31-fold higher odds (95% CI: 3.06, 9.21) of DKD (P = 2.72 × 10-9). Aggregate gene-based analyses further identified ERAP2 (P = 4.03 × 10-8) and NPEPPS (P = 1.51 × 10-7), which are both expressed in the kidney and implicated in renin-angiotensin-aldosterone system modulated immune response. In the largest WES study of DKD, we identified novel rare variant loci attaining exome-wide significance. These findings provide new insights into the molecular mechanisms underlying DKD.
Keywords: Aminopeptidases; Diabetes Mellitus; Diabetic Nephropathies; Exome Sequencing; Humans; Kidney; Renal Insufficiency, Chronic

Accounting for population structure in genetic studies of cystic fibrosis. - Kingston, Hanley; Stilp, Adrienne M; Gordon, William; Broome, Jai; Gogarten, Stephanie M; Ling, Hua; Barnard, John; Dugan-Perez, Shannon; Ellinor, Patrick T; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; et al. (HGG Adv, 2022)
F508del (c.1521_1523delCTT, p.Phe508delPhe) is the most common pathogenic allele underlying cystic fibrosis (CF), and its frequency varies in a geographic cline across Europe. We hypothesized that genetic variation associated with this cline is overrepresented in a large cohort (N > 5,000) of persons with CF who underwent whole-genome sequencing and that this pattern could result in spurious associations between variants correlated with both the F508del genotype and CF-related outcomes. Using principal-component (PC) analyses, we showed that variation in the region disproportionately contributes to a PC explaining a relatively high proportion of genetic variance. Variation near was correlated with population structure among persons with CF, and this correlation was driven by a subset of the sample inferred to have European ancestry. We performed genome-wide association studies comparing persons with CF with one versus two copies of the F508del allele; this allowed us to identify genetic variation associated with the F508del allele and to determine that standard PC-adjustment strategies eliminated the significant association signals. Our results suggest that PC adjustment can adequately prevent spurious associations between genetic variants and CF-related traits and are therefore effective tools to control for population structure even when population structure is confounded with disease severity and a common pathogenic variant.

Association of Pathogenic Variants in Hereditary Cancer Genes With Multiple Diseases. - Zeng, Chenjie; Bastarache, Lisa A; Tao, Ran; Eric Venner; Hebbring, Scott; Andujar, Justin D; Bland, Sarah T; Crosslin, David R; Pratap, Siddharth; Cooley, Ayorinde; Pacheco, Jennifer A; Christensen, Kurt D; et al. (JAMA Oncol, 2022)
IMPORTANCE: Knowledge about the spectrum of diseases associated with hereditary cancer syndromes may improve disease diagnosis and management for patients and help to identify high-risk individuals. OBJECTIVE: To identify phenotypes associated with hereditary cancer genes through a phenome-wide association study. DESIGN, SETTING, AND PARTICIPANTS: This phenome-wide association study used health data from participants in 3 cohorts. The Electronic Medical Records and Genomics Sequencing (eMERGEseq) data set recruited predominantly healthy individuals from 10 US medical centers from July 16, 2016, through February 18, 2018, with a mean follow-up through electronic health records (EHRs) of 12.7 (7.4) years. The UK Biobank (UKB) cohort recruited participants from March 15, 2006, through August 1, 2010, with a mean (SD) follow-up of 12.4 (1.0) years. The Hereditary Cancer Registry (HCR) recruited patients undergoing clinical genetic testing at Vanderbilt University Medical Center from May 1, 2012, through December 31, 2019, with a mean (SD) follow-up through EHRs of 8.8 (6.5) years. EXPOSURES: Germline variants in 23 hereditary cancer genes. Pathogenic and likely pathogenic variants for each gene were aggregated for association analyses. MAIN OUTCOMES AND MEASURES: Phenotypes in the eMERGEseq and HCR cohorts were derived from the linked EHRs. Phenotypes in UKB were from multiple sources of health-related data. RESULTS: A total of 214 020 participants were identified, including 23 544 in eMERGEseq cohort (mean [SD] age, 47.8 [23.7] years; 12 611 women [53.6%]), 187 234 in the UKB cohort (mean [SD] age, 56.7 [8.1] years; 104 055 [55.6%] women), and 3242 in the HCR cohort (mean [SD] age, 52.5 [15.5] years; 2851 [87.9%] women). All 38 established gene-cancer associations were replicated, and 19 new associations were identified. These included the following 7 associations with neoplasms: CHEK2 with leukemia (odds ratio [OR], 3.81 [95% CI, 2.64-5.48]) and plasma cell neoplasms (OR, 3.12 [95% CI, 1.84-5.28]), ATM with gastric cancer (OR, 4.27 [95% CI, 2.35-7.44]) and pancreatic cancer (OR, 4.44 [95% CI, 2.66-7.40]), MUTYH (biallelic) with kidney cancer (OR, 32.28 [95% CI, 6.40-162.73]), MSH6 with bladder cancer (OR, 5.63 [95% CI, 2.75-11.49]), and APC with benign liver/intrahepatic bile duct tumors (OR, 52.01 [95% CI, 14.29-189.29]). The remaining 12 associations with nonneoplastic diseases included BRCA1/2 with ovarian cysts (OR, 3.15 [95% CI, 2.22-4.46] and 3.12 [95% CI, 2.36-4.12], respectively), MEN1 with acute pancreatitis (OR, 33.45 [95% CI, 9.25-121.02]), APC with gastritis and duodenitis (OR, 4.66 [95% CI, 2.61-8.33]), and PTEN with chronic gastritis (OR, 15.68 [95% CI, 6.01-40.92]). CONCLUSIONS AND RELEVANCE: The findings of this genetic association study analyzing the EHRs of 3 large cohorts suggest that these new phenotypes associated with hereditary cancer genes may facilitate early detection and better management of cancers. This study highlights the potential benefits of using EHR data in genomic medicine.
Keywords: Acute Disease; Female; Gastritis; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Male; Neoplastic Syndromes, Hereditary; Pancreatitis

Author Correction: Comparative and demographic analysis of orang-utan genomes. - Locke, Devin P; Hillier, LaDeana W; Warren, Wesley C; Kim C Worley; Nazareth, Lynne V; Donna M Muzny; Yang, Shiaw-Pyng; Wang, Zhengyuan; Chinwalla, Asif T; Minx, Pat; Mitreva, Makedonka; Cook, Lisa; et al. (Nature, 2022)

Best practices for the interpretation and reporting of clinical whole genome sequencing. - Austin-Tse, Christina A; Jobanputra, Vaidehi; Perry, Denise L; Bick, David; Taft, Ryan J; Eric Venner; Richard A Gibbs; Young, Ted; Barnett, Sarah; Belmont, John W; Boczek, Nicole; Chowdhury, Shimul; et al. (NPJ Genom Med, 2022)
Whole genome sequencing (WGS) shows promise as a first-tier diagnostic test for patients with rare genetic disorders. However, standards addressing the definition and deployment practice of a best-in-class test are lacking. To address these gaps, the Medical Genome Initiative, a consortium of leading health care and research organizations in the US and Canada, was formed to expand access to high quality clinical WGS by convening experts and publishing best practices. Here, we present best practice recommendations for the interpretation and reporting of clinical diagnostic WGS, including discussion of challenges and emerging approaches that will be critical to harness the full potential of this comprehensive test.

Biallelic variants in SLC38A3 encoding a glutamine transporter cause epileptic encephalopathy. - Marafi, Dana; Fatih, Jawid M; Kaiyrzhanov, Rauan; Ferla, Matteo P; Gijavanekar, Charul; Al-Maraghi, Aljazi; Liu, Ning; Sites, Emily; Alsaif, Hessa S; Al-Owain, Mohammad; Zakkariah, Mohamed; El-Anany, Ehab; et al. (Brain, 2022)
The solute carrier (SLC) superfamily encompasses >400 transmembrane transporters involved in the exchange of amino acids, nutrients, ions, metals, neurotransmitters and metabolites across biological membranes. SLCs are highly expressed in the mammalian brain; defects in nearly 100 unique SLC-encoding genes (OMIM: https://www.omim.org) are associated with rare Mendelian disorders including developmental and epileptic encephalopathy and severe neurodevelopmental disorders. Exome sequencing and family-based rare variant analyses on a cohort with neurodevelopmental disorders identified two siblings with developmental and epileptic encephalopathy and a shared deleterious homozygous splicing variant in SLC38A3. The gene encodes SNAT3, a sodium-coupled neutral amino acid transporter and a principal transporter of the amino acids asparagine, histidine, and glutamine, the latter being the precursor for the neurotransmitters GABA and glutamate. Additional subjects with a similar developmental and epileptic encephalopathy phenotype and biallelic predicted-damaging SLC38A3 variants were ascertained through GeneMatcher and collaborations with research and clinical molecular diagnostic laboratories. Untargeted metabolomic analysis was performed to identify novel metabolic biomarkers. Ten individuals from seven unrelated families from six different countries with deleterious biallelic variants in SLC38A3 were identified. Global developmental delay, intellectual disability, hypotonia, and absent speech were common features while microcephaly, epilepsy, and visual impairment were present in the majority. Epilepsy was drug-resistant in half. Metabolomic analysis revealed perturbations of glutamate, histidine, and nitrogen metabolism in plasma, urine, and CSF of selected subjects, potentially representing biomarkers of disease. Our data support the contention that SLC38A3 is a novel disease gene for developmental and epileptic encephalopathy and illuminate the likely pathophysiology of the disease as perturbations in glutamine homeostasis.
Keywords: Epilepsy, Generalized; Glutamine; Histidine; Humans; Metabolome; Nitrogen; Sodium-Calcium Exchanger

Biallelic Variants in the Ectonucleotidase ENTPD1 Cause a Complex Neurodevelopmental Disorder with Intellectual Disability, Distinct White Matter Abnormalities, and Spastic Paraplegia. - Calame, Daniel G; Herman, Isabella; Maroofian, Reza; Marshall, Aren E; Donis, Karina Carvalho; Fatih, Jawid M; Mitani, Tadahiro; Du, Haowei; Grochowski, Christopher M; Sousa, Sergio B; Gijavanekar, Charul; Bakhtiari, Somayeh; et al. (Ann Neurol, 2022)
OBJECTIVE: Human genomics established that pathogenic variation in diverse genes can underlie a single disorder. For example, hereditary spastic paraplegia is associated with >80 genes, with frequently only few affected individuals described for each gene. Herein, we characterize a large cohort of individuals with biallelic variation in ENTPD1, a gene previously linked to spastic paraplegia 64 (Mendelian Inheritance in Man # 615683). METHODS: Individuals with biallelic ENTPD1 variants were recruited worldwide. Deep phenotyping and molecular characterization were performed. RESULTS: A total of 27 individuals from 17 unrelated families were studied; additional phenotypic information was collected from published cases. Twelve novel pathogenic ENTPD1 variants are described (NM 001776.6): c.398_399delinsAA; p.(Gly133Glu), c.540del; p.(Thr181Leufs*18), c.640del; p.(Gly216Glufs*75), c.185 T > G; p.(Leu62*), c.1531 T > C; p.(*511Glnext*100), c.967C > T; p.(Gln323*), c.414-2_414-1del, and c.146 A > G; p.(Tyr49Cys) including 4 recurrent variants c.1109 T > A; p.(Leu370*), c.574-6_574-3del, c.770_771del; p.(Gly257Glufs*18), and c.1041del; p.(Ile348Phefs*19). Shared disease traits include childhood onset, progressive spastic paraplegia, intellectual disability (ID), dysarthria, and white matter abnormalities. In vitro assays demonstrate that ENTPD1 expression and function are impaired and that c.574-6_574-3del causes exon skipping. Global metabolomics demonstrate ENTPD1 deficiency leads to impaired nucleotide, lipid, and energy metabolism. INTERPRETATION: The ENTPD1 locus trait consists of childhood disease onset, ID, progressive spastic paraparesis, dysarthria, dysmorphisms, and white matter abnormalities, with some individuals showing neurocognitive regression. Investigation of an allelic series of ENTPD1 (1) expands previously described features of ENTPD1-related neurological disease, (2) highlights the importance of genotype-driven deep phenotyping, (3) documents the need for global collaborative efforts to characterize rare autosomal recessive disease traits, and (4) provides insights into disease trait neurobiology. ANN NEUROL 2022;92:304-321.
Keywords: Apyrase; Dysarthria; Humans; Intellectual Disability; Mutation; Paraplegia; Pedigree; Phenotype; Spastic Paraplegia, Hereditary; White Matter

C. Thomas Caskey, M.D. (1938-2022): A remembrance. - Beaudet, Arthur L; Richard A Gibbs (Am J Hum Genet, 2022)

Centers for Mendelian Genomics: A decade of facilitating gene discovery. - Baxter, Samantha M; Posey, Jennifer E; Lake, Nicole J; Sobreira, Nara; Chong, Jessica X; Buyske, Steven; Blue, Elizabeth E; Chadwick, Lisa H; Coban-Akdemir, Zeynep H; Doheny, Kimberly F; Davis, Colleen P; Lek, Monkol; et al. (Genet Med, 2022)
PURPOSE: Mendelian disease genomic research has undergone a massive transformation over the past decade. With increasing availability of exome and genome sequencing, the role of Mendelian research has expanded beyond data collection, sequencing, and analysis to worldwide data sharing and collaboration. METHODS: Over the past 10 years, the National Institutes of Health-supported Centers for Mendelian Genomics (CMGs) have played a major role in this research and clinical evolution. RESULTS: We highlight the cumulative gene discoveries facilitated by the program, biomedical research leveraged by the approach, and the larger impact on the research community. Beyond generating a list of gene-phenotype relationships and participating in widespread data sharing, the CMGs have created resources, tools, and training for the larger community to foster understanding of genes and genome variation. The CMGs have participated in a wide range of data sharing activities, including deposition of all eligible CMG data into the Analysis, Visualization, and Informatics Lab-space (AnVIL), sharing candidate genes through the Matchmaker Exchange and the CMG website, and sharing variants in Genotypes to Mendelian Phenotypes (Geno2MP) and VariantMatcher. CONCLUSION: The work is far from complete; strengthening communication between research and clinical realms, continued development and sharing of knowledge and tools, and improving access to richly characterized data sets are all required to diagnose the remaining molecularly undiagnosed patients.
Keywords: Exome; Exome Sequencing; Genetic Association Studies; Genomics; Humans; Phenotype

Clinical and molecular features of pediatric cancer patients with Lynch syndrome. - Scollon, Sarah; Eldomery, Mohammad K; Reuther, Jacquelyn; Lin, Frank Y; Potter, Samara L; Desrosiers, Lauren; McClain, Kenneth L; Smith, Valeria; Su, Jack Meng-Fen; Venkatramani, Rajkumar; Jianhong Hu; Korchina, Viktoriya; et al. (Pediatr Blood Cancer, 2022)
BACKGROUND: The association of childhood cancer with Lynch syndrome is not established compared with the significant pediatric cancer risk in recessive constitutional mismatch repair deficiency syndrome (CMMRD). PROCEDURE: We describe the clinical features, germline analysis, and tumor genomic profiling of patients with Lynch syndrome among patients enrolled in pediatric cancer genomic studies. RESULTS: There were six of 773 (0.8%) pediatric patients with solid tumors identified with Lynch syndrome, defined as a germline heterozygous pathogenic variant in one of the mismatch repair (MMR) genes (three with MSH6, two with MLH1, and one with MSH2). Tumor analysis demonstrated evidence for somatic second hits and/or increased tumor mutation burden in three of four patients with available tumor with potential implications for therapy and identification of at-risk family members. Only one patient met current guidelines for pediatric cancer genetics evaluation at the time of tumor diagnosis. CONCLUSION: Approximately 1% of children with cancer have Lynch syndrome, which is missed with current referral guidelines, suggesting the importance of adding MMR genes to tumor and hereditary pediatric cancer panels. Tumor analysis may provide the first suggestion of an underlying cancer predisposition syndrome and is useful in distinguishing between Lynch syndrome and CMMRD.
Keywords: Brain Neoplasms; Child; Colorectal Neoplasms; Colorectal Neoplasms, Hereditary Nonpolyposis; DNA Mismatch Repair; DNA-Binding Proteins; Germ-Line Mutation; Humans; MutL Protein Homolog 1; MutS Homolog 2 Protein; Neoplastic Syndromes, Hereditary

Clonal hematopoiesis of indeterminate potential, DNA methylation, and risk for coronary artery disease. - Uddin, M D Mesbah; Nguyen, Ngoc Quynh H; Yu, Bing; Brody, Jennifer A; Pampana, Akhil; Nakao, Tetsushi; Fornage, Myriam; Bressler, Jan; Sotoodehnia, Nona; Weinstock, Joshua S; Honigberg, Michael C; Nachun, Daniel; et al. (Nat Commun, 2022)
Age-related changes to the genome-wide DNA methylation (DNAm) pattern observed in blood are well-documented. Clonal hematopoiesis of indeterminate potential (CHIP), characterized by the age-related acquisition and expansion of leukemogenic mutations in hematopoietic stem cells (HSCs), is associated with blood cancer and coronary artery disease (CAD). Epigenetic regulators DNMT3A and TET2 are the two most frequently mutated CHIP genes. Here, we present results from an epigenome-wide association study for CHIP in 582 Cardiovascular Health Study (CHS) participants, with replication in 2655 Atherosclerosis Risk in Communities (ARIC) Study participants. We show that DNMT3A and TET2 CHIP have distinct and directionally opposing genome-wide DNAm association patterns consistent with their regulatory roles, albeit both promoting self-renewal of HSCs. Mendelian randomization analyses indicate that a subset of DNAm alterations associated with these two leading CHIP genes may promote the risk for CAD.
Keywords: Clonal Hematopoiesis; Coronary Artery Disease; DNA Methylation; Hematopoiesis; Hematopoietic Stem Cells; Humans

Developmental genomics of limb malformations: Allelic series in association with gene dosage effects contribute to the clinical variability. - Duan, Ruizhi; Hijazi, Hadia; Gulec, Elif Yilmaz; Eker, Hatice Koçak; Costa, Silvia R; Sahin, Yavuz; Ocak, Zeynep; Isikay, Sedat; Ozalp, Ozge; Bozdogan, Sevcan; Aslan, Huseyin; Elcioglu, Nursel; et al. (HGG Adv, 2022)
Genetic heterogeneity, reduced penetrance, and variable expressivity, the latter including asymmetric body axis plane presentations, have all been described in families with congenital limb malformations (CLMs). Interfamilial and intrafamilial heterogeneity highlight the complexity of the underlying genetic pathogenesis of these developmental anomalies. Family-based genomics by exome sequencing (ES) and rare variant analyses combined with whole-genome array-based comparative genomic hybridization were implemented to investigate 18 families with limb birth defects. Eleven of 18 (61%) families revealed explanatory variants, including 7 single-nucleotide variant alleles and 3 copy number variants (CNVs), at previously reported "disease trait associated loci": , cluster, , , and . Breakpoint junction analyses for all three CNV alleles revealed mutational signatures consistent with microhomology-mediated break-induced replication, a mechanism facilitated by -mediated rearrangement. Homozygous duplication of was observed in one Turkish kindred and represents a novel contributory genetic mechanism to Gollop-Wolfgang Complex (MIM: 228250), where triplication of the locus has been reported in one family from Japan (i.e., 4n = 2n + 2n versus 4n = 3n + 1n allelic configurations). Genes acting on limb patterning are sensitive to a gene dosage effect and are often associated with an allelic series. We extend an allele-specific gene dosage model to potentially assist, in an adjuvant way, interpretations of interconnections among an allelic series, clinical severity, and reduced penetrance of the -related CLM spectrum.

Distinct somatic DICER1 hotspot mutations in three metachronous ovarian Sertoli-Leydig cell tumors in a patient with DICER1 syndrome. - Garcia, Annie; Desrosiers, Lauren; Scollon, Sarah; Gruner, Stephanie; Reuther, Jacquelyn; Gandhi, Ilavarasi; Patil, Ninad; Fuller, Maren Y; Dai, Hongzheng; Donna M Muzny; Richard A Gibbs; Bercaw-Pratt, Jennifer L; et al. (Cancer Genet, 2022)
Keywords: DEAD-box RNA Helicases; Female; Humans; Mutation; Ovarian Neoplasms; Ribonuclease III; Sertoli-Leydig Cell Tumor

The Earth BioGenome Project 2020: Starting the clock. - Lewin, Harris A; Stephen Richards; Lieberman Aiden, Erez; Allende, Miguel L; Archibald, John M; Bálint, Miklós; Barker, Katharine B; Baumgartner, Bridget; Belov, Katherine; Bertorelle, Giorgio; Blaxter, Mark L; Cai, Jing; et al. (Proc Natl Acad Sci U S A, 2022)
Keywords: Animals; Base Sequence; Biodiversity; Eukaryota; Genomics; Humans

An ELF4 hypomorphic variant results in NK cell deficiency. - Salinas, Sandra Andrea; Mace, Emily M; Conte, Matilde I; Park, Chun Shik; Li, Yu; Rosario-Sepulveda, Joshua I; Mahapatra, Sanjana; Moore, Emily K; Hernandez, Evelyn R; Chinn, Ivan K; Reed, Abigail E; Lee, Barclay J; et al. (JCI Insight, 2022)
NK cell deficiencies (NKD) are a type of primary immune deficiency in which the major immunologic abnormality affects NK cell number, maturity, or function. Since NK cells contribute to immune defense against virally infected cells, patients with NKD experience higher susceptibility to chronic, recurrent, and fatal viral infections. An individual with recurrent viral infections and mild hypogammaglobulinemia was identified to have an X-linked damaging variant in the transcription factor gene ELF4. The variant does not decrease expression but disrupts ELF4 protein interactions and DNA binding, reducing transcriptional activation of target genes and selectively impairing ELF4 function. Corroborating previous murine models of ELF4 deficiency (Elf4-/-) and using a knockdown human NK cell line, we determined that ELF4 is necessary for normal NK cell development, terminal maturation, and function. Through characterization of the NK cells of the proband, expression of the proband's variant in Elf4-/- mouse hematopoietic precursor cells, and a human in vitro NK cell maturation model, we established this ELF4 variant as a potentially novel cause of NKD.
Keywords: Animals; DNA-Binding Proteins; Humans; Killer Cells, Natural; Mice; Transcription Factors

Expanding the phenotypic and allelic spectrum of SMG8: Clinical observations reveal overlap with SMG9-associated disease trait. - Abdel-Salam, Ghada M H; Duan, Ruizhi; Abdel-Hamid, Mohamed S; Sayed, Inas S M; Jhangiani, Shalini N; Ziad Khan; Du, Haowei; Richard A Gibbs; Posey, Jennifer E; Marafi, Dana; James R Lupski (Am J Med Genet A, 2022)
SMG8 (MIM *617315) is a regulatory subunit involved in nonsense-mediated mRNA decay (NMD), a cellular protective pathway that regulates mRNA transcription, transcript stability, and degrades transcripts containing premature stop codons. SMG8 binds SMG9 and SMG1 to form the SMG1C complex and inhibit the kinase activity of SMG1. Biallelic deleterious variants in SMG9 are known to cause a heart and brain malformation syndrome (HBMS; MIM #616920), whereas biallelic deleterious variants in SMG8 were recently described to cause a novel neurodevelopmental disorder (NDD) with dysmorphic facies and cataracts, now defined as Alzahrani-Kuwahara syndrome (ALKUS: MIM #619268). Only eight subjects from four families with ALKUS have been described to date. Through research reanalysis of a nondiagnostic clinical exome, we identified a subject from a fifth unrelated family with a homozygous deleterious variant in SMG8 and features consistent with ALKUS. Interestingly, the subject also had unilateral microphthalmia, a clinical feature that has been described in SMG9-related disorder. Our study expands the phenotypic spectrum of SMG8-related disorder, demonstrates an overlapping phenotype between SMG8- and SMG9-related rare disease traits, provides further evidence for the SMG8 and SMG9 protein interactions, and highlights the importance of revisiting nondiagnostic exome data to identify and affirm emerging novel genes for rare disease traits.
Keywords: Alleles; Homozygote; Humans; Intracellular Signaling Peptides and Proteins; Nonsense Mediated mRNA Decay; Phenotype; Phosphorylation

Fully resolved assembly of Cryptosporidium parvum. - Vipin Menon; Okhuysen, Pablo C; Chappell, Cynthia L; Mahmoud, Medhat; Mahmoud, Medhat; Meng, Qingchang; Harshavardhan Doddapaneni; Vee, Vanesa; Yi Han; Salvi, Sejal; Bhamidipati, Sravya; Kottapalli, Kavya; et al. (Gigascience, 2022)
BACKGROUND: Cryptosporidium parvum is an apicomplexan parasite commonly found across many host species with a global infection prevalence in human populations of 7.6%. Understanding its diversity and genomic makeup can help in fighting established infections and prohibiting further transmission. The basis of every genomic study is a high-quality reference genome that has continuity and completeness, thus enabling comprehensive comparative studies. FINDINGS: Here, we provide a highly accurate and complete reference genome of Cryptosporidium parvum. The assembly is based on Oxford Nanopore reads and was improved using Illumina reads for error correction. We also outline how to evaluate and choose from different assembly methods based on 2 main approaches that can be applied to other Cryptosporidium species. The assembly encompasses 8 chromosomes and includes 13 telomeres that were resolved. Overall, the assembly shows a high completion rate with 98.4% single-copy BUSCO genes. CONCLUSIONS: This high-quality reference genome of a zoonotic IIaA17G2R1 C. parvum subtype isolate provides the basis for subsequent comparative genomic studies across the Cryptosporidium clade. This will enable improved understanding of diversity, functional, and association studies.
Keywords: Cryptosporidiosis; Cryptosporidium; Cryptosporidium parvum; Genome; Genomics; Humans

Functional characteristics of a broad spectrum of TBX6 variants in Mayer-Rokitansky-Küster-Hauser syndrome. - Ma, Congcong; Chen, Na; Jolly, Angad; Zhao, Sen; Coban-Akdemir, Zeynep; Tian, Weijie; Kang, Jia; Ye, Yang; Wang, Yuan; Koch, André; Zhang, Yuanqiang; Qin, Chenglu; et al. (Genet Med, 2022)
PURPOSE: Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) is characterized by congenital absence of the uterus, cervix, and the upper part of the vagina in females. Whole-gene deletion and loss-of-function variants in TBX6 have been identified in association with MRKHS. We aimed to expand the spectrum of TBX6 variants in MRKHS and explore the biological effect of the variant alleles. METHODS: Rare variants in TBX6 were called from a combined multiethnic cohort of 622 probands with MRKHS who underwent exome sequencing or genome sequencing. Multiple in vitro functional experiments were performed, including messenger RNA analysis, western blotting, transcriptional activity assay, and immunofluorescence staining. RESULTS: We identified 16 rare variants in TBX6 from the combined cohort, including 1 protein-truncating variant reported in our previous study and 15 variants with unknown effects. By comparing the prevalence of TBX6 variants in the Chinese MRKHS cohort vs 1038 female controls, we observed a significant mutational burden of TBX6 in affected individuals (P = .0004, odds ratio = 5.25), suggesting a causal role of TBX6 variants in MRKHS. Of the 15 variants with uncertain effects, 7 were shown to induce a loss-of-function effect through various mechanisms. The c.423G>A (p.Leu141=) and c.839+5G>A variants impaired the normal splicing of TBX6 messenger RNA, c.422T>C (p.Leu141Pro) and c.745G>A (p.Val249Met) led to decreased protein expression, c.10C>T (p.Pro4Ser) and c.400G>A (p.Glu134Lys) resulted in perturbed transcriptional activity, and c.356G>A (p.Arg119His) caused protein mislocalization. We observed incomplete penetrance and variable expressivity in families carrying deleterious variants, which indicates a more complex genetic mechanism than classical Mendelian inheritance. CONCLUSION: Our study expands the mutational spectrum of TBX6 in MRKHS and delineates the molecular pathogenesis of TBX6 variants, supporting the association between deleterious variants in TBX6 and MRKHS.
Keywords: 46, XX Disorders of Sex Development; Congenital Abnormalities; Female; Humans; Mullerian Ducts; RNA, Messenger; T-Box Domain Proteins; Vagina

Genetic errors of immunity distinguish pediatric nonmalignant lymphoproliferative disorders. - Forbes, Lisa R; Eckstein, Olive S; Gulati, Nitya; Peckham-Gregory, Erin C; Ozuah, Nmazuo W; Lubega, Joseph; El-Mallawany, Nader K; Agrusa, Jennifer E; Poli, M Cecilia; Vogel, Tiphanie P; Chaimowitz, Natalia S; Rider, Nicholas L; et al. (J Allergy Clin Immunol, 2022)
BACKGROUND: Pediatric nonmalignant lymphoproliferative disorders (PLPDs) are clinically and genetically heterogeneous. Long-standing immune dysregulation and lymphoproliferation in children may be life-threatening, and a paucity of data exists to guide evaluation and treatment of children with PLPD. OBJECTIVE: The primary objective of this study was to ascertain the spectrum of genomic immunologic defects in PLPD. Secondary objectives included characterization of clinical outcomes and associations between genetic diagnoses and those outcomes. METHODS: PLPD was defined by persistent lymphadenopathy, lymph organ involvement, or lymphocytic infiltration for more than 3 months, with or without chronic or significant Epstein-Barr virus (EBV) infection. Fifty-one subjects from 47 different families with PLPD were analyzed using whole exome sequencing. RESULTS: Whole exome sequencing identified likely genetic errors of immunity in 51% to 62% of families (53% to 65% of affected children). Presence of a genetic etiology was associated with younger age and hemophagocytic lymphohistiocytosis. Ten-year survival for the cohort was 72.4%, and patients with viable genetic diagnoses had a higher survival rate (82%) compared to children without a genetic explanation (48%, P = .03). Survival outcomes for individuals with EBV-associated disease and no genetic explanation were particularly worse than outcomes for subjects with EBV-associated disease and a genetic explanation (17% vs 90%; P = .002). Ascertainment of a molecular diagnosis provided targetable treatment options for up to 18 individuals and led to active management changes for 12 patients. CONCLUSIONS: PLPD defines children at high risk for mortality, and whole exome sequencing informs clinical risks and therapeutic opportunities for this diagnosis.
Keywords: Adolescent; Autoimmunity; Child; Child, Preschool; Exome Sequencing; Female; Genetic Association Studies; Genetic Testing; Herpesvirus 4, Human; Humans; Immunity; Infant; Lymphoproliferative Disorders; Male; Young Adult

Genome Sequencing in the Parkinson Disease Clinic. - Hill, Emily J; Robak, Laurie A; Al-Ouran, Rami; Deger, Jennifer; Fong, Jamie C; Vandeventer, Paul Jerrod; Schulman, Emily; Rao, Sindhu; Saade, Hiba; Savitt, Joseph M; von Coelln, Rainer; Desai, Neeja; et al. (Neurol Genet, 2022)
BACKGROUND AND OBJECTIVES: Genetic variants affect both Parkinson disease (PD) risk and manifestations. Although genetic information is of potential interest to patients and clinicians, genetic testing is rarely performed during routine PD clinical care. The goal of this study was to examine interest in comprehensive genetic testing among patients with PD and document reactions to possible findings from genome sequencing in 2 academic movement disorder clinics. METHODS: In 203 subjects with PD (age = 63 years, 67% male), genome sequencing was performed and filtered using a custom panel, including 49 genes associated with PD, parkinsonism, or related disorders, as well as a 90-variant PD genetic risk score. Based on the results, 231 patients (age = 67 years, 63% male) were surveyed on interest in genetic testing and responses to vignettes covering (1) familial risk of PD (); (2) risk of PD dementia (); (3) PD genetic risk score; and (4) secondary, medically actionable variants (). RESULTS: Genome sequencing revealed a variant in 3% and a risk variant in 10% of our clinical sample. The genetic risk score was normally distributed, identifying 41 subjects with a high risk of PD. Medically actionable findings were discovered in 2 subjects (1%). In our survey, the majority (82%) responded that they would share a variant with relatives. Most registered unchanged or increased interest in testing when confronted with a potential risk for dementia or medically actionable findings, and most (75%) expressed interest in learning their PD genetic risk score. DISCUSSION: Our results highlight broad interest in comprehensive genetic testing among patients with PD and may facilitate integration of genome sequencing in clinical practice.

Harmonizing variant classification for return of results in the All of Us Research Program. - Harrison, Steven M; Austin-Tse, Christina A; Kim, Serra; Lebo, Matthew; Leon, Annette; David R Murdock; Radhakrishnan, Aparna; Shirts, Brian H; Steeves, Marcie; Eric Venner; Richard A Gibbs; Jarvik, Gail P; et al. (Hum Mutat, 2022)
The All of Us Research Program (AoURP) is a historic effort to accelerate research and improve healthcare by generating and collating data from one million people in the United States. Participants will have the option to receive results from their genome analysis, including actionable findings in 59 gene-disorder pairs for which disorder-associated variants are recommended for return by the American College of Medical Genetics and Genomics. To ensure consistent reporting across the AoURP, in a prelaunch study the four participating clinical laboratories shared all variant classifications in the 59 genes of interest from their internal databases. Of the 11,813 unique variants classified by at least two of the four laboratories, classifications were concordant with regard to reportability for 99.1% (11,711), with only 0.9% (102) having reportability differences. Through variant reassessment, data sharing, and discussion of rationale, participating laboratories resolved all 102 reportable differences. These approaches will be maintained during routine AoU reporting to ensure continuous classification harmonization and consistent reporting within AoURP.
Keywords: Genetic Testing; Genetic Variation; Genome, Human; Genomics; Humans; Population Health; United States

Implementation of preemptive DNA sequence-based pharmacogenomics testing across a large academic medical center: The Mayo-Baylor RIGHT 10K Study. - Wang, Liewei; Steven E Scherer; Bielinski, Suzette J; Donna M Muzny; Jones, Leila A; Black, John Logan; Moyer, Ann M; Giri, Jyothsna; Sharp, Richard R; Matey, Eric T; Wright, Jessica A; Oyen, Lance J; et al. (Genet Med, 2022)
PURPOSE: The Mayo-Baylor RIGHT 10K Study enabled preemptive, sequence-based pharmacogenomics (PGx)-driven drug prescribing practices in routine clinical care within a large cohort. We also generated the tools and resources necessary for clinical PGx implementation and identified challenges that need to be overcome. Furthermore, we measured the frequency of both common genetic variation for which clinical guidelines already exist and rare variation that could be detected by DNA sequencing, rather than genotyping. METHODS: Targeted oligonucleotide-capture sequencing of 77 pharmacogenes was performed using DNA from 10,077 consented Mayo Clinic Biobank volunteers. The resulting predicted drug response-related phenotypes for 13 genes, including CYP2D6 and HLA, affecting 21 drug-gene pairs, were deposited preemptively in the Mayo electronic health record. RESULTS: For the 13 pharmacogenes of interest, the genomes of 79% of participants carried clinically actionable variants in 3 or more genes, and DNA sequencing identified an average of 3.3 additional conservatively predicted deleterious variants that would not have been evident using genotyping. CONCLUSION: Implementation of preemptive rather than reactive and sequence-based rather than genotype-based PGx prescribing revealed nearly universal patient applicability and required integrated institution-wide resources to fully realize individualized drug therapy and to show more efficient use of health care resources.
Keywords: Academic Medical Centers; Base Sequence; Cytochrome P-450 CYP2D6; Genotype; Humans; Pharmacogenetics

Long read sequencing and expression studies of AHDC1 deletions in Xia-Gibbs syndrome reveal a novel genetic regulatory mechanism. - Chander, Varuna; Mahmoud, Medhat; Jianhong Hu; Dardas, Zain; Grochowski, Christopher M; Dawood, Moez; Khayat, Michael M; Li, He; Li, Shoudong; Jhangiani, Shalini; Korchina, Viktoriya; Shen, Hua; et al. (Hum Mutat, 2022)
Xia-Gibbs syndrome (XGS; MIM# 615829) is a rare mendelian disorder characterized by Development Delay (DD), intellectual disability (ID), and hypotonia. Individuals with XGS typically harbor de novo protein-truncating mutations in the AT-Hook DNA binding motif containing 1 (AHDC1) gene, although some missense mutations can also cause XGS. Large de novo heterozygous deletions that encompass the AHDC1 gene have also been ascribed as diagnostic for the disorder, without substantial evidence to support their pathogenicity. We analyzed 19 individuals with large contiguous deletions involving AHDC1, along with other genes. One individual bore the smallest known contiguous AHDC1 deletion (∼350 Kb), encompassing eight other genes within chr1p36.11 (Feline Gardner-Rasheed, IFI6, FAM76A, STX12, PPP1R8, THEMIS2, RPA2, SMPDL3B) and terminating within the first intron of AHDC1. The breakpoint junctions and phase of the deletion were identified using both short and long read sequencing (Oxford Nanopore). Quantification of RNA expression patterns in whole blood revealed that AHDC1 exhibited a mono-allelic expression pattern with no deficiency in overall AHDC1 expression levels, in contrast to the other deleted genes, which exhibited a 50% reduction in mRNA expression. These results suggest that AHDC1 expression in this individual is compensated by a novel regulatory mechanism and advances understanding of mutational and regulatory mechanisms in neurodevelopmental disorders.
Keywords: Abnormalities, Multiple; DNA-Binding Proteins; Endoribonucleases; Humans; Intellectual Disability; Musculoskeletal Abnormalities; Neurodevelopmental Disorders; Phosphoprotein Phosphatases; Qa-SNARE Proteins; RNA-Binding Proteins; Sphingomyelin Phosphodiesterase

The multiple de novo copy number variant (MdnCNV) phenomenon presents with peri-zygotic DNA mutational signatures and multilocus pathogenic variation. - Du, Haowei; Jolly, Angad; Grochowski, Christopher M; Bo Yuan; Dawood, Moez; Jhangiani, Shalini N; Li, He; Donna M Muzny; Fatih, Jawid M; Coban-Akdemir, Zeynep; Carlin, Mary Esther; Scheuerle, Angela E; et al. (Genome Med, 2022)
BACKGROUND: The multiple de novo copy number variant (MdnCNV) phenotype is described by having four or more constitutional de novo CNVs (dnCNVs) arising independently throughout the human genome within one generation. It is a rare peri-zygotic mutational event, previously reported to be seen once in every 12,000 individuals referred for genome-wide chromosomal microarray analysis due to congenital abnormalities. These rare families provide a unique opportunity to understand the genetic factors of peri-zygotic genome instability and the impact of dnCNV on human diseases. METHODS: Chromosomal microarray analysis (CMA), array-based comparative genomic hybridization, short- and long-read genome sequencing (GS) were performed on the newly identified MdnCNV family to identify de novo mutations including dnCNVs, de novo single-nucleotide variants (dnSNVs), and indels. Short-read GS was performed on four previously published MdnCNV families for dnSNV analysis. Trio-based rare variant analysis was performed on the newly identified individual and four previously published MdnCNV families to identify potential genetic etiologies contributing to the peri-zygotic genomic instability. Lin semantic similarity scores informed quantitative human phenotype ontology analysis on three MdnCNV families to identify gene(s) driving or contributing to the clinical phenotype. RESULTS: In the newly identified MdnCNV case, we revealed eight de novo tandem duplications, each ~ 1 Mb, with microhomology at 6/8 breakpoint junctions. Enrichment of de novo single-nucleotide variants (SNV; 6/79) and de novo indels (1/12) was found within 4 Mb of the dnCNV genomic regions. An elevated post-zygotic SNV mutation rate was observed in MdnCNV families. Maternal rare variant analyses identified three genes in distinct families that may contribute to the MdnCNV phenomenon. Phenotype analysis suggests that gene(s) within dnCNV regions contribute to the observed proband phenotype in 3/3 cases. CNVs in two cases, a contiguous gene duplication encompassing PMP22 and RAI1 and another duplication affecting NSD1 and SMARCC2, contribute to the clinically observed phenotypic manifestations. CONCLUSIONS: Characteristic features of dnCNVs reported here are consistent with a microhomology-mediated break-induced replication (MMBIR)-driven mechanism during the peri-zygotic period. Maternal genetic variants in DNA repair genes potentially contribute to peri-zygotic genomic instability. Variable phenotypic features were observed across a cohort of three MdnCNV probands, and computational quantitative phenotyping revealed that two out of three had evidence for the contribution of more than one genetic locus to the proband's phenotype supporting the hypothesis of de novo multilocus pathogenic variation (MPV) in those families.
Keywords: Comparative Genomic Hybridization; DNA; DNA Copy Number Variations; DNA-Binding Proteins; Genomic Instability; Humans; Mutation; Nucleotides; Transcription Factors

Novel pathogenic variants and quantitative phenotypic analyses of Robinow syndrome: WNT signaling perturbation and phenotypic variability. - Zhang, Chaofan; Jolly, Angad; Shayota, Brian J; Mazzeu, Juliana F; Du, Haowei; Dawood, Moez; Soper, Patricia Celestino; Ramalho de Lima, Ariadne; Ferreira, Barbara Merfort; Coban-Akdemir, Zeynep; White, Janson; Shears, Deborah; et al. (HGG Adv, 2022)
Robinow syndrome (RS) is a genetically heterogeneous disorder with six genes that converge on the WNT/planar cell polarity (PCP) signaling pathway implicated (, , , , , and ). RS is characterized by skeletal dysplasia and distinctive facial and physical characteristics. To further explore the genetic heterogeneity, paralog contribution, and phenotypic variability of RS, we investigated a cohort of 22 individuals clinically diagnosed with RS from 18 unrelated families. Pathogenic or likely pathogenic variants in genes associated with RS or RS phenocopies were identified in all 22 individuals, including the first variant to be reported in . We retrospectively collected medical records of 16 individuals from this cohort and extracted clinical descriptions from 52 previously published cases. We performed Human Phenotype Ontology (HPO) based quantitative phenotypic analyses to dissect allele-specific phenotypic differences. Individuals with variants clustered into two groups with demonstrable phenotypic differences between those with missense and truncating alleles. Probands with biallelic variants clustered together with the majority of probands carrying , , and variants, demonstrating no phenotypic distinction between the -autosomal recessive and dominant forms of RS. While phenotypically similar diseases on the RS differential matched through HPO analysis, clustering using phenotype similarity score placed RS-associated phenotypes in a unique cluster containing , , and apart from non-RS-associated paralogs. Through human phenotype analyses of this RS cohort and OMIM clinical synopses of Mendelian disease, this study begins to tease apart specific biologic roles for non-canonical WNT-pathway proteins.

Novel RETREG1 (FAM134B) founder allele is linked to HSAN2B and renal disease in a Turkish family. - Taşdelen, Elifcan; Calame, Daniel G; Akay, Gulsen; Mitani, Tadahiro; Fatih, Jawid M; Herman, Isabella; Du, Haowei; Coban-Akdemir, Zeynep; Marafi, Dana; Jhangiani, Shalini N; Posey, Jennifer E; Richard A Gibbs; et al. (Am J Med Genet A, 2022)
Hereditary sensory and autonomic neuropathy type 2B (HSAN2B) is a rare autosomal recessive peripheral neuropathy caused by biallelic variants in RETREG1 (formerly FAM134B). HSAN2B is characterized by sensory impairment resulting in skin ulcerations, amputations, and osteomyelitis as well as variable weakness, spasticity, and autonomic dysfunction. Here, we report four affected individuals with recurrent osteomyelitis, ulceration, and amputation of hands and feet, sensory neuropathy, hyperhidrosis, urinary incontinence, and renal failure from a family without any known shared parental ancestry. Due to the history of chronic recurrent multifocal osteomyelitis and microcytic anemia, a diagnosis of Majeed syndrome was considered; however, sequencing of LPIN2 was negative. Family-based exome sequencing (ES) revealed a novel homozygous ultrarare RETREG1 variant NM_001034850.2:c.321G>A;p.Trp107Ter. Electrophysiological studies of the proband demonstrated axonal sensorimotor neuropathy predominantly in the lower extremities. Consistent with the lack of shared ancestry, the coefficient of inbreeding calculated from ES data was low (F = 0.002), but absence of heterozygosity (AOH) analysis demonstrated a 7.2 Mb AOH block surrounding the variant consistent with a founder allele. Two of the four affected individuals had unexplained renal failure which has not been reported in HSAN2B cases to date. Therefore, this report describes a novel RETREG1 founder allele and suggests renal failure may be an unrecognized feature of the RETREG1-disease spectrum.
Keywords: Alleles; Hereditary Sensory and Autonomic Neuropathies; Humans; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Osteomyelitis; Pedigree; Renal Insufficiency

Patient and Clinician Perceptions of Precision Cardiology Care: Findings From the HeartCare Study. - Smith, Hadley Stevens; Sanchez, Clarissa E; Maag, Ronald; Buentello, Alexandria; David R Murdock; Ginger A Metcalf; Hadley, Trevor D; Riconda, Daniel L; Eric Boerwinkle; Wehrens, Xander H T; Ballantyne, Christie M; Richard A Gibbs; et al. (Circ Genom Precis Med, 2022)
BACKGROUND: Routine genome-wide screening for cardiovascular disease risk may inform clinical decision-making. However, little is known about whether clinicians and patients would find such testing useful or acceptable within the context of a genomics-enabled learning health system. METHODS: We conducted surveys with patients and their clinicians who were participating in the HeartCare Study, a precision cardiology care project that returned results from a next-generation sequencing panel of 158 genes associated with cardiovascular disease risk. Six weeks after return of results, we assessed patients' and clinicians' perceived utility and disutility of HeartCare, the effect of the test on clinical recommendations, and patients' attitudes toward integration of research and clinical care. RESULTS: Among 666 HeartCare patients with a result returned during the survey study period, 42.0% completed a full or partial survey. Patient-participants who completed a full survey (n=224) generally had positive perceptions of HeartCare independent of whether they received a positive or negative result. Most patient-participants considered genetic testing for cardiovascular disease risk to have more benefit than risk (88.3%) and agreed that it provided information that they wanted to know (81.2%), while most disagreed that the test caused them to feel confused (77.7%) or overwhelmed (78.0%). For 122 of their patients with positive results, clinicians (n=13) reported making changes in clinical care for 66.4% of patients, recommending changes in health behaviors for 36.9% of patients, and recommending to 33.6% of patients that their family members have clinical testing. CONCLUSIONS: Both patients and clinicians thought the HeartCare panel screen for cardiovascular disease risk provided information that was useful in terms of personal or health benefits to the patient and that informed clinical care without causing patients to be confused or overwhelmed. Further research is needed to assess perceptions of genome-wide screening among the US cardiology clinic population.
Keywords: Cardiology; Cardiovascular Diseases; Clinical Decision-Making; Family; Humans; Surveys and Questionnaires

Phenotypic and mutational spectrum of ROR2-related Robinow syndrome. - Lima, Ariadne R; Ferreira, Barbara M; Zhang, Chaofan; Jolly, Angad; Du, Haowei; White, Janson J; Dawood, Moez; Lins, Tulio C; Chiabai, Marcela A; van Beusekom, Ellen; Cordoba, Mara S; Caldas Rosa, Erica C C; et al. (Hum Mutat, 2022)
Robinow syndrome is characterized by a triad of craniofacial dysmorphisms, disproportionate-limb short stature, and genital hypoplasia. A significant degree of phenotypic variability seems to correlate with different genes/loci. Disturbances of the noncanonical WNT-pathway have been identified as the main cause of the syndrome. Biallelic variants in ROR2 cause an autosomal recessive form of the syndrome with distinctive skeletal findings. Twenty-two patients with a clinical diagnosis of autosomal recessive Robinow syndrome were screened for variants in ROR2 using multiple molecular approaches. We identified 25 putatively pathogenic ROR2 variants, 16 novel, including single nucleotide variants and exonic deletions. Detailed phenotypic analyses revealed that all subjects presented with a prominent forehead, hypertelorism, short nose, abnormality of the nasal tip, brachydactyly, mesomelic limb shortening, short stature, and genital hypoplasia in male patients. A total of 19 clinical features were present in more than 75% of the subjects, thus pointing to an overall uniformity of the phenotype. Disease-causing variants in ROR2, contribute to a clinically recognizable autosomal recessive trait phenotype with multiple skeletal defects. A comprehensive quantitative clinical evaluation of this cohort delineated the phenotypic spectrum of ROR2-related Robinow syndrome. The identification of exonic deletion variant alleles further supports the contention of a loss-of-function mechanism in the etiology of the syndrome.
Keywords: Craniofacial Abnormalities; Dwarfism; Genes, Recessive; Humans; Limb Deformities, Congenital; Male; Phenotype; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities

Proteogenomic Markers of Chemotherapy Resistance and Response in Triple-Negative Breast Cancer. - Anurag, Meenakshi; Jaehnig, Eric J; Krug, Karsten; Lei, Jonathan T; Bergstrom, Erik J; Kim, Beom-Jun; Vashist, Tanmayi D; Huynh, Anh Minh Tran; Dou, Yongchao; Gou, Xuxu; Huang, Chen; Shi, Zhiao; et al. (Cancer Discov, 2022)
UNLABELLED: Microscaled proteogenomics was deployed to probe the molecular basis for differential response to neoadjuvant carboplatin and docetaxel combination chemotherapy for triple-negative breast cancer (TNBC). Proteomic analyses of pretreatment patient biopsies uniquely revealed metabolic pathways, including oxidative phosphorylation, adipogenesis, and fatty acid metabolism, that were associated with resistance. Both proteomics and transcriptomics revealed that sensitivity was marked by elevation of DNA repair, E2F targets, G2-M checkpoint, interferon-gamma signaling, and immune-checkpoint components. Proteogenomic analyses of somatic copy-number aberrations identified a resistance-associated 19q13.31-33 deletion where LIG1, POLD1, and XRCC1 are located. In orthogonal datasets, LIG1 (DNA ligase I) gene deletion and/or low mRNA expression levels were associated with lack of pathologic complete response, higher chromosomal instability index (CIN), and poor prognosis in TNBC, as well as carboplatin-selective resistance in TNBC preclinical models. Hemizygous loss of LIG1 was also associated with higher CIN and poor prognosis in other cancer types, demonstrating broader clinical implications. SIGNIFICANCE: Proteogenomic analysis of triple-negative breast tumors revealed a complex landscape of chemotherapy response associations, including a 19q13.31-33 somatic deletion encoding genes serving lagging-strand DNA synthesis (LIG1, POLD1, and XRCC1), that correlate with lack of pathologic response, carboplatin-selective resistance, and, in pan-cancer studies, poor prognosis and CIN. This article is highlighted in the In This Issue feature, p. 2483.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Carboplatin; Humans; Neoadjuvant Therapy; Proteogenomics; Proteomics; Triple Negative Breast Neoplasms; X-ray Repair Cross Complementing Protein 1

Quantitative dissection of multilocus pathogenic variation in an Egyptian infant with severe neurodevelopmental disorder resulting from multiple molecular diagnoses. - Herman, Isabella; Jolly, Angad; Du, Haowei; Dawood, Moez; Abdel-Salam, Ghada M H; Marafi, Dana; Mitani, Tadahiro; Calame, Daniel G; Coban-Akdemir, Zeynep; Fatih, Jawid M; Hegazy, Ibrahim; Jhangiani, Shalini N; et al. (Am J Med Genet A, 2022)
Genomic sequencing and clinical genomics have demonstrated that substantial subsets of atypical and/or severe disease presentations result from multilocus pathogenic variation (MPV) causing blended phenotypes. In an infant with a severe neurodevelopmental disorder, four distinct molecular diagnoses were found by exome sequencing (ES). The blended phenotype that includes brain malformation, dysmorphism, and hypotonia was dissected using the Human Phenotype Ontology (HPO). ES revealed variants in CAPN3 (c.259C > G:p.L87V), MUSK (c.1781C > T:p.A594V), NAV2 (c.1996G > A:p.G666R), and ZC4H2 (c.595A > C:p.N199H). CAPN3, MUSK, and ZC4H2 are established disease genes linked to limb-girdle muscular dystrophy (OMIM# 253600), congenital myasthenia (OMIM# 616325), and Wieacker-Wolff syndrome (WWS; OMIM# 314580), respectively. NAV2 is a retinoic-acid responsive novel disease gene candidate with biological roles in neurite outgrowth and cerebellar dysgenesis in mouse models. Using semantic similarity, we show that no gene identified by ES individually explains the proband phenotype, but rather the totality of the clinically observed disease is explained by the combination of disease-contributing effects of the identified genes. These data reveal that multilocus pathogenic variation can result in a blended phenotype with each gene affecting a different part of the nervous system and nervous system-muscle connection. We provide evidence from this n = 1 study that in patients with MPV and complex blended phenotypes resulting from multiple molecular diagnoses, quantitative HPO analysis can allow for dissection of phenotypic contribution of both established disease genes and novel disease gene candidates not yet proven to cause human disease.
Keywords: Animals; Calpain; Egypt; Exome Sequencing; Humans; Infant; Muscle Proteins; Muscular Dystrophies, Limb-Girdle; Mutation; Neurodevelopmental Disorders; Phenotype

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Rare Variants in Genes Encoding Subunits of the Epithelial Na Channel Are Associated With Blood Pressure and Kidney Function. - Blobner, Brandon M; Kirabo, Annet; Kashlan, Ossama B; Sheng, Shaohu; Arnett, Donna K; Becker, Lewis C; Eric Boerwinkle; Carlson, Jenna C; Gao, Yan; Richard A Gibbs; He, Jiang; Irvin, Marguerite R; et al. (Hypertension, 2022)
BACKGROUND: The epithelial Na channel (ENaC) is intrinsically linked to fluid volume homeostasis and blood pressure. Specific rare mutations in , , and , genes encoding the α, β, and γ subunits of ENaC, respectively, are associated with extreme blood pressure phenotypes. No associations between blood pressure and , which encodes the δ subunit of ENaC, have been reported. A small number of sequence variants in ENaC subunits have been reported to affect functional transport in vitro or blood pressure. The effects of the vast majority of rare and low-frequency ENaC variants on blood pressure are not known. METHODS: We explored the association of low frequency and rare variants in the genes encoding ENaC subunits, with systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure. Using whole-genome sequencing data from 14 studies participating in the Trans-Omics in Precision Medicine Whole-Genome Sequencing Program, and sequence kernel association tests. RESULTS: We found that variants in and were associated with diastolic blood pressure and mean arterial pressure (<0.00625). Although is poorly expressed in human kidney tissue, variants were associated with systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure (<0.00625). ENaC variants in 2 of the 4 subunits ( and ) were also associated with estimated glomerular filtration rate (<0.00625), but not with stroke. CONCLUSIONS: Our results suggest that variants in extrarenal ENaCs, in addition to ENaCs expressed in kidneys, influence blood pressure and kidney function.
Keywords: Blood Pressure; Epithelial Sodium Channels; Humans; Kidney; Phenotype; Sodium

A reverse genetics and genomics approach to gene paralog function and disease: Myokymia and the juxtaparanode. - Marafi, Dana; Kozar, Nina; Duan, Ruizhi; Bradley, Stephen; Yokochi, Kenji; Al Mutairi, Fuad; Saadi, Nebal Waill; Whalen, Sandra; Brunet, Theresa; Kotzaeridou, Urania; Choukair, Daniela; Keren, Boris; et al. (Am J Hum Genet, 2022)
The leucine-rich glioma-inactivated (LGI) family consists of four highly conserved paralogous genes, LGI1-4, that are highly expressed in mammalian central and/or peripheral nervous systems. LGI1 antibodies are detected in subjects with autoimmune limbic encephalitis and peripheral nerve hyperexcitability syndromes (PNHSs) such as Isaacs and Morvan syndromes. Pathogenic variations of LGI1 and LGI4 are associated with neurological disorders as disease traits including familial temporal lobe epilepsy and neurogenic arthrogryposis multiplex congenita 1 with myelin defects, respectively. No human disease has been reported associated with either LGI2 or LGI3. We implemented exome sequencing and family-based genomics to identify individuals with deleterious variants in LGI3 and utilized GeneMatcher to connect practitioners and researchers worldwide to investigate the clinical and electrophysiological phenotype in affected subjects. We also generated Lgi3-null mice and performed peripheral nerve dissection and immunohistochemistry to examine the juxtaparanode LGI3 microarchitecture. As a result, we identified 16 individuals from eight unrelated families with loss-of-function (LoF) bi-allelic variants in LGI3. Deep phenotypic characterization showed LGI3 LoF causes a potentially clinically recognizable PNHS trait characterized by global developmental delay, intellectual disability, distal deformities with diminished reflexes, visible facial myokymia, and distinctive electromyographic features suggestive of motor nerve instability. Lgi3-null mice showed reduced and mis-localized Kv1 channel complexes in myelinated peripheral axons. Our data demonstrate bi-allelic LoF variants in LGI3 cause a clinically distinguishable disease trait of PNHS, most likely caused by disturbed Kv1 channel distribution in the absence of LGI3.
Keywords: Animals; Autoantibodies; Axons; Genomics; Humans; Intracellular Signaling Peptides and Proteins; Mammals; Mice; Myokymia; Nerve Tissue Proteins; Phenotype; Reverse Genetics

TCEAL1 loss-of-function results in an X-linked dominant neurodevelopmental syndrome and drives the neurological disease trait in Xq22.2 deletions. - Hijazi, Hadia; Reis, Linda M; Pehlivan, Davut; Bernstein, Jonathan A; Muriello, Michael; Syverson, Erin; Bonner, Devon; Estiar, Mehrdad A; Gan-Or, Ziv; Rouleau, Guy A; Lyulcheva, Ekaterina; Greenhalgh, Lynn; et al. (Am J Hum Genet, 2022)
An Xq22.2 region upstream of PLP1 has been proposed to underly a neurological disease trait when deleted in 46,XX females. Deletion mapping revealed that heterozygous deletions encompassing the smallest region of overlap (SRO) spanning six Xq22.2 genes (BEX3, RAB40A, TCEAL4, TCEAL3, TCEAL1, and MORF4L2) associate with an early-onset neurological disease trait (EONDT) consisting of hypotonia, intellectual disability, neurobehavioral abnormalities, and dysmorphic facial features. None of the genes within the SRO have been associated with monogenic disease in OMIM. Through local and international collaborations facilitated by GeneMatcher and Matchmaker Exchange, we have identified and herein report seven de novo variants involving TCEAL1 in seven unrelated families: three hemizygous truncating alleles; one hemizygous missense allele; one heterozygous TCEAL1 full gene deletion; one heterozygous contiguous deletion of TCEAL1, TCEAL3, and TCEAL4; and one heterozygous frameshift variant allele. Variants were identified through exome or genome sequencing with trio analysis or through chromosomal microarray. Comparison with previously reported Xq22 deletions encompassing TCEAL1 identified a more-defined syndrome consisting of hypotonia, abnormal gait, developmental delay/intellectual disability especially affecting expressive language, autistic-like behavior, and mildly dysmorphic facial features. Additional features include strabismus, refractive errors, variable nystagmus, gastroesophageal reflux, constipation, dysmotility, recurrent infections, seizures, and structural brain anomalies. An additional maternally inherited hemizygous missense allele of uncertain significance was identified in a male with hypertonia and spasticity without syndromic features. These data provide evidence that TCEAL1 loss of function causes a neurological rare disease trait involving significant neurological impairment with features overlapping the EONDT phenotype in females with the Xq22 deletion.
Keywords: Autistic Disorder; Female; Humans; Intellectual Disability; Male; Muscle Hypotonia; Phenotype; Syndrome; Transcription Factors

Truvari: refined structural variant comparison preserves allelic diversity. - English, Adam C; Menon, Vipin K; Richard A Gibbs; Ginger A Metcalf; Fritz J Sedlazeck (Genome Biol, 2022)
The fundamental challenge of multi-sample structural variant (SV) analysis such as merging and benchmarking is identifying when two SVs are the same. Common approaches for comparing SVs were developed alongside technologies which produce ill-defined boundaries. As SV detection becomes more exact, algorithms to preserve this refined signal are needed. Here, we present Truvari-an SV comparison, annotation, and analysis toolkit-and demonstrate the effect of SV comparison choices by building population-level VCFs from 36 haplotype-resolved long-read assemblies. We observe over-merging from other SV merging approaches which cause up to a 2.2× inflation of allele frequency, relative to Truvari.
Keywords: Algorithms; Alleles; Benchmarking; Gene Frequency; Genome, Human; Genomic Structural Variation; High-Throughput Nucleotide Sequencing; Humans

Whole genome sequence analysis of blood lipid levels in >66,000 individuals. - Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Pampana, Akhil; Zhang, David Y; Park, Joseph; Aslibekyan, Stella; Bis, Joshua C; Brody, Jennifer A; Cade, Brian E; Chuang, Lee-Ming; Chung, Ren-Hua; et al. (Nat Commun, 2022)
Blood lipids are heritable modifiable causal factors for coronary artery disease. Despite well-described monogenic and polygenic bases of dyslipidemia, limitations remain in discovery of lipid-associated alleles using whole genome sequencing (WGS), partly due to limited sample sizes, ancestral diversity, and interpretation of clinical significance. Among 66,329 ancestrally diverse (56% non-European) participants, we associate 428M variants from deep-coverage WGS with lipid levels; ~400M variants were not assessed in prior lipids genetic analyses. We find multiple lipid-related genes strongly associated with blood lipids through analysis of common and rare coding variants. We discover several associated rare non-coding variants, largely at Mendelian lipid genes. Notably, we observe rare LDLR intronic variants associated with markedly increased LDL-C, similar to rare LDLR exonic variants. In conclusion, we conducted a systematic whole genome scan for blood lipids expanding the alleles linked to lipids for multiple ancestries and characterize a clinically-relevant rare non-coding variant model for lipids.
Keywords: Alleles; Cholesterol, LDL; Genome-Wide Association Study; Humans; Lipids; Whole Genome Sequencing

Whole-exome sequencing of 14 389 individuals from the ESP and CHARGE consortia identifies novel rare variation associated with hemostatic factors. - Pankratz, Nathan; Wei, Peng; Brody, Jennifer A; Chen, Ming-Huei; de Vries, Paul S; Huffman, Jennifer E; Stimson, Mary Rachel; Auer, Paul L; Eric Boerwinkle; Cushman, Mary; de Maat, Moniek P M; Folsom, Aaron R; et al. (Hum Mol Genet, 2022)
Plasma levels of fibrinogen, coagulation factors VII and VIII and von Willebrand factor (vWF) are four intermediate phenotypes that are heritable and have been associated with the risk of clinical thrombotic events. To identify rare and low-frequency variants associated with these hemostatic factors, we conducted whole-exome sequencing in 10 860 individuals of European ancestry (EA) and 3529 African Americans (AAs) from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and the National Heart, Lung and Blood Institute's Exome Sequencing Project. Gene-based tests demonstrated significant associations with rare variation (minor allele frequency < 5%) in fibrinogen gamma chain (FGG) (with fibrinogen, P = 9.1 × 10-13), coagulation factor VII (F7) (with factor VII, P = 1.3 × 10-72; seven novel variants) and VWF (with factor VIII and vWF; P = 3.2 × 10-14; one novel variant). These eight novel rare variant associations were independent of the known common variants at these loci and tended to have much larger effect sizes. In addition, one of the rare novel variants in F7 was significantly associated with an increased risk of venous thromboembolism in AAs (Ile200Ser; rs141219108; P = 4.2 × 10-5). After restricting gene-based analyses to only loss-of-function variants, a novel significant association was detected and replicated between factor VIII levels and a stop-gain mutation exclusive to AAs (rs3211938) in CD36 molecule (CD36). This variant has previously been linked to dyslipidemia but not with the levels of a hemostatic factor. These efforts represent the largest integration of whole-exome sequence data from two national projects to identify genetic variation associated with plasma hemostatic factors.
Keywords: Exome Sequencing; Factor VII; Factor VIII; Fibrinogen; Hemostatics; Humans; Polymorphism, Single Nucleotide; von Willebrand Factor

Whole-genome sequencing as an investigational device for return of hereditary disease risk and pharmacogenomic results as part of the All of Us Research Program. - Eric Venner; Donna M Muzny; Smith, Joshua D; Kimberly Walker; Neben, Cynthia L; Lockwood, Christina M; Empey, Phillip E; Ginger A Metcalf; Kachulis, Chris; Mian, Sana; Musick, Anjene; Rehm, Heidi L; et al. (Genome Med, 2022)
BACKGROUND: The All of Us Research Program (AoURP, "the program") is an initiative, sponsored by the National Institutes of Health (NIH), that aims to enroll one million people (or more) across the USA. Through repeated engagement of participants, a research resource is being created to enable a variety of future observational and interventional studies. The program has also committed to genomic data generation and returning important health-related information to participants. METHODS: Whole-genome sequencing (WGS), variant calling processes, data interpretation, and return-of-results procedures had to be created and receive an Investigational Device Exemption (IDE) from the United States Food and Drug Administration (FDA). The performance of the entire workflow was assessed through the largest known cross-center, WGS-based, validation activity that was refined iteratively through interactions with the FDA over many months. RESULTS: The accuracy and precision of the WGS process as a device for the return of certain health-related genomic results was determined to be sufficient, and an IDE was granted. CONCLUSIONS: We present here both the process of navigating the IDE application process with the FDA and the results of the validation study as a guide to future projects which may need to follow a similar path. Changes to the program in the future will be covered in supplementary submissions to the IDE and will support additional variant classes, sample types, and any expansion to the reportable regions.
Keywords: Genomics; Humans; Pharmacogenetics; Population Health; United States; Whole Genome Sequencing

xAtlas: scalable small variant calling across heterogeneous next-generation sequencing experiments. - Farek, Jesse; Hughes, Daniel; Salerno, William; Zhu, Yiming; Pisupati, Aishwarya; Mansfield, Adam; Krasheninina, Olga; English, Adam C; Ginger A Metcalf; Eric Boerwinkle; Donna M Muzny; Richard A Gibbs; et al. (Gigascience, 2022)
BACKGROUND: The growing volume and heterogeneity of next-generation sequencing (NGS) data complicate the further optimization of identifying DNA variation, especially considering that curated high-confidence variant call sets frequently used to validate these methods are generally developed from the analysis of comparatively small and homogeneous sample sets. FINDINGS: We have developed xAtlas, a single-sample variant caller for single-nucleotide variants (SNVs) and small insertions and deletions (indels) in NGS data. xAtlas features rapid runtimes, support for CRAM and gVCF file formats, and retraining capabilities. xAtlas reports SNVs with 99.11% recall and 98.43% precision across a reference HG002 sample at 60× whole-genome coverage in less than 2 CPU hours. Applying xAtlas to 3,202 samples at 30× whole-genome coverage from the 1000 Genomes Project achieves an average runtime of 1.7 hours per sample and a clear separation of the individual populations in principal component analysis across called SNVs. CONCLUSIONS: xAtlas is a fast, lightweight, and accurate SNV and small indel calling method. Source code for xAtlas is available under a BSD 3-clause license at https://github.com/jfarek/xatlas.
Keywords: Algorithms; Genome; High-Throughput Nucleotide Sequencing; INDEL Mutation; Polymorphism, Single Nucleotide; Software

Author Correction: High-depth African genomes inform human migration and health. - Choudhury, Ananyo; Aron, Shaun; Botigué, Laura R; Sengupta, Dhriti; Botha, Gerrit; Bensellak, Taoufik; Wells, Gordon; Kumuthini, Judit; Shriner, Daniel; Fakim, Yasmina J; Ghoorah, Anisah W; Dareng, Eileen; et al. (Nature, 2021)

Biallelic loss-of-function variants in the splicing regulator NSRP1 cause a severe neurodevelopmental disorder with spastic cerebral palsy and epilepsy. - Calame, Daniel G; Bakhtiari, Somayeh; Logan, Rachel; Coban-Akdemir, Zeynep; Du, Haowei; Mitani, Tadahiro; Fatih, Jawid M; Hunter, Jill V; Herman, Isabella; Pehlivan, Davut; Jhangiani, Shalini N; Person, Richard; et al. (Genet Med, 2021)
PURPOSE: Alternative splicing plays a critical role in mouse neurodevelopment, regulating neurogenesis, cortical lamination, and synaptogenesis, yet few human neurodevelopmental disorders are known to result from pathogenic variation in splicing regulator genes. Nuclear Speckle Splicing Regulator Protein 1 (NSRP1) is a ubiquitously expressed splicing regulator not known to underlie a Mendelian disorder. METHODS: Exome sequencing and rare variant family-based genomics was performed as a part of the Baylor-Hopkins Center for Mendelian Genomics Initiative. Additional families were identified via GeneMatcher. RESULTS: We identified six patients from three unrelated families with homozygous loss-of-function variants in NSRP1. Clinical features include developmental delay, epilepsy, variable microcephaly (Z-scores -0.95 to -5.60), hypotonia, and spastic cerebral palsy. Brain abnormalities included simplified gyral pattern, underopercularization, and/or vermian hypoplasia. Molecular analysis identified three pathogenic NSRP1 predicted loss-of-function variant alleles: c.1359_1362delAAAG (p.Glu455AlafsTer20), c.1272dupG (p.Lys425GlufsTer5), and c.52C>T (p.Gln18Ter). The two frameshift variants result in a premature termination codon in the last exon, and the mutant transcripts are predicted to escape nonsense mediated decay and cause loss of a C-terminal nuclear localization signal required for NSRP1 function. CONCLUSION: We establish NSRP1 as a gene for a severe autosomal recessive neurodevelopmental disease trait characterized by developmental delay, epilepsy, microcephaly, and spastic cerebral palsy.
Keywords: Cerebral Palsy; Epilepsy; Humans; Microcephaly; Neurodevelopmental Disorders; Nuclear Proteins; Pedigree; RNA Splicing

Biallelic Pathogenic Variants in Associated With Congenital Myopathy. - Calame, Daniel G; Fatih, Jawid; Herman, Isabella; Akdemir, Zeynep Coban; Du, Haowei; Jhangiani, Shalini N; Richard A Gibbs; Marafi, Dana; Pehlivan, Davut; Posey, Jennifer E; Lotze, Timothy; Mancias, Pedro; et al. (Neurol Genet, 2021)
OBJECTIVE: Pathogenic variants in , the gene encoding fast skeletal muscle troponin T, were first described in autosomal dominant distal arthrogryposis type 2B2. Recently, a homozygous splice site variant, c.681+1G>A, was identified in a patient with nemaline myopathy and distal arthrogryposis. Here, we describe the second individual with congenital myopathy associated with biallelic variants. METHODS: Clinical exome sequencing data from a patient with molecularly undiagnosed congenital myopathy underwent research reanalysis. Clinical and histopathologic data were collected and compared with the single reported patient with -related congenital myopathy. RESULTS: A homozygous variant, c.481-1G>A, was identified. This variant alters a consensus splice acceptor and is predicted to affect splicing by multiple prediction tools. Both the patient reported here and the previously published patient exhibited limb, bulbar, and respiratory muscle weakness from birth, which improved over time. Other shared features include history of polyhydramnios, hypotonia, scoliosis, and high-arched palate. Distal arthrogryposis and nemaline rods, findings reported in the first patient with -related congenital myopathy, were not observed in the patient reported here. CONCLUSIONS: This report provides further evidence for the association of biallelic variants with severe recessive congenital myopathy with or without nemaline rods and distal arthrogryposis. sequencing and copy number analysis should be incorporated into the workup of congenital myopathies.

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.
Keywords: Cardiometabolic Risk Factors; Chromosomes, Human, X; Eye Proteins; Female; Gene Expression Regulation; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genotype; Humans; Lipids; Male; Middle Aged; Nerve Tissue Proteins; Phenomics; Polymorphism, Single Nucleotide; Subcutaneous Tissue; Whole Genome Sequencing

COPB2 loss of function causes a coatopathy with osteoporosis and developmental delay. - Marom, Ronit; Burrage, Lindsay C; Venditti, Rossella; Clément, Aurélie; Blanco-Sánchez, Bernardo; Jain, Mahim; Scott, Daryl A; Rosenfeld, Jill A; Sutton, V Reid; Shinawi, Marwan; Mirzaa, Ghayda; DeVile, Catherine; et al. (Am J Hum Genet, 2021)
Coatomer complexes function in the sorting and trafficking of proteins between subcellular organelles. Pathogenic variants in coatomer subunits or associated factors have been reported in multi-systemic disorders, i.e., coatopathies, that can affect the skeletal and central nervous systems. We have identified loss-of-function variants in COPB2, a component of the coatomer complex I (COPI), in individuals presenting with osteoporosis, fractures, and developmental delay of variable severity. Electron microscopy of COPB2-deficient subjects' fibroblasts showed dilated endoplasmic reticulum (ER) with granular material, prominent rough ER, and vacuoles, consistent with an intracellular trafficking defect. We studied the effect of COPB2 deficiency on collagen trafficking because of the critical role of collagen secretion in bone biology. COPB2 siRNA-treated fibroblasts showed delayed collagen secretion with retention of type I collagen in the ER and Golgi and altered distribution of Golgi markers. copb2-null zebrafish embryos showed retention of type II collagen, disorganization of the ER and Golgi, and early larval lethality. Copb2 mice exhibited low bone mass, and consistent with the findings in human cells and zebrafish, studies in Copb2 mouse fibroblasts suggest ER stress and a Golgi defect. Interestingly, ascorbic acid treatment partially rescued the zebrafish developmental phenotype and the cellular phenotype in Copb2 mouse fibroblasts. This work identifies a form of coatopathy due to COPB2 haploinsufficiency, explores a potential therapeutic approach for this disorder, and highlights the role of the COPI complex as a regulator of skeletal homeostasis.
Keywords: Animals; Ascorbic Acid; Bone and Bones; Brain; Child; Child, Preschool; Coat Protein Complex I; Coatomer Protein; Collagen Type I; Developmental Disabilities; Embryo, Nonmammalian; Endoplasmic Reticulum; Female; Fibroblasts; Gene Expression Regulation, Developmental; Golgi Apparatus; Haploinsufficiency; Humans; Intellectual Disability; Male; Mice; Osteoporosis; RNA, Small Interfering; Severity of Illness Index; Zebrafish

Correction to: Diversity and evolution of the transposable element repertoire in arthropods with particular reference to insects. - Petersen, Malte; Armisén, David; Richard A Gibbs; Hering, Lars; Khila, Abderrahman; Mayer, Georg; Stephen Richards; Niehuis, Oliver; Misof, Bernhard (BMC Ecol Evol, 2021)

Deep clinicopathological phenotyping identifies a previously unrecognized pathogenic EMD splice variant. - Calame, Daniel G; Fatih, Jawid M; Herman, Isabella; Coban-Akdemir, Zeynep; Du, Haowei; Mitani, Tadahiro; Jhangiani, Shalini N; Marafi, Dana; Richard A Gibbs; Posey, Jennifer E; Mehta, Vidya P; Mohila, Carrie A; et al. (Ann Clin Transl Neurol, 2021)
Exome sequencing (ES) has revolutionized rare disease management, yet only ~25%-30% of patients receive a molecular diagnosis. A limiting factor is the quality of available phenotypic data. Here, we describe how deep clinicopathological phenotyping yielded a molecular diagnosis for a 19-year-old proband with muscular dystrophy and negative clinical ES. Deep phenotypic analysis identified two critical data points: (1) the absence of emerin protein in muscle biopsy and (2) clinical features consistent with Emery-Dreifuss muscular dystrophy. Sequencing data analysis uncovered an ultra-rare, intronic variant in EMD, the gene encoding emerin. The variant, NM_000117.3: c.188-6A > G, is predicted to impact splicing by in silico tools. This case thus illustrates how better integration of clinicopathologic data into ES analysis can enhance diagnostic yield with implications for clinical practice.
Keywords: Adult; Exome Sequencing; Humans; Male; Membrane Proteins; Muscle, Skeletal; Muscular Dystrophy, Emery-Dreifuss; Nuclear Proteins; Young Adult

DNA methylation patterns identify subgroups of pancreatic neuroendocrine tumors with clinical association. - Lakis, Vanessa; Lawlor, Rita T; Newell, Felicity; Patch, Ann-Marie; Mafficini, Andrea; Sadanandam, Anguraj; Koufariotis, Lambros T; Johnston, Rebecca L; Leonard, Conrad; Wood, Scott; Rusev, Borislav; Corbo, Vincenzo; et al. (Commun Biol, 2021)
Here we report the DNA methylation profile of 84 sporadic pancreatic neuroendocrine tumors (PanNETs) with associated clinical and genomic information. We identified three subgroups of PanNETs, termed T1, T2 and T3, with distinct patterns of methylation. The T1 subgroup was enriched for functional tumors and ATRX, DAXX and MEN1 wild-type genotypes. The T2 subgroup contained tumors with mutations in ATRX, DAXX and MEN1 and recurrent patterns of chromosomal losses in half of the genome with no association between regions with recurrent loss and methylation levels. T2 tumors were larger and had lower methylation in the MGMT gene body, which showed positive correlation with gene expression. The T3 subgroup harboured mutations in MEN1 with recurrent loss of chromosome 11, was enriched for grade G1 tumors and showed histological parameters associated with better prognosis. Our results suggest a role for methylation in both driving tumorigenesis and potentially stratifying prognosis in PanNETs.
Keywords: Biomarkers, Tumor; Carcinoma, Neuroendocrine; DNA Methylation; Epigenesis, Genetic; Epigenome; Epigenomics; Genetic Predisposition to Disease; Humans; Neoplasm Grading; Pancreatic Neoplasms; Phenotype; Tumor Burden

Durable Response to Larotrectinib in a Child With Histologic Diagnosis of Recurrent Disseminated Ependymoma Discovered to Harbor an Fusion: The Impact of Integrated Genomic Profiling. - Mangum, Ross; Reuther, Jacquelyn; Bertrand, Kelsey C; Chandramohan, Raghu; Kukreja, Marcia K; Paulino, Arnold C; Donna M Muzny; Jianhong Hu; Richard A Gibbs; Curry, Daniel J; Malbari, Fatema; Chintagumpala, Murali M; et al. (JCO Precis Oncol, 2021)
Keywords: Brain Neoplasms; Child; Ependymoma; Gene Expression Profiling; Humans; Male; Membrane Glycoproteins; Neoplasm Recurrence, Local; Pyrazoles; Pyrimidines; Receptor, trkB

Exome sequencing in children with clinically suspected maturity-onset diabetes of the young. - Tosur, Mustafa; Soler-Alfonso, Claudia; Chan, Katie M; Khayat, Michael M; Jhangiani, Shalini N; Meng, Qingchang; Refaey, Ahmad; Donna M Muzny; Richard A Gibbs; David R Murdock; Posey, Jennifer E; Balasubramanyam, Ashok; et al. (Pediatr Diabetes, 2021)
OBJECTIVE: Commercial gene panels identify pathogenic variants in as low as 27% of patients suspected to have MODY, suggesting the role of yet unidentified pathogenic variants. We sought to identify novel gene variants associated with MODY. RESEARCH DESIGN AND METHODS: We recruited 10 children with a clinical suspicion of MODY but non-diagnostic commercial MODY gene panels. We performed exome sequencing (ES) in them and their parents. RESULTS: Mean age at diabetes diagnosis was 10 (± 3.8) years. Six were females; 4 were non-Hispanic white, 5 Hispanic, and 1 Asian. Our variant prioritization analysis identified a pathogenic, de novo variant in INS (c.94G > A, p.Gly32Ser), confirmed by Sanger sequencing, in a proband who was previously diagnosed with "autoantibody-negative type 1 diabetes (T1D)" at 3 y/o. This rare variant, absent in the general population (gnomAD database), has been reported previously in neonatal diabetes. We also identified a frameshift deletion (c.2650delC, p.Gln884AsnfsTer57) in RFX6 in a child with a previous diagnosis of "autoantibody-negative T1D" at 12 y/o. The variant was inherited from the mother, who was diagnosed with "thin type 2 diabetes" at 25 y/o. Heterozygous protein-truncating variants in RFX6 gene have been recently reported in individuals with MODY. CONCLUSIONS: We diagnosed two patients with MODY using ES in children initially classified as "T1D". One has a likely pathogenic novel gene variant not previously associated with MODY. We demonstrate the clinical utility of ES in patients with clinical suspicion of MODY.
Keywords: Adolescent; Autoantibodies; Child; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; Diagnosis, Differential; Exome Sequencing; Female; Frameshift Mutation; Genetic Variation; Humans; Islets of Langerhans; Male; Mutation, Missense; Pedigree

Exome variant discrepancies due to reference-genome differences. - Li, He; Dawood, Moez; Khayat, Michael M; Farek, Jesse R; Jhangiani, Shalini N; Khan, Ziad M; Mitani, Tadahiro; Coban-Akdemir, Zeynep; James R Lupski; Eric Venner; Posey, Jennifer E; Aniko Sabo; et al. (Am J Hum Genet, 2021)
Despite release of the GRCh38 human reference genome more than seven years ago, GRCh37 remains more widely used by most research and clinical laboratories. To date, no study has quantified the impact of utilizing different reference assemblies for the identification of variants associated with rare and common diseases from large-scale exome-sequencing data. By calling variants on both the GRCh37 and GRCh38 references, we identified single-nucleotide variants (SNVs) and insertion-deletions (indels) in 1,572 exomes from participants with Mendelian diseases and their family members. We found that a total of 1.5% of SNVs and 2.0% of indels were discordant when different references were used. Notably, 76.6% of the discordant variants were clustered within discrete discordant reference patches (DISCREPs) comprising only 0.9% of loci targeted by exome sequencing. These DISCREPs were enriched for genomic elements including segmental duplications, fix patch sequences, and loci known to contain alternate haplotypes. We identified 206 genes significantly enriched for discordant variants, most of which were in DISCREPs and caused by multi-mapped reads on the reference assembly that lacked the variant call. Among these 206 genes, eight are implicated in known Mendelian diseases and 53 are associated with common phenotypes from genome-wide association studies. In addition, variant interpretations could also be influenced by the reference after lifting-over variant loci to another assembly. Overall, we identified genes and genomic loci affected by reference assembly choice, including genes associated with Mendelian disorders and complex human diseases that require careful evaluation in both research and clinical applications.
Keywords: Cohort Studies; Exome; Genetic Diseases, Inborn; Genome, Human; Humans; Polymorphism, Single Nucleotide; Reference Values

Genetic testing in ambulatory cardiology clinics reveals high rate of findings with clinical management implications. - David R Murdock; Eric Venner; Donna M Muzny; Ginger A Metcalf; Mullai Murugan; Hadley, Trevor D; Chander, Varuna; de Vries, Paul S; Jia, Xiaoming; Hussain, Aliza; Agha, Ali M; Aniko Sabo; et al. (Genet Med, 2021)
PURPOSE: Cardiovascular disease (CVD) is the leading cause of death in adults in the United States, yet the benefits of genetic testing are not universally accepted. METHODS: We developed the "HeartCare" panel of genes associated with CVD, evaluating high-penetrance Mendelian conditions, coronary artery disease (CAD) polygenic risk, LPA gene polymorphisms, and specific pharmacogenetic (PGx) variants. We enrolled 709 individuals from cardiology clinics at Baylor College of Medicine, and samples were analyzed in a CAP/CLIA-certified laboratory. Results were returned to the ordering physician and uploaded to the electronic medical record. RESULTS: Notably, 32% of patients had a genetic finding with clinical management implications, even after excluding PGx results, including 9% who were molecularly diagnosed with a Mendelian condition. Among surveyed physicians, 84% reported medical management changes based on these results, including specialist referrals, cardiac tests, and medication changes. LPA polymorphisms and high polygenic risk of CAD were found in 20% and 9% of patients, respectively, leading to diet, lifestyle, and other changes. Warfarin and simvastatin pharmacogenetic variants were present in roughly half of the cohort. CONCLUSION: Our results support the use of genetic information in routine cardiovascular health management and provide a roadmap for accompanying research.
Keywords: Adult; Cardiology; Cardiovascular Diseases; Genetic Testing; Humans; Pharmacogenetics; Pharmacogenomic Testing; United States

Genomic considerations for FHIR®; eMERGE implementation lessons. - Mullai Murugan; Babb, Lawrence J; Overby Taylor, Casey; Rasmussen, Luke V; Freimuth, Robert R; Eric Venner; Yan, Fei; Yi, Victoria; Granite, Stephen J; Zouk, Hana; Aronson, Samuel J; Power, Kevin; et al. (J Biomed Inform, 2021)
Structured representation of clinical genetic results is necessary for advancing precision medicine. The Electronic Medical Records and Genomics (eMERGE) Network's Phase III program initially used a commercially developed XML message format for standardized and structured representation of genetic results for electronic health record (EHR) integration. In a desire to move towards a standard representation, the network created a new standardized format based upon Health Level Seven Fast Healthcare Interoperability Resources (HL7® FHIR®), to represent clinical genomics results. These new standards improve the utility of HL7® FHIR® as an international healthcare interoperability standard for management of genetic data from patients. This work advances the establishment of standards that are being designed for broad adoption in the current health information technology landscape.
Keywords: Electronic Health Records; Genomics; Health Level Seven; Humans; Medical Informatics; Precision Medicine

Germline Cancer Predisposition Variants in Pediatric Rhabdomyosarcoma: A Report From the Children's Oncology Group. - Li, He; Sisoudiya, Saumya D; Martin-Giacalone, Bailey A; Khayat, Michael M; Dugan-Perez, Shannon; Marquez-Do, Deborah A; Scheurer, Michael E; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Chi, Yueh-Yun; Barkauskas, Donald A; et al. (J Natl Cancer Inst, 2021)
BACKGROUND: Several cancer-susceptibility syndromes are reported to underlie pediatric rhabdomyosarcoma (RMS); however, to our knowledge there have been no systematic efforts to characterize the heterogeneous genetic etiologies of this often-fatal malignancy. METHODS: We performed exome-sequencing on germline DNA from 615 patients with newly diagnosed RMS consented through the Children's Oncology Group. We compared the prevalence of cancer predisposition variants in 63 autosomal-dominant cancer predisposition genes in these patients with population controls (n = 9963). All statistical tests were 2-sided. RESULTS: We identified germline cancer predisposition variants in 45 RMS patients (7.3%; all FOXO1 fusion negative) across 15 autosomal dominant genes, which was statistically significantly enriched compared with controls (1.4%, P = 1.3 × 10-22). Specifically, 73.3% of the predisposition variants were found in predisposition syndrome genes previously associated with pediatric RMS risk, such as Li-Fraumeni syndrome (TP53) and neurofibromatosis type I (NF1). Notably, 5 patients had well-described oncogenic missense variants in HRAS (p.G12V and p.G12S) associated with Costello syndrome. Also, genetic etiology differed with histology, as germline variants were more frequent in embryonal vs alveolar RMS patients (10.0% vs 3.0%, P = .02). Although patients with a cancer predisposition variant tended to be younger at diagnosis (P = 9.9 × 10-4), 40.0% of germline variants were identified in those older than 3 years of age, which is in contrast to current genetic testing recommendations based on early age at diagnosis. CONCLUSIONS: These findings demonstrate that genetic risk of RMS results from germline predisposition variants associated with a wide spectrum of cancer susceptibility syndromes. Germline genetic testing for children with RMS should be informed by RMS subtypes and not be limited to only young patients.
Keywords: Child; Genetic Predisposition to Disease; Germ Cells; Germ-Line Mutation; Humans; Li-Fraumeni Syndrome; Rhabdomyosarcoma

Germline mutation in : a heterogeneous, multi-systemic developmental disorder characterized by transcriptional dysregulation. - Hansen, Adam W; Arora, Payal; Khayat, Michael M; Smith, Leah J; Lewis, Andrea M; Rossetti, Linda Z; Jayaseelan, Joy; Cristian, Ingrid; Haynes, Devon; DiTroia, Stephanie; Meeks, Naomi; Delgado, Mauricio R; et al. (HGG Adv, 2021)
germline variation in was recently reported to associate with a neurodevelopmental disorder. We report twelve individuals harboring putatively pathogenic or inherited variants in , detail their phenotypes, and map all known variants to the domain structure of and crystal structure of RNA polymerase II. Affected individuals were ascertained from a local data lake, pediatric genetics clinic, and an online community of families of affected individuals. These include six affected by missense variants (including one previously reported individual), four clinical laboratory samples affected by missense variation with unknown inheritance-with yeast functional assays further supporting altered function-one affected by a in-frame deletion, and one affected by a C-terminal frameshift variant inherited from a largely asymptomatic mother. Recurrently observed phenotypes include ataxia, joint hypermobility, short stature, skin abnormalities, congenital cardiac abnormalities, immune system abnormalities, hip dysplasia, and short Achilles tendons. We report a significantly higher occurrence of epilepsy (8/12, 66.7%) than previously reported (3/15, 20%) (p value = 0.014196; chi-square test) and a lower occurrence of hypotonia (8/12, 66.7%) than previously reported (14/15, 93.3%) (p value = 0.076309). -related developmental disorders likely represent a spectrum of related, multi-systemic developmental disorders, driven by distinct mechanisms, converging at a single locus.

Hidden biases in germline structural variant detection. - Khayat, Michael M; Sahraeian, Sayed Mohammad Ebrahim; Zarate, Samantha; Carroll, Andrew; Hong, Huixiao; Pan, Bohu; Shi, Leming; Richard A Gibbs; Mohiyuddin, Marghoob; Zheng, Yuanting; Fritz J Sedlazeck (Genome Biol, 2021)
BACKGROUND: Genomic structural variations (SV) are important determinants of genotypic and phenotypic changes in many organisms. However, the detection of SV from next-generation sequencing data remains challenging. RESULTS: In this study, DNA from a Chinese family quartet is sequenced at three different sequencing centers in triplicate. A total of 288 derivative data sets are generated utilizing different analysis pipelines and compared to identify sources of analytical variability. Mapping methods provide the major contribution to variability, followed by sequencing centers and replicates. Interestingly, SV supported by only one center or replicate often represent true positives with 47.02% and 45.44% overlapping the long-read SV call set, respectively. This is consistent with an overall higher false negative rate for SV calling in centers and replicates compared to mappers (15.72%). Finally, we observe that the SV calling variability also persists in a genotyping approach, indicating the impact of the underlying sequencing and preparation approaches. CONCLUSIONS: This study provides the first detailed insights into the sources of variability in SV identification from next-generation sequencing and highlights remaining challenges in SV calling for large cohorts. We further give recommendations on how to reduce SV calling variability and the choice of alignment methodology.
Keywords: Base Sequence; Bias; Chromosome Mapping; Genomic Structural Variation; Genomics; Germ Cells; High-Throughput Nucleotide Sequencing; Sequence Analysis, DNA

High prevalence of multilocus pathogenic variation in neurodevelopmental disorders in the Turkish population. - Mitani, Tadahiro; Isikay, Sedat; Gezdirici, Alper; Gulec, Elif Yilmaz; Punetha, Jaya; Fatih, Jawid M; Herman, Isabella; Akay, Gulsen; Du, Haowei; Calame, Daniel G; Ayaz, Akif; Tos, Tulay; et al. (Am J Hum Genet, 2021)
Neurodevelopmental disorders (NDDs) are clinically and genetically heterogenous; many such disorders are secondary to perturbation in brain development and/or function. The prevalence of NDDs is > 3%, resulting in significant sociocultural and economic challenges to society. With recent advances in family-based genomics, rare-variant analyses, and further exploration of the Clan Genomics hypothesis, there has been a logarithmic explosion in neurogenetic "disease-associated genes" molecular etiology and biology of NDDs; however, the majority of NDDs remain molecularly undiagnosed. We applied genome-wide screening technologies, including exome sequencing (ES) and whole-genome sequencing (WGS), to identify the molecular etiology of 234 newly enrolled subjects and 20 previously unsolved Turkish NDD families. In 176 of the 234 studied families (75.2%), a plausible and genetically parsimonious molecular etiology was identified. Out of 176 solved families, deleterious variants were identified in 218 distinct genes, further documenting the enormous genetic heterogeneity and diverse perturbations in human biology underlying NDDs. We propose 86 candidate disease-trait-associated genes for an NDD phenotype. Importantly, on the basis of objective and internally established variant prioritization criteria, we identified 51 families (51/176 = 28.9%) with multilocus pathogenic variation (MPV), mostly driven by runs of homozygosity (ROHs) - reflecting genomic segments/haplotypes that are identical-by-descent. Furthermore, with the use of additional bioinformatic tools and expansion of ES to additional family members, we established a molecular diagnosis in 5 out of 20 families (25%) who remained undiagnosed in our previously studied NDD cohort emanating from Turkey.
Keywords: Adolescent; Adult; Child; Child, Preschool; Cohort Studies; Exome Sequencing; Female; Genomics; Humans; Infant; Infant, Newborn; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree; Phenotype; Prevalence; Turkey; Young Adult

Immune Dysregulation Mimicking Systemic Lupus Erythematosus in a Patient With Lysinuric Protein Intolerance: Case Report and Review of the Literature. - Contreras, Josefina Longeri; Ladino, Mabel A; Aránguiz, Katherine; Mendez, Gonzalo P; Coban-Akdemir, Zeynep; Bo Yuan; Richard A Gibbs; Burrage, Lindsay C; James R Lupski; Chinn, Ivan K; Vogel, Tiphanie P; Orange, Jordan S; et al. (Front Pediatr, 2021)
Lysinuric protein intolerance (LPI) is an inborn error of metabolism caused by defective transport of cationic amino acids in epithelial cells of intestines, kidneys and other tissues as well as non-epithelial cells including macrophages. LPI is caused by biallelic, pathogenic variants in . The clinical phenotype of LPI includes failure to thrive and multi-system disease including hematologic, neurologic, pulmonary and renal manifestations. Individual presentations are extremely variable, often leading to misdiagnosis or delayed diagnosis. Here we describe a patient that clinically presented with immune dysregulation in the setting of early-onset systemic lupus erythematosus (SLE), including renal involvement, in whom an LPI diagnosis was suspected post-mortem based on exome sequencing analysis. A review of the literature was performed to provide an overview of the clinical spectrum and immune mechanisms involved in this disease. The precise mechanism by which ineffective amino acid transport triggers systemic inflammatory features is not yet understood. However, LPI should be considered in the differential diagnosis of early-onset SLE, particularly in the absence of response to immunosuppressive therapy.

missense mutations in Xia-Gibbs syndrome. - Khayat, Michael M; Jianhong Hu; Jiang, Yunyun; Li, He; Chander, Varuna; Dawood, Moez; Hansen, Adam W; Li, Shoudong; Friedman, Jennifer; Cross, Laura; Bijlsma, Emilia K; Ruivenkamp, Claudia A L; et al. (HGG Adv, 2021)
Xia-Gibbs syndrome (XGS; MIM: 615829) is a phenotypically heterogeneous neurodevelopmental disorder (NDD) caused by newly arising mutations in the AT-Hook DNA-Binding Motif-Containing 1 () gene that are predicted to lead to truncated AHDC1 protein synthesis. More than 270 individuals have been diagnosed with XGS worldwide. Despite the absence of an independent assay for AHDC1 protein function to corroborate potential functional consequences of rare variant genetic findings, there are also reports of individuals with XGS-like trait manifestations who have missense mutations and who have been provided a molecular diagnosis of the disorder. To investigate a potential contribution of missense mutations to XGS, we mapped the missense mutations from 10 such individuals to the AHDC1 conserved protein domain structure and detailed the observed phenotypes. Five newly identified individuals were ascertained from a local XGS Registry, and an additional five were taken from external reports or databases, including one publication. Where clinical data were available, individuals with missense mutations all displayed phenotypes consistent with those observed in individuals with truncating mutations, including delayed motor milestones, intellectual disability (ID), hypotonia, and speech delay. A subset of the 10 reported missense mutations cluster in two regions of the AHDC1 protein with known conserved domains, likely representing functional motifs. Variants outside the clustered regions score lower for computational prediction of their likely damaging effects. Overall, missense variants in are likely diagnostic of XGS when analysis of their position relative to conserved regions is considered together with disease trait manifestations.

muCNV: Genotyping Structural Variants for Population-level Sequencing. - Jun, Goo; Fritz J Sedlazeck; Zhu, Qihui; English, Adam; Ginger A Metcalf; Kang, Hyun Min; Lee, Charles; Richard A Gibbs; Eric Boerwinkle (Bioinformatics, 2021)
MOTIVATION: There are high demands for joint genotyping of structural variations with short-read sequencing, but efficient and accurate genotyping in population scale is a challenging task. RESULTS: We developed muCNV that aggregates per-sample summary pileups for joint genotyping of > 100,000 samples. Pilot results show very low Mendelian inconsistencies. Applications to large-scale projects in cloud show the computational efficiencies of muCNV genotyping pipeline. AVAILABILITY: muCNV is publicly available for download at: https://github.com/gjun/muCNV. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.

Neptune: an environment for the delivery of genomic medicine. - Eric Venner; Yi, Victoria; David R Murdock; Sara E Kalla; Wu, Tsung-Jung; Aniko Sabo; Li, Shoudong; Meng, Qingchang; Tian, Xia; Mullai Murugan; Cohen, Michelle; Kovar, Christie; et al. (Genet Med, 2021)
PURPOSE: Genomic medicine holds great promise for improving health care, but integrating searchable and actionable genetic data into electronic health records (EHRs) remains a challenge. Here we describe Neptune, a system for managing the interaction between a clinical laboratory and an EHR system during the clinical reporting process. METHODS: We developed Neptune and applied it to two clinical sequencing projects that required report customization, variant reanalysis, and EHR integration. RESULTS: Neptune has been applied for the generation and delivery of over 15,000 clinical genomic reports. This work spans two clinical tests based on targeted gene panels that contain 68 and 153 genes respectively. These projects demanded customizable clinical reports that contained a variety of genetic data types including single-nucleotide variants (SNVs), copy-number variants (CNVs), pharmacogenomics, and polygenic risk scores. Two variant reanalysis activities were also supported, highlighting this important workflow. CONCLUSION: Methods are needed for delivering structured genetic data to EHRs. This need extends beyond developing data formats to providing infrastructure that manages the reporting process itself. Neptune was successfully applied on two high-throughput clinical sequencing projects to build and deliver clinical reports to EHR systems. The software is open source and available at https://gitlab.com/bcm-hgsc/neptune .
Keywords: Electronic Health Records; Genomics; High-Throughput Nucleotide Sequencing; Humans; Neptune; Software

Neurodevelopmental disorder in an Egyptian family with a biallelic ALKBH8 variant. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Du, Haowei; Rafat, Karima; Fatih, Jawid M; Jhangiani, Shalini N; Coban-Akdemir, Zeynep; Richard A Gibbs; Pehlivan, Davut; Hunter, Jill V; Posey, Jennifer E; et al. (Am J Med Genet A, 2021)
Alkylated DNA repair protein AlkB homolog 8 (ALKBH8) is a member of the AlkB family of dioxygenases. ALKBH8 is a methyltransferase of the highly variable wobble nucleoside position in the anticodon loop of tRNA and thus plays a critical role in tRNA modification by preserving codon recognition and preventing errors in amino acid incorporation during translation. Moreover, its activity catalyzes uridine modifications that are proposed to be critical for accurate protein translation. Previously, two distinct homozygous truncating variants in the final exon of ALKBH8 were described in two unrelated large Saudi Arabian kindreds with intellectual developmental disorder and autosomal recessive 71 (MRT71) syndrome (MIM# 618504). Here, we report a third family-of Egyptian descent-harboring a novel homozygous frame-shift variant in the last exon of ALKBH8. Two affected siblings in this family exhibit global developmental delay and intellectual disability as shared characteristic features of MRT71 syndrome, and we further characterize their observed dysmorphic features and brain MRI findings. This description of a third family with a truncating ALKBH8 variant from a distinct population broadens the phenotypic and genotypic spectrum of MRT71 syndrome, affirms that perturbations in tRNA biogenesis can contribute to neurogenetic disease traits, and firmly establishes ALKBH8 as a novel neurodevelopmental disease gene.
Keywords: Adolescent; AlkB Homolog 8, tRNA Methyltransferase; Brain; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Infant; Magnetic Resonance Imaging; Male; Neurodevelopmental Disorders; Pedigree

NMIHBA results from hypomorphic PRUNE1 variants that lack short-chain exopolyphosphatase activity. - Nistala, Harikiran; Dronzek, John; Gonzaga-Jauregui, Claudia; Chim, Shek Man; Rajamani, Saathyaki; Nuwayhid, Samer; Delgado, Dennis; Burke, Elizabeth; Karaca, Ender; Franklin, Matthew C; Sarangapani, Prasad; Podgorski, Michael; et al. (Hum Mol Genet, 2021)
Neurodevelopmental disorder with microcephaly, hypotonia and variable brain anomalies (NMIHBA) is an autosomal recessive neurodevelopmental and neurodegenerative disorder characterized by global developmental delay and severe intellectual disability. Microcephaly, progressive cortical atrophy, cerebellar hypoplasia and delayed myelination are neurological hallmarks in affected individuals. NMIHBA is caused by biallelic variants in PRUNE1 encoding prune exopolyphosphatase 1. We provide in-depth clinical description of two affected siblings harboring compound heterozygous variant alleles, c.383G > A (p.Arg128Gln), c.520G > T (p.Gly174*) in PRUNE1. To gain insights into disease biology, we biochemically characterized missense variants within the conserved N-terminal aspartic acid-histidine-histidine (DHH) motif and provide evidence that they result in the destabilization of protein structure and/or loss of exopolyphosphatase activity. Genetic ablation of Prune1 results in midgestational lethality in mice, associated with perturbations to embryonic growth and vascular development. Our findings suggest that NMIHBA results from hypomorphic variant alleles in humans and underscore the potential key role of PRUNE1 exopolyphoshatase activity in neurodevelopment.
Keywords: Acid Anhydride Hydrolases; Alleles; Animals; Child, Preschool; Female; Humans; Infant; Intellectual Disability; Male; Mice; Microcephaly; Muscle Hypotonia; Mutation; Neurodevelopmental Disorders; Pedigree; Phenotype; Phosphoric Monoester Hydrolases

A novel homozygous SLC13A5 whole-gene deletion generated by Alu/Alu-mediated rearrangement in an Iraqi family with epileptic encephalopathy. - Duan, Ruizhi; Saadi, Nebal Waill; Grochowski, Christopher M; Bhadila, Ghalia; Faridoun, Afnan; Mitani, Tadahiro; Du, Haowei; Fatih, Jawid M; Jhangiani, Shalini N; Akdemir, Zeynep C; Richard A Gibbs; Pehlivan, Davut; et al. (Am J Med Genet A, 2021)
Biallelic loss-of-function (LoF) of SLC13A5 (solute carrier family 13, member 5) induced deficiency in sodium/citrate transporter (NaCT) causes autosomal recessive developmental epileptic encephalopathy 25 with hypoplastic amelogenesis imperfecta (DEE25; MIM #615905). Many pathogenic SLC13A5 single nucleotide variants (SNVs) and small indels have been described; however, no cases with copy number variants (CNVs) have been sufficiently investigated. We describe a consanguineous Iraqi family harboring an 88.5 kb homozygous deletion including SLC13A5 in Chr17p13.1. The three affected male siblings exhibit neonatal-onset epilepsy with fever-sensitivity, recurrent status epilepticus, global developmental delay/intellectual disability (GDD/ID), and other variable neurological findings as shared phenotypical features of DEE25. Two of the three affected subjects exhibit hypoplastic amelogenesis imperfecta (AI), while the proband shows no evidence of dental abnormalities or AI at 2 years of age with apparently unaffected primary dentition. Characterization of the genomic architecture at this locus revealed evidence for genomic instability generated by an Alu/Alu-mediated rearrangement; confirmed by break-point junction Sanger sequencing. This multiplex family from a distinct population elucidates the phenotypic consequence of complete LoF of SLC13A5 and illustrates the importance of read-depth-based CNV detection in comprehensive exome sequencing analysis to solve cases that otherwise remain molecularly unsolved.
Keywords: Alu Elements; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; Epilepsy, Generalized; Exome Sequencing; Female; Homozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Pedigree; Sequence Deletion; Symporters

Novel pathogenic genomic variants leading to autosomal dominant and recessive Robinow syndrome. - Zhang, Chaofan; Mazzeu, Juliana F; Eisfeldt, Jesper; Grochowski, Christopher M; White, Janson; Akdemir, Zeynep C; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lindstrand, Anna; James R Lupski; Sutton, V Reid; et al. (Am J Med Genet A, 2021)
Robinow syndrome (RS) is a genetically heterogeneous disorder characterized by skeletal dysplasia and a distinctive facial appearance. Previous studies have revealed locus heterogeneity with rare variants in DVL1, DVL3, FZD2, NXN, ROR2, and WNT5A underlying the etiology of RS. The aforementioned "Robinow-associated genes" and their gene products all play a role in the WNT/planar cell polarity signaling pathway. We performed gene-targeted Sanger sequencing, exome sequencing, genome sequencing, and array comparative genomic hybridization on four subjects with a clinical diagnosis of RS who had not had prior DNA testing. Individuals in our cohort were found to carry pathogenic or likely pathogenic variants in three RS related genes: DVL1, ROR2, and NXN. One subject was found to have a nonsense variant (c.817C > T [p.Gln273*]) in NXN in trans with an ~1 Mb telomeric deletion on chromosome 17p containing NXN, which supports our contention that biallelic NXN variant alleles are responsible for a novel autosomal recessive RS locus. These findings provide increased understanding of the role of WNT signaling in skeletal development and maintenance. These data further support the hypothesis that dysregulation of the noncanonical WNT pathway in humans gives rise to RS.
Keywords: Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exome Sequencing; Female; Genes, Dominant; Genes, Recessive; Genetic Heterogeneity; Genetic Predisposition to Disease; Genomic Structural Variation; Humans; Limb Deformities, Congenital; Male; Oxidoreductases; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities; Whole Genome Sequencing; Wnt Signaling Pathway

Oligonucleotide capture sequencing of the SARS-CoV-2 genome and subgenomic fragments from COVID-19 individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (PLoS One, 2021)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity among samples. Mixed allelic frequencies along the 20kb ORF1ab gene in one sample, suggested the presence of a defective viral RNA species subpopulation maintained in mixture with functional RNA in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.
Keywords: COVID-19; DNA, Complementary; Gene Frequency; Genetic Variation; Genome, Viral; Humans; Open Reading Frames; Real-Time Polymerase Chain Reaction; RNA, Viral; SARS-CoV-2; Sequence Analysis, DNA; Viral Load

Phenotypic and protein localization heterogeneity associated with AHDC1 pathogenic protein-truncating alleles in Xia-Gibbs syndrome. - Khayat, Michael M; Li, He; Chander, Varuna; Jianhong Hu; Hansen, Adam W; Li, Shoudong; Traynelis, Josh; Shen, Hua; Weissenberger, George; Stossi, Fabio; Johnson, Hannah L; James R Lupski; et al. (Hum Mutat, 2021)
Xia-Gibbs syndrome (XGS) is a rare Mendelian disease typically caused by de novo stop-gain or frameshift mutations in the AT-hook DNA binding motif containing 1 (AHDC1) gene. Patients usually present in early infancy with hypotonia and developmental delay and later exhibit intellectual disability (ID). The overall presentation is variable, however, and the emerging clinical picture is still evolving. A detailed phenotypic analysis of 34 XGS individuals revealed five core phenotypes (delayed motor milestones, speech delay, low muscle tone, ID, and hypotonia) in more than 80% of individuals and an additional 12 features that occurred more variably. Seizures and scoliosis were more frequently associated with truncations that arise before the midpoint of the protein although the occurrence of most features could not be predicted by the mutation position. Transient expression of wild type and different patient truncated AHDC1 protein forms in human cell lines revealed abnormal patterns of nuclear localization including a diffuse distribution of a short truncated form and nucleolar aggregation in mid-protein truncated forms. Overall, both the occurrence of variable phenotypes and the different distribution of the expressed protein reflect the heterogeneity of this syndrome.
Keywords: Abnormalities, Multiple; Alleles; DNA-Binding Proteins; Humans; Intellectual Disability; Mutation; Phenotype; Syndrome

RCL1 copy number variants are associated with a range of neuropsychiatric phenotypes. - Brownstein, Catherine A; Smith, Richard S; Rodan, Lance H; Gorman, Mark P; Hojlo, Margaret A; Garvey, Emily A; Li, Jianqiao; Cabral, Kristin; Bowen, Joshua J; Rao, Abhijit S; Genetti, Casie A; Carroll, Devon; et al. (Mol Psychiatry, 2021)
Mendelian and early-onset severe psychiatric phenotypes often involve genetic variants having a large effect, offering opportunities for genetic discoveries and early therapeutic interventions. Here, the index case is an 18-year-old boy, who at 14 years of age had a decline in cognitive functioning over the course of a year and subsequently presented with catatonia, auditory and visual hallucinations, paranoia, aggression, mood dysregulation, and disorganized thoughts. Exome sequencing revealed a stop-gain mutation in RCL1 (NM_005772.4:c.370 C > T, p.Gln124Ter), encoding an RNA 3'-terminal phosphate cyclase-like protein that is highly conserved across eukaryotic species. Subsequent investigations across two academic medical centers identified eleven additional cases of RCL1 copy number variations (CNVs) with varying neurodevelopmental or psychiatric phenotypes. These findings suggest that dosage variation of RCL1 contributes to a range of neurological and clinical phenotypes.
Keywords: Adolescent; DNA Copy Number Variations; Exome Sequencing; Humans; Male; Mutation; Phenotype

Response to Biesecker et al. - Hamosh, Ada; Amberger, Joanna S; Bocchini, Carol A; Bodurtha, Joann; Bult, Carol J; Chute, Christopher G; Cutting, Garry R; Dietz, Harry C; Firth, Helen V; Richard A Gibbs; Grody, Wayne W; Haendel, Melissa A; et al. (Am J Hum Genet, 2021)
Keywords: Blepharophimosis; Facies; Humans

Risk of sudden cardiac death in EXOSC5-related disease. - Calame, Daniel G; Herman, Isabella; Fatih, Jawid M; Du, Haowei; Akay, Gulsen; Jhangiani, Shalini N; Coban-Akdemir, Zeynep; Milewicz, Dianna M; Richard A Gibbs; Posey, Jennifer E; Marafi, Dana; Hunter, Jill V; et al. (Am J Med Genet A, 2021)
The RNA exosome is a multi-subunit complex involved in the processing, degradation, and regulated turnover of RNA. Several subunits are linked to Mendelian disorders, including pontocerebellar hypoplasia (EXOSC3, MIM #614678; EXOSC8, MIM #616081: and EXOSC9, MIM #618065) and short stature, hearing loss, retinitis pigmentosa, and distinctive facies (EXOSC2, MIM #617763). More recently, EXOSC5 (MIM *606492) was found to underlie an autosomal recessive neurodevelopmental disorder characterized by developmental delay, hypotonia, cerebellar abnormalities, and dysmorphic facies. An unusual feature of EXOSC5-related disease is the occurrence of complete heart block requiring a pacemaker in a subset of affected individuals. Here, we provide a detailed clinical and molecular characterization of two siblings with microcephaly, developmental delay, cerebellar volume loss, hypomyelination, with cardiac conduction and rhythm abnormalities including sinus node dysfunction, intraventricular conduction delay, atrioventricular block, and ventricular tachycardia (VT) due to compound heterozygous variants in EXOSC5: (1) NM_020158.4:c.341C > T (p.Thr114Ile; pathogenic, previously reported) and (2) NM_020158.4:c.302C > A (p.Thr101Lys; novel variant). A review of the literature revealed an additional family with biallelic EXOSC5 variants and cardiac conduction abnormalities. These clinical and molecular data provide compelling evidence that cardiac conduction abnormalities and arrhythmias are part of the EXOSC5-related disease spectrum and argue for proactive screening due to potential risk of sudden cardiac death.
Keywords: Antigens, Neoplasm; Atrioventricular Block; Child; Death, Sudden, Cardiac; Echocardiography; Electrocardiography; Exosome Multienzyme Ribonuclease Complex; Facies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Mutation; Pedigree; Phenotype; RNA-Binding Proteins; Sequence Analysis, DNA; Young Adult

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.
Keywords: Cytochrome P-450 CYP2D6; Genetic Variation; Genome, Human; Genomics; Haplotypes; Heterozygote; Humans; INDEL Mutation; Loss of Function Mutation; Mutagenesis; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Population Density; Precision Medicine; Quality Control; Sample Size; United States; Whole Genome Sequencing

Sequencing of a central nervous system tumor demonstrates cancer transmission in an organ transplant. - Marie-Claude Gingras; Aniko Sabo; Cardenas, Maria; Rana, Abbas; Dhingra, Sadhna; Meng, Qingchang; Jianhong Hu; Donna M Muzny; Harshavardhan Doddapaneni; Perez, Lesette; Korchina, Viktoriya; Nessner, Caitlin; et al. (Life Sci Alliance, 2021)
Four organ transplant recipients from an organ donor diagnosed with anaplastic pleomorphic xanthoastrocytoma developed fatal malignancies for which the origin could not be confirmed by standard methods. We identified the somatic mutational profiles of the neoplasms using next-generation sequencing technologies and tracked the relationship between the different samples. The data were consistent with the presence of an aggressive clonal entity in the donor and the subsequent proliferation of descendent tumors in each recipient. Deleterious mutations in , , , , and , and a chromosomal deletion spanning the genes, were shared between the recipients' lesions. In addition to demonstrating that DNA sequencing tracked a donor/recipient cancer transmission, this study established that the genetic profile of a donor tumor and its potential aggressive phenotype could have been determined before transplantation was considered. As the genetic correlates of tumor invasion and metastases become better known, adding genetic profiling by DNA sequencing to the data considered for transplant safety should be considered.
Keywords: Adolescent; Adult; Biomarkers, Tumor; Biopsy; Central Nervous System Neoplasms; DNA Mutational Analysis; Exome Sequencing; Female; Humans; INDEL Mutation; Male; Middle Aged; Mutation; Organ Transplantation; Prognosis; Sequence Analysis, DNA; Tissue Donors; Transplant Recipients; Transplants; Young Adult

Transmission event of SARS-CoV-2 Delta variant reveals multiple vaccine breakthrough infections. - Farinholt, Timothy; Harshavardhan Doddapaneni; Xiang Qin; Menon, Vipin; Meng, Qingchang; Ginger A Metcalf; Chao, Hsu; Marie-Claude Gingras; Farinholt, Paige; Agrawal, Charu; Donna M Muzny; Piedra, Pedro A; et al. (medRxiv, 2021)
IMPORTANCE: Vaccine breakthrough by an emergent SARS-CoV-2 variant poses a great risk to global public health. OBJECTIVE: To determine the SARS-CoV-2 variant responsible for 6 cases of vaccine breakthrough. DESIGN: Nasopharyngeal swabs from suspected vaccine breakthrough cases were tested for SARS-CoV-2 by qPCR for Wuhan-Hu1 and Alpha variant. Positive samples were then sequenced by Swift Normalase Amplicon Panels to determine the causal variant. SETTING: Transmission event occurred at events surrounding a wedding outside of Houston, TX. Two patients from India, likely transmitted the Delta variant to other guests. PARTICIPANTS: Following a positive SARS-CoV-2 qPCR test at a third-party site, six fully vaccinated patients were investigated. Three males and three females ranged from 53 to 69 years old. One patient suffered from diabetes while three others were classified as overweight. No significant other comorbidities were identified. None of the patients had a history of failed vaccination. KEY POINTS: Which SARS-CoV-2 variant is responsible for 6 cases of vaccine breakthrough, one interventional monoclonal antibody treatment, and one death? Viral sequencing revealed 6 vaccinated patients were infected with the Delta SARS-CoV-2 variant. With no histories of vaccine breakthrough, this suggests Delta variant may possess immune evasion in patients that received the Pfizer BNT162b2, Moderna mRNA-1273, and Covaxin BBV152. Delta variant may pose the highest risk out of any currently circulating SARS-CoV-2 variants, with increased transmissibility over Alpha variant and possible vaccine breakthrough.

Transmission event of SARS-CoV-2 delta variant reveals multiple vaccine breakthrough infections. - Farinholt, Timothy; Harshavardhan Doddapaneni; Xiang Qin; Menon, Vipin; Meng, Qingchang; Ginger A Metcalf; Chao, Hsu; Marie-Claude Gingras; Avadhanula, Vasanthi; Farinholt, Paige; Agrawal, Charu; Donna M Muzny; et al. (BMC Med, 2021)
BACKGROUND: This study aims to identify the causative strain of SARS-CoV-2 in a cluster of vaccine breakthroughs. Vaccine breakthrough by a highly transmissible SARS-CoV-2 strain is a risk to global public health. METHODS: Nasopharyngeal swabs from suspected vaccine breakthrough cases were tested for SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) by qPCR (quantitative polymerase chain reaction) for Wuhan-Hu1 and alpha variant. Positive samples were then sequenced by Swift Normalase Amplicon Panels to determine the causal variant. GATK (genome analysis toolkit) variants were filtered with allele fraction ≥80 and min read depth 30x. RESULTS: Viral sequencing revealed an infection cluster of 6 vaccinated patients infected with the delta (B.1.617.2) SARS-CoV-2 variant. With no history of vaccine breakthrough, this suggests the delta variant may possess immune evasion in patients that received the Pfizer BNT162b2, Moderna mRNA-1273, and Covaxin BBV152. CONCLUSIONS: Delta variant may pose the highest risk out of any currently circulating SARS-CoV-2 variants, with previously described increased transmissibility over alpha variant and now, possible vaccine breakthrough. FUNDING: Parts of this work was supported by the National Institute of Allergy and Infectious Diseases (1U19AI144297) and Baylor College of Medicine internal funding.
Keywords: BNT162 Vaccine; COVID-19; COVID-19 Vaccines; Humans; Immune Evasion; SARS-CoV-2

Two novel bi-allelic KDELR2 missense variants cause osteogenesis imperfecta with neurodevelopmental features. - Efthymiou, Stephanie; Herman, Isabella; Rahman, Fatima; Anwar, Najwa; Maroofian, Reza; Yip, Janice; Mitani, Tadahiro; Calame, Daniel G; Hunter, Jill V; Sutton, V Reid; Yilmaz Gulec, Elif; Duan, Ruizhi; et al. (Am J Med Genet A, 2021)
Keywords: Alleles; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Neurodevelopmental Disorders; Osteogenesis Imperfecta; Vesicular Transport Proteins

Biallelic GRM7 variants cause epilepsy, microcephaly, and cerebral atrophy. - Marafi, Dana; Mitani, Tadahiro; Isikay, Sedat; Hertecant, Jozef; Almannai, Mohammed; Manickam, Kandamurugu; Abou Jamra, Rami; El-Hattab, Ayman W; Rajah, Jaishen; Fatih, Jawid M; Du, Haowei; Karaca, Ender; et al. (Ann Clin Transl Neurol, 2020)
OBJECTIVE: Defects in ion channels and neurotransmitter receptors are implicated in developmental and epileptic encephalopathy (DEE). Metabotropic glutamate receptor 7 (mGluR7), encoded by GRM7, is a presynaptic G-protein-coupled glutamate receptor critical for synaptic transmission. We previously proposed GRM7 as a candidate disease gene in two families with neurodevelopmental disorders (NDDs). One additional family has been published since. Here, we describe three additional families with GRM7 biallelic variants and deeply characterize the associated clinical neurological and electrophysiological phenotype and molecular data in 11 affected individuals from six unrelated families. METHODS: Exome sequencing and family-based rare variant analyses on a cohort of 220 consanguineous families with NDDs revealed three families with GRM7 biallelic variants; three additional families were identified through literature search and collaboration with a clinical molecular laboratory. RESULTS: We compared the observed clinical features and variants of 11 affected individuals from the six unrelated families. Identified novel deleterious variants included two homozygous missense variants (c.2671G>A:p.Glu891Lys and c.1973G>A:p.Arg685Gln) and one homozygous stop-gain variant (c.1975C>T:p.Arg659Ter). Developmental delay, neonatal- or infantile-onset epilepsy, and microcephaly were universal. Three individuals had hypothalamic-pituitary-axis dysfunction without pituitary structural abnormality. Neuroimaging showed cerebral atrophy and hypomyelination in a majority of cases. Two siblings demonstrated progressive loss of myelination by 2 years in both and an acquired microcephaly pattern in one. Five individuals died in early or late childhood. CONCLUSION: Detailed clinical characterization of 11 individuals from six unrelated families demonstrates that rare biallelic GRM7 pathogenic variants can cause DEEs, microcephaly, hypomyelination, and cerebral atrophy.
Keywords: Adolescent; Alleles; Atrophy; Child; Child, Preschool; Cohort Studies; Consanguinity; Epilepsy; Exome Sequencing; Female; Humans; Infant; Male; Microcephaly; Neurodevelopmental Disorders; Pedigree; Phenotype; Receptors, Metabotropic Glutamate

Biallelic in-frame deletion in TRAPPC4 in a family with developmental delay and cerebellar atrophy. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Jolly, Angad; Du, Haowei; Elbendary, Hasnaa M; Jhangiani, Shalini N; Akdemir, Zeynep C; Richard A Gibbs; Hunter, Jill V; Carvalho, Claudia M B C; Pehlivan, Davut; et al. (Brain, 2020)
Keywords: Atrophy; Cerebellar Diseases; Humans; Intellectual Disability; Sequence Deletion

Brown marmorated stink bug, Halyomorpha halys (Stål), genome: putative underpinnings of polyphagy, insecticide resistance potential and biology of a top worldwide pest. - Sparks, Michael E; Bansal, Raman; Benoit, Joshua B; Blackburn, Michael B; Chao, Hsu; Chen, Mengyao; Cheng, Sammy; Childers, Christopher; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; Elpidina, Elena N; et al. (BMC Genomics, 2020)
BACKGROUND: Halyomorpha halys (Stål), the brown marmorated stink bug, is a highly invasive insect species due in part to its exceptionally high levels of polyphagy. This species is also a nuisance due to overwintering in human-made structures. It has caused significant agricultural losses in recent years along the Atlantic seaboard of North America and in continental Europe. Genomic resources will assist with determining the molecular basis for this species' feeding and habitat traits, defining potential targets for pest management strategies. RESULTS: Analysis of the 1.15-Gb draft genome assembly has identified a wide variety of genetic elements underpinning the biological characteristics of this formidable pest species, encompassing the roles of sensory functions, digestion, immunity, detoxification and development, all of which likely support H. halys' capacity for invasiveness. Many of the genes identified herein have potential for biomolecular pesticide applications. CONCLUSIONS: Availability of the H. halys genome sequence will be useful for the development of environmentally friendly biomolecular pesticides to be applied in concert with more traditional, synthetic chemical-based controls.
Keywords: Animals; Ecosystem; Gene Transfer, Horizontal; Genome Size; Heteroptera; Insect Proteins; Insecticide Resistance; Introduced Species; Phylogeny; Whole Genome Sequencing

CNVs cause autosomal recessive genetic diseases with or without involvement of SNV/indels. - Bo Yuan; Wang, Lei; Liu, Pengfei; Shaw, Chad; Dai, Hongzheng; Cooper, Lance; Zhu, Wenmiao; Anderson, Stephanie A; Meng, Linyan; Wang, Xia; Wang, Yue; Xia, Fan; et al. (Genet Med, 2020)
PURPOSE: Improved resolution of molecular diagnostic technologies enabled detection of smaller sized exonic level copy-number variants (CNVs). The contribution of CNVs to autosomal recessive (AR) conditions may be better recognized using a large clinical cohort. METHODS: We retrospectively investigated the CNVs' contribution to AR conditions in cases subjected to chromosomal microarray analysis (CMA, N = ~70,000) and/or clinical exome sequencing (ES, N = ~12,000) at Baylor Genetics; most had pediatric onset neurodevelopmental disorders. RESULTS: CNVs contributed to biallelic variations in 87 cases, including 81 singletons and three affected sibling pairs. Seventy cases had CNVs affecting both alleles, and 17 had a CNV and a single-nucleotide variant (SNV)/indel in trans. In total, 94.3% of AR-CNVs affected one gene; among these 41.4% were single-exon and 35.0% were multiexon partial-gene events. Sixty-nine percent of homozygous AR-CNVs were embedded in homozygous genomic intervals. Five cases had large deletions unmasking an SNV/indel on the intact allele for a recessive condition, resulting in multiple molecular diagnoses. CONCLUSIONS: AR-CNVs are often smaller in size, transmitted through generations, and underrecognized due to limitations in clinical CNV detection methods. Our findings from a large clinical cohort emphasized integrated CNV and SNV/indel analyses for precise clinical and molecular diagnosis especially in the context of genomic disorders.
Keywords: Child; DNA Copy Number Variations; Exome Sequencing; Exons; Humans; INDEL Mutation; Retrospective Studies

Cohort Profile: The Right Drug, Right Dose, Right Time: Using Genomic Data to Individualize Treatment Protocol (RIGHT Protocol). - Bielinski, Suzette J; St Sauver, Jennifer L; Olson, Janet E; Larson, Nicholas B; Black, John L; Steven E Scherer; Bernard, Matthew E; Eric Boerwinkle; Borah, Bijan J; Caraballo, Pedro J; Curry, Timothy B; Harshavardhan Doddapaneni; et al. (Int J Epidemiol, 2020)
Keywords: Clinical Protocols; Cohort Studies; Female; Genomics; Humans; Male; Pharmacogenetics; Precision Medicine

Combination of whole exome sequencing and animal modeling identifies TMPRSS9 as a candidate gene for autism spectrum disorder. - Chen, Chun-An; Pal, Rituraj; Yin, Jiani; Tao, Huifang; Amawi, Abdallah; Aniko Sabo; Bainbridge, Matthew N; Richard A Gibbs; Zoghbi, Huda Y; Schaaf, Christian P (Hum Mol Genet, 2020)
Autism spectrum disorders are associated with some degree of developmental regression in up to 30% of all cases. Rarely, however, is the regression so extreme that a developmentally advanced young child would lose almost all ability to communicate and interact with her surroundings. We applied trio whole exome sequencing to a young woman who experienced extreme developmental regression starting at 2.5 years of age and identified compound heterozygous nonsense mutations in TMPRSS9, which encodes for polyserase-1, a transmembrane serine protease of poorly understood physiological function. Using semiquantitative polymerase chain reaction, we showed that Tmprss9 is expressed in various mouse tissues, including the brain. To study the consequences of TMPRSS9 loss of function on the mammalian brain, we generated a knockout mouse model. Through a battery of behavioral assays, we found that Tmprss9-/- mice showed decreased social interest and social recognition. We observed a borderline recognition memory deficit by novel object recognition in aged Tmprss9-/- female mice, but not in aged Tmprss9-/- male mice or younger adult Tmprss9-/- mice in both sexes. This study provides evidence to suggest that loss of function variants in TMPRSS9 are related to an autism spectrum disorder. However, the identification of more individuals with similar phenotypes and TMPRSS9 loss of function variants is required to establish a robust gene-disease relationship.
Keywords: Adolescent; Adult; Animals; Anxiety Disorders; Autism Spectrum Disorder; Child; Child, Preschool; Codon, Nonsense; Exome Sequencing; Female; Humans; Male; Membrane Proteins; Memory Disorders; Mice; Mice, Knockout; Motor Activity; Phenotype; Serine Endopeptidases

Community-based recruitment and exome sequencing indicates high diagnostic yield in adults with intellectual disability. - Aniko Sabo; David R Murdock; Dugan, Shannon; Meng, Qingchang; Marie-Claude Gingras; Jianhong Hu; Donna M Muzny; Richard A Gibbs (Mol Genet Genomic Med, 2020)
BACKGROUND: Establishing a genetic diagnosis for individuals with intellectual disability (ID) benefits patients and their families as it may inform the prognosis, lead to appropriate therapy, and facilitate access to medical and supportive services. Exome sequencing has been successfully applied in a diagnostic setting, but most clinical exome referrals are pediatric patients, with many adults with ID lacking a comprehensive genetic evaluation. METHODS: Our unique recruitment strategy involved partnering with service and education providers for individuals with ID. We performed exome sequencing and analysis, and clinical variant interpretation for each recruited family. RESULTS: All five families enrolled in the study opted-in for the return of genetic results. In three out of five families exome sequencing analysis identified pathogenic or likely pathogenic variants in KANSL1, TUSC3, and MED13L genes. Families discussed the results and any potential medical follow-up in an appointment with a board certified clinical geneticist. CONCLUSION: Our study suggests high yield of exome sequencing as a diagnostic tool in adult patients with ID who have not undergone comprehensive sequencing-based genetic testing. Research studies including an option of return of results through a genetic clinic could help minimize the disparity in exome diagnostic testing between pediatric and adult patients with ID.
Keywords: Adult; Exome Sequencing; Female; Genetic Testing; Humans; Independent Living; Intellectual Disability; Male; Mediator Complex; Membrane Proteins; Nuclear Proteins; Patient Selection; Sensitivity and Specificity; Tumor Suppressor Proteins

Correction to: Genome-enabled insights into the biology of thrips as crop pests. - Rotenberg, Dorith; Baumann, Aaron A; Ben-Mahmoud, Sulley; Christiaens, Olivier; Dermauw, Wannes; Ioannidis, Panagiotis; Jacobs, Chris G C; Vargas Jentzsch, Iris M; Oliver, Jonathan E; Poelchau, Monica F; Rajarapu, Swapna Priya; Schneweis, Derek J; et al. (BMC Biol, 2020)
An amendment to this paper has been published and can be accessed via the original article.

Correction: Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
A correction to this paper has been published and can be accessed via a link at the top of the paper.

Cultivating DNA Sequencing Technology After the Human Genome Project. - Schloss, Jeffery A; Richard A Gibbs; Makhijani, Vinod B; Marziali, Andre (Annu Rev Genomics Hum Genet, 2020)
When the Human Genome Project was completed in 2003, automated Sanger DNA sequencing with fluorescent dye labels was the dominant technology. Several nascent alternative methods based on older ideas that had not been fully developed were the focus of technical researchers and companies. Funding agencies recognized the dynamic nature of technology development and that, beyond the Human Genome Project, there were growing opportunities to deploy DNA sequencing in biological research. Consequently, the National Human Genome Research Institute of the National Institutes of Health created a program-widely known as the Advanced Sequencing Technology Program-that stimulated all stages of development of new DNA sequencing methods, from innovation to advanced manufacturing and production testing, with the goal of reducing the cost of sequencing a human genome first to $100,000 and then to $1,000. The events of this period provide a powerful example of how judicious funding of academic and commercial partners can rapidly advance core technology developments that lead to profound advances across the scientific landscape.
Keywords: Genome, Human; High-Throughput Nucleotide Sequencing; Human Genome Project; Humans; Sequence Analysis, DNA

Deficiencies in vesicular transport mediated by TRAPPC4 are associated with severe syndromic intellectual disability. - Van Bergen, Nicole J; Guo, Yiran; Al-Deri, Noraldin; Lipatova, Zhanna; Stanga, Daniela; Zhao, Sarah; Murtazina, Rakhilya; Gyurkovska, Valeriya; Pehlivan, Davut; Mitani, Tadahiro; Gezdirici, Alper; Antony, Jayne; et al. (Brain, 2020)
The conserved transport protein particle (TRAPP) complexes regulate key trafficking events and are required for autophagy. TRAPPC4, like its yeast Trs23 orthologue, is a core component of the TRAPP complexes and one of the essential subunits for guanine nucleotide exchange factor activity for Rab1 GTPase. Pathogenic variants in specific TRAPP subunits are associated with neurological disorders. We undertook exome sequencing in three unrelated families of Caucasian, Turkish and French-Canadian ethnicities with seven affected children that showed features of early-onset seizures, developmental delay, microcephaly, sensorineural deafness, spastic quadriparesis and progressive cortical and cerebellar atrophy in an effort to determine the genetic aetiology underlying neurodevelopmental disorders. All seven affected subjects shared the same identical rare, homozygous, potentially pathogenic variant in a non-canonical, well-conserved splice site within TRAPPC4 (hg19:chr11:g.118890966A>G; TRAPPC4: NM_016146.5; c.454+3A>G). Single nucleotide polymorphism array analysis revealed there was no haplotype shared between the tested Turkish and Caucasian families suggestive of a variant hotspot region rather than a founder effect. In silico analysis predicted the variant to cause aberrant splicing. Consistent with this, experimental evidence showed both a reduction in full-length transcript levels and an increase in levels of a shorter transcript missing exon 3, suggestive of an incompletely penetrant splice defect. TRAPPC4 protein levels were significantly reduced whilst levels of other TRAPP complex subunits remained unaffected. Native polyacrylamide gel electrophoresis and size exclusion chromatography demonstrated a defect in TRAPP complex assembly and/or stability. Intracellular trafficking through the Golgi using the marker protein VSVG-GFP-ts045 demonstrated significantly delayed entry into and exit from the Golgi in fibroblasts derived from one of the affected subjects. Lentiviral expression of wild-type TRAPPC4 in these fibroblasts restored trafficking, suggesting that the trafficking defect was due to reduced TRAPPC4 levels. Consistent with the recent association of the TRAPP complex with autophagy, we found that the fibroblasts had a basal autophagy defect and a delay in autophagic flux, possibly due to unsealed autophagosomes. These results were validated using a yeast trs23 temperature sensitive variant that exhibits constitutive and stress-induced autophagic defects at permissive temperature and a secretory defect at restrictive temperature. In summary we provide strong evidence for pathogenicity of this variant in a member of the core TRAPP subunit, TRAPPC4 that associates with vesicular trafficking and autophagy defects. This is the first report of a TRAPPC4 variant, and our findings add to the growing number of TRAPP-associated neurological disorders.
Keywords: Atrophy; Autophagy; Cerebellum; Cerebral Cortex; Child; Child, Preschool; Craniofacial Abnormalities; Deafness; Developmental Disabilities; Epilepsy; Female; Fibroblasts; Hearing Loss, Sensorineural; Humans; Infant; Infant, Newborn; Intellectual Disability; Male; Microcephaly; Microscopy, Fluorescence; Muscle Spasticity; Nerve Tissue Proteins; Neurodevelopmental Disorders; Pedigree; Quadriplegia; RNA Splice Sites; Syndrome; Vesicular Transport Proteins

A diagnostic ceiling for exome sequencing in cerebellar ataxia and related neurological disorders. - Ngo, Kathie J; Rexach, Jessica E; Lee, Hane; Petty, Lauren E; Perlman, Susan; Valera, Juliana M; Deignan, Joshua L; Mao, Yuanming; Aker, Mamdouh; Posey, Jennifer E; Jhangiani, Shalini N; Coban-Akdemir, Zeynep H; et al. (Hum Mutat, 2020)
Genetic ataxias are associated with mutations in hundreds of genes with high phenotypic overlap complicating the clinical diagnosis. Whole-exome sequencing (WES) has increased the overall diagnostic rate considerably. However, the upper limit of this method remains ill-defined, hindering efforts to address the remaining diagnostic gap. To further assess the role of rare coding variation in ataxic disorders, we reanalyzed our previously published exome cohort of 76 predominantly adult and sporadic-onset patients, expanded the total number of cases to 260, and introduced analyses for copy number variation and repeat expansion in a representative subset. For new cases (n = 184), our resulting clinically relevant detection rate remained stable at 47% with 24% classified as pathogenic. Reanalysis of the previously sequenced 76 patients modestly improved the pathogenic rate by 7%. For the combined cohort (n = 260), the total observed clinical detection rate was 52% with 25% classified as pathogenic. Published studies of similar neurological phenotypes report comparable rates. This consistency across multiple cohorts suggests that, despite continued technical and analytical advancements, an approximately 50% diagnostic rate marks a relative ceiling for current WES-based methods and a more comprehensive genome-wide assessment is needed to identify the missing causative genetic etiologies for cerebellar ataxia and related neurodegenerative diseases.
Keywords: Cerebellar Ataxia; DNA Copy Number Variations; Exome; Exome Sequencing; Genetic Association Studies; Genetic Linkage; Genetic Predisposition to Disease; Humans; Microsatellite Repeats; Nervous System Diseases

Disease-associated CTNNBL1 mutation impairs somatic hypermutation by decreasing nuclear AID. - Kuhny, Marcel; Forbes, Lisa R; Çakan, Elif; Vega-Loza, Andrea; Kostiuk, Valentyna; Dinesh, Ravi K; Glauzy, Salomé; Stray-Pedersen, Asbjorg; Pezzi, Ashley E; Hanson, I Celine; Vargas-Hernandez, Alexander; Xu, Mina LuQuing; et al. (J Clin Invest, 2020)
Patients with common variable immunodeficiency associated with autoimmune cytopenia (CVID+AIC) generate few isotype-switched B cells with severely decreased frequencies of somatic hypermutations (SHMs), but their underlying molecular defects remain poorly characterized. We identified a CVID+AIC patient who displays a rare homozygous missense M466V mutation in β-catenin-like protein 1 (CTNNBL1). Because CTNNBL1 binds activation-induced cytidine deaminase (AID) that catalyzes SHM, we tested AID interactions with the CTNNBL1 M466V variant. We found that the M466V mutation interfered with the association of CTNNBL1 with AID, resulting in decreased AID in the nuclei of patient EBV-transformed B cell lines and of CTNNBL1 466V/V Ramos B cells engineered to express only CTNNBL1 M466V using CRISPR/Cas9 technology. As a consequence, the scarce IgG+ memory B cells from the CTNNBL1 466V/V patient showed a low SHM frequency that averaged 6.7 mutations compared with about 18 mutations per clone in healthy-donor counterparts. In addition, CTNNBL1 466V/V Ramos B cells displayed a decreased incidence of SHM that was reduced by half compared with parental WT Ramos B cells, demonstrating that the CTNNBL1 M466V mutation is responsible for defective SHM induction. We conclude that CTNNBL1 plays an important role in regulating AID-dependent antibody diversification in humans.
Keywords: Amino Acid Substitution; Apoptosis Regulatory Proteins; B-Lymphocytes; Cell Line; Child, Preschool; Common Variable Immunodeficiency; Cytidine Deaminase; Female; Homozygote; Humans; Immunologic Memory; Mutation, Missense; Nuclear Proteins; Somatic Hypermutation, Immunoglobulin

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gozde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Bo Yuan; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Gene content evolution in the arthropods. - Thomas, Gregg W C; Dohmen, Elias; Hughes, Daniel S T; Murali, Shwetha C; Poelchau, Monica; Glastad, Karl; Anstead, Clare A; Ayoub, Nadia A; Batterham, Phillip; Bellair, Michelle; Binford, Greta J; Chao, Hsu; et al. (Genome Biol, 2020)
BACKGROUND: Arthropods comprise the largest and most diverse phylum on Earth and play vital roles in nearly every ecosystem. Their diversity stems in part from variations on a conserved body plan, resulting from and recorded in adaptive changes in the genome. Dissection of the genomic record of sequence change enables broad questions regarding genome evolution to be addressed, even across hyper-diverse taxa within arthropods. RESULTS: Using 76 whole genome sequences representing 21 orders spanning more than 500 million years of arthropod evolution, we document changes in gene and protein domain content and provide temporal and phylogenetic context for interpreting these innovations. We identify many novel gene families that arose early in the evolution of arthropods and during the diversification of insects into modern orders. We reveal unexpected variation in patterns of DNA methylation across arthropods and examples of gene family and protein domain evolution coincident with the appearance of notable phenotypic and physiological adaptations such as flight, metamorphosis, sociality, and chemoperception. CONCLUSIONS: These analyses demonstrate how large-scale comparative genomics can provide broad new insights into the genotype to phenotype map and generate testable hypotheses about the evolution of animal diversity.
Keywords: Animals; Arthropods; DNA Methylation; Evolution, Molecular; Genetic Speciation; Genetic Variation; Phylogeny

Genetic Burden Contributing to Extremely Low or High Bone Mineral Density in a Senior Male Population From the Osteoporotic Fractures in Men Study (MrOS). - Chen, Shan; Jain, Mahim; Jhangiani, Shalini; Akdemir, Zeynep C; Campeau, Philippe M; Klein, Robert F; Nielson, Carrie; Dai, Hongzheng; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Orwoll, Eric S; et al. (JBMR Plus, 2020)
Worldwide, one in five men aged over 50 years will experience osteoporosis or a clinical bone fracture, with a greater fracture-related mortality rate than women. However, the genetic etiology of osteoporosis in men is still poorly understood. We aimed to identify the genetic variants and candidate genes associated with extremely low or high BMD for a better understanding of the biology underlying low bone density that may point to potential therapeutic targets for increasing bone mass. Subjects from the Osteoporotic Fractures in Men Study (MrOS) cohort were evaluated by age and BMI-adjusted total hip BMD. Those with BMD values 3 SDs away from the mean were selected and the remaining individuals whose adjusted BMD ranked at the highest or lowest 100 were included. Men with the lowest adjusted BMD ( = 98) and highest adjusted BMD ( = 110) were chosen for exome sequencing. Controls ( = 82) were men of Northern and Western European descent from the US Utah population of the 1000 Genomes Project. Fisher's exact test was performed to compare low- or high-BMD subjects with controls for single-gene associations. Additionally, sets of candidate genes causative of heritable disorders of connective tissue, including osteogenesis imperfecta (OI) and Ehlers-Danlos syndrome (EDS), were grouped for multigene and mutation burden analyses. No single-gene associations with rare variants were found for either the low BMD group (33 genes) or high BMD group (18 genes). In the group of OI genes, we detected a significant threefold increased accumulation of rare variants in low-BMD subjects compared with controls ( = 0.009). Additionally, genes associated with EDS had a twofold increased frequency in low-BMD subjects compared with controls ( = 0.03). These findings reveal a rare variant burden in OI and EDS disease genes at low BMD, which suggests a potential gene-panel approach to screen for multivariant associations in larger cohorts. © 2019 The Authors. published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.

Genetics of schizophrenia in the South African Xhosa. - Gulsuner, S; Stein, D J; Susser, E S; Sibeko, G; Pretorius, A; Walsh, T; Majara, L; Mndini, M M; Mqulwana, S G; Ntola, O A; Casadei, S; Ngqengelele, L L; et al. (Science, 2020)
Africa, the ancestral home of all modern humans, is the most informative continent for understanding the human genome and its contribution to complex disease. To better understand the genetics of schizophrenia, we studied the illness in the Xhosa population of South Africa, recruiting 909 cases and 917 age-, gender-, and residence-matched controls. Individuals with schizophrenia were significantly more likely than controls to harbor private, severely damaging mutations in genes that are critical to synaptic function, including neural circuitry mediated by the neurotransmitters glutamine, γ-aminobutyric acid, and dopamine. Schizophrenia is genetically highly heterogeneous, involving severe ultrarare mutations in genes that are critical to synaptic plasticity. The depth of genetic variation in Africa revealed this relationship with a moderate sample size and informed our understanding of the genetics of schizophrenia worldwide.
Keywords: Age Factors; Autistic Disorder; Bipolar Disorder; Dopamine; Female; gamma-Aminobutyric Acid; Genetic Variation; Glutamine; Humans; Male; Mutation; Neural Pathways; Schizophrenia; Sex Factors; South Africa; Synapses; Synaptic Transmission

Genome-enabled insights into the biology of thrips as crop pests. - Rotenberg, Dorith; Baumann, Aaron A; Ben-Mahmoud, Sulley; Christiaens, Olivier; Dermauw, Wannes; Ioannidis, Panagiotis; Jacobs, Chris G C; Vargas Jentzsch, Iris M; Oliver, Jonathan E; Poelchau, Monica F; Rajarapu, Swapna Priya; Schneweis, Derek J; et al. (BMC Biol, 2020)
BACKGROUND: The western flower thrips, Frankliniella occidentalis (Pergande), is a globally invasive pest and plant virus vector on a wide array of food, fiber, and ornamental crops. The underlying genetic mechanisms of the processes governing thrips pest and vector biology, feeding behaviors, ecology, and insecticide resistance are largely unknown. To address this gap, we present the F. occidentalis draft genome assembly and official gene set. RESULTS: We report on the first genome sequence for any member of the insect order Thysanoptera. Benchmarking Universal Single-Copy Ortholog (BUSCO) assessments of the genome assembly (size = 415.8 Mb, scaffold N50 = 948.9 kb) revealed a relatively complete and well-annotated assembly in comparison to other insect genomes. The genome is unusually GC-rich (50%) compared to other insect genomes to date. The official gene set (OGS v1.0) contains 16,859 genes, of which ~ 10% were manually verified and corrected by our consortium. We focused on manual annotation, phylogenetic, and expression evidence analyses for gene sets centered on primary themes in the life histories and activities of plant-colonizing insects. Highlights include the following: (1) divergent clades and large expansions in genes associated with environmental sensing (chemosensory receptors) and detoxification (CYP4, CYP6, and CCE enzymes) of substances encountered in agricultural environments; (2) a comprehensive set of salivary gland genes supported by enriched expression; (3) apparent absence of members of the IMD innate immune defense pathway; and (4) developmental- and sex-specific expression analyses of genes associated with progression from larvae to adulthood through neometaboly, a distinct form of maturation differing from either incomplete or complete metamorphosis in the Insecta. CONCLUSIONS: Analysis of the F. occidentalis genome offers insights into the polyphagous behavior of this insect pest that finds, colonizes, and survives on a widely diverse array of plants. The genomic resources presented here enable a more complete analysis of insect evolution and biology, providing a missing taxon for contemporary insect genomics-based analyses. Our study also offers a genomic benchmark for molecular and evolutionary investigations of other Thysanoptera species.
Keywords: Animals; Crops, Agricultural; Feeding Behavior; Food Chain; Genome, Insect; Immunity, Innate; Life History Traits; Perception; Phylogeny; Reproduction; Thysanoptera; Transcriptome

HEM1 deficiency disrupts mTORC2 and F-actin control in inherited immunodysregulatory disease. - Cook, Sarah A; Comrie, William A; Poli, M Cecilia; Similuk, Morgan; Oler, Andrew J; Faruqi, Aiman J; Kuhns, Douglas B; Yang, Sheng; Vargas-Hernandez, Alexander; Carisey, Alexandre F; Fournier, Benjamin; Anderson, D Eric; et al. (Science, 2020)
Immunodeficiency often coincides with hyperactive immune disorders such as autoimmunity, lymphoproliferation, or atopy, but this coincidence is rarely understood on a molecular level. We describe five patients from four families with immunodeficiency coupled with atopy, lymphoproliferation, and cytokine overproduction harboring mutations in , which encodes the hematopoietic-specific HEM1 protein. These mutations cause the loss of the HEM1 protein and the WAVE regulatory complex (WRC) or disrupt binding to the WRC regulator, Arf1, thereby impairing actin polymerization, synapse formation, and immune cell migration. Diminished cortical actin networks caused by WRC loss led to uncontrolled cytokine release and immune hyperresponsiveness. HEM1 loss also blocked mechanistic target of rapamycin complex 2 (mTORC2)-dependent AKT phosphorylation, T cell proliferation, and selected effector functions, leading to immunodeficiency. Thus, the evolutionarily conserved HEM1 protein simultaneously regulates filamentous actin (F-actin) and mTORC2 signaling to achieve equipoise in immune responses.
Keywords: Actins; ADP-Ribosylation Factor 1; CD4-Positive T-Lymphocytes; Cell Proliferation; Cytokines; Humans; Immunologic Deficiency Syndromes; Lymphoproliferative Disorders; Mechanistic Target of Rapamycin Complex 2; Membrane Proteins; Pedigree; Phosphorylation; Wiskott-Aldrich Syndrome Protein Family

High-depth African genomes inform human migration and health. - Choudhury, Ananyo; Aron, Shaun; Botigué, Laura R; Sengupta, Dhriti; Botha, Gerrit; Bensellak, Taoufik; Wells, Gordon; Kumuthini, Judit; Shriner, Daniel; Fakim, Yasmina J; Ghoorah, Anisah W; Dareng, Eileen; et al. (Nature, 2020)
The African continent is regarded as the cradle of modern humans and African genomes contain more genetic variation than those from any other continent, yet only a fraction of the genetic diversity among African individuals has been surveyed. Here we performed whole-genome sequencing analyses of 426 individuals-comprising 50 ethnolinguistic groups, including previously unsampled populations-to explore the breadth of genomic diversity across Africa. We uncovered more than 3 million previously undescribed variants, most of which were found among individuals from newly sampled ethnolinguistic groups, as well as 62 previously unreported loci that are under strong selection, which were predominantly found in genes that are involved in viral immunity, DNA repair and metabolism. We observed complex patterns of ancestral admixture and putative-damaging and novel variation, both within and between populations, alongside evidence that Zambia was a likely intermediate site along the routes of expansion of Bantu-speaking populations. Pathogenic variants in genes that are currently characterized as medically relevant were uncommon-but in other genes, variants denoted as 'likely pathogenic' in the ClinVar database were commonly observed. Collectively, these findings refine our current understanding of continental migration, identify gene flow and the response to human disease as strong drivers of genome-level population variation, and underscore the scientific imperative for a broader characterization of the genomic diversity of African individuals to understand human ancestry and improve health.
Keywords: Africa; Datasets as Topic; DNA Repair; Female; Gene Flow; Genetic Variation; Genetics, Medical; Genetics, Population; Genome, Human; Genomics; Health; History, Ancient; Human Migration; Humans; Immunity; Language; Male; Metabolism; Selection, Genetic; Whole Genome Sequencing

The Human Genome Project changed everything. - Richard A Gibbs (Nat Rev Genet, 2020)
Thirty years on from the launch of the Human Genome Project, Richard Gibbs reflects on the promises that this voyage of discovery bore. Its success should be measured by how this project transformed the rules of research, the way of practising biological discovery and the ubiquitous digitization of biological science.
Keywords: Genetic Testing; Genetic Therapy; Genome, Human; Genomics; Human Genome Project; Humans; Information Dissemination; Pharmacogenetics; Risk Assessment

Human NK cell deficiency as a result of biallelic mutations in MCM10. - Mace, Emily M; Paust, Silke; Conte, Matilde I; Baxley, Ryan M; Schmit, Megan M; Patil, Sagar L; Guilz, Nicole C; Mukherjee, Malini; Pezzi, Ashley E; Chmielowiec, Jolanta; Tatineni, Swetha; Chinn, Ivan K; et al. (J Clin Invest, 2020)
Human natural killer cell deficiency (NKD) arises from inborn errors of immunity that lead to impaired NK cell development, function, or both. Through the understanding of the biological perturbations in individuals with NKD, requirements for the generation of terminally mature functional innate effector cells can be elucidated. Here, we report a cause of NKD resulting from compound heterozygous mutations in minichromosomal maintenance complex member 10 (MCM10) that impaired NK cell maturation in a child with fatal susceptibility to CMV. MCM10 has not been previously associated with monogenic disease and plays a critical role in the activation and function of the eukaryotic DNA replisome. Through evaluation of patient primary fibroblasts, modeling patient mutations in fibroblast cell lines, and MCM10 knockdown in human NK cell lines, we have shown that loss of MCM10 function leads to impaired cell cycle progression and induction of DNA damage-response pathways. By modeling MCM10 deficiency in primary NK cell precursors, including patient-derived induced pluripotent stem cells, we further demonstrated that MCM10 is required for NK cell terminal maturation and acquisition of immunological system function. Together, these data define MCM10 as an NKD gene and provide biological insight into the requirement for the DNA replisome in human NK cell maturation and function.
Keywords: Alleles; Cell Cycle Checkpoints; Cell Differentiation; Cell Line; Codon, Nonsense; DNA Damage; Fatal Outcome; Female; Gene Knockdown Techniques; Heterozygote; Humans; Induced Pluripotent Stem Cells; Infant; Killer Cells, Natural; Male; Minichromosome Maintenance Proteins; Models, Immunological; Mutation; Mutation, Missense; Pedigree; Primary Immunodeficiency Diseases

NF-κB and STAT3 co-operation enhances high glucose induced aggressiveness of cholangiocarcinoma cells. - Saengboonmee, Charupong; Phoomak, Chatchai; Supabphol, Suangson; Covington, Kyle R; Hampton, Oliver; Wongkham, Chaisiri; Richard A Gibbs; Umezawa, Kazuo; Seubwai, Wunchana; Marie-Claude Gingras; Wongkham, Sopit (Life Sci, 2020)
AIMS: The present report aimed to investigate the underlying genes and pathways of high glucose driving cholangiocarcinoma (CCA) aggressiveness. MAIN METHODS: We screened and compared the gene expression profiles obtained by RNA sequencing, of CCA cells cultured in high and normal glucose. Results from the transcriptomic analysis were confirmed in additional cell lines using in vitro migration-invasion assay, Western blotting and immunocytofluorescence. KEY FINDINGS: Data indicated that high glucose increased the expression of interleukin-1β (IL-1β), an upstream regulator of nuclear factor-κB (NF-κB) pathway, through the nuclear localization of NF-κB. High glucose-induced NF-κB increased the migration and invasion of CCA cells and the expression of downstream NF-κB targeted genes associated with aggressiveness, including interleukin-6, a potent triggering signal of the signal transducer and activator of transcription 3 (STAT3) pathway. Such effects were reversed by inhibiting NF-κB nuclear translocation which additionally reduced the phosphorylation of STAT3 at Y705. SIGNIFICANCE: These results indicate that NF-κB is activated by high glucose and they suggest that NF-κB interaction with STAT3 enhances CCA aggressiveness. Therefore, targeting multiple pathways such as STAT3 and NF-κB might improve CCA treatment outcome especially in condition such as hyperglycemia.
Keywords: Bile Duct Neoplasms; Cell Line, Tumor; Cell Movement; Cholangiocarcinoma; Gene Expression Regulation, Neoplastic; Glucose; Humans; Interleukin-1beta; Neoplasm Invasiveness; NF-kappa B; STAT3 Transcription Factor

Oligonucleotide capture sequencing of the SARS-CoV-2 genome and subgenomic fragments from COVID-19 individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (bioRxiv, 2020)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity and provided evidence of expression of ORF10. Heterogeneous allelic frequencies along the 20kb ORF1ab gene suggested the presence of a defective interfering viral RNA species subpopulation in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.

Oligonucleotide Capture Sequencing of the SARS-CoV-2 Genome and Subgenomic Fragments from COVID-19 Individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (bioRxiv, 2020)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity and provided evidence of expression of ORF10. Heterogeneous allelic frequencies along the 20kb ORF1ab gene suggested the presence of a defective interfering viral RNA species subpopulation in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.

Parliament2: Accurate structural variant calling at scale. - Zarate, Samantha; Carroll, Andrew; Mahmoud, Medhat; Krasheninina, Olga; Jun, Goo; Salerno, William J; Schatz, Michael C; Eric Boerwinkle; Richard A Gibbs; Fritz J Sedlazeck (Gigascience, 2020)
BACKGROUND: Structural variants (SVs) are critical contributors to genetic diversity and genomic disease. To predict the phenotypic impact of SVs, there is a need for better estimates of both the occurrence and frequency of SVs, preferably from large, ethnically diverse cohorts. Thus, the current standard approach requires the use of short paired-end reads, which remain challenging to detect, especially at the scale of hundreds to thousands of samples. FINDINGS: We present Parliament2, a consensus SV framework that leverages multiple best-in-class methods to identify high-quality SVs from short-read DNA sequence data at scale. Parliament2 incorporates pre-installed SV callers that are optimized for efficient execution in parallel to reduce the overall runtime and costs. We demonstrate the accuracy of Parliament2 when applied to data from NovaSeq and HiSeq X platforms with the Genome in a Bottle (GIAB) SV call set across all size classes. The reported quality score per SV is calibrated across different SV types and size classes. Parliament2 has the highest F1 score (74.27%) measured across the independent gold standard from GIAB. We illustrate the compute performance by processing all 1000 Genomes samples (2,691 samples) in <1 day on GRCH38. Parliament2 improves the runtime performance of individual methods and is open source (https://github.com/slzarate/parliament2), and a Docker image, as well as a WDL implementation, is available. CONCLUSION: Parliament2 provides both a highly accurate single-sample SV call set from short-read DNA sequence data and enables cost-efficient application over cloud or cluster environments, processing thousands of samples.
Keywords: Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis; Software

PCM1 is necessary for focal ciliary integrity and is a candidate for severe schizophrenia. - Monroe, Tanner O; Garrett, Melanie E; Kousi, Maria; Rodriguiz, Ramona M; Moon, Sungjin; Bai, Yushi; Brodar, Steven C; Soldano, Karen L; Savage, Jeremiah; Hansen, Thomas F; Donna M Muzny; Richard A Gibbs; et al. (Nat Commun, 2020)
The neuronal primary cilium and centriolar satellites have functions in neurogenesis, but little is known about their roles in the postnatal brain. We show that ablation of pericentriolar material 1 in the mouse leads to progressive ciliary, anatomical, psychomotor, and cognitive abnormalities. RNAseq reveals changes in amine- and G-protein coupled receptor pathways. The physiological relevance of this phenotype is supported by decreased available dopamine D2 receptor (D2R) levels and the failure of antipsychotic drugs to rescue adult behavioral defects. Immunoprecipitations show an association with Pcm1 and D2Rs. Finally, we sequence PCM1 in two human cohorts with severe schizophrenia. Systematic modeling of all discovered rare alleles by zebrafish in vivo complementation reveals an enrichment for pathogenic alleles. Our data emphasize a role for the pericentriolar material in the postnatal brain, with progressive degenerative ciliary and behavioral phenotypes; and they support a contributory role for PCM1 in some individuals diagnosed with schizophrenia.
Keywords: Adult; Aged; Alleles; Amines; Animals; Antipsychotic Agents; Brain; Cell Cycle Proteins; Cilia; Drug Resistance; Genetic Predisposition to Disease; Humans; Mice; Mice, Knockout; Middle Aged; Mutation; Phenotype; Receptors, Dopamine D2; Receptors, G-Protein-Coupled; Schizophrenia; Signal Transduction; Young Adult; Zebrafish

Phenotypic expansion in KIF1A-related dominant disorders: A description of novel variants and review of published cases. - Montenegro-Garreaud, Ximena; Hansen, Adam W; Khayat, Michael M; Chander, Varuna; Grochowski, Christopher M; Jiang, Yunyun; Li, He; Mitani, Tadahiro; Kessler, Elena; Jayaseelan, Joy; Shen, Hua; Gezdirici, Alper; et al. (Hum Mutat, 2020)
KIF1A is a molecular motor for membrane-bound cargo important to the development and survival of sensory neurons. KIF1A dysfunction has been associated with several Mendelian disorders with a spectrum of overlapping phenotypes, ranging from spastic paraplegia to intellectual disability. We present a novel pathogenic in-frame deletion in the KIF1A molecular motor domain inherited by two affected siblings from an unaffected mother with apparent germline mosaicism. We identified eight additional cases with heterozygous, pathogenic KIF1A variants ascertained from a local data lake. Our data provide evidence for the expansion of KIF1A-associated phenotypes to include hip subluxation and dystonia as well as phenotypes observed in only a single case: gelastic cataplexy, coxa valga, and double collecting system. We review the literature and suggest that KIF1A dysfunction is better understood as a single neuromuscular disorder with variable involvement of other organ systems than a set of discrete disorders converging at a single locus.
Keywords: Child; Child, Preschool; Family; Female; Genes, Dominant; Genetic Predisposition to Disease; Humans; Kinesins; Male; Mutation; Pedigree; Peru; Phenotype

Primate phylogenomics uncovers multiple rapid radiations and ancient interspecific introgression. - Vanderpool, Dan; Minh, Bui Quang; Lanfear, Robert; Hughes, Daniel; Murali, Shwetha; R. Alan Harris; Raveendran, Muthuswamy; Donna M Muzny; Hibbins, Mark S; Williamson, Robert J; Richard A Gibbs; Kim C Worley; et al. (PLoS Biol, 2020)
Our understanding of the evolutionary history of primates is undergoing continual revision due to ongoing genome sequencing efforts. Bolstered by growing fossil evidence, these data have led to increased acceptance of once controversial hypotheses regarding phylogenetic relationships, hybridization and introgression, and the biogeographical history of primate groups. Among these findings is a pattern of recent introgression between species within all major primate groups examined to date, though little is known about introgression deeper in time. To address this and other phylogenetic questions, here, we present new reference genome assemblies for 3 Old World monkey (OWM) species: Colobus angolensis ssp. palliatus (the black and white colobus), Macaca nemestrina (southern pig-tailed macaque), and Mandrillus leucophaeus (the drill). We combine these data with 23 additional primate genomes to estimate both the species tree and individual gene trees using thousands of loci. While our species tree is largely consistent with previous phylogenetic hypotheses, the gene trees reveal high levels of genealogical discordance associated with multiple primate radiations. We use strongly asymmetric patterns of gene tree discordance around specific branches to identify multiple instances of introgression between ancestral primate lineages. In addition, we exploit recent fossil evidence to perform fossil-calibrated molecular dating analyses across the tree. Taken together, our genome-wide data help to resolve multiple contentious sets of relationships among primates, while also providing insight into the biological processes and technical artifacts that led to the disagreements in the first place.
Keywords: Animals; Biological Evolution; Cercopithecidae; Computational Biology; Databases, Genetic; Fossils; Gene Flow; Genetic Introgression; Genome; Models, Genetic; Phylogeny; Primates; Sequence Analysis, DNA

Sawfly Genomes Reveal Evolutionary Acquisitions That Fostered the Mega-Radiation of Parasitoid and Eusocial Hymenoptera. - Oeyen, Jan Philip; Baa-Puyoulet, Patrice; Benoit, Joshua B; Beukeboom, Leo W; Bornberg-Bauer, Erich; Buttstedt, Anja; Calevro, Federica; Cash, Elizabeth I; Chao, Hsu; Charles, Hubert; Chen, Mei-Ju May; Childers, Christopher; et al. (Genome Biol Evol, 2020)
The tremendous diversity of Hymenoptera is commonly attributed to the evolution of parasitoidism in the last common ancestor of parasitoid sawflies (Orussidae) and wasp-waisted Hymenoptera (Apocrita). However, Apocrita and Orussidae differ dramatically in their species richness, indicating that the diversification of Apocrita was promoted by additional traits. These traits have remained elusive due to a paucity of sawfly genome sequences, in particular those of parasitoid sawflies. Here, we present comparative analyses of draft genomes of the primarily phytophagous sawfly Athalia rosae and the parasitoid sawfly Orussus abietinus. Our analyses revealed that the ancestral hymenopteran genome exhibited traits that were previously considered unique to eusocial Apocrita (e.g., low transposable element content and activity) and a wider gene repertoire than previously thought (e.g., genes for CO2 detection). Moreover, we discovered that Apocrita evolved a significantly larger array of odorant receptors than sawflies, which could be relevant to the remarkable diversification of Apocrita by enabling efficient detection and reliable identification of hosts.
Keywords: Amino Acid Sequence; Animals; Conserved Sequence; DNA Transposable Elements; Female; Gene Dosage; Genetic Speciation; Genome, Insect; Glycoproteins; Herbivory; Host-Parasite Interactions; Hymenoptera; Immunity; Insect Proteins; Male; Multigene Family; Receptors, Odorant; Social Behavior; Vision, Ocular

Sequence analysis in reveals pervasiveness of X-Y arms races in mammalian lineages. - Hughes, Jennifer F; Skaletsky, Helen; Pyntikova, Tatyana; Koutseva, Natalia; Raudsepp, Terje; Brown, Laura G; Bellott, Daniel W; Cho, Ting-Jan; Dugan-Rocha, Shannon; Ziad Khan; Kremitzki, Colin; Fronick, Catrina; et al. (Genome Res, 2020)
Studies of Y Chromosome evolution have focused primarily on gene decay, a consequence of suppression of crossing-over with the X Chromosome. Here, we provide evidence that suppression of X-Y crossing-over unleashed a second dynamic: selfish X-Y arms races that reshaped the sex chromosomes in mammals as different as cattle, mice, and men. Using super-resolution sequencing, we explore the Y Chromosome of (bull) and find it to be dominated by massive, lineage-specific amplification of testis-expressed gene families, making it the most gene-dense Y Chromosome sequenced to date. As in mice, an X-linked homolog of a bull Y-amplified gene has become testis-specific and amplified. This evolutionary convergence implies that lineage-specific X-Y coevolution through gene amplification, and the selfish forces underlying this phenomenon, were dominatingly powerful among diverse mammalian lineages. Together with Y gene decay, X-Y arms races molded mammalian sex chromosomes and influenced the course of mammalian evolution.
Keywords: Animals; Cattle; Cell Lineage; Crossing Over, Genetic; Evolution, Molecular; Female; Gene Amplification; Humans; Male; Mice; Organ Specificity; Sequence Analysis, DNA; Testis; X Chromosome; Y Chromosome

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Exome Sequencing; Female; Gene Expression Regulation; Haplotypes; Humans; Immunity; Immunoglobulin G; Kruppel-Like Transcription Factors; Male; Polymorphism, Genetic; RNA, Long Noncoding; Transcription, Genetic

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Wolff-Parkinson-White Syndrome; Young Adult

ARBoR: an identity and security solution for clinical reporting. - Eric Venner; Mullai Murugan; Hale, Walker; Jones, Jordan M; Lu, Shan; Yi, Victoria; Richard A Gibbs (J Am Med Inform Assoc, 2019)
MOTIVATION: Clinical genome sequencing laboratories return reports containing clinical testing results, signed by a board-certified clinical geneticist, to the ordering physician. This report is often a PDF, but can also be a paper copy or a structured data file. The reports are frequently modified and reissued due to changes in variant interpretation or clinical attributes. MATERIALS AND METHODS: To precisely track report authenticity, we developed ARBoR (Authenticated Resources in a Hashed Block Registry), an application for tracking the authenticity and lineage of versioned clinical reports even when they are distributed as PDF or paper copies. ARBoR tracks clinical reports as cryptographically signed hash blocks in an electronic ledger file, which is then exactly replicated to many clients. RESULTS: ARBoR was implemented for clinical reporting in the Human Genome Sequencing Center Clinical Laboratory, initially as part of the National Institute of Health's Electronic Medical Record and Genomics (eMERGE) project. CONCLUSIONS: To date, we have issued 15 205 versioned clinical reports tracked by ARBoR. This system has provided us with a simple and tamper-proof mechanism for tracking clinical reports with a complicated update history.
Keywords: Clinical Laboratory Techniques; Computer Security; Genetic Testing; Genome, Human; Genomics; Humans; Laboratories; Medical Records; Organizational Case Studies

Atlas-CNV: a validated approach to call single-exon CNVs in the eMERGESeq gene panel. - Chiang, Theodore; Liu, Xiuping; Wu, Tsung-Jung; Jianhong Hu; Fritz J Sedlazeck; White, Simon; Schaid, Daniel; Andrade, Mariza de; Jarvik, Gail P; Crosslin, David; Stanaway, Ian; Carrell, David S; et al. (Genet Med, 2019)
PURPOSE: To provide a validated method to confidently identify exon-containing copy-number variants (CNVs), with a low false discovery rate (FDR), in targeted sequencing data from a clinical laboratory with particular focus on single-exon CNVs. METHODS: DNA sequence coverage data are normalized within each sample and subsequently exonic CNVs are identified in a batch of samples, when the target log ratio of the sample to the batch median exceeds defined thresholds. The quality of exonic CNV calls is assessed by C-scores (Z-like scores) using thresholds derived from gold standard samples and simulation studies. We integrate an ExonQC threshold to lower FDR and compare performance with alternate software (VisCap). RESULTS: Thirteen CNVs were used as a truth set to validate Atlas-CNV and compared with VisCap. We demonstrated FDR reduction in validation, simulation, and 10,926 eMERGESeq samples without sensitivity loss. Sixty-four multiexon and 29 single-exon CNVs with high C-scores were assessed by Multiplex Ligation-dependent Probe Amplification (MLPA). CONCLUSION: Atlas-CNV is validated as a method to identify exonic CNVs in targeted sequencing data generated in the clinical laboratory. The ExonQC and C-score assignment can reduce FDR (identification of targets with high variance) and improve calling accuracy of single-exon CNVs respectively. We propose guidelines and criteria to identify high confidence single-exon CNVs.
Keywords: DNA Copy Number Variations; Exons; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software

Biallelic CACNA2D2 variants in epileptic encephalopathy and cerebellar atrophy. - Punetha, Jaya; Karaca, Ender; Gezdirici, Alper; Lamont, Ryan E; Pehlivan, Davut; Marafi, Dana; Appendino, Juan P; Hunter, Jill V; Akdemir, Zeynep C; Fatih, Jawid M; Jhangiani, Shalini N; Richard A Gibbs; et al. (Ann Clin Transl Neurol, 2019)
OBJECTIVE: To characterize the molecular and clinical phenotypic basis of developmental and epileptic encephalopathies caused by rare biallelic variants in CACNA2D2. METHODS: Two affected individuals from a family with clinical features of early onset epileptic encephalopathy were recruited for exome sequencing at the Centers for Mendelian Genomics to identify their molecular diagnosis. GeneMatcher facilitated identification of a second family with a shared candidate disease gene identified through clinical gene panel-based testing. RESULTS: Rare biallelic CACNA2D2 variants have been previously reported in three families with developmental and epileptic encephalopathy, and one family with congenital ataxia. We identified three individuals in two unrelated families with novel homozygous rare variants in CACNA2D2 with clinical features of developmental and epileptic encephalopathy and cerebellar atrophy. Family 1 includes two affected siblings with a likely damaging homozygous rare missense variant c.1778G>C; p.(Arg593Pro) in CACNA2D2. Family 2 includes a proband with a homozygous rare nonsense variant c.485_486del; p.(Tyr162Ter) in CACNA2D2. We compared clinical and molecular findings from all nine individuals reported to date and note that cerebellar atrophy is shared among all. INTERPRETATION: Our study supports the candidacy of CACNA2D2 as a disease gene associated with a phenotypic spectrum of neurological disease that include features of developmental and epileptic encephalopathy, ataxia, and cerebellar atrophy. Age at presentation may affect apparent penetrance of neurogenetic trait manifestations and of a particular clinical neurological endophenotype, for example, seizures or ataxia.
Keywords: Adult; Atrophy; Calcium Channels; Cerebellar Ataxia; Cerebellar Diseases; Epilepsy; Female; Humans; Male; Mutation, Missense; Pedigree; Seizures; Siblings; Spasms, Infantile

Bi-allelic Pathogenic Variants in TUBGCP2 Cause Microcephaly and Lissencephaly Spectrum Disorders. - Mitani, Tadahiro; Punetha, Jaya; Akalin, Ibrahim; Pehlivan, Davut; Dawidziuk, Mateusz; Coban Akdemir, Zeynep; Yilmaz, Sarenur; Aslan, Ezgi; Hunter, Jill V; Hijazi, Hadia; Grochowski, Christopher M; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2019)
Lissencephaly comprises a spectrum of malformations of cortical development. This spectrum includes agyria, pachygyria, and subcortical band heterotopia; each represents anatomical malformations of brain cortical development caused by neuronal migration defects. The molecular etiologies of neuronal migration anomalies are highly enriched for genes encoding microtubules and microtubule-associated proteins, and this enrichment highlights the critical role for these genes in cortical growth and gyrification. Using exome sequencing and family based rare variant analyses, we identified a homozygous variant (c.997C>T [p.Arg333Cys]) in TUBGCP2, encoding gamma-tubulin complex protein 2 (GCP2), in two individuals from a consanguineous family; both individuals presented with microcephaly and developmental delay. GCP2 forms the multiprotein γ-tubulin ring complex (γ-TuRC) together with γ-tubulin and other GCPs to regulate the assembly of microtubules. By querying clinical exome sequencing cases and through GeneMatcher-facilitated collaborations, we found three additional families with bi-allelic variation and similarly affected phenotypes including a homozygous variant (c.1843G>C [p.Ala615Pro]) in two families and compound heterozygous variants consisting of one missense variant (c.889C>T [p.Arg297Cys]) and one splice variant (c.2025-2A>G) in another family. Brain imaging from all five affected individuals revealed varying degrees of cortical malformations including pachygyria and subcortical band heterotopia, presumably caused by disruption of neuronal migration. Our data demonstrate that pathogenic variants in TUBGCP2 cause an autosomal recessive neurodevelopmental trait consisting of a neuronal migration disorder, and our data implicate GCP2 as a core component of γ-TuRC in neuronal migrating cells.
Keywords: Alleles; Brain; Cell Movement; Child; Exome; Female; Genetic Variation; Homozygote; Humans; Lissencephaly; Male; Microcephaly; Microtubule-Associated Proteins; Microtubules; Nervous System Malformations; Neurons; Phenotype; Tubulin

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes. - Burrage, Lindsay C; Reynolds, John J; Baratang, Nissan Vida; Phillips, Jennifer B; Wegner, Jeremy; McFarquhar, Ashley; Higgs, Martin R; Christiansen, Audrey E; Lanza, Denise G; Seavitt, John R; Jain, Mahim; Li, Xiaohui; et al. (Am J Hum Genet, 2019)
SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomal-recessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in individuals with SPONASTRIME dysplasia. Here, we identified bi-allelic variants in TONSL, which encodes the Tonsoku-like DNA repair protein, in nine subjects (from eight families) with SPONASTRIME dysplasia, and four subjects (from three families) with short stature of varied severity and spondylometaphyseal dysplasia with or without immunologic and hematologic abnormalities, but no definitive metaphyseal striations at diagnosis. The finding of early embryonic lethality in a Tonsl murine model and the discovery of reduced length, spinal abnormalities, reduced numbers of neutrophils, and early lethality in a tonsl zebrafish model both support the hypomorphic nature of the identified TONSL variants. Moreover, functional studies revealed increased amounts of spontaneous replication fork stalling and chromosomal aberrations, as well as fewer camptothecin (CPT)-induced RAD51 foci in subject-derived cell lines. Importantly, these cellular defects were rescued upon re-expression of wild-type (WT) TONSL; this rescue is consistent with the hypothesis that hypomorphic TONSL variants are pathogenic. Overall, our studies in humans, mice, zebrafish, and subject-derived cell lines confirm that pathogenic variants in TONSL impair DNA replication and homologous recombination-dependent repair processes, and they lead to a spectrum of skeletal dysplasia phenotypes with numerous extra-skeletal manifestations.
Keywords: Adolescent; Adult; Alleles; Animals; Cells, Cultured; Child; Child, Preschool; Chromosomal Instability; DNA Damage; Exome Sequencing; Female; Fibroblasts; Genetic Association Studies; Genetic Variation; Humans; Mice; Mice, Knockout; Musculoskeletal Abnormalities; NF-kappa B; Osteochondrodysplasias; Young Adult; Zebrafish

The comparative genomics and complex population history of baboons. - Jeffrey Rogers; Raveendran, Muthuswamy; R. Alan Harris; Mailund, Thomas; Leppälä, Kalle; Athanasiadis, Georgios; Schierup, Mikkel Heide; Cheng, Jade; Munch, Kasper; Walker, Jerilyn A; Konkel, Miriam K; Jordan, Vallmer; et al. (Sci Adv, 2019)
Recent studies suggest that closely related species can accumulate substantial genetic and phenotypic differences despite ongoing gene flow, thus challenging traditional ideas regarding the genetics of speciation. Baboons (genus ) are Old World monkeys consisting of six readily distinguishable species. Baboon species hybridize in the wild, and prior data imply a complex history of differentiation and introgression. We produced a reference genome assembly for the olive baboon () and whole-genome sequence data for all six extant species. We document multiple episodes of admixture and introgression during the radiation of baboons, thus demonstrating their value as a model of complex evolutionary divergence, hybridization, and reticulation. These results help inform our understanding of similar cases, including modern humans, Neanderthals, Denisovans, and other ancient hominins.
Keywords: Animals; Base Sequence; Biological Evolution; Female; Gene Flow; Genomics; Haplotypes; Humans; Hybridization, Genetic; Male; Papio; Phylogeny; Polymorphism, Genetic; Whole Genome Sequencing

Copy number variant and runs of homozygosity detection by microarrays enabled more precise molecular diagnoses in 11,020 clinical exome cases. - Dharmadhikari, Avinash V; Ghosh, Rajarshi; Bo Yuan; Liu, Pengfei; Dai, Hongzheng; Al Masri, Sami; Scull, Jennifer; Posey, Jennifer E; Jiang, Allen H; He, Weimin; Vetrini, Francesco; Braxton, Alicia A; et al. (Genome Med, 2019)
BACKGROUND: Exome sequencing (ES) has been successfully applied in clinical detection of single nucleotide variants (SNVs) and small indels. However, identification of copy number variants (CNVs) using ES data remains challenging. The purpose of this study is to understand the contribution of CNVs and copy neutral runs of homozygosity (ROH) in molecular diagnosis of patients referred for ES. METHODS: In a cohort of 11,020 consecutive ES patients, an Illumina SNP array analysis interrogating mostly coding SNPs was performed as a quality control (QC) measurement and for CNV/ROH detection. Among these patients, clinical chromosomal microarray analysis (CMA) was performed at Baylor Genetics (BG) on 3229 patients, either before, concurrently, or after ES. We retrospectively analyzed the findings from CMA and the QC array. RESULTS: The QC array can detect ~ 70% of pathogenic/likely pathogenic CNVs (PCNVs) detectable by CMA. Out of the 11,020 ES cases, the QC array identified PCNVs in 327 patients and uniparental disomy (UPD) disorder-related ROH in 10 patients. The overall PCNV/UPD detection rate was 5.9% in the 3229 ES patients who also had CMA at BG; PCNV/UPD detection rate was higher in concurrent ES and CMA than in ES with prior CMA (7.2% vs 4.6%). The PCNVs/UPD contributed to the molecular diagnoses in 17.4% (189/1089) of molecularly diagnosed ES cases with CMA and were estimated to contribute in 10.6% of all molecularly diagnosed ES cases. Dual diagnoses with both PCNVs and SNVs were detected in 38 patients. PCNVs affecting single recessive disorder genes in a compound heterozygous state with SNVs were detected in 4 patients, and homozygous deletions (mostly exonic deletions) were detected in 17 patients. A higher PCNV detection rate was observed for patients with syndromic phenotypes and/or cardiovascular abnormalities. CONCLUSIONS: Our clinical genomics study demonstrates that detection of PCNV/UPD through the QC array or CMA increases ES diagnostic rate, provides more precise molecular diagnosis for dominant as well as recessive traits, and enables more complete genetic diagnoses in patients with dual or multiple molecular diagnoses. Concurrent ES and CMA using an array with exonic coverage for disease genes enables most effective detection of both CNVs and SNVs and therefore is recommended especially in time-sensitive clinical situations.
Keywords: Chromosome Aberrations; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Testing; Homozygote; Humans; Limit of Detection; Male; Microarray Analysis

Correction to: De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
It was highlighted that the original article [1] contained a typographical error in the Results section. Subject 17 was incorrectly cited as Subject 1. This Correction article shows the revised statement. The original article has been updated.

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

A Diagnosis for All Rare Genetic Diseases: The Horizon and the Next Frontiers. - Boycott, Kym M; Hartley, Taila; Biesecker, Leslie G; Richard A Gibbs; Innes, A Micheil; Riess, Olaf; Belmont, John; Dunwoodie, Sally L; Jojic, Nebojsa; Lassmann, Timo; Mackay, Deborah; Temple, I Karen; et al. (Cell, 2019)
The introduction of exome sequencing in the clinic has sparked tremendous optimism for the future of rare disease diagnosis, and there is exciting opportunity to further leverage these advances. To provide diagnostic clarity to all of these patients, however, there is a critical need for the field to develop and implement strategies to understand the mechanisms underlying all rare diseases and translate these to clinical care.
Keywords: Exome; Exome Sequencing; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Rare Diseases; Sequence Analysis, DNA; Translational Research, Biomedical

Diversity and evolution of the transposable element repertoire in arthropods with particular reference to insects. - Petersen, Malte; Armisén, David; Richard A Gibbs; Hering, Lars; Khila, Abderrahman; Mayer, Georg; Richards, Stephen; Niehuis, Oliver; Misof, Bernhard (BMC Evol Biol, 2019)
BACKGROUND: Transposable elements (TEs) are a major component of metazoan genomes and are associated with a variety of mechanisms that shape genome architecture and evolution. Despite the ever-growing number of insect genomes sequenced to date, our understanding of the diversity and evolution of insect TEs remains poor. RESULTS: Here, we present a standardized characterization and an order-level comparison of arthropod TE repertoires, encompassing 62 insect and 11 outgroup species. The insect TE repertoire contains TEs of almost every class previously described, and in some cases even TEs previously reported only from vertebrates and plants. Additionally, we identified a large fraction of unclassifiable TEs. We found high variation in TE content, ranging from less than 6% in the antarctic midge (Diptera), the honey bee and the turnip sawfly (Hymenoptera) to more than 58% in the malaria mosquito (Diptera) and the migratory locust (Orthoptera), and a possible relationship between the content and diversity of TEs and the genome size. CONCLUSION: While most insect orders exhibit a characteristic TE composition, we also observed intraordinal differences, e.g., in Diptera, Hymenoptera, and Hemiptera. Our findings shed light on common patterns and reveal lineage-specific differences in content and evolution of TEs in insects. We anticipate our study to provide the basis for future comparative research on the insect TE repertoire.
Keywords: Animals; Antarctic Regions; Base Sequence; DNA Transposable Elements; Evolution, Molecular; Genetic Variation; Genome Size; Genome, Insect; Insecta; Phylogeny

Evaluation of computational genotyping of structural variation for clinical diagnoses. - Chander, Varuna; Richard A Gibbs; Fritz J Sedlazeck (Gigascience, 2019)
BACKGROUND: Structural variation (SV) plays a pivotal role in genetic disease. The discovery of SVs based on short DNA sequence reads from next-generation DNA sequence methods is error-prone, with low sensitivity and high false discovery rates. These shortcomings can be partially overcome with extensive orthogonal validation methods or use of long reads, but the current cost precludes their application for routine clinical diagnostics. In contrast, SV genotyping of known sites of SV occurrence is relatively robust and therefore offers a cost-effective clinical diagnostic tool with potentially few false-positive and false-negative results, even when applied to short-read DNA sequence data. RESULTS: We assess 5 state-of-the-art SV genotyping software methods, applied to short-read sequence data. The methods are characterized on the basis of their ability to genotype different SV types, spanning different size ranges. Furthermore, we analyze their ability to parse different VCF file subformats and assess their reliance on specific metadata. We compare the SV genotyping methods across a range of simulated and real data including SVs that were not found with Illumina data alone. We assess sensitivity and the ability to filter initial false discovery calls. We determined the impact of SV type and size on the performance for each SV genotyper. Overall, STIX performed the best on both simulated and GiaB based SV calls, demonstrating a good balance between sensitivity and specificty. CONCLUSION: Our results indicate that, although SV genotyping software methods have superior performance to SV callers, there are limitations that suggest the need for further innovation.
Keywords: Arthritis; Computer Simulation; Deafness; Genomic Structural Variation; Genotype; Humans; Polychondritis, Relapsing; Software

Exome sequencing of 457 autism families recruited online provides evidence for autism risk genes. - Feliciano, Pamela; Zhou, Xueya; Astrovskaya, Irina; Turner, Tychele N; Wang, Tianyun; Brueggeman, Leo; Barnard, Rebecca; Hsieh, Alexander; Snyder, LeeAnne Green; Donna M Muzny; Aniko Sabo; Richard A Gibbs; et al. (NPJ Genom Med, 2019)
Autism spectrum disorder (ASD) is a genetically heterogeneous condition, caused by a combination of rare de novo and inherited variants as well as common variants in at least several hundred genes. However, significantly larger sample sizes are needed to identify the complete set of genetic risk factors. We conducted a pilot study for SPARK (SPARKForAutism.org) of 457 families with ASD, all consented online. Whole exome sequencing (WES) and genotyping data were generated for each family using DNA from saliva. We identified variants in genes and loci that are clinically recognized causes or significant contributors to ASD in 10.4% of families without previous genetic findings. In addition, we identified variants that are possibly associated with ASD in an additional 3.4% of families. A meta-analysis using the TADA framework at a false discovery rate (FDR) of 0.1 provides statistical support for 26 ASD risk genes. While most of these genes are already known ASD risk genes, has the strongest statistical support and reaches genome-wide significance as a risk gene for ASD (-value = 2.3e-06). Future studies leveraging the thousands of individuals with ASD who have enrolled in SPARK are likely to further clarify the genetic risk factors associated with ASD as well as allow accelerate ASD research that incorporates genetic etiology.

Exome Sequencing of a Primary Ovarian Insufficiency Cohort Reveals Common Molecular Etiologies for a Spectrum of Disease. - Jolly, Angad; Bayram, Yavuz; Turan, Serap; Aycan, Zehra; Tos, Tulay; Abali, Zehra Yavas; Hacihamdioglu, Bulent; Coban Akdemir, Zeynep Hande; Hijazi, Hadia; Bas, Serpil; Atay, Zeynep; Guran, Tulay; et al. (J Clin Endocrinol Metab, 2019)
CONTEXT: Primary ovarian insufficiency (POI) encompasses a spectrum of premature menopause, including both primary and secondary amenorrhea. For 75% to 90% of individuals with hypergonadotropic hypogonadism presenting as POI, the molecular etiology is unknown. Common etiologies include chromosomal abnormalities, environmental factors, and congenital disorders affecting ovarian development and function, as well as syndromic and nonsyndromic single gene disorders suggesting POI represents a complex trait. OBJECTIVE: To characterize the contribution of known disease genes to POI and identify molecular etiologies and biological underpinnings of POI. DESIGN, SETTING, AND PARTICIPANTS: We applied exome sequencing (ES) and family-based genomics to 42 affected female individuals from 36 unrelated Turkish families, including 31 with reported parental consanguinity. RESULTS: This analysis identified likely damaging, potentially contributing variants and molecular diagnoses in 16 families (44%), including 11 families with likely damaging variants in known genes and five families with predicted deleterious variants in disease genes (IGSF10, MND1, MRPS22, and SOHLH1) not previously associated with POI. Of the 16 families, 2 (13%) had evidence for potentially pathogenic variants at more than one locus. Absence of heterozygosity consistent with identity-by-descent mediated recessive disease burden contributes to molecular diagnosis in 15 of 16 (94%) families. GeneMatcher allowed identification of additional families from diverse genetic backgrounds. CONCLUSIONS: ES analysis of a POI cohort further characterized locus heterogeneity, reaffirmed the association of genes integral to meiotic recombination, demonstrated the likely contribution of genes involved in hypothalamic development, and documented multilocus pathogenic variation suggesting the potential for oligogenic inheritance contributing to the development of POI.
Keywords: Cell Cycle Proteins; Cohort Studies; DNA Helicases; DNA-Binding Proteins; Exome Sequencing; Female; Gene Frequency; Humans; Hypogonadism; Immunoglobulins; Minichromosome Maintenance Proteins; Primary Ovarian Insufficiency

Functionally oriented analysis of cardiometabolic traits in a trans-ethnic sample. - Petty, Lauren E; Highland, Heather M; Gamazon, Eric R; Hu, Hao; Karhade, Mandar; Chen, Hung-Hsin; de Vries, Paul S; Grove, Megan L; Aguilar, David; Bell, Graeme I; Huff, Chad D; Hanis, Craig L; et al. (Hum Mol Genet, 2019)
Interpretation of genetic association results is difficult because signals often lack biological context. To generate hypotheses of the functional genetic etiology of complex cardiometabolic traits, we estimated the genetically determined component of gene expression from common variants using PrediXcan (1) and determined genes with differential predicted expression by trait. PrediXcan imputes tissue-specific expression levels from genetic variation using variant-level effect on gene expression in transcriptome data. To explore the value of imputed genetically regulated gene expression (GReX) models across different ancestral populations, we evaluated imputed expression levels for predictive accuracy genome-wide in RNA sequence data in samples drawn from European-ancestry and African-ancestry populations and identified substantial predictive power using European-derived models in a non-European target population. We then tested the association of GReX on 15 cardiometabolic traits including blood lipid levels, body mass index, height, blood pressure, fasting glucose and insulin, RR interval, fibrinogen level, factor VII level and white blood cell and platelet counts in 15 755 individuals across three ancestry groups, resulting in 20 novel gene-phenotype associations reaching experiment-wide significance across ancestries. In addition, we identified 18 significant novel gene-phenotype associations in our ancestry-specific analyses. Top associations were assessed for additional support via query of S-PrediXcan (2) results derived from publicly available genome-wide association studies summary data. Collectively, these findings illustrate the utility of transcriptome-based imputation models for discovery of cardiometabolic effect genes in a diverse dataset.
Keywords: Adult; Aged; Blood Pressure; Body Mass Index; Chromosome Mapping; Ethnicity; Female; Forecasting; Genetic Association Studies; Genome-Wide Association Study; Humans; Male; Metabolome; Middle Aged; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide; Transcriptome; White People

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.
Keywords: Animals; Body Patterning; Embryonic Development; Exome Sequencing; Female; Genetic Association Studies; Genome, Human; Genomics; GTP Phosphohydrolases; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Male; Peroxidases; Zebrafish; Zebrafish Proteins

A Genocentric Approach to Discovery of Mendelian Disorders. - Hansen, Adam W; Mullai Murugan; Li, He; Khayat, Michael M; Wang, Liwen; Rosenfeld, Jill; B. Kim Andrews; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Fritz J Sedlazeck; Ashley-Koch, Allison E; Liu, Pengfei; et al. (Am J Hum Genet, 2019)
The advent of inexpensive, clinical exome sequencing (ES) has led to the accumulation of genetic data from thousands of samples from individuals affected with a wide range of diseases, but for whom the underlying genetic and molecular etiology of their clinical phenotype remains unknown. In many cases, detailed phenotypes are unavailable or poorly recorded and there is little family history to guide study. To accelerate discovery, we integrated ES data from 18,696 individuals referred for suspected Mendelian disease, together with relatives, in an Apache Hadoop data lake (Hadoop Architecture Lake of Exomes [HARLEE]) and implemented a genocentric analysis that rapidly identified 154 genes harboring variants suspected to cause Mendelian disorders. The approach did not rely on case-specific phenotypic classifications but was driven by optimization of gene- and variant-level filter parameters utilizing historical Mendelian disease-gene association discovery data. Variants in 19 of the 154 candidate genes were subsequently reported as causative of a Mendelian trait and additional data support the association of all other candidate genes with disease endpoints.
Keywords: Databases, Genetic; Exome; Exome Sequencing; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Variation; Genomics; Humans; Pedigree; Phenotype

The Genomics of Arthrogryposis, a Complex Trait: Candidate Genes and Further Evidence for Oligogenic Inheritance. - Pehlivan, Davut; Bayram, Yavuz; Gunes, Nilay; Coban Akdemir, Zeynep; Shukla, Anju; Bierhals, Tatjana; Tabakci, Burcu; Sahin, Yavuz; Gezdirici, Alper; Fatih, Jawid M; Gulec, Elif Yilmaz; Yesil, Gozde; et al. (Am J Hum Genet, 2019)
Arthrogryposis is a clinical finding that is present either as a feature of a neuromuscular condition or as part of a systemic disease in over 400 Mendelian conditions. The underlying molecular etiology remains largely unknown because of genetic and phenotypic heterogeneity. We applied exome sequencing (ES) in a cohort of 89 families with the clinical sign of arthrogryposis. Additional molecular techniques including array comparative genomic hybridization (aCGH) and Droplet Digital PCR (ddPCR) were performed on individuals who were found to have pathogenic copy number variants (CNVs) and mosaicism, respectively. A molecular diagnosis was established in 65.2% (58/89) of families. Eleven out of 58 families (19.0%) showed evidence for potential involvement of pathogenic variation at more than one locus, probably driven by absence of heterozygosity (AOH) burden due to identity-by-descent (IBD). RYR3, MYOM2, ERGIC1, SPTBN4, and ABCA7 represent genes, identified in two or more families, for which mutations are probably causative for arthrogryposis. We also provide evidence for the involvement of CNVs in the etiology of arthrogryposis and for the idea that both mono-allelic and bi-allelic variants in the same gene cause either similar or distinct syndromes. We were able to identify the molecular etiology in nine out of 20 families who underwent reanalysis. In summary, our data from family-based ES further delineate the molecular etiology of arthrogryposis, yielded several candidate disease-associated genes, and provide evidence for mutational burden in a biological pathway or network. Our study also highlights the importance of reanalysis of individuals with unsolved diagnoses in conjunction with sequencing extended family members.
Keywords: Adolescent; Adult; Arthrogryposis; Child; Child, Preschool; Cohort Studies; Connectin; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Markers; Genomics; Gestational Age; Humans; Infant; Infant, Newborn; Male; Mosaicism; Multifactorial Inheritance; Mutation; Pedigree; Ryanodine Receptor Calcium Release Channel; Vesicular Transport Proteins; Young Adult

Identification of Polycystic Kidney Disease 1 Like 1 Gene Variants in Children With Biliary Atresia Splenic Malformation Syndrome. - Berauer, John-Paul; Mezina, Anya I; Okou, David T; Aniko Sabo; Donna M Muzny; Richard A Gibbs; Hegde, Madhuri R; Chopra, Pankaj; Cutler, David J; Perlmutter, David H; Bull, Laura N; Thompson, Richard J; et al. (Hepatology, 2019)
Biliary atresia (BA) is the most common cause of end-stage liver disease in children and the primary indication for pediatric liver transplantation, yet underlying etiologies remain unknown. Approximately 10% of infants affected by BA exhibit various laterality defects (heterotaxy) including splenic abnormalities and complex cardiac malformations-a distinctive subgroup commonly referred to as the biliary atresia splenic malformation (BASM) syndrome. We hypothesized that genetic factors linking laterality features with the etiopathogenesis of BA in BASM patients could be identified through whole-exome sequencing (WES) of an affected cohort. DNA specimens from 67 BASM subjects, including 58 patient-parent trios, from the National Institute of Diabetes and Digestive and Kidney Diseases-supported Childhood Liver Disease Research Network (ChiLDReN) underwent WES. Candidate gene variants derived from a prespecified set of 2,016 genes associated with ciliary dysgenesis and/or dysfunction or cholestasis were prioritized according to pathogenicity, population frequency, and mode of inheritance. Five BASM subjects harbored rare and potentially deleterious biallelic variants in polycystic kidney disease 1 like 1 (PKD1L1), a gene associated with ciliary calcium signaling and embryonic laterality determination in fish, mice, and humans. Heterozygous PKD1L1 variants were found in 3 additional subjects. Immunohistochemical analysis of liver from the one BASM subject available revealed decreased PKD1L1 expression in bile duct epithelium when compared to normal livers and livers affected by other noncholestatic diseases. Conclusion: WES identified biallelic and heterozygous PKD1L1 variants of interest in 8 BASM subjects from the ChiLDReN data set; the dual roles for PKD1L1 in laterality determination and ciliary function suggest that PKD1L1 is a biologically plausible, cholangiocyte-expressed candidate gene for the BASM syndrome.
Keywords: Abnormalities, Multiple; Biliary Atresia; Child; Databases, Factual; Exome Sequencing; Female; Gene Expression Regulation, Developmental; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Polycystic Kidney Diseases; Retrospective Studies; Spleen; Syndrome

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Exome Sequencing; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States

Interchromosomal template-switching as a novel molecular mechanism for imprinting perturbations associated with Temple syndrome. - Carvalho, Claudia M B; Coban-Akdemir, Zeynep; Hijazi, Hadia; Bo Yuan; Pendleton, Matthew; Harrington, Eoghan; Beaulaurier, John; Juul, Sissel; Turner, Daniel J; Kanchi, Rupa S; Jhangiani, Shalini N; Donna M Muzny; et al. (Genome Med, 2019)
BACKGROUND: Intrachromosomal triplications (TRP) can contribute to disease etiology via gene dosage effects, gene disruption, position effects, or fusion gene formation. Recently, post-zygotic de novo triplications adjacent to copy-number neutral genomic intervals with runs of homozygosity (ROH) have been shown to result in uniparental isodisomy (UPD). The genomic structure of these complex genomic rearrangements (CGRs) shows a consistent pattern of an inverted triplication flanked by duplications (DUP-TRP/INV-DUP) formed by an iterative DNA replisome template-switching mechanism during replicative repair of a single-ended, double-stranded DNA (seDNA), the ROH results from an interhomolog or nonsister chromatid template switch. It has been postulated that these CGRs may lead to genetic abnormalities in carriers due to dosage-sensitive genes mapping within the copy-number variant regions, homozygosity for alleles at a locus causing an autosomal recessive (AR) disease trait within the ROH region, or imprinting-associated diseases. METHODS: Here, we report a family wherein the affected subject carries a de novo 2.2-Mb TRP followed by 42.2 Mb of ROH and manifests clinical features overlapping with those observed in association with chromosome 14 maternal UPD (UPD(14)mat). UPD(14)mat can cause clinical phenotypic features enabling a diagnosis of Temple syndrome. This CGR was then molecularly characterized by high-density custom aCGH, genome-wide single-nucleotide polymorphism (SNP) and methylation arrays, exome sequencing (ES), and the Oxford Nanopore long-read sequencing technology. RESULTS: We confirmed the postulated DUP-TRP/INV-DUP structure by multiple orthogonal genomic technologies in the proband. The methylation status of known differentially methylated regions (DMRs) on chromosome 14 revealed that the subject shows the typical methylation pattern of UPD(14)mat. Consistent with these molecular findings, the clinical features overlap with those observed in Temple syndrome, including speech delay. CONCLUSIONS: These data provide experimental evidence that, in humans, triplication can lead to segmental UPD and imprinting disease. Importantly, genotype/phenotype analyses further reveal how a post-zygotically generated complex structural variant, resulting from a replication-based mutational mechanism, contributes to expanding the clinical phenotype of known genetic syndromes. Mechanistically, such events can distort transmission genetics resulting in homozygosity at a locus for which only one parent is a carrier as well as cause imprinting diseases.
Keywords: Chromosome Aberrations; Chromosome Disorders; Chromosomes, Human, Pair 14; DNA Methylation; DNA Replication; Genomic Imprinting; Humans; Male; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Young Adult

Leveraging Human Microbiome Features to Diagnose and Stratify Children with Irritable Bowel Syndrome. - Hollister, Emily B; Oezguen, Numan; Chumpitazi, Bruno P; Luna, Ruth Ann; Weidler, Erica M; Rubio-Gonzales, Michelle; Dahdouli, Mahmoud; Cope, Julia L; Mistretta, Toni-Ann; Raza, Sabeen; Ginger A Metcalf; Donna M Muzny; et al. (J Mol Diagn, 2019)
Accurate diagnosis and stratification of children with irritable bowel syndrome (IBS) remain challenging. Given the central role of recurrent abdominal pain in IBS, we evaluated the relationships of pediatric IBS and abdominal pain with intestinal microbes and fecal metabolites using a comprehensive clinical characterization and multiomics strategy. Using rigorous clinical phenotyping, we identified preadolescent children (aged 7 to 12 years) with Rome III IBS (n = 23) and healthy controls (n = 22) and characterized their fecal microbial communities using whole-genome shotgun metagenomics and global unbiased fecal metabolomic profiling. Correlation-based approaches and machine learning algorithms identified associations between microbes, metabolites, and abdominal pain. IBS cases differed from controls with respect to key bacterial taxa (eg, Flavonifractor plautii and Lachnospiraceae bacterium 7_1_58FAA), metagenomic functions (eg, carbohydrate metabolism and amino acid metabolism), and higher-order metabolites (eg, secondary bile acids, sterols, and steroid-like compounds). Significant associations between abdominal pain frequency and severity and intestinal microbial features were identified. A random forest classifier built on metagenomic and metabolic markers successfully distinguished IBS cases from controls (area under the curve, 0.93). Leveraging multiple lines of evidence, intestinal microbes, genes/pathways, and metabolites were associated with IBS, and these features were capable of distinguishing children with IBS from healthy children. These multi-omics features, and their links to childhood IBS coupled with nutritional interventions, may lead to new microbiome-guided diagnostic and therapeutic strategies.
Keywords: Abdominal Pain; Bacteria; Case-Control Studies; Child; Feces; Female; Gastrointestinal Tract; Genomics; Humans; Irritable Bowel Syndrome; Male; Metabolome; Microbiota; Multivariate Analysis; Principal Component Analysis; Statistics, Nonparametric

Megabase Length Hypermutation Accompanies Human Structural Variation at 17p11.2. - Beck, Christine R; Carvalho, Claudia M B; Akdemir, Zeynep C; Fritz J Sedlazeck; Song, Xiaofei; Meng, Qingchang; Jianhong Hu; Harshavardhan Doddapaneni; Chong, Zechen; Chen, Edward S; Thornton, Philip C; Liu, Pengfei; et al. (Cell, 2019)
DNA rearrangements resulting in human genome structural variants (SVs) are caused by diverse mutational mechanisms. We used long- and short-read sequencing technologies to investigate end products of de novo chromosome 17p11.2 rearrangements and query the molecular mechanisms underlying both recurrent and non-recurrent events. Evidence for an increased rate of clustered single-nucleotide variant (SNV) mutation in cis with non-recurrent rearrangements was found. Indel and SNV formation are associated with both copy-number gains and losses of 17p11.2, occur up to ∼1 Mb away from the breakpoint junctions, and favor C > G transversion substitutions; results suggest that single-stranded DNA is formed during the genesis of the SV and provide compelling support for a microhomology-mediated break-induced replication (MMBIR) mechanism for SV formation. Our data show an additional mutational burden of MMBIR consisting of hypermutation confined to the locus and manifesting as SNVs and indels predominantly within genes.
Keywords: Abnormalities, Multiple; Chromosome Breakpoints; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Repair; DNA Replication; Gene Rearrangement; Genome, Human; Genomic Structural Variation; Humans; INDEL Mutation; Models, Genetic; Mutation; Polymorphism, Single Nucleotide; Recombination, Genetic; Sequence Analysis, DNA; Smith-Magenis Syndrome

Molecular evolutionary trends and feeding ecology diversification in the Hemiptera, anchored by the milkweed bug genome. - Panfilio, Kristen A; Vargas Jentzsch, Iris M; Benoit, Joshua B; Erezyilmaz, Deniz; Suzuki, Yuichiro; Colella, Stefano; Robertson, Hugh M; Poelchau, Monica F; Waterhouse, Robert M; Ioannidis, Panagiotis; Weirauch, Matthew T; Hughes, Daniel S T; et al. (Genome Biol, 2019)
BACKGROUND: The Hemiptera (aphids, cicadas, and true bugs) are a key insect order, with high diversity for feeding ecology and excellent experimental tractability for molecular genetics. Building upon recent sequencing of hemipteran pests such as phloem-feeding aphids and blood-feeding bed bugs, we present the genome sequence and comparative analyses centered on the milkweed bug Oncopeltus fasciatus, a seed feeder of the family Lygaeidae. RESULTS: The 926-Mb Oncopeltus genome is well represented by the current assembly and official gene set. We use our genomic and RNA-seq data not only to characterize the protein-coding gene repertoire and perform isoform-specific RNAi, but also to elucidate patterns of molecular evolution and physiology. We find ongoing, lineage-specific expansion and diversification of repressive C2H2 zinc finger proteins. The discovery of intron gain and turnover specific to the Hemiptera also prompted the evaluation of lineage and genome size as predictors of gene structure evolution. Furthermore, we identify enzymatic gains and losses that correlate with feeding biology, particularly for reductions associated with derived, fluid nutrition feeding. CONCLUSIONS: With the milkweed bug, we now have a critical mass of sequenced species for a hemimetabolous insect order and close outgroup to the Holometabola, substantially improving the diversity of insect genomics. We thereby define commonalities among the Hemiptera and delve into how hemipteran genomes reflect distinct feeding ecologies. Given Oncopeltus's strength as an experimental model, these new sequence resources bolster the foundation for molecular research and highlight technical considerations for the analysis of medium-sized invertebrate genomes.
Keywords: Amino Acid Sequence; Animals; CYS2-HIS2 Zinc Fingers; Evolution, Molecular; Feeding Behavior; Gene Dosage; Gene Expression Profiling; Gene Transfer, Horizontal; Genes, Homeobox; Genome, Insect; Hemiptera; Pigmentation; Smell; Transcription Factors

A novel disorder involving dyshematopoiesis, inflammation, and HLH due to aberrant CDC42 function. - Lam, Michael T; Coppola, Simona; Krumbach, Oliver H F; Prencipe, Giusi; Insalaco, Antonella; Cifaldi, Cristina; Brigida, Immacolata; Zara, Erika; Scala, Serena; Di Cesare, Silvia; Martinelli, Simone; Di Rocco, Martina; et al. (J Exp Med, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is characterized by immune dysregulation due to inadequate restraint of overactivated immune cells and is associated with a variable clinical spectrum having overlap with more common pathophysiologies. HLH is difficult to diagnose and can be part of inflammatory syndromes. Here, we identify a novel hematological/autoinflammatory condition (NOCARH syndrome) in four unrelated patients with superimposable features, including neonatal-onset cytopenia with dyshematopoiesis, autoinflammation, rash, and HLH. Patients shared the same de novo mutation (Chr1:22417990C>T, p.R186C) and altered hematopoietic compartment, immune dysregulation, and inflammation. mutations had been associated with syndromic neurodevelopmental disorders. In vitro and in vivo assays documented unique effects of p.R186C on CDC42 localization and function, correlating with the distinctiveness of the trait. Emapalumab was critical to the survival of one patient, who underwent successful bone marrow transplantation. Early recognition of the disorder and establishment of treatment followed by bone marrow transplant are important to survival.
Keywords: Alleles; Amino Acid Substitution; Animals; Binding Sites; cdc42 GTP-Binding Protein; Cell Line, Tumor; Child; Disease Susceptibility; Female; Genetic Association Studies; Genotype; Humans; Infant; Lymphohistiocytosis, Hemophagocytic; Male; Mice; Models, Molecular; Molecular Conformation; Mutation; Phenotype; Protein Binding

Paralog Studies Augment Gene Discovery: DDX and DHX Genes. - Paine, Ingrid; Posey, Jennifer E; Grochowski, Christopher M; Jhangiani, Shalini N; Rosenheck, Sarah; Kleyner, Robert; Marmorale, Taylor; Yoon, Margaret; Wang, Kai; Robison, Reid; Cappuccio, Gerarda; Pinelli, Michele; et al. (Am J Hum Genet, 2019)
Members of a paralogous gene family in which variation in one gene is known to cause disease are eight times more likely to also be associated with human disease. Recent studies have elucidated DHX30 and DDX3X as genes for which pathogenic variant alleles are involved in neurodevelopmental disorders. We hypothesized that variants in paralogous genes encoding members of the DExD/H-box RNA helicase superfamily might also underlie developmental delay and/or intellectual disability (DD and/or ID) disease phenotypes. Here we describe 15 unrelated individuals who have DD and/or ID, central nervous system (CNS) dysfunction, vertebral anomalies, and dysmorphic features and were found to have probably damaging variants in DExD/H-box RNA helicase genes. In addition, these individuals exhibit a variety of other tissue and organ system involvement including ocular, outer ear, hearing, cardiac, and kidney tissues. Five individuals with homozygous (one), compound-heterozygous (two), or de novo (two) missense variants in DHX37 were identified by exome sequencing. We identified ten total individuals with missense variants in three other DDX/DHX paralogs: DHX16 (four individuals), DDX54 (three individuals), and DHX34 (three individuals). Most identified variants are rare, predicted to be damaging, and occur at conserved amino acid residues. Taken together, these 15 individuals implicate the DExD/H-box helicases in both dominantly and recessively inherited neurodevelopmental phenotypes and highlight the potential for more than one disease mechanism underlying these disorders.
Keywords: DEAD-box RNA Helicases; Exome Sequencing; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Neoplasm Proteins; Neurodevelopmental Disorders; Pedigree; RNA Helicases

Pharmacogenomics of statin-related myopathy: Meta-analysis of rare variants from whole-exome sequencing. - Floyd, James S; Bloch, Katarzyna M; Brody, Jennifer A; Maroteau, Cyrielle; Siddiqui, Moneeza K; Gregory, Richard; Carr, Daniel F; Molokhia, Mariam; Liu, Xiaoming; Bis, Joshua C; Ahmed, Ammar; Liu, Xuan; et al. (PLoS One, 2019)
AIMS: Statin-related myopathy (SRM), which includes rhabdomyolysis, is an uncommon but important adverse drug reaction because the number of people prescribed statins world-wide is large. Previous association studies of common genetic variants have had limited success in identifying a genetic basis for this adverse drug reaction. We conducted a multi-site whole-exome sequencing study to investigate whether rare coding variants confer an increased risk of SRM. METHODS AND RESULTS: SRM 3-5 cases (N = 505) and statin treatment-tolerant controls (N = 2047) were recruited from multiple sites in North America and Europe. SRM 3-5 was defined as symptoms consistent with muscle injury and an elevated creatine phosphokinase level >4 times upper limit of normal without another likely cause of muscle injury. Whole-exome sequencing and variant calling was coordinated from two analysis centres, and results of single-variant and gene-based burden tests were meta-analysed. No genome-wide significant associations were identified. Given the large number of cases, we had 80% power to identify a variant with minor allele frequency of 0.01 that increases the risk of SRM 6-fold at genome-wide significance. CONCLUSIONS: In this large whole-exome sequencing study of severe statin-related muscle injury conducted to date, we did not find evidence that rare coding variants are responsible for this adverse drug reaction. Larger sample sizes would be required to identify rare variants with small effects, but it is unclear whether such findings would be clinically actionable.
Keywords: Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Muscle, Skeletal; Rhabdomyolysis; Whole Genome Sequencing

Prospective virome analyses in young children at increased genetic risk for type 1 diabetes. - Vehik, Kendra; Lynch, Kristian F; Wong, Matthew C; Tian, Xiangjun; Ross, Matthew C; Richard A Gibbs; Ajami, Nadim J; Petrosino, Joseph F; Rewers, Marian; Toppari, Jorma; Ziegler, Anette G; She, Jin-Xiong; et al. (Nat Med, 2019)
Viruses are implicated in autoimmune destruction of pancreatic islet β cells, which results in insulin deficiency and type 1 diabetes (T1D). Certain enteroviruses can infect β cells in vitro, have been detected in the pancreatic islets of patients with T1D and have shown an association with T1D in meta-analyses. However, establishing consistency in findings across studies has proven difficult. Obstacles to convincingly linking RNA viruses to islet autoimmunity may be attributed to rapid viral mutation rates, the cyclical periodicity of viruses and the selection of variants with altered pathogenicity and ability to spread in populations. β cells strongly express cell-surface coxsackie and adenovirus receptor (CXADR) genes, which can facilitate enterovirus infection. Studies of human pancreata and cultured islets have shown significant variation in enteroviral virulence to β cells between serotypes and within the same serotype. In this large-scale study of known eukaryotic DNA and RNA viruses in stools from children, we evaluated fecally shed viruses in relation to islet autoimmunity and T1D. This study showed that prolonged enterovirus B rather than independent, short-duration enterovirus B infections may be involved in the development of islet autoimmunity, but not T1D, in some young children. Furthermore, we found that fewer early-life human mastadenovirus C infections, as well as CXADR rs6517774, independently correlated with islet autoimmunity.
Keywords: Adolescent; Autoimmunity; Child; Child, Preschool; Diabetes Mellitus, Type 1; Enterovirus; Feces; Female; Humans; Infant; Insulin; Insulin-Secreting Cells; Islets of Langerhans; Male; Pancreas; RNA, Viral

Rare variants in SLC5A10 are associated with serum 1,5-anhydroglucitol (1,5-AG) in the Atherosclerosis Risk in Communities (ARIC) Study. - Loomis, Stephanie J; Köttgen, Anna; Li, Man; Tin, Adrienne; Coresh, Josef; Eric Boerwinkle; Richard A Gibbs; Donna M Muzny; Pankow, James; Selvin, Elizabeth; Duggal, Priya (Sci Rep, 2019)
Serum 1,5-anhydroglucitol (1,5-AG) is an emerging biomarker used to monitor glycemic control in persons with diabetes. We performed whole-exome sequencing, examining the association between rare, coding genetic variants and 1,5-AG among European ancestry (N = 6,589) and African ancestry (N = 2,309) participants without diagnosed diabetes in the Atherosclerosis Risk in Communities (ARIC) Study. Five variants representing 3 independent signals on chromosome 17 in SLC5A10, a glucose transporter not previously known to transport 1,5-AG, were associated with 1,5-AG levels up to 10.38 µg/mL lower per allele (1,5-AG range 3.4-32.8 µg/mL) in the European ancestry sample and validated in the African ancestry sample. Together these variants explained 6% of the variance in 1,5-AG. Two of these variants (rs61741107, p = 8.85E-56; rs148178887, p = 1.13E-36) were rare, nonsynonymous, and predicted to be damaging or deleterious by multiple algorithms. Gene-based SKAT-O analysis supported these results (SLC5A10 p = 5.13E-64 in European ancestry, validated in African ancestry, p = 0.006). Interestingly, these novel variants are not associated with other biomarkers of hyperglycemia or diabetes (p > 0.2). The large effect sizes and protein-altering, multiple independent signals suggest SLC5A10 may code for an important transporter of 1,5-AG in the kidney, with a potential nonglucose-related effect on 1,5-AG, impacting its clinical utility as a diabetes biomarker in this subpopulation.
Keywords: Atherosclerosis; Deoxyglucose; Exome Sequencing; Female; Humans; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Sodium-Glucose Transport Proteins

Reanalysis of Clinical Exome Sequencing Data. - Liu, Pengfei; Meng, Linyan; Normand, Elizabeth A; Xia, Fan; Song, Xiaofei; Ghazi, Andrew; Rosenfeld, Jill; Magoulas, Pilar L; Braxton, Alicia; Ward, Patricia; Dai, Hongzheng; Bo Yuan; et al. (N Engl J Med, 2019)
Keywords: Exome; Genetic Diseases, Inborn; Genetic Testing; Humans; Mutation; Phenotype; Sequence Analysis, DNA; Whole Exome Sequencing

Xia-Gibbs syndrome in adulthood: a case report with insight into the natural history of the condition. - David R Murdock; Jiang, Yunyun; Wangler, Michael; Khayat, Michael M; Aniko Sabo; Juusola, Jane; McWalter, Kirsty; Schatz, Krista Sondergaard; Gunay-Aygun, Meral; Richard A Gibbs (Cold Spring Harb Mol Case Stud, 2019)
A 55-yr-old male with severe intellectual disability, behavioral problems, kyphoscoliosis, and dysmorphic features was referred for a genetic evaluation. Chromosomal microarray, RASopathy gene panel, mitochondrial sequencing, and fragile X testing were all negative. Subsequent whole-exome sequencing revealed a heterozygous, truncating variant in the gene, consistent with a diagnosis of Xia-Gibbs syndrome (XGS). Review of his clinical history showed many classic dysmorphic and clinical features of XGS, but no major health issues in adulthood other than intellectual disability. This individual is the oldest published XGS case to date, demonstrates the wide phenotypic spectrum of the disorder, and provides information on the condition's natural history. As more adults undergo genomic studies, we will continue to learn about the adult phenotypes of genetic conditions typically diagnosed in the pediatric setting.
Keywords: Abnormalities, Multiple; Exome Sequencing; Heterozygote; Humans; Intellectual Disability; Male; Middle Aged

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Eric Boerwinkle; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Exome Sequencing; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Microfilament Proteins; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface

Challenges of Francisella classification exemplified by an atypical clinical isolate. - Matz, L M; Kamdar, K Y; Holder, M E; Ginger A Metcalf; Weissenberger, G M; Meng, Q; Vee, V; Han, Y; Donna M Muzny; Richard A Gibbs; Johnson, C L; Revell, P A; et al. (Diagn Microbiol Infect Dis, 2018)
The accumulation of sequenced Francisella strains has made it increasingly apparent that the 16S rRNA gene alone is not enough to stratify the Francisella genus into precise and clinically useful classifications. Continued whole-genome sequencing of isolates will provide a larger base of knowledge for targeted approaches with broad applicability. Additionally, examination of genomic information on a case-by-case basis will help resolve outstanding questions regarding strain stratification. We report the complete genome sequence of a clinical isolate, designated here as F. novicida-like strain TCH2015, acquired from the lymph node of a 6-year-old male. Two features were atypical for F. novicida: exhibition of functional oxidase activity and additional gene content, including proposed virulence determinants. These differences, which could potentially impact virulence and clinical diagnosis, emphasize the need for more comprehensive methods to profile Francisella isolates. This study highlights the value of whole-genome sequencing, which will lead to a more robust database of environmental and clinical genomes and inform strategies to improve detection and classification of Francisella strains.
Keywords: Child; DNA, Bacterial; Francisella; Genes, Bacterial; Genetic Variation; Genome, Bacterial; Genotype; Humans; Lymph Nodes; Male; Oxidoreductases; Sequence Analysis, DNA; Tularemia; Virulence Factors; Whole Genome Sequencing

Clinical exome sequencing for fetuses with ultrasound abnormalities and a suspected Mendelian disorder. - Normand, Elizabeth A; Braxton, Alicia; Nassef, Salma; Ward, Patricia A; Vetrini, Francesco; He, Weimin; Patel, Vipulkumar; Qu, Chunjing; Westerfield, Lauren E; Stover, Samantha; Dharmadhikari, Avinash V; Donna M Muzny; et al. (Genome Med, 2018)
BACKGROUND: Exome sequencing is now being incorporated into clinical care for pediatric and adult populations, but its integration into prenatal diagnosis has been more limited. One reason for this is the paucity of information about the clinical utility of exome sequencing in the prenatal setting. METHODS: We retrospectively reviewed indications, results, time to results (turnaround time, TAT), and impact of exome results for 146 consecutive "fetal exomes" performed in a clinical diagnostic laboratory between March 2012 and November 2017. We define a fetal exome as one performed on a sample obtained from a fetus or a product of conception with at least one structural anomaly detected by prenatal imaging or autopsy. Statistical comparisons were performed using Fisher's exact test. RESULTS: Prenatal exome yielded an overall molecular diagnostic rate of 32% (n = 46/146). Of the 46 molecular diagnoses, 50% were autosomal dominant disorders (n = 23/46), 41% were autosomal recessive disorders (n = 19/46), and 9% were X-linked disorders (n = 4/46). The molecular diagnostic rate was highest for fetuses with anomalies affecting multiple organ systems and for fetuses with craniofacial anomalies. Out of 146 cases, a prenatal trio exome option designed for ongoing pregnancies was performed on 62 fetal specimens, resulting in a diagnostic yield of 35% with an average TAT of 14 days for initial reporting (excluding tissue culture time). The molecular diagnoses led to refined recurrence risk estimates, altered medical management, and informed reproductive planning for families. CONCLUSION: Exome sequencing is a useful diagnostic tool when fetal structural anomalies suggest a genetic etiology, but other standard prenatal genetic tests did not provide a diagnosis.
Keywords: Exome Sequencing; Family; Fetus; Genetic Diseases, Inborn; Humans; Inheritance Patterns; Phenotype; Ultrasonography, Prenatal

Common Coding Variants in Are Associated With the Nav1.8 Late Current and Cardiac Conduction. - Macri, Vincenzo; Brody, Jennifer A; Arking, Dan E; Hucker, William J; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W; Sinner, Moritz F; Lubitz, Steven A; Liu, Ching-Ti; Morrison, Alanna C; Alonso, Alvaro; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Genetic variants at the / locus are strongly associated with electrocardiographic PR and QRS intervals. While is the canonical cardiac sodium channel gene, the role of in cardiac conduction is less well characterized. METHODS: We sequenced the locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21,000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. RESULTS: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium (  =0.86) with each other to be the strongest signals for PR (rs10428132, β=-4.74, =1.52×10) and QRS intervals (rs6599251, QRS β=-0.73; =1.2×10), respectively. Although these variants were not associated with or expression in human atrial tissue (n=490), they were in high linkage disequilibrium (  ≥0.72) with a common missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, =0.03, and I962V+V1073A, 22.4±0.8%, =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, =0.03). CONCLUSIONS: Our findings suggest an association between genetic variation in , the late sodium current, and alterations in cardiac conduction.
Keywords: Biophysical Phenomena; Electrocardiography; Genetic Association Studies; Haplotypes; Heart Conduction System; Humans; Ion Channel Gating; Mutation, Missense; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Comparative genomics of the miniature wasp and pest control agent Trichogramma pretiosum. - Lindsey, Amelia R I; Kelkar, Yogeshwar D; Wu, Xin; Sun, Dan; Martinson, Ellen O; Yan, Zhichao; Rugman-Jones, Paul F; Hughes, Daniel S T; Murali, Shwetha C; Qu, Jiaxin; Dugan, Shannon; Lee, Sandra L; et al. (BMC Biol, 2018)
BACKGROUND: Trichogrammatids are minute parasitoid wasps that develop within other insect eggs. They are less than half a millimeter long, smaller than some protozoans. The Trichogrammatidae are one of the earliest branching families of Chalcidoidea: a diverse superfamily of approximately half a million species of parasitoid wasps, proposed to have evolved from a miniaturized ancestor. Trichogramma are frequently used in agriculture, released as biological control agents against major moth and butterfly pests. Additionally, Trichogramma are well known for their symbiotic bacteria that induce asexual reproduction in infected females. Knowledge of the genome sequence of Trichogramma is a major step towards further understanding its biology and potential applications in pest control. RESULTS: We report the 195-Mb genome sequence of Trichogramma pretiosum and uncover signatures of miniaturization and adaptation in Trichogramma and related parasitoids. Comparative analyses reveal relatively rapid evolution of proteins involved in ribosome biogenesis and function, transcriptional regulation, and ploidy regulation. Chalcids also show loss or especially rapid evolution of 285 gene clusters conserved in other Hymenoptera, including many that are involved in signal transduction and embryonic development. Comparisons between sexual and asexual lineages of Trichogramma pretiosum reveal that there is no strong evidence for genome degradation (e.g., gene loss) in the asexual lineage, although it does contain a lower repeat content than the sexual lineage. Trichogramma shows particularly rapid genome evolution compared to other hymenopterans. We speculate these changes reflect adaptations to miniaturization, and to life as a specialized egg parasitoid. CONCLUSIONS: The genomes of Trichogramma and related parasitoids are a valuable resource for future studies of these diverse and economically important insects, including explorations of parasitoid biology, symbiosis, asexuality, biological control, and the evolution of miniaturization. Understanding the molecular determinants of parasitism can also inform mass rearing of Trichogramma and other parasitoids for biological control.
Keywords: Animals; Evolution, Molecular; Genomics; Moths; Pest Control, Biological; Phylogeny; Wasps; Whole Genome Sequencing

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

Empowering genomic medicine by establishing critical sequencing result data flows: the eMERGE example. - Aronson, Samuel; Babb, Lawrence; Ames, Darren; Richard A Gibbs; Eric Venner; Connelly, John J; Marsolo, Keith; Weng, Chunhua; Williams, Marc S; Hartzler, Andrea L; Liang, Wayne H; Ralston, James D; et al. (J Am Med Inform Assoc, 2018)
The eMERGE Network is establishing methods for electronic transmittal of patient genetic test results from laboratories to healthcare providers across organizational boundaries. We surveyed the capabilities and needs of different network participants, established a common transfer format, and implemented transfer mechanisms based on this format. The interfaces we created are examples of the connectivity that must be instantiated before electronic genetic and genomic clinical decision support can be effectively built at the point of care. This work serves as a case example for both standards bodies and other organizations working to build the infrastructure required to provide better electronic clinical decision support for clinicians.
Keywords: Computer Communication Networks; Electronic Health Records; Genetic Testing; Genome, Human; Genomics; Humans; Information Dissemination; Sequence Analysis, DNA; United States

Genetic and mechanistic diversity in pediatric hemophagocytic lymphohistiocytosis. - Chinn, Ivan K; Eckstein, Olive S; Peckham-Gregory, Erin C; Goldberg, Baruch R; Forbes, Lisa R; Nicholas, Sarah K; Mace, Emily M; Vogel, Tiphanie P; Abhyankar, Harshal A; Diaz, Maria I; Heslop, Helen E; Krance, Robert A; et al. (Blood, 2018)
The HLH-2004 criteria are used to diagnose hemophagocytic lymphohistiocytosis (HLH), yet concern exists for their misapplication, resulting in suboptimal treatment of some patients. We sought to define the genomic spectrum and associated outcomes of a diverse cohort of children who met the HLH-2004 criteria. Genetic testing was performed clinically or through research-based whole-exome sequencing. Clinical metrics were analyzed with respect to genomic results. Of 122 subjects enrolled over the course of 17 years, 101 subjects received genetic testing. Biallelic familial HLH (fHLH) gene defects were identified in only 19 (19%) and correlated with presentation at younger than 1 year of age ( < .0001). Digenic fHLH variants were observed but lacked statistical support for disease association. In 28 (58%) of 48 subjects, research whole-exome sequencing analyses successfully identified likely molecular explanations, including underlying primary immunodeficiency diseases, dysregulated immune activation and proliferation disorders, and potentially novel genetic conditions. Two-thirds of patients identified by the HLH-2004 criteria had underlying etiologies for HLH, including genetic defects, autoimmunity, and malignancy. Overall survival was 45%, and increased mortality correlated with HLH triggered by infection or malignancy ( < .05). Differences in survival did not correlate with genetic profile or extent of therapy. HLH should be conceptualized as a phenotype of critical illness characterized by toxic activation of immune cells from different underlying mechanisms. In most patients with HLH, targeted sequencing of fHLH genes remains insufficient for identifying pathogenic mechanisms. Whole-exome sequencing, however, may identify specific therapeutic opportunities and affect hematopoietic stem cell transplantation options for these patients.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Genetic Testing; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Lymphohistiocytosis, Hemophagocytic; Male; Multifactorial Inheritance

The genome of the water strider Gerris buenoi reveals expansions of gene repertoires associated with adaptations to life on the water. - Armisén, David; Rajakumar, Rajendhran; Friedrich, Markus; Benoit, Joshua B; Robertson, Hugh M; Panfilio, Kristen A; Ahn, Seung-Joon; Poelchau, Monica F; Chao, Hsu; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; et al. (BMC Genomics, 2018)
BACKGROUND: Having conquered water surfaces worldwide, the semi-aquatic bugs occupy ponds, streams, lakes, mangroves, and even open oceans. The diversity of this group has inspired a range of scientific studies from ecology and evolution to developmental genetics and hydrodynamics of fluid locomotion. However, the lack of a representative water strider genome hinders our ability to more thoroughly investigate the molecular mechanisms underlying the processes of adaptation and diversification within this group. RESULTS: Here we report the sequencing and manual annotation of the Gerris buenoi (G. buenoi) genome; the first water strider genome to be sequenced thus far. The size of the G. buenoi genome is approximately 1,000 Mb, and this sequencing effort has recovered 20,949 predicted protein-coding genes. Manual annotation uncovered a number of local (tandem and proximal) gene duplications and expansions of gene families known for their importance in a variety of processes associated with morphological and physiological adaptations to a water surface lifestyle. These expansions may affect key processes associated with growth, vision, desiccation resistance, detoxification, olfaction and epigenetic regulation. Strikingly, the G. buenoi genome contains three insulin receptors, suggesting key changes in the rewiring and function of the insulin pathway. Other genomic changes affecting with opsin genes may be associated with wavelength sensitivity shifts in opsins, which is likely to be key in facilitating specific adaptations in vision for diverse water habitats. CONCLUSIONS: Our findings suggest that local gene duplications might have played an important role during the evolution of water striders. Along with these findings, the sequencing of the G. buenoi genome now provides us the opportunity to pursue exciting research opportunities to further understand the genomic underpinnings of traits associated with the extreme body plan and life history of water striders.
Keywords: Adaptation, Physiological; Animals; Evolution, Molecular; Genome; Genomics; Heteroptera; Insect Proteins; Phenotype; Phylogeny

Hemimetabolous genomes reveal molecular basis of termite eusociality. - Harrison, Mark C; Jongepier, Evelien; Robertson, Hugh M; Arning, Nicolas; Bitard-Feildel, Tristan; Chao, Hsu; Childers, Christopher P; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; Gowin, Johannes; Greiner, Carolin; et al. (Nat Ecol Evol, 2018)
Around 150 million years ago, eusocial termites evolved from within the cockroaches, 50 million years before eusocial Hymenoptera, such as bees and ants, appeared. Here, we report the 2-Gb genome of the German cockroach, Blattella germanica, and the 1.3-Gb genome of the drywood termite Cryptotermes secundus. We show evolutionary signatures of termite eusociality by comparing the genomes and transcriptomes of three termites and the cockroach against the background of 16 other eusocial and non-eusocial insects. Dramatic adaptive changes in genes underlying the production and perception of pheromones confirm the importance of chemical communication in the termites. These are accompanied by major changes in gene regulation and the molecular evolution of caste determination. Many of these results parallel molecular mechanisms of eusocial evolution in Hymenoptera. However, the specific solutions are remarkably different, thus revealing a striking case of convergence in one of the major evolutionary transitions in biological complexity.
Keywords: Animals; Biological Evolution; Blattellidae; Evolution, Molecular; Genome; Isoptera; Phylogeny; Social Behavior

Heterozygous Truncating Variants in POMP Escape Nonsense-Mediated Decay and Cause a Unique Immune Dysregulatory Syndrome. - Poli, M Cecilia; Ebstein, Frédéric; Nicholas, Sarah K; de Guzman, Marietta M; Forbes, Lisa R; Chinn, Ivan K; Mace, Emily M; Vogel, Tiphanie P; Carisey, Alexandre F; Benavides, Felipe; Coban-Akdemir, Zeynep H; Richard A Gibbs; et al. (Am J Hum Genet, 2018)
The proteasome processes proteins to facilitate immune recognition and host defense. When inherently defective, it can lead to aberrant immunity resulting in a dysregulated response that can cause autoimmunity and/or autoinflammation. Biallelic or digenic loss-of-function variants in some of the proteasome subunits have been described as causing a primary immunodeficiency disease that manifests as a severe dysregulatory syndrome: chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE). Proteasome maturation protein (POMP) is a chaperone for proteasome assembly and is critical for the incorporation of catalytic subunits into the proteasome. Here, we characterize and describe POMP-related autoinflammation and immune dysregulation disease (PRAID) discovered in two unrelated individuals with a unique constellation of early-onset combined immunodeficiency, inflammatory neutrophilic dermatosis, and autoimmunity. We also begin to delineate a complex genetic mechanism whereby de novo heterozygous frameshift variants in the penultimate exon of POMP escape nonsense-mediated mRNA decay (NMD) and result in a truncated protein that perturbs proteasome assembly by a dominant-negative mechanism. To our knowledge, this mechanism has not been reported in any primary immunodeficiencies, autoinflammatory syndromes, or autoimmune diseases. Here, we define a unique hypo- and hyper-immune phenotype and report an immune dysregulation syndrome caused by frameshift mutations that escape NMD.
Keywords: Base Sequence; Cell Line; Endoplasmic Reticulum Stress; Exons; Family; Frameshift Mutation; Genetic Predisposition to Disease; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Infant, Newborn; Inflammation; Interferon Type I; Male; Molecular Chaperones; Mutant Proteins; Mutation; Nonsense Mediated mRNA Decay; Phenotype; Proteasome Endopeptidase Complex; RNA, Messenger; Syndrome; Unfolded Protein Response

Identification of a pathogenic PMP2 variant in a multi-generational family with CMT type 1: Clinical gene panels versus genome-wide approaches to molecular diagnosis. - Punetha, Jaya; Mackay-Loder, Loren; Harel, Tamar; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Richard A Gibbs; Lee, Ian; Terespolsky, Deborah; Lupski, James R; Posey, Jennifer E (Mol Genet Metab, 2018)
Charcot-Marie-Tooth (CMT) disease type 1 is an inherited peripheral neuropathy characterized by demyelination and reduced nerve conduction velocities. We present a multi-generational family with peripheral neuropathy in whom clinical CMT panel testing failed to conclude a molecular diagnosis. We found a PMP2 pathogenic variant c.155T > C, p.(Ile52Thr) that segregates with disease suggesting that PMP2 variants should be considered in patients with neuropathy and that it may be prudent to include in clinical CMT gene panels.
Keywords: Charcot-Marie-Tooth Disease; Demyelinating Diseases; Humans; Mutation; Myelin P2 Protein; Neural Conduction; Pathology, Molecular; Peripheral Nervous System Diseases

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Petty, Lauren E; Donna M Muzny; Below, Jennifer E; Eric Boerwinkle; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Kalinin; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Identifying Genes Whose Mutant Transcripts Cause Dominant Disease Traits by Potential Gain-of-Function Alleles. - Coban-Akdemir, Zeynep; White, Janson J; Song, Xiaofei; Jhangiani, Shalini N; Fatih, Jawid M; Gambin, Tomasz; Bayram, Yavuz; Chinn, Ivan K; Karaca, Ender; Punetha, Jaya; Poli, Cecilia; Eric Boerwinkle; et al. (Am J Hum Genet, 2018)
Premature termination codon (PTC)-bearing transcripts are often degraded by nonsense-mediated decay (NMD) resulting in loss-of-function (LoF) alleles. However, not all PTCs result in LoF mutations, i.e., some such transcripts escape NMD and are translated to truncated peptide products that result in disease due to gain-of-function (GoF) effects. Since the location of the PTC is a major factor determining transcript fate, we hypothesized that depletion of protein-truncating variants (PTVs) within the gene region predicted to escape NMD in control databases could provide a rank for genic susceptibility for disease through GoF versus LoF. We developed an NMD escape intolerance score to rank genes based on the depletion of PTVs that would render them able to escape NMD using the Atherosclerosis Risk in Communities Study (ARIC) and the Exome Aggregation Consortium (ExAC) control databases, which was further used to screen the Baylor-Center for Mendelian Genomics disease database. This analysis revealed 1,996 genes significantly depleted for PTVs that are predicted to escape from NMD, i.e., PTVesc; further studies provided evidence that revealed a subset as candidate genes underlying Mendelian phenotypes. Importantly, these genes have characteristically low pLI scores, which can cause them to be overlooked as candidates for dominant diseases. Collectively, we demonstrate that this NMD escape intolerance score is an effective and efficient tool for gene discovery in Mendelian diseases due to production of truncated or altered proteins. More importantly, we provide a complementary analytical tool to aid identification of genes associated with dominant traits through a mechanism distinct from LoF.
Keywords: Alleles; Codon, Nonsense; Databases, Genetic; Exome; Gain of Function Mutation; Humans; Mutation; Nonsense Mediated mRNA Decay; Phenotype

MLH1-rheMac hereditary nonpolyposis colorectal cancer syndrome in rhesus macaques. - Brammer, David W; Gillespie, Patrick J; Tian, Mei; Young, Daniel; Raveendran, Muthuswamy; Williams, Lawrence E; Gagea, Mihai; Benavides, Fernando J; Perez, Carlos J; Broaddus, Russell R; Bernacky, Bruce J; Barnhart, Kirstin F; et al. (Proc Natl Acad Sci U S A, 2018)
Over the past two decades, 33 cases of colonic adenocarcinomas have been diagnosed in rhesus macaques () at the nonhuman primate colony of the Keeling Center for Comparative Medicine and Research at The University of Texas MD Anderson Cancer Center. The distinctive feature in these cases, based on PET/computed tomography (CT) imaging, was the presence of two or three tumor lesions in different locations, including proximal to the ileocecal juncture, proximal to the hepatic flexure, and/or in the sigmoid colon. These colon carcinoma lesions selectively accumulated [F]fluorodeoxyglucose ([F]FDG) and [F]fluoroacetate ([F]FACE) at high levels, reflecting elevated carbohydrate and fatty acid metabolism in these tumors. In contrast, the accumulation of [F]fluorothymidine ([F]FLT) was less significant, reflecting slow proliferative activity in these tumors. The diagnoses of colon carcinomas were confirmed by endoscopy. The expression of MLH1, MSH2, and MSH6 proteins and the degree of microsatellite instability (MSI) was assessed in colon carcinomas. The loss of MLH1 protein expression was observed in all tumors and was associated with a deletion mutation in the promoter region and/or multiple single-nucleotide polymorphism (SNP) mutations in the gene. All tumors exhibited various degrees of MSI. The pedigree analysis of this rhesus macaque population revealed several clusters of affected animals related to each other over several generations, suggesting an autosomal dominant transmission of susceptibility for colon cancer. The newly discovered hereditary nonpolyposis colorectal cancer syndrome in rhesus macaques, termed -rheMac, may serve as a model for development of novel approaches to diagnosis and therapy of Lynch syndrome in humans.
Keywords: Animals; Colorectal Neoplasms, Hereditary Nonpolyposis; Female; Macaca mulatta; Male; Microsatellite Instability; MutL Protein Homolog 1; Polymorphism, Single Nucleotide; Positron Emission Tomography Computed Tomography; Primate Diseases

Mutations in PI3K110δ cause impaired natural killer cell function partially rescued by rapamycin treatment. - Ruiz-García, Raquel; Vargas-Hernandez, Alexander; Chinn, Ivan K; Angelo, Laura S; Cao, Tram N; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Meng, Qingchang; Forbes, Lisa R; Donna M Muzny; Allende, Luis M; Ehlayel, Mohammed S; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Heterozygous gain-of-function mutations in PI3K110δ lead to lymphadenopathy, lymphoid hyperplasia, EBV and cytomegalovirus viremia, and sinopulmonary infections. OBJECTIVE: The known role of natural killer (NK) cell function in the control of EBV and cytomegalovirus prompted us to investigate the functional and phenotypic effects of PI3K110δ mutations on NK cell subsets and cytotoxic function. METHODS: Mutations in patients were identified by using whole-exome or targeted sequencing. We performed NK cell phenotyping and functional analysis of patients' cells using flow cytometry, standard Cr cytotoxicity assays, and quantitative confocal microscopy. RESULTS: PI3K110δ mutations led to an altered NK cell developmental phenotype and cytotoxic dysfunction. Impaired NK cell cytotoxicity was due to decreased conjugate formation with susceptible target cells and abrogated activation of cell machinery required for target cell killing. These defects were restored partially after initiation of treatment with rapamycin in 3 patients. CONCLUSION: We describe novel NK cell functional deficiency caused by PI3K110δ mutation, which is a likely contributor to the severe viremia observed in these patients. Rapamycin treatment partially restores NK cell function, providing a further rationale for its use in patients with this disease.
Keywords: Cell Differentiation; Cells, Cultured; Class I Phosphatidylinositol 3-Kinases; Cytomegalovirus; Cytomegalovirus Infections; Cytotoxicity, Immunologic; Epstein-Barr Virus Infections; Exome Sequencing; Herpesvirus 4, Human; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunological Synapses; Immunophenotyping; Killer Cells, Natural; Lymphocyte Activation; Microscopy, Confocal; Mutation; Phosphatidylinositol 3-Kinases; Sirolimus; Viremia

Phenotypic expansion illuminates multilocus pathogenic variation. - Karaca, Ender; Posey, Jennifer E; Coban Akdemir, Zeynep; Pehlivan, Davut; Harel, Tamar; Jhangiani, Shalini N; Bayram, Yavuz; Song, Xiaofei; Bahrambeigi, Vahid; Yuregir, Ozge Ozalp; Bozdogan, Sevcan; Yesil, Gozde; et al. (Genet Med, 2018)
PURPOSE: Multilocus variation-pathogenic variants in two or more disease genes-can potentially explain the underlying genetic basis for apparent phenotypic expansion in cases for which the observed clinical features extend beyond those reported in association with a "known" disease gene. METHODS: Analyses focused on 106 patients, 19 for whom apparent phenotypic expansion was previously attributed to variation at known disease genes. We performed a retrospective computational reanalysis of whole-exome sequencing data using stringent Variant Call File filtering criteria to determine whether molecular diagnoses involving additional disease loci might explain the observed expanded phenotypes. RESULTS: Multilocus variation was identified in 31.6% (6/19) of families with phenotypic expansion and 2.3% (2/87) without phenotypic expansion. Intrafamilial clinical variability within two families was explained by multilocus variation identified in the more severely affected sibling. CONCLUSION: Our findings underscore the role of multiple rare variants at different loci in the etiology of genetically and clinically heterogeneous cohorts. Intrafamilial phenotypic and genotypic variability allowed a dissection of genotype-phenotype relationships in two families. Our data emphasize the critical role of the clinician in diagnostic genomic analyses and demonstrate that apparent phenotypic expansion may represent blended phenotypes resulting from pathogenic variation at more than one locus.
Keywords: Child, Preschool; Exome; Exome Sequencing; Female; Genetic Association Studies; Genetic Diseases, Inborn; Genetic Variation; Genotype; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Male; Mutation; Pathology, Molecular; Pedigree; Phenotype

Phenotypic expansion in - a common cause of intellectual disability in females. - Wang, Xia; Posey, Jennifer E; Rosenfeld, Jill A; Bacino, Carlos A; Scaglia, Fernando; Immken, Ladonna; Harris, Jill M; Hickey, Scott E; Mosher, Theresa M; Slavotinek, Anne; Zhang, Jing; Beuten, Joke; et al. (Ann Clin Transl Neurol, 2018)
De variants in account for 1-3% of unexplained intellectual disability (ID) cases and are amongst the most common causes of ID especially in females. Forty-seven patients (44 females, 3 males) have been described. We identified 31 additional individuals carrying 29 unique variants, including 30 postnatal individuals with complex clinical presentations of developmental delay or ID, and one fetus with abnormal ultrasound findings. Rare or novel phenotypes observed include respiratory problems, congenital heart disease, skeletal muscle mitochondrial DNA depletion, and late-onset neurologic decline. Our findings expand the spectrum of DNA variants and phenotypes associated with disorders.

The phenotypic spectrum of Xia-Gibbs syndrome. - Jiang, Yunyun; Wangler, Michael F; McGuire, Amy L; Lupski, James R; Posey, Jennifer E; Khayat, Michael M; Murdock, David R; Sanchez-Pulido, Luis; Ponting, Chris P; Xia, Fan; Hunter, Jill V; Meng, Qingchang; et al. (Am J Med Genet A, 2018)
Xia-Gibbs syndrome (XGS: OMIM # 615829) results from de novo truncating mutations within the AT-Hook DNA Binding Motif Containing 1 gene (AHDC1). To further define the phenotypic and molecular spectrum of this disorder, we established an XGS Registry and recruited patients from a worldwide pool of approximately 60 probands. Additional de novo truncating mutations were observed among 25 individuals, extending both the known number of mutation sites and the range of positions within the coding region that were sensitive to alteration. Detailed phenotypic examination of 20 of these patients via clinical records review and data collection from additional surveys showed a wider age range than previously described. Data from developmental milestones showed evidence for delayed speech and that males were more severely affected. Neuroimaging from six available patients showed an associated thinning of the corpus callosum and posterior fossa cysts. An increased risk of both scoliosis and seizures relative to the population burden was also observed. Data from a modified autism screening tool revealed that XGS shares significant overlap with autism spectrum disorders. These details of the phenotypic heterogeneity of XGS implicate specific genotype/phenotype correlations and suggest potential clinical management guidelines.
Keywords: Autism Spectrum Disorder; Child; Cognition; Corpus Callosum; Developmental Disabilities; DNA-Binding Proteins; Face; Female; Humans; Male; Mutation; Pedigree; Phenotype; Registries; Seizures; Syndrome; Young Adult

Reproductive Longevity Predicts Mutation Rates in Primates. - Thomas, Gregg W C; Wang, Richard J; Puri, Arthi; R. Alan Harris; Raveendran, Muthuswamy; Hughes, Daniel S T; Murali, Shwetha C; Williams, Lawrence E; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Abee, Christian R; et al. (Curr Biol, 2018)
Mutation rates vary between species across several orders of magnitude, with larger organisms having the highest per-generation mutation rates. Hypotheses for this pattern typically invoke physiological or population-genetic constraints imposed on the molecular machinery preventing mutations [1]. However, continuing germline cell division in multicellular eukaryotes means that organisms with longer generation times and of larger size will leave more mutations to their offspring simply as a byproduct of their increased lifespan [2, 3]. Here, we deeply sequence the genomes of 30 owl monkeys (Aotus nancymaae) from six multi-generation pedigrees to demonstrate that paternal age is the major factor determining the number of de novo mutations in this species. We find that owl monkeys have an average mutation rate of 0.81 × 10 per site per generation, roughly 32% lower than the estimate in humans. Based on a simple model of reproductive longevity that does not require any changes to the mutational machinery, we show that this is the expected mutation rate in owl monkeys. We further demonstrate that our model predicts species-specific mutation rates in other primates, including study-specific mutation rates in humans based on the average paternal age. Our results suggest that variation in life history traits alone can explain variation in the per-generation mutation rate among primates, and perhaps among a wide range of multicellular organisms.
Keywords: Animals; Aotidae; Genetic Fitness; Genetics, Population; Genome; Humans; Longevity; Mutation; Mutation Rate; Pedigree; Population Density; Primates; Reproduction

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

Sequence-Based Analysis of Lipid-Related Metabolites in a Multiethnic Study. - Feofanova, Elena V; Yu, Bing; Ginger A Metcalf; Liu, Xiaoming; Donna M Muzny; Below, Jennifer E; Wagenknecht, Lynne E; Richard A Gibbs; Morrison, Alanna C; Eric Boerwinkle (Genetics, 2018)
Small molecule lipid-related metabolites are important components of fatty acid and steroid metabolism-two important contributors to human health. This study investigated the extent to which rare and common genetic variants spanning the human genome influence the lipid-related metabolome. Sequence data from 1552 European-Americans (EA) and 1872 African-Americans (AA) were analyzed to examine the impact of common and rare variants on the levels of 102 circulating lipid-related metabolites measured by a combination of chromatography and mass spectroscopy. We conducted single variant tests [minor allele frequency (MAF) > 5%, statistical significance -value ≤ 2.45 × 10] and tests aggregating rare variants (MAF ≤ 5%) across multiple genomic motifs, such as coding regions and regulatory domains, and sliding windows. Multiethnic meta-analyses detected 53 lipid-related metabolites-locus pairs, which were inspected for evidence of consistent signal between the two ethnic groups. Thirty-eight lipid-related metabolite-genomic region associations were consistent across ethnicities, among which seven were novel. The regions contain genes that are related to metabolite transport () and metabolism (, , , and ). Six of the seven novel findings lie in expression quantitative trait loci affecting the expression levels of 14 surrounding genes in multiple tissues. Imputed expression levels of 10 of the affected genes were associated with four corresponding lipid-related traits in at least one tissue. Our findings offer valuable insight into circulating lipid-related metabolite regulation in a multiethnic population.
Keywords: Black or African American; Female; Humans; Lipid Metabolism; Male; Metabolome; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; White People

Sheep genome functional annotation reveals proximal regulatory elements contributed to the evolution of modern breeds. - Naval-Sanchez, Marina; Nguyen, Quan; McWilliam, Sean; Porto-Neto, Laercio R; Tellam, Ross; Vuocolo, Tony; Reverter, Antonio; Perez-Enciso, Miguel; Brauning, Rudiger; Clarke, Shannon; McCulloch, Alan; Zamani, Wahid; et al. (Nat Commun, 2018)
Domestication fundamentally reshaped animal morphology, physiology and behaviour, offering the opportunity to investigate the molecular processes driving evolutionary change. Here we assess sheep domestication and artificial selection by comparing genome sequence from 43 modern breeds (Ovis aries) and their Asian mouflon ancestor (O. orientalis) to identify selection sweeps. Next, we provide a comparative functional annotation of the sheep genome, validated using experimental ChIP-Seq of sheep tissue. Using these annotations, we evaluate the impact of selection and domestication on regulatory sequences and find that sweeps are significantly enriched for protein coding genes, proximal regulatory elements of genes and genome features associated with active transcription. Finally, we find individual sites displaying strong allele frequency divergence are enriched for the same regulatory features. Our data demonstrate that remodelling of gene expression is likely to have been one of the evolutionary forces that drove phenotypic diversification of this common livestock species.
Keywords: Animals; Breeding; Evolution, Molecular; Female; Gene Frequency; Genome; Male; Molecular Sequence Annotation; Phylogeny; Regulatory Elements, Transcriptional; Sheep

Sooty mangabey genome sequence provides insight into AIDS resistance in a natural SIV host. - Palesch, David; Bosinger, Steven E; Tharp, Gregory K; Vanderford, Thomas H; Paiardini, Mirko; Chahroudi, Ann; Johnson, Zachary P; Kirchhoff, Frank; Hahn, Beatrice H; Norgren, Robert B; Patel, Nirav B; Sodora, Donald L; et al. (Nature, 2018)
In contrast to infections with human immunodeficiency virus (HIV) in humans and simian immunodeficiency virus (SIV) in macaques, SIV infection of a natural host, sooty mangabeys (Cercocebus atys), is non-pathogenic despite high viraemia. Here we sequenced and assembled the genome of a captive sooty mangabey. We conducted genome-wide comparative analyses of transcript assemblies from C. atys and AIDS-susceptible species, such as humans and macaques, to identify candidates for host genetic factors that influence susceptibility. We identified several immune-related genes in the genome of C. atys that show substantial sequence divergence from macaques or humans. One of these sequence divergences, a C-terminal frameshift in the toll-like receptor-4 (TLR4) gene of C. atys, is associated with a blunted in vitro response to TLR-4 ligands. In addition, we found a major structural change in exons 3-4 of the immune-regulatory protein intercellular adhesion molecule 2 (ICAM-2); expression of this variant leads to reduced cell surface expression of ICAM-2. These data provide a resource for comparative genomic studies of HIV and/or SIV pathogenesis and may help to elucidate the mechanisms by which SIV-infected sooty mangabeys avoid AIDS.
Keywords: Acquired Immunodeficiency Syndrome; Amino Acid Sequence; Animals; Cell Adhesion Molecules; Cercocebus atys; Exons; Female; Frameshift Mutation; Genetic Predisposition to Disease; Genetic Variation; Genome; Genomics; HIV; Host Specificity; Humans; Macaca; Sequence Deletion; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Species Specificity; Toll-Like Receptor 4; Transcriptome; Whole Genome Sequencing

Syndromic congenital myelofibrosis associated with a loss-of-function variant in . - Magoulas, Pilar L; Shchelochkov, Oleg A; Bainbridge, Matthew N; Ben-Shachar, Shay; Yatsenko, Svetlana; Potocki, Lorraine; Lewis, Richard A; Searby, Charles; Marcogliese, Andrea N; Elghetany, M Tarek; Zapata, Gladys; Hernández, Paula P; et al. (Blood, 2018)
There is a Commentary on this article in this issue.
Keywords: Abnormalities, Multiple; Bone Marrow Transplantation; Child; Consanguinity; Fatal Outcome; Female; Gonadal Dysgenesis, 46,XY; Hematopoietic Stem Cell Transplantation; Humans; Infant; Intellectual Disability; Male; Pedigree; Phenotype; Primary Myelofibrosis; Syndrome; Vesicular Transport Proteins

SYT1-associated neurodevelopmental disorder: a case series. - Baker, Kate; Gordon, Sarah L; Melland, Holly; Bumbak, Fabian; Scott, Daniel J; Jiang, Tess J; Owen, David; Turner, Bradley J; Boyd, Stewart G; Rossi, Mari; Al-Raqad, Mohammed; Elpeleg, Orly; et al. (Brain, 2018)
Synaptotagmin 1 (SYT1) is a critical mediator of fast, synchronous, calcium-dependent neurotransmitter release and also modulates synaptic vesicle endocytosis. This paper describes 11 patients with de novo heterozygous missense mutations in SYT1. All mutations alter highly conserved residues, and cluster in two regions of the SYT1 C2B domain at positions Met303 (M303K), Asp304 (D304G), Asp366 (D366E), Ile368 (I368T) and Asn371 (N371K). Phenotypic features include infantile hypotonia, congenital ophthalmic abnormalities, childhood-onset hyperkinetic movement disorders, motor stereotypies, and developmental delay varying in severity from moderate to profound. Behavioural characteristics include sleep disturbance and episodic agitation. Absence of epileptic seizures and normal orbitofrontal head circumference are important negative features. Structural MRI is unremarkable but EEG disturbance is universal, characterized by intermittent low frequency high amplitude oscillations. The functional impact of these five de novo SYT1 mutations has been assessed by expressing rat SYT1 protein containing the equivalent human variants in wild-type mouse primary hippocampal cultures. All mutant forms of SYT1 were expressed at levels approximately equal to endogenous wild-type protein, and correctly localized to nerve terminals at rest, except for SYT1M303K, which was expressed at a lower level and failed to localize at nerve terminals. Following stimulation, SYT1I368T and SYT1N371K relocalized to nerve terminals at least as efficiently as wild-type SYT1. However, SYT1D304G and SYT1D366E failed to relocalize to nerve terminals following stimulation, indicative of impairments in endocytic retrieval and trafficking of SYT1. In addition, the presence of SYT1 variants at nerve terminals induced a slowing of exocytic rate following sustained action potential stimulation. The extent of disturbance to synaptic vesicle kinetics is mirrored by the severity of the affected individuals' phenotypes, suggesting that the efficiency of SYT1-mediated neurotransmitter release is critical to cognitive development. In summary, de novo dominant SYT1 missense mutations are associated with a recognizable neurodevelopmental syndrome, and further cases can now be diagnosed based on clinical features, electrophysiological signature and mutation characteristics. Variation in phenotype severity may reflect mutation-specific impact on the diverse physiological functions of SYT1.
Keywords: Action Potentials; Adolescent; Animals; Calcium; Child; Child, Preschool; Electrophysiological Phenomena; Endocytosis; Female; Humans; Intellectual Disability; Male; Mice; Mice, Inbred C57BL; Movement Disorders; Mutation, Missense; Neurodevelopmental Disorders; Neurons; Rats; Synaptic Transmission; Synaptic Vesicles; Synaptotagmin I; Young Adult

Temporal development of the gut microbiome in early childhood from the TEDDY study. - Stewart, Christopher J; Ajami, Nadim J; O'Brien, Jacqueline L; Hutchinson, Diane S; Smith, Daniel P; Wong, Matthew C; Ross, Matthew C; Lloyd, Richard E; Harshavardhan Doddapaneni; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; et al. (Nature, 2018)
The development of the microbiome from infancy to childhood is dependent on a range of factors, with microbial-immune crosstalk during this time thought to be involved in the pathobiology of later life diseases such as persistent islet autoimmunity and type 1 diabetes. However, to our knowledge, no studies have performed extensive characterization of the microbiome in early life in a large, multi-centre population. Here we analyse longitudinal stool samples from 903 children between 3 and 46 months of age by 16S rRNA gene sequencing (n = 12,005) and metagenomic sequencing (n = 10,867), as part of the The Environmental Determinants of Diabetes in the Young (TEDDY) study. We show that the developing gut microbiome undergoes three distinct phases of microbiome progression: a developmental phase (months 3-14), a transitional phase (months 15-30), and a stable phase (months 31-46). Receipt of breast milk, either exclusive or partial, was the most significant factor associated with the microbiome structure. Breastfeeding was associated with higher levels of Bifidobacterium species (B. breve and B. bifidum), and the cessation of breast milk resulted in faster maturation of the gut microbiome, as marked by the phylum Firmicutes. Birth mode was also significantly associated with the microbiome during the developmental phase, driven by higher levels of Bacteroides species (particularly B. fragilis) in infants delivered vaginally. Bacteroides was also associated with increased gut diversity and faster maturation, regardless of the birth mode. Environmental factors including geographical location and household exposures (such as siblings and furry pets) also represented important covariates. A nested case-control analysis revealed subtle associations between microbial taxonomy and the development of islet autoimmunity or type 1 diabetes. These data determine the structural and functional assembly of the microbiome in early life and provide a foundation for targeted mechanistic investigation into the consequences of microbial-immune crosstalk for long-term health.
Keywords: Adolescent; Animals; Bifidobacterium; Breast Feeding; Case-Control Studies; Child; Child, Preschool; Cluster Analysis; Datasets as Topic; Diabetes Mellitus, Type 1; Female; Firmicutes; Gastrointestinal Microbiome; Humans; Infant; Male; Milk, Human; Pets; RNA, Ribosomal, 16S; Siblings; Surveys and Questionnaires; Time Factors

The Toxicogenome of Hyalella azteca: A Model for Sediment Ecotoxicology and Evolutionary Toxicology. - Poynton, Helen C; Hasenbein, Simone; Benoit, Joshua B; Sepulveda, Maria S; Poelchau, Monica F; Hughes, Daniel S T; Murali, Shwetha C; Chen, Shuai; Glastad, Karl M; Goodisman, Michael A D; Werren, John H; Vineis, Joseph H; et al. (Environ Sci Technol, 2018)
Hyalella azteca is a cryptic species complex of epibenthic amphipods of interest to ecotoxicology and evolutionary biology. It is the primary crustacean used in North America for sediment toxicity testing and an emerging model for molecular ecotoxicology. To provide molecular resources for sediment quality assessments and evolutionary studies, we sequenced, assembled, and annotated the genome of the H. azteca U.S. Lab Strain. The genome quality and completeness is comparable with other ecotoxicological model species. Through targeted investigation and use of gene expression data sets of H. azteca exposed to pesticides, metals, and other emerging contaminants, we annotated and characterized the major gene families involved in sequestration, detoxification, oxidative stress, and toxicant response. Our results revealed gene loss related to light sensing, but a large expansion in chemoreceptors, likely underlying sensory shifts necessary in their low light habitats. Gene family expansions were also noted for cytochrome P450 genes, cuticle proteins, ion transporters, and include recent gene duplications in the metal sequestration protein, metallothionein. Mapping of differentially expressed transcripts to the genome significantly increased the ability to functionally annotate toxicant responsive genes. The H. azteca genome will greatly facilitate development of genomic tools for environmental assessments and promote an understanding of how evolution shapes toxicological pathways with implications for environmental and human health.
Keywords: Amphipoda; Animals; Ecotoxicology; Geologic Sediments; North America; Toxicity Tests; Water Pollutants, Chemical

The transcription factor POU3F2 regulates a gene coexpression network in brain tissue from patients with psychiatric disorders. - Chen, Chao; Meng, Qingtuan; Xia, Yan; Ding, Chaodong; Wang, Le; Dai, Rujia; Cheng, Lijun; Gunaratne, Preethi; Richard A Gibbs; Min, Shishi; Coarfa, Cristian; Reid, Jeffrey G; et al. (Sci Transl Med, 2018)
Schizophrenia and bipolar disorder are complex psychiatric diseases with risks contributed by multiple genes. Dysregulation of gene expression has been implicated in these disorders, but little is known about such dysregulation in the human brain. We analyzed three transcriptome datasets from 394 postmortem brain tissue samples from patients with schizophrenia or bipolar disorder or from healthy control individuals without a known history of psychiatric disease. We built genome-wide coexpression networks that included microRNAs (miRNAs). We identified a coexpression network module that was differentially expressed in the brain tissue from patients compared to healthy control individuals. This module contained genes that were principally involved in glial and neural cell genesis and glial cell differentiation, and included schizophrenia risk genes carrying rare variants. This module included five miRNAs and 545 mRNAs, with six transcription factors serving as hub genes in this module. We found that the most connected transcription factor gene , also identified on a genome-wide association study for bipolar disorder, could regulate the miRNA and other putative target mRNAs. These regulatory relationships were replicated using PsychENCODE/BrainGVEX datasets and validated by knockdown and overexpression experiments in SH-SY5Y cells and human neural progenitor cells in vitro. Thus, we identified a brain gene expression module that was enriched for rare coding variants in genes associated with schizophrenia and that contained the putative bipolar disorder risk gene The transcription factor may be a key regulator of gene expression in this disease-associated gene coexpression module.
Keywords: Brain; Cell Differentiation; Cell Proliferation; Databases, Genetic; Gene Expression Regulation; Gene Regulatory Networks; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Mental Disorders; Neural Stem Cells; Postmortem Changes; POU Domain Factors; Reproducibility of Results; RNA, Messenger

Whole-Exome Sequencing Identifies an Intronic Cryptic Splice Site in Causing Osteogenesis Imperfecta Type VI. - Jin, Zixue; Burrage, Lindsay C; Jiang, Ming-Ming; Lee, Yi-Chien; Bertin, Terry; Chen, Yuqing; Tran, Alyssa; Richard A Gibbs; Jhangiani, Shalini; Sutton, V Reid; Rauch, Frank; Lee, Brendan; et al. (JBMR Plus, 2018)
The heritable disorder osteogenesis imperfecta (OI) is characterized by bone fragility and low bone mass. OI type VI is an autosomal recessive form of the disorder with moderate to severe bone fragility. OI type VI is caused by mutations in the serpin peptidase inhibitor, clade F, member 1 (), the gene coding for pigment epithelium-derived factor (PEDF). Here, we report a patient with OI type VI caused by a novel homozygous intronic variant in identified by whole-exome sequencing (WES). The mutation was not identified using a low bone mass gene panel based on next-generation sequencing. This variant creates a novel consensus splice donor site (AGGC to AGGT) in intron 4. Analysis of cDNA generated from fibroblasts revealed retention of a 32-bp intronic fragment between exons 4 and 5 in the cDNA, a result of alternative splicing from the novel splice-donor site. As a result, the aberrant insertion of this intronic fragment generated a frameshift pathogenic variant and induced nonsense-mediated decay. Furthermore, gene expression by quantitative PCR showed expression was dramatically reduced in patient fibroblasts, and PEDF level was also significantly reduced in the patient's plasma. In conclusion, we report a novel homozygous variant that generates an alternative splice-donor in intron 4 of which gives rise to severe bone fragility. The work also demonstrates clinical utility of WES analysis, and consideration of noncoding variants, in the diagnostic setting of rare bone diseases. © 2018 The Authors. is published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.

Whole-Exome Sequencing Identifies Novel Variants for Tooth Agenesis. - Dinckan, N; Du, R; Petty, L E; Coban-Akdemir, Z; Jhangiani, S N; Paine, I; Baugh, E H; Erdem, A P; Kayserili, H; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; et al. (J Dent Res, 2018)
Tooth agenesis is a common craniofacial abnormality in humans and represents failure to develop 1 or more permanent teeth. Tooth agenesis is complex, and variations in about a dozen genes have been reported as contributing to the etiology. Here, we combined whole-exome sequencing, array-based genotyping, and linkage analysis to identify putative pathogenic variants in candidate disease genes for tooth agenesis in 10 multiplex Turkish families. Novel homozygous and heterozygous variants in LRP6, DKK1, LAMA3, and COL17A1 genes, as well as known variants in WNT10A, were identified as likely pathogenic in isolated tooth agenesis. Novel variants in KREMEN1 were identified as likely pathogenic in 2 families with suspected syndromic tooth agenesis. Variants in more than 1 gene were identified segregating with tooth agenesis in 2 families, suggesting oligogenic inheritance. Structural modeling of missense variants suggests deleterious effects to the encoded proteins. Functional analysis of an indel variant (c.3607+3_6del) in LRP6 suggested that the predicted resulting mRNA is subject to nonsense-mediated decay. Our results support a major role for WNT pathways genes in the etiology of tooth agenesis while revealing new candidate genes. Moreover, oligogenic cosegregation was suggestive for complex inheritance and potentially complex gene product interactions during development, contributing to improved understanding of the genetic etiology of familial tooth agenesis.
Keywords: Anodontia; Exome Sequencing; Female; Genetic Linkage; Genetic Variation; Humans; Intercellular Signaling Peptides and Proteins; Laminin; Low Density Lipoprotein Receptor-Related Protein-6; Male; Membrane Proteins; Mutation, Missense; Pedigree; Real-Time Polymerase Chain Reaction; Turkey; Wnt Proteins

WNT Signaling Perturbations Underlie the Genetic Heterogeneity of Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Coban-Akdemir, Zeynep; Bayram, Yavuz; Bahrambeigi, Vahid; Hoischen, Alexander; van Bon, Bregje W M; Gezdirici, Alper; Gulec, Elif Yilmaz; Ramond, Francis; Touraine, Renaud; Thevenon, Julien; et al. (Am J Hum Genet, 2018)
Locus heterogeneity characterizes a variety of skeletal dysplasias often due to interacting or overlapping signaling pathways. Robinow syndrome is a skeletal disorder historically refractory to molecular diagnosis, potentially stemming from substantial genetic heterogeneity. All current known pathogenic variants reside in genes within the noncanonical Wnt signaling pathway including ROR2, WNT5A, and more recently, DVL1 and DVL3. However, ∼70% of autosomal-dominant Robinow syndrome cases remain molecularly unsolved. To investigate this missing heritability, we recruited 21 families with at least one family member clinically diagnosed with Robinow or Robinow-like phenotypes and performed genetic and genomic studies. In total, four families with variants in FZD2 were identified as well as three individuals from two families with biallelic variants in NXN that co-segregate with the phenotype. Importantly, both FZD2 and NXN are relevant protein partners in the WNT5A interactome, supporting their role in skeletal development. In addition to confirming that clustered -1 frameshifting variants in DVL1 and DVL3 are the main contributors to dominant Robinow syndrome, we also found likely pathogenic variants in candidate genes GPC4 and RAC3, both linked to the Wnt signaling pathway. These data support an initial hypothesis that Robinow syndrome results from perturbation of the Wnt/PCP pathway, suggest specific relevant domains of the proteins involved, and reveal key contributors in this signaling cascade during human embryonic development. Contrary to the view that non-allelic genetic heterogeneity hampers gene discovery, this study demonstrates the utility of rare disease genomic studies to parse gene function in human developmental pathways.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Chromosome Segregation; Craniofacial Abnormalities; Diagnosis, Differential; Dwarfism; Female; Genes, Dominant; Genetic Association Studies; Genetic Heterogeneity; Humans; Limb Deformities, Congenital; Male; Middle Aged; Mutation, Missense; Phenotype; Urogenital Abnormalities; Wnt Signaling Pathway

Analyses of SLC13A5-epilepsy patients reveal perturbations of TCA cycle. - Bainbridge, Matthew N; Cooney, Erin; Miller, Marcus; Kennedy, Adam D; Wulff, Jacob E; Donti, Taraka; Jhangiani, Shalini N; Richard A Gibbs; Sarah H Elsea; Porter, Brenda E; Graham, Brett H (Mol Genet Metab, 2017)
OBJECTIVE: To interrogate the metabolic profile of five subjects from three families with rare, nonsense and missense mutations in SLC13A5 and Early Infantile Epileptic Encephalopathies (EIEE) characterized by severe, neonatal onset seizures, psychomotor retardation and global developmental delay. METHODS: Mass spectrometry of plasma, CSF and urine was used to identify consistently dysregulated analytes in our subjects. RESULTS: Distinctive elevations of citrate and dysregulation of citric acid cycle intermediates, supporting the hypothesis that loss of SLC13A5 function alters tricarboxylic acid cycle (TCA) metabolism and may disrupt metabolic compartmentation in the brain. SIGNIFICANCE: Our results indicate that analysis of plasma citrate and other TCA analytes in SLC13A5 deficient patients define a diagnostic metabolic signature that can aid in diagnosing children with this disease.
Keywords: Child; Citric Acid; Citric Acid Cycle; Exome Sequencing; Female; Humans; Infant, Newborn; Male; Mass Spectrometry; Metabolome; Metabolomics; Mutation; Mutation, Missense; Seizures; Spasms, Infantile; Symporters

Analysis commons, a team approach to discovery in a big-data environment for genetic epidemiology. - Brody, Jennifer A; Morrison, Alanna C; Bis, Joshua C; O'Connell, Jeffrey R; Brown, Michael R; Huffman, Jennifer E; Ames, Darren C; Carroll, Andrew; Conomos, Matthew P; Gabriel, Stacey; Richard A Gibbs; Gogarten, Stephanie M; et al. (Nat Genet, 2017)
The exploding volume of whole-genome sequence (WGS) and multi-omics data requires new approaches for analysis. As one solution, we have created a cloud-based Analysis Commons, which brings together genotype and phenotype data from multiple studies in a setting that is accessible by multiple investigators. This framework addresses many of the challenges of multi-center WGS analyses, including data sharing mechanisms, phenotype harmonization, integrated multi-omics analyses, annotation, and computational flexibility. In this setting, the computational pipeline facilitates a sequence-to-discovery analysis workflow illustrated here by an analysis of plasma fibrinogen levels in 3996 individuals from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) WGS program. The Analysis Commons represents a novel model for transforming WGS resources from a massive quantity of phenotypic and genomic data into knowledge of the determinants of health and disease risk in diverse human populations.
Keywords: big data; Fibrinogen; Genetics, Population; Genome; Humans; Information Dissemination; Mobile Applications; Molecular Epidemiology; Regression Analysis; Software; Workflow

Corner fracture type spondylometaphyseal dysplasia: Overlap with type II collagenopathies. - Machol, Keren; Jain, Mahim; Almannai, Mohammed; Orand, Thibault; Lu, James T; Tran, Alyssa; Chen, Yuqing; Schlesinger, Alan; Richard A Gibbs; Bonafe, Luisa; Campos-Xavier, Ana Belinda; Unger, Sheila; et al. (Am J Med Genet A, 2017)
Spondylometaphyseal dysplasia (SMD) corner fracture type (also known as SMD "Sutcliffe" type, MIM 184255) is a rare skeletal dysplasia that presents with mild to moderate short stature, developmental coxa vara, mild platyspondyly, corner fracture-like lesions, and metaphyseal abnormalities with sparing of the epiphyses. The molecular basis for this disorder has yet to be clarified. We describe two patients with SMD corner fracture type and heterozygous pathogenic variants in COL2A1. These two cases together with a third case of SMD corner fracture type with a heterozygous COL2A1 pathogenic variant previously described suggest that this disorder overlaps with type II collagenopathies. The finding of one of the pathogenic variants in a previously reported case of spondyloepimetaphyseal dysplasia (SEMD) Strudwick type and the significant clinical similarity suggest an overlap between SMD corner fracture and SEMD Strudwick types. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Amino Acid Substitution; Bone Diseases, Developmental; Child, Preschool; Collagen Type II; Diagnosis, Differential; Exome; Genetic Association Studies; Genotype; Growth Disorders; High-Throughput Nucleotide Sequencing; Hip Joint; Humans; Infant; Male; Mutation; Osteochondrodysplasias; Phenotype; Radiography; Tibial Fractures

Creating a data resource: what will it take to build a medical information commons? - Deverka, Patricia A; Majumder, Mary A; Villanueva, Angela G; Anderson, Margaret; Bakker, Annette C; Bardill, Jessica; Eric Boerwinkle; Bubela, Tania; Evans, Barbara J; Garrison, Nanibaa' A; Richard A Gibbs; Gentleman, Robert; et al. (Genome Med, 2017)
National and international public-private partnerships, consortia, and government initiatives are underway to collect and share genomic, personal, and healthcare data on a massive scale. Ideally, these efforts will contribute to the creation of a medical information commons (MIC), a comprehensive data resource that is widely available for both research and clinical uses. Stakeholder participation is essential in clarifying goals, deepening understanding of areas of complexity, and addressing long-standing policy concerns such as privacy and security and data ownership. This article describes eight core principles proposed by a diverse group of expert stakeholders to guide the formation of a successful, sustainable MIC. These principles promote formation of an ethically sound, inclusive, participant-centric MIC and provide a framework for advancing the policy response to data-sharing opportunities and challenges.
Keywords: Humans; Information Dissemination; Information Services; Medical Informatics

Dual molecular diagnosis contributes to atypical Prader-Willi phenotype in monozygotic twins. - Jehee, Fernanda S; de Oliveira, Valdirene T; Gurgel-Giannetti, Juliana; Pietra, Rafaella X; Rubatino, Fernando V M; Carobin, Natália V; Vianna, Gabrielle S; de Freitas, Mariana L; Fernandes, Karla S; Ribeiro, Beatriz S V; Brüggenwirth, Hennie T; Ali-Amin, Roza; et al. (Am J Med Genet A, 2017)
We describe monozygotic twin girls with genetic variation at two separate loci resulting in a blended phenotype of Prader-Willi syndrome and Pitt-Hopkins syndrome. These girls were diagnosed in early infancy with Prader-Willi syndrome, but developed an atypical phenotype, with apparent intellectual deficiency and lack of obesity. Array-comparative genomic hybridization confirmed a de novo paternal deletion of the 15q11.2q13 region and exome sequencing identified a second mutational event in both girls, which was a novel variant c.145+1G>A affecting a TCF4 canonical splicing site inherited from the mosaic mother. RNA studies showed that the variant abolished the donor splicing site, which was accompanied by activation of an alternative non-canonical splicing-site which then predicts a premature stop codon in the following exon. Clinical re-evaluation of the twins indicated that both variants are likely contributing to the more severe phenotypic presentation. Our data show that atypical clinical presentations may actually be the expression of blended clinical phenotypes arising from independent pathogenic events at two loci.
Keywords: Adolescent; Base Sequence; Child; Chromosome Deletion; Chromosomes, Human, Pair 15; Comparative Genomic Hybridization; Exome; Facies; Female; Humans; Hyperventilation; Intellectual Disability; Obesity; Pathology, Molecular; Phenotype; Prader-Willi Syndrome; Transcription Factor 4; Twins, Monozygotic

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Rett Syndrome

Erratum to: Genomic innovations, transcriptional plasticity and gene loss underlying the evolution and divergence of two highly polyphagous and invasive Helicoverpa pest species. - Pearce, S L; Clarke, D F; East, P D; Elfekih, S; Gordon, K H J; Jermiin, L S; McGaughran, A; Oakeshott, J G; Papanicolaou, A; Perera, O P; Rane, R V; Richards, S; et al. (BMC Biol, 2017)

Erratum to: The whole genome sequence of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), reveals insights into the biology and adaptive evolution of a highly invasive pest species. - Papanicolaou, Alexie; Schetelig, Marc F; Arensburger, Peter; Atkinson, Peter W; Benoit, Joshua B; Bourtzis, Kostas; Castañera, Pedro; Cavanaugh, John P; Chao, Hsu; Childers, Christopher; Curril, Ingrid; Dinh, Huyen; et al. (Genome Biol, 2017)

Evolutionary History of Chemosensory-Related Gene Families across the Arthropoda. - Eyun, Seong-Il; Soh, Ho Young; Posavi, Marijan; Munro, James B; Hughes, Daniel S T; Murali, Shwetha C; Qu, Jiaxin; Dugan, Shannon; Lee, Sandra L; Chao, Hsu; Dinh, Huyen; Yi Han; et al. (Mol Biol Evol, 2017)
Chemosensory-related gene (CRG) families have been studied extensively in insects, but their evolutionary history across the Arthropoda had remained relatively unexplored. Here, we address current hypotheses and prior conclusions on CRG family evolution using a more comprehensive data set. In particular, odorant receptors were hypothesized to have proliferated during terrestrial colonization by insects (hexapods), but their association with other pancrustacean clades and with independent terrestrial colonizations in other arthropod subphyla have been unclear. We also examine hypotheses on which arthropod CRG family is most ancient. Thus, we reconstructed phylogenies of CRGs, including those from new arthropod genomes and transcriptomes, and mapped CRG gains and losses across arthropod lineages. Our analysis was strengthened by including crustaceans, especially copepods, which reside outside the hexapod/branchiopod clade within the subphylum Pancrustacea. We generated the first high-resolution genome sequence of the copepod Eurytemora affinis and annotated its CRGs. We found odorant receptors and odorant binding proteins present only in hexapods (insects) and absent from all other arthropod lineages, indicating that they are not universal adaptations to land. Gustatory receptors likely represent the oldest chemosensory receptors among CRGs, dating back to the Placozoa. We also clarified and confirmed the evolutionary history of antennal ionotropic receptors across the Arthropoda. All antennal ionotropic receptors in E. affinis were expressed more highly in males than in females, suggestive of an association with male mate-recognition behavior. This study is the most comprehensive comparative analysis to date of CRG family evolution across the largest and most speciose metazoan phylum Arthropoda.
Keywords: Animals; Arthropods; Chemoreceptor Cells; Copepoda; Crustacea; Databases, Nucleic Acid; Evolution, Molecular; Genome; Insecta; Multigene Family; Phylogeny; Receptors, Odorant

Exome sequencing reveals novel genetic loci influencing obesity-related traits in Hispanic children. - Aniko Sabo; Mishra, Pamela; Dugan-Perez, Shannon; Voruganti, V Saroja; Kent, Jack W; Kalra, Divya; Cole, Shelley A; Comuzzie, Anthony G; Donna M Muzny; Richard A Gibbs; Butte, Nancy F (Obesity (Silver Spring), 2017)
OBJECTIVE: To perform whole exome sequencing in 928 Hispanic children and identify variants and genes associated with childhood obesity. METHODS: Single-nucleotide variants (SNVs) were identified from Illumina whole exome sequencing data using integrated read mapping, variant calling, and an annotation pipeline (Mercury). Association analyses of 74 obesity-related traits and exonic variants were performed using SeqMeta software. Rare autosomal variants were analyzed using gene-based association analyses, and common autosomal variants were analyzed at the SNV level. RESULTS: (1) Rare exonic variants in 10 genes and 16 common SNVs in 11 genes that were associated with obesity traits in a cohort of Hispanic children were identified, (2) novel rare variants in peroxisome biogenesis factor 1 (PEX1) associated with several obesity traits (weight, weight z score, BMI, BMI z score, waist circumference, fat mass, trunk fat mass) were discovered, and (3) previously reported SNVs associated with childhood obesity were replicated. CONCLUSIONS: Convergence of whole exome sequencing, a family-based design, and extensive phenotyping discovered novel rare and common variants associated with childhood obesity. Linking PEX1 to obesity phenotypes poses a novel mechanism of peroxisomal biogenesis and metabolism underlying the development of childhood obesity.
Keywords: Adolescent; ATPases Associated with Diverse Cellular Activities; Body Mass Index; Body Weight; Child; Child, Preschool; Cohort Studies; Exome; Genetic Loci; Genome-Wide Association Study; Hispanic or Latino; Humans; Membrane Proteins; Pediatric Obesity; Polymorphism, Single Nucleotide; Risk Factors; Sequence Analysis, DNA; Software; Waist Circumference; Young Adult

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Exome Sequencing; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin

Extremely low-coverage whole genome sequencing in South Asians captures population genomics information. - Rustagi, Navin; Zhou, Anbo; Watkins, W Scott; Gedvilaite, Erika; Wang, Shuoguo; Ramesh, Naveen; Donna M Muzny; Richard A Gibbs; Jorde, Lynn B; Fuli Yu; Xing, Jinchuan (BMC Genomics, 2017)
BACKGROUND: The cost of Whole Genome Sequencing (WGS) has decreased tremendously in recent years due to advances in next-generation sequencing technologies. Nevertheless, the cost of carrying out large-scale cohort studies using WGS is still daunting. Past simulation studies with coverage at ~2x have shown promise for using low coverage WGS in studies focused on variant discovery, association study replications, and population genomics characterization. However, the performance of low coverage WGS in populations with a complex history and no reference panel remains to be determined. RESULTS: South Indian populations are known to have a complex population structure and are an example of a major population group that lacks adequate reference panels. To test the performance of extremely low-coverage WGS (EXL-WGS) in populations with a complex history and to provide a reference resource for South Indian populations, we performed EXL-WGS on 185 South Indian individuals from eight populations to ~1.6x coverage. Using two variant discovery pipelines, SNPTools and GATK, we generated a consensus call set that has ~90% sensitivity for identifying common variants (minor allele frequency ≥ 10%). Imputation further improves the sensitivity of our call set. In addition, we obtained high-coverage for the whole mitochondrial genome to infer the maternal lineage evolutionary history of the Indian samples. CONCLUSIONS: Overall, we demonstrate that EXL-WGS with imputation can be a valuable study design for variant discovery with a dramatically lower cost than standard WGS, even in populations with a complex history and without available reference data. In addition, the South Indian EXL-WGS data generated in this study will provide a valuable resource for future Indian genomic studies.
Keywords: Asian People; Genetic Variation; Genome, Mitochondrial; Humans; Metagenomics; Whole Genome Sequencing

Generating Clinical Reports from Genomic Data on the Cloud-based Neptune Platform - Eric Venner; Leduc, Magalie S; Matthew N Bainbridge; Wu, Tsung-Jung; Kovar, Christie; Chiang, Theodore; Mullai Murugan; William J Salerno; Donna M Muzny; Richard A Gibbs (ACMG Annual Clinical Genetics Meeting 2017, 2017)
High throughput clinical analysis of DNA capture panels demand automated processing to provide timely and cost-efficient reporting. We developed Neptune, an automated analytical platform to sign-out and deliver clinical reports, to address this need. Initial data intake occurs in a HIPAA compliant environment on DNAnexus, and samples are de-identified before moving into the CLIA lab. After analysis with the Human Genome Sequencing Center’s Mercury Pipeline, Neptune’s custom annotation software identifies variants of putative clinical relevance for manual review and possible addition to a “VIP” database of clinically relevant variation. This resource draws on both public resources (ClinVar, literature review) and internal data sets accessed via Anton, the HGSC’s Hadoop-based data store. The VIP database currently houses 20,872 SNPs and 3,946 indels, and contains a curated set of copy number variants (CNVs) annotated with internal frequency data. Using Neptune’s manual review interface, a clinical geneticist updates the VIP database accordingly. Once all variants have been categorized, Neptune extracts reportable, pathogenic variants using the VIP set, and Neptune outputs an automated clinical pre-report populated with prioritized variants (or a negative report if no relevant variants are found), descriptive text, and coverage statistics produced by the HGSC’s ExCiD software. The modular nature of Neptune allows it to be deployed locally, on the cloud or as a hybrid. Clinical reports integrate SNVs, Indels and CNVs. Early applications include reporting for the National Institutes of Health eMERGE network where more than 12,500 samples and a panel of 109 genes will be processed in less than three years, as well as the Right10k pharmacogenomics project in collaboration with the Mayo Clinic.

Genomic innovations, transcriptional plasticity and gene loss underlying the evolution and divergence of two highly polyphagous and invasive Helicoverpa pest species. - Pearce, S L; Clarke, D F; East, P D; Elfekih, S; Gordon, K H J; Jermiin, L S; McGaughran, A; Oakeshott, J G; Papanicolaou, A; Perera, O P; Rane, R V; Richards, S; et al. (BMC Biol, 2017)
BACKGROUND: Helicoverpa armigera and Helicoverpa zea are major caterpillar pests of Old and New World agriculture, respectively. Both, particularly H. armigera, are extremely polyphagous, and H. armigera has developed resistance to many insecticides. Here we use comparative genomics, transcriptomics and resequencing to elucidate the genetic basis for their properties as pests. RESULTS: We find that, prior to their divergence about 1.5 Mya, the H. armigera/H. zea lineage had accumulated up to more than 100 more members of specific detoxification and digestion gene families and more than 100 extra gustatory receptor genes, compared to other lepidopterans with narrower host ranges. The two genomes remain very similar in gene content and order, but H. armigera is more polymorphic overall, and H. zea has lost several detoxification genes, as well as about 50 gustatory receptor genes. It also lacks certain genes and alleles conferring insecticide resistance found in H. armigera. Non-synonymous sites in the expanded gene families above are rapidly diverging, both between paralogues and between orthologues in the two species. Whole genome transcriptomic analyses of H. armigera larvae show widely divergent responses to different host plants, including responses among many of the duplicated detoxification and digestion genes. CONCLUSIONS: The extreme polyphagy of the two heliothines is associated with extensive amplification and neofunctionalisation of genes involved in host finding and use, coupled with versatile transcriptional responses on different hosts. H. armigera's invasion of the Americas in recent years means that hybridisation could generate populations that are both locally adapted and insecticide resistant.
Keywords: Animals; Gene Expression Profiling; Genome, Insect; Genomics; Herbivory; Introduced Species; Larva; Moths; Sequence Analysis, DNA

Germline mutations in ABL1 cause an autosomal dominant syndrome characterized by congenital heart defects and skeletal malformations. - Wang, Xia; Charng, Wu-Lin; Chen, Chun-An; Rosenfeld, Jill A; Al Shamsi, Aisha; Al-Gazali, Lihadh; McGuire, Marianne; Mew, Nicholas Ah; Arnold, Georgianne L; Qu, Chunjing; Ding, Yan; Donna M Muzny; et al. (Nat Genet, 2017)
ABL1 is a proto-oncogene well known as part of the fusion gene BCR-ABL1 in the Philadelphia chromosome of leukemia cancer cells. Inherited germline ABL1 changes have not been associated with genetic disorders. Here we report ABL1 germline variants cosegregating with an autosomal dominant disorder characterized by congenital heart disease, skeletal abnormalities, and failure to thrive. The variant c.734A>G (p.Tyr245Cys) was found to occur de novo or cosegregate with disease in five individuals (families 1-3). Additionally, a de novo c.1066G>A (p.Ala356Thr) variant was identified in a sixth individual (family 4). We overexpressed the mutant constructs in HEK 293T cells and observed increased tyrosine phosphorylation, suggesting increased ABL1 kinase activities associated with both the p.Tyr245Cys and p.Ala356Thr substitutions. Our clinical and experimental findings, together with previously reported teratogenic effects of selective BCR-ABL inhibitors in humans and developmental defects in Abl1 knockout mice, suggest that ABL1 has an important role during organismal development.
Keywords: Abnormalities, Multiple; Animals; Bone Diseases, Developmental; Cell Line; Chromosome Disorders; Craniofacial Abnormalities; Feeding and Eating Disorders; Female; Fusion Proteins, bcr-abl; Germ-Line Mutation; Heart Defects, Congenital; HEK293 Cells; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Limb Deformities, Congenital; Male; Mice; Mice, Knockout; Philadelphia Chromosome; Phosphorylation; Proto-Oncogene Mas; Signal Transduction

The gut mycobiome of the Human Microbiome Project healthy cohort. - Nash, Andrea K; Auchtung, Thomas A; Wong, Matthew C; Smith, Daniel P; Gesell, Jonathan R; Ross, Matthew C; Stewart, Christopher J; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; Ajami, Nadim J; Petrosino, Joseph F (Microbiome, 2017)
BACKGROUND: Most studies describing the human gut microbiome in healthy and diseased states have emphasized the bacterial component, but the fungal microbiome (i.e., the mycobiome) is beginning to gain recognition as a fundamental part of our microbiome. To date, human gut mycobiome studies have primarily been disease centric or in small cohorts of healthy individuals. To contribute to existing knowledge of the human mycobiome, we investigated the gut mycobiome of the Human Microbiome Project (HMP) cohort by sequencing the Internal Transcribed Spacer 2 (ITS2) region as well as the 18S rRNA gene. RESULTS: Three hundred seventeen HMP stool samples were analyzed by ITS2 sequencing. Fecal fungal diversity was significantly lower in comparison to bacterial diversity. Yeast dominated the samples, comprising eight of the top 15 most abundant genera. Specifically, fungal communities were characterized by a high prevalence of Saccharomyces, Malassezia, and Candida, with S. cerevisiae, M. restricta, and C. albicans operational taxonomic units (OTUs) present in 96.8, 88.3, and 80.8% of samples, respectively. There was a high degree of inter- and intra-volunteer variability in fungal communities. However, S. cerevisiae, M. restricta, and C. albicans OTUs were found in 92.2, 78.3, and 63.6% of volunteers, respectively, in all samples donated over an approximately 1-year period. Metagenomic and 18S rRNA gene sequencing data agreed with ITS2 results; however, ITS2 sequencing provided greater resolution of the relatively low abundance mycobiome constituents. CONCLUSIONS: Compared to bacterial communities, the human gut mycobiome is low in diversity and dominated by yeast including Saccharomyces, Malassezia, and Candida. Both inter- and intra-volunteer variability in the HMP cohort were high, revealing that unlike bacterial communities, an individual's mycobiome is no more similar to itself over time than to another person's. Nonetheless, several fungal species persisted across a majority of samples, evidence that a core gut mycobiome may exist. ITS2 sequencing data provided greater resolution of the mycobiome membership compared to metagenomic and 18S rRNA gene sequencing data, suggesting that it is a more sensitive method for studying the mycobiome of stool samples.
Keywords: Candida; Cohort Studies; DNA, Ribosomal Spacer; Feces; Fungi; Gastrointestinal Microbiome; Genetic Variation; Healthy Volunteers; High-Throughput Nucleotide Sequencing; Humans; Malassezia; Metagenomics; Microbiota; Mycobiome; RNA, Ribosomal, 18S; Saccharomyces; Sequence Analysis, DNA

Heterozygous variants in ACTL6A, encoding a component of the BAF complex, are associated with intellectual disability. - Marom, Ronit; Jain, Mahim; Burrage, Lindsay C; Song, I-Wen; Graham, Brett H; Brown, Chester W; Stevens, Servi J C; Stegmann, Alexander P A; Gunter, Andrew T; Kaplan, Julie D; Gavrilova, Ralitza H; Shinawi, Marwan; et al. (Hum Mutat, 2017)
Pathogenic variants in genes encoding components of the BRG1-associated factor (BAF) chromatin remodeling complex have been associated with intellectual disability syndromes. We identified heterozygous, novel variants in ACTL6A, a gene encoding a component of the BAF complex, in three subjects with varying degrees of intellectual disability. Two subjects have missense variants affecting highly conserved amino acid residues within the actin-like domain. Missense mutations in the homologous region in yeast actin were previously reported to be dominant lethal and were associated with impaired binding of the human ACTL6A to β-actin and BRG1. A third subject has a splicing variant that creates an in-frame deletion. Our findings suggest that the variants identified in our subjects may have a deleterious effect on the function of the protein by disturbing the integrity of the BAF complex. Thus, ACTL6A gene mutation analysis should be considered in patients with intellectual disability, learning disabilities, or developmental language disorder.
Keywords: Actins; Adolescent; Child; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; DNA Helicases; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Multiprotein Complexes; Mutation, Missense; Nuclear Proteins; Protein Binding; Transcription Factors

Homozygous and hemizygous CNV detection from exome sequencing data in a Mendelian disease cohort. - Gambin, Tomasz; Akdemir, Zeynep C; Bo Yuan; Gu, Shen; Chiang, Theodore; Carvalho, Claudia M B; Shaw, Chad; Jhangiani, Shalini; Boone, Philip M; Eldomery, Mohammad K; Karaca, Ender; Bayram, Yavuz; et al. (Nucleic Acids Res, 2017)
We developed an algorithm, HMZDelFinder, that uses whole exome sequencing (WES) data to identify rare and intragenic homozygous and hemizygous (HMZ) deletions that may represent complete loss-of-function of the indicated gene. HMZDelFinder was applied to 4866 samples in the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) cohort and detected 773 HMZ deletion calls (567 homozygous or 206 hemizygous) with an estimated sensitivity of 86.5% (82% for single-exonic and 88% for multi-exonic calls) and precision of 78% (53% single-exonic and 96% for multi-exonic calls). Out of 773 HMZDelFinder-detected deletion calls, 82 were subjected to array comparative genomic hybridization (aCGH) and/or breakpoint PCR and 64 were confirmed. These include 18 single-exon deletions out of which 8 were exclusively detected by HMZDelFinder and not by any of seven other CNV detection tools examined. Further investigation of the 64 validated deletion calls revealed at least 15 pathogenic HMZ deletions. Of those, 7 accounted for 17-50% of pathogenic CNVs in different disease cohorts where 7.1-11% of the molecular diagnosis solved rate was attributed to CNVs. In summary, we present an algorithm to detect rare, intragenic, single-exon deletion CNVs using WES data; this tool can be useful for disease gene discovery efforts and clinical WES analyses.
Keywords: Algorithms; Alternative Splicing; Cohort Studies; Computational Biology; Consanguinity; Datasets as Topic; DNA Copy Number Variations; Exome; Genetic Diseases, Inborn; Hemizygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Inheritance Patterns; Models, Genetic; Pedigree; Reproducibility of Results; Sequence Deletion; Workflow

The house spider genome reveals an ancient whole-genome duplication during arachnid evolution. - Schwager, Evelyn E; Sharma, Prashant P; Clarke, Thomas; Leite, Daniel J; Wierschin, Torsten; Pechmann, Matthias; Akiyama-Oda, Yasuko; Esposito, Lauren; Bechsgaard, Jesper; Bilde, Trine; Buffry, Alexandra D; Chao, Hsu; et al. (BMC Biol, 2017)
BACKGROUND: The duplication of genes can occur through various mechanisms and is thought to make a major contribution to the evolutionary diversification of organisms. There is increasing evidence for a large-scale duplication of genes in some chelicerate lineages including two rounds of whole genome duplication (WGD) in horseshoe crabs. To investigate this further, we sequenced and analyzed the genome of the common house spider Parasteatoda tepidariorum. RESULTS: We found pervasive duplication of both coding and non-coding genes in this spider, including two clusters of Hox genes. Analysis of synteny conservation across the P. tepidariorum genome suggests that there has been an ancient WGD in spiders. Comparison with the genomes of other chelicerates, including that of the newly sequenced bark scorpion Centruroides sculpturatus, suggests that this event occurred in the common ancestor of spiders and scorpions, and is probably independent of the WGDs in horseshoe crabs. Furthermore, characterization of the sequence and expression of the Hox paralogs in P. tepidariorum suggests that many have been subject to neo-functionalization and/or sub-functionalization since their duplication. CONCLUSIONS: Our results reveal that spiders and scorpions are likely the descendants of a polyploid ancestor that lived more than 450 MYA. Given the extensive morphological diversity and ecological adaptations found among these animals, rivaling those of vertebrates, our study of the ancient WGD event in Arachnopulmonata provides a new comparative platform to explore common and divergent evolutionary outcomes of polyploidization events across eukaryotes.
Keywords: Animals; Evolution, Molecular; Female; Gene Duplication; Genome; Male; Spiders; Synteny

Hybrid de novo genome assembly and centromere characterization of the gray mouse lemur (Microcebus murinus). - Larsen, Peter A; R. Alan Harris; Liu, Yue; Murali, Shwetha C; Campbell, C Ryan; Brown, Adam D; Sullivan, Beth A; Shelton, Jennifer; Brown, Susan J; Raveendran, Muthuswamy; Dudchenko, Olga; Machol, Ido; et al. (BMC Biol, 2017)
BACKGROUND: The de novo assembly of repeat-rich mammalian genomes using only high-throughput short read sequencing data typically results in highly fragmented genome assemblies that limit downstream applications. Here, we present an iterative approach to hybrid de novo genome assembly that incorporates datasets stemming from multiple genomic technologies and methods. We used this approach to improve the gray mouse lemur (Microcebus murinus) genome from early draft status to a near chromosome-scale assembly. METHODS: We used a combination of advanced genomic technologies to iteratively resolve conflicts and super-scaffold the M. murinus genome. RESULTS: We improved the M. murinus genome assembly to a scaffold N50 of 93.32 Mb. Whole genome alignments between our primary super-scaffolds and 23 human chromosomes revealed patterns that are congruent with historical comparative cytogenetic data, thus demonstrating the accuracy of our de novo scaffolding approach and allowing assignment of scaffolds to M. murinus chromosomes. Moreover, we utilized our independent datasets to discover and characterize sequences associated with centromeres across the mouse lemur genome. Quality assessment of the final assembly found 96% of mouse lemur canonical transcripts nearly complete, comparable to other published high-quality reference genome assemblies. CONCLUSIONS: We describe a new assembly of the gray mouse lemur (Microcebus murinus) genome with chromosome-scale scaffolds produced using a hybrid bioinformatic and sequencing approach. The approach is cost effective and produces superior results based on metrics of contiguity and completeness. Our results show that emerging genomic technologies can be used in combination to characterize centromeres of non-model species and to produce accurate de novo chromosome-scale genome assemblies of complex mammalian genomes.
Keywords: Animals; Centromere; Cheirogaleidae; Computational Biology; Female; Genome; High-Throughput Nucleotide Sequencing; Sequence Analysis, DNA

Improved full-length killer cell immunoglobulin-like receptor transcript discovery in Mauritian cynomolgus macaques. - Prall, Trent M; Graham, Michael E; Karl, Julie A; Wiseman, Roger W; Ericsen, Adam J; Raveendran, Muthuswamy; R. Alan Harris; Donna M Muzny; Richard A Gibbs; Jeffrey Rogers; O'Connor, David H (Immunogenetics, 2017)
Killer cell immunoglobulin-like receptors (KIRs) modulate disease progression of pathogens including HIV, malaria, and hepatitis C. Cynomolgus and rhesus macaques are widely used as nonhuman primate models to study human pathogens, and so, considerable effort has been put into characterizing their KIR genetics. However, previous studies have relied on cDNA cloning and Sanger sequencing that lack the throughput of current sequencing platforms. In this study, we present a high throughput, full-length allele discovery method utilizing Pacific Biosciences circular consensus sequencing (CCS). We also describe a new approach to Macaque Exome Sequencing (MES) and the development of the Rhexome1.0, an adapted target capture reagent that includes macaque-specific capture probe sets. By using sequence reads generated by whole genome sequencing (WGS) and MES to inform primer design, we were able to increase the sensitivity of KIR allele discovery. We demonstrate this increased sensitivity by defining nine novel alleles within a cohort of Mauritian cynomolgus macaques (MCM), a geographically isolated population with restricted KIR genetics that was thought to be completely characterized. Finally, we describe an approach to genotyping KIRs directly from sequence reads generated using WGS/MES reads. The findings presented here expand our understanding of KIR genetics in MCM by associating new genes with all eight KIR haplotypes and demonstrating the existence of at least one KIR3DS gene associated with every haplotype.
Keywords: Animals; Exome; Gene Frequency; High-Throughput Nucleotide Sequencing; Macaca fascicularis; Receptors, KIR; Sequence Analysis, DNA

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails. - Kariminejad, Ariana; Ajeawung, Norbert Fonya; Bozorgmehr, Bita; Dionne-Laporte, Alexandre; Molidperee, Sirinart; Najafi, Kimia; Richard A Gibbs; Lee, Brendan H; Hennekam, Raoul C; Campeau, Philippe M (J Hum Genet, 2017)
Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes that were initially considered include DOORS syndrome, Coffin-Siris syndrome and Dubowitz syndrome. Clinical investigations coupled with karyotype analysis, array-comparative genomic hybridization, exome and Sanger sequencing were performed to characterize the condition in this child. Sanger sequencing was negative for the DOORS syndrome gene TBC1D24 but exome sequencing identified a homozygous deletion in UBE3B (NM_183415:c.3139_3141del, p.1047_1047del) located within the terminal portion of the HECT domain. This finding coupled with the presence of characteristic features such as brachycephaly, ptosis, blepharophimosis, hypertelorism, short palpebral fissures, cleft palate and developmental delay allowed us to make a diagnosis of KOS. In conclusion, our findings highlight the importance of considering KOS as a differential diagnosis for patients under evaluation for DOORS syndrome and expand the phenotype of KOS to include small or absent terminal phalanges, nails, and the presence of hallux varus and multicystic dysplastic kidneys.
Keywords: Abnormalities, Multiple; Adult; Carrier Proteins; Child; Child, Preschool; Diagnosis, Differential; Eczema; Eye Abnormalities; Face; Facies; Female; Growth Disorders; GTPase-Activating Proteins; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotype; Limb Deformities, Congenital; Male; Membrane Proteins; Microcephaly; Micrognathism; Mutation; Neck; Nerve Tissue Proteins; Pathology, Molecular; Sequence Analysis, DNA; Ubiquitin-Protein Ligases

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Neonatal fractures as a presenting feature of LMOD3-associated congenital myopathy. - Abbott, Megan; Jain, Mahim; Pferdehirt, Rachel; Chen, Yuqing; Tran, Alyssa; Duz, Mehmet B; Seven, Mehmet; Richard A Gibbs; Donna M Muzny; Lee, Brendan; Marom, Ronit; Burrage, Lindsay C (Am J Med Genet A, 2017)
Nemaline myopathy is a rare inherited disorder characterized by weakness, hypotonia, and depressed deep tendon reflexes. It is clinically and genetically heterogeneous, with the most severe phenotype presenting as perinatal akinesia, severe muscle weakness, feeding difficulties and respiratory failure, leading to early mortality. Pathogenic variants in 12 genes, encoding components of the sarcomere or factors related to myogenesis, have been reported in patients affected with the disorder. Here, we describe an early, lethal presentation of decreased fetal movements, hypotonia, muscle weakness, and neonatal respiratory failure requiring ventilator support in three siblings from a consanguineous family. All exhibited perinatal fractures, and thus, a skeletal dysplasia was considered as possibly contributing to the phenotype. However, whole exome sequencing revealed a homozygous, loss-of-function pathogenic variant in LMOD3, which has recently been associated with nemaline myopathy and, in a subset of patients, perinatal fractures. This case demonstrates the importance of considering congenital neuromuscular disorders in the differential diagnosis of perinatal fractures.
Keywords: Female; Fractures, Bone; Homozygote; Humans; Infant, Newborn; Male; Microfilament Proteins; Muscle Proteins; Mutation; Myopathies, Structural, Congenital; Pedigree

A non-mosaic mutation in a male with severe congenital anomalies overlapping focal dermal hypoplasia. - Madan, Simran; Liu, Wei; Lu, James T; Sutton, V Reid; Toth, Bryant; Joe, Priscilla; Waterson, John R; Richard A Gibbs; Van den Veyver, Ignatia B; Lammer, Edward J; Campeau, Philippe M; Lee, Brendan H (Mol Genet Metab Rep, 2017)
Mutations in the gene cause the X-linked dominant condition focal dermal hypoplasia (FDH). Features of FDH include striated pigmentation of the skin, ocular and skeletal malformations. FDH is generally associated with lethality in non-mosaic males and most of the currently reported male patients show mosaicism due to post-zygotic mutations in the gene. There is only one previous report of a surviving male with an inherited mutation in the gene. Here, we report two male siblings with multiple malformations including skeletal, ocular and renal defects overlapping with FDH. A novel mutation (p.Ser250Phe) was identified in a non-mosaic, hemizygous state in one of the siblings who survived to 8 years of age. The mother is a heterozygous carrier, has a random X-inactivation pattern and is asymptomatic. Findings unusual for FDH include dysplastic clavicles and bilateral Tessier IV facial clefts. This is the second case report of a non-mosaic mutation in a male individual with multiple congenital anomalies. While the pathogenicity of this mutation remains to be further investigated, the survival of a male with a non-mosaic mutation in is suggestive of a functionally mild mutation leading to an X-linked recessive mode of inheritance.

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Bo Yuan; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

Practical Approaches for Whole-Genome Sequence Analysis of Heart- and Blood-Related Traits. - Morrison, Alanna C; Huang, Zhuoyi; Yu, Bing; Ginger A Metcalf; Liu, Xiaoming; Ballantyne, Christie; Coresh, Josef; Fuli Yu; Donna M Muzny; Feofanova, Elena; Rustagi, Navin; Richard A Gibbs; et al. (Am J Hum Genet, 2017)
Whole-genome sequencing (WGS) allows for a comprehensive view of the sequence of the human genome. We present and apply integrated methodologic steps for interrogating WGS data to characterize the genetic architecture of 10 heart- and blood-related traits in a sample of 1,860 African Americans. In order to evaluate the contribution of regulatory and non-protein coding regions of the genome, we conducted aggregate tests of rare variation across the entire genomic landscape using a sliding window, complemented by an annotation-based assessment of the genome using predefined regulatory elements and within the first intron of all genes. These tests were performed treating all variants equally as well as with individual variants weighted by a measure of predicted functional consequence. Significant findings were assessed in 1,705 individuals of European ancestry. After these steps, we identified and replicated components of the genomic landscape significantly associated with heart- and blood-related traits. For two traits, lipoprotein(a) levels and neutrophil count, aggregate tests of low-frequency and rare variation were significantly associated across multiple motifs. For a third trait, cardiac troponin T, investigation of regulatory domains identified a locus on chromosome 9. These practical approaches for WGS analysis led to the identification of informative genomic regions and also showed that defined non-coding regions, such as first introns of genes and regulatory domains, are associated with important risk factor phenotypes. This study illustrates the tractable nature of WGS data and outlines an approach for characterizing the genetic architecture of complex traits.
Keywords: Black or African American; C-Reactive Protein; Cholesterol, HDL; Cholesterol, LDL; Chromosomes, Human, Pair 9; Gene Frequency; Genome, Human; Genome-Wide Association Study; Genomics; Hemoglobins; Humans; Introns; Leukocyte Count; Lipoprotein(a); Magnesium; Natriuretic Peptide, Brain; Neutrophils; Peptide Fragments; Phosphorus; Platelet Count; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Troponin T; White People

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Bo Yuan; Jhangiani, Shalini N; Donna M Muzny; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

Renal cell carcinoma harboring somatic TSC2 mutations in a child with methylmalonic acidemia. - Potter, Samara L; Venkatramani, Rajkumar; Wenderfer, Scott; Graham, Brett H; Vasudevan, Sanjeev A; Sher, Andrew; Wu, Hao; Wheeler, David A; Yang, Yaping; Eng, Christine M; Richard A Gibbs; Roy, Angshumoy; et al. (Pediatr Blood Cancer, 2017)
Pediatric renal cell carcinoma (RCC) is a rare cancer that can be associated with inherited diseases including tuberous sclerosis complex (TSC) caused by germline mutations in TSC1 or TSC2. Somatic mutations in TSC1 and TSC2 have also been reported in adult RCC, which predict response to mTOR inhibitors. Here, we present the first case of RCC in a child with methylmalonic acidemia (MMA). Clinical whole exome sequencing of blood and tumor samples confirmed the diagnosis of MMA and revealed two somatic inactivating mutations in TSC2, suggesting the potential consideration of an mTOR inhibitor in the event of tumor recurrence.
Keywords: Amino Acid Metabolism, Inborn Errors; Antineoplastic Agents; Carcinoma, Renal Cell; Child; Everolimus; Female; Humans; Kidney Neoplasms; Sirolimus; TOR Serine-Threonine Kinases; Tuberous Sclerosis Complex 2 Protein; Tumor Suppressor Proteins

Resolution of Disease Phenotypes Resulting from Multilocus Genomic Variation. - Posey, Jennifer E; Harel, Tamar; Liu, Pengfei; Rosenfeld, Jill A; James, Regis A; Coban Akdemir, Zeynep H; Walkiewicz, Magdalena; Bi, Weimin; Xiao, Rui; Ding, Yan; Xia, Fan; Beaudet, Arthur L; et al. (N Engl J Med, 2017)
BACKGROUND: Whole-exome sequencing can provide insight into the relationship between observed clinical phenotypes and underlying genotypes. METHODS: We conducted a retrospective analysis of data from a series of 7374 consecutive unrelated patients who had been referred to a clinical diagnostic laboratory for whole-exome sequencing; our goal was to determine the frequency and clinical characteristics of patients for whom more than one molecular diagnosis was reported. The phenotypic similarity between molecularly diagnosed pairs of diseases was calculated with the use of terms from the Human Phenotype Ontology. RESULTS: A molecular diagnosis was rendered for 2076 of 7374 patients (28.2%); among these patients, 101 (4.9%) had diagnoses that involved two or more disease loci. We also analyzed parental samples, when available, and found that de novo variants accounted for 67.8% (61 of 90) of pathogenic variants in autosomal dominant disease genes and 51.7% (15 of 29) of pathogenic variants in X-linked disease genes; both variants were de novo in 44.7% (17 of 38) of patients with two monoallelic variants. Causal copy-number variants were found in 12 patients (11.9%) with multiple diagnoses. Phenotypic similarity scores were significantly lower among patients in whom the phenotype resulted from two distinct mendelian disorders that affected different organ systems (50 patients) than among patients with disorders that had overlapping phenotypic features (30 patients) (median score, 0.21 vs. 0.36; P=1.77×10). CONCLUSIONS: In our study, we found multiple molecular diagnoses in 4.9% of cases in which whole-exome sequencing was informative. Our results show that structured clinical ontologies can be used to determine the degree of overlap between two mendelian diseases in the same patient; the diseases can be distinct or overlapping. Distinct disease phenotypes affect different organ systems, whereas overlapping disease phenotypes are more likely to be caused by two genes encoding proteins that interact within the same pathway. (Funded by the National Institutes of Health and the Ting Tsung and Wei Fong Chao Foundation.).
Keywords: Exome; Genetic Diseases, Inborn; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Phenotype; Retrospective Studies; Sequence Analysis, DNA

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis. - Bayram, Yavuz; White, Janson J; Elcioglu, Nursel; Cho, Megan T; Zadeh, Neda; Gedikbasi, Asuman; Palanduz, Sukru; Ozturk, Sukru; Cefle, Kivanc; Kasapcopur, Ozgur; Coban Akdemir, Zeynep; Pehlivan, Davut; et al. (Am J Hum Genet, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exon-truncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Adolescent; Base Sequence; Chromosome Segregation; Exons; Family; Female; Fibromatosis, Gingival; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Repressor Proteins

SeqCNV: a novel method for identification of copy number variations in targeted next-generation sequencing data. - Chen, Yong; Zhao, Li; Wang, Yi; Cao, Ming; Gelowani, Violet; Xu, Mingchu; Agrawal, Smriti A; Yumei Li; Daiger, Stephen P; Richard A Gibbs; Wang, Fei; Rui Chen (BMC Bioinformatics, 2017)
BACKGROUND: Targeted next-generation sequencing (NGS) has been widely used as a cost-effective way to identify the genetic basis of human disorders. Copy number variations (CNVs) contribute significantly to human genomic variability, some of which can lead to disease. However, effective detection of CNVs from targeted capture sequencing data remains challenging. RESULTS: Here we present SeqCNV, a novel CNV calling method designed to use capture NGS data. SeqCNV extracts the read depth information and utilizes the maximum penalized likelihood estimation (MPLE) model to identify the copy number ratio and CNV boundary. We applied SeqCNV to both bacterial artificial clone (BAC) and human patient NGS data to identify CNVs. These CNVs were validated by array comparative genomic hybridization (aCGH). CONCLUSIONS: SeqCNV is able to robustly identify CNVs of different size using capture NGS data. Compared with other CNV-calling methods, SeqCNV shows a significant improvement in both sensitivity and specificity.
Keywords: DNA Copy Number Variations; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Likelihood Functions; Sensitivity and Specificity; Sequence Analysis, DNA; Software

SVachra: a tool to identify genomic structural variation in mate pair sequencing data containing inward and outward facing reads. - Hampton, Oliver A; English, Adam C; Wang, Mark; Salerno, William J; Liu, Yue; Donna M Muzny; Yi Han; Wheeler, David A; Worley, Kim C; Lupski, James R; Richard A Gibbs (BMC Genomics, 2017)
BACKGROUND: Characterization of genomic structural variation (SV) is essential to expanding the research and clinical applications of genome sequencing. Reliance upon short DNA fragment paired end sequencing has yielded a wealth of single nucleotide variants and internal sequencing read insertions-deletions, at the cost of limited SV detection. Multi-kilobase DNA fragment mate pair sequencing has supplemented the void in SV detection, but introduced new analytic challenges requiring SV detection tools specifically designed for mate pair sequencing data. Here, we introduce SVachra - Structural Variation Assessment of CHRomosomal Aberrations, a breakpoint calling program that identifies large insertions-deletions, inversions, inter- and intra-chromosomal translocations utilizing both inward and outward facing read types generated by mate pair sequencing. RESULTS: We demonstrate SVachra's utility by executing the program on large-insert (Illumina Nextera) mate pair sequencing data from the personal genome of a single subject (HS1011). An additional data set of long-read (Pacific BioSciences RSII) was also generated to validate SV calls from SVachra and other comparison SV calling programs. SVachra exhibited the highest validation rate and reported the widest distribution of SV types and size ranges when compared to other SV callers. CONCLUSIONS: SVachra is a highly specific breakpoint calling program that exhibits a more unbiased SV detection methodology than other callers.
Keywords: Genetic Variation; Genomics; Sequence Analysis, DNA

Unraveling genetic predisposition to familial or early onset gastric cancer using germline whole-exome sequencing. - Vogelaar, Ingrid P; van der Post, Rachel S; van Krieken, J Han Jm; Spruijt, Liesbeth; van Zelst-Stams, Wendy Ag; Kets, C Marleen; Lubinski, Jan; Jakubowska, Anna; Teodorczyk, Urszula; Aalfs, Cora M; van Hest, Liselotte P; Pinheiro, Hugo; et al. (Eur J Hum Genet, 2017)
Recognition of individuals with a genetic predisposition to gastric cancer (GC) enables preventive measures. However, the underlying cause of genetic susceptibility to gastric cancer remains largely unexplained. We performed germline whole-exome sequencing on leukocyte DNA of 54 patients from 53 families with genetically unexplained diffuse-type and intestinal-type GC to identify novel GC-predisposing candidate genes. As young age at diagnosis and familial clustering are hallmarks of genetic tumor susceptibility, we selected patients that were diagnosed below the age of 35, patients from families with two cases of GC at or below age 60 and patients from families with three GC cases at or below age 70. All included individuals were tested negative for germline CDH1 mutations before or during the study. Variants that were possibly deleterious according to in silico predictions were filtered using several independent approaches that were based on gene function and gene mutation burden in controls. Despite a rigorous search, no obvious candidate GC predisposition genes were identified. This negative result stresses the importance of future research studies in large, homogeneous cohorts.
Keywords: Adult; Aged; Antigens, CD; Cadherins; Early Detection of Cancer; Exome; Female; Genetic Predisposition to Disease; Genetic Testing; Germ-Line Mutation; Humans; Male; Middle Aged; Sequence Analysis, DNA; Stomach Neoplasms

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
IMPORTANCE: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. OBJECTIVE: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. DESIGN, SETTING, AND PARTICIPANTS: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. MAIN OUTCOMES AND MEASURES: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. RESULTS: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. CONCLUSIONS AND RELEVANCE: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Exome Sequencing; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Donna M Muzny; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Exome Sequencing; Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male

Whole-exome sequencing in the molecular diagnosis of individuals with congenital anomalies of the kidney and urinary tract and identification of a new causative gene. - Bekheirnia, Mir Reza; Bekheirnia, Nasim; Bainbridge, Matthew N; Gu, Shen; Coban Akdemir, Zeynep Hande; Gambin, Tomek; Janzen, Nicolette K; Jhangiani, Shalini N; Donna M Muzny; Michael, Mini; Brewer, Eileen D; Elenberg, Ewa; et al. (Genet Med, 2017)
PURPOSE: To investigate the utility of whole-exome sequencing (WES) to define a molecular diagnosis for patients clinically diagnosed with congenital anomalies of kidney and urinary tract (CAKUT). METHODS: WES was performed in 62 families with CAKUT. WES data were analyzed for single-nucleotide variants (SNVs) in 35 known CAKUT genes, putatively deleterious sequence changes in new candidate genes, and potentially disease-associated copy-number variants (CNVs). RESULTS: In approximately 5% of families, pathogenic SNVs were identified in PAX2, HNF1B, and EYA1. Observed phenotypes in these families expand the current understanding about the role of these genes in CAKUT. Four pathogenic CNVs were also identified using two CNV detection tools. In addition, we found one deleterious de novo SNV in FOXP1 among the 62 families with CAKUT. The clinical database of the Baylor Miraca Genetics laboratory was queried and seven additional unrelated individuals with novel de novo SNVs in FOXP1 were identified. Six of these eight individuals with FOXP1 SNVs have syndromic urinary tract defects, implicating this gene in urinary tract development. CONCLUSION: We conclude that WES can be used to identify molecular etiology (SNVs, CNVs) in a subset of individuals with CAKUT. WES can also help identify novel CAKUT genes.Genet Med 19 4, 412-420.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-beta; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Nuclear Proteins; PAX2 Transcription Factor; Pedigree; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases; Repressor Proteins; Urogenital Abnormalities; Vesico-Ureteral Reflux; Young Adult

Whole-genome landscape of pancreatic neuroendocrine tumours. - Scarpa, Aldo; Chang, David K; Nones, Katia; Corbo, Vincenzo; Patch, Ann-Marie; Bailey, Peter; Lawlor, Rita T; Johns, Amber L; Miller, David K; Mafficini, Andrea; Rusev, Borislav; Scardoni, Maria; et al. (Nature, 2017)
The diagnosis of pancreatic neuroendocrine tumours (PanNETs) is increasing owing to more sensitive detection methods, and this increase is creating challenges for clinical management. We performed whole-genome sequencing of 102 primary PanNETs and defined the genomic events that characterize their pathogenesis. Here we describe the mutational signatures they harbour, including a deficiency in G:C > T:A base excision repair due to inactivation of MUTYH, which encodes a DNA glycosylase. Clinically sporadic PanNETs contain a larger-than-expected proportion of germline mutations, including previously unreported mutations in the DNA repair genes MUTYH, CHEK2 and BRCA2. Together with mutations in MEN1 and VHL, these mutations occur in 17% of patients. Somatic mutations, including point mutations and gene fusions, were commonly found in genes involved in four main pathways: chromatin remodelling, DNA damage repair, activation of mTOR signalling (including previously undescribed EWSR1 gene fusions), and telomere maintenance. In addition, our gene expression analyses identified a subgroup of tumours associated with hypoxia and HIF signalling.
Keywords: Base Sequence; Calmodulin-Binding Proteins; Carcinoma, Neuroendocrine; Chromatin Assembly and Disassembly; Chromosome Aberrations; DNA Copy Number Variations; DNA Glycosylases; DNA Mutational Analysis; DNA Repair; Female; Genome, Human; Genomics; Germ-Line Mutation; Humans; Male; Pancreatic Neoplasms; RNA-Binding Protein EWS; RNA-Binding Proteins; Telomere; TOR Serine-Threonine Kinases

Whole-genome sequencing study of serum peptide levels: the Atherosclerosis Risk in Communities study. - de Vries, Paul S; Yu, Bing; Feofanova, Elena V; Ginger A Metcalf; Brown, Michael R; Zeighami, Atefeh L; Liu, Xiaoming; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; Morrison, Alanna C (Hum Mol Genet, 2017)
Oligopeptides are important markers of protein metabolism, as they are cleaved from larger polypeptides and proteins. Genetic association studies may help elucidate their origin and function. In 1,552 European Americans and 1,872 African Americans of the Atherosclerosis Risk in Communities study, we performed whole-genome and whole-exome sequencing and measured serum levels of 25 peptides. Common variants (minor allele frequency > 5%) were analysed individually. We grouped low-frequency variants (minor allele frequency ≤ 5%) by a genome-wide sliding window using region-based aggregate tests. Furthermore, low-frequency regulatory variants were grouped by gene, as were functional coding variants. All analyses were performed separately in each ancestry group and then meta-analysed. We identified 22 common variant associations with peptide levels (P-value < 4.2 × 10-10), including 16 novel gene-peptide pairs. Notably, variants in kinin-kallikrein genes KNG1, F12, KLKB1, and ACE were associated with several different peptides. Variants in KLKB1 and ACE were associated with a fragment of complement component 3f. Both common variants and low-frequency coding variants in CPN1 were associated with a fibrinogen cleavage peptide. Four sliding windows were significantly associated with peptide levels (P-value < 4.2 × 10-10). Our results highlight the importance of the kinin-kallikrein system in the regulation of serum peptide levels, strengthen the evidence for a broad link between the kinin-kallikrein and complement systems, and suggest a role of CPN1 in the conversion of fibrinogen to fibrin.
Keywords: Alleles; Atherosclerosis; Black or African American; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kallikreins; Male; Middle Aged; Peptides; Polymorphism, Single Nucleotide; Proteins; Risk Factors; White People; Whole Genome Sequencing

Ampullary Cancers Harbor ELF3 Tumor Suppressor Gene Mutations and Exhibit Frequent WNT Dysregulation. - Marie-Claude Gingras; Covington, Kyle R; Chang, David K; Donehower, Lawrence A; Gill, Anthony J; Ittmann, Michael M; Creighton, Chad J; Johns, Amber L; Shinbrot, Eve; Dewal, Ninad; Fisher, William E; Pilarsky, Christian; et al. (Cell Rep, 2016)
The ampulla of Vater is a complex cellular environment from which adenocarcinomas arise to form a group of histopathologically heterogenous tumors. To evaluate the molecular features of these tumors, 98 ampullary adenocarcinomas were evaluated and compared to 44 distal bile duct and 18 duodenal adenocarcinomas. Genomic analyses revealed mutations in the WNT signaling pathway among half of the patients and in all three adenocarcinomas irrespective of their origin and histological morphology. These tumors were characterized by a high frequency of inactivating mutations of ELF3, a high rate of microsatellite instability, and common focal deletions and amplifications, suggesting common attributes in the molecular pathogenesis are at play in these tumors. The high frequency of WNT pathway activating mutation, coupled with small-molecule inhibitors of β-catenin in clinical trials, suggests future treatment decisions for these patients may be guided by genomic analysis.
Keywords: Adenocarcinoma; Ampulla of Vater; Base Sequence; DNA-Binding Proteins; Duodenal Neoplasms; Genomic Instability; Humans; Microsatellite Repeats; Molecular Sequence Data; Mutation; Pancreatic Neoplasms; Proto-Oncogene Proteins c-ets; Transcription Factors; Wnt Signaling Pathway

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Association of the IGF1 gene with fasting insulin levels. - Willems, Sara M; Cornes, Belinda K; Brody, Jennifer A; Morrison, Alanna C; Lipovich, Leonard; Dauriz, Marco; Chen, Yuning; Liu, Ching-Ti; Rybin, Denis V; Richard A Gibbs; Donna M Muzny; Pankow, James S; et al. (Eur J Hum Genet, 2016)
Insulin-like growth factor 1 (IGF-I) has been associated with insulin resistance. Genome-wide association studies (GWASs) of fasting insulin (FI) identified single-nucleotide variants (SNVs) near the IGF1 gene, raising two hypotheses: (1) these associations are mediated by IGF-I levels and (2) these noncoding variants either tag other functional variants in the region or are directly functional. In our study, analyses including 5141 individuals from population-based cohorts suggest that FI associations near IGF1 are not mediated by IGF-I. Analyses of targeted sequencing data in 3539 individuals reveal a large number of novel rare variants at the IGF1 locus and show a FI association with a subset of rare nonsynonymous variants (PSKAT=5.7 × 10(-4)). Conditional analyses suggest that this association is partly explained by the GWAS signal and the presence of a residual independent rare variant effect (Pconditional=0.019). Annotation using ENCODE data suggests that the GWAS variants may have a direct functional role in insulin biology. In conclusion, our study provides insight into variation present at the IGF1 locus and into the genetic architecture underlying FI levels, suggesting that FI associations of SNVs near IGF1 are not mediated by IGF-I and suggesting a role for both rare nonsynonymous and common functional variants in insulin biology.
Keywords: Adult; Aged; Fasting; Female; Humans; Insulin; Insulin-Like Growth Factor I; Male; Middle Aged; Polymorphism, Single Nucleotide

Bi-allelic Mutations in PKD1L1 Are Associated with Laterality Defects in Humans. - Vetrini, Francesco; D'Alessandro, Lisa C A; Akdemir, Zeynep C; Braxton, Alicia; Azamian, Mahshid S; Eldomery, Mohammad K; Miller, Kathryn; Kois, Chelsea; Sack, Virginia; Shur, Natasha; Rijhsinghani, Asha; Chandarana, Jignesh; et al. (Am J Hum Genet, 2016)
Disruption of the establishment of left-right (L-R) asymmetry leads to situs anomalies ranging from situs inversus totalis (SIT) to situs ambiguus (heterotaxy). The genetic causes of laterality defects in humans are highly heterogeneous. Via whole-exome sequencing (WES), we identified homozygous mutations in PKD1L1 from three affected individuals in two unrelated families. PKD1L1 encodes a polycystin-1-like protein and its loss of function is known to cause laterality defects in mouse and medaka fish models. Family 1 had one fetus and one deceased child with heterotaxy and complex congenital heart malformations. WES identified a homozygous splicing mutation, c.6473+2_6473+3delTG, which disrupts the invariant splice donor site in intron 42, in both affected individuals. In the second family, a homozygous c.5072G>C (p.Cys1691Ser) missense mutation was detected in an individual with SIT and congenital heart disease. The p.Cys1691Ser substitution affects a highly conserved cysteine residue and is predicted by molecular modeling to disrupt a disulfide bridge essential for the proper folding of the G protein-coupled receptor proteolytic site (GPS) motif. Damaging effects associated with substitutions of this conserved cysteine residue in the GPS motif have also been reported in other genes, namely GPR56, BAI3, and PKD1 in human and lat-1 in C. elegans, further supporting the likely pathogenicity of p.Cys1691Ser in PKD1L1. The identification of bi-allelic PKD1L1 mutations recapitulates previous findings regarding phenotypic consequences of loss of function of the orthologous genes in mice and medaka fish and further expands our understanding of genetic contributions to laterality defects in humans.
Keywords: Alleles; Amino Acid Motifs; Amino Acid Sequence; Animals; Caenorhabditis elegans; Cysteine; Exome; Female; Fetal Diseases; Functional Laterality; Heart Defects, Congenital; Heterotaxy Syndrome; Homozygote; Humans; Infant, Newborn; Introns; Male; Membrane Proteins; Mice; Middle Aged; Models, Molecular; Mutation; Mutation, Missense; Oryzias; Pedigree; RNA Splicing; Situs Inversus

Comparative genomic study of arachnid immune systems indicates loss of beta-1,3-glucanase-related proteins and the immune deficiency pathway. - Bechsgaard, J; Vanthournout, B; Funch, P; Vestbo, S; Richard A Gibbs; Richards, S; Sanggaard, K W; Enghild, J J; Bilde, T (J Evol Biol, 2016)
Analyses of arthropod genomes have shown that the genes in the different innate humoral immune responses are conserved. These genes encode proteins that are involved in immune signalling pathways that recognize pathogens and activate immune responses. These immune responses include phagocytosis, encapsulation of the pathogen and production of effector molecules for pathogen elimination. So far, most studies have focused on insects leaving other major arthropod groups largely unexplored. Here, we annotate the immune-related genes of six arachnid genomes and present evidence for a conserved pattern of some immune genes, but also evolutionary changes in the arachnid immune system. Specifically, our results suggest that the family of recognition molecules of beta-1,3-glucanase-related proteins (βGRPs) and the genes from the immune deficiency (IMD) signalling pathway have been lost in a common ancestor of arachnids. These findings are consistent with previous work suggesting that the humoral immune effector proteins are constitutively produced in arachnids in contrast to insects, where these have to be induced. Further functional studies are needed to verify this. We further show that the full haemolymph clotting cascade found in the horseshoe crab is retrieved in most arachnid genomes. Tetranychus lacks at least one major component, although it is possible that this cascade could still function through recruitment of a different protein. The gel-forming protein in horseshoe crabs, coagulogen, was not recovered in any of the arachnid genomes; however, it is possible that the arachnid clot consists of a related protein, spätzle, that is present in all of the genomes.
Keywords: Amino Acid Sequence; Animals; Antimicrobial Cationic Peptides; Arachnida; Blood Proteins; Defensins; Gene Dosage; Genome; Genomics; Hemolymph; Immune System; Immunity, Innate; Protein Domains; Sequence Alignment; Signal Transduction

A comprehensive transcriptional map of primate brain development. - Bakken, Trygve E; Miller, Jeremy A; Ding, Song-Lin; Sunkin, Susan M; Smith, Kimberly A; Ng, Lydia; Szafer, Aaron; Dalley, Rachel A; Royall, Joshua J; Lemon, Tracy; Shapouri, Sheila; Aiona, Kaylynn; et al. (Nature, 2016)
The transcriptional underpinnings of brain development remain poorly understood, particularly in humans and closely related non-human primates. We describe a high-resolution transcriptional atlas of rhesus monkey (Macaca mulatta) brain development that combines dense temporal sampling of prenatal and postnatal periods with fine anatomical division of cortical and subcortical regions associated with human neuropsychiatric disease. Gene expression changes more rapidly before birth, both in progenitor cells and maturing neurons. Cortical layers and areas acquire adult-like molecular profiles surprisingly late in postnatal development. Disparate cell populations exhibit distinct developmental timing of gene expression, but also unexpected synchrony of processes underlying neural circuit construction including cell projection and adhesion. Candidate risk genes for neurodevelopmental disorders including primary microcephaly, autism spectrum disorder, intellectual disability, and schizophrenia show disease-specific spatiotemporal enrichment within developing neocortex. Human developmental expression trajectories are more similar to monkey than rodent, although approximately 9% of genes show human-specific regulation with evidence for prolonged maturation or neoteny compared to monkey.
Keywords: Aging; Animals; Autism Spectrum Disorder; Brain; Cell Adhesion; Conserved Sequence; Female; Humans; Intellectual Disability; Macaca mulatta; Male; Microcephaly; Neocortex; Neurodevelopmental Disorders; Neurogenesis; Risk Factors; Schizophrenia; Spatio-Temporal Analysis; Species Specificity; Transcription, Genetic; Transcriptome

Deep Sequencing of Random Mutant Libraries Reveals the Active Site of the Narrow Specificity CphA Metallo-β-Lactamase is Fragile to Mutations. - Sun, Zhizeng; Mehta, Shrenik C; Adamski, Carolyn J; Richard A Gibbs; Palzkill, Timothy (Sci Rep, 2016)
CphA is a Zn(2+)-dependent metallo-β-lactamase that efficiently hydrolyzes only carbapenem antibiotics. To understand the sequence requirements for CphA function, single codon random mutant libraries were constructed for residues in and near the active site and mutants were selected for E. coli growth on increasing concentrations of imipenem, a carbapenem antibiotic. At high concentrations of imipenem that select for phenotypically wild-type mutants, the active-site residues exhibit stringent sequence requirements in that nearly all residues in positions that contact zinc, the substrate, or the catalytic water do not tolerate amino acid substitutions. In addition, at high imipenem concentrations a number of residues that do not directly contact zinc or substrate are also essential and do not tolerate substitutions. Biochemical analysis confirmed that amino acid substitutions at essential positions decreased the stability or catalytic activity of the CphA enzyme. Therefore, the CphA active - site is fragile to substitutions, suggesting active-site residues are optimized for imipenem hydrolysis. These results also suggest that resistance to inhibitors targeted to the CphA active site would be slow to develop because of the strong sequence constraints on function.
Keywords: Aeromonas hydrophila; Amino Acid Sequence; Bacterial Proteins; Base Sequence; beta-Lactam Resistance; beta-Lactamases; Carbapenems; Catalytic Domain; Conserved Sequence; High-Throughput Nucleotide Sequencing; Hydrolysis; Kinetics; Mutation, Missense; Substrate Specificity

Diagnostic Yield of Clinical Tumor and Germline Whole-Exome Sequencing for Children With Solid Tumors. - Parsons, D Williams; Roy, Angshumoy; Yang, Yaping; Wang, Tao; Scollon, Sarah; Bergstrom, Katie; Kerstein, Robin A; Gutierrez, Stephanie; Petersen, Andrea K; Bavle, Abhishek; Lin, Frank Y; López-Terrada, Dolores H; et al. (JAMA Oncol, 2016)
IMPORTANCE: Whole-exome sequencing (WES) has the potential to reveal tumor and germline mutations of clinical relevance, but the diagnostic yield for pediatric patients with solid tumors is unknown. OBJECTIVE: To characterize the diagnostic yield of combined tumor and germline WES for children with solid tumors. DESIGN: Unselected children with newly diagnosed and previously untreated central nervous system (CNS) and non-CNS solid tumors were prospectively enrolled in the BASIC3 study at a large academic children's hospital during a 23-month period from August 2012 through June 2014. Blood and tumor samples underwent WES in a certified clinical laboratory with genetic results categorized on the basis of perceived clinical relevance and entered in the electronic health record. MAIN OUTCOMES AND MEASURES: Clinical categorization of somatic mutations; frequencies of deleterious germline mutations related to patient phenotype and incidental medically-actionable mutations. RESULTS: Of the first 150 participants (80 boys and 70 girls, mean age, 7.4 years), tumor samples adequate for WES were available from 121 patients (81%). Somatic mutations of established clinical utility (category I) were reported in 4 (3%) of 121 patients, with mutations of potential utility (category II) detected in an additional 29 (24%) of 121 patients. CTNNB1 was the gene most frequently mutated, with recurrent mutations in KIT, TSC2, and MAPK pathway genes (BRAF, KRAS, and NRAS) also identified. Mutations in consensus cancer genes (category III) were found in an additional 24 (20%) of 121 tumors. Fewer than half of somatic mutations identified were in genes known to be recurrently mutated in the tumor type tested. Diagnostic germline findings related to patient phenotype were discovered in 15 (10%) of 150 cases: 13 pathogenic or likely pathogenic dominant mutations in adult and pediatric cancer susceptibility genes (including 2 each in TP53, VHL, and BRCA1), 1 recessive liver disorder with hepatocellular carcinoma (TJP2), and 1 renal diagnosis (CLCN5). Incidental findings were reported in 8 (5%) of 150 patients. Most patients harbored germline uncertain variants in cancer genes (98%), pharmacogenetic variants (89%), and recessive carrier mutations (85%). CONCLUSIONS AND RELEVANCE: Tumor and germline WES revealed mutations in a broad spectrum of genes previously implicated in both adult and pediatric cancers. Combined reporting of tumor and germline WES identified diagnostic and/or potentially actionable findings in nearly 40% of newly diagnosed pediatric patients with solid tumors.

DNAism: exploring genomic datasets on the web with Horizon Charts. - Rio Deiros, David; Richard A Gibbs; Jeffrey Rogers (BMC Bioinformatics, 2016)
BACKGROUND: Computational biologists daily face the need to explore massive amounts of genomic data. New visualization techniques can help researchers navigate and understand these big data. Horizon Charts are a relatively new visualization method that, under the right circumstances, maximizes data density without losing graphical perception. RESULTS: Horizon Charts have been successfully applied to understand multi-metric time series data. We have adapted an existing JavaScript library (Cubism) that implements Horizon Charts for the time series domain so that it works effectively with genomic datasets. We call this new library DNAism. CONCLUSIONS: Horizon Charts can be an effective visual tool to explore complex and large genomic datasets. Researchers can use our library to leverage these techniques to extract additional insights from their own datasets.
Keywords: Computational Biology; Computer Graphics; Datasets as Topic; Gene Library; Genome, Human; Genomics; Humans; Internet; Software

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

The ethics of conducting molecular autopsies in cases of sudden death in the young. - McGuire, Amy L; Moore, Quianta; Majumder, Mary; Walkiewicz, Magdalena; Eng, Christine M; Belmont, John W; Nassef, Salma; Darilek, Sandra; Rutherford, Katie; Pereira, Stacey; Steven E Scherer; Sutton, V Reid; et al. (Genome Res, 2016)
Keywords: Autopsy; Child; Child, Preschool; Confidentiality; Consent Forms; Coroners and Medical Examiners; Disclosure; Ethics, Medical; Genetic Testing; Humans; Infant; Infant, Newborn

Exome sequencing in mostly consanguineous Arab families with neurologic disease provides a high potential molecular diagnosis rate. - Charng, Wu-Lin; Karaca, Ender; Coban Akdemir, Zeynep; Gambin, Tomasz; Atik, Mehmed M; Gu, Shen; Posey, Jennifer E; Jhangiani, Shalini N; Donna M Muzny; Harshavardhan Doddapaneni; Jianhong Hu; Eric Boerwinkle; et al. (BMC Med Genomics, 2016)
BACKGROUND: Neurodevelopment is orchestrated by a wide range of genes, and the genetic causes of neurodevelopmental disorders are thus heterogeneous. We applied whole exome sequencing (WES) for molecular diagnosis and in silico analysis to identify novel disease gene candidates in a cohort from Saudi Arabia with primarily Mendelian neurologic diseases. METHODS: We performed WES in 31 mostly consanguineous Arab families and analyzed both single nucleotide and copy number variants (CNVs) from WES data. Interaction/expression network and pathway analyses, as well as paralog studies were utilized to investigate potential pathogenicity and disease association of novel candidate genes. Additional cases for candidate genes were identified through the clinical WES database at Baylor Miraca Genetics Laboratories and GeneMatcher. RESULTS: We found known pathogenic or novel variants in known disease genes with phenotypic expansion in 6 families, disease-associated CNVs in 2 families, and 12 novel disease gene candidates in 11 families, including KIF5B, GRM7, FOXP4, MLLT1, and KDM2B. Overall, a potential molecular diagnosis was provided by variants in known disease genes in 17 families (54.8 %) and by novel candidate disease genes in an additional 11 families, making the potential molecular diagnostic rate ~90 %. CONCLUSIONS: Molecular diagnostic rate from WES is improved by exome-predicted CNVs. Novel candidate disease gene discovery is facilitated by paralog studies and through the use of informatics tools and available databases to identify additional evidence for pathogenicity. TRIAL REGISTRATION: Not applicable.
Keywords: Arabs; Cohort Studies; Consanguinity; Data Mining; Databases, Genetic; DNA Copy Number Variations; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Diagnostic Techniques; Nervous System Diseases; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Genome of the Asian longhorned beetle (Anoplophora glabripennis), a globally significant invasive species, reveals key functional and evolutionary innovations at the beetle-plant interface. - McKenna, Duane D; Scully, Erin D; Pauchet, Yannick; Hoover, Kelli; Kirsch, Roy; Geib, Scott M; Mitchell, Robert F; Waterhouse, Robert M; Ahn, Seung-Joon; Arsala, Deanna; Benoit, Joshua B; Blackmon, Heath; et al. (Genome Biol, 2016)
BACKGROUND: Relatively little is known about the genomic basis and evolution of wood-feeding in beetles. We undertook genome sequencing and annotation, gene expression assays, studies of plant cell wall degrading enzymes, and other functional and comparative studies of the Asian longhorned beetle, Anoplophora glabripennis, a globally significant invasive species capable of inflicting severe feeding damage on many important tree species. Complementary studies of genes encoding enzymes involved in digestion of woody plant tissues or detoxification of plant allelochemicals were undertaken with the genomes of 14 additional insects, including the newly sequenced emerald ash borer and bull-headed dung beetle. RESULTS: The Asian longhorned beetle genome encodes a uniquely diverse arsenal of enzymes that can degrade the main polysaccharide networks in plant cell walls, detoxify plant allelochemicals, and otherwise facilitate feeding on woody plants. It has the metabolic plasticity needed to feed on diverse plant species, contributing to its highly invasive nature. Large expansions of chemosensory genes involved in the reception of pheromones and plant kairomones are consistent with the complexity of chemical cues it uses to find host plants and mates. CONCLUSIONS: Amplification and functional divergence of genes associated with specialized feeding on plants, including genes originally obtained via horizontal gene transfer from fungi and bacteria, contributed to the addition, expansion, and enhancement of the metabolic repertoire of the Asian longhorned beetle, certain other phytophagous beetles, and to a lesser degree, other phytophagous insects. Our results thus begin to establish a genomic basis for the evolutionary success of beetles on plants.
Keywords: Animals; Coleoptera; Evolution, Molecular; Gene Transfer, Horizontal; Genome, Insect; Host-Parasite Interactions; Introduced Species; Larva; Sequence Analysis, DNA; Trees

Genome Sequencing of the Phytoseiid Predatory Mite Metaseiulus occidentalis Reveals Completely Atomized Hox Genes and Superdynamic Intron Evolution. - Hoy, Marjorie A; Waterhouse, Robert M; Wu, Ke; Estep, Alden S; Ioannidis, Panagiotis; Palmer, William J; Pomerantz, Aaron F; Simão, Felipe A; Thomas, Jainy; Jiggins, Francis M; Murphy, Terence D; Pritham, Ellen J; et al. (Genome Biol Evol, 2016)
Metaseiulus occidentalis is an eyeless phytoseiid predatory mite employed for the biological control of agricultural pests including spider mites. Despite appearances, these predator and prey mites are separated by some 400 Myr of evolution and radically different lifestyles. We present a 152-Mb draft assembly of the M. occidentalis genome: Larger than that of its favored prey, Tetranychus urticae, but considerably smaller than those of many other chelicerates, enabling an extremely contiguous and complete assembly to be built-the best arachnid to date. Aided by transcriptome data, genome annotation cataloged 18,338 protein-coding genes and identified large numbers of Helitron transposable elements. Comparisons with other arthropods revealed a particularly dynamic and turbulent genomic evolutionary history. Its genes exhibit elevated molecular evolution, with strikingly high numbers of intron gains and losses, in stark contrast to the deer tick Ixodes scapularis Uniquely among examined arthropods, this predatory mite's Hox genes are completely atomized, dispersed across the genome, and it encodes five copies of the normally single-copy RNA processing Dicer-2 gene. Examining gene families linked to characteristic biological traits of this tiny predator provides initial insights into processes of sex determination, development, immune defense, and how it detects, disables, and digests its prey. As the first reference genome for the Phytoseiidae, and for any species with the rare sex determination system of parahaploidy, the genome of the western orchard predatory mite improves genomic sampling of chelicerates and provides invaluable new resources for functional genomic analyses of this family of agriculturally important mites.
Keywords: Acari; Animals; Genes, Homeobox; Genome; Genomics; High-Throughput Nucleotide Sequencing; Introns; Pest Control, Biological; Tetranychidae; Transcriptome

Genome-culture coevolution promotes rapid divergence of killer whale ecotypes. - Foote, Andrew D; Vijay, Nagarjun; Ávila-Arcos, María C; Baird, Robin W; Durban, John W; Fumagalli, Matteo; Richard A Gibbs; Hanson, M Bradley; Korneliussen, Thorfinn S; Martin, Michael D; Robertson, Kelly M; Sousa, Vitor C; et al. (Nat Commun, 2016)
Analysing population genomic data from killer whale ecotypes, which we estimate have globally radiated within less than 250,000 years, we show that genetic structuring including the segregation of potentially functional alleles is associated with socially inherited ecological niche. Reconstruction of ancestral demographic history revealed bottlenecks during founder events, likely promoting ecological divergence and genetic drift resulting in a wide range of genome-wide differentiation between pairs of allopatric and sympatric ecotypes. Functional enrichment analyses provided evidence for regional genomic divergence associated with habitat, dietary preferences and post-zygotic reproductive isolation. Our findings are consistent with expansion of small founder groups into novel niches by an initial plastic behavioural response, perpetuated by social learning imposing an altered natural selection regime. The study constitutes an important step towards an understanding of the complex interaction between demographic history, culture, ecological adaptation and evolution at the genomic level.
Keywords: Adaptation, Biological; Animals; Biopsy; Ecotype; Evolution, Molecular; Female; Gene-Environment Interaction; Genetic Drift; Genetic Speciation; Genetic Variation; Genetics, Population; Genome; Genomics; Male; Phylogeny; Reproductive Isolation; Selection, Genetic; Skin; Sympatry; Whale, Killer

Genomic analyses identify molecular subtypes of pancreatic cancer. - Bailey, Peter; Chang, David K; Nones, Katia; Johns, Amber L; Patch, Ann-Marie; Marie-Claude Gingras; Miller, David K; Christ, Angelika N; Bruxner, Tim J C; Quinn, Michael C; Nourse, Craig; Murtaugh, L Charles; et al. (Nature, 2016)
Integrated genomic analysis of 456 pancreatic ductal adenocarcinomas identified 32 recurrently mutated genes that aggregate into 10 pathways: KRAS, TGF-β, WNT, NOTCH, ROBO/SLIT signalling, G1/S transition, SWI-SNF, chromatin modification, DNA repair and RNA processing. Expression analysis defined 4 subtypes: (1) squamous; (2) pancreatic progenitor; (3) immunogenic; and (4) aberrantly differentiated endocrine exocrine (ADEX) that correlate with histopathological characteristics. Squamous tumours are enriched for TP53 and KDM6A mutations, upregulation of the TP63∆N transcriptional network, hypermethylation of pancreatic endodermal cell-fate determining genes and have a poor prognosis. Pancreatic progenitor tumours preferentially express genes involved in early pancreatic development (FOXA2/3, PDX1 and MNX1). ADEX tumours displayed upregulation of genes that regulate networks involved in KRAS activation, exocrine (NR5A2 and RBPJL), and endocrine differentiation (NEUROD1 and NKX2-2). Immunogenic tumours contained upregulated immune networks including pathways involved in acquired immune suppression. These data infer differences in the molecular evolution of pancreatic cancer subtypes and identify opportunities for therapeutic development.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Carcinoma, Pancreatic Ductal; Cell Line, Tumor; DNA Methylation; DNA-Binding Proteins; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genes, Neoplasm; Genome, Human; Genomics; Hepatocyte Nuclear Factor 3-beta; Hepatocyte Nuclear Factor 3-gamma; Histone Demethylases; Homeobox Protein Nkx-2.2; Homeodomain Proteins; Humans; Mice; Mutation; Nuclear Proteins; Pancreatic Neoplasms; Prognosis; Receptors, Cytoplasmic and Nuclear; Survival Analysis; Trans-Activators; Transcription Factors; Transcription, Genetic; Transcriptome; Tumor Suppressor Protein p53; Tumor Suppressor Proteins; Zebrafish Proteins

Hutterite-type cataract maps to chromosome 6p21.32-p21.31, cosegregates with a homozygous mutation in LEMD2, and is associated with sudden cardiac death. - Boone, Philip M; Bo Yuan; Gu, Shen; Ma, Zhiwei; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Jain, Mahim; Murdock, Todd J; White, Janson J; Jhangiani, Shalini N; Kimberly Walker; Wang, Qiaoyan; et al. (Mol Genet Genomic Med, 2016)
BACKGROUND: Juvenile-onset cataracts are known among the Hutterites of North America. Despite being identified over 30 years ago, this autosomal recessive condition has not been mapped, and the disease gene is unknown. METHODS: We performed whole exome sequencing of three Hutterite-type cataract trios and follow-up genotyping and mapping in four extended kindreds. RESULTS: Trio exomes enabled genome-wide autozygosity mapping, which localized the disease gene to a 9.5-Mb region on chromosome 6p. This region contained two candidate variants, LEMD2 c.T38G and MUC21 c.665delC. Extended pedigrees recruited for variant genotyping revealed multiple additional relatives with juvenile-onset cataract, as well as six deceased relatives with both cataracts and sudden cardiac death. The candidate variants were genotyped in 84 family members, including 17 with cataracts; only the variant in LEMD2 cosegregated with cataracts (LOD = 9.62). SNP-based fine mapping within the 9.5 Mb linked region supported this finding by refining the cataract locus to a 0.5- to 2.9-Mb subregion (6p21.32-p21.31) containing LEMD2 but not MUC21. LEMD2 is expressed in mouse and human lenses and encodes a LEM domain-containing protein; the c.T38G missense mutation is predicted to mutate a highly conserved residue within this domain (p.Leu13Arg). CONCLUSION: We performed a genetic and genomic study of Hutterite-type cataract and found evidence for an association of this phenotype with sudden cardiac death. Using combined genetic and genomic approaches, we mapped cataracts to a small portion of chromosome 6 and propose that they result from a homozygous missense mutation in LEMD2.

A hybrid computational strategy to address WGS variant analysis in >5000 samples. - Huang, Zhuoyi; Rustagi, Navin; Veeraraghavan, Narayanan; Carroll, Andrew; Richard A Gibbs; Eric Boerwinkle; Venkata, Manjunath Gorentla; Fuli Yu (BMC Bioinformatics, 2016)
BACKGROUND: The decreasing costs of sequencing are driving the need for cost effective and real time variant calling of whole genome sequencing data. The scale of these projects are far beyond the capacity of typical computing resources available with most research labs. Other infrastructures like the cloud AWS environment and supercomputers also have limitations due to which large scale joint variant calling becomes infeasible, and infrastructure specific variant calling strategies either fail to scale up to large datasets or abandon joint calling strategies. RESULTS: We present a high throughput framework including multiple variant callers for single nucleotide variant (SNV) calling, which leverages hybrid computing infrastructure consisting of cloud AWS, supercomputers and local high performance computing infrastructures. We present a novel binning approach for large scale joint variant calling and imputation which can scale up to over 10,000 samples while producing SNV callsets with high sensitivity and specificity. As a proof of principle, we present results of analysis on Cohorts for Heart And Aging Research in Genomic Epidemiology (CHARGE) WGS freeze 3 dataset in which joint calling, imputation and phasing of over 5300 whole genome samples was produced in under 6 weeks using four state-of-the-art callers. The callers used were SNPTools, GATK-HaplotypeCaller, GATK-UnifiedGenotyper and GotCloud. We used Amazon AWS, a 4000-core in-house cluster at Baylor College of Medicine, IBM power PC Blue BioU at Rice and Rhea at Oak Ridge National Laboratory (ORNL) for the computation. AWS was used for joint calling of 180 TB of BAM files, and ORNL and Rice supercomputers were used for the imputation and phasing step. All other steps were carried out on the local compute cluster. The entire operation used 5.2 million core hours and only transferred a total of 6 TB of data across the platforms. CONCLUSIONS: Even with increasing sizes of whole genome datasets, ensemble joint calling of SNVs for low coverage data can be accomplished in a scalable, cost effective and fast manner by using heterogeneous computing platforms without compromising on the quality of variants.
Keywords: Databases, Genetic; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

Identification of Intellectual Disability Genes in Female Patients with a Skewed X-Inactivation Pattern. - Fieremans, Nathalie; Van Esch, Hilde; Holvoet, Maureen; Van Goethem, Gert; Devriendt, Koenraad; Rosello, Monica; Mayo, Sonia; Martinez, Francisco; Jhangiani, Shalini; Donna M Muzny; Richard A Gibbs; Lupski, James R; et al. (Hum Mutat, 2016)
Intellectual disability (ID) is a heterogeneous disorder with an unknown molecular etiology in many cases. Previously, X-linked ID (XLID) studies focused on males because of the hemizygous state of their X chromosome. Carrier females are generally unaffected because of the presence of a second normal allele, or inactivation of the mutant X chromosome in most of their cells (skewing). However, in female ID patients, we hypothesized that the presence of skewing of X-inactivation would be an indicator for an X chromosomal ID cause. We analyzed the X-inactivation patterns of 288 females with ID, and found that 22 (7.6%) had extreme skewing (>90%), which is significantly higher than observed in the general population (3.6%; P = 0.029). Whole-exome sequencing of 19 females with extreme skewing revealed causal variants in six females in the XLID genes DDX3X, NHS, WDR45, MECP2, and SMC1A. Interestingly, variants in genes escaping X-inactivation presumably cause both XLID and skewing of X-inactivation in three of these patients. Moreover, variants likely accounting for skewing only were detected in MED12, HDAC8, and TAF9B. All tested candidate causative variants were de novo events. Hence, extreme skewing is a good indicator for the presence of X-linked variants in female patients.
Keywords: Carrier Proteins; Cell Cycle Proteins; Chromosomal Proteins, Non-Histone; DEAD-box RNA Helicases; Exome; Female; Genetic Variation; Humans; Intellectual Disability; Membrane Proteins; Methyl-CpG-Binding Protein 2; Nuclear Proteins; Sequence Analysis, DNA; X Chromosome Inactivation

ITD assembler: an algorithm for internal tandem duplication discovery from short-read sequencing data. - Rustagi, Navin; Hampton, Oliver A; Li, Jie; Xi, Liu; Richard A Gibbs; Plon, Sharon E; Kimmel, Marek; Wheeler, David A (BMC Bioinformatics, 2016)
BACKGROUND: Detection of tandem duplication within coding exons, referred to as internal tandem duplication (ITD), remains challenging due to inefficiencies in alignment of ITD-containing reads to the reference genome. There is a critical need to develop efficient methods to recover these important mutational events. RESULTS: In this paper we introduce ITD Assembler, a novel approach that rapidly evaluates all unmapped and partially mapped reads from whole exome NGS data using a De Bruijn graphs approach to select reads that harbor cycles of appropriate length, followed by assembly using overlap-layout-consensus. We tested ITD Assembler on The Cancer Genome Atlas AML dataset as a truth set. ITD Assembler identified the highest percentage of reported FLT3-ITDs when compared to other ITD detection algorithms, and discovered additional ITDs in FLT3, KIT, CEBPA, WT1 and other genes. Evidence of polymorphic ITDs in 54 genes were also found. Novel ITDs were validated by analyzing the corresponding RNA sequencing data. CONCLUSIONS: ITD Assembler is a very sensitive tool which can detect partial, large and complex tandem duplications. This study highlights the need to more effectively look for ITD's in other cancers and Mendelian diseases.
Keywords: Algorithms; Exome; Exons; fms-Like Tyrosine Kinase 3; Humans; Leukemia, Myeloid, Acute; Molecular Diagnostic Techniques; Mutation; Tandem Repeat Sequences

Loss-of-function variants influence the human serum metabolome. - Yu, Bing; Li, Alexander H; Ginger A Metcalf; Donna M Muzny; Morrison, Alanna C; White, Simon; Mosley, Thomas H; Richard A Gibbs; Eric Boerwinkle (Sci Adv, 2016)
The metabolome is a collection of small molecules resulting from multiple cellular and biological processes that can act as biomarkers of disease, and African-Americans exhibit high levels of genetic diversity. Exome sequencing of a sample of deeply phenotyped African-Americans allowed us to analyze the effects of annotated loss-of-function (LoF) mutations on 308 serum metabolites measured by untargeted liquid and gas chromatography coupled with mass spectrometry. In an independent sample, we identified and replicated four genes harboring six LoF mutations that significantly affected five metabolites. These sites were related to a 19 to 45% difference in geometric mean metabolite levels, with an average effect size of 25%. We show that some of the affected metabolites are risk predictors or diagnostic biomarkers of disease and, using the principle of Mendelian randomization, are in the causal pathway of disease. For example, LoF mutations in SLCO1B1 elevate the levels of hexadecanedioate, a fatty acid significantly associated with increased blood pressure levels and risk of incident heart failure in both African-Americans and an independent sample of European-Americans. We show that SLCO1B1 LoF mutations significantly increase the risk of incident heart failure, thus implicating the metabolite in the causal pathway of disease. These results reveal new avenues into gene function and the understanding of disease etiology by integrating -omic technologies into a deeply phenotyped population study.
Keywords: Aged; Biomarkers; Black or African American; Exome; Female; Genetic Variation; Heart Failure; High-Throughput Nucleotide Sequencing; Humans; Hypertension; Liver-Specific Organic Anion Transporter 1; Male; Metabolome; Middle Aged; Mutation; Risk Factors; White People

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gozde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Membrane Proteins; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Multiallelic Positions in the Human Genome: Challenges for Genetic Analyses. - Campbell, Ian M; Gambin, Tomasz; Jhangiani, Shalini; Grove, Megan L; Veeraraghavan, Narayanan; Donna M Muzny; Shaw, Chad A; Richard A Gibbs; Eric Boerwinkle; Fuli Yu; Lupski, James R (Hum Mutat, 2016)
As the amount of human genomic sequence available from personal genomes and exomes has increased, so too has the observation of genomic positions having two or more alternative alleles, so-called multiallelic sites. For portions of the haploid genome that are present in more than one copy, including segmental duplications, variation at such multisite variant positions becomes even more complex. Despite the frequency of multiallelic variants, a number of commonly used resources and tools in genomic research and diagnostics do not support these multiallelic variants all together or require special modifications. Here, we explore the frequency of multiallelic sites in large samples with whole exome sequencing and discuss potential outcomes of failing to account for multiple variant alleles. We also briefly discuss some commonly utilized resources that fully support multiallelic sites.
Keywords: Alleles; Exome; Genome, Human; Humans

Multilevel Genomics-Based Taxonomy of Renal Cell Carcinoma. - Chen, Fengju; Zhang, Yiqun; Şenbabaoğlu, Yasin; Ciriello, Giovanni; Yang, Lixing; Reznik, Ed; Shuch, Brian; Micevic, Goran; De Velasco, Guillermo; Shinbrot, Eve; Noble, Michael S; Lu, Yiling; et al. (Cell Rep, 2016)
On the basis of multidimensional and comprehensive molecular characterization (including DNA methalylation and copy number, RNA, and protein expression), we classified 894 renal cell carcinomas (RCCs) of various histologic types into nine major genomic subtypes. Site of origin within the nephron was one major determinant in the classification, reflecting differences among clear cell, chromophobe, and papillary RCC. Widespread molecular changes associated with TFE3 gene fusion or chromatin modifier genes were present within a specific subtype and spanned multiple subtypes. Differences in patient survival and in alteration of specific pathways (including hypoxia, metabolism, MAP kinase, NRF2-ARE, Hippo, immune checkpoint, and PI3K/AKT/mTOR) could further distinguish the subtypes. Immune checkpoint markers and molecular signatures of T cell infiltrates were both highest in the subtype associated with aggressive clear cell RCC. Differences between the genomic subtypes suggest that therapeutic strategies could be tailored to each RCC disease subset.
Keywords: Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Carcinoma, Renal Cell; Chromatin; Gene Expression Profiling; Genomics; Humans; Kidney Neoplasms; MicroRNAs; Mutation; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; RNA, Messenger; Signal Transduction; Survival Rate; TOR Serine-Threonine Kinases

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis. - Gomez-Ospina, Natalia; Potter, Carol J; Xiao, Rui; Manickam, Kandamurugu; Kim, Mi-Sun; Kim, Kang Ho; Shneider, Benjamin L; Picarsic, Jennifer L; Jacobson, Theodora A; Zhang, Jing; He, Weimin; Liu, Pengfei; et al. (Nat Commun, 2016)
Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, persistent NR1H4-related cholestasis include neonatal onset with rapid progression to end-stage liver disease, vitamin K-independent coagulopathy, low-to-normal serum gamma-glutamyl transferase activity, elevated serum alpha-fetoprotein and undetectable liver bile salt export pump (ABCB11) expression. Our findings demonstrate a pivotal function for FXR in bile acid homeostasis and liver protection.
Keywords: ATP Binding Cassette Transporter, Subfamily B, Member 11; ATP-Binding Cassette Transporters; Bile Acids and Salts; Cholestasis, Intrahepatic; Female; Humans; Male; Mutation; Receptors, Cytoplasmic and Nuclear; Young Adult

An open access pilot freely sharing cancer genomic data from participants in Texas. - Becnel, Lauren B; Pereira, Stacey; Drummond, Jennifer A; Marie-Claude Gingras; Covington, Kyle R; Kovar, Christie L; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; McGuire, Amy L; Wheeler, David A; Richard A Gibbs (Sci Data, 2016)
Genomic data sharing in cancer has been restricted to aggregate or controlled-access initiatives to protect the privacy of research participants. By limiting access to these data, it has been argued that the autonomy of individuals who decide to participate in data sharing efforts has been superseded and the utility of the data as research and educational tools reduced. In a pilot Open Access (OA) project from the CPRIT-funded Texas Cancer Research Biobank, many Texas cancer patients were willing to openly share genomic data from tumor and normal matched pair specimens. For the first time, genetic data from 7 human cancer cases with matched normal are freely available without requirement for data use agreements nor any major restriction except that end users cannot attempt to re-identify the participants (http://txcrb.org/open.html).
Keywords: Access to Information; Biological Specimen Banks; Databases, Genetic; DNA, Neoplasm; Genome, Human; Humans; Information Dissemination; Pancreatic Neoplasms; Texas

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Donna M Muzny; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Eric Boerwinkle; Richard A Gibbs; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

Phenotypic Expansion of Congenital Disorder of Glycosylation Due to SRD5A3 Null Mutation. - Tuysuz, Beyhan; Pehlivan, Davut; Özkök, Ahmet; Jhangiani, Shalini; Yalcinkaya, Cengiz; Zeybek, Çiğdem Aktuğlu; Donna M Muzny; Lupski, James R; Richard A Gibbs; Jaeken, Jaak (JIMD Rep, 2016)
We present a boy, admitted at 4 months, with facial dysmorphism, hypertrichosis, loose skin, bilateral inguinal hernia, severe hypotonia, psychomotor disability, seizures with hypsarrhythmia (West syndrome), hepatosplenomegaly, increased serum transaminases, iris coloboma, glaucoma, corneal clouding and bilateral dilated lateral ventricles, and extra-axial post-cerebellar space. Serum transferrin isoelectrofocusing (IEF) showed a type 1 pattern. Whole-exome genotyping showed a previously reported homozygous nonsense mutation c.320G>A; p.Trp107X in SRD5A3. Epilepsy and glaucoma have been reported only once in the 19 described SRD5A3-congenital glycosylation defect patients, and corneal clouding not at all.

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

The population genomics of rhesus macaques (Macaca mulatta) based on whole-genome sequences. - Xue, Cheng; Raveendran, Muthuswamy; R. Alan Harris; Fawcett, Gloria L; Liu, Xiaoming; White, Simon; Dahdouli, Mahmoud; Rio Deiros, David; Below, Jennifer E; Salerno, William; Cox, Laura; Fan, Guoping; et al. (Genome Res, 2016)
Rhesus macaques (Macaca mulatta) are the most widely used nonhuman primate in biomedical research, have the largest natural geographic distribution of any nonhuman primate, and have been the focus of much evolutionary and behavioral investigation. Consequently, rhesus macaques are one of the most thoroughly studied nonhuman primate species. However, little is known about genome-wide genetic variation in this species. A detailed understanding of extant genomic variation among rhesus macaques has implications for the use of this species as a model for studies of human health and disease, as well as for evolutionary population genomics. Whole-genome sequencing analysis of 133 rhesus macaques revealed more than 43.7 million single-nucleotide variants, including thousands predicted to alter protein sequences, transcript splicing, and transcription factor binding sites. Rhesus macaques exhibit 2.5-fold higher overall nucleotide diversity and slightly elevated putative functional variation compared with humans. This functional variation in macaques provides opportunities for analyses of coding and noncoding variation, and its cellular consequences. Despite modestly higher levels of nonsynonymous variation in the macaques, the estimated distribution of fitness effects and the ratio of nonsynonymous to synonymous variants suggest that purifying selection has had stronger effects in rhesus macaques than in humans. Demographic reconstructions indicate this species has experienced a consistently large but fluctuating population size. Overall, the results presented here provide new insights into the population genomics of nonhuman primates and expand genomic information directly relevant to primate models of human disease.
Keywords: Animals; Evolution, Molecular; Female; Genetic Fitness; High-Throughput Nucleotide Sequencing; Macaca mulatta; Models, Animal; Polymorphism, Single Nucleotide; Population Density; Whole Genome Sequencing

Postmortem genetic screening for the identification, verification, and reporting of genetic variants contributing to the sudden death of the young. - Methner, D Nicole R; Steven E Scherer; Welch, Katherine; Walkiewicz, Magdalena; Eng, Christine M; Belmont, John W; Powell, Mark C; Korchina, Viktoriya; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Wolf, Dwayne A; et al. (Genome Res, 2016)
Each year in the United States, thousands of cases of sudden and unexpected deaths of infants, children, and young adults are assigned an undetermined cause of death after postmortem investigation and autopsy. Heritable genetic variants have been suggested as the cause of up to a third of sudden death (SD) cases. Elucidation of the genetic variants involved in SD cases is important to not only help establish cause and manner of death of these individuals, but to also aid in determining whether familial genetic testing should be considered. Previously, these types of postmortem screenings have not been a feasible option for most county medical examiners' and coroners' offices. We sequenced full exons of 64 genes associated with SD in the largest known cohort (351) of infant and young SD decedents using massively parallel sequencing at <$600 per sample. Genetic variants were assessed through literature review and clinical evaluation by a multidisciplinary consortium of experts. Thirteen individuals (3.7%), eight infants (2.8% of those <1 yr of age) and five children/young adults (7.0% of those >1 yr of age), were found to have a reportable genetic variant contributing to SD. These percentages represent an estimate lower than those previously reported. Overall yields and results likely vary between studies due to differences in evaluation techniques and reporting. Additionally, we recommend ongoing assessment of data, including nonreported novel variants, as technology and literature continually advance. This study demonstrates a strategy to implement molecular autopsies in medicolegal investigations of young SD decedents.
Keywords: Adolescent; Adult; Autopsy; Cardiomyopathies; Child; Child, Preschool; Death, Sudden; Diagnosis; Female; Genetic Testing; Genetic Variation; Humans; Infant; Infant, Newborn; Male; United States; Young Adult

A potential founder variant in in three Norwegian families with warts, molluscum contagiosum, and T-cell dysfunction. - Sorte, Hanne S; Osnes, Liv T; Fevang, Børre; Aukrust, Pål; Erichsen, Hans C; Backe, Paul H; Abrahamsen, Tore G; Kittang, Ole B; Øverland, Torstein; Jhangiani, Shalini N; Donna M Muzny; Vigeland, Magnus D; et al. (Mol Genet Genomic Med, 2016)
BACKGROUND: Four patients from three Norwegian families presented with a common skin phenotype of warts, molluscum contagiosum, and dermatitis since early childhood, and various other immunological features. Warts are a common manifestation of (HPV), but when they are overwhelming, disseminated and/or persistent, and presenting together with other immunological features, a primary immunodeficiency disease (PIDD) may be suspected. METHODS AND RESULTS: The four patients were exome sequenced as part of a larger study for detecting genetic causes of primary immunodeficiencies. No disease-causing variants were identified in known primary immunodeficiency genes or in other disease-related OMIM genes. However, the same homozygous missense variant in (also known as ) was identified in all four patients. In each family, the variant was located within a narrow region of homozygosity, representing a potential region of autozygosity. is a protein of undetermined function. A role in T-cell activation has been suggested and the mouse protein homolog (Rltpr) is essential for costimulation of T-cell activation via CD28, and for the development of regulatory T cells. Immunophenotyping demonstrated reduced regulatory, CD4+ memory, and CD4+ follicular T cells in all four patients. In addition, they all seem to have a deficiency in IFN -synthesis in CD4+ T cells and NK cells. CONCLUSIONS: We report a novel primary immunodeficiency, and a differential molecular diagnosis to ,,,,,,, and related diseases. The specific variant may represent a Norwegian founder variant segregating on a population-specific haplotype.

Rare Exome Sequence Variants in CLCN6 Reduce Blood Pressure Levels and Hypertension Risk. - Yu, Bing; Pulit, Sara L; Hwang, Shih-Jen; Brody, Jennifer A; Amin, Najaf; Auer, Paul L; Bis, Joshua C; Eric Boerwinkle; Burke, Gregory L; Chakravarti, Aravinda; Correa, Adolfo; Dreisbach, Albert W; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: Rare genetic variants influence blood pressure (BP). METHODS AND RESULTS: Whole-exome sequencing was performed on DNA samples from 17 956 individuals of European ancestry and African ancestry (14 497, first-stage discovery and 3459, second-stage discovery) to examine the effect of rare variants on hypertension and 4 BP traits: systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Tests of ≈170 000 common variants (minor allele frequency, ≥1%; statistical significance, P≤2.9×10(-7)) and gene-based tests of rare variants (minor allele frequency, <1%; ≈17 000 genes; statistical significance, P≤1.5×10(-6)) were evaluated for each trait and ancestry, followed by multiethnic meta-analyses. In the first-stage discovery, rare coding variants (splicing, stop-gain, stop-loss, nonsynonymous variants, or indels) in CLCN6 were associated with lower diastolic BP (cumulative minor allele frequency, 1.3%; β=-3.20; P=4.1×10(-6)) and were independent of a nearby common variant (rs17367504) previously associated with BP. CLCN6 rare variants were also associated with lower systolic BP (β=-4.11; P=2.8×10(-4)), mean arterial pressure (β=-3.50; P=8.9×10(-6)), and reduced hypertension risk (odds ratio, 0.72; P=0.017). Meta-analysis of the 2-stage discovery samples showed that CLCN6 was associated with lower diastolic BP at exome-wide significance (cumulative minor allele frequency, 1.1%; β=-3.30; P=5.0×10(-7)). CONCLUSIONS: These findings implicate the effect of rare coding variants in CLCN6 in BP variation and offer new insights into BP regulation.
Keywords: Alleles; Black People; Blood Pressure; Chloride Channels; Exome; Female; Gene Frequency; Humans; Hypertension; Male; Risk Factors; White People

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic or Latino; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis; White People

The role of combined SNV and CNV burden in patients with distal symmetric polyneuropathy. - Pehlivan, Davut; Beck, Christine R; Okamoto, Yuji; Harel, Tamar; Akdemir, Zeynep H C; Jhangiani, Shalini N; Withers, Marjorie A; Goksungur, Meryem Tuba; Carvalho, Claudia M B; Czesnik, Dirk; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; et al. (Genet Med, 2016)
PURPOSE: Charcot-Marie-Tooth (CMT) disease is a heterogeneous group of genetic disorders of the peripheral nervous system. Copy-number variants (CNVs) contribute significantly to CMT, as duplication of PMP22 underlies the majority of CMT1 cases. We hypothesized that CNVs and/or single-nucleotide variants (SNVs) might exist in patients with CMT with an unknown molecular genetic etiology. METHODS: Two hundred patients with CMT, negative for both SNV mutations in several CMT genes and for CNVs involving PMP22, were screened for CNVs by high-resolution oligonucleotide array comparative genomic hybridization. Whole-exome sequencing was conducted on individuals with rare, potentially pathogenic CNVs. RESULTS: Putatively causative CNVs were identified in five subjects (~2.5%); four of the five map to known neuropathy genes. Breakpoint sequencing revealed Alu-Alu-mediated junctions as a predominant contributor. Exome sequencing identified MFN2 SNVs in two of the individuals. CONCLUSION: Neuropathy-associated CNV outside of the PMP22 locus is rare in CMT. Nevertheless, there is potential clinical utility in testing for CNVs and exome sequencing in CMT cases negative for the CMT1A duplication. These findings suggest that complex phenotypes including neuropathy can potentially be caused by a combination of SNVs and CNVs affecting more than one disease-associated locus and contributing to a mutational burden.Genet Med 18 5, 443-451.
Keywords: Adult; Age of Onset; Charcot-Marie-Tooth Disease; Child, Preschool; Comparative Genomic Hybridization; DNA Copy Number Variations; Exome; Female; Genetic Predisposition to Disease; GTP Phosphohydrolases; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Motor Neurons; Myelin P0 Protein; Myelin Proteins; Neural Conduction; Polymorphism, Single Nucleotide; Polyneuropathies

SV-STAT accurately detects structural variation via alignment to reference-based assemblies. - Davis, Caleb F; Ritter, Deborah I; Wheeler, David A; Wang, Hongmei; Ding, Yan; Dugan, Shannon P; Bainbridge, Matthew N; Donna M Muzny; Rao, Pulivarthi H; Man, Tsz-Kwong; Plon, Sharon E; Richard A Gibbs; et al. (Source Code Biol Med, 2016)
BACKGROUND: Genomic deletions, inversions, and other rearrangements known collectively as structural variations (SVs) are implicated in many human disorders. Technologies for sequencing DNA provide a potentially rich source of information in which to detect breakpoints of structural variations at base-pair resolution. However, accurate prediction of SVs remains challenging, and existing informatics tools predict rearrangements with significant rates of false positives or negatives. RESULTS: To address this challenge, we developed 'Structural Variation detection by STAck and Tail' (SV-STAT) which implements a novel scoring metric. The software uses this statistic to quantify evidence for structural variation in genomic regions suspected of harboring rearrangements. To demonstrate SV-STAT, we used targeted and genome-wide approaches. First, we applied a custom capture array followed by Roche/454 and SV-STAT to three pediatric B-lineage acute lymphoblastic leukemias, identifying five structural variations joining known and novel breakpoint regions. Next, we detected SVs genome-wide in paired-end Illumina data collected from additional tumor samples. SV-STAT showed predictive accuracy as high as or higher than leading alternatives. The software is freely available under the terms of the GNU General Public License version 3 at https://gitorious.org/svstat/svstat. CONCLUSIONS: SV-STAT works across multiple sequencing chemistries, paired and single-end technologies, targeted or whole-genome strategies, and it complements existing SV-detection software. The method is a significant advance towards accurate detection and genotyping of genomic rearrangements from DNA sequencing data.

A t(5;16) translocation is the likely driver of a syndrome with ambiguous genitalia, facial dysmorphism, intellectual disability, and speech delay. - Ozantürk, Ayşegül; Davis, Erica E; Aniko Sabo; Weiss, Marjan M; Donna M Muzny; Dugan-Perez, Shannon; Sistermans, Erik A; Richard A Gibbs; Özgül, Köksal R; Yalnızoglu, Dilek; Serdaroglu, Esra; Dursun, Ali; et al. (Cold Spring Harb Mol Case Stud, 2016)
Genetic studies grounded on monogenic paradigms have accelerated both gene discovery and molecular diagnosis. At the same time, complex genomic rearrangements are also appreciated as potent drivers of disease pathology. Here, we report two male siblings with a dysmorphic face, ambiguous genitalia, intellectual disability, and speech delay. Through quad-based whole-exome sequencing and concomitant molecular cytogenetic testing, we identified two copy-number variants (CNVs) in both affected individuals likely arising from a balanced translocation: a 13.5-Mb duplication on Chromosome 16 (16q23.1 → 16qter) and a 7.7-Mb deletion on Chromosome 5 (5p15.31 → 5pter), as well as a hemizygous missense variant in CXorf36 (also known as DIA1R). The 5p terminal deletion has been associated previously with speech delay, whereas craniofacial dysmorphia and genital/urinary anomalies have been reported in patients with a terminal duplication of 16q. However, dosage changes in either genomic region alone could not account for the overall clinical presentation in our family; functional testing of CXorf36 in zebrafish did not induce defects in neurogenesis or the craniofacial skeleton. Notably, literature and database analysis revealed a similar dosage disruption in two siblings with extensive phenotypic overlap with our patients. Taken together, our data suggest that dosage perturbation of genes within the two chromosomal regions likely drives the syndromic manifestations of our patients and highlight how multiple genetic lesions can contribute to complex clinical pathologies.

Targeted sequencing of genome wide significant loci associated with bone mineral density (BMD) reveals significant novel and rare variants: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study. - Hsu, Yi-Hsiang; Li, Guo; Liu, Ching-Ti; Brody, Jennifer A; Karasik, David; Chou, Wen-Chi; Demissie, Serkalem; Nandakumar, Kannabiran; Zhou, Yanhua; Cheng, Chia-Ho; Gill, Richard; Richard A Gibbs; et al. (Hum Mol Genet, 2016)
Bone mineral density (BMD) is a heritable phenotype that predicts fracture risk. We performed fine-mapping by targeted sequencing at WLS, MEF2C, ARHGAP1/F2 and JAG1 loci prioritized by eQTL and bioinformatic approaches among 56 BMD loci from our previous GWAS meta-analysis. Targeted sequencing was conducted in 1,291 Caucasians from the Framingham Heart Study ( n =  925) and Cardiovascular Health Study ( n =  366), including 206 women and men with extreme low femoral neck (FN) BMD. A total of 4,964 sequence variants (SNVs) were observed and 80% were rare with MAF <1%. The associations between previously identified SNPs in these loci and BMD, while nominally significant in sequenced participants, were no longer significant after multiple testing corrections. Conditional analyses did not find protein-coding variants that may be responsible for GWAS signals. On the other hand, in the sequenced subjects, we identified novel associations in WLS , ARHGAP1 , and 5' of MEF2C ( P- values < 8x10  -   5 ; false discovery rate (FDR) q-values < 0.01) that were much more strongly associated with BMD compared to the GWAS SNPs. These associated SNVs are less-common; independent from previous GWAS signals in the same loci; and located in gene regulatory elements. Our findings suggest that protein-coding variants in selected GWAS loci did not contribute to GWAS signals. By performing targeted sequencing in GWAS loci, we identified less-common and rare non-coding SNVs associated with BMD independently from GWAS common SNPs, suggesting both common and less-common variants may associate with disease risks and phenotypes in the same loci.
Keywords: Aging; Bone Density; Cardiovascular Diseases; Cohort Studies; Epidemiologic Studies; Female; Femur Neck; Genetic Predisposition to Disease; Genome-Wide Association Study; GTPase-Activating Proteins; Humans; Male; MEF2 Transcription Factors; Middle Aged; Polymorphism, Single Nucleotide

Two male sibs with severe micrognathia and a missense variant in MED12. - Prescott, Trine E; Kulseth, Mari Ann; Heimdal, Ketil R; Stadheim, Barbro; Hopp, Einar; Gambin, Tomasz; Coban Akdemir, Zeynep H; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lupski, James R; Stray-Pedersen, Asbjørg (Eur J Med Genet, 2016)
Missense variants in MED12 cause three partially overlapping dysmorphic X-linked intellectual disability (XLID) syndromes: Lujan-Fryns syndrome (also known as Lujan syndrome), FG syndrome (also known as Opitz-Kaveggia syndrome) and X-linked Ohdo syndrome. We report a family with two severely micrognathic male sibs, a 10½ year old boy and a fetus, in which hemizygosity for a previously unreported missense variant in exon 13 of MED12 (NM_005120.2), c.1862G > A, p.(Arg621Gln) was detected by whole exome sequencing. The affected sibs shared no other rare variant with relevance to the phenotype. X-chromosome inactivation in blood was completely skewed (100:0) in the unaffected heterozygous mother, most likely as a result of preferential inactivation of the X-chromosome harbouring the missense variant in MED12. Neither the unaffected brother nor the unaffected maternal grandfather carried the missense variant in MED12. In the 10½ year old boy, upper airway obstruction secondary to Pierre Robin sequence necessitated a tracheostomy for the first 10 months of life. He has mild to moderate intellectual disability and some dysmorphic features seen in MED12-related syndromes. In addition, he has a horizontal gaze paresis, anomalies of the inner ear, and a cervical block vertebra. This report contributes to the expanding phenotypic range associated with MED12-mutations.
Keywords: Exons; Genes, X-Linked; Genetic Association Studies; Genotype; Humans; Infant; Male; Mediator Complex; Micrognathism; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Severity of Illness Index; Siblings; Tomography, X-Ray Computed; X Chromosome Inactivation

Unique features of a global human ectoparasite identified through sequencing of the bed bug genome. - Benoit, Joshua B; Adelman, Zach N; Reinhardt, Klaus; Dolan, Amanda; Poelchau, Monica; Jennings, Emily C; Szuter, Elise M; Hagan, Richard W; Gujar, Hemant; Shukla, Jayendra Nath; Zhu, Fang; Mohan, M; et al. (Nat Commun, 2016)
The bed bug, Cimex lectularius, has re-established itself as a ubiquitous human ectoparasite throughout much of the world during the past two decades. This global resurgence is likely linked to increased international travel and commerce in addition to widespread insecticide resistance. Analyses of the C. lectularius sequenced genome (650 Mb) and 14,220 predicted protein-coding genes provide a comprehensive representation of genes that are linked to traumatic insemination, a reduced chemosensory repertoire of genes related to obligate hematophagy, host-symbiont interactions, and several mechanisms of insecticide resistance. In addition, we document the presence of multiple putative lateral gene transfer events. Genome sequencing and annotation establish a solid foundation for future research on mechanisms of insecticide resistance, human-bed bug and symbiont-bed bug associations, and unique features of bed bug biology that contribute to the unprecedented success of C. lectularius as a human ectoparasite.
Keywords: Animals; Bedbugs; Ectoparasitic Infestations; Feeding Behavior; Gene Transfer, Horizontal; Genome; Host-Parasite Interactions; Humans; Insecticide Resistance; Insecticides; Sequence Analysis, DNA

WGSA: an annotation pipeline for human genome sequencing studies. - Liu, Xiaoming; White, Simon; Peng, Bo; Johnson, Andrew D; Brody, Jennifer A; Li, Alexander H; Huang, Zhuoyi; Carroll, Andrew; Wei, Peng; Richard A Gibbs; Klein, Robert J; Eric Boerwinkle (J Med Genet, 2016)
Keywords: Cloud Computing; Genome, Human; Humans; Molecular Sequence Annotation; Sequence Analysis, DNA; Software

Whole exome sequencing identifies the first STRADA point mutation in a patient with polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE). - Bi, Weimin; Glass, Ian A; Donna M Muzny; Richard A Gibbs; Eng, Christine M; Yang, Yaping; Sun, Angela (Am J Med Genet A, 2016)
Polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE) is an ultra rare neurodevelopmental disorder characterized by severe, infantile-onset intractable epilepsy, neurocognitive delay, macrocephaly, and craniofacial dysmorphism. The molecular diagnosis of this condition has thus far only been made in 16 Old Order Mennonite patients carrying a homozygous 7 kb founder deletion of exons 9-13 of STRADA. We performed clinical whole exome sequencing (WES) on a 4-year-old Indian male with global developmental delay, history of failure to thrive, infantile spasms, repetitive behaviors, hypotonia, low muscle mass, marked joint laxity, and dysmorphic facial features including tall forehead, long face, arched eyebrows, small chin, wide mouth, and tented upper lip. A homozygous single nucleotide duplication, c.842dupA (p.D281fs), in exon 10 of STRADA was identified. Sanger sequencing confirmed the mutation in the individual and identified both parents as carriers. In light of the molecular discoveries, the patient's clinical phenotype was considered to be a good fit for PMSE. We identified for the first time a homozygous point mutation in STRADA causing PMSE. Additional bi-allelic mutations related to PMSE thus far have not been observed in Baylor ∼6,000 consecutive clinical WES cases, supporting the rarity of this disorder. Our findings may have treatment implications for the patient since previous studies have shown rapamycin as a potential therapeutic agent for the seizures and cognitive problems in PMSE patients. © 2016 Wiley Periodicals, Inc.
Keywords: Adaptor Proteins, Vesicular Transport; Child, Preschool; DNA Mutational Analysis; Epilepsy; Exome; Facies; Genetic Association Studies; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Megalencephaly; Pedigree; Phenotype; Physical Examination; Point Mutation; Polyhydramnios; Psychomotor Disorders; Syndrome

Whole Exome Sequencing in Atrial Fibrillation. - Lubitz, Steven A; Brody, Jennifer A; Bihlmeyer, Nathan A; Roselli, Carolina; Weng, Lu-Chen; Christophersen, Ingrid E; Alonso, Alvaro; Eric Boerwinkle; Richard A Gibbs; Bis, Joshua C; Cupples, L Adrienne; Mohler, Peter J; et al. (PLoS Genet, 2016)
Atrial fibrillation (AF) is a morbid and heritable arrhythmia. Over 35 genes have been reported to underlie AF, most of which were described in small candidate gene association studies. Replication remains lacking for most, and therefore the contribution of coding variation to AF susceptibility remains poorly understood. We examined whole exome sequencing data in a large community-based sample of 1,734 individuals with and 9,423 without AF from the Framingham Heart Study, Cardiovascular Health Study, Atherosclerosis Risk in Communities Study, and NHLBI-GO Exome Sequencing Project and meta-analyzed the results. We also examined whether genetic variation was enriched in suspected AF genes (N = 37) in AF cases versus controls. The mean age ranged from 59 to 73 years; 8,656 (78%) were of European ancestry. None of the 99,404 common variants evaluated was significantly associated after adjusting for multiple testing. Among the most significantly associated variants was a common (allele frequency = 86%) missense variant in SYNPO2L (rs3812629, p.Pro707Leu, [odds ratio 1.27, 95% confidence interval 1.13-1.43, P = 6.6x10-5]) which lies at a known AF susceptibility locus and is in linkage disequilibrium with a top marker from prior analyses at the locus. We did not observe significant associations between rare variants and AF in gene-based tests. Individuals with AF did not display any statistically significant enrichment for common or rare coding variation in previously implicated AF genes. In conclusion, we did not observe associations between coding genetic variants and AF, suggesting that large-effect coding variation is not the predominant mechanism underlying AF. A coding variant in SYNPO2L requires further evaluation to determine whether it is causally related to AF. Efforts to identify biologically meaningful coding variation underlying AF may require large sample sizes or populations enriched for large genetic effects.
Keywords: Aged; Atrial Fibrillation; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Microfilament Proteins; Middle Aged; Polymorphism, Single Nucleotide

Whole genome sequence analysis of serum amino acid levels. - Yu, Bing; de Vries, Paul S; Ginger A Metcalf; Wang, Zhe; Feofanova, Elena V; Liu, Xiaoming; Donna M Muzny; Wagenknecht, Lynne E; Richard A Gibbs; Morrison, Alanna C; Eric Boerwinkle (Genome Biol, 2016)
BACKGROUND: Blood levels of amino acids are important biomarkers of disease and are influenced by synthesis, protein degradation, and gene-environment interactions. Whole genome sequence analysis of amino acid levels may establish a paradigm for analyzing quantitative risk factors. RESULTS: In a discovery cohort of 1872 African Americans and a replication cohort of 1552 European Americans we sequenced exons and whole genomes and measured serum levels of 70 amino acids. Rare and low-frequency variants (minor allele frequency ≤5%) were analyzed by three types of aggregating motifs defined by gene exons, regulatory regions, or genome-wide sliding windows. Common variants (minor allele frequency >5%) were analyzed individually. Over all four analysis strategies, 14 gene-amino acid associations were identified and replicated. The 14 loci accounted for an average of 1.8% of the variance in amino acid levels, which ranged from 0.4 to 9.7%. Among the identified locus-amino acid pairs, four are novel and six have been reported to underlie known Mendelian conditions. These results suggest that there may be substantial genetic effects on amino acid levels in the general population that may underlie inborn errors of metabolism. We also identify a predicted promoter variant in AGA (the gene that encodes aspartylglucosaminidase) that is significantly associated with asparagine levels, with an effect that is independent of any observed coding variants. CONCLUSIONS: These data provide insights into genetic influences on circulating amino acid levels by integrating -omic technologies in a multi-ethnic population. The results also help establish a paradigm for whole genome sequence analysis of quantitative traits.
Keywords: Adult; Aged; Amino Acids; Biomarkers; Exons; Female; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Nucleotide Motifs; Polymorphism, Single Nucleotide; Population Surveillance; Regulatory Sequences, Nucleic Acid

The whole genome sequence of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), reveals insights into the biology and adaptive evolution of a highly invasive pest species. - Papanicolaou, Alexie; Schetelig, Marc F; Arensburger, Peter; Atkinson, Peter W; Benoit, Joshua B; Bourtzis, Kostas; Castañera, Pedro; Cavanaugh, John P; Chao, Hsu; Childers, Christopher; Curril, Ingrid; Dinh, Huyen; et al. (Genome Biol, 2016)
BACKGROUND: The Mediterranean fruit fly (medfly), Ceratitis capitata, is a major destructive insect pest due to its broad host range, which includes hundreds of fruits and vegetables. It exhibits a unique ability to invade and adapt to ecological niches throughout tropical and subtropical regions of the world, though medfly infestations have been prevented and controlled by the sterile insect technique (SIT) as part of integrated pest management programs (IPMs). The genetic analysis and manipulation of medfly has been subject to intensive study in an effort to improve SIT efficacy and other aspects of IPM control. RESULTS: The 479 Mb medfly genome is sequenced from adult flies from lines inbred for 20 generations. A high-quality assembly is achieved having a contig N50 of 45.7 kb and scaffold N50 of 4.06 Mb. In-depth curation of more than 1800 messenger RNAs shows specific gene expansions that can be related to invasiveness and host adaptation, including gene families for chemoreception, toxin and insecticide metabolism, cuticle proteins, opsins, and aquaporins. We identify genes relevant to IPM control, including those required to improve SIT. CONCLUSIONS: The medfly genome sequence provides critical insights into the biology of one of the most serious and widespread agricultural pests. This knowledge should significantly advance the means of controlling the size and invasive potential of medfly populations. Its close relationship to Drosophila, and other insect species important to agriculture and human health, will further comparative functional and structural studies of insect genomes that should broaden our understanding of gene family evolution.
Keywords: Animals; Animals, Genetically Modified; Biological Evolution; Ceratitis capitata; Genome, Insect; High-Throughput Nucleotide Sequencing; Humans; Introduced Species; Molecular Sequence Annotation; Pest Control, Biological

Is Whole-Exome Sequencing an Ethically Disruptive Technology? Perspectives of Pediatric Oncologists and Parents of Pediatric Patients With Solid Tumors. - McCullough, Laurence B; Slashinski, Melody J; McGuire, Amy L; Street, Richard L; Eng, Christine M; Richard A Gibbs; Parsons, D William; Plon, Sharon E (Pediatr Blood Cancer, 2016)
BACKGROUND: It has been anticipated that physician and parents will be ill prepared or unprepared for the clinical introduction of genome sequencing, making it ethically disruptive. PROCEDURE: As a part of the Baylor Advancing Sequencing in Childhood Cancer Care study, we conducted semistructured interviews with 16 pediatric oncologists and 40 parents of pediatric patients with cancer prior to the return of sequencing results. We elicited expectations and attitudes concerning the impact of sequencing on clinical decision making, clinical utility, and treatment expectations from both groups. Using accepted methods of qualitative research to analyze interview transcripts, we completed a thematic analysis to provide inductive insights into their views of sequencing. RESULTS: Our major findings reveal that neither pediatric oncologists nor parents anticipate sequencing to be an ethically disruptive technology, because they expect to be prepared to integrate sequencing results into their existing approaches to learning and using new clinical information for care. Pediatric oncologists do not expect sequencing results to be more complex than other diagnostic information and plan simply to incorporate these data into their evidence-based approach to clinical practice, although they were concerned about impact on parents. For parents, there is an urgency to protect their child's health and in this context they expect genomic information to better prepare them to participate in decisions about their child's care. CONCLUSIONS: Our data do not support the concern that introducing genome sequencing into childhood cancer care will be ethically disruptive, that is, leave physicians or parents ill prepared or unprepared to make responsible decisions about patient care.
Keywords: Child; Ethics, Medical; Exome; Humans; Interview, Psychological; Medical Oncology; Molecular Sequence Data; Neoplasms; Patients; Physicians

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)
Circulating blood cell counts and indices are important indicators of hematopoietic function and a number of clinical parameters, such as blood oxygen-carrying capacity, inflammation, and hemostasis. By performing whole-exome sequence association analyses of hematologic quantitative traits in 15,459 community-dwelling individuals, followed by in silico replication in up to 52,024 independent samples, we identified two previously undescribed coding variants associated with lower platelet count: a common missense variant in CPS1 (rs1047891, MAF = 0.33, discovery + replication p = 6.38 × 10(-10)) and a rare synonymous variant in GFI1B (rs150813342, MAF = 0.009, discovery + replication p = 1.79 × 10(-27)). By performing CRISPR/Cas9 genome editing in hematopoietic cell lines and follow-up targeted knockdown experiments in primary human hematopoietic stem and progenitor cells, we demonstrate an alternative splicing mechanism by which the GFI1B rs150813342 variant suppresses formation of a GFI1B isoform that preferentially promotes megakaryocyte differentiation and platelet production. These results demonstrate how unbiased studies of natural variation in blood cell traits can provide insight into the regulation of human hematopoiesis.
Keywords: Alternative Splicing; Blood Platelets; CRISPR-Cas Systems; DNA Mutational Analysis; Exome; Gene Editing; Genetic Loci; Hematopoiesis; Hematopoietic Stem Cells; Humans; Megakaryocytes; Platelet Count; Proto-Oncogene Proteins; Repressor Proteins

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Eric Boerwinkle; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Richard A Gibbs; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Whole-exome sequencing reveals an inherited R566X mutation of the epithelial sodium channel β-subunit in a case of early-onset phenotype of Liddle syndrome. - Polfus, Linda M; Eric Boerwinkle; Richard A Gibbs; Ginger A Metcalf; Donna M Muzny; Veeraraghavan, Narayanan; Grove, Megan; Shete, Sanjay; Wallace, Stephanie; Milewicz, Dianna; Hanchard, Neil; Lupski, James R; et al. (Cold Spring Harb Mol Case Stud, 2016)
To comprehensively evaluate a European-American child with severe hypertension, whole-exome sequencing (WES) was performed on the child and parents, which identified causal variation of the proband's early-onset disease. The proband's hypertension was resistant to treatment, requiring a multiple drug regimen including amiloride, spironolactone, and hydrochlorothiazide. We suspected a monogenic form of hypertension because of the persistent hypokalemia with low plasma levels of renin and aldosterone. To address this, we focused on rare functional variants and indels, and performed gene-based tests incorporating linkage scores and allele frequency and filtered on deleterious functional mutations. Drawing upon clinical presentation, 27 genes were selected evidenced to cause monogenic hypertension and matched to the gene-based results. This resulted in the identification of a stop-gain mutation in an epithelial sodium channel (ENaC), , an established Liddle syndrome gene, shared by the child and her father. Interestingly, the father also harbored a missense mutation (p.Trp552Arg) in the α-subunit of the ENaC trimer, , possibly pointing to pseudohypoaldosteronism type I. This case is unique in that we present the early-onset disease and treatment response caused by a canonical stop-gain mutation (p.Arg566*) as well as ENaC digenic hits in the father, emphasizing the utility of WES informing precision medicine.
Keywords: Adult; Aldosterone; Alleles; Amiloride; Child, Preschool; Epithelial Sodium Channels; Exome; Exome Sequencing; Female; Gene Frequency; Germ-Line Mutation; Humans; Hydrochlorothiazide; Hypertension; Hypokalemia; Liddle Syndrome; Male; Mutation; Mutation, Missense; Renin

16S gut community of the Cameron County Hispanic Cohort. - Ross, Matthew C; Donna M Muzny; McCormick, Joseph B; Richard A Gibbs; Fisher-Hoch, Susan P; Petrosino, Joseph F (Microbiome, 2015)
BACKGROUND: Obesity and type 2 diabetes (T2D) are major public health concerns worldwide, and their prevalence has only increased in recent years. Mexican Americans are disproportionately afflicted by obesity and T2D, and rates are even higher in the United States-Mexico border region. To determine the factors associated with the increased risk of T2D, obesity, and other diseases in this population, the Cameron County Hispanic Cohort was established in 2004. RESULTS: In this study, we characterized the 16S gut community of a subset of 63 subjects from this unique cohort. We found that these communities, when compared to Human Microbiome Project subjects, exhibit community shifts often observed in obese and T2D individuals in published studies. We also examined microbial network relationships between operational taxonomic units (OTUs) in the Cameron County Hispanic Cohort (CCHC) and three additional datasets. We identified a group of seven genera that form a tightly interconnected network present in all four tested datasets, dominated by butyrate producers, which are often increased in obese individuals while being depleted in T2D patients. CONCLUSIONS: Through a combination of increased disease prevalence and relatively high gut microbial homogeneity in the subset of CCHC members we examined, we believe that the CCHC may represent an ideal community to dissect mechanisms underlying the role of the gut microbiome in human health and disease. The lack of CCHC subject gut community segregation based on all tested metadata suggests that the community structure we observe in the CCHC likely occurs early in life, and endures. This persistent 'disease'-related gut microbial community in CCHC subjects may enhance existing genetic or lifestyle predispositions to the prevalent diseases of the CCHC, leading to increased attack rates of obesity, T2D, non-alcoholic fatty liver disease, and others.

Adult presentation of X-linked Conradi-Hünermann-Happle syndrome. - Posey, Jennifer E; Burrage, Lindsay C; Campeau, Philippe M; Lu, James T; Eble, Tanya N; Kratz, Lisa; Schlesinger, Alan E; Richard A Gibbs; Lee, Brendan H; Nagamani, Sandesh C S (Am J Med Genet A, 2015)
Conradi-Hünermann-Happle syndrome, or X-linked dominant chondrodysplasia punctata type 2 (CDPX2), is a genodermatosis caused by mutations in EBP. While typically lethal in males, females with CDPX2 generally manifest by infancy or childhood with variable features including congenital ichthyosiform erythroderma, chondrodysplasia punctata, asymmetric shortening of the long bones, and cataracts. We present a 36-year-old female with short stature, rhizomelic and asymmetric limb shortening, severe scoliosis, a sectorial cataract, and no family history of CDPX2. Whole exome sequencing (WES) revealed a p.Arg63del mutation in EBP, and biochemical studies confirmed a diagnosis of CDPX2. Short stature in combination with ichthyosis or alopecia, cataracts, and limb shortening in an adult should prompt consideration of a diagnosis of CDPX2. As in many genetic syndromes, the hallmark features of CDPX2 in pediatric patients are not readily identifiable in adults. This demonstrates the utility of WES as a diagnostic tool in the evaluation of adults with genetic disorders.
Keywords: Adult; Alopecia; Base Sequence; Black or African American; Cataract; Chondrodysplasia Punctata; Dwarfism; Exome; Female; Genes, X-Linked; Humans; Molecular Sequence Data; Sequence Deletion; Steroid Isomerases

Analysis of loss-of-function variants and 20 risk factor phenotypes in 8,554 individuals identifies loci influencing chronic disease. - Li, Alexander H; Morrison, Alanna C; Kovar, Christie; Cupples, L Adrienne; Brody, Jennifer A; Polfus, Linda M; Yu, Bing; Ginger A Metcalf; Donna M Muzny; Veeraraghavan, Narayanan; Liu, Xiaoming; Lumley, Thomas; et al. (Nat Genet, 2015)
A typical human exome harbors dozens of loss-of-function (LOF) variants, which can lower disease risk factor levels and affect drug efficacy. We hypothesized that LOF variants are enriched in genes influencing risk factor levels and the onset of common chronic diseases, such as cardiovascular disease and diabetes. To test this hypothesis, we sequenced the exomes of 8,554 individuals and analyzed the effects of predicted LOF variants on 20 chronic disease risk factor phenotypes. Analysis of this sample as discovery and replication strata of equal size verified two relationships in well-studied genes (PCSK9 and APOC3) and identified eight new loci. Previously unknown relationships included elevated fasting glucose in carriers of heterozygous LOF variation in TXNDC5, which encodes a biomarker for type 1 diabetes progression, and apparent recessive effects of C1QTNF8 on serum magnesium levels. These data demonstrate the utility of functional-variant annotation within a large sample of deeply phenotyped individuals for gene discovery.
Keywords: Atherosclerosis; Chronic Disease; Exome; Gene Frequency; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Humans; Molecular Sequence Annotation; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Assessing structural variation in a personal genome-towards a human reference diploid genome. - English, Adam C; Salerno, William J; Hampton, Oliver A; Gonzaga-Jauregui, Claudia; Ambreth, Shruthi; Ritter, Deborah I; Beck, Christine R; Davis, Caleb F; Dahdouli, Mahmoud; Ma, Singer; Carroll, Andrew; Veeraraghavan, Narayanan; et al. (BMC Genomics, 2015)
BACKGROUND: Characterizing large genomic variants is essential to expanding the research and clinical applications of genome sequencing. While multiple data types and methods are available to detect these structural variants (SVs), they remain less characterized than smaller variants because of SV diversity, complexity, and size. These challenges are exacerbated by the experimental and computational demands of SV analysis. Here, we characterize the SV content of a personal genome with Parliament, a publicly available consensus SV-calling infrastructure that merges multiple data types and SV detection methods. RESULTS: We demonstrate Parliament's efficacy via integrated analyses of data from whole-genome array comparative genomic hybridization, short-read next-generation sequencing, long-read (Pacific BioSciences RSII), long-insert (Illumina Nextera), and whole-genome architecture (BioNano Irys) data from the personal genome of a single subject (HS1011). From this genome, Parliament identified 31,007 genomic loci between 100 bp and 1 Mbp that are inconsistent with the hg19 reference assembly. Of these loci, 9,777 are supported as putative SVs by hybrid local assembly, long-read PacBio data, or multi-source heuristics. These SVs span 59 Mbp of the reference genome (1.8%) and include 3,801 events identified only with long-read data. The HS1011 data and complete Parliament infrastructure, including a BAM-to-SV workflow, are available on the cloud-based service DNAnexus. CONCLUSIONS: HS1011 SV analysis reveals the limits and advantages of multiple sequencing technologies, specifically the impact of long-read SV discovery. With the full Parliament infrastructure, the HS1011 data constitute a public resource for novel SV discovery, software calibration, and personal genome structural variation analysis.
Keywords: Computational Biology; Databases, Genetic; Diploidy; Genome, Human; Genomic Structural Variation; Humans; Sequence Analysis, DNA; Software

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; Black or African American; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; White People

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Donna M Muzny; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, Andre; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; Alleles; Black or African American; Coronary Disease; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation; White People

Autosomal-Dominant Multiple Pterygium Syndrome Is Caused by Mutations in MYH3. - Chong, Jessica X; Burrage, Lindsay C; Beck, Anita E; Marvin, Colby T; McMillin, Margaret J; Shively, Kathryn M; Harrell, Tanya M; Buckingham, Kati J; Bacino, Carlos A; Jain, Mahim; Alanay, Yasemin; Berry, Susan A; et al. (Am J Hum Genet, 2015)
Multiple pterygium syndrome (MPS) is a phenotypically and genetically heterogeneous group of rare Mendelian conditions characterized by multiple pterygia, scoliosis, and congenital contractures of the limbs. MPS typically segregates as an autosomal-recessive disorder, but rare instances of autosomal-dominant transmission have been reported. Whereas several mutations causing recessive MPS have been identified, the genetic basis of dominant MPS remains unknown. We identified four families affected by dominantly transmitted MPS characterized by pterygia, camptodactyly of the hands, vertebral fusions, and scoliosis. Exome sequencing identified predicted protein-altering mutations in embryonic myosin heavy chain (MYH3) in three families. MYH3 mutations underlie distal arthrogryposis types 1, 2A, and 2B, but all mutations reported to date occur in the head and neck domains. In contrast, two of the mutations found to cause MPS in this study occurred in the tail domain. The phenotypic overlap among persons with MPS, coupled with physical findings distinct from other conditions caused by mutations in MYH3, suggests that the developmental mechanism underlying MPS differs from that of other conditions and/or that certain functions of embryonic myosin might be perturbed by disruption of specific residues and/or domains. Moreover, the vertebral fusions in persons with MPS, coupled with evidence of MYH3 expression in bone, suggest that embryonic myosin plays a role in skeletal development.
Keywords: Arthrogryposis; Cytoskeletal Proteins; Exome; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Mutation; Myosins; Osteogenesis

Comparison and integration of deleteriousness prediction methods for nonsynonymous SNVs in whole exome sequencing studies. - Dong, Chengliang; Wei, Peng; Jian, Xueqiu; Richard A Gibbs; Eric Boerwinkle; Wang, Kai; Liu, Xiaoming (Hum Mol Genet, 2015)
Accurate deleteriousness prediction for nonsynonymous variants is crucial for distinguishing pathogenic mutations from background polymorphisms in whole exome sequencing (WES) studies. Although many deleteriousness prediction methods have been developed, their prediction results are sometimes inconsistent with each other and their relative merits are still unclear in practical applications. To address these issues, we comprehensively evaluated the predictive performance of 18 current deleteriousness-scoring methods, including 11 function prediction scores (PolyPhen-2, SIFT, MutationTaster, Mutation Assessor, FATHMM, LRT, PANTHER, PhD-SNP, SNAP, SNPs&GO and MutPred), 3 conservation scores (GERP++, SiPhy and PhyloP) and 4 ensemble scores (CADD, PON-P, KGGSeq and CONDEL). We found that FATHMM and KGGSeq had the highest discriminative power among independent scores and ensemble scores, respectively. Moreover, to ensure unbiased performance evaluation of these prediction scores, we manually collected three distinct testing datasets, on which no current prediction scores were tuned. In addition, we developed two new ensemble scores that integrate nine independent scores and allele frequency. Our scores achieved the highest discriminative power compared with all the deleteriousness prediction scores tested and showed low false-positive prediction rate for benign yet rare nonsynonymous variants, which demonstrated the value of combining information from multiple orthologous approaches. Finally, to facilitate variant prioritization in WES studies, we have pre-computed our ensemble scores for 87 347 044 possible variants in the whole-exome and made them publicly available through the ANNOVAR software and the dbNSFP database.
Keywords: Computational Biology; Exome; Genome, Human; Humans; Polymorphism, Single Nucleotide; Software

Convergent evolution of the genomes of marine mammals. - Foote, Andrew D; Liu, Yue; Thomas, Gregg W C; Vinar, Tomas; Alföldi, Jessica; Deng, Jixin; Dugan, Shannon; van Elk, Cornelis E; Hunter, Margaret E; Joshi, Vandita; Ziad Khan; Kovar, Christie; et al. (Nat Genet, 2015)
Marine mammals from different mammalian orders share several phenotypic traits adapted to the aquatic environment and therefore represent a classic example of convergent evolution. To investigate convergent evolution at the genomic level, we sequenced and performed de novo assembly of the genomes of three species of marine mammals (the killer whale, walrus and manatee) from three mammalian orders that share independently evolved phenotypic adaptations to a marine existence. Our comparative genomic analyses found that convergent amino acid substitutions were widespread throughout the genome and that a subset of these substitutions were in genes evolving under positive selection and putatively associated with a marine phenotype. However, we found higher levels of convergent amino acid substitutions in a control set of terrestrial sister taxa to the marine mammals. Our results suggest that, whereas convergent molecular evolution is relatively common, adaptive molecular convergence linked to phenotypic convergence is comparatively rare.
Keywords: Adaptation, Physiological; Amino Acid Substitution; Animals; Evolution, Molecular; Genome; Humans; Mammals; Phenotype; Phylogeny; Selection, Genetic

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

Coronary heart disease and genetic variants with low phospholipase A2 activity. - Polfus, Linda M; Richard A Gibbs; Eric Boerwinkle (N Engl J Med, 2015)
Keywords: Aged; Black or African American; Coronary Disease; Exome; Female; Genetic Variation; Heterozygote; Humans; Male; Middle Aged; Mutation; Phospholipases A2; Risk Factors; White People

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

The distribution and mutagenesis of short coding INDELs from 1,128 whole exomes. - Challis, Danny; Antunes, Lilian; Garrison, Erik; Banks, Eric; Evani, Uday S; Donna M Muzny; Poplin, Ryan; Richard A Gibbs; Marth, Gábor; Fuli Yu (BMC Genomics, 2015)
BACKGROUND: Identifying insertion/deletion polymorphisms (INDELs) with high confidence has been intrinsically challenging in short-read sequencing data. Here we report our approach for improving INDEL calling accuracy by using a machine learning algorithm to combine call sets generated with three independent methods, and by leveraging the strengths of each individual pipeline. Utilizing this approach, we generated a consensus exome INDEL call set from a large dataset generated by the 1000 Genomes Project (1000G), maximizing both the sensitivity and the specificity of the calls. RESULTS: This consensus exome INDEL call set features 7,210 INDELs, from 1,128 individuals across 13 populations included in the 1000 Genomes Phase 1 dataset, with a false discovery rate (FDR) of about 7.0%. CONCLUSIONS: In our study we further characterize the patterns and distributions of these exonic INDELs with respect to density, allele length, and site frequency spectrum, as well as the potential mutagenic mechanisms of coding INDELs in humans.
Keywords: Computational Biology; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Human Genome Project; Humans; INDEL Mutation; Machine Learning; Mutagenesis

Do echinoderm genomes measure up? - Cameron, R Andrew; Kudtarkar, Parul; Gordon, Susan M; Worley, Kim C; Richard A Gibbs (Mar Genomics, 2015)
Echinoderm genome sequences are a corpus of useful information about a clade of animals that serve as research models in fields ranging from marine ecology to cell and developmental biology. Genomic information from echinoids has contributed to insights into the gene interactions that drive the developmental process at the molecular level. Such insights often rely heavily on genomic information and the kinds of questions that can be asked thus depend on the quality of the sequence information. Here we describe the history of echinoderm genomic sequence assembly and present details about the quality of the data obtained. All of the sequence information discussed here is posted on the echinoderm information web system, Echinobase.org.
Keywords: Animals; Echinodermata; Genome; History, 21st Century; Models, Genetic; Phylogeny; Sequence Analysis, DNA; Species Specificity; Transcriptome

DVL1 frameshift mutations clustering in the penultimate exon cause autosomal-dominant Robinow syndrome. - White, Janson; Mazzeu, Juliana F; Hoischen, Alexander; Jhangiani, Shalini N; Gambin, Tomasz; Alcino, Michele Calijorne; Penney, Samantha; Saraiva, Jorge M; Hove, Hanne; Skovby, Flemming; Kayserili, Hulya; Estrella, Elicia; et al. (Am J Hum Genet, 2015)
Robinow syndrome is a genetically heterogeneous disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features and for which both autosomal-recessive and autosomal-dominant inheritance patterns have been described. Causative variants in the non-canonical signaling gene WNT5A underlie a subset of autosomal-dominant Robinow syndrome (DRS) cases, but most individuals with DRS remain without a molecular diagnosis. We performed whole-exome sequencing in four unrelated DRS-affected individuals without coding mutations in WNT5A and found heterozygous DVL1 exon 14 mutations in three of them. Targeted Sanger sequencing in additional subjects with DRS uncovered DVL1 exon 14 mutations in five individuals, including a pair of monozygotic twins. In total, six distinct frameshift mutations were found in eight subjects, and all were heterozygous truncating variants within the penultimate exon of DVL1. In five families in which samples from unaffected parents were available, the variants were demonstrated to represent de novo mutations. All variant alleles are predicted to result in a premature termination codon within the last exon, escape nonsense-mediated decay (NMD), and most likely generate a C-terminally truncated protein with a distinct -1 reading-frame terminus. Study of the transcripts extracted from affected subjects' leukocytes confirmed expression of both wild-type and variant alleles, supporting the hypothesis that mutant mRNA escapes NMD. Genomic variants identified in our study suggest that truncation of the C-terminal domain of DVL1, a protein hypothesized to have a downstream role in the Wnt-5a non-canonical pathway, is a common cause of DRS.
Keywords: Adaptor Proteins, Signal Transducing; Amino Acid Sequence; Base Sequence; Craniofacial Abnormalities; Dishevelled Proteins; DNA Primers; Dwarfism; Exome; Exons; Frameshift Mutation; Gene Components; Humans; Limb Deformities, Congenital; Molecular Sequence Data; Phosphoproteins; Sequence Analysis, DNA; Urogenital Abnormalities

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

Exome sequencing identifies a homozygous C5orf42 variant in a Turkish kindred with oral-facial-digital syndrome type VI. - Bayram, Yavuz; Aydin, Hatip; Gambin, Tomasz; Akdemir, Zeynep Coban; Atik, Mehmed M; Karaca, Ender; Karaman, Ali; Pehlivan, Davut; Jhangiani, Shalini N; Richard A Gibbs; Lupski, James R (Am J Med Genet A, 2015)
Oral-facial-digital syndrome type VI (OFDVI) is a rare ciliopathy in the spectrum of Joubert syndrome (JS) and distinguished from other oral-facial-digital syndromes by metacarpal abnormalities with central polydactyly and by a molar tooth sign on cranial MRI. Additional characteristic features include short stature, micrognathia, posteriorly rotated low-set ears, hypertelorism, epicanthal folds, broad nasal tip, tongue hamartoma, upper lip notch, intraoral frenula, cleft lip/palate, and renal anomalies. Recently, novel mutations in C5orf42 were identified in 9 out of 11 OFDVI families. In a subsequent study C5orf42 was found to be mutated in only 2 out of 17 OFDVI probands while 28 patients with a pure JS phenotype also had pathogenic mutations of C5orf42. We report on two affected cousins diagnosed with OFDVI who were born from first degree cousin marriages. Whole exome sequencing (WES) identified a homozygous predicted damaging missense mutation (c.4034A > G; p.Gln1345Arg) in the C5orf42 gene. Our data contribute to the evidence that C5orf42 is one of the causative genes for OFDVI.
Keywords: Abnormalities, Multiple; Cerebellar Diseases; Cerebellum; Child; Cleft Palate; Exome; Eye Abnormalities; Female; Genetic Predisposition to Disease; Hamartoma; Homozygote; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Mutation; Orofaciodigital Syndromes; Phenotype; Retina; Turkey

Exome sequencing reveals homozygous TRIM2 mutation in a patient with early onset CMT and bilateral vocal cord paralysis. - Pehlivan, Davut; Coban Akdemir, Zeynep; Karaca, Ender; Bayram, Yavuz; Jhangiani, Shalini; Yildiz, Edibe Pembegul; Donna M Muzny; Uluc, Kayihan; Richard A Gibbs; Elcioglu, Nursel; Lupski, James R; Harel, Tamar (Hum Genet, 2015)
Charcot-Marie-Tooth disease is a heterogeneous group of inherited distal symmetric polyneuropathies associated with mutations in genes encoding components essential for normal functioning of the Schwann cell and axon. TRIM2, encoding a ligase that ubiquitinates the neurofilament light chain, was recently associated with early-onset neuropathy in a single patient. We report a TRIM2 homozygous missense mutation (c.2000A>C; p.D667A) in a patient with peripheral neuropathy and bilateral vocal cord paralysis, allowing for further delineation of the associated phenotypic spectrum.
Keywords: Adult; Charcot-Marie-Tooth Disease; Exome; Female; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant, Newborn; Male; Mutation, Missense; Nuclear Proteins; Vocal Cord Paralysis

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

The genomes of two key bumblebee species with primitive eusocial organization. - Sadd, Ben M; Barribeau, Seth M; Bloch, Guy; de Graaf, Dirk C; Dearden, Peter; Elsik, Christine G; Gadau, Jürgen; Grimmelikhuijzen, Cornelis J P; Hasselmann, Martin; Lozier, Jeffrey D; Robertson, Hugh M; Smagghe, Guy; et al. (Genome Biol, 2015)
BACKGROUND: The shift from solitary to social behavior is one of the major evolutionary transitions. Primitively eusocial bumblebees are uniquely placed to illuminate the evolution of highly eusocial insect societies. Bumblebees are also invaluable natural and agricultural pollinators, and there is widespread concern over recent population declines in some species. High-quality genomic data will inform key aspects of bumblebee biology, including susceptibility to implicated population viability threats. RESULTS: We report the high quality draft genome sequences of Bombus terrestris and Bombus impatiens, two ecologically dominant bumblebees and widely utilized study species. Comparing these new genomes to those of the highly eusocial honeybee Apis mellifera and other Hymenoptera, we identify deeply conserved similarities, as well as novelties key to the biology of these organisms. Some honeybee genome features thought to underpin advanced eusociality are also present in bumblebees, indicating an earlier evolution in the bee lineage. Xenobiotic detoxification and immune genes are similarly depauperate in bumblebees and honeybees, and multiple categories of genes linked to social organization, including development and behavior, show high conservation. Key differences identified include a bias in bumblebee chemoreception towards gustation from olfaction, and striking differences in microRNAs, potentially responsible for gene regulation underlying social and other traits. CONCLUSIONS: These two bumblebee genomes provide a foundation for post-genomic research on these key pollinators and insect societies. Overall, gene repertoires suggest that the route to advanced eusociality in bees was mediated by many small changes in many genes and processes, and not by notable expansion or depauperation.
Keywords: Animals; Bee Venoms; Bees; Behavior, Animal; Chemoreceptor Cells; Chromosome Mapping; Databases, Genetic; Evolution, Molecular; Female; Gene Expression Regulation; Gene Rearrangement; Genes, Insect; Genomics; Interspersed Repetitive Sequences; Male; Open Reading Frames; Polymorphism, Single Nucleotide; Selenoproteins; Sequence Analysis, DNA; Social Behavior; Species Specificity; Synteny

Genomic profiling of Sézary syndrome identifies alterations of key T cell signaling and differentiation genes. - Wang, Linghua; Ni, Xiao; Covington, Kyle R; Yang, Betty Y; Shiu, Jessica; Zhang, Xiang; Xi, Liu; Meng, Qingchang; Langridge, Timothy; Drummond, Jennifer; Donehower, Lawrence A; Harshavardhan Doddapaneni; et al. (Nat Genet, 2015)
Sézary syndrome is a rare leukemic form of cutaneous T cell lymphoma characterized by generalized redness, scaling, itching and increased numbers of circulating atypical T lymphocytes. It is rarely curable, with poor prognosis. Here we present a multiplatform genomic analysis of 37 patients with Sézary syndrome that implicates dysregulation of cell cycle checkpoint and T cell signaling. Frequent somatic alterations were identified in TP53, CARD11, CCR4, PLCG1, CDKN2A, ARID1A, RPS6KA1 and ZEB1. Activating CCR4 and CARD11 mutations were detected in nearly one-third of patients. ZEB1, encoding a transcription repressor essential for T cell differentiation, was deleted in over one-half of patients. IL32 and IL2RG were overexpressed in nearly all cases. Our results demonstrate profound disruption of key signaling pathways in Sézary syndrome and suggest potential targets for new therapies.
Keywords: Case-Control Studies; Cell Differentiation; Exome; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genetic Drift; Genomics; High-Throughput Nucleotide Sequencing; Humans; Lymphocyte Activation; Mutation; Prognosis; Sezary Syndrome; Signal Transduction; Skin Neoplasms; Survival Rate; T-Lymphocytes

Genomic signatures of cooperation and conflict in the social amoeba. - Ostrowski, Elizabeth A; Shen, Yufeng; Tian, Xiangjun; Sucgang, Richard; Jiang, Huaiyang; Qu, Jiaxin; Katoh-Kurasawa, Mariko; Brock, Debra A; Dinh, Christopher; Lara-Garduno, Fremiet; Lee, Sandra L; Kovar, Christie L; et al. (Curr Biol, 2015)
Cooperative systems are susceptible to invasion by selfish individuals that profit from receiving the social benefits but fail to contribute. These so-called "cheaters" can have a fitness advantage in the laboratory, but it is unclear whether cheating provides an important selective advantage in nature. We used a population genomic approach to examine the history of genes involved in cheating behaviors in the social amoeba Dictyostelium discoideum, testing whether these genes experience rapid evolutionary change as a result of conflict over spore-stalk fate. Candidate genes and surrounding regions showed elevated polymorphism, unusual patterns of linkage disequilibrium, and lower levels of population differentiation, but they did not show greater between-species divergence. The signatures were most consistent with frequency-dependent selection acting to maintain multiple alleles, suggesting that conflict may lead to stalemate rather than an escalating arms race. Our results reveal the evolutionary dynamics of cooperation and cheating and underscore how sequence-based approaches can be used to elucidate the history of conflicts that are difficult to observe directly.
Keywords: Dictyostelium; Evolution, Molecular; Genome, Protozoan; Genomics; Polymorphism, Genetic; Selection, Genetic

Germline mutations in shelterin complex genes are associated with familial glioma. - Bainbridge, Matthew N; Armstrong, Georgina N; Gramatges, M Monica; Bertuch, Alison A; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Lewis, Lora; Tombrello, Joseph; Tsavachidis, Spyros; Liu, Yanhong; Jalali, Ali; Plon, Sharon E; et al. (J Natl Cancer Inst, 2015)
Gliomas are the most common brain tumor, with several histological subtypes of various malignancy grade. The genetic contribution to familial glioma is not well understood. Using whole exome sequencing of 90 individuals from 55 families, we identified two families with mutations in POT1 (p.G95C, p.E450X), a member of the telomere shelterin complex, shared by both affected individuals in each family and predicted to impact DNA binding and TPP1 binding, respectively. Validation in a separate cohort of 264 individuals from 246 families identified an additional mutation in POT1 (p.D617Efs), also predicted to disrupt TPP1 binding. All families with POT1 mutations had affected members with oligodendroglioma, a specific subtype of glioma more sensitive to irradiation. These findings are important for understanding the origin of glioma and could have importance for the future diagnostics and treatment of glioma.
Keywords: Adult; Aged; Brain Neoplasms; Exome; Female; Genetic Predisposition to Disease; Germ-Line Mutation; Glioma; Humans; Male; Middle Aged; Oligodendroglioma; Pedigree; Shelterin Complex; Telomere-Binding Proteins

Global transcriptional disturbances underlie Cornelia de Lange syndrome and related phenotypes. - Bo Yuan; Pehlivan, Davut; Karaca, Ender; Patel, Nisha; Charng, Wu-Lin; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Sutton, V Reid; Yesil, Gozde; Bozdogan, Sevcan Tug; Tos, Tulay; Koparir, Asuman; et al. (J Clin Invest, 2015)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder that presents with extensive phenotypic variability, including facial dysmorphism, developmental delay/intellectual disability (DD/ID), abnormal extremities, and hirsutism. About 65% of patients harbor mutations in genes that encode subunits or regulators of the cohesin complex, including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. Wiedemann-Steiner syndrome (WDSTS), which shares CdLS phenotypic features, is caused by mutations in lysine-specific methyltransferase 2A (KMT2A). Here, we performed whole-exome sequencing (WES) of 2 male siblings clinically diagnosed with WDSTS; this revealed a hemizygous, missense mutation in SMC1A that was predicted to be deleterious. Extensive clinical evaluation and WES of 32 Turkish patients clinically diagnosed with CdLS revealed the presence of a de novo heterozygous nonsense KMT2A mutation in 1 patient without characteristic WDSTS features. We also identified de novo heterozygous mutations in SMC3 or SMC1A that affected RNA splicing in 2 independent patients with combined CdLS and WDSTS features. Furthermore, in families from 2 separate world populations segregating an autosomal-recessive disorder with CdLS-like features, we identified homozygous mutations in TAF6, which encodes a core transcriptional regulatory pathway component. Together, our data, along with recent transcriptome studies, suggest that CdLS and related phenotypes may be "transcriptomopathies" rather than cohesinopathies.
Keywords: Adolescent; Adult; Cell Cycle Proteins; Child; Child, Preschool; Chondroitin Sulfate Proteoglycans; Chromosomal Proteins, Non-Histone; Codon, Nonsense; De Lange Syndrome; Exome; Exonucleases; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Heterozygote; Histone Deacetylases; Histone-Lysine N-Methyltransferase; Humans; Infant; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Proteins; Repressor Proteins; Transcriptome

Hemichordate genomes and deuterostome origins. - Simakov, Oleg; Kawashima, Takeshi; Marlétaz, Ferdinand; Jenkins, Jerry; Koyanagi, Ryo; Mitros, Therese; Hisata, Kanako; Bredeson, Jessen; Shoguchi, Eiichi; Gyoja, Fuki; Yue, Jia-Xing; Chen, Yi-Chih; et al. (Nature, 2015)
Acorn worms, also known as enteropneust (literally, 'gut-breathing') hemichordates, are marine invertebrates that share features with echinoderms and chordates. Together, these three phyla comprise the deuterostomes. Here we report the draft genome sequences of two acorn worms, Saccoglossus kowalevskii and Ptychodera flava. By comparing them with diverse bilaterian genomes, we identify shared traits that were probably inherited from the last common deuterostome ancestor, and then explore evolutionary trajectories leading from this ancestor to hemichordates, echinoderms and chordates. The hemichordate genomes exhibit extensive conserved synteny with amphioxus and other bilaterians, and deeply conserved non-coding sequences that are candidates for conserved gene-regulatory elements. Notably, hemichordates possess a deuterostome-specific genomic cluster of four ordered transcription factor genes, the expression of which is associated with the development of pharyngeal 'gill' slits, the foremost morphological innovation of early deuterostomes, and is probably central to their filter-feeding lifestyle. Comparative analysis reveals numerous deuterostome-specific gene novelties, including genes found in deuterostomes and marine microbes, but not other animals. The putative functions of these genes can be linked to physiological, metabolic and developmental specializations of the filter-feeding ancestor.
Keywords: Animals; Chordata, Nonvertebrate; Conserved Sequence; Echinodermata; Evolution, Molecular; Genome; Multigene Family; Phylogeny; Signal Transduction; Synteny; Transforming Growth Factor beta

High-Quality Draft Genome Sequence of Francisella tularensis subsp. holarctica Strain OR96-0246. - Atkins, L M; Holder, M E; Ajami, N J; Ginger A Metcalf; Weissenberger, G M; Wang, M; Vee, V; Han, Y; Donna M Muzny; Richard A Gibbs; Petrosino, J F (Genome Announc, 2015)
The bacterial pathogen Francisella tularensis was recently renewed as a tier-one select agent. F. tularensis subsp. tularensis (type A) and holarctica (type B) are of clinical relevance. Here, we report the complete genome of a virulent F. tularensis type B strain and describe its usefulness in comparative genomics.

Homozygous loss-of-function mutations in SOHLH1 in patients with nonsyndromic hypergonadotropic hypogonadism. - Bayram, Yavuz; Gulsuner, Suleyman; Guran, Tulay; Abaci, Ayhan; Yesil, Gozde; Gulsuner, Hilal Unal; Atay, Zeynep; Pierce, Sarah B; Gambin, Tomasz; Lee, Ming; Turan, Serap; Bober, Ece; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Hypergonadotropic hypogonadism presents in females with delayed or arrested puberty, primary or secondary amenorrhea due to gonadal dysfunction, and is further characterized by elevated gonadotropins and low sex steroids. Chromosomal aberrations and various specific gene defects can lead to hypergonadotropic hypogonadism. Responsible genes include those with roles in gonadal development or maintenance, sex steroid synthesis, or end-organ resistance to gonadotropins. Identification of novel causative genes in this disorder will contribute to our understanding of the regulation of human reproductive function. OBJECTIVES: The aim of this study was to identify and report the gene responsible for autosomal-recessive hypergonadotropic hypogonadism in two unrelated families. DESIGN AND PARTICIPANTS: Clinical evaluation and whole-exome sequencing were performed in two pairs of sisters with nonsyndromic hypergonadotropic hypogonadism from two unrelated families. RESULTS: Exome sequencing analysis revealed two different truncating mutations in the same gene: SOHLH1 c.705delT (p.Pro235fs*4) and SOHLH1 c.27C>G (p.Tyr9stop). Both mutations were unique to the families and segregation was consistent with Mendelian expectations for an autosomal-recessive mode of inheritance. CONCLUSIONS: Sohlh1 was known from previous mouse studies to be a transcriptional regulator that functions in the maintenance and survival of primordial ovarian follicles, but loss-of-function mutations in human females have not been reported. Our results provide evidence that homozygous-truncating mutations in SOHLH1 cause female nonsyndromic hypergonadotropic hypogonadism.
Keywords: Adolescent; Basic Helix-Loop-Helix Transcription Factors; Child; Exome; Female; Homozygote; Humans; Hypogonadism; Mutation

Identifying gene disruptions in novel balanced de novo constitutional translocations in childhood cancer patients by whole-genome sequencing. - Ritter, Deborah I; Haines, Katherine; Cheung, Hannah; Davis, Caleb F; Lau, Ching C; Berg, Jonathan S; Brown, Chester W; Thompson, Patrick A; Richard A Gibbs; Wheeler, David A; Plon, Sharon E (Genet Med, 2015)
PURPOSE: We applied whole-genome sequencing (WGS) to children diagnosed with neoplasms and found to carry apparently balanced constitutional translocations to discover novel genic disruptions. METHODS: We applied the structural variation (SV) calling programs CREST, BreakDancer, SV-STAT, and CGAP-CNV, and we developed an annotative filtering strategy to achieve nucleotide resolution at the translocations. RESULTS: We identified the breakpoints for t(6;12)(p21.1;q24.31), disrupting HNF1A in a patient diagnosed with hepatic adenomas and maturity-onset diabetes of the young (MODY). Translocation as the disruptive event of HNF1A, a gene known to be involved in MODY3, has not been previously reported. In a subject with Hodgkin lymphoma and subsequent low-grade glioma, we identified t(5;18)(q35.1;q21.2), disrupting both SLIT3 and DCC, genes previously implicated in both glioma and lymphoma. CONCLUSION: These examples suggest that implementing clinical WGS in the diagnostic workup of patients with novel but apparently balanced translocations may reveal unanticipated disruption of disease-associated genes and aid in prediction of the clinical phenotype.
Keywords: Adenoma; Adult; Age Factors; Base Sequence; Child; Child, Preschool; Chromosome Breakpoints; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 18; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; DCC Receptor; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Female; Genetic Association Studies; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Liver Neoplasms; Male; Membrane Proteins; Molecular Sequence Data; Neoplasms; Polymorphism, Single Nucleotide; Receptors, Cell Surface; Translocation, Genetic; Tumor Suppressor Proteins

Loss of Function Mutations in NNT Are Associated With Left Ventricular Noncompaction. - Bainbridge, Matthew N; Davis, Erica E; Choi, Wen-Yee; Dickson, Amy; Martinez, Hugo R; Wang, Min; Dinh, Huyen; Donna M Muzny; Pignatelli, Ricardo; Katsanis, Nicholas; Eric Boerwinkle; Richard A Gibbs; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Left ventricular noncompaction (LVNC) is an autosomal-dominant, genetically heterogeneous cardiomyopathy with variable severity, which may co-occur with cardiac hypertrophy. METHODS AND RESULTS: Here, we generated whole exome sequence data from multiple members from 5 families with LVNC. In 4 of 5 families, the candidate causative mutation segregates with disease in known LVNC genes MYH7 and TPM1. Subsequent sequencing of MYH7 in a larger LVNC cohort identified 7 novel likely disease causing variants. In the fifth family, we identified a frameshift mutation in NNT, a nuclear-encoded mitochondrial protein, not implicated previously in human cardiomyopathies. Resequencing of NNT in additional LVNC families identified a second likely pathogenic missense allele. Suppression of nnt in zebrafish caused early ventricular malformation and contractility defects, probably driven by altered cardiomyocyte proliferation. In vivo complementation studies showed that mutant human NNT failed to rescue nnt morpholino-induced heart dysfunction, indicating a probable haploinsufficiency mechanism. CONCLUSIONS: Together, our data expand the genetic spectrum of LVNC and demonstrate how the intersection of whole exome sequence with in vivo functional studies can accelerate the identification of genes that drive human genetic disorders.
Keywords: Animals; Animals, Genetically Modified; Embryo, Nonmammalian; Exome; Family Health; Female; Frameshift Mutation; Genetic Complementation Test; Genetic Predisposition to Disease; Humans; Isolated Noncompaction of the Ventricular Myocardium; Luminescent Proteins; Male; Microscopy, Confocal; Mitochondrial Proteins; NADP Transhydrogenase, AB-Specific; Pedigree; Sequence Analysis, DNA; Zebrafish

Lucilia cuprina genome unlocks parasitic fly biology to underpin future interventions. - Anstead, Clare A; Korhonen, Pasi K; Young, Neil D; Hall, Ross S; Jex, Aaron R; Murali, Shwetha C; Hughes, Daniel S T; Lee, Siu F; Perry, Trent; Stroehlein, Andreas J; Ansell, Brendan R E; Breugelmans, Bert; et al. (Nat Commun, 2015)
Lucilia cuprina is a parasitic fly of major economic importance worldwide. Larvae of this fly invade their animal host, feed on tissues and excretions and progressively cause severe skin disease (myiasis). Here we report the sequence and annotation of the 458-megabase draft genome of Lucilia cuprina. Analyses of this genome and the 14,544 predicted protein-encoding genes provide unique insights into the fly's molecular biology, interactions with the host animal and insecticide resistance. These insights have broad implications for designing new methods for the prevention and control of myiasis.
Keywords: Animals; Diptera; Female; Gene Expression Regulation; Genome, Insect; Insect Proteins; Insecticide Resistance; Insecticides; Larva; Male; Transcriptome

The Matchmaker Exchange: a platform for rare disease gene discovery. - Philippakis, Anthony A; Azzariti, Danielle R; Beltran, Sergi; Brookes, Anthony J; Brownstein, Catherine A; Brudno, Michael; Brunner, Han G; Buske, Orion J; Carey, Knox; Doll, Cassie; Dumitriu, Sergiu; Dyke, Stephanie O M; et al. (Hum Mutat, 2015)
There are few better examples of the need for data sharing than in the rare disease community, where patients, physicians, and researchers must search for "the needle in a haystack" to uncover rare, novel causes of disease within the genome. Impeding the pace of discovery has been the existence of many small siloed datasets within individual research or clinical laboratory databases and/or disease-specific organizations, hoping for serendipitous occasions when two distant investigators happen to learn they have a rare phenotype in common and can "match" these cases to build evidence for causality. However, serendipity has never proven to be a reliable or scalable approach in science. As such, the Matchmaker Exchange (MME) was launched to provide a robust and systematic approach to rare disease gene discovery through the creation of a federated network connecting databases of genotypes and rare phenotypes using a common application programming interface (API). The core building blocks of the MME have been defined and assembled. Three MME services have now been connected through the API and are available for community use. Additional databases that support internal matching are anticipated to join the MME network as it continues to grow.
Keywords: Database Management Systems; Databases, Genetic; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Information Dissemination; Rare Diseases; Software

Mutations in COL27A1 cause Steel syndrome and suggest a founder mutation effect in the Puerto Rican population. - Gonzaga-Jauregui, Claudia; Gamble, Candace N; Bo Yuan; Penney, Samantha; Jhangiani, Shalini; Donna M Muzny; Richard A Gibbs; Lupski, James R; Hecht, Jacqueline T (Eur J Hum Genet, 2015)
Osteochondrodysplasias represent a large group of developmental structural disorders that can be caused by mutations in a variety of genes responsible for chondrocyte development, differentiation, mineralization and early ossification. The application of whole-exome sequencing to disorders apparently segregating as Mendelian traits has proven to be an effective approach to disease gene identification for conditions with unknown molecular etiology. We identified a homozygous missense variant p.(Gly697Arg) in COL27A1, in a family with Steel syndrome and no consanguinity. Interestingly, the identified variant seems to have arisen as a founder mutation in the Puerto Rican population.
Keywords: Amino Acid Sequence; Child, Preschool; Comparative Genomic Hybridization; Exome; Female; Fibrillar Collagens; Follow-Up Studies; Founder Effect; Genotype; Hispanic or Latino; Humans; Infant; Male; Molecular Sequence Data; Mutation; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Prostaglandins F; Puerto Rico; Sequence Alignment

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Donna M Muzny; Bo Yuan; Eric Boerwinkle; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic or Latino; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

PacBio-LITS: a large-insert targeted sequencing method for characterization of human disease-associated chromosomal structural variations. - Wang, Min; Beck, Christine R; English, Adam C; Meng, Qingchang; Buhay, Christian; Yi Han; Harshavardhan Doddapaneni; Fuli Yu; Eric Boerwinkle; Lupski, James R; Donna M Muzny; Richard A Gibbs (BMC Genomics, 2015)
BACKGROUND: Generation of long (>5 Kb) DNA sequencing reads provides an approach for interrogation of complex regions in the human genome. Currently, large-insert whole genome sequencing (WGS) technologies from Pacific Biosciences (PacBio) enable analysis of chromosomal structural variations (SVs), but the cost to achieve the required sequence coverage across the entire human genome is high. RESULTS: We developed a method (termed PacBio-LITS) that combines oligonucleotide-based DNA target-capture enrichment technologies with PacBio large-insert library preparation to facilitate SV studies at specific chromosomal regions. PacBio-LITS provides deep sequence coverage at the specified sites at substantially reduced cost compared with PacBio WGS. The efficacy of PacBio-LITS is illustrated by delineating the breakpoint junctions of low copy repeat (LCR)-associated complex structural rearrangements on chr17p11.2 in patients diagnosed with Potocki-Lupski syndrome (PTLS; MIM#610883). We successfully identified previously determined breakpoint junctions in three PTLS cases, and also were able to discover novel junctions in repetitive sequences, including LCR-mediated breakpoints. The new information has enabled us to propose mechanisms for formation of these structural variants. CONCLUSIONS: The new method leverages the cost efficiency of targeted capture-sequencing as well as the mappability and scaffolding capabilities of long sequencing reads generated by the PacBio platform. It is therefore suitable for studying complex SVs, especially those involving LCRs, inversions, and the generation of chimeric Alu elements at the breakpoints. Other genomic research applications, such as haplotype phasing and small insertion and deletion validation could also benefit from this technology.
Keywords: Chromosome Aberrations; Gene Library; Gene Rearrangement; Genetic Association Studies; Genomics; High-Throughput Nucleotide Sequencing; Humans; Workflow

Population genomic analysis of 962 whole genome sequences of humans reveals natural selection in non-coding regions. - Fuli Yu; Lu, Jian; Liu, Xiaoming; Gazave, Elodie; Chang, Diana; Raj, Srilakshmi; Hunter-Zinck, Haley; Blekhman, Ran; Arbiza, Leonardo; Van Hout, Cris; Morrison, Alanna; Johnson, Andrew D; et al. (PLoS One, 2015)
Whole genome analysis in large samples from a single population is needed to provide adequate power to assess relative strengths of natural selection across different functional components of the genome. In this study, we analyzed next-generation sequencing data from 962 European Americans, and found that as expected approximately 60% of the top 1% of positive selection signals lie in intergenic regions, 33% in intronic regions, and slightly over 1% in coding regions. Several detailed functional annotation categories in intergenic regions showed statistically significant enrichment in positively selected loci when compared to the null distribution of the genomic span of ENCODE categories. There was a significant enrichment of purifying selection signals detected in enhancers, transcription factor binding sites, microRNAs and target sites, but not on lincRNA or piRNAs, suggesting different evolutionary constraints for these domains. Loci in "repressed or low activity regions" and loci near or overlapping the transcription start site were the most significantly over-represented annotations among the top 1% of signals for positive selection.
Keywords: DNA, Intergenic; Genetic Loci; Humans; Metagenomics; Open Reading Frames; Polymorphism, Single Nucleotide

Rare variants in the notch signaling pathway describe a novel type of autosomal recessive Klippel-Feil syndrome. - Karaca, Ender; Yuregir, Ozge O; Bozdogan, Sevcan T; Aslan, Huseyin; Pehlivan, Davut; Jhangiani, Shalini N; Akdemir, Zeynep C; Gambin, Tomasz; Bayram, Yavuz; Atik, Mehmed M; Erdin, Serkan; Donna M Muzny; et al. (Am J Med Genet A, 2015)
Klippel-Feil syndrome is a rare disorder represented by a subgroup of segmentation defects of the vertebrae and characterized by fusion of the cervical vertebrae, low posterior hairline, and short neck with limited motion. Both autosomal dominant and recessive inheritance patterns were reported in families with Klippel-Feil. Mutated genes for both dominant (GDF6 and GDF3) and recessive (MEOX1) forms of Klippel-Feil syndrome have been shown to be involved in somite development via transcription regulation and signaling pathways. Heterotaxy arises from defects in proteins that function in the development of left-right asymmetry of the developing embryo. We describe a consanguineous family with a male proband who presents with classical Klippel-Feil syndrome together with heterotaxy (situs inversus totalis). The present patient also had Sprengel's deformity, deformity of the sternum, and a solitary kidney. Using exome sequencing, we identified a homozygous frameshift mutation (c.299delT; p.L100fs) in RIPPLY2, a gene shown to play a crucial role in somitogenesis and participate in the Notch signaling pathway via negatively regulating Tbx6. Our data confirm RIPPLY2 as a novel gene for autosomal recessive Klippel-Feil syndrome, and in addition-from a mechanistic standpoint-suggest the possibility that mutations in RIPPLY2 could also lead to heterotaxy. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescent; Base Sequence; Female; Humans; Klippel-Feil Syndrome; Male; Molecular Sequence Data; Mutation; Pedigree; Radiography; Receptors, Notch; Signal Transduction; Spine

Secondary findings and carrier test frequencies in a large multiethnic sample. - Gambin, Tomasz; Jhangiani, Shalini N; Below, Jennifer E; Campbell, Ian M; Wiszniewski, Wojciech; Donna M Muzny; Staples, Jeffrey; Morrison, Alanna C; Bainbridge, Matthew N; Penney, Samantha; McGuire, Amy L; Richard A Gibbs; et al. (Genome Med, 2015)
BACKGROUND: Besides its growing importance in clinical diagnostics and understanding the genetic basis of Mendelian and complex diseases, whole exome sequencing (WES) is a rich source of additional information of potential clinical utility for physicians, patients and their families. We analyzed the frequency and nature of single nucleotide variants (SNVs) considered secondary findings and recessive disease allele carrier status in the exomes of 8554 individuals from a large, randomly sampled cohort study and 2514 patients from a study of presumed Mendelian disease having undergone WES. METHODS: We used the same sequencing platform and data processing pipeline to analyze all samples and characterized the distributions of reported pathogenic (ClinVar, Human Gene Mutation Database (HGMD)) and predicted deleterious variants in the pre-specified American College of Medical Genetics and Genomics (ACMG) secondary findings and recessive disease genes in different ethnic groups. RESULTS: In the 56 ACMG secondary findings genes, the average number of predicted deleterious variants per individual was 0.74, and the mean number of ClinVar reported pathogenic variants was 0.06. We observed an average of 10 deleterious and 0.78 ClinVar reported pathogenic variants per individual in 1423 autosomal recessive disease genes. By repeatedly sampling pairs of exomes, 0.5 % of the randomly generated couples were at 25 % risk of having an affected offspring for an autosomal recessive disorder based on the ClinVar variants. CONCLUSIONS: By investigating reported pathogenic and novel, predicted deleterious variants we estimated the lower and upper limits of the population fraction for which exome sequencing may reveal additional medically relevant information. We suggest that the observed wide range for the lower and upper limits of these frequency numbers will be gradually reduced due to improvement in classification databases and prediction algorithms.

Structure and function of the healthy pre-adolescent pediatric gut microbiome. - Hollister, Emily B; Riehle, Kevin; Luna, Ruth Ann; Weidler, Erica M; Rubio-Gonzales, Michelle; Mistretta, Toni-Ann; Raza, Sabeen; Harshavardhan Doddapaneni; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; Petrosino, Joseph F; et al. (Microbiome, 2015)
BACKGROUND: The gut microbiome influences myriad host functions, including nutrient acquisition, immune modulation, brain development, and behavior. Although human gut microbiota are recognized to change as we age, information regarding the structure and function of the gut microbiome during childhood is limited. Using 16S rRNA gene and shotgun metagenomic sequencing, we characterized the structure, function, and variation of the healthy pediatric gut microbiome in a cohort of school-aged, pre-adolescent children (ages 7-12 years). We compared the healthy pediatric gut microbiome with that of healthy adults previously recruited from the same region (Houston, TX, USA). RESULTS: Although healthy children and adults harbored similar numbers of taxa and functional genes, their composition and functional potential differed significantly. Children were enriched in Bifidobacterium spp., Faecalibacterium spp., and members of the Lachnospiraceae, while adults harbored greater abundances of Bacteroides spp. From a functional perspective, significant differences were detected with respect to the relative abundances of genes involved in vitamin synthesis, amino acid degradation, oxidative phosphorylation, and triggering mucosal inflammation. Children's gut communities were enriched in functions which may support ongoing development, while adult communities were enriched in functions associated with inflammation, obesity, and increased risk of adiposity. CONCLUSIONS: Previous studies suggest that the human gut microbiome is relatively stable and adult-like after the first 1 to 3 years of life. Our results suggest that the healthy pediatric gut microbiome harbors compositional and functional qualities that differ from those of healthy adults and that the gut microbiome may undergo a more prolonged development than previously suspected.
Keywords: Adult; Age Factors; Biodiversity; Child; Cluster Analysis; DNA Barcoding, Taxonomic; Female; Gastrointestinal Microbiome; Healthy Volunteers; Humans; Male; Metagenome; RNA, Ribosomal, 16S

Structure-activity analysis of human ghrelin O-acyltransferase reveals chemical determinants of ghrelin selectivity and acyl group recognition. - Darling, Joseph E; Zhao, Feifei; Loftus, Rosemary J; Patton, Leslie M; Richard A Gibbs; Hougland, James L (Biochemistry, 2015)
Ghrelin O-acyltransferase (GOAT) is an integral membrane acyltransferase responsible for catalyzing a serine-octanoylation posttranslational modification within the peptide hormone ghrelin. Ghrelin requires this octanoylation for its biological activity in stimulating appetite and in regulating other physiological pathways involved in energy balance. Blocking ghrelin acylation using GOAT inhibitors is a new potential avenue to treat health conditions impacted by ghrelin signaling, such as obesity and diabetes. Designing novel and potent GOAT inhibitors as potential therapeutics requires insight into the interactions between the ghrelin and octanoyl coenzyme A substrates and the GOAT active site. Through structure-activity investigation of ghrelin-mimetic peptide substrates and inhibitors, we have analyzed the amino acid selectivity of the enzyme as well as the functional groups involved in substrate recognition by human GOAT (hGOAT). This analysis reveals that hGOAT both prefers and tolerates a distinct set of chemical properties at each position within the N-terminal sequence of ghrelin and that sequence elements downstream of the ghrelin N-terminal sequence contribute to ghrelin binding to hGOAT. We also found that the hGOAT active site exhibits a marked preference for binding an eight-carbon acyl chain, which potentially explains the biological observation of ghrelin octanoylation in light of the acyl donor promiscuity reported for GOAT. Bioinformatics analysis, guided by our reactivity data, supports the conclusion that ghrelin is a unique substrate for hGOAT within the human proteome, providing further justification for the ghrelin-hGOAT system as a desirable drug target. By defining an array of substrate-enzyme interactions used by hGOAT to bind, recognize, and acylate ghrelin, this study yields novel insight into the character of the hGOAT active site that can serve as a guide toward the rational design of hGOAT inhibitors.
Keywords: Acylation; Acyltransferases; Amino Acid Sequence; Animals; Cell Line; Ghrelin; Humans; Insecta; Molecular Sequence Data; Protein Binding; Structure-Activity Relationship

Tissue-specific transcriptome sequencing analysis expands the non-human primate reference transcriptome resource (NHPRTR). - Peng, Xinxia; Thierry-Mieg, Jean; Thierry-Mieg, Danielle; Nishida, Andrew; Pipes, Lenore; Bozinoski, Marjan; Thomas, Matthew J; Kelly, Sara; Weiss, Jeffrey M; Raveendran, Muthuswamy; Donna M Muzny; Richard A Gibbs; et al. (Nucleic Acids Res, 2015)
The non-human primate reference transcriptome resource (NHPRTR, available online at http://nhprtr.org/) aims to generate comprehensive RNA-seq data from a wide variety of non-human primates (NHPs), from lemurs to hominids. In the 2012 Phase I of the NHPRTR project, 19 billion fragments or 3.8 terabases of transcriptome sequences were collected from pools of ∼ 20 tissues in 15 species and subspecies. Here we describe a major expansion of NHPRTR by adding 10.1 billion fragments of tissue-specific RNA-seq data. For this effort, we selected 11 of the original 15 NHP species and subspecies and constructed total RNA libraries for the same ∼ 15 tissues in each. The sequence quality is such that 88% of the reads align to human reference sequences, allowing us to compute the full list of expression abundance across all tissues for each species, using the reads mapped to human genes. This update also includes improved transcript annotations derived from RNA-seq data for rhesus and cynomolgus macaques, two of the most commonly used NHP models and additional RNA-seq data compiled from related projects. Together, these comprehensive reference transcriptomes from multiple primates serve as a valuable community resource for genome annotation, gene dynamics and comparative functional analysis.
Keywords: Animals; Databases, Genetic; Gene Expression Profiling; Internet; Macaca; Molecular Sequence Annotation; Organ Specificity; Primates; Reference Standards; Sequence Alignment; Sequence Analysis, RNA

Whole Exome Sequencing Identifies an Adult-Onset Case of Methylmalonic Aciduria and Homocystinuria Type C (cblC) with Non-Syndromic Bull's Eye Maculopathy. - Collison, Frederick T; Xie, Yajing Angela; Gambin, Tomasz; Jhangiani, Shalini; Donna M Muzny; Richard A Gibbs; Lupski, James R; Fishman, Gerald A; Allikmets, Rando (Ophthalmic Genet, 2015)
BACKGROUND: Methylmalonic aciduria and homocystinuria type C (cblC), a disorder of vitamin B12 (cobalamin) metabolism caused by mutations in the MMACHC gene, presents with many systemic symptoms, including neurological, cognitive, psychiatric, and thromboembolic events. Retinal phenotypes, including maculopathy, pigmentary retinopathy, and optic atrophy are common in early onset form of the disease but are rare in adult onset forms. MATERIALS AND METHODS: An adult Hispanic female presented with decreased central vision, bilateral pericentral ring scotomas and bull's eye-appearing macular lesions at 28 years of age. Her medical history was otherwise unremarkable except for iron deficiency anemia and both urinary tract and kidney infections. Screening of the ABCA4 gene, mutations in which frequently cause bull's eye maculopathy, was negative. Subsequently, analysis with whole exome sequencing was performed. RESULTS: Whole exome sequencing discovered compound heterozygous mutations in MMACHC, c.G482A:p.Arg161Gln and c.270_271insA:p.Arg91Lysfs*14, which segregated with the disease in the family. The genetic diagnosis was confirmed by biochemical laboratory testing, showing highly elevated urine methylmalonic acid/creatinine and homocysteine levels, and suggesting disease management with hydroxycobalamin injections and carnitine supplementation. CONCLUSIONS: In summary, a unique case of an adult patient with bull's eye macular lesions and no clinically relevant systemic symptoms was diagnosed with cblC by genetic screening and follow-up biochemical laboratory tests.
Keywords: Adult; Carrier Proteins; Electroretinography; Exome; Female; Genetic Testing; Heterozygote; Homocystinuria; Humans; Macular Degeneration; Mutation; Oxidoreductases; Pedigree; Scotoma; Sequence Analysis, DNA; Tomography, Optical Coherence; Visual Acuity; Visual Fields; Vitamin B 12; Vitamin B 12 Deficiency; Vitamin B Complex

Whole-exome sequencing identifies homozygous GPR161 mutation in a family with pituitary stalk interruption syndrome. - Karaca, Ender; Buyukkaya, Ramazan; Pehlivan, Davut; Charng, Wu-Lin; Yaykasli, Kursat O; Bayram, Yavuz; Gambin, Tomasz; Withers, Marjorie; Atik, Mehmed M; Arslanoglu, Ilknur; Bolu, Semih; Erdin, Serkan; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Pituitary stalk interruption syndrome (PSIS) is a rare, congenital anomaly of the pituitary gland characterized by pituitary gland insufficiency, thin or discontinuous pituitary stalk, anterior pituitary hypoplasia, and ectopic positioning of the posterior pituitary gland (neurohypophysis). The clinical presentation of patients with PSIS varies from isolated growth hormone (GH) deficiency to combined pituitary insufficiency and accompanying extrapituitary findings. Mutations in HESX1, LHX4, OTX2, SOX3, and PROKR2 have been associated with PSIS in less than 5% of cases; thus, the underlying genetic etiology for the vast majority of cases remains to be determined. OBJECTIVE: We applied whole-exome sequencing (WES) to a consanguineous family with two affected siblings who have pituitary gland insufficiency and radiographic findings of hypoplastic (thin) pituitary gland, empty sella, ectopic neurohypophysis, and interrupted pitiutary stalk-characteristic clinical diagnostic findings of PSIS. DESIGN AND PARTICIPANTS: WES was applied to two affected and one unaffected siblings. RESULTS: WES of two affected and one unaffected sibling revealed a unique homozygous missense mutation in GPR161, which encodes the orphan G protein-coupled receptor 161, a protein responsible for transducing extracellular signals across the plasma membrane into the cell. CONCLUSION: Mutations of GPR161 may be implicated as a potential novel cause of PSIS.
Keywords: Adolescent; Child, Preschool; Exome; Female; Genome-Wide Association Study; Humans; Hypopituitarism; Mutation; Pituitary Gland; Receptors, G-Protein-Coupled

Whole-exome sequencing identifies novel homozygous mutation in NPAS2 in family with nonobstructive azoospermia. - Ramasamy, Ranjith; Bakırcıoğlu, M Emre; Cengiz, Cenk; Karaca, Ender; Scovell, Jason; Jhangiani, Shalini N; Akdemir, Zeynep C; Bainbridge, Matthew; Yu, Yao; Huff, Chad; Richard A Gibbs; Lupski, James R; et al. (Fertil Steril, 2015)
OBJECTIVE: To investigate the genetic cause of nonobstructive azoospermia (NOA) in a consanguineous Turkish family through homozygosity mapping followed by targeted exon/whole-exome sequencing to identify genetic variations. DESIGN: Whole-exome sequencing (WES). SETTING: Research laboratory. PATIENT(S): Two siblings in a consanguineous family with NOA. INTERVENTION(S): Validating all variants passing filter criteria with Sanger sequencing to confirm familial segregation and absence in the control population. MAIN OUTCOME MEASURE(S): Discovery of a mutation that could potentially cause NOA. RESULT(S): A novel nonsynonymous mutation in the neuronal PAS-2 domain (NPAS2) was identified in a consanguineous family from Turkey. This mutation in exon 14 (chr2: 101592000 C>G) of NPAS2 is likely a disease-causing mutation as it is predicted to be damaging, it is a novel variant, and it segregates with the disease. Family segregation of the variants showed the presence of the homozygous mutation in the three brothers with NOA and a heterozygous mutation in the mother as well as one brother and one sister who were both fertile. The mutation is not found in the single-nucleotide polymorphism database, the 1000 Genomes Project, the Baylor College of Medicine cohort of 500 Turkish patients (not a population-specific polymorphism), or the matching 50 fertile controls. CONCLUSION(S): With the use of WES we identified a novel homozygous mutation in NPAS2 as a likely disease-causing variant in a Turkish family diagnosed with NOA. Our data reinforce the clinical role of WES in the molecular diagnosis of highly heterogeneous genetic diseases for which conventional genetic approaches have previously failed to find a molecular diagnosis.
Keywords: Adult; Azoospermia; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Exome; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Nerve Tissue Proteins; Pedigree

Whole-exome sequencing points to considerable genetic heterogeneity of cerebral palsy. - McMichael, G; Bainbridge, M N; Haan, E; Corbett, M; Gardner, A; Thompson, S; van Bon, B W M; van Eyk, C L; Broadbent, J; Reynolds, C; O'Callaghan, M E; Nguyen, L S; et al. (Mol Psychiatry, 2015)
Cerebral palsy (CP) is a common, clinically heterogeneous group of disorders affecting movement and posture. Its prevalence has changed little in 50 years and the causes remain largely unknown. The genetic contribution to CP causation has been predicted to be ~2%. We performed whole-exome sequencing of 183 cases with CP including both parents (98 cases) or one parent (67 cases) and 18 singleton cases (no parental DNA). We identified and validated 61 de novo protein-altering variants in 43 out of 98 (44%) case-parent trios. Initial prioritization of variants for causality was by mutation type, whether they were known or predicted to be deleterious and whether they occurred in known disease genes whose clinical spectrum overlaps CP. Further, prioritization used two multidimensional frameworks-the Residual Variation Intolerance Score and the Combined Annotation-dependent Depletion score. Ten de novo mutations in three previously identified disease genes (TUBA1A (n=2), SCN8A (n=1) and KDM5C (n=1)) and in six novel candidate CP genes (AGAP1, JHDM1D, MAST1, NAA35, RFX2 and WIPI2) were predicted to be potentially pathogenic for CP. In addition, we identified four predicted pathogenic, hemizygous variants on chromosome X in two known disease genes, L1CAM and PAK3, and in two novel candidate CP genes, CD99L2 and TENM1. In total, 14% of CP cases, by strict criteria, had a potentially disease-causing gene variant. Half were in novel genes. The genetic heterogeneity highlights the complexity of the genetic contribution to CP. Function and pathway studies are required to establish the causative role of these putative pathogenic CP genes.
Keywords: Adult; Animals; Cerebral Palsy; Cohort Studies; Exome; Female; Gene Library; Genetic Heterogeneity; Genetic Predisposition to Disease; Gestational Age; Humans; Male; Mutation; Parents; Sequence Analysis, DNA

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Associations of NINJ2 sequence variants with incident ischemic stroke in the Cohorts for Heart and Aging in Genomic Epidemiology (CHARGE) consortium. - Bis, Joshua C; DeStefano, Anita; Liu, Xiaoming; Brody, Jennifer A; Choi, Seung Hoan; Verhaaren, Benjamin F J; Debette, Stephanie; Ikram, M Arfan; Shahar, Eyal; Butler, Kenneth R; Gottesman, Rebecca F; Donna M Muzny; et al. (PLoS One, 2014)
BACKGROUND: Stroke, the leading neurologic cause of death and disability, has a substantial genetic component. We previously conducted a genome-wide association study (GWAS) in four prospective studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and demonstrated that sequence variants near the NINJ2 gene are associated with incident ischemic stroke. Here, we sought to fine-map functional variants in the region and evaluate the contribution of rare variants to ischemic stroke risk. METHODS AND RESULTS: We sequenced 196 kb around NINJ2 on chromosome 12p13 among 3,986 European ancestry participants, including 475 ischemic stroke cases, from the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, and Framingham Heart Study. Meta-analyses of single-variant tests for 425 common variants (minor allele frequency [MAF] ≥ 1%) confirmed the original GWAS results and identified an independent intronic variant, rs34166160 (MAF = 0.012), most significantly associated with incident ischemic stroke (HR = 1.80, p = 0.0003). Aggregating 278 putatively-functional variants with MAF≤ 1% using count statistics, we observed a nominally statistically significant association, with the burden of rare NINJ2 variants contributing to decreased ischemic stroke incidence (HR = 0.81; p = 0.026). CONCLUSION: Common and rare variants in the NINJ2 region were nominally associated with incident ischemic stroke among a subset of CHARGE participants. Allelic heterogeneity at this locus, caused by multiple rare, low frequency, and common variants with disparate effects on risk, may explain the difficulties in replicating the original GWAS results. Additional studies that take into account the complex allelic architecture at this locus are needed to confirm these findings.
Keywords: Cell Adhesion Molecules, Neuronal; Female; Genetic Association Studies; Genetic Heterogeneity; Humans; Introns; Ischemia; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA; White People

Comparative primate genomics: emerging patterns of genome content and dynamics. - Jeffrey Rogers; Richard A Gibbs (Nat Rev Genet, 2014)
Advances in genome sequencing technologies have created new opportunities for comparative primate genomics. Genome assemblies have been published for various primate species, and analyses of several others are underway. Whole-genome assemblies for the great apes provide remarkable new information about the evolutionary origins of the human genome and the processes involved. Genomic data for macaques and other non-human primates offer valuable insights into genetic similarities and differences among species that are used as models for disease-related research. This Review summarizes current knowledge regarding primate genome content and dynamics, and proposes a series of goals for the near future.
Keywords: Animals; Base Sequence; Evolution, Molecular; Genetic Speciation; Genetic Variation; Genome; Genome, Human; Genomics; Humans; Primates

Comparative validation of the D. melanogaster modENCODE transcriptome annotation. - Chen, Zhen-Xia; Sturgill, David; Qu, Jiaxin; Jiang, Huaiyang; Park, Soo; Boley, Nathan; Suzuki, Ana Maria; Fletcher, Anthony R; Plachetzki, David C; FitzGerald, Peter C; Artieri, Carlo G; Atallah, Joel; et al. (Genome Res, 2014)
Accurate gene model annotation of reference genomes is critical for making them useful. The modENCODE project has improved the D. melanogaster genome annotation by using deep and diverse high-throughput data. Since transcriptional activity that has been evolutionarily conserved is likely to have an advantageous function, we have performed large-scale interspecific comparisons to increase confidence in predicted annotations. To support comparative genomics, we filled in divergence gaps in the Drosophila phylogeny by generating draft genomes for eight new species. For comparative transcriptome analysis, we generated mRNA expression profiles on 81 samples from multiple tissues and developmental stages of 15 Drosophila species, and we performed cap analysis of gene expression in D. melanogaster and D. pseudoobscura. We also describe conservation of four distinct core promoter structures composed of combinations of elements at three positions. Overall, each type of genomic feature shows a characteristic divergence rate relative to neutral models, highlighting the value of multispecies alignment in annotating a target genome that should prove useful in the annotation of other high priority genomes, especially human and other mammalian genomes that are rich in noncoding sequences. We report that the vast majority of elements in the annotation are evolutionarily conserved, indicating that the annotation will be an important springboard for functional genetic testing by the Drosophila community.
Keywords: Animals; Cluster Analysis; Computational Biology; Drosophila melanogaster; Evolution, Molecular; Exons; Female; Gene Expression Profiling; Genome, Insect; Humans; Male; Molecular Sequence Annotation; Nucleotide Motifs; Phylogeny; Position-Specific Scoring Matrices; Promoter Regions, Genetic; Reproducibility of Results; RNA Editing; RNA Splice Sites; RNA Splicing; Transcription Initiation Site; Transcriptome

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

Diagnosis of ALG12-CDG by exome sequencing in a case of severe skeletal dysplasia. - Murali, Chaya; Lu, James T; Jain, Mahim; Liu, David S; Lachman, Ralph; Richard A Gibbs; Lee, Brendan H; Cohn, Daniel; Campeau, Philippe M (Mol Genet Metab Rep, 2014)
Congenital Disorder of Glycosylation type Ig (ALG12-CDG) is part of a group of autosomal recessive conditions caused by deficiency of proteins involved in the assembly of dolichol-oligosaccharides used for protein N-glycosylation. In ALG12-CDG, the enzyme affected is encoded by the gene. Affected individuals present clinically with neurodevelopmental delay, growth retardation, immune deficiency, male genital hypoplasia, and cardiomyopathy. A total of six individuals have been reported in the literature. Here, we present an infant with rhizomelic short stature, talipes equinovarus, platyspondyly, and joint dislocations. The infant had marked underossification of the pubic bones. Exome sequencing was performed and two deletions, each resulting in frameshifts, were found in . A review of the literature revealed two infants with ALG12-CDG and a severe skeletal dysplasia, including under-ossification of cervical vertebrae, pubic bones, and knees; in addition to talipes equinovarus and rhizomelic short stature. The phenotype of the individual we describe resembles pseudodiastrophic dysplasia and we discuss similarities and differences between ALG12-CDG and pseudodiastrophic dysplasia. The differential diagnosis in selected undiagnosed skeletal dysplasias should include CDGs.

Draft genome sequences and description of Lactobacillus rhamnosus strains L31, L34, and L35. - Boonma, Prapaporn; Spinler, Jennifer K; Qin, Xiang; Jittaprasatsin, Chutima; Donna M Muzny; Harshavardhan Doddapaneni; Richard A Gibbs; Petrosino, Joe; Tumwasorn, Somying; Versalovic, James (Stand Genomic Sci, 2014)
Lactobacillus rhamnosus is a facultative, lactic acid bacterium in the phylum Firmicutes. Lactobacillus spp. are generally considered beneficial, and specific strains of L. rhamnosus are validated probiotics. We describe the draft genomes of three L. rhamnosus strains (L31, L34, and L35) isolated from the feces of Thai breastfed infants, which exhibit anti-inflammatory properties in vitro. The three genomes range between 2.8 - 2.9 Mb, and contain approximately 2,700 protein coding genes.

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

Effects of TP53 mutational status on gene expression patterns across 10 human cancer types. - Parikh, Neha; Hilsenbeck, Susan; Creighton, Chad J; Dayaram, Tajhal; Shuck, Ryan; Shinbrot, Eve; Xi, Liu; Richard A Gibbs; Wheeler, David A; Donehower, Lawrence A (J Pathol, 2014)
Mutations in the TP53 tumour suppressor gene occur in half of all human cancers, indicating its critical importance in inhibiting cancer development. Despite extensive studies, the mechanisms by which mutant p53 enhances tumour progression remain only partially understood. Here, using data from the Cancer Genome Atlas (TCGA), genomic and transcriptomic analyses were performed on 2256 tumours from 10 human cancer types. We show that tumours with TP53 mutations have altered gene expression profiles compared to tumours retaining two wild-type TP53 alleles. Among 113 known p53-up-regulated target genes identified from cell culture assays, 10 were consistently up-regulated in at least eight of 10 cancer types that retain both copies of wild-type TP53. RPS27L, CDKN1A (p21(CIP1)) and ZMAT3 were significantly up-regulated in all 10 cancer types retaining wild-type TP53. Using this p53-based expression analysis as a discovery tool, we used cell-based assays to identify five novel p53 target genes from genes consistently up-regulated in wild-type p53 cancers. Global gene expression analyses revealed that cell cycle regulatory genes and transcription factors E2F1, MYBL2 and FOXM1 were disproportionately up-regulated in many TP53 mutant cancer types. Finally, > 93% of tumours with a TP53 mutation exhibited greatly reduced wild-type p53 messenger expression, due to loss of heterozygosity or copy neutral loss of heterozygosity, supporting the concept of p53 as a recessive tumour suppressor. The data indicate that tumours with wild-type TP53 retain some aspects of p53-mediated growth inhibitory signalling through activation of p53 target genes and suppression of cell cycle regulatory genes.
Keywords: Biomarkers, Tumor; Cell Cycle Proteins; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Humans; Loss of Heterozygosity; Mutation; Neoplasms; RNA, Messenger; Signal Transduction; Transcription Factors; Tumor Suppressor Protein p53

Exome sequencing identifies a novel homozygous mutation in the phosphate transporter SLC34A1 in hypophosphatemia and nephrocalcinosis. - Rajagopal, Abbhirami; Braslavsky, Débora; Lu, James T; Kleppe, Soledad; Clément, Florencia; Cassinelli, Hamilton; Liu, David S; Liern, Jose Miguel; Vallejo, Graciela; Bergadá, Ignacio; Richard A Gibbs; Campeau, Phillipe M; et al. (J Clin Endocrinol Metab, 2014)
CONTEXT: Two Argentinean siblings (a boy and a girl) from a nonconsanguineous family presented with hypercalcemia, hypercalciuria, hypophosphatemia, low parathyroid hormone (PTH), and nephrocalcinosis. OBJECTIVE: The goal of this study was to identify genetic causes of the clinical findings in the two siblings. DESIGN: Whole exome sequencing was performed to identify disease-causing mutations in the youngest sibling, and a candidate variant was screened in other family members by Sanger sequencing. In vitro experiments were conducted to determine the effects of the mutation that was identified. PATIENTS AND OTHER PARTICIPANTS: Affected siblings (2 y.o. female and 10 y.o male) and their parents were included in the study. Informed consent was obtained for genetic studies. RESULTS: A novel homozygous mutation in the gene encoding the renal sodium-dependent phosphate transporter SLC34A1 was identified in both siblings (c.1484G>A, p.Arg495His). In vitro studies showed that the p.Arg495His mutation resulted in decreased phosphate uptake when compared to wild-type SLC34A1. CONCLUSIONS: The homozygous G>A transition that results in the substitution of histidine for arginine at position 495 of the renal sodium-dependent phosphate transporter, SLC34A1, is involved in disease pathogenesis in these patients. Our report of the second family with two mutated SLC34A1 alleles expands the known phenotype of this rare condition.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Exome; Female; Humans; Hypercalcemia; Hypercalciuria; Hypophosphatemia; Male; Mutation; Nephrocalcinosis; Parathyroid Hormone; Pedigree; Phenotype; Sodium-Phosphate Cotransporter Proteins, Type IIa

Exonic duplication CNV of NDRG1 associated with autosomal-recessive HMSN-Lom/CMT4D. - Okamoto, Yuji; Goksungur, Meryem Tuba; Pehlivan, Davut; Beck, Christine R; Gonzaga-Jauregui, Claudia; Donna M Muzny; Atik, Mehmed M; Carvalho, Claudia M B; Matur, Zeliha; Bayraktar, Serife; Boone, Philip M; Akyuz, Kaya; et al. (Genet Med, 2014)
PURPOSE: Copy-number variations as a mutational mechanism contribute significantly to human disease. Approximately one-half of the patients with Charcot-Marie-Tooth (CMT) disease have a 1.4 Mb duplication copy-number variation as the cause of their neuropathy. However, non-CMT1A neuropathy patients rarely have causative copy-number variations, and to date, autosomal-recessive disease has not been associated with copy-number variation as a mutational mechanism. METHODS: We performed Agilent 8 × 60 K array comparative genomic hybridization on DNA from 12 recessive Turkish families with CMT disease. Additional molecular studies were conducted to detect breakpoint junctions and to evaluate gene expression levels in a family in which we detected an intragenic duplication copy-number variation. RESULTS: We detected an ~6.25 kb homozygous intragenic duplication in NDRG1, a gene known to be causative for recessive HMSNL/CMT4D, in three individuals from a Turkish family with CMT neuropathy. Further studies showed that this intragenic copy-number variation resulted in a homozygous duplication of exons 6-8 that caused decreased mRNA expression of NDRG1. CONCLUSION: Exon-focused high-resolution array comparative genomic hybridization enables the detection of copy-number variation carrier states in recessive genes, particularly small copy-number variations encompassing or disrupting single genes. In families for whom a molecular diagnosis has not been elucidated by conventional clinical assays, an assessment for copy-number variations in known CMT genes might be considered.
Keywords: Adult; Base Sequence; Cell Cycle Proteins; Charcot-Marie-Tooth Disease; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Expression; Genes, Recessive; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation; Refsum Disease; Sequence Analysis, DNA; Turkey; Young Adult

Exonuclease mutations in DNA polymerase epsilon reveal replication strand specific mutation patterns and human origins of replication. - Shinbrot, Eve; Henninger, Erin E; Weinhold, Nils; Covington, Kyle R; Göksenin, A Yasemin; Schultz, Nikolaus; Chao, Hsu; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Sander, Chris; Pursell, Zachary F; et al. (Genome Res, 2014)
Tumors with somatic mutations in the proofreading exonuclease domain of DNA polymerase epsilon (POLE-exo*) exhibit a novel mutator phenotype, with markedly elevated TCT→TAT and TCG→TTG mutations and overall mutation frequencies often exceeding 100 mutations/Mb. Here, we identify POLE-exo* tumors in numerous cancers and classify them into two groups, A and B, according to their mutational properties. Group A mutants are found only in POLE, whereas Group B mutants are found in POLE and POLD1 and appear to be nonfunctional. In Group A, cell-free polymerase assays confirm that mutations in the exonuclease domain result in high mutation frequencies with a preference for C→A mutation. We describe the patterns of amino acid substitutions caused by POLE-exo* and compare them to other tumor types. The nucleotide preference of POLE-exo* leads to increased frequencies of recurrent nonsense mutations in key tumor suppressors such as TP53, ATM, and PIK3R1. We further demonstrate that strand-specific mutation patterns arise from some of these POLE-exo* mutants during genome duplication. This is the first direct proof of leading strand-specific replication by human POLE, which has only been demonstrated in yeast so far. Taken together, the extremely high mutation frequency and strand specificity of mutations provide a unique identifier of eukaryotic origins of replication.
Keywords: Ataxia Telangiectasia Mutated Proteins; Class Ia Phosphatidylinositol 3-Kinase; Codon, Nonsense; Databases, Genetic; DNA Mutational Analysis; DNA Polymerase II; DNA Polymerase III; DNA Replication; Exonucleases; Genome-Wide Association Study; Humans; Microsatellite Instability; Models, Molecular; Mutation, Missense; Neoplasms; Phosphatidylinositol 3-Kinases; Protein Structure, Tertiary; Replication Origin; Tumor Suppressor Protein p53

The first myriapod genome sequence reveals conservative arthropod gene content and genome organisation in the centipede Strigamia maritima. - Chipman, Ariel D; Ferrier, David E K; Brena, Carlo; Qu, Jiaxin; Hughes, Daniel S T; Schröder, Reinhard; Torres-Oliva, Montserrat; Znassi, Nadia; Jiang, Huaiyang; Almeida, Francisca C; Alonso, Claudio R; Apostolou, Zivkos; et al. (PLoS Biol, 2014)
Myriapods (e.g., centipedes and millipedes) display a simple homonomous body plan relative to other arthropods. All members of the class are terrestrial, but they attained terrestriality independently of insects. Myriapoda is the only arthropod class not represented by a sequenced genome. We present an analysis of the genome of the centipede Strigamia maritima. It retains a compact genome that has undergone less gene loss and shuffling than previously sequenced arthropods, and many orthologues of genes conserved from the bilaterian ancestor that have been lost in insects. Our analysis locates many genes in conserved macro-synteny contexts, and many small-scale examples of gene clustering. We describe several examples where S. maritima shows different solutions from insects to similar problems. The insect olfactory receptor gene family is absent from S. maritima, and olfaction in air is likely effected by expansion of other receptor gene families. For some genes S. maritima has evolved paralogues to generate coding sequence diversity, where insects use alternate splicing. This is most striking for the Dscam gene, which in Drosophila generates more than 100,000 alternate splice forms, but in S. maritima is encoded by over 100 paralogues. We see an intriguing linkage between the absence of any known photosensory proteins in a blind organism and the additional absence of canonical circadian clock genes. The phylogenetic position of myriapods allows us to identify where in arthropod phylogeny several particular molecular mechanisms and traits emerged. For example, we conclude that juvenile hormone signalling evolved with the emergence of the exoskeleton in the arthropods and that RR-1 containing cuticle proteins evolved in the lineage leading to Mandibulata. We also identify when various gene expansions and losses occurred. The genome of S. maritima offers us a unique glimpse into the ancestral arthropod genome, while also displaying many adaptations to its specific life history.
Keywords: Animals; Arthropods; Circadian Rhythm Signaling Peptides and Proteins; DNA Methylation; Evolution, Molecular; Female; Genome; Genome, Mitochondrial; Hormones; Male; Multigene Family; Phylogeny; Polymorphism, Genetic; Protein Kinases; Receptors, Odorant; RNA, Untranslated; Selenoproteins; Sex Chromosomes; Synteny; Transcription Factors

A framework for the interpretation of de novo mutation in human disease. - Samocha, Kaitlin E; Robinson, Elise B; Sanders, Stephan J; Stevens, Christine; Aniko Sabo; McGrath, Lauren M; Kosmicki, Jack A; Rehnström, Karola; Mallick, Swapan; Kirby, Andrew; Wall, Dennis P; MacArthur, Daniel G; et al. (Nat Genet, 2014)
Spontaneously arising (de novo) mutations have an important role in medical genetics. For diseases with extensive locus heterogeneity, such as autism spectrum disorders (ASDs), the signal from de novo mutations is distributed across many genes, making it difficult to distinguish disease-relevant mutations from background variation. Here we provide a statistical framework for the analysis of excesses in de novo mutation per gene and gene set by calibrating a model of de novo mutation. We applied this framework to de novo mutations collected from 1,078 ASD family trios, and, whereas we affirmed a significant role for loss-of-function mutations, we found no excess of de novo loss-of-function mutations in cases with IQ above 100, suggesting that the role of de novo mutations in ASDs might reside in fundamental neurodevelopmental processes. We also used our model to identify ∼1,000 genes that are significantly lacking in functional coding variation in non-ASD samples and are enriched for de novo loss-of-function mutations identified in ASD cases.
Keywords: Child Development Disorders, Pervasive; Exome; Female; Genetic Code; Genetic Predisposition to Disease; Genetics, Medical; Humans; Male; Mutation

Gene-specific function prediction for non-synonymous mutations in monogenic diabetes genes. - Li, Quan; Liu, Xiaoming; Richard A Gibbs; Eric Boerwinkle; Polychronakos, Constantin; Qu, Hui-Qi (PLoS One, 2014)
The rapid progress of genomic technologies has been providing new opportunities to address the need of maturity-onset diabetes of the young (MODY) molecular diagnosis. However, whether a new mutation causes MODY can be questionable. A number of in silico methods have been developed to predict functional effects of rare human mutations. The purpose of this study is to compare the performance of different bioinformatics methods in the functional prediction of nonsynonymous mutations in each MODY gene, and provides reference matrices to assist the molecular diagnosis of MODY. Our study showed that the prediction scores by different methods of the diabetes mutations were highly correlated, but were more complimentary than replacement to each other. The available in silico methods for the prediction of diabetes mutations had varied performances across different genes. Applying gene-specific thresholds defined by this study may be able to increase the performance of in silico prediction of disease-causing mutations.
Keywords: Adolescent; Apoptosis Regulatory Proteins; Basic Helix-Loop-Helix Transcription Factors; Cell Cycle Proteins; Child; Computational Biology; Diabetes Mellitus, Type 2; Hepatocyte Nuclear Factor 1-alpha; Hepatocyte Nuclear Factor 1-beta; Hepatocyte Nuclear Factor 4; Homeodomain Proteins; Humans; Lipase; Mutation, Missense; Paired Box Transcription Factors; Potassium Channels, Inwardly Rectifying; Repressor Proteins; src-Family Kinases; Sulfonylurea Receptors; Trans-Activators; Young Adult

The genetic basis of DOORS syndrome: an exome-sequencing study. - Campeau, Philippe M; Kasperaviciute, Dalia; Lu, James T; Burrage, Lindsay C; Kim, Choel; Hori, Mutsuki; Powell, Berkley R; Stewart, Fiona; Félix, Têmis Maria; van den Ende, Jenneke; Wisniewska, Marzena; Kayserili, Hulya; et al. (Lancet Neurol, 2014)
BACKGROUND: Deafness, onychodystrophy, osteodystrophy, mental retardation, and seizures (DOORS) syndrome is a rare autosomal recessive disorder of unknown cause. We aimed to identify the genetic basis of this syndrome by sequencing most coding exons in affected individuals. METHODS: Through a search of available case studies and communication with collaborators, we identified families that included at least one individual with at least three of the five main features of the DOORS syndrome: deafness, onychodystrophy, osteodystrophy, intellectual disability, and seizures. Participants were recruited from 26 centres in 17 countries. Families described in this study were enrolled between Dec 1, 2010, and March 1, 2013. Collaborating physicians enrolling participants obtained clinical information and DNA samples from the affected child and both parents if possible. We did whole-exome sequencing in affected individuals as they were enrolled, until we identified a candidate gene, and Sanger sequencing to confirm mutations. We did expression studies in human fibroblasts from one individual by real-time PCR and western blot analysis, and in mouse tissues by immunohistochemistry and real-time PCR. FINDINGS: 26 families were included in the study. We did exome sequencing in the first 17 enrolled families; we screened for TBC1D24 by Sanger sequencing in subsequent families. We identified TBC1D24 mutations in 11 individuals from nine families (by exome sequencing in seven families, and Sanger sequencing in two families). 18 families had individuals with all five main features of DOORS syndrome, and TBC1D24 mutations were identified in half of these families. The seizure types in individuals with TBC1D24 mutations included generalised tonic-clonic, complex partial, focal clonic, and infantile spasms. Of the 18 individuals with DOORS syndrome from 17 families without TBC1D24 mutations, eight did not have seizures and three did not have deafness. In expression studies, some mutations abrogated TBC1D24 mRNA stability. We also detected Tbc1d24 expression in mouse phalangeal chondrocytes and calvaria, which suggests a role of TBC1D24 in skeletogenesis. INTERPRETATION: Our findings suggest that mutations in TBC1D24 seem to be an important cause of DOORS syndrome and can cause diverse phenotypes. Thus, individuals with DOORS syndrome without deafness and seizures but with the other features should still be screened for TBC1D24 mutations. More information is needed to understand the cellular roles of TBC1D24 and identify the genes responsible for DOORS phenotypes in individuals who do not have a mutation in TBC1D24. FUNDING: US National Institutes of Health, the CIHR (Canada), the NIHR (UK), the Wellcome Trust, the Henry Smith Charity, and Action Medical Research.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Craniofacial Abnormalities; Exome; Female; GTPase-Activating Proteins; Hand Deformities, Congenital; Hearing Loss, Sensorineural; Humans; Infant; Intellectual Disability; Internationality; Male; Membrane Proteins; Nails, Malformed; Nerve Tissue Proteins; Phenotype; Sequence Analysis, DNA; Young Adult

Genomic encyclopedia of bacteria and archaea: sequencing a myriad of type strains. - Kyrpides, Nikos C; Hugenholtz, Philip; Eisen, Jonathan A; Woyke, Tanja; Göker, Markus; Parker, Charles T; Amann, Rudolf; Beck, Brian J; Chain, Patrick S G; Chun, Jongsik; Colwell, Rita R; Danchin, Antoine; et al. (PLoS Biol, 2014)
Microbes hold the key to life. They hold the secrets to our past (as the descendants of the earliest forms of life) and the prospects for our future (as we mine their genes for solutions to some of the planet's most pressing problems, from global warming to antibiotic resistance). However, the piecemeal approach that has defined efforts to study microbial genetic diversity for over 20 years and in over 30,000 genome projects risks squandering that promise. These efforts have covered less than 20% of the diversity of the cultured archaeal and bacterial species, which represent just 15% of the overall known prokaryotic diversity. Here we call for the funding of a systematic effort to produce a comprehensive genomic catalog of all cultured Bacteria and Archaea by sequencing, where available, the type strain of each species with a validly published name (currently∼11,000). This effort will provide an unprecedented level of coverage of our planet's genetic diversity, allow for the large-scale discovery of novel genes and functions, and lead to an improved understanding of microbial evolution and function in the environment.
Keywords: Archaea; Bacteria; Databases, Genetic; Genome, Archaeal; Genome, Bacterial; Genomics; Phylogeny; Sequence Analysis, DNA

Gibbon genome and the fast karyotype evolution of small apes. - Carbone, Lucia; R. Alan Harris; Gnerre, Sante; Veeramah, Krishna R; Lorente-Galdos, Belen; Huddleston, John; Meyer, Thomas J; Herrero, Javier; Roos, Christian; Aken, Bronwen; Anaclerio, Fabio; Archidiacono, Nicoletta; et al. (Nature, 2014)
Gibbons are small arboreal apes that display an accelerated rate of evolutionary chromosomal rearrangement and occupy a key node in the primate phylogeny between Old World monkeys and great apes. Here we present the assembly and analysis of a northern white-cheeked gibbon (Nomascus leucogenys) genome. We describe the propensity for a gibbon-specific retrotransposon (LAVA) to insert into chromosome segregation genes and alter transcription by providing a premature termination site, suggesting a possible molecular mechanism for the genome plasticity of the gibbon lineage. We further show that the gibbon genera (Nomascus, Hylobates, Hoolock and Symphalangus) experienced a near-instantaneous radiation ∼5 million years ago, coincident with major geographical changes in southeast Asia that caused cycles of habitat compression and expansion. Finally, we identify signatures of positive selection in genes important for forelimb development (TBX5) and connective tissues (COL1A1) that may have been involved in the adaptation of gibbons to their arboreal habitat.
Keywords: Animals; Evolution, Molecular; Genome; Hominidae; Humans; Hylobates; Karyotype; Molecular Sequence Data; Phylogeny; Retroelements; Selection, Genetic; Transcription Termination, Genetic

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; RNA-Binding Proteins; Transcription Factors

Launching genomics into the cloud: deployment of Mercury, a next generation sequence analysis pipeline. - Reid, Jeffrey G; Carroll, Andrew; Veeraraghavan, Narayanan; Dahdouli, Mahmoud; Sundquist, Andreas; English, Adam; Bainbridge, Matthew; White, Simon; Salerno, William; Buhay, Christian; Fuli Yu; Donna M Muzny; et al. (BMC Bioinformatics, 2014)
BACKGROUND: Massively parallel DNA sequencing generates staggering amounts of data. Decreasing cost, increasing throughput, and improved annotation have expanded the diversity of genomics applications in research and clinical practice. This expanding scale creates analytical challenges: accommodating peak compute demand, coordinating secure access for multiple analysts, and sharing validated tools and results. RESULTS: To address these challenges, we have developed the Mercury analysis pipeline and deployed it in local hardware and the Amazon Web Services cloud via the DNAnexus platform. Mercury is an automated, flexible, and extensible analysis workflow that provides accurate and reproducible genomic results at scales ranging from individuals to large cohorts. CONCLUSIONS: By taking advantage of cloud computing and with Mercury implemented on the DNAnexus platform, we have demonstrated a powerful combination of a robust and fully validated software pipeline and a scalable computational resource that, to date, we have applied to more than 10,000 whole genome and whole exome samples.
Keywords: Genome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Internet; Software

Mammalian Y chromosomes retain widely expressed dosage-sensitive regulators. - Bellott, Daniel W; Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Cho, Ting-Jan; Koutseva, Natalia; Zaghlul, Sara; Graves, Tina; Rock, Susie; Kremitzki, Colin; Fulton, Robert S; et al. (Nature, 2014)
The human X and Y chromosomes evolved from an ordinary pair of autosomes, but millions of years ago genetic decay ravaged the Y chromosome, and only three per cent of its ancestral genes survived. We reconstructed the evolution of the Y chromosome across eight mammals to identify biases in gene content and the selective pressures that preserved the surviving ancestral genes. Our findings indicate that survival was nonrandom, and in two cases, convergent across placental and marsupial mammals. We conclude that the gene content of the Y chromosome became specialized through selection to maintain the ancestral dosage of homologous X-Y gene pairs that function as broadly expressed regulators of transcription, translation and protein stability. We propose that beyond its roles in testis determination and spermatogenesis, the Y chromosome is essential for male viability, and has unappreciated roles in Turner's syndrome and in phenotypic differences between the sexes in health and disease.
Keywords: Animals; Chromosomes, Human, X; Chromosomes, Human, Y; Disease; Evolution, Molecular; Female; Gene Dosage; Gene Expression Regulation; Health; Humans; Male; Mammals; Marsupialia; Molecular Sequence Annotation; Molecular Sequence Data; Protein Biosynthesis; Protein Stability; Selection, Genetic; Sequence Homology; Sex Characteristics; Spermatogenesis; Testis; Transcription, Genetic; Turner Syndrome; X Chromosome; Y Chromosome

Molecular findings among patients referred for clinical whole-exome sequencing. - Yang, Yaping; Donna M Muzny; Xia, Fan; Niu, Zhiyv; Person, Richard; Ding, Yan; Ward, Patricia; Braxton, Alicia; Wang, Min; Buhay, Christian; Veeraraghavan, Narayanan; Hawes, Alicia; et al. (JAMA, 2014)
IMPORTANCE: Clinical whole-exome sequencing is increasingly used for diagnostic evaluation of patients with suspected genetic disorders. OBJECTIVE: To perform clinical whole-exome sequencing and report (1) the rate of molecular diagnosis among phenotypic groups, (2) the spectrum of genetic alterations contributing to disease, and (3) the prevalence of medically actionable incidental findings such as FBN1 mutations causing Marfan syndrome. DESIGN, SETTING, AND PATIENTS: Observational study of 2000 consecutive patients with clinical whole-exome sequencing analyzed between June 2012 and August 2014. Whole-exome sequencing tests were performed at a clinical genetics laboratory in the United States. Results were reported by clinical molecular geneticists certified by the American Board of Medical Genetics and Genomics. Tests were ordered by the patient's physician. The patients were primarily pediatric (1756 [88%]; mean age, 6 years; 888 females [44%], 1101 males [55%], and 11 fetuses [1% gender unknown]), demonstrating diverse clinical manifestations most often including nervous system dysfunction such as developmental delay. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing diagnosis rate overall and by phenotypic category, mode of inheritance, spectrum of genetic events, and reporting of incidental findings. RESULTS: A molecular diagnosis was reported for 504 patients (25.2%) with 58% of the diagnostic mutations not previously reported. Molecular diagnosis rates for each phenotypic category were 143/526 (27.2%; 95% CI, 23.5%-31.2%) for the neurological group, 282/1147 (24.6%; 95% CI, 22.1%-27.2%) for the neurological plus other organ systems group, 30/83 (36.1%; 95% CI, 26.1%-47.5%) for the specific neurological group, and 49/244 (20.1%; 95% CI, 15.6%-25.8%) for the nonneurological group. The Mendelian disease patterns of the 527 molecular diagnoses included 280 (53.1%) autosomal dominant, 181 (34.3%) autosomal recessive (including 5 with uniparental disomy), 65 (12.3%) X-linked, and 1 (0.2%) mitochondrial. Of 504 patients with a molecular diagnosis, 23 (4.6%) had blended phenotypes resulting from 2 single gene defects. About 30% of the positive cases harbored mutations in disease genes reported since 2011. There were 95 medically actionable incidental findings in genes unrelated to the phenotype but with immediate implications for management in 92 patients (4.6%), including 59 patients (3%) with mutations in genes recommended for reporting by the American College of Medical Genetics and Genomics. CONCLUSIONS AND RELEVANCE: Whole-exome sequencing provided a potential molecular diagnosis for 25% of a large cohort of patients referred for evaluation of suspected genetic conditions, including detection of rare genetic events and new mutations contributing to disease. The yield of whole-exome sequencing may offer advantages over traditional molecular diagnostic approaches in certain patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Fetus; Genetic Diseases, Inborn; Genetic Testing; Genomics; Humans; Incidental Findings; Infant; Infant, Newborn; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Referral and Consultation; Sequence Analysis, DNA

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

Mutational landscape of aggressive cutaneous squamous cell carcinoma. - Pickering, Curtis R; Zhou, Jane H; Lee, J Jack; Drummond, Jennifer A; Peng, S Andrew; Saade, Rami E; Tsai, Kenneth Y; Curry, Jonathan L; Tetzlaff, Michael T; Lai, Stephen Y; Yu, Jun; Donna M Muzny; et al. (Clin Cancer Res, 2014)
PURPOSE: Aggressive cutaneous squamous cell carcinoma (cSCC) is often a disfiguring and lethal disease. Very little is currently known about the mutations that drive aggressive cSCC. EXPERIMENTAL DESIGN: Whole-exome sequencing was performed on 39 cases of aggressive cSCC to identify driver genes and novel therapeutic targets. Significantly, mutated genes were identified with MutSig or complementary methods developed to specifically identify candidate tumor suppressors based upon their inactivating mutation bias. RESULTS: Despite the very high-mutational background caused by UV exposure, 23 candidate drivers were identified, including the well-known cancer-associated genes TP53, CDKN2A, NOTCH1, AJUBA, HRAS, CASP8, FAT1, and KMT2C (MLL3). Three novel candidate tumor suppressors with putative links to cancer or differentiation, NOTCH2, PARD3, and RASA1, were also identified as possible drivers in cSCC. KMT2C mutations were associated with poor outcome and increased bone invasion. CONCLUSIONS: The mutational spectrum of cSCC is similar to that of head and neck squamous cell carcinoma and dominated by tumor-suppressor genes. These results improve the foundation for understanding this disease and should aid in identifying and treating aggressive cSCC.
Keywords: Carcinoma, Squamous Cell; Cluster Analysis; Computational Biology; Disease Progression; DNA Copy Number Variations; Exome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Mutation; Prognosis; Skin Neoplasms

Mutations in NGLY1 cause an inherited disorder of the endoplasmic reticulum-associated degradation pathway. - Enns, Gregory M; Shashi, Vandana; Bainbridge, Matthew; Gambello, Michael J; Zahir, Farah R; Bast, Thomas; Crimian, Rebecca; Schoch, Kelly; Platt, Julia; Cox, Rachel; Bernstein, Jonathan A; Scavina, Mena; et al. (Genet Med, 2014)
PURPOSE: The endoplasmic reticulum-associated degradation pathway is responsible for the translocation of misfolded proteins across the endoplasmic reticulum membrane into the cytosol for subsequent degradation by the proteasome. To define the phenotype associated with a novel inherited disorder of cytosolic endoplasmic reticulum-associated degradation pathway dysfunction, we studied a series of eight patients with deficiency of N-glycanase 1. METHODS: Whole-genome, whole-exome, or standard Sanger sequencing techniques were employed. Retrospective chart reviews were performed in order to obtain clinical data. RESULTS: All patients had global developmental delay, a movement disorder, and hypotonia. Other common findings included hypolacrima or alacrima (7/8), elevated liver transaminases (6/7), microcephaly (6/8), diminished reflexes (6/8), hepatocyte cytoplasmic storage material or vacuolization (5/6), and seizures (4/8). The nonsense mutation c.1201A>T (p.R401X) was the most common deleterious allele. CONCLUSION: NGLY1 deficiency is a novel autosomal recessive disorder of the endoplasmic reticulum-associated degradation pathway associated with neurological dysfunction, abnormal tear production, and liver disease. The majority of patients detected to date carry a specific nonsense mutation that appears to be associated with severe disease. The phenotypic spectrum is likely to enlarge as cases with a broader range of mutations are detected.
Keywords: Abnormalities, Multiple; Adolescent; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Exome; Family Health; Fatal Outcome; Female; Genome-Wide Association Study; Humans; Infant; Male; Microcephaly; Movement Disorders; Muscle Hypotonia; Mutation; Pedigree; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Retrospective Studies; Seizures; Sequence Analysis, DNA; Signal Transduction; Young Adult

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Natural variation in genome architecture among 205 Drosophila melanogaster Genetic Reference Panel lines. - Huang, Wen; Massouras, Andreas; Inoue, Yutaka; Peiffer, Jason; Ràmia, Miquel; Tarone, Aaron M; Turlapati, Lavanya; Zichner, Thomas; Zhu, Dianhui; Lyman, Richard F; Magwire, Michael M; Blankenburg, Kerstin; et al. (Genome Res, 2014)
The Drosophila melanogaster Genetic Reference Panel (DGRP) is a community resource of 205 sequenced inbred lines, derived to improve our understanding of the effects of naturally occurring genetic variation on molecular and organismal phenotypes. We used an integrated genotyping strategy to identify 4,853,802 single nucleotide polymorphisms (SNPs) and 1,296,080 non-SNP variants. Our molecular population genomic analyses show higher deletion than insertion mutation rates and stronger purifying selection on deletions. Weaker selection on insertions than deletions is consistent with our observed distribution of genome size determined by flow cytometry, which is skewed toward larger genomes. Insertion/deletion and single nucleotide polymorphisms are positively correlated with each other and with local recombination, suggesting that their nonrandom distributions are due to hitchhiking and background selection. Our cytogenetic analysis identified 16 polymorphic inversions in the DGRP. Common inverted and standard karyotypes are genetically divergent and account for most of the variation in relatedness among the DGRP lines. Intriguingly, variation in genome size and many quantitative traits are significantly associated with inversions. Approximately 50% of the DGRP lines are infected with Wolbachia, and four lines have germline insertions of Wolbachia sequences, but effects of Wolbachia infection on quantitative traits are rarely significant. The DGRP complements ongoing efforts to functionally annotate the Drosophila genome. Indeed, 15% of all D. melanogaster genes segregate for potentially damaged proteins in the DGRP, and genome-wide analyses of quantitative traits identify novel candidate genes. The DGRP lines, sequence data, genotypes, quality scores, phenotypes, and analysis and visualization tools are publicly available.
Keywords: Animals; Chromatin; Drosophila melanogaster; Female; Genetic Linkage; Genetic Variation; Genome Size; Genome, Insect; Genome-Wide Association Study; Genotype; Genotyping Techniques; High-Throughput Nucleotide Sequencing; INDEL Mutation; Linkage Disequilibrium; Male; Molecular Sequence Annotation; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Reproducibility of Results

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

Next-generation sequencing identifies rare variants associated with Noonan syndrome. - Chen, Peng-Chieh; Yin, Jiani; Yu, Hui-Wen; Yuan, Tao; Fernandez, Minerva; Yung, Christina K; Trinh, Quang M; Peltekova, Vanya D; Reid, Jeffrey G; Tworog-Dube, Erica; Morgan, Margaret B; Donna M Muzny; et al. (Proc Natl Acad Sci U S A, 2014)
Noonan syndrome (NS) is a relatively common genetic disorder, characterized by typical facies, short stature, developmental delay, and cardiac abnormalities. Known causative genes account for 70-80% of clinically diagnosed NS patients, but the genetic basis for the remaining 20-30% of cases is unknown. We performed next-generation sequencing on germ-line DNA from 27 NS patients lacking a mutation in the known NS genes. We identified gain-of-function alleles in Ras-like without CAAX 1 (RIT1) and mitogen-activated protein kinase kinase 1 (MAP2K1) and previously unseen loss-of-function variants in RAS p21 protein activator 2 (RASA2) that are likely to cause NS in these patients. Expression of the mutant RASA2, MAP2K1, or RIT1 alleles in heterologous cells increased RAS-ERK pathway activation, supporting a causative role in NS pathogenesis. Two patients had more than one disease-associated variant. Moreover, the diagnosis of an individual initially thought to have NS was revised to neurofibromatosis type 1 based on an NF1 nonsense mutation detected in this patient. Another patient harbored a missense mutation in NF1 that resulted in decreased protein stability and impaired ability to suppress RAS-ERK activation; however, this patient continues to exhibit a NS-like phenotype. In addition, a nonsense mutation in RPS6KA3 was found in one patient initially diagnosed with NS whose diagnosis was later revised to Coffin-Lowry syndrome. Finally, we identified other potential candidates for new NS genes, as well as potential carrier alleles for unrelated syndromes. Taken together, our data suggest that next-generation sequencing can provide a useful adjunct to RASopathy diagnosis and emphasize that the standard clinical categories for RASopathies might not be adequate to describe all patients.
Keywords: Alleles; Genetic Association Studies; High-Throughput Nucleotide Sequencing; Humans; MAP Kinase Kinase 1; MAP Kinase Signaling System; Mutation; Neurofibromin 1; Noonan Syndrome; ras Proteins

Novel somatic and germline mutations in intracranial germ cell tumours. - Wang, Linghua; Yamaguchi, Shigeru; Burstein, Matthew D; Terashima, Keita; Chang, Kyle; Ng, Ho-Keung; Nakamura, Hideo; He, Zongxiao; Harshavardhan Doddapaneni; Lewis, Lora; Wang, Mark; Suzuki, Tomonari; et al. (Nature, 2014)
Intracranial germ cell tumours (IGCTs) are a group of rare heterogeneous brain tumours that are clinically and histologically similar to the more common gonadal GCTs. IGCTs show great variation in their geographical and gender distribution, histological composition and treatment outcomes. The incidence of IGCTs is historically five- to eightfold greater in Japan and other East Asian countries than in Western countries, with peak incidence near the time of puberty. About half of the tumours are located in the pineal region. The male-to-female incidence ratio is approximately 3-4:1 overall, but is even higher for tumours located in the pineal region. Owing to the scarcity of tumour specimens available for research, little is currently known about this rare disease. Here we report the analysis of 62 cases by next-generation sequencing, single nucleotide polymorphism array and expression array. We find the KIT/RAS signalling pathway frequently mutated in more than 50% of IGCTs, including novel recurrent somatic mutations in KIT, its downstream mediators KRAS and NRAS, and its negative regulator CBL. Novel somatic alterations in the AKT/mTOR pathway included copy number gains of the AKT1 locus at 14q32.33 in 19% of patients, with corresponding upregulation of AKT1 expression. We identified loss-of-function mutations in BCORL1, a transcriptional co-repressor and tumour suppressor. We report significant enrichment of novel and rare germline variants in JMJD1C, which codes for a histone demethylase and is a coactivator of the androgen receptor, among Japanese IGCT patients. This study establishes a molecular foundation for understanding the biology of IGCTs and suggests potentially promising therapeutic strategies focusing on the inhibition of KIT/RAS activation and the AKT1/mTOR pathway.
Keywords: Adult; Brain Neoplasms; Child; Female; Germ-Line Mutation; Humans; Japan; Male; Mutation; Neoplasms, Germ Cell and Embryonal; Oncogene Protein v-akt; Proto-Oncogene Proteins c-kit; ras Proteins; Reproducibility of Results; Signal Transduction; TOR Serine-Threonine Kinases; Young Adult

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Donna M Muzny; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

Obtaining informed consent for clinical tumor and germline exome sequencing of newly diagnosed childhood cancer patients. - Scollon, Sarah; Bergstrom, Katie; Kerstein, Robin A; Wang, Tao; Hilsenbeck, Susan G; Ramamurthy, Uma; Richard A Gibbs; Eng, Christine M; Chintagumpala, Murali M; Berg, Stacey L; McCullough, Laurence B; McGuire, Amy L; et al. (Genome Med, 2014)
BACKGROUND: Effectively educating families about the risks and benefits of genomic tests such as whole exome sequencing (WES) offers numerous challenges, including the complexity of test results and potential loss of privacy. Research on best practices for obtaining informed consent (IC) in a variety of clinical settings is needed. The BASIC3 study of clinical tumor and germline WES in an ethnically diverse cohort of newly diagnosed pediatric cancer patients offers the opportunity to study the IC process in the setting of critical illness. We report on our experience for the first 100 families enrolled, including study participation rates, reasons for declining enrollment, assessment of clinical and demographic factors that might impact study enrollment, and preferences of parents for participation in optional genomics study procedures. METHODS: A specifically trained IC team offered study enrollment to parents of eligible children for procedures including clinical tumor and germline WES with results deposited in the medical record and disclosure of both diagnostic and incidental results to the family. Optional study procedures were also offered, such as receiving recessive carrier status and deposition of data into research databases. Stated reasons for declining participation were recorded. Clinical and demographic data were collected and comparisons made between enrolled and non-enrolled patients. RESULTS: Over 15 months, 100 of 121 (83%) eligible families elected to enroll in the study. No significant differences in enrollment were detected based on factors such as race, ethnicity, use of Spanish interpreters and Spanish consent forms, and tumor features (central nervous system versus non-central nervous system, availability of tumor for WES). The most common reason provided for declining enrollment (10% of families) was being overwhelmed by the new cancer diagnosis. Risks specific to clinical genomics, such as privacy concerns, were less commonly reported (5.5%). More than 85% of parents consented to each of the optional study procedures. CONCLUSIONS: An IC process was developed that utilizes a specialized IC team, active communication with the oncology team, and an emphasis on scheduling flexibility. Most parents were willing to participate in a clinical germline and tumor WES study as well as optional procedures such as genomic data sharing independent of race, ethnicity or language spoken.

Open access data sharing in genomic research. - Pereira, Stacey; Richard A Gibbs; McGuire, Amy L (Genes (Basel), 2014)
The current emphasis on broad sharing of human genomic data generated in research in order to maximize utility and public benefit is a significant legacy of the Human Genome Project. Concerns about privacy and discrimination have led to policy responses that restrict access to genomic data as the means for protecting research participants. Our research and experience show, however, that a considerable number of research participants agree to open access sharing of their genomic data when given the choice. General policies that limit access to all genomic data fail to respect the autonomy of these participants and, at the same time, unnecessarily limit the utility of the data. We advocate instead a more balanced approach that allows for individual choice and encourages informed decision making, while protecting against the misuse of genomic data through enhanced legislation.

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Recurrent CNVs and SNVs at the NPHP1 locus contribute pathogenic alleles to Bardet-Biedl syndrome. - Lindstrand, Anna; Davis, Erica E; Carvalho, Claudia M B; Pehlivan, Davut; Willer, Jason R; Tsai, I-Chun; Ramanathan, Subhadra; Zuppan, Craig; Aniko Sabo; Donna M Muzny; Richard A Gibbs; Liu, Pengfei; et al. (Am J Hum Genet, 2014)
Homozygosity for a recurrent 290 kb deletion of NPHP1 is the most frequent cause of isolated nephronophthisis (NPHP) in humans. A deletion of the same genomic interval has also been detected in individuals with Joubert syndrome (JBTS), and in the mouse, Nphp1 interacts genetically with Ahi1, a known JBTS locus. Given these observations, we investigated the contribution of NPHP1 in Bardet-Biedl syndrome (BBS), a ciliopathy of intermediate severity. By using a combination of array-comparative genomic hybridization, TaqMan copy number assays, and sequencing, we studied 200 families affected by BBS. We report a homozygous NPHP1 deletion CNV in a family with classical BBS that is transmitted with autosomal-recessive inheritance. Further, we identified heterozygous NPHP1 deletions in two more unrelated persons with BBS who bear primary mutations at another BBS locus. In parallel, we identified five families harboring an SNV in NPHP1 resulting in a conserved missense change, c.14G>T (p.Arg5Leu), that is enriched in our Hispanic pedigrees; in each case, affected individuals carried additional bona fide pathogenic alleles in another BBS gene. In vivo functional modeling in zebrafish embryos demonstrated that c.14G>T is a loss-of-function variant, and suppression of nphp1 in concert with each of the primary BBS loci found in our NPHP1-positive pedigrees exacerbated the severity of the phenotype. These results suggest that NPHP1 mutations are probably rare primary causes of BBS that contribute to the mutational burden of the disorder.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Bardet-Biedl Syndrome; Cytoskeletal Proteins; DNA Copy Number Variations; Gastrulation; Genetic Loci; Heterozygote; Homozygote; Humans; Kidney; Membrane Proteins; Mice; Pedigree; Sequence Deletion; Zebrafish

The relationship of JAK2(V617F) and acquired UPD at chromosome 9p in polycythemia vera. - Wang, L; Swierczek, S I; Lanikova, L; Kim, S J; Hickman, K; Kimberly Walker; Wang, K; Drummond, J; Harshavardhan Doddapaneni; Reid, J G; Donna M Muzny; Richard A Gibbs; et al. (Leukemia, 2014)
Keywords: Chromosomes, Human, Pair 9; Genotype; Humans; Janus Kinase 2; Polycythemia Vera; Uniparental Disomy

Sequence analysis of six blood pressure candidate regions in 4,178 individuals: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study. - Morrison, Alanna C; Bis, Joshua C; Hwang, Shih-Jen; Ehret, Georg B; Lumley, Thomas; Rice, Kenneth; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; Psaty, Bruce M; Chakravarti, Aravinda; Levy, Daniel (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) identified multiple loci for blood pressure (BP) and hypertension. Six genes--ATP2B1, CACNB2, CYP17A1, JAG1, PLEKHA7, and SH2B3--were evaluated for sequence variation with large effects on systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), and mean arterial pressure (MAP). METHODS AND RESULTS: Targeted genomic sequence was determined in 4,178 European ancestry participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Common variants (≥50 minor allele copies) were evaluated individually and rare variants (minor allele frequency, MAF≤1%) were aggregated by locus. 464 common variants were identified across the 6 genes. An upstream CYP17A1 variant, rs11191416 (MAF = 0.09), was the most significant association for SBP (P = 0.0005); however the association was attenuated (P = 0.0469) after conditioning on the GWAS index single nucleotide polymorphism (SNP). A PLEKHA7 intronic variant was the strongest DBP association (rs12806040, MAF = 0.007, P = 0.0006) and was not in LD (r² = 0.01) with the GWAS SNP. A CACNB2 intronic SNP, rs1571787, was the most significant association with PP (MAF = 0.27, P = 0.0003), but was not independent from the GWAS SNP (r² = 0.34). Three variants (rs6163 and rs743572 in the CYP17A1 region and rs112467382 in PLEKHA7) were associated with BP traits (P<0.001). Rare variation, aggregately assessed in the 6 regions, was not significantly associated with BP measures. CONCLUSION: Six targeted gene regions, previously identified by GWAS, did not harbor novel variation with large effects on BP in this sample.
Keywords: Aging; Blood Pressure; Cohort Studies; Heart; Humans; Sequence Analysis

The sheep genome illuminates biology of the rumen and lipid metabolism. - Jiang, Yu; Xie, Min; Chen, Wenbin; Talbot, Richard; Maddox, Jillian F; Faraut, Thomas; Wu, Chunhua; Donna M Muzny; Li, Yuxiang; Zhang, Wenguang; Stanton, Jo-Ann; Brauning, Rudiger; et al. (Science, 2014)
Sheep (Ovis aries) are a major source of meat, milk, and fiber in the form of wool and represent a distinct class of animals that have a specialized digestive organ, the rumen, that carries out the initial digestion of plant material. We have developed and analyzed a high-quality reference sheep genome and transcriptomes from 40 different tissues. We identified highly expressed genes encoding keratin cross-linking proteins associated with rumen evolution. We also identified genes involved in lipid metabolism that had been amplified and/or had altered tissue expression patterns. This may be in response to changes in the barrier lipids of the skin, an interaction between lipid metabolism and wool synthesis, and an increased role of volatile fatty acids in ruminants compared with nonruminant animals.
Keywords: Amino Acid Sequence; Animals; Fatty Acids, Volatile; Gene Expression Regulation; Genome; Keratins, Hair-Specific; Lipid Metabolism; Molecular Sequence Data; Phylogeny; Rumen; Sheep, Domestic; Transcriptome; Wool

The somatic genomic landscape of chromophobe renal cell carcinoma. - Davis, Caleb F; Ricketts, Christopher J; Wang, Min; Yang, Lixing; Cherniack, Andrew D; Shen, Hui; Buhay, Christian; Kang, Hyojin; Kim, Sang Cheol; Fahey, Catherine C; Hacker, Kathryn E; Bhanot, Gyan; et al. (Cancer Cell, 2014)
We describe the landscape of somatic genomic alterations of 66 chromophobe renal cell carcinomas (ChRCCs) on the basis of multidimensional and comprehensive characterization, including mtDNA and whole-genome sequencing. The result is consistent that ChRCC originates from the distal nephron compared with other kidney cancers with more proximal origins. Combined mtDNA and gene expression analysis implicates changes in mitochondrial function as a component of the disease biology, while suggesting alternative roles for mtDNA mutations in cancers relying on oxidative phosphorylation. Genomic rearrangements lead to recurrent structural breakpoints within TERT promoter region, which correlates with highly elevated TERT expression and manifestation of kataegis, representing a mechanism of TERT upregulation in cancer distinct from previously observed amplifications and point mutations.
Keywords: Base Sequence; Carcinoma, Renal Cell; Chromosome Breakpoints; Chromosome Deletion; Chromosomes, Human; DNA Copy Number Variations; DNA Methylation; DNA Mutational Analysis; DNA, Mitochondrial; Exome; Genome, Human; Humans; Kidney Neoplasms; Molecular Sequence Data; Promoter Regions, Genetic; Telomerase; Transcriptome

Squamous cell carcinoma of the oral tongue in young non-smokers is genomically similar to tumors in older smokers. - Pickering, Curtis R; Zhang, Jiexin; Neskey, David M; Zhao, Mei; Jasser, Samar A; Wang, Jiping; Ward, Alexandra; Tsai, C Jillian; Ortega Alves, Marcus V; Zhou, Jane H; Drummond, Jennifer; El-Naggar, Adel K; et al. (Clin Cancer Res, 2014)
PURPOSE: Epidemiologic studies have identified an increasing incidence of squamous cell carcinoma of the oral tongue (SCCOT) in younger patients. EXPERIMENTAL DESIGN: DNA isolated from tongue tumors of young (<45 years, non-smokers) and old (>45 years) patients at was subjected to whole-exome sequencing and copy-number analysis. These data were compared with data from similar patients in the TCGA (The Cancer Genome Atlas) project. RESULTS: In this study, we found that gene-specific mutation and copy-number alteration frequencies were similar between young and old patients with SCCOT in two independent cohorts. Likewise, the types of base changes observed in the young cohort were similar to those in the old cohort even though they differed in smoking history. TCGA data also demonstrate that the genomic effects of smoking are tumor site-specific, and we find that smoking has only a minor impact on the types of mutations observed in SCCOT. CONCLUSIONS: Overall, tumors from young patients with SCCOT appear genomically similar to those of older patients with SCCOT, and the cause for the increasing incidence of young SCCOT remains unknown. These data indicate that the functional impact of smoking on carcinogenesis in SCCOT is still poorly understood.
Keywords: Adult; Age Factors; Carcinoma, Squamous Cell; DNA Copy Number Variations; DNA Mutational Analysis; Female; Humans; Male; Middle Aged; Mutation; Prognosis; Smoking; Tongue Neoplasms

Targeted sequencing in candidate genes for atrial fibrillation: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Lin, Honghuang; Sinner, Moritz F; Brody, Jennifer A; Arking, Dan E; Lunetta, Kathryn L; Rienstra, Michiel; Lubitz, Steven A; Magnani, Jared W; Sotoodehnia, Nona; McKnight, Barbara; McManus, David D; Eric Boerwinkle; et al. (Heart Rhythm, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified common genetic variants that predispose to atrial fibrillation (AF). It is unclear whether rare and low-frequency variants in genes implicated by such GWAS confer additional risk of AF. OBJECTIVE: To study the association of genetic variants with AF at GWAS top loci. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study, we selected and sequenced 77 target gene regions from GWAS loci of complex diseases or traits, including 4 genes hypothesized to be related to AF (PRRX1, CAV1, CAV2, and ZFHX3). Sequencing was performed in participants with (n = 948) and without (n = 3330) AF from the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Massachusetts General Hospital. RESULTS: One common variant (rs11265611; P = 1.70 × 10(-6)) intronic to IL6R (interleukin-6 receptor gene) was significantly associated with AF after Bonferroni correction (odds ratio 0.70; 95% confidence interval 0.58-0.85). The variant was not genotyped or imputed by prior GWAS, but it is in linkage disequilibrium (r(2) = .69) with the single-nucleotide polymorphism, with the strongest association with AF so far at this locus (rs4845625). In the rare variant joint analysis, damaging variants within the PRRX1 region showed significant association with AF after Bonferroni correction (P = .01). CONCLUSIONS: We identified 1 common single-nucleotide polymorphism and 1 gene region that were significantly associated with AF. Future sequencing efforts with larger sample sizes and more comprehensive genome coverage are anticipated to identify additional AF-related variants.
Keywords: Aged; Atrial Fibrillation; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Interleukin-6

Trans-ancestry mutational landscape of hepatocellular carcinoma genomes. - Totoki, Yasushi; Tatsuno, Kenji; Covington, Kyle R; Ueda, Hiroki; Creighton, Chad J; Kato, Mamoru; Tsuji, Shingo; Donehower, Lawrence A; Slagle, Betty L; Nakamura, Hiromi; Yamamoto, Shogo; Shinbrot, Eve; et al. (Nat Genet, 2014)
Diverse epidemiological factors are associated with hepatocellular carcinoma (HCC) prevalence in different populations. However, the global landscape of the genetic changes in HCC genomes underpinning different epidemiological and ancestral backgrounds still remains uncharted. Here a collection of data from 503 liver cancer genomes from different populations uncovered 30 candidate driver genes and 11 core pathway modules. Furthermore, a collaboration of two large-scale cancer genome projects comparatively analyzed the trans-ancestry substitution signatures in 608 liver cancer cases and identified unique mutational signatures that predominantly contribute to Asian cases. This work elucidates previously unexplored ancestry-associated mutational processes in HCC development. A combination of hotspot TERT promoter mutation, TERT focal amplification and viral genome integration occurs in more than 68% of cases, implicating TERT as a central and ancestry-independent node of hepatocarcinogenesis. Newly identified alterations in genes encoding metabolic enzymes, chromatin remodelers and a high proportion of mTOR pathway activations offer potential therapeutic and diagnostic opportunities.
Keywords: Algorithms; Asian People; Carcinoma, Hepatocellular; CpG Islands; DNA Mutational Analysis; Exome; Gene Expression Regulation, Neoplastic; Genome, Human; Genome, Viral; Hepacivirus; Hepatitis B virus; Humans; Japan; Liver Neoplasms; Models, Statistical; Mutation; Principal Component Analysis; Telomerase; TOR Serine-Threonine Kinases; United States; White People

Whole exome sequencing identifies novel genes for fetal hemoglobin response to hydroxyurea in children with sickle cell anemia. - Sheehan, Vivien A; Crosby, Jacy R; Aniko Sabo; Mortier, Nicole A; Howard, Thad A; Donna M Muzny; Dugan-Perez, Shannon; Aygun, Banu; Nottage, Kerri A; Eric Boerwinkle; Richard A Gibbs; Ware, Russell E; et al. (PLoS One, 2014)
Hydroxyurea has proven efficacy in children and adults with sickle cell anemia (SCA), but with considerable inter-individual variability in the amount of fetal hemoglobin (HbF) produced. Sibling and twin studies indicate that some of that drug response variation is heritable. To test the hypothesis that genetic modifiers influence pharmacological induction of HbF, we investigated phenotype-genotype associations using whole exome sequencing of children with SCA treated prospectively with hydroxyurea to maximum tolerated dose (MTD). We analyzed 171 unrelated patients enrolled in two prospective clinical trials, all treated with dose escalation to MTD. We examined two MTD drug response phenotypes: HbF (final %HbF minus baseline %HbF), and final %HbF. Analyzing individual genetic variants, we identified multiple low frequency and common variants associated with HbF induction by hydroxyurea. A validation cohort of 130 pediatric sickle cell patients treated to MTD with hydroxyurea was genotyped for 13 non-synonymous variants with the strongest association with HbF response to hydroxyurea in the discovery cohort. A coding variant in Spalt-like transcription factor, or SALL2, was associated with higher final HbF in this second independent replication sample and SALL2 represents an outstanding novel candidate gene for further investigation. These findings may help focus future functional studies and provide new insights into the pharmacological HbF upregulation by hydroxyurea in patients with SCA.
Keywords: Anemia, Sickle Cell; Child; Cohort Studies; DNA-Binding Proteins; Dose-Response Relationship, Drug; Exome; Fetal Hemoglobin; Genomics; Humans; Hydroxyurea; Maximum Tolerated Dose; Open Reading Frames; Phenotype; Prospective Studies; Sequence Analysis, DNA; Transcription Factors; Treatment Outcome

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Donna M Muzny; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Microfilament Proteins; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Whole-exome sequencing links TMCO1 defect syndrome with cerebro-facio-thoracic dysplasia. - Pehlivan, Davut; Karaca, Ender; Aydin, Hatip; Beck, Christine R; Gambin, Tomasz; Donna M Muzny; Bilge Geckinli, B; Karaman, Ali; Jhangiani, Shalini N; Richard A Gibbs; Lupski, James R (Eur J Hum Genet, 2014)
Whole-exome sequencing (WES) is a type of disruptive technology that has tremendous influence on human and clinical genetics research. An efficient and cost-effective method, WES is now widely used as a diagnostic tool for identifying the molecular basis of genetic syndromes that are often challenging to diagnose. Here we report a patient with a clinical diagnosis of cerebro-facio-thoracic dysplasia (CFTD; MIM#213980) in whom we identified a homozygous splice-site mutation in the transmembrane and coiled-coil domains 1 (TMCO1) gene using WES. TMCO1 mutations cause craniofacial dysmorphism, skeletal anomalies characterized by multiple malformations of the vertebrae and ribs, and intellectual disability (MIM#614132). A retrospective review revealed that clinical manifestations of both syndromes are very similar and overlap remarkably. We propose that mutations of TMCO1 are not only responsible for craniofacial dysmorphism, skeletal anomalies and mental retardation syndrome but also for CFTD.
Keywords: Abnormalities, Multiple; Calcium Channels; Exome; Humans; Infant; Intellectual Disability; Male; Membrane Proteins; Mutation; Protein Isoforms

Whole-exome sequencing of polycythemia vera revealed novel driver genes and somatic mutation shared by T cells and granulocytes. - Wang, L; Swierczek, S I; Drummond, J; Hickman, K; Kim, S J; Kimberly Walker; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Wheeler, D A; Prchal, J T (Leukemia, 2014)
To better understand the underlying molecular basis of polycythemia vera (PV), we performed whole-exome sequencing and DNA copy-number analysis of 31 -positive patients and further investigated the evolution of somatic mutations using longitudinal samples. In addition to and 9pUPD, we identified frequent recurrent somatic mutation in , and . Forty two percent of patients had a somatic mutation in at least one epigenetic modifier gene. In 4 of 31 patients, variant allele abundance suggested mutation of was preceded by other somatic mutations including , and . Strikingly, in 7 patients, apparent germline variants were detected at COSMIC codons in one or more PV-related genes in which we had also discovered somatic mutations across the cohort, suggesting that some pre- mutations contribute to substantial T-lymphocyte progeny. This study contributes to novel understanding of the complexity of PV pathogenesis.
Keywords: DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; Exome; Granulocytes; Humans; Janus Kinase 2; Mutation; Polycythemia Vera; Repressor Proteins; Sequence Analysis, DNA; T-Lymphocytes

Analysis of rare, exonic variation amongst subjects with autism spectrum disorders and population controls. - Liu, Li; Aniko Sabo; Neale, Benjamin M; Nagaswamy, Uma; Stevens, Christine; Lim, Elaine; Bodea, Corneliu A; Donna M Muzny; Reid, Jeffrey G; Banks, Eric; Coon, Hillary; DePristo, Mark; et al. (PLoS Genet, 2013)
We report on results from whole-exome sequencing (WES) of 1,039 subjects diagnosed with autism spectrum disorders (ASD) and 870 controls selected from the NIMH repository to be of similar ancestry to cases. The WES data came from two centers using different methods to produce sequence and to call variants from it. Therefore, an initial goal was to ensure the distribution of rare variation was similar for data from different centers. This proved straightforward by filtering called variants by fraction of missing data, read depth, and balance of alternative to reference reads. Results were evaluated using seven samples sequenced at both centers and by results from the association study. Next we addressed how the data and/or results from the centers should be combined. Gene-based analyses of association was an obvious choice, but should statistics for association be combined across centers (meta-analysis) or should data be combined and then analyzed (mega-analysis)? Because of the nature of many gene-based tests, we showed by theory and simulations that mega-analysis has better power than meta-analysis. Finally, before analyzing the data for association, we explored the impact of population structure on rare variant analysis in these data. Like other recent studies, we found evidence that population structure can confound case-control studies by the clustering of rare variants in ancestry space; yet, unlike some recent studies, for these data we found that principal component-based analyses were sufficient to control for ancestry and produce test statistics with appropriate distributions. After using a variety of gene-based tests and both meta- and mega-analysis, we found no new risk genes for ASD in this sample. Our results suggest that standard gene-based tests will require much larger samples of cases and controls before being effective for gene discovery, even for a disorder like ASD.
Keywords: Case-Control Studies; Child; Child Development Disorders, Pervasive; Exome; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Population Control; Sequence Analysis, DNA; Software

Assemblathon 2: evaluating de novo methods of genome assembly in three vertebrate species. - Bradnam, Keith R; Fass, Joseph N; Alexandrov, Anton; Baranay, Paul; Bechner, Michael; Birol, Inanç; Boisvert, Sébastien; Chapman, Jarrod A; Chapuis, Guillaume; Chikhi, Rayan; Chitsaz, Hamidreza; Chou, Wen-Chi; et al. (Gigascience, 2013)
BACKGROUND: The process of generating raw genome sequence data continues to become cheaper, faster, and more accurate. However, assembly of such data into high-quality, finished genome sequences remains challenging. Many genome assembly tools are available, but they differ greatly in terms of their performance (speed, scalability, hardware requirements, acceptance of newer read technologies) and in their final output (composition of assembled sequence). More importantly, it remains largely unclear how to best assess the quality of assembled genome sequences. The Assemblathon competitions are intended to assess current state-of-the-art methods in genome assembly. RESULTS: In Assemblathon 2, we provided a variety of sequence data to be assembled for three vertebrate species (a bird, a fish, and snake). This resulted in a total of 43 submitted assemblies from 21 participating teams. We evaluated these assemblies using a combination of optical map data, Fosmid sequences, and several statistical methods. From over 100 different metrics, we chose ten key measures by which to assess the overall quality of the assemblies. CONCLUSIONS: Many current genome assemblers produced useful assemblies, containing a significant representation of their genes and overall genome structure. However, the high degree of variability between the entries suggests that there is still much room for improvement in the field of genome assembly and that approaches which work well in assembling the genome of one species may not necessarily work well for another.

Bioactivity and bioavailability of ginsenosides are dependent on the glycosidase activities of the A/J mouse intestinal microbiome defined by pyrosequencing. - Niu, Tao; Smith, Diane L; Yang, Zhen; Gao, Song; Yin, Taijun; Jiang, Zhi-Hong; You, Ming; Richard A Gibbs; Petrosino, Joseph F; Hu, Ming (Pharm Res, 2013)
PURPOSE: To investigate the ability of bacteria in the intestinal microbiome to convert naturally occurring primary ginsenosides in red ginseng extract to active secondary ginsenosides. METHODS: Anti-proliferative ginsenoside activity was tested using mouse lung cancer LM1 cells. Permeabilities were evaluated in Caco-2 cell monolayers. Systemic exposure of secondary ginsenosides was determined in A/J mice. 16S rRNA gene pyrosequencing was used to determine membership and abundance of bacteria in intestinal microbiome. RESULTS: Secondary ginsenoside C-K exhibited higher anti-proliferative activity and permeability than primary ginsenosides. Significant amounts of secondary ginsenosides (F2 and C-K) were found in blood of A/J mice following oral administration of primary ginsenoside Rb1. Because mammalian cells did not hydrolyze ginsenoside, we determined the ability of bacteria to hydrolyze ginsenosides and found that Rb1 underwent stepwise hydrolysis to Rd, F2, and then C-K. Formation of F2 from Rd was the rate-limiting step in the biotransformation of Rb1 to C-K. CONCLUSION: Conversion to F2 is the rate-limiting step in bioactivation of primary ginsenosides by A/J mouse intestinal microbiome, whose characterization reveals the presence of certain bacterial families capable of enabling the formation of F2 and C-K in vivo.
Keywords: Animals; Antineoplastic Agents, Phytogenic; Bacteria; Biological Availability; Biotransformation; Caco-2 Cells; Cell Line, Tumor; Cell Proliferation; Drugs, Chinese Herbal; Ginsenosides; Glycoside Hydrolases; Humans; Hydrolysis; Intestinal Mucosa; Intestines; Male; Metagenome; Mice; Neoplasms; Panax; RNA, Bacterial

Characterizing polymorphisms and allelic diversity of von Willebrand factor gene in the 1000 Genomes. - Wang, Q Y; Song, J; Richard A Gibbs; Eric Boerwinkle; Dong, J F; Yu, F L (J Thromb Haemost, 2013)
BACKGROUND: The von Willebrand factor (VWF) gene is highly polymorphic, with variants correlated with VWF antigen levels, adhesion activity, clearance and factor VIII binding. VWF mutations are detected in patients with von Willebrand disease (VWD), whereas polymorphic variants could be associated with thrombosis. However, information on the ethnic diversity of VWF variants and their association with diseases is limited. OBJECTIVES: To characterize novel VWF variants from different ethnicities in the general population. PATIENTS/METHODS: We analyzed samples from 1092 subjects of 14 ethnicities available in the 1000 Genomes database for VWF variants and their potential functional impacts. RESULTS: We identified 2728 SNPs and 91 insertions and deletions that had a high level of ethnic diversity, with Africans having the highest number of variants. The highest level of diversity was found in the D' and D2 domains. Among 94 non-synonymous variants, 31 were predicted to be deleterious, including 19 that were previously associated with VWD. Most of these 'VWD variants' had allele frequencies consistent with disease incidence in European subjects, but some had a significantly higher frequency in other ethnicities. The mutations R2185Q, H817Q and M740I associated with type 1 and type 2N VWD were present in more than 13% of African subjects. CONCLUSIONS: These results highlight the complexity of VWF variations in different ethnic groups and emphasize the importance of interrogating variations on multiple ethnic backgrounds for associations with bleeding and thrombosis.
Keywords: Asian People; Black or African American; Black People; Databases, Genetic; DNA Mutational Analysis; Ethnicity; Gene Frequency; Genetic Predisposition to Disease; Hemostasis; Human Genome Project; Humans; Incidence; Mutation; Phenotype; Polymorphism, Single Nucleotide; von Willebrand Diseases; von Willebrand Factor; White People

Combined sequence-based and genetic mapping analysis of complex traits in outbred rats. - Baud, Amelie; Hermsen, Roel; Guryev, Victor; Stridh, Pernilla; Graham, Delyth; McBride, Martin W; Foroud, Tatiana; Calderari, Sophie; Diez, Margarita; Ockinger, Johan; Beyeen, Amennai D; Gillett, Alan; et al. (Nat Genet, 2013)
Genetic mapping on fully sequenced individuals is transforming understanding of the relationship between molecular variation and variation in complex traits. Here we report a combined sequence and genetic mapping analysis in outbred rats that maps 355 quantitative trait loci for 122 phenotypes. We identify 35 causal genes involved in 31 phenotypes, implicating new genes in models of anxiety, heart disease and multiple sclerosis. The relationship between sequence and genetic variation is unexpectedly complex: at approximately 40% of quantitative trait loci, a single sequence variant cannot account for the phenotypic effect. Using comparable sequence and mapping data from mice, we show that the extent and spatial pattern of variation in inbred rats differ substantially from those of inbred mice and that the genetic variants in orthologous genes rarely contribute to the same phenotype in both species.
Keywords: Animals; Animals, Outbred Strains; Anxiety; Chromosome Mapping; Genetic Variation; Genotype; Heart Diseases; Humans; Mice; Mice, Inbred C57BL; Models, Molecular; Multiple Sclerosis; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Rats; Sequence Analysis, DNA

Complete Genome Sequence of Elephant Endotheliotropic Herpesvirus 1A. - Ling, Paul D; Reid, Jeffrey G; Qin, Xiang; Donna M Muzny; Richard A Gibbs; Petrosino, Joseph; Peng, Rongsheng; Zong, Jian-Chao; Heaggans, Sarah Y; Hayward, Gary S (Genome Announc, 2013)
Elephant endotheliotropic herpesvirus 1A is a member of the Proboscivirus genus and is a major cause of fatal hemorrhagic disease in endangered juvenile Asian elephants worldwide. Here, we report the first complete genome sequence from this genus, obtained directly from necropsy DNA, in which 60 of the 115 predicted genes are not found in any known herpesvirus.

CRHR1 genotypes, neural circuits and the diathesis for anxiety and depression. - Rogers, J; Raveendran, M; Fawcett, G L; Fox, A S; Shelton, S E; Oler, J A; Cheverud, J; Donna M Muzny; Richard A Gibbs; Davidson, R J; Kalin, N H (Mol Psychiatry, 2013)
The corticotrophin-releasing hormone (CRH) system integrates the stress response and is associated with stress-related psychopathology. Previous reports have identified interactions between childhood trauma and sequence variation in the CRH receptor 1 gene (CRHR1) that increase risk for affective disorders. However, the underlying mechanisms that connect variation in CRHR1 to psychopathology are unknown. To explore potential mechanisms, we used a validated rhesus macaque model to investigate association between genetic variation in CRHR1, anxious temperament (AT) and brain metabolic activity. In young rhesus monkeys, AT is analogous to the childhood risk phenotype that predicts the development of human anxiety and depressive disorders. Regional brain metabolism was assessed with (18)F-labeled fluoro-2-deoxyglucose (FDG) positron emission tomography in 236 young, normally reared macaques that were also characterized for AT. We show that single nucleotide polymorphisms (SNPs) affecting exon 6 of CRHR1 influence both AT and metabolic activity in the anterior hippocampus and amygdala, components of the neural circuit underlying AT. We also find evidence for association between SNPs in CRHR1 and metabolism in the intraparietal sulcus and precuneus. These translational data suggest that genetic variation in CRHR1 affects the risk for affective disorders by influencing the function of the neural circuit underlying AT and that differences in gene expression or the protein sequence involving exon 6 may be important. These results suggest that variation in CRHR1 may influence brain function before any childhood adversity and may be a diathesis for the interaction between CRHR1 genotypes and childhood trauma reported to affect human psychopathology.
Keywords: Animals; Anxiety; Brain; Depression; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Macaca mulatta; Male; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Receptors, Corticotropin-Releasing Hormone

De novo truncating mutations in ASXL3 are associated with a novel clinical phenotype with similarities to Bohring-Opitz syndrome. - Bainbridge, Matthew N; Hu, Hao; Donna M Muzny; Musante, Luciana; Lupski, James R; Graham, Brett H; Chen, Wei; Gripp, Karen W; Jenny, Kim; Wienker, Thomas F; Yang, Yaping; Sutton, V Reid; et al. (Genome Med, 2013)
BACKGROUND: Molecular diagnostics can resolve locus heterogeneity underlying clinical phenotypes that may otherwise be co-assigned as a specific syndrome based on shared clinical features, and can associate phenotypically diverse diseases to a single locus through allelic affinity. Here we describe an apparently novel syndrome, likely caused by de novo truncating mutations in ASXL3, which shares characteristics with Bohring-Opitz syndrome, a disease associated with de novo truncating mutations in ASXL1. METHODS: We used whole-genome and whole-exome sequencing to interrogate the genomes of four subjects with an undiagnosed syndrome. RESULTS: Using genome-wide sequencing, we identified heterozygous, de novo truncating mutations in ASXL3, a transcriptional repressor related to ASXL1, in four unrelated probands. We found that these probands shared similar phenotypes, including severe feeding difficulties, failure to thrive, and neurologic abnormalities with significant developmental delay. Further, they showed less phenotypic overlap with patients who had de novo truncating mutations in ASXL1. CONCLUSION: We have identified truncating mutations in ASXL3 as the likely cause of a novel syndrome with phenotypic overlap with Bohring-Opitz syndrome.

Deep resequencing and association analysis of schizophrenia candidate genes. - Crowley, J J; Hilliard, C E; Kim, Y; Morgan, M B; Lewis, L R; Donna M Muzny; Hawes, A C; Aniko Sabo; Wheeler, D A; Lieberman, J A; Sullivan, P F; Richard A Gibbs (Mol Psychiatry, 2013)
Keywords: Adolescent; Adult; Aged; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Schizophrenia; Young Adult

Exome sequencing resolves apparent incidental findings and reveals further complexity of SH3TC2 variant alleles causing Charcot-Marie-Tooth neuropathy. - Lupski, James R; Gonzaga-Jauregui, Claudia; Yang, Yaping; Bainbridge, Matthew N; Jhangiani, Shalini; Buhay, Christian J; Kovar, Christie L; Wang, Min; Hawes, Alicia C; Reid, Jeffrey G; Eng, Christine; Donna M Muzny; et al. (Genome Med, 2013)
BACKGROUND: The debate regarding the relative merits of whole genome sequencing (WGS) versus exome sequencing (ES) centers around comparative cost, average depth of coverage for each interrogated base, and their relative efficiency in the identification of medically actionable variants from the myriad of variants identified by each approach. Nevertheless, few genomes have been subjected to both WGS and ES, using multiple next generation sequencing platforms. In addition, no personal genome has been so extensively analyzed using DNA derived from peripheral blood as opposed to DNA from transformed cell lines that may either accumulate mutations during propagation or clonally expand mosaic variants during cell transformation and propagation. METHODS: We investigated a genome that was studied previously by SOLiD chemistry using both ES and WGS, and now perform six independent ES assays (Illumina GAII (x2), Illumina HiSeq (x2), Life Technologies' Personal Genome Machine (PGM) and Proton), and one additional WGS (Illumina HiSeq). RESULTS: We compared the variants identified by the different methods and provide insights into the differences among variants identified between ES runs in the same technology platform and among different sequencing technologies. We resolved the true genotypes of medically actionable variants identified in the proband through orthogonal experimental approaches. Furthermore, ES identified an additional SH3TC2 variant (p.M1?) that likely contributes to the phenotype in the proband. CONCLUSIONS: ES identified additional medically actionable variant calls and helped resolve ambiguous single nucleotide variants (SNV) documenting the power of increased depth of coverage of the captured targeted regions. Comparative analyses of WGS and ES reveal that pseudogenes and segmental duplications may explain some instances of apparent disease mutations in unaffected individuals.

Exploring the utility of whole-exome sequencing as a diagnostic tool in a child with atypical episodic muscle weakness. - Hanchard, Neil A; David R Murdock; Magoulas, Pilar L; Matthew N Bainbridge; Donna M Muzny; Wu, Yuanqing; Wang, Min; James R Lupski; Richard A Gibbs; Brown, Chester W (Clin Genet, 2013)
The advent of whole-exome next-generation sequencing (WES) has been pivotal for the molecular characterization of Mendelian disease; however, the clinical applicability of WES has remained relatively unexplored. We describe our exploration of WES as a diagnostic tool in a 3½-year old female patient with a 2-year history of episodic muscle weakness and paroxysmal dystonia who presented following a previous extensive but unrevealing diagnostic work-up. WES was performed on the proband and her two parents. Parental exome data was used to filter potential de novo genomic events in the proband and suspected variants were confirmed using di-deoxy sequencing. WES revealed a de novo non-synonymous mutation in exon 21 of the calcium channel gene CACNA1S that has been previously reported in a single patient as a rare cause of atypical hypokalemic periodic paralysis. This was unexpected, as the proband's original differential diagnosis had included hypokalemic periodic paralysis, but clinical and laboratory features were equivocal, and standard clinical molecular testing for hypokalemic periodic paralysis and related disorders was negative. This report highlights the potential diagnostic utility of WES in clinical practice, with implications for the approach to similar diagnostic dilemmas in the future.
Keywords: Base Sequence; Calcium Channels; Child, Preschool; Exome; Exons; Female; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Muscle Weakness; Mutation; NAV1.4 Voltage-Gated Sodium Channel; Pedigree; Phenotype

Identification of TP53 as an acute lymphocytic leukemia susceptibility gene through exome sequencing. - Powell, Bradford C; Jiang, Lichun; Donna M Muzny; Treviño, Lisa R; Dreyer, Zoann E; Strong, Louise C; Wheeler, David A; Richard A Gibbs; Plon, Sharon E (Pediatr Blood Cancer, 2013)
Although acute lymphocytic leukemia (ALL) is the most common childhood cancer, genetic predisposition to ALL remains poorly understood. Whole-exome sequencing was performed in an extended kindred in which five individuals had been diagnosed with leukemia. Analysis revealed a nonsense variant of TP53 which has been previously reported in families with sarcomas and other typical Li Fraumeni syndrome-associated cancers but never in a familial leukemia kindred. This unexpected finding enabled identification of an appropriate sibling bone marrow donor and illustrates that exome sequencing will reveal atypical clinical presentations of even well-studied genes.
Keywords: Exome; Female; Genetic Predisposition to Disease; Humans; Male; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Tumor Suppressor Protein p53

Integrative annotation of variants from 1092 humans: application to cancer genomics. - Khurana, Ekta; Fu, Yao; Colonna, Vincenza; Mu, Xinmeng Jasmine; Kang, Hyun Min; Lappalainen, Tuuli; Sboner, Andrea; Lochovsky, Lucas; Chen, Jieming; Harmanci, Arif; Das, Jishnu; Abyzov, Alexej; et al. (Science, 2013)
Interpreting variants, especially noncoding ones, in the increasing number of personal genomes is challenging. We used patterns of polymorphisms in functionally annotated regions in 1092 humans to identify deleterious variants; then we experimentally validated candidates. We analyzed both coding and noncoding regions, with the former corroborating the latter. We found regions particularly sensitive to mutations ("ultrasensitive") and variants that are disruptive because of mechanistic effects on transcription-factor binding (that is, "motif-breakers"). We also found variants in regions with higher network centrality tend to be deleterious. Insertions and deletions followed a similar pattern to single-nucleotide variants, with some notable exceptions (e.g., certain deletions and enhancers). On the basis of these patterns, we developed a computational tool (FunSeq), whose application to ~90 cancer genomes reveals nearly a hundred candidate noncoding drivers.
Keywords: Binding Sites; Genetic Variation; Genome, Human; Genomics; Humans; Kruppel-Like Transcription Factors; Molecular Sequence Annotation; Mutation; Neoplasms; Polymorphism, Single Nucleotide; Population; RNA, Untranslated; Selection, Genetic

Integrative genomic characterization of oral squamous cell carcinoma identifies frequent somatic drivers. - Pickering, Curtis R; Zhang, Jiexin; Yoo, Suk Young; Bengtsson, Linnea; Moorthy, Shhyam; Neskey, David M; Zhao, Mei; Ortega Alves, Marcus V; Chang, Kyle; Drummond, Jennifer; Cortez, Elsa; Xie, Tong-Xin; et al. (Cancer Discov, 2013)
The survival of patients with oral squamous cell carcinoma (OSCC) has not changed significantly in several decades, leading clinicians and investigators to search for promising molecular targets. To this end, we conducted comprehensive genomic analysis of gene expression, copy number, methylation, and point mutations in OSCC. Integrated analysis revealed more somatic events than previously reported, identifying four major driver pathways (mitogenic signaling, Notch, cell cycle, and TP53) and two additional key genes (FAT1, CASP8). The Notch pathway was defective in 66% of patients, and in follow-up studies of mechanism, functional NOTCH1 signaling inhibited proliferation of OSCC cell lines. Frequent mutation of caspase-8 (CASP8) defines a new molecular subtype of OSCC with few copy number changes. Although genomic alterations are dominated by loss of tumor suppressor genes, 80% of patients harbored at least one genomic alteration in a targetable gene, suggesting that novel approaches to treatment may be possible for this debilitating subset of head and neck cancers.
Keywords: Carcinoma, Squamous Cell; Caspase 8; Cell Line, Tumor; DNA Copy Number Variations; DNA Methylation; Gene Expression Regulation, Neoplastic; Genomics; Humans; Mouth Neoplasms; Point Mutation; Receptors, Notch

An integrative variant analysis pipeline for accurate genotype/haplotype inference in population NGS data. - Wang, Yi; Lu, James; Yu, Jin; Richard A Gibbs; Fuli Yu (Genome Res, 2013)
Next-generation sequencing is a powerful approach for discovering genetic variation. Sensitive variant calling and haplotype inference from population sequencing data remain challenging. We describe methods for high-quality discovery, genotyping, and phasing of SNPs for low-coverage (approximately 5×) sequencing of populations, implemented in a pipeline called SNPTools. Our pipeline contains several innovations that specifically address challenges caused by low-coverage population sequencing: (1) effective base depth (EBD), a nonparametric statistic that enables more accurate statistical modeling of sequencing data; (2) variance ratio scoring, a variance-based statistic that discovers polymorphic loci with high sensitivity and specificity; and (3) BAM-specific binomial mixture modeling (BBMM), a clustering algorithm that generates robust genotype likelihoods from heterogeneous sequencing data. Last, we develop an imputation engine that refines raw genotype likelihoods to produce high-quality phased genotypes/haplotypes. Designed for large population studies, SNPTools' input/output (I/O) and storage aware design leads to improved computing performance on large sequencing data sets. We apply SNPTools to the International 1000 Genomes Project (1000G) Phase 1 low-coverage data set and obtain genotyping accuracy comparable to that of SNP microarray.
Keywords: Algorithms; Base Sequence; Genotype; Haplotypes; High-Throughput Nucleotide Sequencing; Human Genome Project; Humans; Polymorphism, Single Nucleotide

MLH1-silenced and non-silenced subgroups of hypermutated colorectal carcinomas have distinct mutational landscapes. - Donehower, Lawrence A; Creighton, Chad J; Schultz, Nikolaus; Shinbrot, Eve; Chang, Kyle; Gunaratne, Preethi H; Donna M Muzny; Sander, Chris; Hamilton, Stanley R; Richard A Gibbs; Wheeler, David (J Pathol, 2013)
Approximately 15% of colorectal carcinomas (CRCs) exhibit a hypermutated genotype accompanied by high levels of microsatellite instability (MSI-H) and defects in DNA mismatch repair. These tumours, unlike the majority of colorectal carcinomas, are often diploid, exhibit frequent epigenetic silencing of the MLH1 DNA mismatch repair gene, and have a better clinical prognosis. As an adjunct study to The Cancer Genome Atlas consortium that recently analysed 224 colorectal cancers by whole exome sequencing, we compared the 35 CRCs (15.6%) with a hypermutated genotype to those with a non-hypermutated genotype. We found that 22 (63%) of the hypermutated CRCs exhibited transcriptional silencing of the MLH1 gene, a high frequency of BRAF V600E gene mutations, and infrequent APC and KRAS mutations, a mutational pattern significantly different from their non-hypermutated counterparts. However, the remaining 13 (37%) hypermutated CRCs lacked MLH1 silencing, contained tumours with the highest mutation rates ('ultramutated' CRCs), and exhibited higher incidences of APC and KRAS mutations, but infrequent BRAF mutations. These patterns were confirmed in an independent validation set of 250 exome-sequenced CRCs. Analysis of mRNA and microRNA expression signatures revealed that hypermutated CRCs with MLH1 silencing had greatly reduced levels of WNT signalling and increased BRAF signalling relative to non-hypermutated CRCs. Our findings suggest that hypermutated CRCs include one subgroup with fundamentally different pathways to malignancy than the majority of CRCs. Examination of MLH1 expression status and frequencies of APC, KRAS, and BRAF mutation in CRC may provide a useful diagnostic tool that could supplement the standard microsatellite instability assays and influence therapeutic decisions.
Keywords: Adaptor Proteins, Signal Transducing; Adenomatous Polyposis Coli Protein; Carcinoma; Colorectal Neoplasms; Gene Expression Profiling; Gene Expression Regulation, Enzymologic; Gene Expression Regulation, Neoplastic; Gene Frequency; Gene Silencing; Genetic Predisposition to Disease; Humans; MicroRNAs; Microsatellite Instability; Mutation; MutL Protein Homolog 1; Nuclear Proteins; Oligonucleotide Array Sequence Analysis; Phenotype; Prognosis; Proto-Oncogene Proteins; Proto-Oncogene Proteins B-raf; Proto-Oncogene Proteins p21(ras); ras Proteins; RNA, Messenger; Wnt Signaling Pathway

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases

Rare complete knockouts in humans: population distribution and significant role in autism spectrum disorders. - Lim, Elaine T; Raychaudhuri, Soumya; Sanders, Stephan J; Stevens, Christine; Aniko Sabo; MacArthur, Daniel G; Neale, Benjamin M; Kirby, Andrew; Ruderfer, Douglas M; Fromer, Menachem; Lek, Monkol; Liu, Li; et al. (Neuron, 2013)
To characterize the role of rare complete human knockouts in autism spectrum disorders (ASDs), we identify genes with homozygous or compound heterozygous loss-of-function (LoF) variants (defined as nonsense and essential splice sites) from exome sequencing of 933 cases and 869 controls. We identify a 2-fold increase in complete knockouts of autosomal genes with low rates of LoF variation (≤ 5% frequency) in cases and estimate a 3% contribution to ASD risk by these events, confirming this observation in an independent set of 563 probands and 4,605 controls. Outside the pseudoautosomal regions on the X chromosome, we similarly observe a significant 1.5-fold increase in rare hemizygous knockouts in males, contributing to another 2% of ASDs in males. Taken together, these results provide compelling evidence that rare autosomal and X chromosome complete gene knockouts are important inherited risk factors for ASD.
Keywords: Case-Control Studies; Child Development Disorders, Pervasive; Child, Preschool; Chromosomes, Human, X; Demography; Female; Gene Deletion; Genetic Variation; Homozygote; Humans; Linkage Disequilibrium; Loss of Heterozygosity; Male; Risk Factors

Whole-genome sequence-based analysis of high-density lipoprotein cholesterol. - Morrison, Alanna C; Voorman, Arend; Johnson, Andrew D; Liu, Xiaoming; Yu, Jin; Li, Alexander; Donna M Muzny; Fuli Yu; Rice, Kenneth; Zhu, Chengsong; Bis, Joshua; Heiss, Gerardo; et al. (Nat Genet, 2013)
We describe initial steps for interrogating whole-genome sequence data to characterize the genetic architecture of a complex trait, levels of high-density lipoprotein cholesterol (HDL-C). We report whole-genome sequencing and analysis of 962 individuals from the Cohorts for Heart and Aging Research in Genetic Epidemiology (CHARGE) studies. From this analysis, we estimate that common variation contributes more to heritability of HDL-C levels than rare variation, and screening for mendelian variants for dyslipidemia identified individuals with extreme HDL-C levels. Whole-genome sequencing analyses highlight the value of regulatory and non-protein-coding regions of the genome in addition to protein-coding regions.
Keywords: Cholesterol, HDL; Computational Biology; Databases, Genetic; Genetic Variation; Genome, Human; Genome-Wide Association Study; Genomics; Heterozygote; Humans; Open Reading Frames

Analysis of microsatellite variation in Drosophila melanogaster with population-scale genome sequencing. - Fondon, John W; Martin, Andy; Richards, Stephen; Richard A Gibbs; Mittelman, David (PLoS One, 2012)
Genome sequencing technologies promise to revolutionize our understanding of genetics, evolution, and disease by making it feasible to survey a broad spectrum of sequence variation on a population scale. However, this potential can only be realized to the extent that methods for extracting and interpreting distinct forms of variation can be established. The error profiles and read length limitations of early versions of next-generation sequencing technologies rendered them ineffective for some sequence variant types, particularly microsatellites and other tandem repeats, and fostered the general misconception that such variants are inherently inaccessible to these platforms. At the same time, tandem repeats have emerged as important sources of functional variation. Tandem repeats are often located in and around genes, and frequent mutations in their lengths exert quantitative effects on gene function and phenotype, rapidly degrading linkage disequilibrium between markers and traits. Sensitive identification of these variants in large-scale next-gen sequencing efforts will enable more comprehensive association studies capable of revealing previously invisible associations. We present a population-scale analysis of microsatellite repeats using whole-genome data from 158 inbred isolates from the Drosophila Genetics Reference Panel, a collection of over 200 extensively phenotypically characterized isolates from a single natural population, to uncover processes underlying repeat mutation and to enable associations with behavioral, morphological, and life-history traits. Analysis of repeat variation from next-generation sequence data will also enhance studies of genome stability and neurodegenerative diseases.
Keywords: Animals; Drosophila melanogaster; Genetic Variation; Genetics, Population; Genome; Genotype; Microsatellite Repeats; Mutation

The Centers for Mendelian Genomics: a new large-scale initiative to identify the genes underlying rare Mendelian conditions. - Bamshad, Michael J; Shendure, Jay A; Valle, David; Hamosh, Ada; Lupski, James R; Richard A Gibbs; Eric Boerwinkle; Lifton, Richard P; Gerstein, Mark; Gunel, Murat; Mane, Shrikant; Nickerson, Deborah A (Am J Med Genet A, 2012)
Next generation exome sequencing (ES) and whole genome sequencing (WGS) are new powerful tools for discovering the gene(s) that underlie Mendelian disorders. To accelerate these discoveries, the National Institutes of Health has established three Centers for Mendelian Genomics (CMGs): the Center for Mendelian Genomics at the University of Washington; the Center for Mendelian Genomics at Yale University; and the Baylor-Johns Hopkins Center for Mendelian Genomics at Baylor College of Medicine and Johns Hopkins University. The CMGs will provide ES/WGS and extensive analysis expertise at no cost to collaborating investigators where the causal gene(s) for a Mendelian phenotype has yet to be uncovered. Over the next few years and in collaboration with the global human genetics community, the CMGs hope to facilitate the identification of the genes underlying a very large fraction of all Mendelian disorders; see http://mendelian.org.
Keywords: Academies and Institutes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Genome-Wide Association Study; Genomics; High-Throughput Nucleotide Sequencing; Humans

Characterizing linkage disequilibrium and evaluating imputation power of human genomic insertion-deletion polymorphisms. - Lu, James T; Wang, Yi; Richard A Gibbs; Fuli Yu (Genome Biol, 2012)
BACKGROUND: Indels are an important cause of human variation and central to the study of human disease. The 1000 Genomes Project Low-Coverage Pilot identified over 1.3 million indels shorter than 50 bp, of which over 890 were identified as potentially disruptive variants. Yet, despite their ubiquity, the local genomic characteristics of indels remain unexplored. RESULTS: Herein we describe population- and minor allele frequency-based differences in linkage disequilibrium and imputation characteristics for indels included in the 1000 Genomes Project Low-Coverage Pilot for the CEU, YRI and CHB+JPT populations. Common indels were well tagged by nearby SNPs in all studied populations, and were also tagged at a similar rate to common SNPs. Both neutral and functionally deleterious common indels were imputed with greater than 95% concordance from HapMap Phase 3 and OMNI SNP sites. Further, 38 to 56% of low frequency indels were tagged by low frequency SNPs. We were able to impute heterozygous low frequency indels with over 50% concordance. Lastly, our analysis also revealed evidence of ascertainment bias. This bias prevents us from extending the applicability of our results to highly polymorphic indels that could not be identified in the Low-Coverage Pilot. CONCLUSIONS: Although further scope exists to improve the imputation of low frequency indels, our study demonstrates that there are already ample opportunities to retrospectively impute indels for prior genome-wide association studies and to incorporate indel imputation into future case/control studies.
Keywords: Gene Frequency; Genetics, Population; Genome, Human; Genome-Wide Association Study; HapMap Project; Heterozygote; Humans; INDEL Mutation; Linkage Disequilibrium; Polymorphism, Genetic; Polymorphism, Single Nucleotide

Complete genome sequence of Enterococcus faecium strain TX16 and comparative genomic analysis of Enterococcus faecium genomes. - Qin, Xiang; Galloway-Peña, Jessica R; Sillanpaa, Jouko; Roh, Jung Hyeob; Nallapareddy, Sreedhar R; Chowdhury, Shahreen; Bourgogne, Agathe; Choudhury, Tina; Donna M Muzny; Buhay, Christian J; Ding, Yan; Dugan-Rocha, Shannon; et al. (BMC Microbiol, 2012)
BACKGROUND: Enterococci are among the leading causes of hospital-acquired infections in the United States and Europe, with Enterococcus faecalis and Enterococcus faecium being the two most common species isolated from enterococcal infections. In the last decade, the proportion of enterococcal infections caused by E. faecium has steadily increased compared to other Enterococcus species. Although the underlying mechanism for the gradual replacement of E. faecalis by E. faecium in the hospital environment is not yet understood, many studies using genotyping and phylogenetic analysis have shown the emergence of a globally dispersed polyclonal subcluster of E. faecium strains in clinical environments. Systematic study of the molecular epidemiology and pathogenesis of E. faecium has been hindered by the lack of closed, complete E. faecium genomes that can be used as references. RESULTS: In this study, we report the complete genome sequence of the E. faecium strain TX16, also known as DO, which belongs to multilocus sequence type (ST) 18, and was the first E. faecium strain ever sequenced. Whole genome comparison of the TX16 genome with 21 E. faecium draft genomes confirmed that most clinical, outbreak, and hospital-associated (HA) strains (including STs 16, 17, 18, and 78), in addition to strains of non-hospital origin, group in the same clade (referred to as the HA clade) and are evolutionally considerably more closely related to each other by phylogenetic and gene content similarity analyses than to isolates in the community-associated (CA) clade with approximately a 3-4% average nucleotide sequence difference between the two clades at the core genome level. Our study also revealed that many genomic loci in the TX16 genome are unique to the HA clade. 380 ORFs in TX16 are HA-clade specific and antibiotic resistance genes are enriched in HA-clade strains. Mobile elements such as IS16 and transposons were also found almost exclusively in HA strains, as previously reported. CONCLUSIONS: Our findings along with other studies show that HA clonal lineages harbor specific genetic elements as well as sequence differences in the core genome which may confer selection advantages over the more heterogeneous CA E. faecium isolates. Which of these differences are important for the success of specific E. faecium lineages in the hospital environment remain(s) to be determined.
Keywords: DNA, Bacterial; Enterococcus faecium; Genome, Bacterial; Humans; Molecular Sequence Data; Sequence Analysis, DNA

Deep sequencing of systematic combinatorial libraries reveals β-lactamase sequence constraints at high resolution. - Deng, Zhifeng; Huang, Wanzhi; Bakkalbasi, Erol; Brown, Nicholas G; Adamski, Carolyn J; Rice, Kacie; Donna M Muzny; Richard A Gibbs; Palzkill, Timothy (J Mol Biol, 2012)
In this study, combinatorial libraries were used in conjunction with ultrahigh-throughput sequencing to comprehensively determine the impact of each of the 19 possible amino acid substitutions at each residue position in the TEM-1 β-lactamase enzyme. The libraries were introduced into Escherichiacoli, and mutants were selected for ampicillin resistance. The selected colonies were pooled and subjected to ultrahigh-throughput sequencing to reveal the sequence preferences at each position. The depth of sequencing provided a clear, statistically significant picture of what amino acids are favored for ampicillin hydrolysis for all 263 positions of the enzyme in one experiment. Although the enzyme is generally tolerant of amino acid substitutions, several surface positions far from the active site are sensitive to substitutions suggesting a role for these residues in enzyme stability, solubility, or catalysis. In addition, information on the frequency of substitutions was used to identify mutations that increase enzyme thermodynamic stability. Finally, a comparison of sequence requirements based on the mutagenesis results versus those inferred from sequence conservation in an alignment of 156 class A β-lactamases reveals significant differences in that several residues in TEM-1 do not tolerate substitutions and yet extensive variation is observed in the alignment and vice versa. An analysis of the TEM-1 and other class A structures suggests that residues that vary in the alignment may nevertheless make unique, but important, interactions within individual enzymes.
Keywords: Amino Acid Sequence; Amino Acid Substitution; Ampicillin; Ampicillin Resistance; Base Sequence; beta-Lactamases; DNA Mutational Analysis; Enzyme Stability; Escherichia coli; Gene Library; High-Throughput Nucleotide Sequencing; Hydrolysis; Models, Molecular; Mutant Proteins; Mutation Rate; Selection, Genetic; Solubility; Thermodynamics

The Drosophila melanogaster Genetic Reference Panel. - Mackay, Trudy F C; Richards, Stephen; Stone, Eric A; Barbadilla, Antonio; Ayroles, Julien F; Zhu, Dianhui; Casillas, Sònia; Yi Han; Magwire, Michael M; Cridland, Julie M; Richardson, Mark F; Anholt, Robert R H; et al. (Nature, 2012)
A major challenge of biology is understanding the relationship between molecular genetic variation and variation in quantitative traits, including fitness. This relationship determines our ability to predict phenotypes from genotypes and to understand how evolutionary forces shape variation within and between species. Previous efforts to dissect the genotype-phenotype map were based on incomplete genotypic information. Here, we describe the Drosophila melanogaster Genetic Reference Panel (DGRP), a community resource for analysis of population genomics and quantitative traits. The DGRP consists of fully sequenced inbred lines derived from a natural population. Population genomic analyses reveal reduced polymorphism in centromeric autosomal regions and the X chromosome, evidence for positive and negative selection, and rapid evolution of the X chromosome. Many variants in novel genes, most at low frequency, are associated with quantitative traits and explain a large fraction of the phenotypic variance. The DGRP facilitates genotype-phenotype mapping using the power of Drosophila genetics.
Keywords: Alleles; Animals; Centromere; Chromosomes, Insect; Drosophila melanogaster; Genome-Wide Association Study; Genomics; Genotype; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Selection, Genetic; Starvation; Telomere; X Chromosome

Epistasis dominates the genetic architecture of Drosophila quantitative traits. - Huang, Wen; Richards, Stephen; Carbone, Mary Anna; Zhu, Dianhui; Anholt, Robert R H; Ayroles, Julien F; Duncan, Laura; Jordan, Katherine W; Lawrence, Faye; Magwire, Michael M; Warner, Crystal B; Blankenburg, Kerstin; et al. (Proc Natl Acad Sci U S A, 2012)
Epistasis-nonlinear genetic interactions between polymorphic loci-is the genetic basis of canalization and speciation, and epistatic interactions can be used to infer genetic networks affecting quantitative traits. However, the role that epistasis plays in the genetic architecture of quantitative traits is controversial. Here, we compared the genetic architecture of three Drosophila life history traits in the sequenced inbred lines of the Drosophila melanogaster Genetic Reference Panel (DGRP) and a large outbred, advanced intercross population derived from 40 DGRP lines (Flyland). We assessed allele frequency changes between pools of individuals at the extremes of the distribution for each trait in the Flyland population by deep DNA sequencing. The genetic architecture of all traits was highly polygenic in both analyses. Surprisingly, none of the SNPs associated with the traits in Flyland replicated in the DGRP and vice versa. However, the majority of these SNPs participated in at least one epistatic interaction in the DGRP. Despite apparent additive effects at largely distinct loci in the two populations, the epistatic interactions perturbed common, biologically plausible, and highly connected genetic networks. Our analysis underscores the importance of epistasis as a principal factor that determines variation for quantitative traits and provides a means to uncover genetic networks affecting these traits. Knowledge of epistatic networks will contribute to our understanding of the genetic basis of evolutionarily and clinically important traits and enhance predictive ability at an individualized level in medicine and agriculture.
Keywords: Animals; Drosophila melanogaster; Epistasis, Genetic; Genes, Insect; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Gene structure in the sea urchin Strongylocentrotus purpuratus based on transcriptome analysis. - Tu, Qiang; Cameron, R Andrew; Worley, Kim C; Richard A Gibbs; Davidson, Eric H (Genome Res, 2012)
A comprehensive transcriptome analysis has been performed on protein-coding RNAs of Strongylocentrotus purpuratus, including 10 different embryonic stages, six feeding larval and metamorphosed juvenile stages, and six adult tissues. In this study, we pooled the transcriptomes from all of these sources and focused on the insights they provide for gene structure in the genome of this recently sequenced model system. The genome had initially been annotated by use of computational gene model prediction algorithms. A large fraction of these predicted genes were recovered in the transcriptome when the reads were mapped to the genome and appropriately filtered and analyzed. However, in a manually curated subset, we discovered that more than half the computational gene model predictions were imperfect, containing errors such as missing exons, prediction of nonexistent exons, erroneous intron/exon boundaries, fusion of adjacent genes, and prediction of multiple genes from single genes. The transcriptome data have been used to provide a systematic upgrade of the gene model predictions throughout the genome, very greatly improving the research usability of the genomic sequence. We have constructed new public databases that incorporate information from the transcriptome analyses. The transcript-based gene model data were used to define average structural parameters for S. purpuratus protein-coding genes. In addition, we constructed a custom sea urchin gene ontology, and assigned about 7000 different annotated transcripts to 24 functional classes. Strong correlations became evident between given functional ontology classes and structural properties, including gene size, exon number, and exon and intron size.
Keywords: Animals; Computational Biology; Databases, Nucleic Acid; Exons; Female; Gene Expression Profiling; Genome; Introns; Male; Models, Genetic; Molecular Sequence Annotation; Molecular Sequence Data; Open Reading Frames; RNA, Spliced Leader; Strongylocentrotus purpuratus; Trans-Splicing; Transcriptome

Gene therapy rescues cilia defects and restores olfactory function in a mammalian ciliopathy model. - McIntyre, Jeremy C; Davis, Erica E; Joiner, Ariell; Williams, Corey L; Tsai, I-Chun; Jenkins, Paul M; McEwen, Dyke P; Zhang, Lian; Escobado, John; Thomas, Sophie; Szymanska, Katarzyna; Johnson, Colin A; et al. (Nat Med, 2012)
Cilia are evolutionarily conserved microtubule-based organelles that are crucial for diverse biological functions, including motility, cell signaling and sensory perception. In humans, alterations in the formation and function of cilia manifest clinically as ciliopathies, a growing class of pleiotropic genetic disorders. Despite the substantial progress that has been made in identifying genes that cause ciliopathies, therapies for these disorders are not yet available to patients. Although mice with a hypomorphic mutation in the intraflagellar transport protein IFT88 (Ift88Tg737Rpw mice, also known as ORPK mice)5 have been well studied, the relevance of IFT88 mutations to human pathology is unknown. We show that a mutation in IFT88 causes a hitherto unknown human ciliopathy. In vivo complementation assays in zebrafish and mIMCD3 cells show the pathogenicity of this newly discovered allele. We further show that ORPK mice are functionally anosmic as a result of the loss of cilia on their olfactory sensory neurons (OSNs). Notably, adenoviral-mediated expression of IFT88 in mature, fully differentiated OSNs of ORPK mice is sufficient to restore ciliary structures and rescue olfactory function. These studies are the first to use in vivo therapeutic treatment to reestablish cilia in a mammalian ciliopathy. More broadly, our studies indicate that gene therapy is a viable option for cellular and functional rescue of the complex ciliary organelle in established differentiated cells.
Keywords: Adenoviridae; Animals; Cilia; Genetic Complementation Test; Genetic Diseases, Inborn; Genetic Therapy; Genetic Vectors; Humans; Mice; Microscopy, Fluorescence; Mutation; Olfactory Receptor Neurons; Smell; Tubulin; Tumor Suppressor Proteins; Zebrafish

Genomic sequencing of key genes in mouse pancreatic cancer cells. - Wang, Y; Zhang, Y; Yang, J; Ni, X; Liu, S; Li, Z; Hodges, S E; Fisher, W E; Brunicardi, F C; Richard A Gibbs; Marie-Claude Gingras; Li, M (Curr Mol Med, 2012)
Pancreatic cancer is a multiple genetic disorder with many mutations identified during the progression. Two mouse pancreatic cancer cell lines were established which showed different phenotype in vivo: a non-metastatic cell line, Panc02, and a highly metastatic cell line, Panc02-H7, a derivative of Panc02. In order to investigate whether the genetic mutations of key genes in pancreatic cancer such as KRAS, TP53 (p53), CDKN2A (p16), SMAD4, ZIP4, and PDX-1 contribute to the phenotypic difference of these two mouse pancreatic cancer cells, we sequenced the exonic regions of these key genes in both cell lines and in the normal syngeneic mouse pancreas and compared them with the reference mouse genome sequence. The exons of KRAS, SMAD4, CDKN2A (p16), TP53 (p53), ZIP4, and PDX-1 genes were amplified and the genotype of these genes was determined by Sanger sequencing. The sequences were analyzed with Sequencher software. A mutation in SMAD4 was identified in both cell lines. This homozygote G to T mutation in the first position of codon 174 (GAA) generated a stop codon resulting in the translation of a truncated protein. Further functional analysis indicates that different TGF-β/SMAD signaling pathways were involved in those two mouse cell lines, which may explain the phonotypic difference between the two cells. A single nucleotide polymorphism (SNP) in KRAS gene (TAT to TAC at codon 32) was also identified in the normal pancreas DNA of the syngenic mouse and in both derived tumoral Panc02 and Panc02-H7 cells. No mutation or SNP was found in CDKN2A (p16), TP53 (p53), ZIP4, and PDX-1 genes in these two cell lines. The absence of mutations in genes such as KRAS, TP53, and CDKN2A, which are considered as key genes in the development of human pancreatic cancer suggests that SMAD4 might play a central and decisive role in mouse pancreatic cancer. These results also suggest that other mechanisms are involved in the substantial phenotypic difference between these two mouse pancreatic cancer cell lines. Further studies are warranted to elucidate the molecular pathways that lead to the aggressive metastatic potential of Panc02-H7.
Keywords: Animals; Cell Line, Tumor; Cyclin-Dependent Kinase Inhibitor p16; Homeodomain Proteins; Mice; Pancreatic Neoplasms; Polymerase Chain Reaction; Proto-Oncogene Proteins p21(ras); Sequence Analysis, DNA; Smad4 Protein; Trans-Activators; Tumor Suppressor Protein p53

Genomics: Gorilla gorilla gorilla. - Richard A Gibbs; Jeffrey Rogers (Nature, 2012)
Keywords: Animals; Evolution, Molecular; Female; Genetic Speciation; Genome; Gorilla gorilla; Humans

Human genome sequencing in health and disease. - Gonzaga-Jauregui, Claudia; Lupski, James R; Richard A Gibbs (Annu Rev Med, 2012)
Following the "finished," euchromatic, haploid human reference genome sequence, the rapid development of novel, faster, and cheaper sequencing technologies is making possible the era of personalized human genomics. Personal diploid human genome sequences have been generated, and each has contributed to our better understanding of variation in the human genome. We have consequently begun to appreciate the vastness of individual genetic variation from single nucleotide to structural variants. Translation of genome-scale variation into medically useful information is, however, in its infancy. This review summarizes the initial steps undertaken in clinical implementation of personal genome information, and describes the application of whole-genome and exome sequencing to identify the cause of genetic diseases and to suggest adjuvant therapies. Better analysis tools and a deeper understanding of the biology of our genome are necessary in order to decipher, interpret, and optimize clinical utility of what the variation in the human genome can teach us. Personal genome sequencing may eventually become an instrument of common medical practice, providing information that assists in the formulation of a differential diagnosis. We outline herein some of the remaining challenges.
Keywords: Genetic Diseases, Inborn; Genetic Privacy; Genome, Human; HapMap Project; Human Genome Project; Humans

Increasing the number of URMS in genomic science; (1854F). - Debra Murray; Whittington, D; Richard A Gibbs (62nd Annual Meeting of The American Society of Human Genetics, 2012)

Integrated analyses of microRNAs demonstrate their widespread influence on gene expression in high-grade serous ovarian carcinoma. - Creighton, Chad J; Hernandez-Herrera, Anadulce; Jacobsen, Anders; Levine, Douglas A; Mankoo, Parminder; Schultz, Nikolaus; Du, Ying; Zhang, Yiqun; Larsson, Erik; Sheridan, Robert; Xiao, Weimin; Spellman, Paul T; et al. (PLoS One, 2012)
BACKGROUND: The Cancer Genome Atlas (TCGA) Network recently comprehensively catalogued the molecular aberrations in 487 high-grade serous ovarian cancers, with much remaining to be elucidated regarding the microRNAs (miRNAs). Here, using TCGA ovarian data, we surveyed the miRNAs, in the context of their predicted gene targets. METHODS AND RESULTS: Integration of miRNA and gene patterns yielded evidence that proximal pairs of miRNAs are processed from polycistronic primary transcripts, and that intronic miRNAs and their host gene mRNAs derive from common transcripts. Patterns of miRNA expression revealed multiple tumor subtypes and a set of 34 miRNAs predictive of overall patient survival. In a global analysis, miRNA:mRNA pairs anti-correlated in expression across tumors showed a higher frequency of in silico predicted target sites in the mRNA 3'-untranslated region (with less frequency observed for coding sequence and 5'-untranslated regions). The miR-29 family and predicted target genes were among the most strongly anti-correlated miRNA:mRNA pairs; over-expression of miR-29a in vitro repressed several anti-correlated genes (including DNMT3A and DNMT3B) and substantially decreased ovarian cancer cell viability. CONCLUSIONS: This study establishes miRNAs as having a widespread impact on gene expression programs in ovarian cancer, further strengthening our understanding of miRNA biology as it applies to human cancer. As with gene transcripts, miRNAs exhibit high diversity reflecting the genomic heterogeneity within a clinically homogeneous disease population. Putative miRNA:mRNA interactions, as identified using integrative analysis, can be validated. TCGA data are a valuable resource for the identification of novel tumor suppressive miRNAs in ovarian as well as other cancers.
Keywords: 3' Untranslated Regions; Breast; Cell Line, Tumor; DNA Copy Number Variations; Female; Gene Expression Regulation, Neoplastic; Humans; MicroRNAs; Neoplasms, Cystic, Mucinous, and Serous; Ovarian Neoplasms

An integrative variant analysis suite for whole exome next-generation sequencing data. - Challis, Danny; Yu, Jin; Evani, Uday S; Jackson, Andrew R; Paithankar, Sameer; Coarfa, Cristian; Milosavljevic, Aleksandar; Richard A Gibbs; Fuli Yu (BMC Bioinformatics, 2012)
BACKGROUND: Whole exome capture sequencing allows researchers to cost-effectively sequence the coding regions of the genome. Although the exome capture sequencing methods have become routine and well established, there is currently a lack of tools specialized for variant calling in this type of data. RESULTS: Using statistical models trained on validated whole-exome capture sequencing data, the Atlas2 Suite is an integrative variant analysis pipeline optimized for variant discovery on all three of the widely used next generation sequencing platforms (SOLiD, Illumina, and Roche 454). The suite employs logistic regression models in conjunction with user-adjustable cutoffs to accurately separate true SNPs and INDELs from sequencing and mapping errors with high sensitivity (96.7%). CONCLUSION: We have implemented the Atlas2 Suite and applied it to 92 whole exome samples from the 1000 Genomes Project. The Atlas2 Suite is available for download at http://sourceforge.net/projects/atlas2/. In addition to a command line version, the suite has been integrated into the Genboree Workbench, allowing biomedical scientists with minimal informatics expertise to remotely call, view, and further analyze variants through a simple web interface. The existing genomic databases displayed via the Genboree browser also streamline the process from variant discovery to functional genomics analysis, resulting in an off-the-shelf toolkit for the broader community.
Keywords: Exome; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Open Reading Frames; Polymorphism, Single Nucleotide; Software

The KAT6B-related disorders genitopatellar syndrome and Ohdo/SBBYS syndrome have distinct clinical features reflecting distinct molecular mechanisms. - Campeau, Philippe M; Lu, James T; Dawson, Brian C; Fokkema, Ivo F A C; Robertson, Stephen P; Richard A Gibbs; Lee, Brendan H (Hum Mutat, 2012)
Genitopatellar syndrome (GPS) and Say-Barber-Biesecker-Young-Simpson syndrome (SBBYSS or Ohdo syndrome) have both recently been shown to be caused by distinct mutations in the histone acetyltransferase KAT6B (a.k.a. MYST4/MORF). All variants are de novo dominant mutations that lead to protein truncation. Mutations leading to GPS occur in the proximal portion of the last exon and lead to the expression of a protein without a C-terminal domain. Mutations leading to SBBYSS occur either throughout the gene, leading to nonsense-mediated decay, or more distally in the last exon. Features present only in GPS are contractures, anomalies of the spine, ribs and pelvis, renal cysts, hydronephrosis, and agenesis of the corpus callosum. Features present only in SBBYSS include long thumbs and long great toes and lacrimal duct abnormalities. Several features occur in both, such as intellectual disability, congenital heart defects, and genital and patellar anomalies. We propose that haploinsufficiency or loss of a function mediated by the C-terminal domain causes the common features, whereas gain-of-function activities would explain the features unique to GPS. Further molecular studies and the compilation of mutations in a database for genotype-phenotype correlations (www.LOVD.nl/KAT6B) might help tease out answers to these questions and understand the developmental programs dysregulated by the different truncations.
Keywords: Abnormalities, Multiple; Base Sequence; Blepharophimosis; Blepharoptosis; Craniofacial Abnormalities; Databases, Nucleic Acid; DNA; Female; Genetic Association Studies; Haploinsufficiency; Heart Defects, Congenital; Histone Acetyltransferases; Humans; Intellectual Disability; Kidney; Male; Molecular Sequence Data; Mutation; Patella; Psychomotor Disorders; Scrotum; Sequence Deletion; Urogenital Abnormalities

Mind the gap: upgrading genomes with Pacific Biosciences RS long-read sequencing technology. - English, Adam C; Richards, Stephen; Yi Han; Wang, Min; Vee, Vanesa; Qu, Jiaxin; Qin, Xiang; Donna M Muzny; Reid, Jeffrey G; Worley, Kim C; Richard A Gibbs (PLoS One, 2012)
Many genomes have been sequenced to high-quality draft status using Sanger capillary electrophoresis and/or newer short-read sequence data and whole genome assembly techniques. However, even the best draft genomes contain gaps and other imperfections due to limitations in the input data and the techniques used to build draft assemblies. Sequencing biases, repetitive genomic features, genomic polymorphism, and other complicating factors all come together to make some regions difficult or impossible to assemble. Traditionally, draft genomes were upgraded to "phase 3 finished" status using time-consuming and expensive Sanger-based manual finishing processes. For more facile assembly and automated finishing of draft genomes, we present here an automated approach to finishing using long-reads from the Pacific Biosciences RS (PacBio) platform. Our algorithm and associated software tool, PBJelly, (publicly available at https://sourceforge.net/projects/pb-jelly/) automates the finishing process using long sequence reads in a reference-guided assembly process. PBJelly also provides "lift-over" co-ordinate tables to easily port existing annotations to the upgraded assembly. Using PBJelly and long PacBio reads, we upgraded the draft genome sequences of a simulated Drosophila melanogaster, the version 2 draft Drosophila pseudoobscura, an assembly of the Assemblathon 2.0 budgerigar dataset, and a preliminary assembly of the Sooty mangabey. With 24× mapped coverage of PacBio long-reads, we addressed 99% of gaps and were able to close 69% and improve 12% of all gaps in D. pseudoobscura. With 4× mapped coverage of PacBio long-reads we saw reads address 63% of gaps in our budgerigar assembly, of which 32% were closed and 63% improved. With 6.8× mapped coverage of mangabey PacBio long-reads we addressed 97% of gaps and closed 66% of addressed gaps and improved 19%. The accuracy of gap closure was validated by comparison to Sanger sequencing on gaps from the original D. pseudoobscura draft assembly and shown to be dependent on initial reference quality.
Keywords: Animals; Base Sequence; Cercocebus atys; Databases, Genetic; Decision Making; Drosophila; Genome; Melopsittacus; Reproducibility of Results; Sequence Analysis, DNA; Software

Mutations in KAT6B, encoding a histone acetyltransferase, cause Genitopatellar syndrome. - Campeau, Philippe M; Kim, Jaeseung C; Lu, James T; Schwartzentruber, Jeremy A; Abdul-Rahman, Omar A; Schlaubitz, Silke; Murdock, David M; Jiang, Ming-Ming; Lammer, Edward J; Enns, Gregory M; Rhead, William J; Rowland, Jon; et al. (Am J Hum Genet, 2012)
Genitopatellar syndrome (GPS) is a skeletal dysplasia with cerebral and genital anomalies for which the molecular basis has not yet been determined. By exome sequencing, we found de novo heterozygous truncating mutations in KAT6B (lysine acetyltransferase 6B, formerly known as MYST4 and MORF) in three subjects; then by Sanger sequencing of KAT6B, we found similar mutations in three additional subjects. The mutant transcripts do not undergo nonsense-mediated decay in cells from subjects with GPS. In addition, human pathological analyses and mouse expression studies point to systemic roles of KAT6B in controlling organismal growth and development. Myst4 (the mouse orthologous gene) is expressed in mouse tissues corresponding to those affected by GPS. Phenotypic differences and similarities between GPS, the Say-Barber-Biesecker variant of Ohdo syndrome (caused by different mutations of KAT6B), and Rubinstein-Taybi syndrome (caused by mutations in other histone acetyltransferases) are discussed. Together, the data support an epigenetic dysregulation of the limb, brain, and genital developmental programs.
Keywords: Abnormalities, Multiple; Animals; Blepharophimosis; Blepharoptosis; Bone Diseases, Developmental; Cerebellum; Epigenomics; Exome; Female; Heart Defects, Congenital; Heterozygote; Histone Acetyltransferases; Humans; Intellectual Disability; Male; Mice; Mice, Inbred C57BL; Musculoskeletal Abnormalities; Mutation; Phenotype; Rubinstein-Taybi Syndrome; Sequence Analysis, DNA; Urogenital Abnormalities

Pancreatic cancer genomes reveal aberrations in axon guidance pathway genes. - Biankin, Andrew V; Waddell, Nicola; Kassahn, Karin S; Marie-Claude Gingras; Muthuswamy, Lakshmi B; Johns, Amber L; Miller, David K; Wilson, Peter J; Patch, Ann-Marie; Wu, Jianmin; Chang, David K; Cowley, Mark J; et al. (Nature, 2012)
Pancreatic cancer is a highly lethal malignancy with few effective therapies. We performed exome sequencing and copy number analysis to define genomic aberrations in a prospectively accrued clinical cohort (n = 142) of early (stage I and II) sporadic pancreatic ductal adenocarcinoma. Detailed analysis of 99 informative tumours identified substantial heterogeneity with 2,016 non-silent mutations and 1,628 copy-number variations. We define 16 significantly mutated genes, reaffirming known mutations (KRAS, TP53, CDKN2A, SMAD4, MLL3, TGFBR2, ARID1A and SF3B1), and uncover novel mutated genes including additional genes involved in chromatin modification (EPC1 and ARID2), DNA damage repair (ATM) and other mechanisms (ZIM2, MAP2K4, NALCN, SLC16A4 and MAGEA6). Integrative analysis with in vitro functional data and animal models provided supportive evidence for potential roles for these genetic aberrations in carcinogenesis. Pathway-based analysis of recurrently mutated genes recapitulated clustering in core signalling pathways in pancreatic ductal adenocarcinoma, and identified new mutated genes in each pathway. We also identified frequent and diverse somatic aberrations in genes described traditionally as embryonic regulators of axon guidance, particularly SLIT/ROBO signalling, which was also evident in murine Sleeping Beauty transposon-mediated somatic mutagenesis models of pancreatic cancer, providing further supportive evidence for the potential involvement of axon guidance genes in pancreatic carcinogenesis.
Keywords: Animals; Axons; Carcinoma, Pancreatic Ductal; Gene Dosage; Gene Expression Regulation, Neoplastic; Genome; Humans; Kaplan-Meier Estimate; Mice; Mutation; Pancreatic Neoplasms; Proteins; Signal Transduction

Patterns and rates of exonic de novo mutations in autism spectrum disorders. - Neale, Benjamin M; Kou, Yan; Liu, Li; Ma'ayan, Avi; Samocha, Kaitlin E; Aniko Sabo; Lin, Chiao-Feng; Stevens, Christine; Wang, Li-San; Makarov, Vladimir; Polak, Paz; Yoon, Seungtai; et al. (Nature, 2012)
Autism spectrum disorders (ASD) are believed to have genetic and environmental origins, yet in only a modest fraction of individuals can specific causes be identified. To identify further genetic risk factors, here we assess the role of de novo mutations in ASD by sequencing the exomes of ASD cases and their parents (n = 175 trios). Fewer than half of the cases (46.3%) carry a missense or nonsense de novo variant, and the overall rate of mutation is only modestly higher than the expected rate. In contrast, the proteins encoded by genes that harboured de novo missense or nonsense mutations showed a higher degree of connectivity among themselves and to previous ASD genes as indexed by protein-protein interaction screens. The small increase in the rate of de novo events, when taken together with the protein interaction results, are consistent with an important but limited role for de novo point mutations in ASD, similar to that documented for de novo copy number variants. Genetic models incorporating these data indicate that most of the observed de novo events are unconnected to ASD; those that do confer risk are distributed across many genes and are incompletely penetrant (that is, not necessarily sufficient for disease). Our results support polygenic models in which spontaneous coding mutations in any of a large number of genes increases risk by 5- to 20-fold. Despite the challenge posed by such models, results from de novo events and a large parallel case-control study provide strong evidence in favour of CHD8 and KATNAL2 as genuine autism risk factors.
Keywords: Autistic Disorder; Case-Control Studies; DNA-Binding Proteins; Exome; Exons; Family Health; Genetic Predisposition to Disease; Humans; Models, Genetic; Multifactorial Inheritance; Mutation; Phenotype; Poisson Distribution; Protein Interaction Maps; Transcription Factors

PDX-1 is a therapeutic target for pancreatic cancer, insulinoma and islet neoplasia using a novel RNA interference platform. - Liu, Shi-He; Rao, Donald D; Nemunaitis, John; Senzer, Neil; Zhou, Guisheng; Dawson, David; Marie-Claude Gingras; Wang, Zhaohui; Richard A Gibbs; Norman, Michael; Templeton, Nancy S; DeMayo, Francesco J; et al. (PLoS One, 2012)
Pancreatic and duodenal homeobox-1 (PDX-1) is a transcription factor that regulates insulin expression and islet maintenance in the adult pancreas. Our recent studies demonstrate that PDX-1 is an oncogene for pancreatic cancer and is overexpressed in pancreatic cancer. The purpose of this study was to demonstrate that PDX-1 is a therapeutic target for both hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Immunohistochemistry of human pancreatic and islet neoplasia specimens revealed marked PDX-1 overexpression, suggesting PDX-1 as a "drugable" target within these diseases. To do so, a novel RNA interference effector platform, bifunctional shRNA(PDX-1), was developed and studied in mouse and human cell lines as well as in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Systemic delivery of bi-shRNA(humanPDX-1) lipoplexes resulted in marked reduction of tumor volume and improved survival in a human pancreatic cancer xenograft mouse model. bi-shRNA(mousePDX-1) lipoplexes prevented death from hyperinsulinemia and hypoglycemia in an insulinoma mouse model. shRNA(mousePDX-1) lipoplexes reversed hyperinsulinemia and hypoglycemia in an immune-competent mouse model of islet neoplasia. PDX-1 was overexpressed in pancreatic neuroendocrine tumors and nesidioblastosis. These data demonstrate that PDX-1 RNAi therapy controls hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia, therefore, PDX-1 is a potential therapeutic target for these pancreatic diseases.
Keywords: Animals; Cell Line, Tumor; Cell Proliferation; Disease Models, Animal; Glucose Tolerance Test; Homeodomain Proteins; Humans; Immunohistochemistry; In Situ Nick-End Labeling; Insulin; Insulinoma; Islets of Langerhans; Male; Mice; Mice, SCID; Neoplasm Transplantation; Pancreas; Pancreatic Neoplasms; RNA Interference; Trans-Activators

Residual plasmatic activity of ADAMTS13 is correlated with phenotype severity in congenital thrombotic thrombocytopenic purpura. - Lotta, Luca A; Wu, Haifeng M; Mackie, Ian J; Noris, Marina; Veyradier, Agnes; Scully, Marie A; Remuzzi, Giuseppe; Coppo, Paul; Liesner, Ri; Donadelli, Roberta; Loirat, Chantal; Richard A Gibbs; et al. (Blood, 2012)
The quantification of residual plasmatic ADAMTS13 activity in congenital thrombotic thrombocytopenic purpura (TTP) patients is constrained by limitations in sensitivity and reproducibility of commonly used assays at low levels of ADAMTS13 activity, blunting efforts to establish genotype-phenotype correlations. In the present study, the residual plasmatic activity of ADAMTS13 was measured centrally by surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (limit of detection = 0.5%) in 29 congenital TTP patients. The results were used to study correlations among ADAMTS13 genotype, residual plasmatic activity, and clinical phenotype severity. An ADAMTS13 activity above 0.5% was measured in 26 (90%) patients and lower levels of activity were associated with earlier age at first TTP episode requiring plasma infusion, more frequent recurrences, and prescription of fresh-frozen plasma prophylaxis. Receiver operating characteristic curve analysis showed that activity levels of less than 2.74% and 1.61% were discriminative of age at first TTP episode requiring plasma infusion < 18 years, annual rate of TTP episodes > 1, and use of prophylaxis. Mutations affecting the highly conserved N-terminal domains of the protein were associated with lower residual ADAMTS13 activity and a more severe phenotype in an allelic-dose dependent manner. The results of the present study show that residual ADAMTS13 activity is associated with the severity of clinical phenotype in congenital TTP and provide insights into genotype-phenotype correlations.
Keywords: ADAM Proteins; ADAMTS13 Protein; Adolescent; Adult; Age Factors; Aged; Blood Chemical Analysis; Blood Transfusion; Child; Child, Preschool; DNA Mutational Analysis; Female; Genetic Association Studies; Humans; Male; Middle Aged; Mutation; Plasma; Purpura, Thrombotic Thrombocytopenic; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Young Adult

Strict evolutionary conservation followed rapid gene loss on human and rhesus Y chromosomes. - Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Graves, Tina; Fulton, Robert S; Dugan, Shannon; Ding, Yan; Buhay, Christian J; Kremitzki, Colin; Wang, Qiaoyan; Shen, Hua; et al. (Nature, 2012)
The human X and Y chromosomes evolved from an ordinary pair of autosomes during the past 200-300 million years. The human MSY (male-specific region of Y chromosome) retains only three percent of the ancestral autosomes' genes owing to genetic decay. This evolutionary decay was driven by a series of five 'stratification' events. Each event suppressed X-Y crossing over within a chromosome segment or 'stratum', incorporated that segment into the MSY and subjected its genes to the erosive forces that attend the absence of crossing over. The last of these events occurred 30 million years ago, 5 million years before the human and Old World monkey lineages diverged. Although speculation abounds regarding ongoing decay and looming extinction of the human Y chromosome, remarkably little is known about how many MSY genes were lost in the human lineage in the 25 million years that have followed its separation from the Old World monkey lineage. To investigate this question, we sequenced the MSY of the rhesus macaque, an Old World monkey, and compared it to the human MSY. We discovered that during the last 25 million years MSY gene loss in the human lineage was limited to the youngest stratum (stratum 5), which comprises three percent of the human MSY. In the older strata, which collectively comprise the bulk of the human MSY, gene loss evidently ceased more than 25 million years ago. Likewise, the rhesus MSY has not lost any older genes (from strata 1-4) during the past 25 million years, despite its major structural differences to the human MSY. The rhesus MSY is simpler, with few amplified gene families or palindromes that might enable intrachromosomal recombination and repair. We present an empirical reconstruction of human MSY evolution in which each stratum transitioned from rapid, exponential loss of ancestral genes to strict conservation through purifying selection.
Keywords: Animals; Chromosomes, Human, Y; Conserved Sequence; Crossing Over, Genetic; Evolution, Molecular; Gene Amplification; Gene Deletion; Humans; In Situ Hybridization, Fluorescence; Macaca mulatta; Male; Models, Genetic; Molecular Sequence Data; Pan troglodytes; Radiation Hybrid Mapping; Selection, Genetic; Time Factors; Y Chromosome

A systematic survey of loss-of-function variants in human protein-coding genes. - MacArthur, Daniel G; Balasubramanian, Suganthi; Frankish, Adam; Huang, Ni; Morris, James; Walter, Klaudia; Jostins, Luke; Habegger, Lukas; Pickrell, Joseph K; Montgomery, Stephen B; Albers, Cornelis A; Zhang, Zhengdong D; et al. (Science, 2012)
Genome-sequencing studies indicate that all humans carry many genetic variants predicted to cause loss of function (LoF) of protein-coding genes, suggesting unexpected redundancy in the human genome. Here we apply stringent filters to 2951 putative LoF variants obtained from 185 human genomes to determine their true prevalence and properties. We estimate that human genomes typically contain ~100 genuine LoF variants with ~20 genes completely inactivated. We identify rare and likely deleterious LoF alleles, including 26 known and 21 predicted severe disease-causing variants, as well as common LoF variants in nonessential genes. We describe functional and evolutionary differences between LoF-tolerant and recessive disease genes and a method for using these differences to prioritize candidate genes found in clinical sequencing studies.
Keywords: Disease; Gene Expression; Gene Frequency; Genetic Variation; Genome, Human; Humans; Phenotype; Polymorphism, Single Nucleotide; Proteins; Selection, Genetic

Using whole-genome sequence data to predict quantitative trait phenotypes in Drosophila melanogaster. - Ober, Ulrike; Ayroles, Julien F; Stone, Eric A; Richards, Stephen; Zhu, Dianhui; Richard A Gibbs; Stricker, Christian; Gianola, Daniel; Schlather, Martin; Mackay, Trudy F C; Simianer, Henner (PLoS Genet, 2012)
Predicting organismal phenotypes from genotype data is important for plant and animal breeding, medicine, and evolutionary biology. Genomic-based phenotype prediction has been applied for single-nucleotide polymorphism (SNP) genotyping platforms, but not using complete genome sequences. Here, we report genomic prediction for starvation stress resistance and startle response in Drosophila melanogaster, using ∼2.5 million SNPs determined by sequencing the Drosophila Genetic Reference Panel population of inbred lines. We constructed a genomic relationship matrix from the SNP data and used it in a genomic best linear unbiased prediction (GBLUP) model. We assessed predictive ability as the correlation between predicted genetic values and observed phenotypes by cross-validation, and found a predictive ability of 0.239±0.008 (0.230±0.012) for starvation resistance (startle response). The predictive ability of BayesB, a Bayesian method with internal SNP selection, was not greater than GBLUP. Selection of the 5% SNPs with either the highest absolute effect or variance explained did not improve predictive ability. Predictive ability decreased only when fewer than 150,000 SNPs were used to construct the genomic relationship matrix. We hypothesize that predictive power in this population stems from the SNP-based modeling of the subtle relationship structure caused by long-range linkage disequilibrium and not from population structure or SNPs in linkage disequilibrium with causal variants. We discuss the implications of these results for genomic prediction in other organisms.
Keywords: Animals; Bayes Theorem; Chromosome Mapping; Drosophila melanogaster; Genetics, Population; Genome, Insect; Genotype; Linkage Disequilibrium; Models, Genetic; Models, Theoretical; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Selection, Genetic; Sequence Analysis, DNA

Whole genome sequences of three Treponema pallidum ssp. pertenue strains: yaws and syphilis treponemes differ in less than 0.2% of the genome sequence. - Čejková, Darina; Zobaníková, Marie; Chen, Lei; Pospíšilová, Petra; Strouhal, Michal; Qin, Xiang; Mikalová, Lenka; Norris, Steven J; Donna M Muzny; Richard A Gibbs; Fulton, Lucinda L; Sodergren, Erica; et al. (PLoS Negl Trop Dis, 2012)
BACKGROUND: The yaws treponemes, Treponema pallidum ssp. pertenue (TPE) strains, are closely related to syphilis causing strains of Treponema pallidum ssp. pallidum (TPA). Both yaws and syphilis are distinguished on the basis of epidemiological characteristics, clinical symptoms, and several genetic signatures of the corresponding causative agents. METHODOLOGY/PRINCIPAL FINDINGS: To precisely define genetic differences between TPA and TPE, high-quality whole genome sequences of three TPE strains (Samoa D, CDC-2, Gauthier) were determined using next-generation sequencing techniques. TPE genome sequences were compared to four genomes of TPA strains (Nichols, DAL-1, SS14, Chicago). The genome structure was identical in all three TPE strains with similar length ranging between 1,139,330 bp and 1,139,744 bp. No major genome rearrangements were found when compared to the four TPA genomes. The whole genome nucleotide divergence (d(A)) between TPA and TPE subspecies was 4.7 and 4.8 times higher than the observed nucleotide diversity (π) among TPA and TPE strains, respectively, corresponding to 99.8% identity between TPA and TPE genomes. A set of 97 (9.9%) TPE genes encoded proteins containing two or more amino acid replacements or other major sequence changes. The TPE divergent genes were mostly from the group encoding potential virulence factors and genes encoding proteins with unknown function. CONCLUSIONS/SIGNIFICANCE: Hypothetical genes, with genetic differences, consistently found between TPE and TPA strains are candidates for syphilitic treponemes virulence factors. Seventeen TPE genes were predicted under positive selection, and eleven of them coded either for predicted exported proteins or membrane proteins suggesting their possible association with the cell surface. Sequence changes between TPE and TPA strains and changes specific to individual strains represent suitable targets for subspecies- and strain-specific molecular diagnostics.
Keywords: DNA, Bacterial; Gene Order; Genetic Variation; Genome, Bacterial; Humans; Molecular Sequence Data; Sequence Analysis, DNA; Synteny; Syphilis; Treponema pallidum; Yaws

Activation of multiple proto-oncogenic tyrosine kinases in breast cancer via loss of the PTPN12 phosphatase. - Sun, Tingting; Aceto, Nicola; Meerbrey, Kristen L; Kessler, Jessica D; Zhou, Chunshui; Migliaccio, Ilenia; Nguyen, Don X; Pavlova, Natalya N; Botero, Maria; Huang, Jian; Bernardi, Ronald J; Schmitt, Earlene; et al. (Cell, 2011)
Among breast cancers, triple-negative breast cancer (TNBC) is the most poorly understood and is refractory to current targeted therapies. Using a genetic screen, we identify the PTPN12 tyrosine phosphatase as a tumor suppressor in TNBC. PTPN12 potently suppresses mammary epithelial cell proliferation and transformation. PTPN12 is frequently compromised in human TNBCs, and we identify an upstream tumor-suppressor network that posttranscriptionally controls PTPN12. PTPN12 suppresses transformation by interacting with and inhibiting multiple oncogenic tyrosine kinases, including HER2 and EGFR. The tumorigenic and metastatic potential of PTPN12-deficient TNBC cells is severely impaired upon restoration of PTPN12 function or combined inhibition of PTPN12-regulated tyrosine kinases, suggesting that TNBCs are dependent on the proto-oncogenic tyrosine kinases constrained by PTPN12. Collectively, these data identify PTPN12 as a commonly inactivated tumor suppressor and provide a rationale for combinatorially targeting proto-oncogenic tyrosine kinases in TNBC and other cancers based on their profile of tyrosine-phosphatase activity.
Keywords: Breast Neoplasms; Cell Line, Tumor; Cell Transformation, Neoplastic; ErbB Receptors; Female; Gene Expression Regulation, Neoplastic; Humans; MAP Kinase Signaling System; MicroRNAs; Mutation; Neoplasm Metastasis; Protein Processing, Post-Translational; Protein Tyrosine Phosphatase, Non-Receptor Type 12; Tumor Suppressor Proteins

Association between somatostatin receptor 5 gene polymorphisms and pancreatic cancer risk and survival. - Li, Donghui; Tanaka, Motofumi; Brunicardi, F Charles; Fisher, William E; Richard A Gibbs; Marie-Claude Gingras (Cancer, 2011)
BACKGROUND: Somatostatin (SST) inhibited cell proliferation and negatively regulated the release of growth hormones by means of specific receptors (SSTR). Genetic variation in SSTR had been associated with risk of human cancers but had never been investigated in pancreatic cancer. METHODS: In this retrospective study the SSTR5 gene in paired tumor and blood samples from 33 pancreatic adenocarcinoma patients using the Sanger method were sequenced. Three single nucleotide polymorphisms (SNPs) in samples from 863 patients with pancreatic ductal adenocarcinoma and 876 healthy controls using the TaqMan method were analyzed. The associations between gene polymorphisms and pancreatic cancer risk and survival were analyzed by multivariate logistic regression and Cox proportional hazard models, respectively. RESULTS: No somatic mutations were identified, but 3 nonsynonymous SSTR5 SNPs (P109S, L48M, and P335L) in pancreatic tumors were identified. The SSTR5 P109S variant allele was associated with a 1.62-fold increased risk of pancreatic cancer (95% confidence interval [CI]: 1.08-2.43, P = 0.019). Furthermore, the SSTR5 L48M AC variant and smoking had a joint effect on pancreatic cancer risk (p(interaction) = 0.035). The odds ratios (95% confidence intervals) were 0.58 (0.34-0.97), 1.49 (1.18-1.89), and 2.27 (1.35-3.83) for the variant genotype alone, smoking alone, and both factors, respectively, compared with no factors. Finally, SSTR5 P335L CC and P109S CC combined were associated with lower overall survival durations in patients with resectable disease. CONCLUSIONS: These data suggest that SSTR5 genetic variants play a role in pancreatic cancer development and progression.
Keywords: Adult; Aged; Aged, 80 and over; Carcinoma, Pancreatic Ductal; Female; Genetic Predisposition to Disease; Genotype; Humans; Male; Middle Aged; Pancreatic Neoplasms; Polymorphism, Single Nucleotide; Proportional Hazards Models; Receptors, Somatostatin; Retrospective Studies; Risk; Sequence Analysis, DNA; Smoking; Somatostatin

Building a comprehensive genomic program for hepatocellular carcinoma. - Harring, Theresa R; Guiteau, Jacfranz J; Nguyen, N Thao T; Cotton, Ron T; Marie-Claude Gingras; Wheeler, David A; O'Mahony, Christine A; Richard A Gibbs; Brunicardi, F Charles; Goss, John A (World J Surg, 2011)
BACKGROUND: Hepatocellular carcinoma (HCC) is the most common primary liver cancer, causing approximately 660,000 deaths worldwide annually. The preferred treatment of HCC is surgical resection or orthotopic liver transplantation (OLT) for patients meeting specific criteria. For patients outside these criteria, options are limited and include medical therapy, radiofrequency ablation, chemoembolization, or palliative measures, and these result in poor outcomes. Various centers at Baylor are elucidating the genomics of HCC to improve treatment options, with a focus on three etiologies: hepatitis C virus, hepatitis B virus, and non-viral. METHODS: Through collaborative efforts, we have established an effective specimen biobanking protocol, and we are using several techniques to analyze HCC, including whole genome sequencing, whole exome sequencing, gene-specific analysis, gene expression, and epigenetic analysis. RESULTS: We have completed whole genome sequencing on two patient samples, whole exome sequencing on 47 patient samples, gene-specific analysis on 94 patient samples, gene expression on 4 patient samples, and epigenetic analysis on 1 patient sample. CONCLUSIONS: We hope to use these results to define novel genetic therapeutic strategies that may work in conjunction with surgical approaches to improve long-term patient and graft survival rates in patients with HCC. We also aim to provide a functional framework of a comprehensive program for genomic analysis that may be imitated by other institutions and for other tumors in the global quest toward personalized genomic medicine.
Keywords: Carcinoma, Hepatocellular; Cell Transformation, Neoplastic; Databases, Nucleic Acid; Disease Progression; Epigenomics; Exome; Forecasting; Gene Expression Regulation, Neoplastic; Genome, Human; Genome-Wide Association Study; Humans; Liver Neoplasms; Precision Medicine; Tissue Banks

Characterization of single-nucleotide variation in Indian-origin rhesus macaques (Macaca mulatta). - Fawcett, Gloria L; Raveendran, Muthuswamy; Deiros, David Rio; Chen, David; Fuli Yu; R. Alan Harris; Ren, Yanru; Donna M Muzny; Reid, Jeffrey G; Wheeler, David A; Worley, Kimberly C; Shelton, Steven E; et al. (BMC Genomics, 2011)
BACKGROUND: Rhesus macaques are the most widely utilized nonhuman primate model in biomedical research. Previous efforts have validated fewer than 900 single nucleotide polymorphisms (SNPs) in this species, which limits opportunities for genetic studies related to health and disease. Extensive information about SNPs and other genetic variation in rhesus macaques would facilitate valuable genetic analyses, as well as provide markers for genome-wide linkage analysis and the genetic management of captive breeding colonies. RESULTS: We used the available rhesus macaque draft genome sequence, new sequence data from unrelated individuals and existing published sequence data to create a genome-wide SNP resource for Indian-origin rhesus monkeys. The original reference animal and two additional Indian-origin individuals were resequenced to low coverage using SOLiD™ sequencing. We then used three strategies to validate SNPs: comparison of potential SNPs found in the same individual using two different sequencing chemistries, and comparison of potential SNPs in different individuals identified with either the same or different sequencing chemistries. Our approach validated approximately 3 million SNPs distributed across the genome. Preliminary analysis of SNP annotations suggests that a substantial number of these macaque SNPs may have functional effects. More than 700 non-synonymous SNPs were scored by Polyphen-2 as either possibly or probably damaging to protein function and these variants now constitute potential models for studying functional genetic variation relevant to human physiology and disease. CONCLUSIONS: Resequencing of a small number of animals identified greater than 3 million SNPs. This provides a significant new information resource for rhesus macaques, an important research animal. The data also suggests that overall genetic variation is high in this species. We identified many potentially damaging non-synonymous coding SNPs, providing new opportunities to identify rhesus models for human disease.
Keywords: Animals; Genetic Variation; India; Macaca mulatta; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Species Specificity

Clan genomics and the complex architecture of human disease. - Lupski, James R; Belmont, John W; Eric Boerwinkle; Richard A Gibbs (Cell, 2011)
Human diseases are caused by alleles that encompass the full range of variant types, from single-nucleotide changes to copy-number variants, and these variations span a broad frequency spectrum, from the very rare to the common. The picture emerging from analysis of whole-genome sequences, the 1000 Genomes Project pilot studies, and targeted genomic sequencing derived from very large sample sizes reveals an abundance of rare and private variants. One implication of this realization is that recent mutation may have a greater influence on disease susceptibility or protection than is conferred by variations that arose in distant ancestors.
Keywords: Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome, Human; Genomics; Humans; Pedigree; Pilot Projects; Precision Medicine

Comparative and demographic analysis of orang-utan genomes. - Locke, Devin P; Hillier, LaDeana W; Warren, Wesley C; Worley, Kim C; Nazareth, Lynne V; Donna M Muzny; Yang, Shiaw-Pyng; Wang, Zhengyuan; Chinwalla, Asif T; Minx, Pat; Mitreva, Makedonka; Cook, Lisa; et al. (Nature, 2011)
'Orang-utan' is derived from a Malay term meaning 'man of the forest' and aptly describes the southeast Asian great apes native to Sumatra and Borneo. The orang-utan species, Pongo abelii (Sumatran) and Pongo pygmaeus (Bornean), are the most phylogenetically distant great apes from humans, thereby providing an informative perspective on hominid evolution. Here we present a Sumatran orang-utan draft genome assembly and short read sequence data from five Sumatran and five Bornean orang-utan genomes. Our analyses reveal that, compared to other primates, the orang-utan genome has many unique features. Structural evolution of the orang-utan genome has proceeded much more slowly than other great apes, evidenced by fewer rearrangements, less segmental duplication, a lower rate of gene family turnover and surprisingly quiescent Alu repeats, which have played a major role in restructuring other primate genomes. We also describe a primate polymorphic neocentromere, found in both Pongo species, emphasizing the gradual evolution of orang-utan genome structure. Orang-utans have extremely low energy usage for a eutherian mammal, far lower than their hominid relatives. Adding their genome to the repertoire of sequenced primates illuminates new signals of positive selection in several pathways including glycolipid metabolism. From the population perspective, both Pongo species are deeply diverse; however, Sumatran individuals possess greater diversity than their Bornean counterparts, and more species-specific variation. Our estimate of Bornean/Sumatran speciation time, 400,000 years ago, is more recent than most previous studies and underscores the complexity of the orang-utan speciation process. Despite a smaller modern census population size, the Sumatran effective population size (N(e)) expanded exponentially relative to the ancestral N(e) after the split, while Bornean N(e) declined over the same period. Overall, the resources and analyses presented here offer new opportunities in evolutionary genomics, insights into hominid biology, and an extensive database of variation for conservation efforts.
Keywords: Animals; Centromere; Cerebrosides; Chromosomes; Evolution, Molecular; Female; Gene Rearrangement; Genetic Speciation; Genetic Variation; Genetics, Population; Genome; Humans; Male; Phylogeny; Pongo abelii; Pongo pygmaeus; Population Density; Population Dynamics; Species Specificity

Complete genome sequence of Treponema paraluiscuniculi, strain Cuniculi A: the loss of infectivity to humans is associated with genome decay. - Smajs, David; Zobaníková, Marie; Strouhal, Michal; Čejková, Darina; Dugan-Rocha, Shannon; Pospíšilová, Petra; Norris, Steven J; Albert, Tom; Qin, Xiang; Hallsworth-Pepin, Kym; Buhay, Christian; Donna M Muzny; et al. (PLoS One, 2011)
Treponema paraluiscuniculi is the causative agent of rabbit venereal spirochetosis. It is not infectious to humans, although its genome structure is very closely related to other pathogenic Treponema species including Treponema pallidum subspecies pallidum, the etiological agent of syphilis. In this study, the genome sequence of Treponema paraluiscuniculi, strain Cuniculi A, was determined by a combination of several high-throughput sequencing strategies. Whereas the overall size (1,133,390 bp), arrangement, and gene content of the Cuniculi A genome closely resembled those of the T. pallidum genome, the T. paraluiscuniculi genome contained a markedly higher number of pseudogenes and gene fragments (51). In addition to pseudogenes, 33 divergent genes were also found in the T. paraluiscuniculi genome. A set of 32 (out of 84) affected genes encoded proteins of known or predicted function in the Nichols genome. These proteins included virulence factors, gene regulators and components of DNA repair and recombination. The majority (52 or 61.9%) of the Cuniculi A pseudogenes and divergent genes were of unknown function. Our results indicate that T. paraluiscuniculi has evolved from a T. pallidum-like ancestor and adapted to a specialized host-associated niche (rabbits) during loss of infectivity to humans. The genes that are inactivated or altered in T. paraluiscuniculi are candidates for virulence factors important in the infectivity and pathogenesis of T. pallidum subspecies.
Keywords: Genome; Humans; Molecular Sequence Data; Sequence Analysis, DNA; Treponema

Copy number variation detection in whole-genome sequencing data using the Bayesian information criterion. - Xi, Ruibin; Hadjipanayis, Angela G; Luquette, Lovelace J; Kim, Tae-Min; Lee, Eunjung; Zhang, Jianhua; Johnson, Mark D; Donna M Muzny; Wheeler, David A; Richard A Gibbs; Kucherlapati, Raju; Park, Peter J (Proc Natl Acad Sci U S A, 2011)
DNA copy number variations (CNVs) play an important role in the pathogenesis and progression of cancer and confer susceptibility to a variety of human disorders. Array comparative genomic hybridization has been used widely to identify CNVs genome wide, but the next-generation sequencing technology provides an opportunity to characterize CNVs genome wide with unprecedented resolution. In this study, we developed an algorithm to detect CNVs from whole-genome sequencing data and applied it to a newly sequenced glioblastoma genome with a matched control. This read-depth algorithm, called BIC-seq, can accurately and efficiently identify CNVs via minimizing the Bayesian information criterion. Using BIC-seq, we identified hundreds of CNVs as small as 40 bp in the cancer genome sequenced at 10× coverage, whereas we could only detect large CNVs (> 15 kb) in the array comparative genomic hybridization profiles for the same genome. Eighty percent (14/16) of the small variants tested (110 bp to 14 kb) were experimentally validated by quantitative PCR, demonstrating high sensitivity and true positive rate of the algorithm. We also extended the algorithm to detect recurrent CNVs in multiple samples as well as deriving error bars for breakpoints using a Gibbs sampling approach. We propose this statistical approach as a principled yet practical and efficient method to estimate CNVs in whole-genome sequencing data.
Keywords: Algorithms; Bayes Theorem; Brain Neoplasms; Comparative Genomic Hybridization; Computer Simulation; DNA Copy Number Variations; Female; Gene Dosage; Genome; Genome, Human; Glioblastoma; Humans; Models, Genetic; Models, Statistical; Sequence Analysis, DNA

Demographic history and rare allele sharing among human populations. - Gravel, Simon; Henn, Brenna M; Gutenkunst, Ryan N; Indap, Amit R; Marth, Gabor T; Clark, Andrew G; Fuli Yu; Richard A Gibbs; Bustamante, Carlos D (Proc Natl Acad Sci U S A, 2011)
High-throughput sequencing technology enables population-level surveys of human genomic variation. Here, we examine the joint allele frequency distributions across continental human populations and present an approach for combining complementary aspects of whole-genome, low-coverage data and targeted high-coverage data. We apply this approach to data generated by the pilot phase of the Thousand Genomes Project, including whole-genome 2-4× coverage data for 179 samples from HapMap European, Asian, and African panels as well as high-coverage target sequencing of the exons of 800 genes from 697 individuals in seven populations. We use the site frequency spectra obtained from these data to infer demographic parameters for an Out-of-Africa model for populations of African, European, and Asian descent and to predict, by a jackknife-based approach, the amount of genetic diversity that will be discovered as sample sizes are increased. We predict that the number of discovered nonsynonymous coding variants will reach 100,000 in each population after ∼1,000 sequenced chromosomes per population, whereas ∼2,500 chromosomes will be needed for the same number of synonymous variants. Beyond this point, the number of segregating sites in the European and Asian panel populations is expected to overcome that of the African panel because of faster recent population growth. Overall, we find that the majority of human genomic variable sites are rare and exhibit little sharing among diverged populations. Our results emphasize that replication of disease association for specific rare genetic variants across diverged populations must overcome both reduced statistical power because of rarity and higher population divergence.
Keywords: Demography; Evolution, Molecular; Gene Frequency; Genes; Genetic Drift; Genetic Variation; Genetics, Population; Genomics; Humans; Models, Genetic; Racial Groups; Sequence Analysis, DNA

Disruptive TP53 mutation is associated with aggressive disease characteristics in an orthotopic murine model of oral tongue cancer. - Sano, Daisuke; Xie, Tong-Xin; Ow, Thomas J; Zhao, Mei; Pickering, Curtis R; Zhou, Ge; Sandulache, Vlad C; Wheeler, David A; Richard A Gibbs; Caulin, Carlos; Myers, Jeffrey N (Clin Cancer Res, 2011)
PURPOSE: To characterize tumor growth and metastatic potential in head and neck squamous cell carcinoma (HNSCC) cell lines in an orthotopic murine model of oral tongue cancer and to correlate TP53 mutation status with these findings. EXPERIMENTAL DESIGN: Cells from each of 48 HNSCC cell lines were orthotopically injected into the oral tongues of nude mice. Tumor volume, cervical lymph node metastasis, and mouse survival were recorded. Direct sequencing of the TP53 gene and Western blot analysis for the p53 protein after induction with 5-fluorouracil was conducted. Cell lines were categorized as either mutant TP53 or wild-type TP53, and lines with TP53 mutation were further categorized on the basis of type of mutation (disruptive or nondisruptive) and level of p53 protein expression. The behavior of tumors in these different groups was compared. RESULTS: These 48 HNSCC cell lines showed a wide range of behavior from highly aggressive and metastatic to no tumor formation. Mice injected with cells harboring disruptive TP53 mutations had faster tumor growth, greater incidence of cervical lymph node metastasis, and shorter survival than mice injected with cells lacking these mutations. CONCLUSIONS: HNSCC cell lines display a wide spectrum of behavior in an orthotopic model of oral cancer. Cell lines with disruptive TP53 mutations are more aggressive in this system, corroborating clinical reports that have linked these mutations to poor patient outcome.
Keywords: Animals; Carcinoma, Squamous Cell; Cell Line, Tumor; Disease Models, Animal; Genes, p53; Head and Neck Neoplasms; Humans; Male; Mice; Mice, Nude; Mutation; Squamous Cell Carcinoma of Head and Neck; Tongue Neoplasms; Transplantation, Heterologous; Tumor Suppressor Protein p53

The Drosophila melanogaster transcriptome by paired-end RNA sequencing. - Daines, Bryce; Wang, Hui; Wang, Liguo; Yumei Li; Yi Han; Emmert, David; Gelbart, William; Wang, Xia; Li, Wei; Richard A Gibbs; Rui Chen (Genome Res, 2011)
RNA-seq was used to generate an extensive map of the Drosophila melanogaster transcriptome by broad sampling of 10 developmental stages. In total, 142.2 million uniquely mapped 64-100-bp paired-end reads were generated on the Illumina GA II yielding 356× sequencing coverage. More than 95% of FlyBase genes and 90% of splicing junctions were observed. Modifications to 30% of FlyBase gene models were made by extension of untranslated regions, inclusion of novel exons, and identification of novel splicing events. A total of 319 novel transcripts were identified, representing a 2% increase over the current annotation. Alternate splicing was observed in 31% of D. melanogaster genes, a 38% increase over previous estimations, but significantly less than that observed in higher organisms. Much of this splicing is subtle such as tandem alternate splice sites.
Keywords: Alternative Splicing; Animals; Drosophila melanogaster; Female; Gene Expression Profiling; Genes, Y-Linked; Male; Molecular Sequence Annotation; Molecular Sequence Data; Oligonucleotide Array Sequence Analysis; Sequence Analysis, RNA

Exome capture sequencing identifies a novel mutation in BBS4. - Wang, Hui; Chen, Xianfeng; Dudinsky, Lynn; Patenia, Claire; Chen, Yiyun; Yumei Li; Wei, Yue; Abboud, Emad B; Al-Rajhi, Ali A; Lewis, Richard Alan; Lupski, James R; Mardon, Graeme; et al. (Mol Vis, 2011)
PURPOSE: Leber congenital amaurosis (LCA) is one of the most severe eye dystrophies characterized by severe vision loss at an early stage and accounts for approximately 5% of all retinal dystrophies. The purpose of this study was to identify a novel LCA disease allele or gene and to develop an approach combining genetic mapping with whole exome sequencing. METHODS: Three patients from King Khaled Eye Specialist Hospital (KKESH205) underwent whole genome single nucleotide polymorphism genotyping, and a single candidate region was identified. Taking advantage of next-generation high-throughput DNA sequencing technologies, whole exome capture sequencing was performed on patient KKESH205#7. Sanger direct sequencing was used during the validation step. The zebrafish model was used to examine the function of the mutant allele. RESULTS: A novel missense mutation in Bardet-Biedl syndrome 4 protein (BBS4) was identified in a consanguineous family from Saudi Arabia. This missense mutation in the fifth exon (c.253G>C;p.E85Q) of BBS4 is likely a disease-causing mutation as it segregates with the disease. The mutation is not found in the single nucleotide polymorphism (SNP) database, the 1000 Genomes Project, or matching normal controls. Functional analysis of this mutation in zebrafish indicates that the G253C allele is pathogenic. Coinjection of the G253C allele cannot rescue the mislocalization of rhodopsin in the retina when BBS4 is knocked down by morpholino injection. Immunofluorescence analysis in cell culture shows that this missense mutation in BBS4 does not cause obvious defects in protein expression or pericentriolar localization. CONCLUSIONS: This mutation likely mainly reduces or abolishes BBS4 function in the retina. Further studies of this allele will provide important insights concerning the pleiotropic nature of BBS4 function.
Keywords: Alleles; Animals; Base Sequence; Chromosome Mapping; Consanguinity; Exome; Exons; Female; Genotype; High-Throughput Nucleotide Sequencing; Humans; Infant; Leber Congenital Amaurosis; Male; Microtubule-Associated Proteins; Molecular Sequence Data; Mutation, Missense; Pedigree; Polymorphism, Single Nucleotide; Proteins; Retina; Rhodopsin; Saudi Arabia; Zebrafish

Exome sequencing of head and neck squamous cell carcinoma reveals inactivating mutations in NOTCH1. - Agrawal, Nishant; Frederick, Mitchell J; Pickering, Curtis R; Bettegowda, Chetan; Chang, Kyle; Li, Ryan J; Fakhry, Carole; Xie, Tong-Xin; Zhang, Jiexin; Wang, Jing; Zhang, Nianxiang; El-Naggar, Adel K; et al. (Science, 2011)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide. To explore the genetic origins of this cancer, we used whole-exome sequencing and gene copy number analyses to study 32 primary tumors. Tumors from patients with a history of tobacco use had more mutations than did tumors from patients who did not use tobacco, and tumors that were negative for human papillomavirus (HPV) had more mutations than did HPV-positive tumors. Six of the genes that were mutated in multiple tumors were assessed in up to 88 additional HNSCCs. In addition to previously described mutations in TP53, CDKN2A, PIK3CA, and HRAS, we identified mutations in FBXW7 and NOTCH1. Nearly 40% of the 28 mutations identified in NOTCH1 were predicted to truncate the gene product, suggesting that NOTCH1 may function as a tumor suppressor gene rather than an oncogene in this tumor type.
Keywords: Carcinoma; Carcinoma, Squamous Cell; Cell Cycle Proteins; Codon, Nonsense; Exons; F-Box Proteins; F-Box-WD Repeat-Containing Protein 7; Gene Dosage; Genes, p53; Genes, Tumor Suppressor; Head and Neck Neoplasms; Humans; INDEL Mutation; Mutation; Mutation, Missense; Neoplasms, Squamous Cell; Nicotiana; Oligonucleotide Array Sequence Analysis; Oncogenes; Papillomaviridae; Papillomavirus Infections; Receptor, Notch1; Sequence Analysis, DNA; Smoking; Squamous Cell Carcinoma of Head and Neck; Ubiquitin-Protein Ligases

Exome sequencing of ion channel genes reveals complex profiles confounding personal risk assessment in epilepsy. - Klassen, Tara; Davis, Caleb; Goldman, Alica; Burgess, Dan; Chen, Tim; Wheeler, David; McPherson, John; Bourquin, Traci; Lewis, Lora; Villasana, Donna; Morgan, Margaret; Donna M Muzny; et al. (Cell, 2011)
Ion channel mutations are an important cause of rare Mendelian disorders affecting brain, heart, and other tissues. We performed parallel exome sequencing of 237 channel genes in a well-characterized human sample, comparing variant profiles of unaffected individuals to those with the most common neuronal excitability disorder, sporadic idiopathic epilepsy. Rare missense variation in known Mendelian disease genes is prevalent in both groups at similar complexity, revealing that even deleterious ion channel mutations confer uncertain risk to an individual depending on the other variants with which they are combined. Our findings indicate that variant discovery via large scale sequencing efforts is only a first step in illuminating the complex allelic architecture underlying personal disease risk. We propose that in silico modeling of channel variation in realistic cell and network models will be crucial to future strategies assessing mutation profile pathogenicity and drug response in individuals with a broad spectrum of excitability disorders.
Keywords: Computer Simulation; Epilepsy; Epistasis, Genetic; Gene Expression Profiling; Hippocampus; Humans; Ion Channels; Mutation, Missense; Neurons; Polymorphism, Single Nucleotide; Risk Assessment

Gastrointestinal microbiome signatures of pediatric patients with irritable bowel syndrome. - Saulnier, Delphine M; Riehle, Kevin; Mistretta, Toni-Ann; Diaz, Maria-Alejandra; Mandal, Debasmita; Raza, Sabeen; Weidler, Erica M; Qin, Xiang; Coarfa, Cristian; Milosavljevic, Aleksandar; Petrosino, Joseph F; Highlander, Sarah; et al. (Gastroenterology, 2011)
BACKGROUND & AIMS: The intestinal microbiomes of healthy children and pediatric patients with irritable bowel syndrome (IBS) are not well defined. Studies in adults have indicated that the gastrointestinal microbiota could be involved in IBS. METHODS: We analyzed 71 samples from 22 children with IBS (pediatric Rome III criteria) and 22 healthy children, ages 7-12 years, by 16S ribosomal RNA gene sequencing, with an average of 54,287 reads/stool sample (average 454 read length = 503 bases). Data were analyzed using phylogenetic-based clustering (Unifrac), or an operational taxonomic unit (OTU) approach using a supervised machine learning tool (randomForest). Most samples were also hybridized to a microarray that can detect 8741 bacterial taxa (16S rRNA PhyloChip). RESULTS: Microbiomes associated with pediatric IBS were characterized by a significantly greater percentage of the class γ-proteobacteria (0.07% vs 0.89% of total bacteria, respectively; P < .05); 1 prominent component of this group was Haemophilus parainfluenzae. Differences highlighted by 454 sequencing were confirmed by high-resolution PhyloChip analysis. Using supervised learning techniques, we were able to classify different subtypes of IBS with a success rate of 98.5%, using limited sets of discriminant bacterial species. A novel Ruminococcus-like microbe was associated with IBS, indicating the potential utility of microbe discovery for gastrointestinal disorders. A greater frequency of pain correlated with an increased abundance of several bacterial taxa from the genus Alistipes. CONCLUSIONS: Using 16S metagenomics by PhyloChip DNA hybridization and deep 454 pyrosequencing, we associated specific microbiome signatures with pediatric IBS. These findings indicate the important association between gastrointestinal microbes and IBS in children; these approaches might be used in diagnosis of functional bowel disorders in pediatric patients.
Keywords: Abdominal Pain; Case-Control Studies; Child; DNA Probes; Female; Gastrointestinal Tract; Haemophilus parainfluenzae; Humans; Incidence; Irritable Bowel Syndrome; Male; Metagenome; Phenotype; Phylogeny; RNA, Ribosomal, 16S; Ruminococcus

Genome sequence of an Australian kangaroo, Macropus eugenii, provides insight into the evolution of mammalian reproduction and development. - Renfree, Marilyn B; Papenfuss, Anthony T; Deakin, Janine E; Lindsay, James; Heider, Thomas; Belov, Katherine; Rens, Willem; Waters, Paul D; Pharo, Elizabeth A; Shaw, Geoff; Wong, Emily S W; Lefèvre, Christophe M; et al. (Genome Biol, 2011)
BACKGROUND: We present the genome sequence of the tammar wallaby, Macropus eugenii, which is a member of the kangaroo family and the first representative of the iconic hopping mammals that symbolize Australia to be sequenced. The tammar has many unusual biological characteristics, including the longest period of embryonic diapause of any mammal, extremely synchronized seasonal breeding and prolonged and sophisticated lactation within a well-defined pouch. Like other marsupials, it gives birth to highly altricial young, and has a small number of very large chromosomes, making it a valuable model for genomics, reproduction and development. RESULTS: The genome has been sequenced to 2 × coverage using Sanger sequencing, enhanced with additional next generation sequencing and the integration of extensive physical and linkage maps to build the genome assembly. We also sequenced the tammar transcriptome across many tissues and developmental time points. Our analyses of these data shed light on mammalian reproduction, development and genome evolution: there is innovation in reproductive and lactational genes, rapid evolution of germ cell genes, and incomplete, locus-specific X inactivation. We also observe novel retrotransposons and a highly rearranged major histocompatibility complex, with many class I genes located outside the complex. Novel microRNAs in the tammar HOX clusters uncover new potential mammalian HOX regulatory elements. CONCLUSIONS: Analyses of these resources enhance our understanding of marsupial gene evolution, identify marsupial-specific conserved non-coding elements and critical genes across a range of biological systems, including reproduction, development and immunity, and provide new insight into marsupial and mammalian biology and genome evolution.
Keywords: Animals; Australia; Biological Evolution; Chromosome Mapping; Chromosomes, Mammalian; Female; Gene Expression Regulation; Genome; Genomic Imprinting; In Situ Hybridization, Fluorescence; Macropodidae; MicroRNAs; Molecular Sequence Data; Reproduction; Sequence Alignment; Sequence Analysis, DNA; Transcriptome

Genome-sequencing anniversary. Bringing genomics and genetics back together. - Richard A Gibbs (Science, 2011)
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Genomics; Human Genome Project; Humans; Sequence Analysis, DNA

A high-resolution map of human evolutionary constraint using 29 mammals. - Lindblad-Toh, Kerstin; Garber, Manuel; Zuk, Or; Lin, Michael F; Parker, Brian J; Washietl, Stefan; Kheradpour, Pouya; Ernst, Jason; Jordan, Gregory; Mauceli, Evan; Ward, Lucas D; Lowe, Craig B; et al. (Nature, 2011)
The comparison of related genomes has emerged as a powerful lens for genome interpretation. Here we report the sequencing and comparative analysis of 29 eutherian genomes. We confirm that at least 5.5% of the human genome has undergone purifying selection, and locate constrained elements covering ∼4.2% of the genome. We use evolutionary signatures and comparisons with experimental data sets to suggest candidate functions for ∼60% of constrained bases. These elements reveal a small number of new coding exons, candidate stop codon readthrough events and over 10,000 regions of overlapping synonymous constraint within protein-coding exons. We find 220 candidate RNA structural families, and nearly a million elements overlapping potential promoter, enhancer and insulator regions. We report specific amino acid residues that have undergone positive selection, 280,000 non-coding elements exapted from mobile elements and more than 1,000 primate- and human-accelerated elements. Overlap with disease-associated variants indicates that our findings will be relevant for studies of human biology, health and disease.
Keywords: Animals; Disease; Evolution, Molecular; Exons; Genome; Genome, Human; Genomics; Health; Humans; Mammals; Molecular Sequence Annotation; Phylogeny; RNA; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

The hypofunctional effect of P335L single nucleotide polymorphism on SSTR5 function. - Zhou, Guisheng; Marie-Claude Gingras; Liu, Shi-He; Li, Donghui; Li, Zhijun; Catania, Robbi L; Stehling, Kelly M; Li, Min; Paganelli, Giovanni; Richard A Gibbs; DeMayo, Francesco J; Fisher, William E; et al. (World J Surg, 2011)
BACKGROUND: Somatostatin receptor subtype 5 (SSTR5) mediates the inhibitory effect of somatostatin on insulin expression/secretion and cell proliferation. A number of single nucleotide polymorphisms (SNPs) of SSTR5 have been identified, including P335L, a nonsynonymous SNP located in the protein C-terminal region and encrypted by the codon CCG (proline) or the codon CTG (leucine). In the present study we sought to determine the distribution of the SSTR5 P335L SNP in a cohort of pancreatic cancer patients and whether the P335L SNP affected cellular function of SSTR5 in human pancreatic cancer. METHODS: The P335L germline genotype of 246 patients with pancreatic cancer (213 Caucasians, 16 Hispanics, and 17 African Americans) and 17 human pancreatic cell lines was determined with the TaqMan SNP Genotyping assay. Human SSTR5 leucine variant (L335) was generated by performing site-directed mutagenesis using SSTR5 proline variant (P335) as a template. Transient transfections were performed in HEK293, Mia PaCa-2, and β-TC-6 cells using Lipofectamine 2000. The expression of SSTR5 L335 was determined with a mouse monoclonal anti-SSTR5 L335 antibody generated in our laboratory. The cell proliferation rate was measured by performing MTS assays. Insulin concentration was measured by performing ELISA assays. RESULTS: Genotyping of the patients' blood indicated that the frequency of the T allele (CT and TT genotypes) in codon 335 of SSTR5 in Caucasians, Hispanics, and African Americans was 52, 69, and 35%, respectively, which was race-dependent. Statistical analysis indicated that association between the frequency of the T allele and the existence of pancreatic cancer in each race missed significance perhaps due to limited sample size. In 17 tested human pancreatic cancer cell lines, 5 (Capan-2, HPAF-II, Panc03.27, Panc-1, and -3) were homozygous (TT genotype) and 9, including Mia PaCa-2, were heterozygous (CT genotype). Overexpression of SSTR5 L335 in Mia PaCa-2 cells enhanced cell proliferation compared to overexpression of SSTR5 P335. Overexpression of SSTR5 P335 enhanced the inhibitory effect of SSTR5 agonist RPL-1980 on cell proliferation of Mia PaCa-2 cells and glucose-stimulated insulin secretion from mouse insulinoma cells, while overexpression of SSTR5 L335 blocked the inhibitory effect of RPL-1980. Overexpression of SSTR5 L335 enhanced PDX-1 expression in Mia PaCa-2 cells. A specific monoclonal antibody was generated to detect SSTR5 P335L. CONCLUSION: SSTR5 P335L SNP widely exists in the human population, in patients with pancreatic cancer, and is race-dependent. The SNP is also present in selected human pancreatic cancer cell lines. In contrast to SSTR5 P335, overexpression of the SSTR5 L335 variant resulted in cellular proliferation and PDX-1 overexpression in human pancreatic cancer cells. Its overexpression blocked the inhibitory effect of an SSTR5-specific analog on human pancreatic cancer cell proliferation and on glucose-stimulated insulin secretion from mouse insulinoma cells. These data suggest that SSTR5 P335L is a hypofunctional protein with a potentially harmful effect on function, as well as potential latent effect, and therefore it could affect the clinical response to somatostatin analog therapy for patients with pancreatic cancer.
Keywords: Adenocarcinoma; Alleles; Animals; Antibodies, Monoclonal; Black or African American; Cell Line, Tumor; Cell Proliferation; Codon; Gene Expression Regulation, Neoplastic; Gene Frequency; Genotype; Hispanic or Latino; Humans; Insulin; Insulin Secretion; Mice; Mice, Inbred BALB C; Pancreatic Neoplasms; Polymorphism, Single Nucleotide; Receptors, Somatostatin; White People

Identification of genetic susceptibility to childhood cancer through analysis of genes in parallel. - Plon, Sharon E; Wheeler, David A; Strong, Louise C; Tomlinson, Gail E; Pirics, Michael; Meng, Qingchang; Cheung, Hannah C; Begin, Phyllis R; Donna M Muzny; Lewis, Lora; Biegel, Jaclyn A; Richard A Gibbs (Cancer Genet, 2011)
Clinical cancer genetic susceptibility analysis typically proceeds sequentially, beginning with the most likely causative gene. The process is time consuming and the yield is low, particularly for families with unusual patterns of cancer. We determined the results of in parallel mutation analysis of a large cancer-associated gene panel. We performed deletion analysis and sequenced the coding regions of 45 genes (8 oncogenes and 37 tumor suppressor or DNA repair genes) in 48 childhood cancer patients who also (i) were diagnosed with a second malignancy under age 30, (ii) have a sibling diagnosed with cancer under age 30, and/or (iii) have a major congenital anomaly or developmental delay. Deleterious mutations were identified in 6 of 48 (13%) families, 4 of which met the sibling criteria. Mutations were identified in genes previously implicated in both dominant and recessive childhood syndromes, including SMARCB1, PMS2, and TP53. No pathogenic deletions were identified. This approach has provided efficient identification of childhood cancer susceptibility mutations and will have greater utility as additional cancer susceptibility genes are identified. Integrating parallel analysis of large gene panels into clinical testing will speed results and increase diagnostic yield. The failure to detect mutations in 87% of families highlights that a number of childhood cancer susceptibility genes remain to be discovered.
Keywords: Adolescent; Adult; Algorithms; Child; DNA Mutational Analysis; DNA Repair; Gene Dosage; Genes, Dominant; Genes, Recessive; Genes, Tumor Suppressor; Genetic Predisposition to Disease; Humans; Immunoprecipitation; Models, Genetic; Mutation; Neoplasms; Oncogenes; Reverse Transcriptase Polymerase Chain Reaction; Rhabdoid Tumor

Minimum information about a marker gene sequence (MIMARKS) and minimum information about any (x) sequence (MIxS) specifications. - Yilmaz, Pelin; Kottmann, Renzo; Field, Dawn; Knight, Rob; Cole, James R; Amaral-Zettler, Linda; Gilbert, Jack A; Karsch-Mizrachi, Ilene; Johnston, Anjanette; Cochrane, Guy; Vaughan, Robert; Hunter, Christopher; et al. (Nat Biotechnol, 2011)
Here we present a standard developed by the Genomic Standards Consortium (GSC) for reporting marker gene sequences--the minimum information about a marker gene sequence (MIMARKS). We also introduce a system for describing the environment from which a biological sample originates. The 'environmental packages' apply to any genome sequence of known origin and can be used in combination with MIMARKS and other GSC checklists. Finally, to establish a unified standard for describing sequence data and to provide a single point of entry for the scientific community to access and learn about GSC checklists, we present the minimum information about any (x) sequence (MIxS). Adoption of MIxS will enhance our ability to analyze natural genetic diversity documented by massive DNA sequencing efforts from myriad ecosystems in our ever-changing biosphere.
Keywords: Biomarkers; Checklist; Databases, Genetic; Environment; Genes, rRNA; Genetic Variation; Humans; Information Storage and Retrieval; Internet; Metagenomics; Programming Languages; Sequence Analysis, DNA; Software

Oligogenic heterozygosity in individuals with high-functioning autism spectrum disorders. - Schaaf, Christian P; Aniko Sabo; Sakai, Yasunari; Crosby, Jacy; Donna M Muzny; Hawes, Alicia; Lewis, Lora; Akbar, Humeira; Varghese, Robin; Eric Boerwinkle; Richard A Gibbs; Zoghbi, Huda Y (Hum Mol Genet, 2011)
Autism spectrum disorders (ASDs) are a heterogeneous group of neuro-developmental disorders. While significant progress has been made in the identification of genes and copy number variants associated with syndromic autism, little is known to date about the etiology of idiopathic non-syndromic autism. Sanger sequencing of 21 known autism susceptibility genes in 339 individuals with high-functioning, idiopathic ASD revealed de novo mutations in at least one of these genes in 6 of 339 probands (1.8%). Additionally, multiple events of oligogenic heterozygosity were seen, affecting 23 of 339 probands (6.8%). Screening of a control population for novel coding variants in CACNA1C, CDKL5, HOXA1, SHANK3, TSC1, TSC2 and UBE3A by the same sequencing technology revealed that controls were carriers of oligogenic heterozygous events at significantly (P < 0.01) lower rate, suggesting oligogenic heterozygosity as a new potential mechanism in the pathogenesis of ASDs.
Keywords: Adolescent; Child; Child Development Disorders, Pervasive; Child, Preschool; Genetic Predisposition to Disease; Heterozygote; Humans; Male; Mutation

PDX-1: demonstration of oncogenic properties in pancreatic cancer. - Liu, Shi-He; Patel, Sanjeet; Marie-Claude Gingras; Nemunaitis, John; Zhou, Guisheng; Chen, Changyi; Li, Min; Fisher, William; Richard A Gibbs; Brunicardi, F Charles (Cancer, 2011)
BACKGROUND: Pancreatic-duodenal homeobox 1 (PDX-1) is a transcription factor that regulates embryologic pancreas development and insulin expression in the adult islet; however, it is overexpressed in many types of cancer, including pancreatic cancer. The purpose of this study was to investigate the role of PDX-1 in tumorigenesis in human cells. METHODS: In vitro cell proliferation, invasion, and transformation were performed in human embryonic kidney cell line (HEK 293), pancreatic cancer cell line MIA PaCa2, and human pancreatic ductal epithelial (HPDE) cells transiently or stably expressing PDX-1 or green fluorescent protein (GFP) PDX-1, with or without cotransfection of PDX-1 short hairpin RNA (shRNA). In vivo tumor formation was carried out in severe combined immunodeficiency (SCID) mice with subcutaneous injection of HEK 293 and MIA PaCa2 stably transfected cells. Cell cycle was analyzed by Western blot or immunostaining. Microarray of RNA from pancreatic adenocarcinoma cells with and without PDX-1 shRNA was performed and analyzed. RESULTS: Transient and stable expressing PDX-1 significantly increased cell proliferation and invasion in HEK 293, human pancreatic ductal epithelial (HPDE), and MIA PaCa2 cells versus controls (P < .05), human PDX-1 shRNA reversed these effects. Expression of PDX-1 significantly increased colony formation in HEK 293, HPDE, and MIA PaCa2 cells versus controls in vitro (P < .05). PDX-1 promoted HEK 293 and MIA PaCa2 tumor formation in SCID mice as compared with that of control (P < .05). PDX-1 overexpression disrupted cell cycles proteins. PDX-1 expression was confirmed by Western blot and tracked by viewing of GFP-PDX-1 expression. Microarray data support an oncogenic role of PDX-1 in pancreas cancer cells. CONCLUSIONS: PDX-1 induced increased cell proliferation, invasion, and colony formation in vitro, and resulted in markedly increased HEK 293 and MIA PaCa2 tumor formation in SCID mice. These data suggest that PDX-1 is a potential oncogene that regulates tumorigenesis.
Keywords: Animals; Cell Cycle; Cell Line, Tumor; Cell Proliferation; HEK293 Cells; Homeodomain Proteins; Humans; Mice; Mice, SCID; Neoplasm Transplantation; Oncogenes; Pancreatic Neoplasms; RNA, Small Interfering; Trans-Activators; Transfection; Up-Regulation

A primer on a hepatocellular carcinoma bioresource bank using the cancer genome atlas guidelines: practical issues and pitfalls. - Nguyen, N Thao T; Cotton, Ron T; Harring, Theresa R; Guiteau, Jacfranz J; Marie-Claude Gingras; Wheeler, David A; O'Mahony, Christine A; Richard A Gibbs; Brunicardi, F Charles; Goss, John A (World J Surg, 2011)
BACKGROUND: Since the advent of the human genome, the era of personalized genomic medicine is indisputably in progress. METHODS: In an effort to contribute to the evolving knowledge of genomic medicine, we have aimed directly at building a bioresource bank for hepatocellular carcinoma. This tumor bank is based on the rigorous guidelines set forth by the National Cancer Institute, and it offers analytes to help elucidate the mechanisms of progression from cirrhosis to malignancy, risk factors for recurrence, and applicability of current treatment options to a diverse group of people. CONCLUSIONS: Surgeons have a privileged position between patients (and their cancer) and the benches of basic science. Thus, we offer a primer based on our own experiences, from which surgeons may take elements to build their own bioresource bank for use in collaboration with others. We highlight some practicalities and pitfalls that could be overlooked, as well as a discussion of possible solutions.
Keywords: Carcinoma, Hepatocellular; Cell Transformation, Neoplastic; Cooperative Behavior; Databases, Genetic; Databases, Nucleic Acid; Disease Progression; Forecasting; Genetic Predisposition to Disease; Genome, Human; Guidelines as Topic; Humans; Interdisciplinary Communication; Liver; Liver Cirrhosis; Liver Neoplasms; National Cancer Institute (U.S.); Neoplasm Invasiveness; Neoplasm Recurrence, Local; Precision Medicine; Tissue Banks; United States

Resequencing of IRS2 reveals rare variants for obesity but not fasting glucose homeostasis in Hispanic children. - Butte, Nancy F; Voruganti, V Saroja; Cole, Shelley A; Haack, Karin; Comuzzie, Anthony G; Donna M Muzny; Wheeler, David A; Chang, Kyle; Hawes, Alicia; Richard A Gibbs (Physiol Genomics, 2011)
Our objective was to resequence insulin receptor substrate 2 (IRS2) to identify variants associated with obesity- and diabetes-related traits in Hispanic children. Exonic and intronic segments, 5' and 3' flanking regions of IRS2 (∼14.5 kb), were bidirectionally sequenced for single nucleotide polymorphism (SNP) discovery in 934 Hispanic children using 3730XL DNA Sequencers. Additionally, 15 SNPs derived from Illumina HumanOmni1-Quad BeadChips were analyzed. Measured genotype analysis tested associations between SNPs and obesity and diabetes-related traits. Bayesian quantitative trait nucleotide analysis was used to statistically infer the most likely functional polymorphisms. A total of 140 SNPs were identified with minor allele frequencies (MAF) ranging from 0.001 to 0.47. Forty-two of the 70 coding SNPs result in nonsynonymous amino acid substitutions relative to the consensus sequence; 28 SNPs were detected in the promoter, 12 in introns, 28 in the 3'-UTR, and 2 in the 5'-UTR. Two insertion/deletions (indels) were detected. Ten independent rare SNPs (MAF = 0.001-0.009) were associated with obesity-related traits (P = 0.01-0.00002). SNP 10510452_139 in the promoter region was shown to have a high posterior probability (P = 0.77-0.86) of influencing BMI, fat mass, and waist circumference in Hispanic children. SNP 10510452_139 contributed between 2 and 4% of the population variance in body weight and composition. None of the SNPs or indels were associated with diabetes-related traits or accounted for a previously identified quantitative trait locus on chromosome 13 for fasting serum glucose. Rare but not common IRS2 variants may play a role in the regulation of body weight but not an essential role in fasting glucose homeostasis in Hispanic children.
Keywords: Bayes Theorem; Child; Diabetes Mellitus; Fasting; Genetic Predisposition to Disease; Genotyping Techniques; Glucose; Hispanic or Latino; Homeostasis; Humans; Insulin Receptor Substrate Proteins; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Sequence Analysis, DNA

SSTR5 P335L monoclonal antibody differentiates pancreatic neuroendocrine neuroplasms with different SSTR5 genotypes. - Zhou, Guisheng; Marie-Claude Gingras; Liu, Shi-He; Sanchez, Robbi; Edwards, Dean; Dawson, David; Christensen, Kurt; Paganelli, Giovanni; Richard A Gibbs; Fisher, William; Brunicardi, Francis C (Surgery, 2011)
BACKGROUND: Somatostatin receptor type 5 (SSTR5) P335L is a hypofunctional, single nucleotide polymorphism of SSTR5 with implications in the diagnostics and therapy of pancreatic neuroendocrine neoplasms. The purpose of this study is to determine whether a SSTR5 P335L-specific monoclonal antibody could sufficiently differentiate pancreatic neuroendocrine neoplasms (PNENs) with different SSTR5 genotypes. METHODS: Cellular proliferation rate, SSTR5 mRNA level, and SSTR5 protein level were measured by performing MTS assay, a quantitative reverse transcription polymerase chain reaction study, Western blot analysis, and immunohistochemistry, respectively. SSTR5 genotype was determined with the TaqMan SNP Genotyping assay (Applied Biosystems, Foster City, CA). RESULTS: We found that the SSTR5 analogue RPL-1980 inhibited cellular proliferation of CAPAN-1 cells more than that of PANC-1 cells. Only PANC-1 (TT) cells, but not CAPAN-1 (CC) cells expressed SSTR5 P335L. In 29 white patients with PNENs, 38% had a TT genotype for SSTR5 P335L, 24% had a CC genotype for WT SSTR5, and 38% hada CT genotype for both SSTR5 P335L and WT SSTR5. Immunohistochemistry using SSTR5 P335L monoclonal antibody detected immunostaining signals only from the neuroendocrine specimens with TT and CT genotypes, but not those with CC genotypes. CONCLUSION: A SSTR5 P335L monoclonal antibody that specifically recognizes SSTR5 P335L but not WT SSTR5 could differentiate PNENs with different SSTR5 genotypes, thereby providing a potential tool for the clinical diagnosis of PNEN.
Keywords: Antibodies, Monoclonal, Murine-Derived; Blotting, Western; Cell Line, Tumor; Genotype; Humans; Immunohistochemistry; Neuroendocrine Tumors; Pancreatic Neoplasms; Polymorphism, Single Nucleotide; Receptors, Somatostatin; Reverse Transcriptase Polymerase Chain Reaction

Targeted enrichment beyond the consensus coding DNA sequence exome reveals exons with higher variant densities. - Bainbridge, Matthew N; Wang, Min; Wu, Yuanqing; Newsham, Irene; Donna M Muzny; Jefferies, John L; Albert, Thomas J; Burgess, Daniel L; Richard A Gibbs (Genome Biol, 2011)
BACKGROUND: Enrichment of loci by DNA hybridization-capture, followed by high-throughput sequencing, is an important tool in modern genetics. Currently, the most common targets for enrichment are the protein coding exons represented by the consensus coding DNA sequence (CCDS). The CCDS, however, excludes many actual or computationally predicted coding exons present in other databases, such as RefSeq and Vega, and non-coding functional elements such as untranslated and regulatory regions. The number of variants per base pair (variant density) and our ability to interrogate regions outside of the CCDS regions is consequently less well understood. RESULTS: We examine capture sequence data from outside of the CCDS regions and find that extremes of GC content that are present in different subregions of the genome can reduce the local capture sequence coverage to less than 50% relative to the CCDS. This effect is due to biases inherent in both the Illumina and SOLiD sequencing platforms that are exacerbated by the capture process. Interestingly, for two subregion types, microRNA and predicted exons, the capture process yields higher than expected coverage when compared to whole genome sequencing. Lastly, we examine the variation present in non-CCDS regions and find that predicted exons, as well as exonic regions specific to RefSeq and Vega, show much higher variant densities than the CCDS. CONCLUSIONS: We show that regions outside of the CCDS perform less efficiently in capture sequence experiments. Further, we show that the variant density in computationally predicted exons is more than 2.5-times higher than that observed in the CCDS.
Keywords: Alleles; Computational Biology; Consensus Sequence; Exome; Exons; Gene Frequency; Genome, Human; Humans; Introns; Mutation Rate; Open Reading Frames; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Transcriptomic analysis supports similar functional roles for the two thymuses of the tammar wallaby. - Wong, Emily S W; Papenfuss, Anthony T; Heger, Andreas; Hsu, Arthur L; Ponting, Chris P; Miller, Robert D; Fenelon, Jane C; Renfree, Marilyn B; Richard A Gibbs; Belov, Katherine (BMC Genomics, 2011)
BACKGROUND: The thymus plays a critical role in the development and maturation of T-cells. Humans have a single thoracic thymus and presence of a second thymus is considered an anomaly. However, many vertebrates have multiple thymuses. The tammar wallaby has two thymuses: a thoracic thymus (typically found in all mammals) and a dominant cervical thymus. Researchers have known about the presence of the two wallaby thymuses since the 1800s, but no genome-wide research has been carried out into possible functional differences between the two thymic tissues. Here, we used pyrosequencing to compare the transcriptomes of a cervical and thoracic thymus from a single 178 day old tammar wallaby. RESULTS: We show that both the tammar thoracic and the cervical thymuses displayed gene expression profiles consistent with roles in T-cell development. Both thymuses expressed genes that mediate distinct phases of T-cells differentiation, including the initial commitment of blood stem cells to the T-lineage, the generation of T-cell receptor diversity and development of thymic epithelial cells. Crucial immune genes, such as chemokines were also present. Comparable patterns of expression of non-coding RNAs were seen. 67 genes differentially expressed between the two thymuses were detected, and the possible significance of these results are discussed. CONCLUSION: This is the first study comparing the transcriptomes of two thymuses from a single individual. Our finding supports that both thymuses are functionally equivalent and drive T-cell development. These results are an important first step in the understanding of the genetic processes that govern marsupial immunity, and also allow us to begin to trace the evolution of the mammalian immune system.
Keywords: Animals; Antigens; Gene Expression Profiling; Macropodidae; Organ Specificity; RNA, Untranslated; Thorax; Thymus Gland

TTC21B contributes both causal and modifying alleles across the ciliopathy spectrum. - Davis, Erica E; Zhang, Qi; Liu, Qin; Diplas, Bill H; Davey, Lisa M; Hartley, Jane; Stoetzel, Corinne; Szymanska, Katarzyna; Ramaswami, Gokul; Logan, Clare V; Donna M Muzny; Young, Alice C; et al. (Nat Genet, 2011)
Ciliary dysfunction leads to a broad range of overlapping phenotypes, collectively termed ciliopathies. This grouping is underscored by genetic overlap, where causal genes can also contribute modifier alleles to clinically distinct disorders. Here we show that mutations in TTC21B, which encodes the retrograde intraflagellar transport protein IFT139, cause both isolated nephronophthisis and syndromic Jeune asphyxiating thoracic dystrophy. Moreover, although resequencing of TTC21B in a large, clinically diverse ciliopathy cohort and matched controls showed a similar frequency of rare changes, in vivo and in vitro evaluations showed a significant enrichment of pathogenic alleles in cases (P < 0.003), suggesting that TTC21B contributes pathogenic alleles to ∼5% of ciliopathy cases. Our data illustrate how genetic lesions can be both causally associated with diverse ciliopathies and interact in trans with other disease-causing genes and highlight how saturated resequencing followed by functional analysis of all variants informs the genetic architecture of inherited disorders.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Ciliary Motility Disorders; Genetic Variation; Humans; Mice; Mutation; Pedigree; Photoreceptor Cells; Zebrafish

Whole-exome sequencing identifies ALMS1, IQCB1, CNGA3, and MYO7A mutations in patients with Leber congenital amaurosis. - Wang, Xia; Wang, Hui; Cao, Ming; Li, Zhe; Chen, Xianfeng; Patenia, Claire; Gore, Athurva; Abboud, Emad B; Al-Rajhi, Ali A; Lewis, Richard A; Lupski, James R; Mardon, Graeme; et al. (Hum Mutat, 2011)
It has been well documented that mutations in the same retinal disease gene can result in different clinical phenotypes due to difference in the mutant allele and/or genetic background. To evaluate this, a set of consanguineous patient families with Leber congenital amaurosis (LCA) that do not carry mutations in known LCA disease genes was characterized through homozygosity mapping followed by targeted exon/whole-exome sequencing to identify genetic variations. Among these families, a total of five putative disease-causing mutations, including four novel alleles, were found for six families. These five mutations are located in four genes, ALMS1, IQCB1, CNGA3, and MYO7A. Therefore, in our LCA collection from Saudi Arabia, three of the 37 unassigned families carry mutations in retinal disease genes ALMS1, CNGA3, and MYO7A, which have not been previously associated with LCA, and 3 of the 37 carry novel mutations in IQCB1, which has been recently associated with LCA. Together with other reports, our results emphasize that the molecular heterogeneity underlying LCA, and likely other retinal diseases, may be highly complex. Thus, to obtain accurate diagnosis and gain a complete picture of the disease, it is essential to sequence a larger set of retinal disease genes and combine the clinical phenotype with molecular diagnosis.
Keywords: Calmodulin-Binding Proteins; Cell Cycle Proteins; Child, Preschool; Chromosome Mapping; Consanguinity; Cyclic Nucleotide-Gated Cation Channels; DNA Mutational Analysis; Exome; Family; Homozygote; Humans; Leber Congenital Amaurosis; Mutation; Myosin VIIa; Myosins; Pedigree; Proteins; Saudi Arabia; Sequence Analysis, DNA

Whole-exome sequencing identifies compound heterozygous mutations in WDR62 in siblings with recurrent polymicrogyria. - Murdock, David R; Clark, Gary D; Bainbridge, Matthew N; Newsham, Irene; Wu, Yuan-Qing; Donna M Muzny; Cheung, Sau Wai; Richard A Gibbs; Ramocki, Melissa B (Am J Med Genet A, 2011)
Polymicrogyria is a disorder of neuronal development resulting in structurally abnormal cerebral hemispheres characterized by over-folding and abnormal lamination of the cerebral cortex. Polymicrogyria is frequently associated with severe neurologic deficits including intellectual disability, motor problems, and epilepsy. There are acquired and genetic causes of polymicrogyria, but most patients with a presumed genetic etiology lack a specific diagnosis. Here we report using whole-exome sequencing to identify compound heterozygous mutations in the WD repeat domain 62 (WDR62) gene as the cause of recurrent polymicrogyria in a sibling pair. Sanger sequencing confirmed that the siblings both inherited 1-bp (maternal allele) and 2-bp (paternal allele) frameshift deletions, which predict premature truncation of WDR62, a protein that has a role in early cortical development. The probands are from a non-consanguineous family of Northern European descent, suggesting that autosomal recessive PMG due to compound heterozygous mutation of WDR62 might be a relatively common cause of PMG in the population. Further studies to identify mutation frequency in the population are needed.
Keywords: Abnormalities, Multiple; Adult; Base Sequence; Cell Cycle Proteins; Child; Craniofacial Abnormalities; Exome; Female; Frameshift Mutation; Genetic Testing; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Malformations of Cortical Development; Mutation; Nerve Tissue Proteins; Sequence Analysis, DNA; Sequence Deletion; Siblings

Whole-genome sequencing for optimized patient management. - Bainbridge, Matthew N; Wiszniewski, Wojciech; Murdock, David R; Friedman, Jennifer; Gonzaga-Jauregui, Claudia; Newsham, Irene; Reid, Jeffrey G; Fink, John K; Morgan, Margaret B; Marie-Claude Gingras; Donna M Muzny; Hoang, Linh D; et al. (Sci Transl Med, 2011)
Whole-genome sequencing of patient DNA can facilitate diagnosis of a disease, but its potential for guiding treatment has been under-realized. We interrogated the complete genome sequences of a 14-year-old fraternal twin pair diagnosed with dopa (3,4-dihydroxyphenylalanine)-responsive dystonia (DRD; Mendelian Inheritance in Man #128230). DRD is a genetically heterogeneous and clinically complex movement disorder that is usually treated with l-dopa, a precursor of the neurotransmitter dopamine. Whole-genome sequencing identified compound heterozygous mutations in the SPR gene encoding sepiapterin reductase. Disruption of SPR causes a decrease in tetrahydrobiopterin, a cofactor required for the hydroxylase enzymes that synthesize the neurotransmitters dopamine and serotonin. Supplementation of l-dopa therapy with 5-hydroxytryptophan, a serotonin precursor, resulted in clinical improvements in both twins.
Keywords: Adolescent; Decision Making; Dystonic Disorders; Female; Genome, Human; Humans; Levodopa; Male; Patient Care; Pedigree; Sequence Analysis, DNA; Treatment Outcome; Twins, Dizygotic

Comparative genomics of Gardnerella vaginalis strains reveals substantial differences in metabolic and virulence potential. - Yeoman, Carl J; Yildirim, Suleyman; Thomas, Susan M; Durkin, A Scott; Torralba, Manolito; Sutton, Granger; Buhay, Christian J; Ding, Yan; Dugan-Rocha, Shannon P; Donna M Muzny; Qin, Xiang; Richard A Gibbs; et al. (PLoS One, 2010)
BACKGROUND: Gardnerella vaginalis is described as a common vaginal bacterial species whose presence correlates strongly with bacterial vaginosis (BV). Here we report the genome sequencing and comparative analyses of three strains of G. vaginalis. Strains 317 (ATCC 14019) and 594 (ATCC 14018) were isolated from the vaginal tracts of women with symptomatic BV, while Strain 409-05 was isolated from a healthy, asymptomatic individual with a Nugent score of 9. PRINCIPAL FINDINGS: Substantial genomic rearrangement and heterogeneity were observed that appeared to have resulted from both mobile elements and substantial lateral gene transfer. These genomic differences translated to differences in metabolic potential. All strains are equipped with significant virulence potential, including genes encoding the previously described vaginolysin, pili for cytoadhesion, EPS biosynthetic genes for biofilm formation, and antimicrobial resistance systems, We also observed systems promoting multi-drug and lantibiotic extrusion. All G. vaginalis strains possess a large number of genes that may enhance their ability to compete with and exclude other vaginal colonists. These include up to six toxin-antitoxin systems and up to nine additional antitoxins lacking cognate toxins, several of which are clustered within each genome. All strains encode bacteriocidal toxins, including two lysozyme-like toxins produced uniquely by strain 409-05. Interestingly, the BV isolates encode numerous proteins not found in strain 409-05 that likely increase their pathogenic potential. These include enzymes enabling mucin degradation, a trait previously described to strongly correlate with BV, although commonly attributed to non-G. vaginalis species. CONCLUSIONS: Collectively, our results indicate that all three strains are able to thrive in vaginal environments, and therein the BV isolates are capable of occupying a niche that is unique from 409-05. Each strain has significant virulence potential, although genomic and metabolic differences, such as the ability to degrade mucin, indicate that the detection of G. vaginalis in the vaginal tract provides only partial information on the physiological potential of the organism.
Keywords: Bacterial Proteins; Female; Gardnerella vaginalis; Genomics; Humans; Male; Molecular Sequence Data; Phylogeny; Vagina; Vaginosis, Bacterial; Virulence

Complete Khoisan and Bantu genomes from southern Africa. - Schuster, Stephan C; Miller, Webb; Ratan, Aakrosh; Tomsho, Lynn P; Giardine, Belinda; Kasson, Lindsay R; Harris, Robert S; Petersen, Desiree C; Zhao, Fangqing; Qi, Ji; Alkan, Can; Kidd, Jeffrey M; et al. (Nature, 2010)
The genetic structure of the indigenous hunter-gatherer peoples of southern Africa, the oldest known lineage of modern human, is important for understanding human diversity. Studies based on mitochondrial and small sets of nuclear markers have shown that these hunter-gatherers, known as Khoisan, San, or Bushmen, are genetically divergent from other humans. However, until now, fully sequenced human genomes have been limited to recently diverged populations. Here we present the complete genome sequences of an indigenous hunter-gatherer from the Kalahari Desert and a Bantu from southern Africa, as well as protein-coding regions from an additional three hunter-gatherers from disparate regions of the Kalahari. We characterize the extent of whole-genome and exome diversity among the five men, reporting 1.3 million novel DNA differences genome-wide, including 13,146 novel amino acid variants. In terms of nucleotide substitutions, the Bushmen seem to be, on average, more different from each other than, for example, a European and an Asian. Observed genomic differences between the hunter-gatherers and others may help to pinpoint genetic adaptations to an agricultural lifestyle. Adding the described variants to current databases will facilitate inclusion of southern Africans in medical research efforts, particularly when family and medical histories can be correlated with genome-wide data.
Keywords: Asian People; Black People; Ethnicity; Exons; Genetics, Medical; Genome, Human; Humans; Phylogeny; Polymorphism, Single Nucleotide; South Africa; White People

Deep resequencing reveals excess rare recent variants consistent with explosive population growth. - Coventry, Alex; Bull-Otterson, Lara M; Liu, Xiaoming; Clark, Andrew G; Maxwell, Taylor J; Crosby, Jacy; Hixson, James E; Rea, Thomas J; Donna M Muzny; Lewis, Lora R; David A Wheeler; Aniko Sabo; et al. (Nat Commun, 2010)
Accurately determining the distribution of rare variants is an important goal of human genetics, but resequencing of a sample large enough for this purpose has been unfeasible until now. Here, we applied Sanger sequencing of genomic PCR amplicons to resequence the diabetes-associated genes KCNJ11 and HHEX in 13,715 people (10,422 European Americans and 3,293 African Americans) and validated amplicons potentially harbouring rare variants using 454 pyrosequencing. We observed far more variation (expected variant-site count ∼578) than would have been predicted on the basis of earlier surveys, which could only capture the distribution of common variants. By comparison with earlier estimates based on common variants, our model shows a clear genetic signal of accelerating population growth, suggesting that humanity harbours a myriad of rare, deleterious variants, and that disease risk and the burden of disease in contemporary populations may be heavily influenced by the distribution of rare variants.

Evidence that multiple genetic variants of MC4R play a functional role in the regulation of energy expenditure and appetite in Hispanic children. - Cole, Shelley A; Butte, Nancy F; Voruganti, V Saroja; Cai, Guowen; Haack, Karin; Kent, Jack W; Blangero, John; Comuzzie, Anthony G; McPherson, John D; Richard A Gibbs (Am J Clin Nutr, 2010)
BACKGROUND: Melanocortin-4-receptor (MC4R) haploinsufficiency is the most common form of monogenic obesity; however, the frequency of MC4R variants and their functional effects in general populations remain uncertain. OBJECTIVE: The aim was to identify and characterize the effects of MC4R variants in Hispanic children. DESIGN: MC4R was resequenced in 376 parents, and the identified single nucleotide polymorphisms (SNPs) were genotyped in 613 parents and 1016 children from the Viva la Familia cohort. Measured genotype analysis (MGA) tested associations between SNPs and phenotypes. Bayesian quantitative trait nucleotide (BQTN) analysis was used to infer the most likely functional polymorphisms influencing obesity-related traits. RESULTS: Seven rare SNPs in coding and 18 SNPs in flanking regions of MC4R were identified. MGA showed suggestive associations between MC4R variants and body size, adiposity, glucose, insulin, leptin, ghrelin, energy expenditure, physical activity, and food intake. BQTN analysis identified SNP 1704 in a predicted micro-RNA target sequence in the downstream flanking region of MC4R as a strong, probable functional variant influencing total, sedentary, and moderate activities with posterior probabilities of 1.0. SNP 2132 was identified as a variant with a high probability (1.0) of exerting a functional effect on total energy expenditure and sleeping metabolic rate. SNP rs34114122 was selected as having likely functional effects on the appetite hormone ghrelin, with a posterior probability of 0.81. CONCLUSION: This comprehensive investigation provides strong evidence that MC4R genetic variants are likely to play a functional role in the regulation of weight, not only through energy intake but through energy expenditure.
Keywords: Adult; Appetite; Body Mass Index; Body Size; Child; Chromosomes, Human, Pair 18; Energy Intake; Energy Metabolism; Exercise; Exons; Family; Genetic Variation; Genotype; Hispanic or Latino; Humans; Life Style; Linkage Disequilibrium; MicroRNAs; Obesity; Overweight; Parents; Polymorphism, Single Nucleotide; Receptor, Melanocortin, Type 4

A full-length cDNA resource for the pea aphid, Acyrthosiphon pisum. - Shigenobu, S; Richards, S; Cree, A G; Morioka, M; Fukatsu, T; Kudo, T; Miyagishima, S; Richard A Gibbs; Stern, D L; Nakabachi, A (Insect Mol Biol, 2010)
Large collections of full-length cDNAs are important resources for genome annotation and functional genomics. We report the creation of a collection of 50 599 full-length cDNA clones from the pea aphid, Acyrthosiphon pisum. Sequencing from 5' and 3' ends of the clones generated 97 828 high-quality expressed sequence tags, representing approximately 9000 genes. These sequences were imported to AphidBase and are shown to play crucial roles in both automatic gene prediction and manual annotation. Our detailed analyses demonstrated that the full-length cDNAs can further improve gene models and can even identify novel genes that are not included in the current version of the official gene set. This full-length cDNA collection can be utilized for a wide variety of functional studies, serving as a community resource for the study of the functional genomics of the pea aphid.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Animals; Aphids; Base Sequence; DNA Primers; DNA, Complementary; Expressed Sequence Tags; Gene Library; Genome, Insect; Host-Pathogen Interactions; Models, Genetic; Pisum sativum

Genetic diversity in India and the inference of Eurasian population expansion. - Xing, Jinchuan; Watkins, W Scott; Hu, Ya; Huff, Chad D; Aniko Sabo; Donna M Muzny; Bamshad, Michael J; Richard A Gibbs; Jorde, Lynn B; Fuli Yu (Genome Biol, 2010)
BACKGROUND: Genetic studies of populations from the Indian subcontinent are of great interest because of India's large population size, complex demographic history, and unique social structure. Despite recent large-scale efforts in discovering human genetic variation, India's vast reservoir of genetic diversity remains largely unexplored. RESULTS: To analyze an unbiased sample of genetic diversity in India and to investigate human migration history in Eurasia, we resequenced one 100-kb ENCODE region in 92 samples collected from three castes and one tribal group from the state of Andhra Pradesh in south India. Analyses of the four Indian populations, along with eight HapMap populations (692 samples), showed that 30% of all SNPs in the south Indian populations are not seen in HapMap populations. Several Indian populations, such as the Yadava, Mala/Madiga, and Irula, have nucleotide diversity levels as high as those of HapMap African populations. Using unbiased allele-frequency spectra, we investigated the expansion of human populations into Eurasia. The divergence time estimates among the major population groups suggest that Eurasian populations in this study diverged from Africans during the same time frame (approximately 90 to 110 thousand years ago). The divergence among different Eurasian populations occurred more than 40,000 years after their divergence with Africans. CONCLUSIONS: Our results show that Indian populations harbor large amounts of genetic variation that have not been surveyed adequately by public SNP discovery efforts. Our data also support a delayed expansion hypothesis in which an ancestral Eurasian founding population remained isolated long after the out-of-Africa diaspora, before expanding throughout Eurasia.
Keywords: DNA, Mitochondrial; Ethnicity; Gene Frequency; Genetic Variation; Genetics, Population; Geography; Humans; India; Polymorphism, Single Nucleotide; Population Density; Population Dynamics; Sequence Analysis, DNA

Genetics: Decoding a national treasure. - Kim C Worley; Richard A Gibbs (Nature, 2010)
Keywords: Animals; Contig Mapping; Genetics, Population; Genome; Genomics; Humans; Sequence Analysis, DNA; Ursidae

Integrating common and rare genetic variation in diverse human populations. - Altshuler, David M; Richard A Gibbs; Peltonen, Leena; Altshuler, David M; Richard A Gibbs; Peltonen, Leena; Dermitzakis, Emmanouil; Schaffner, Stephen F; Fuli Yu; Peltonen, Leena; Dermitzakis, Emmanouil; Bonnen, Penelope E; et al. (Nature, 2010)
Despite great progress in identifying genetic variants that influence human disease, most inherited risk remains unexplained. A more complete understanding requires genome-wide studies that fully examine less common alleles in populations with a wide range of ancestry. To inform the design and interpretation of such studies, we genotyped 1.6 million common single nucleotide polymorphisms (SNPs) in 1,184 reference individuals from 11 global populations, and sequenced ten 100-kilobase regions in 692 of these individuals. This integrated data set of common and rare alleles, called 'HapMap 3', includes both SNPs and copy number polymorphisms (CNPs). We characterized population-specific differences among low-frequency variants, measured the improvement in imputation accuracy afforded by the larger reference panel, especially in imputing SNPs with a minor allele frequency of <or=5%, and demonstrated the feasibility of imputing newly discovered CNPs and SNPs. This expanded public resource of genome variants in global populations supports deeper interrogation of genomic variation and its role in human disease, and serves as a step towards a high-resolution map of the landscape of human genetic variation.
Keywords: DNA Copy Number Variations; Genome, Human; Human Genome Project; Humans; Polymorphism, Single Nucleotide; Population Groups

A map of human genome variation from population-scale sequencing. - Abecasis, Gonçalo R; Altshuler, David; Auton, Adam; Brooks, Lisa D; Durbin, Richard M; Richard A Gibbs; Hurles, Matt E; McVean, Gil A (Nature, 2010)
The 1000 Genomes Project aims to provide a deep characterization of human genome sequence variation as a foundation for investigating the relationship between genotype and phenotype. Here we present results of the pilot phase of the project, designed to develop and compare different strategies for genome-wide sequencing with high-throughput platforms. We undertook three projects: low-coverage whole-genome sequencing of 179 individuals from four populations; high-coverage sequencing of two mother-father-child trios; and exon-targeted sequencing of 697 individuals from seven populations. We describe the location, allele frequency and local haplotype structure of approximately 15 million single nucleotide polymorphisms, 1 million short insertions and deletions, and 20,000 structural variants, most of which were previously undescribed. We show that, because we have catalogued the vast majority of common variation, over 95% of the currently accessible variants found in any individual are present in this data set. On average, each person is found to carry approximately 250 to 300 loss-of-function variants in annotated genes and 50 to 100 variants previously implicated in inherited disorders. We demonstrate how these results can be used to inform association and functional studies. From the two trios, we directly estimate the rate of de novo germline base substitution mutations to be approximately 10(-8) per base pair per generation. We explore the data with regard to signatures of natural selection, and identify a marked reduction of genetic variation in the neighbourhood of genes, due to selection at linked sites. These methods and public data will support the next phase of human genetic research.
Keywords: Calibration; Chromosomes, Human, Y; Computational Biology; DNA Mutational Analysis; DNA, Mitochondrial; Evolution, Molecular; Female; Genetic Association Studies; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genomics; Genotype; Haplotypes; Humans; Male; Mutation; Pilot Projects; Polymorphism, Single Nucleotide; Recombination, Genetic; Sample Size; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

Rapid identification of heterozygous mutations in Drosophila melanogaster using genomic capture sequencing. - Wang, Hui; Chattopadhyay, Abanti; Li, Zhe; Daines, Bryce; Yumei Li; Gao, Chunxu; Richard A Gibbs; Zhang, Kun; Rui Chen (Genome Res, 2010)
One of the key advantages of using Drosophila melanogaster as a genetic model organism is the ability to conduct saturation mutagenesis screens to identify genes and pathways underlying a given phenotype. Despite the large number of genetic tools developed to facilitate downstream cloning of mutations obtained from such screens, the current procedure remains labor intensive, time consuming, and costly. To address this issue, we designed an efficient strategy for rapid identification of heterozygous mutations in the fly genome by combining rough genetic mapping, targeted DNA capture, and second generation sequencing technology. We first tested this method on heterozygous flies carrying either a previously characterized dac(5) or sens(E2) mutation. Targeted amplification of genomic regions near these two loci was used to enrich DNA for sequencing, and both point mutations were successfully identified. When this method was applied to uncharacterized twr mutant flies, the underlying mutation was identified as a single-base mutation in the gene Spase18-21. This targeted-genome-sequencing method reduces time and effort required for mutation cloning by up to 80% compared with the current approach and lowers the cost to <$1000 for each mutant. Introduction of this and other sequencing-based methods for mutation cloning will enable broader usage of forward genetics screens and have significant impacts in the field of model organisms such as Drosophila.
Keywords: Animals; Animals, Genetically Modified; Base Sequence; Cost-Benefit Analysis; DNA Mutational Analysis; Drosophila melanogaster; Genetic Carrier Screening; Genome, Insect; Heterozygote; Models, Biological; Molecular Sequence Data; Point Mutation; Sequence Homology, Nucleic Acid; Time Factors

A SNP discovery method to assess variant allele probability from next-generation resequencing data. - Shen, Yufeng; Wan, Zhengzheng; Coarfa, Cristian; Drabek, Rafal; Chen, Lei; Ostrowski, Elizabeth A; Liu, Yue; Weinstock, George M; Wheeler, David A; Richard A Gibbs; Fuli Yu (Genome Res, 2010)
Accurate identification of genetic variants from next-generation sequencing (NGS) data is essential for immediate large-scale genomic endeavors such as the 1000 Genomes Project, and is crucial for further genetic analysis based on the discoveries. The key challenge in single nucleotide polymorphism (SNP) discovery is to distinguish true individual variants (occurring at a low frequency) from sequencing errors (often occurring at frequencies orders of magnitude higher). Therefore, knowledge of the error probabilities of base calls is essential. We have developed Atlas-SNP2, a computational tool that detects and accounts for systematic sequencing errors caused by context-related variables in a logistic regression model learned from training data sets. Subsequently, it estimates the posterior error probability for each substitution through a Bayesian formula that integrates prior knowledge of the overall sequencing error probability and the estimated SNP rate with the results from the logistic regression model for the given substitutions. The estimated posterior SNP probability can be used to distinguish true SNPs from sequencing errors. Validation results show that Atlas-SNP2 achieves a false-positive rate of lower than 10%, with an approximately 5% or lower false-negative rate.
Keywords: Algorithms; Alleles; Bayes Theorem; Computer Simulation; Genome, Bacterial; Logistic Models; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Software; Staphylococcus aureus

Taking DNA from the dead. - McGuire, Amy L; Majumder, Mary A; Halpern, Scott D; Swindell, J S; Yaeger, Laura V; Richard A Gibbs; Wheeler, Thomas M (Nat Rev Genet, 2010)
Keywords: Cadaver; DNA; Ethics, Medical; Informed Consent

Whole exome capture in solution with 3 Gbp of data. - Bainbridge, Matthew N; Wang, Min; Burgess, Daniel L; Kovar, Christie; Rodesch, Matthew J; D'Ascenzo, Mark; Kitzman, Jacob; Wu, Yuan-Qing; Newsham, Irene; Richmond, Todd A; Jeddeloh, Jeffrey A; Donna M Muzny; et al. (Genome Biol, 2010)
We have developed a solution-based method for targeted DNA capture-sequencing that is directed to the complete human exome. Using this approach allows the discovery of greater than 95% of all expected heterozygous singe base variants, requires as little as 3 Gbp of raw sequence data and constitutes an effective tool for identifying rare coding alleles in large scale genomic studies.
Keywords: Base Pairing; Databases, Nucleic Acid; Exons; Gene Library; Haplotypes; Humans; Polymorphism, Single Nucleotide; Reproducibility of Results; Sequence Alignment; Sequence Analysis, DNA; Solutions

Whole-genome sequencing in a patient with Charcot-Marie-Tooth neuropathy. - Lupski, James R; Reid, Jeffrey G; Gonzaga-Jauregui, Claudia; Rio Deiros, David; Chen, David C Y; Nazareth, Lynne; Bainbridge, Matthew; Dinh, Huyen; Jing, Chyn; Wheeler, David A; McGuire, Amy L; Zhang, Feng; et al. (N Engl J Med, 2010)
BACKGROUND: Whole-genome sequencing may revolutionize medical diagnostics through rapid identification of alleles that cause disease. However, even in cases with simple patterns of inheritance and unambiguous diagnoses, the relationship between disease phenotypes and their corresponding genetic changes can be complicated. Comprehensive diagnostic assays must therefore identify all possible DNA changes in each haplotype and determine which are responsible for the underlying disorder. The high number of rare, heterogeneous mutations present in all humans and the paucity of known functional variants in more than 90% of annotated genes make this challenge particularly difficult. Thus, the identification of the molecular basis of a genetic disease by means of whole-genome sequencing has remained elusive. We therefore aimed to assess the usefulness of human whole-genome sequencing for genetic diagnosis in a patient with Charcot-Marie-Tooth disease. METHODS: We identified a family with a recessive form of Charcot-Marie-Tooth disease for which the genetic basis had not been identified. We sequenced the whole genome of the proband, identified all potential functional variants in genes likely to be related to the disease, and genotyped these variants in the affected family members. RESULTS: We identified and validated compound, heterozygous, causative alleles in SH3TC2 (the SH3 domain and tetratricopeptide repeats 2 gene), involving two mutations, in the proband and in family members affected by Charcot-Marie-Tooth disease. Separate subclinical phenotypes segregated independently with each of the two mutations; heterozygous mutations confer susceptibility to neuropathy, including the carpal tunnel syndrome. CONCLUSIONS: As shown in this study of a family with Charcot-Marie-Tooth disease, whole-genome sequencing can identify clinically relevant variants and provide diagnostic information to inform the care of patients.
Keywords: Adult; Aged; Aged, 80 and over; Charcot-Marie-Tooth Disease; Codon, Nonsense; Female; Genes, Recessive; Genetic Association Studies; Genome, Human; Genotype; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Bos taurus genome assembly. - Liu, Yue; Qin, Xiang; Song, Xing-Zhi Henry; Jiang, Huaiyang; Shen, Yufeng; Durbin, K James; Lien, Sigbjørn; Kent, Matthew Peter; Sodeland, Marte; Ren, Yanru; Zhang, Lan; Sodergren, Erica; et al. (BMC Genomics, 2009)
BACKGROUND: We present here the assembly of the bovine genome. The assembly method combines the BAC plus WGS local assembly used for the rat and sea urchin with the whole genome shotgun (WGS) only assembly used for many other animal genomes including the rhesus macaque. RESULTS: The assembly process consisted of multiple phases: First, BACs were assembled with BAC generated sequence, then subsequently in combination with the individual overlapping WGS reads. Different assembly parameters were tested to separately optimize the performance for each BAC assembly of the BAC and WGS reads. In parallel, a second assembly was produced using only the WGS sequences and a global whole genome assembly method. The two assemblies were combined to create a more complete genome representation that retained the high quality BAC-based local assembly information, but with gaps between BACs filled in with the WGS-only assembly. Finally, the entire assembly was placed on chromosomes using the available map information.Over 90% of the assembly is now placed on chromosomes. The estimated genome size is 2.87 Gb which represents a high degree of completeness, with 95% of the available EST sequences found in assembled contigs. The quality of the assembly was evaluated by comparison to 73 finished BACs, where the draft assembly covers between 92.5 and 100% (average 98.5%) of the finished BACs. The assembly contigs and scaffolds align linearly to the finished BACs, suggesting that misassemblies are rare. Genotyping and genetic mapping of 17,482 SNPs revealed that more than 99.2% were correctly positioned within the Btau_4.0 assembly, confirming the accuracy of the assembly. CONCLUSION: The biological analysis of this bovine genome assembly is being published, and the sequence data is available to support future bovine research.
Keywords: Animals; Cattle; Chromosome Mapping; Chromosomes, Artificial, Bacterial; Genetic Markers; Genome; Genomics; Sequence Analysis, DNA

A collagen-binding adhesin, Acb, and ten other putative MSCRAMM and pilus family proteins of Streptococcus gallolyticus subsp. gallolyticus (Streptococcus bovis Group, biotype I). - Sillanpaa, Jouko; Nallapareddy, Sreedhar R; Qin, Xiang; Singh, Kavindra V; Donna M Muzny; Kovar, Christie L; Nazareth, Lynne V; Richard A Gibbs; Ferraro, Mary J; Steckelberg, James M; Weinstock, George M; Murray, Barbara E (J Bacteriol, 2009)
Members of the Streptococcus bovis group are important causes of endocarditis. However, factors associated with their pathogenicity, such as adhesins, remain uncharacterized. We recently demonstrated that endocarditis-derived Streptococcus gallolyticus subsp. gallolyticus isolates frequently adhere to extracellular matrix (ECM) proteins. Here, we generated a draft genome sequence of an ECM protein-adherent S. gallolyticus subsp. gallolyticus strain and found, by genome-wide analyses, 11 predicted LPXTG-type cell wall-anchored proteins with characteristics of MSCRAMMs, including a modular architecture of domains predicted to adopt immunoglobulin (Ig)-like folding. A recombinant segment of one of these, Acb, showed high-affinity binding to immobilized collagen, and cell surface expression of Acb correlated with the presence of acb and collagen adherence of isolates. Three of the 11 proteins have similarities to major pilus subunits and are organized in separate clusters, each including a second Ig-fold-containing MSCRAMM and a class C sortase, suggesting that the sequenced strain encodes three distinct types of pili. Reverse transcription-PCR demonstrated that all three genes of one cluster, acb-sbs7-srtC1, are cotranscribed, consistent with pilus operons of other gram-positive bacteria. Further analysis detected expression of all 11 genes in cells grown to mid to late exponential growth phases. Wide distribution of 9 of the 11 genes was observed among S. gallolyticus subsp. gallolyticus isolates with fewer genes present in other S. bovis group species/subspecies. The high prevalence of genes encoding putative MSCRAMMs and pili, including a collagen-binding MSCRAMM, among S. gallolyticus subsp. gallolyticus isolates may play an important role in the predominance of this subspecies in S. bovis endocarditis.
Keywords: Adhesins, Bacterial; Fimbriae, Bacterial; Gene Expression Profiling; Gene Expression Regulation, Bacterial; Genome, Bacterial; Multigene Family; Streptococcus

A common allele in RPGRIP1L is a modifier of retinal degeneration in ciliopathies. - Khanna, Hemant; Davis, Erica E; Murga-Zamalloa, Carlos A; Estrada-Cuzcano, Alejandro; Lopez, Irma; den Hollander, Anneke I; Zonneveld, Marijke N; Othman, Mohammad I; Waseem, Naushin; Chakarova, Christina F; Maubaret, Cecilia; Diaz-Font, Anna; et al. (Nat Genet, 2009)
Despite rapid advances in the identification of genes involved in disease, the predictive power of the genotype remains limited, in part owing to poorly understood effects of second-site modifiers. Here we demonstrate that a polymorphic coding variant of RPGRIP1L (retinitis pigmentosa GTPase regulator-interacting protein-1 like), a ciliary gene mutated in Meckel-Gruber (MKS) and Joubert (JBTS) syndromes, is associated with the development of retinal degeneration in individuals with ciliopathies caused by mutations in other genes. As part of our resequencing efforts of the ciliary proteome, we identified several putative loss-of-function RPGRIP1L mutations, including one common variant, A229T. Multiple genetic lines of evidence showed this allele to be associated with photoreceptor loss in ciliopathies. Moreover, we show that RPGRIP1L interacts biochemically with RPGR, loss of which causes retinal degeneration, and that the Thr229-encoded protein significantly compromises this interaction. Our data represent an example of modification of a discrete phenotype of syndromic disease and highlight the importance of a multifaceted approach for the discovery of modifier alleles of intermediate frequency and effect.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Bardet-Biedl Syndrome; Ciliary Body; Europe; Genetic Variation; GTP Phosphohydrolases; Humans; Mutation; Polymorphism, Single Nucleotide; Retinal Degeneration; Retinitis Pigmentosa; RNA, Messenger; Uveitis; Zebrafish

The completion of the Mammalian Gene Collection (MGC). - Temple, Gary; Gerhard, Daniela S; Rasooly, Rebekah; Feingold, Elise A; Good, Peter J; Robinson, Cristen; Mandich, Allison; Derge, Jeffrey G; Lewis, Jeanne; Shoaf, Debonny; Collins, Francis S; Jang, Wonhee; et al. (Genome Res, 2009)
Since its start, the Mammalian Gene Collection (MGC) has sought to provide at least one full-protein-coding sequence cDNA clone for every human and mouse gene with a RefSeq transcript, and at least 6200 rat genes. The MGC cloning effort initially relied on random expressed sequence tag screening of cDNA libraries. Here, we summarize our recent progress using directed RT-PCR cloning and DNA synthesis. The MGC now contains clones with the entire protein-coding sequence for 92% of human and 89% of mouse genes with curated RefSeq (NM-accession) transcripts, and for 97% of human and 96% of mouse genes with curated RefSeq transcripts that have one or more PubMed publications, in addition to clones for more than 6300 rat genes. These high-quality MGC clones and their sequences are accessible without restriction to researchers worldwide.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA; DNA, Complementary; Gene Library; Genes; Humans; Mammals; Mice; National Institutes of Health (U.S.); Rats; Reverse Transcriptase Polymerase Chain Reaction; United States

Developing a tissue resource to characterize the genome of pancreatic cancer. - Voidonikolas, Georgios; Marie-Claude Gingras; Hodges, Sally; McGuire, Amy L; Chen, Changyi; Richard A Gibbs; Brunicardi, F Charles; Fisher, William E (World J Surg, 2009)
With recent advances in DNA sequencing technology, medicine is entering an era in which a personalized genomic approach to diagnosis and treatment of disease is feasible. However, discovering the role of altered DNA sequences in various disease states will be a challenging task. The genomic approach offers great promise for diseases, such as pancreatic cancer, in which the effect of current diagnostic and treatment modalities is disappointing. To facilitate the characterization of the genome of pancreatic cancer, high-quality and well-annotated tissue repositories are needed. This article summarizes the basic principles that guide the creation of such a repository, including sample processing and preservation techniques, sample size and composition, and collection of clinical data elements.
Keywords: Adenocarcinoma; Computational Biology; Confidentiality; Databases, Genetic; Genomics; Humans; Informed Consent; Organ Preservation Solutions; Pancreatic Neoplasms; Prevalence; Quality Control; Specimen Handling; Tissue Banks; United States

The genome sequence of taurine cattle: a window to ruminant biology and evolution. - Elsik, Christine G; Tellam, Ross L; Worley, Kim C; Richard A Gibbs; Donna M Muzny; Weinstock, George M; Adelson, David L; Eichler, Evan E; Elnitski, Laura; Guigó, Roderic; Hamernik, Debora L; Kappes, Steve M; et al. (Science, 2009)
To understand the biology and evolution of ruminants, the cattle genome was sequenced to about sevenfold coverage. The cattle genome contains a minimum of 22,000 genes, with a core set of 14,345 orthologs shared among seven mammalian species of which 1217 are absent or undetected in noneutherian (marsupial or monotreme) genomes. Cattle-specific evolutionary breakpoint regions in chromosomes have a higher density of segmental duplications, enrichment of repetitive elements, and species-specific variations in genes associated with lactation and immune responsiveness. Genes involved in metabolism are generally highly conserved, although five metabolic genes are deleted or extensively diverged from their human orthologs. The cattle genome sequence thus provides a resource for understanding mammalian evolution and accelerating livestock genetic improvement for milk and meat production.
Keywords: Alternative Splicing; Animals; Animals, Domestic; Biological Evolution; Cattle; Evolution, Molecular; Female; Genetic Variation; Genome; Humans; Male; MicroRNAs; Molecular Sequence Data; Proteins; Sequence Analysis, DNA; Species Specificity; Synteny

Genome-wide survey of SNP variation uncovers the genetic structure of cattle breeds. - Richard A Gibbs; Taylor, Jeremy F; Van Tassell, Curtis P; Barendse, William; Eversole, Kellye A; Gill, Clare A; Green, Ronnie D; Hamernik, Debora L; Kappes, Steven M; Lien, Sigbjørn; Matukumalli, Lakshmi K; McEwan, John C; et al. (Science, 2009)
The imprints of domestication and breed development on the genomes of livestock likely differ from those of companion animals. A deep draft sequence assembly of shotgun reads from a single Hereford female and comparative sequences sampled from six additional breeds were used to develop probes to interrogate 37,470 single-nucleotide polymorphisms (SNPs) in 497 cattle from 19 geographically and biologically diverse breeds. These data show that cattle have undergone a rapid recent decrease in effective population size from a very large ancestral population, possibly due to bottlenecks associated with domestication, selection, and breed formation. Domestication and artificial selection appear to have left detectable signatures of selection within the cattle genome, yet the current levels of diversity within breeds are at least as great as exists within humans.
Keywords: Animals; Breeding; Cattle; Female; Gene Frequency; Genetic Variation; Genome; Male; Molecular Sequence Data; Mutation; Polymorphism, Single Nucleotide; Population Density

Genomics. Genome project standards in a new era of sequencing. - Chain, P S G; Grafham, D V; Fulton, R S; Fitzgerald, M G; Hostetler, J; Donna M Muzny; Ali, J; Birren, B; Bruce, D C; Buhay, C; Cole, J R; Ding, Y; et al. (Science, 2009)
More detailed sequence standards that keep up with revolutionary sequencing technologies will aid the research community in evaluating data.
Keywords: Computational Biology; Databases, Nucleic Acid; Genome; Genomics; Sequence Analysis, DNA

High-throughput multiplex sequencing to discover copy number variants in Drosophila. - Daines, Bryce; Wang, Hui; Yumei Li; Yi Han; Richard A Gibbs; Rui Chen (Genetics, 2009)
Copy number variation (CNV) contributes in phenotypically relevant ways to the genetic variability of many organisms. Cost-effective genomewide methods for identifying copy number variation are necessary to elucidate the contribution that these structural variants make to the genomes of model organisms. We have developed a novel approach for the identification of copy number variation by next generation sequencing. As a proof of concept our method has been applied to map the deletions of three Drosophila deficiency strains. We demonstrate that low sequence coverage is sufficient for identifying and mapping large deletions at kilobase resolution, suggesting that data generated from high-throughput sequencing experiments are sufficient for simultaneously analyzing many strains. Genomic DNA from two Drosophila deficiency stocks was barcoded and sequenced in multiplex, and the breakpoints associated with each deletion were successfully identified. The approach we describe is immediately applicable to the systematic exploration of copy number variation in model organisms and humans.
Keywords: Animals; DNA Copy Number Variations; Drosophila melanogaster; Genome, Insect; Methods; Sequence Analysis, DNA; Sequence Deletion

Low frequency of MLL3 mutations in colorectal carcinoma. - Vakoc, Christopher R; Wen, Yu-Ye; Richard A Gibbs; Johnstone, Cameron N; Rustgi, Anil K; Blobel, Gerd A (Cancer Genet Cytogenet, 2009)
Keywords: Carcinoma; Case-Control Studies; Colorectal Neoplasms; DNA-Binding Proteins; Gene Frequency; Genetic Testing; Humans; Mutation; Polymorphism, Single Nucleotide

Metagenomic pyrosequencing and microbial identification. - Petrosino, Joseph F; Highlander, Sarah; Luna, Ruth Ann; Richard A Gibbs; Versalovic, James (Clin Chem, 2009)
BACKGROUND: The Human Microbiome Project has ushered in a new era for human metagenomics and high-throughput next-generation sequencing strategies. CONTENT: This review describes evolving strategies in metagenomics, with a special emphasis on the core technology of DNA pyrosequencing. The challenges of microbial identification in the context of microbial populations are discussed. The development of next-generation pyrosequencing strategies and the technical hurdles confronting these methodologies are addressed. Bioinformatics-related topics include taxonomic systems, sequence databases, sequence-alignment tools, and classifiers. DNA sequencing based on 16S rRNA genes or entire genomes is summarized with respect to potential pyrosequencing applications. SUMMARY: Both the approach of 16S rDNA amplicon sequencing and the whole-genome sequencing approach may be useful for human metagenomics, and numerous bioinformatics tools are being deployed to tackle such vast amounts of microbiological sequence diversity. Metagenomics, or genetic studies of microbial communities, may ultimately contribute to a more comprehensive understanding of human health, disease susceptibilities, and the pathophysiology of infectious and immune-mediated diseases.
Keywords: Computational Biology; DNA, Bacterial; Genomics; Humans; Metagenome; RNA, Ribosomal, 16S; Sequence Analysis, DNA

Microarray analysis of somatostatin receptor 5-regulated gene expression profiles in murine pancreas. - Patel, Sanjeet G; Zhou, Guisheng; Liu, Shi-He; Li, Min; Jeong, Jae-Wook; DeMayo, Francesco J; Marie-Claude Gingras; Richard A Gibbs; Fisher, William E; Brunicardi, F Charles (World J Surg, 2009)
BACKGROUND: We previously demonstrated that somatostatin receptor type 5 (SSTR5) gene ablation results in alterations in insulin secretion and glucose metabolism, accompanied by morphologic alterations in the islets of Langerhans. The underlying mechanism(s) by which SSTR5 exerts its cellular functions remain(s) unknown. We hypothesized that SSTR5 mediates the inhibitory effect of somatostatin (SST) on insulin secretion and islet proliferation by regulating a specific set of pancreatic genes. METHODS: To identify SSTR5-regulated pancreatic genes, gene expression microarray analysis was performed on the whole pancreas of 1- and 3-month-old wild-type (WT) and SSTR5 knockout (SSTR5-/-) male mice. Real-time RT-PCR and immunofluorescence were performed to validate selected differentially expressed genes. RESULTS: A set of 143 probes were identified to be differentially expressed in the pancreas of 1-month-old SSTR5-/- mice, 72 of which were downregulated and 71 upregulated. At 3 months of age, SSTR5 gene ablation resulted in downregulation of a set of 30 probes and upregulation of a set of 37 probes. Among these differentially expressed genes, there were 15 and 5 genes that were upregulated and downregulated, respectively, in mice at both 1 and 3 months of age. Three genes, PAP/INGAP, ANG, and TDE1, were selected to be validated by real-time RT-PCR and immunofluorescence. CONCLUSIONS: A specific set of genes linked to a wide range of cellular functions such as islet proliferation, apoptosis, angiogenesis, and tumorigenesis were either upregulated or downregulated in SSTR5-deficient male mice compared with their expression in wild-type mice. Therefore, these genes are potential SSTR5-regulated genes during normal pancreatic development and functional maintenance.
Keywords: Animals; Apoptosis; Cell Proliferation; Down-Regulation; Fluorescent Antibody Technique; Gene Expression Profiling; Islets of Langerhans; Male; Mice; Mice, Knockout; Neoplasm Proteins; Neovascularization, Pathologic; Oligonucleotide Array Sequence Analysis; Pancreas; Pancreatitis-Associated Proteins; Proteins; Receptors, Cell Surface; Receptors, Somatostatin; Reverse Transcriptase Polymerase Chain Reaction; Ribonuclease, Pancreatic; Up-Regulation

Mutation survey of known LCA genes and loci in the Saudi Arabian population. - Yumei Li; Wang, Hui; Peng, Jianlan; Richard A Gibbs; Lewis, Richard Alan; Lupski, James R; Mardon, Graeme; Rui Chen (Invest Ophthalmol Vis Sci, 2009)
PURPOSE: The purpose of this study was to perform a comprehensive survey of all known Leber congenital amaurosis (LCA) genes and loci in a collection of 37 consanguineous LCA families from Saudi Arabia. METHODS: Direct PCR and sequencing were used to screen 13 known LCA genes (GUCY2D, CRX, RPE65, TULP1, AIPL1, CRB1, RPGRIP1, LRAT, RDH12, IMPDH1, CEP290, RD3, LCA5). In addition, families without mutations identified were further screened with STR markers around these 13 known LCA genes and two loci. RESULTS: Disease-causing mutations were identified in nine of the 37 families: five in TULP1, two in CRB1, one in RPE65, and one in GUCY2D. Mutations in known genes only accounted for 24% of the Saudi families--much less than what has been observed in the European population (65%). Phenotype-genotype analysis was carried out to investigate the LCA disease penetrance for all families whose mutations identified. All identified mutations were found to segregate perfectly with the disease phenotype. On the other hand, severity of the disease varies for different patients carrying the same mutation and even within the same family. Furthermore, based on homozygosity mapping with both STR and SNP markers, one family is likely to map to the LCA3 locus. CONCLUSIONS: These results underscore the importance of studying LCA disease families from different ethnic backgrounds to identify additional novel LCA disease genes. Furthermore, perfect segregation between mutation and disease indicates that LCA is fully penetrant. However, phenotypic variations among patients carrying the same mutation suggest that at least some of the variations in the clinical phenotype is due to modification from the genetic background, environment, or other factors.
Keywords: Blindness; Carrier Proteins; cis-trans-Isomerases; Consanguinity; DNA Mutational Analysis; Eye Proteins; Female; Genes; Genotype; Guanylate Cyclase; Humans; Male; Membrane Proteins; Microsatellite Repeats; Mutation; Nerve Tissue Proteins; Pedigree; Phenotype; Polymerase Chain Reaction; Receptors, Cell Surface; Retinal Degeneration; Saudi Arabia

Personalized copy number and segmental duplication maps using next-generation sequencing. - Alkan, Can; Kidd, Jeffrey M; Marques-Bonet, Tomas; Aksay, Gozde; Antonacci, Francesca; Hormozdiari, Fereydoun; Kitzman, Jacob O; Baker, Carl; Malig, Maika; Mutlu, Onur; Sahinalp, S Cenk; Richard A Gibbs; et al. (Nat Genet, 2009)
Despite their importance in gene innovation and phenotypic variation, duplicated regions have remained largely intractable owing to difficulties in accurately resolving their structure, copy number and sequence content. We present an algorithm (mrFAST) to comprehensively map next-generation sequence reads, which allows for the prediction of absolute copy-number variation of duplicated segments and genes. We examine three human genomes and experimentally validate genome-wide copy number differences. We estimate that, on average, 73-87 genes vary in copy number between any two individuals and find that these genic differences overwhelmingly correspond to segmental duplications (odds ratio = 135; P < 2.2 x 10(-16)). Our method can distinguish between different copies of highly identical genes, providing a more accurate assessment of gene content and insight into functional constraint without the limitations of array-based technology.
Keywords: Algorithms; Chromosome Mapping; DNA; Gene Dosage; Gene Duplication; Genome, Human; Genomic Library; Humans; Polymorphism, Genetic; Sequence Analysis, DNA

A sequence-level map of chromosomal breakpoints in the MCF-7 breast cancer cell line yields insights into the evolution of a cancer genome. - Hampton, Oliver A; Den Hollander, Petra; Miller, Christopher A; Delgado, David A; Li, Jian; Coarfa, Cristian; R. Alan Harris; Richards, Stephen; Scherer, Steven E; Donna M Muzny; Richard A Gibbs; Lee, Adrian V; et al. (Genome Res, 2009)
By applying a method that combines end-sequence profiling and massively parallel sequencing, we obtained a sequence-level map of chromosomal aberrations in the genome of the MCF-7 breast cancer cell line. A total of 157 distinct somatic breakpoints of two distinct types, dispersed and clustered, were identified. A total of 89 breakpoints are evenly dispersed across the genome. A majority of dispersed breakpoints are in regions of low copy repeats (LCRs), indicating a possible role for LCRs in chromosome breakage. The remaining 68 breakpoints form four distinct clusters of closely spaced breakpoints that coincide with the four highly amplified regions in MCF-7 detected by array CGH located in the 1p13.1-p21.1, 3p14.1-p14.2, 17q22-q24.3, and 20q12-q13.33 chromosomal cytobands. The clustered breakpoints are not significantly associated with LCRs. Sequences flanking most (95%) breakpoint junctions are consistent with double-stranded DNA break repair by nonhomologous end-joining or template switching. A total of 79 known or predicted genes are involved in rearrangement events, including 10 fusions of coding exons from different genes and 77 other rearrangements. Four fusions result in novel expressed chimeric mRNA transcripts. One of the four expressed fusion products (RAD51C-ATXN7) and one gene truncation (BRIP1 or BACH1) involve genes coding for members of protein complexes responsible for homology-driven repair of double-stranded DNA breaks. Another one of the four expressed fusion products (ARFGEF2-SULF2) involves SULF2, a regulator of cell growth and angiogenesis. We show that knock-down of SULF2 in cell lines causes tumorigenic phenotypes, including increased proliferation, enhanced survival, and increased anchorage-independent growth.
Keywords: Breast Neoplasms; Cell Line, Tumor; Chromosome Breakage; Chromosome Mapping; Chromosomes, Artificial, Bacterial; DNA Repair; Evolution, Molecular; Gene Expression Profiling; Genes, Neoplasm; Genome, Human; Humans; Locus Control Region; Models, Biological; Mutant Chimeric Proteins; Sequence Analysis, DNA

Sequencing the full-length of the phosphatase and tensin homolog (PTEN) gene in hepatocellular carcinoma (HCC) using the 454 GS20 and Illumina GA DNA sequencing platforms. - Rodriguez, Joel A; Guiteau, Jacfranz J; Nazareth, Lynne; Reid, Jeff G; Goss, John A; Richard A Gibbs; Marie-Claude Gingras (World J Surg, 2009)
BACKGROUND: Phosphatase and tensin homolog (PTEN) is a tumor-suppressor gene that is mutated in cancer of the liver, pancreas, endometrium, and prostate. PTEN-dependent pathways are involved in mediating cell growth and invasion. To sequence the whole gene (including introns and exons), we have taken advantage of new technologies that allow for rapid, inexpensive sequencing to great depth. METHODS: DNA from 15 HCC specimens were pooled, and long-range PCR was performed by using the GeneAmp XL PCR kit. Primer parameters included: length of 20-30 base pairs (bp), melting temperature of -68 degrees C, and G/C content of 50-60%. PCR products were then column-purified and pooled, and DNA libraries were prepared for "shotgun sequencing" on both the 454 GS and Illumina GA sequencing platforms. RESULTS: We successfully amplified approximately 98.9% of the PTEN gene by using one long-range PCR protocol applied to 24 primer sets, resulting in 20 amplicons approximately 6.5 kilobases (kb) in length, 2 amplicons approximately 10 kb in length, and 2 amplicons approximately 2.5 kb in length. Sequencing of fragmented PCR products on both sequencing platforms identified six high-frequency SNPs that were catalogued in dbSNP as known variants. CONCLUSIONS: Shotgun sequencing based on a single long-range PCR protocol in pooled samples is an efficient and relatively inexpensive way to sequence an entire gene.
Keywords: Carcinoma, Hepatocellular; Exons; Gene Library; Genes, Tumor Suppressor; Humans; Inteins; Liver Neoplasms; Polymerase Chain Reaction; PTEN Phosphohydrolase; Sequence Analysis, DNA; Sequence Analysis, Protein

Single nucleotide polymorphism in RECQL and survival in resectable pancreatic adenocarcinoma. - Cotton, Ronald T; Li, Donghui; Scherer, Steven E; Donna M Muzny; Hodges, Sally E; Catania, Robbi L; Witkiewicz, Agnieszka K; Brody, Jonathan R; Kennedy, Eugene P; Yeo, Charles J; Brunicardi, F Charles; Richard A Gibbs; et al. (HPB (Oxford), 2009)
BACKGROUND: RECQL is a DNA helicase involved in DNA mismatch repair. The RECQL polymorphism, 3' untranslated region (UTR) A159C, was previously associated with overall survival of patients with resectable pancreatic adenocarcinoma treated with neoadjuvant chemoradiation. In the present study, we examined RECQL for somatic mutations and other polymorphisms and compared these findings with the outcome in patients who received adjuvant or neoadjuvant chemoradiation. We hypothesized that RECQL (i) would be mutated in cancer, (ii) would have polymorphisms linked to the 3'UTR A159C and that either or both events would affect function. We also hypothesized that (iii) these changes would be associated with survival in both cohorts of patients. MATERIAL AND METHODS: We sequenced RECQL's 15 exons and surrounding sequences in paired blood and tumour DNA of 39 patients. The 3'UTR A159C genotype was determined in blood DNA samples from 176 patients with resectable pancreatic adenocarcinoma treated with adjuvant (53) or neoadjuvant (123) chemoradiation. Survival was calculated using the Kaplan-Meier method, with log rank comparisons between groups. The relative impact of genotype on time to overall survival was performed using the Cox proportional hazards model. RESULTS: Somatic mutations were found in UTRs and intronic regions but not in exonic coding regions of the RECQL gene. Two single nucleotide polymorphisms (SNPs), located in introns 2 and 11, were found to be part of the same haplotype block as the RECQL A159C SNP and showed a similar association with overall survival. No short-term difference in survival between treatment strategies was found. We identified a subgroup of patients responsive to neoadjuvant therapy in which the 159 A allele conferred strikingly improved long-term survival. DISCUSSION: The RECQL 3'UTR A159C SNP is not linked with other functional SNPs within RECQL but may function as a site for regulatory molecules. The mechanism of action needs to be clarified further.

Analysis of transcriptome data in the red flour beetle, Tribolium castaneum. - Park, Yoonseong; Aikins, Jamie; Wang, L J; Beeman, Richard W; Oppert, Brenda; Lord, Jeffrey C; Brown, Susan J; Lorenzen, Marcé D; Richards, Stephen; Weinstock, George M; Richard A Gibbs (Insect Biochem Mol Biol, 2008)
The whole genome sequence of Tribolium castaneum, a worldwide coleopteran pest of stored products, has recently been determined. In order to facilitate accurate annotation and detailed functional analysis of this genome, we have compiled and analyzed all available expressed sequence tag (EST) data. The raw data consist of 61,228 ESTs, including 10,704 obtained from NCBI and an additional 50,524 derived from 32,544 clones generated in our laboratories. These sequences were amassed from cDNA libraries representing six different tissues or stages, namely: whole embryos, whole larvae, larval hindguts and Malpighian tubules, larval fat bodies and carcasses, adult ovaries, and adult heads. Assembly of the 61,228 sequences collapsed into 12,269 clusters (groups of overlapping ESTs representing single genes), of which 10,134 mapped onto 6,463 (39%) of the 16,422 GLEAN gene models (i.e. official Tribolium gene list). Approximately 1,600 clusters (13% of the total) lack corresponding GLEAN models, despite high matches to the genome, suggesting that a considerable number of transcribed sequences were missed by the gene prediction programs or were removed by GLEAN. We conservatively estimate that the current EST set represents more than 7,500 transcription units.
Keywords: Animals; Databases, Nucleic Acid; Expressed Sequence Tags; Gene Expression Profiling; Gene Library; Tribolium

The complete genome of an individual by massively parallel DNA sequencing. - Wheeler, David A; Srinivasan, Maithreyan; Egholm, Michael; Shen, Yufeng; Chen, Lei; McGuire, Amy; He, Wen; Chen, Yi-Ju; Makhijani, Vinod; Roth, G Thomas; Gomes, Xavier; Tartaro, Karrie; et al. (Nature, 2008)
The association of genetic variation with disease and drug response, and improvements in nucleic acid technologies, have given great optimism for the impact of 'genomic medicine'. However, the formidable size of the diploid human genome, approximately 6 gigabases, has prevented the routine application of sequencing methods to deciphering complete individual human genomes. To realize the full potential of genomics for human health, this limitation must be overcome. Here we report the DNA sequence of a diploid genome of a single individual, James D. Watson, sequenced to 7.4-fold redundancy in two months using massively parallel sequencing in picolitre-size reaction vessels. This sequence was completed in two months at approximately one-hundredth of the cost of traditional capillary electrophoresis methods. Comparison of the sequence to the reference genome led to the identification of 3.3 million single nucleotide polymorphisms, of which 10,654 cause amino-acid substitution within the coding sequence. In addition, we accurately identified small-scale (2-40,000 base pair (bp)) insertion and deletion polymorphism as well as copy number variation resulting in the large-scale gain and loss of chromosomal segments ranging from 26,000 to 1.5 million base pairs. Overall, these results agree well with recent results of sequencing of a single individual by traditional methods. However, in addition to being faster and significantly less expensive, this sequencing technology avoids the arbitrary loss of genomic sequences inherent in random shotgun sequencing by bacterial cloning because it amplifies DNA in a cell-free system. As a result, we further demonstrate the acquisition of novel human sequence, including novel genes not previously identified by traditional genomic sequencing. This is the first genome sequenced by next-generation technologies. Therefore it is a pilot for the future challenges of 'personalized genome sequencing'.
Keywords: Alleles; Computational Biology; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genomics; Genotype; Humans; Individuality; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity; Sequence Alignment; Sequence Analysis, DNA; Software

The complete genome sequence of Escherichia coli DH10B: insights into the biology of a laboratory workhorse. - Durfee, Tim; Nelson, Richard; Baldwin, Schuyler; Plunkett, Guy; Burland, Valerie; Mau, Bob; Petrosino, Joseph F; Qin, Xiang; Donna M Muzny; Ayele, Mulu; Richard A Gibbs; Csörgo, Bálint; et al. (J Bacteriol, 2008)
Escherichia coli DH10B was designed for the propagation of large insert DNA library clones. It is used extensively, taking advantage of properties such as high DNA transformation efficiency and maintenance of large plasmids. The strain was constructed by serial genetic recombination steps, but the underlying sequence changes remained unverified. We report the complete genomic sequence of DH10B by using reads accumulated from the bovine sequencing project at Baylor College of Medicine and assembled with DNAStar's SeqMan genome assembler. The DH10B genome is largely colinear with that of the wild-type K-12 strain MG1655, although it is substantially more complex than previously appreciated, allowing DH10B biology to be further explored. The 226 mutated genes in DH10B relative to MG1655 are mostly attributable to the extensive genetic manipulations the strain has undergone. However, we demonstrate that DH10B has a 13.5-fold higher mutation rate than MG1655, resulting from a dramatic increase in insertion sequence (IS) transposition, especially IS150. IS elements appear to have remodeled genome architecture, providing homologous recombination sites for a 113,260-bp tandem duplication and an inversion. DH10B requires leucine for growth on minimal medium due to the deletion of leuLABCD and harbors both the relA1 and spoT1 alleles causing both sensitivity to nutritional downshifts and slightly lower growth rates relative to the wild type. Finally, while the sequence confirms most of the reported alleles, the sequence of deoR is wild type, necessitating reexamination of the assumed basis for the high transformability of DH10B.
Keywords: Escherichia coli; Genes, Bacterial; Genome, Bacterial; Models, Genetic; Mutation; Sequence Analysis, DNA

The genome of the model beetle and pest Tribolium castaneum. - Stephen Richards; Richard A Gibbs; Weinstock, George M; Brown, Susan J; Denell, Robin; Beeman, Richard W; Richard A Gibbs; Beeman, Richard W; Brown, Susan J; Bucher, Gregor; Friedrich, Markus; Grimmelikhuijzen, Cornelis J P; et al. (Nature, 2008)
Tribolium castaneum is a member of the most species-rich eukaryotic order, a powerful model organism for the study of generalized insect development, and an important pest of stored agricultural products. We describe its genome sequence here. This omnivorous beetle has evolved the ability to interact with a diverse chemical environment, as shown by large expansions in odorant and gustatory receptors, as well as P450 and other detoxification enzymes. Development in Tribolium is more representative of other insects than is Drosophila, a fact reflected in gene content and function. For example, Tribolium has retained more ancestral genes involved in cell-cell communication than Drosophila, some being expressed in the growth zone crucial for axial elongation in short-germ development. Systemic RNA interference in T. castaneum functions differently from that in Caenorhabditis elegans, but nevertheless offers similar power for the elucidation of gene function and identification of targets for selective insect control.
Keywords: Animals; Base Composition; Body Patterning; Cytochrome P-450 Enzyme System; DNA Transposable Elements; Genes, Insect; Genome, Insect; Growth and Development; Humans; Insecticides; Neurotransmitter Agents; Oogenesis; Phylogeny; Proteome; Receptors, G-Protein-Coupled; Receptors, Odorant; Repetitive Sequences, Nucleic Acid; RNA Interference; Taste; Telomere; Tribolium; Vision, Ocular

High-precision, whole-genome sequencing of laboratory strains facilitates genetic studies. - Srivatsan, Anjana; Yi Han; Peng, Jianlan; Tehranchi, Ashley K; Richard A Gibbs; Wang, Jue D; Rui Chen (PLoS Genet, 2008)
Whole-genome sequencing is a powerful technique for obtaining the reference sequence information of multiple organisms. Its use can be dramatically expanded to rapidly identify genomic variations, which can be linked with phenotypes to obtain biological insights. We explored these potential applications using the emerging next-generation sequencing platform Solexa Genome Analyzer, and the well-characterized model bacterium Bacillus subtilis. Combining sequencing with experimental verification, we first improved the accuracy of the published sequence of the B. subtilis reference strain 168, then obtained sequences of multiple related laboratory strains and different isolates of each strain. This provides a framework for comparing the divergence between different laboratory strains and between their individual isolates. We also demonstrated the power of Solexa sequencing by using its results to predict a defect in the citrate signal transduction pathway of a common laboratory strain, which we verified experimentally. Finally, we examined the molecular nature of spontaneously generated mutations that suppress the growth defect caused by deletion of the stringent response mediator relA. Using whole-genome sequencing, we rapidly mapped these suppressor mutations to two small homologs of relA. Interestingly, stable suppressor strains had mutations in both genes, with each mutation alone partially relieving the relA growth defect. This supports an intriguing three-locus interaction module that is not easily identifiable through traditional suppressor mapping. We conclude that whole-genome sequencing can drastically accelerate the identification of suppressor mutations and complex genetic interactions, and it can be applied as a standard tool to investigate the genetic traits of model organisms.
Keywords: Bacillus subtilis; Bacterial Proteins; Genetic Variation; Genome, Bacterial; Molecular Sequence Data; Phenotype; Sequence Analysis, DNA; Suppression, Genetic

Large scale variation in Enterococcus faecalis illustrated by the genome analysis of strain OG1RF. - Bourgogne, Agathe; Garsin, Danielle A; Qin, Xiang; Singh, Kavindra V; Sillanpaa, Jouko; Yerrapragada, Shailaja; Ding, Yan; Dugan-Rocha, Shannon; Buhay, Christian; Shen, Hua; Chen, Guan; Williams, Gabrielle; et al. (Genome Biol, 2008)
BACKGROUND: Enterococcus faecalis has emerged as a major hospital pathogen. To explore its diversity, we sequenced E. faecalis strain OG1RF, which is commonly used for molecular manipulation and virulence studies. RESULTS: The 2,739,625 base pair chromosome of OG1RF was found to contain approximately 232 kilobases unique to this strain compared to V583, the only publicly available sequenced strain. Almost no mobile genetic elements were found in OG1RF. The 64 areas of divergence were classified into three categories. First, OG1RF carries 39 unique regions, including 2 CRISPR loci and a new WxL locus. Second, we found nine replacements where a sequence specific to V583 was substituted by a sequence specific to OG1RF. For example, the iol operon of OG1RF replaces a possible prophage and the vanB transposon in V583. Finally, we found 16 regions that were present in V583 but missing from OG1RF, including the proposed pathogenicity island, several probable prophages, and the cpsCDEFGHIJK capsular polysaccharide operon. OG1RF was more rapidly but less frequently lethal than V583 in the mouse peritonitis model and considerably outcompeted V583 in a murine model of urinary tract infections. CONCLUSION: E. faecalis OG1RF carries a number of unique loci compared to V583, but the almost complete lack of mobile genetic elements demonstrates that this is not a defining feature of the species. Additionally, OG1RF's effects in experimental models suggest that mediators of virulence may be diverse between different E. faecalis strains and that virulence is not dependent on the presence of mobile genetic elements.
Keywords: Animals; Anti-Bacterial Agents; Bacterial Proteins; Biofilms; DNA, Bacterial; Drug Resistance, Bacterial; Enterococcus faecalis; Fusidic Acid; Genetic Variation; Genome, Bacterial; Genomics; Interspersed Repetitive Sequences; Membrane Proteins; Mice; Operon; Repetitive Sequences, Nucleic Acid; Rifampin; Sequence Homology, Nucleic Acid

Mouse let-7 miRNA populations exhibit RNA editing that is constrained in the 5'-seed/ cleavage/anchor regions and stabilize predicted mmu-let-7a:mRNA duplexes. - Reid, Jeffrey G; Nagaraja, Ankur K; Lynn, Francis C; Drabek, Rafal B; Donna M Muzny; Shaw, Chad A; Weiss, Michelle K; Naghavi, Arash O; Khan, Mahjabeen; Zhu, Huifeng; Tennakoon, Jayantha; Gunaratne, Gemunu H; et al. (Genome Res, 2008)
Massively parallel sequencing of millions of < 30-nt RNAs expressed in mouse ovary, embryonic pancreas (E14.5), and insulin-secreting beta-cells (betaTC-3) reveals that approximately 50% of the mature miRNAs representing mostly the mmu-let-7 family display internal insertion/deletions and substitutions when compared to precursor miRNA and the mouse genome reference sequences. Approximately, 12%-20% of species associated with mmu-let-7 populations exhibit sequence discrepancies that are dramatically reduced in nucleotides 3-7 (5'-seed) and 10-15 (cleavage and anchor sites). This observation is inconsistent with sequencing error and leads us to propose that the changes arise predominantly from post-transcriptional RNA-editing activity operating on miRNA:target mRNA complexes. Internal nucleotide modifications are most enriched at the ninth nucleotide position. A common ninth base edit of U-to-G results in a significant increase in stability of down-regulated let-7a targets in inhibin-deficient mice (Inha-/-). An excess of U-insertions (14.8%) over U-deletions (1.5%) and the presence of cleaved intermediates suggest that a mammalian TUTase (terminal uridylyl transferase) mediated dUTP-dependent U-insertion/U-deletion cycle may be a possible mechanism. We speculate that mRNA target site-directed editing of mmu-let-7a duplex-bulges stabilizes "loose" miRNA:mRNA target associations and functions to expand the target repertoire and/or enhance mRNA decay over translational repression. Our results also demonstrate that the systematic study of sequence variation within specific RNA classes in a given cell type from millions of sequences generated by next-generation sequencing (NGS) technologies ("intranomics") can be used broadly to infer functional constraints on specific parts of completely uncharacterized RNAs.
Keywords: Animals; Base Sequence; Cells, Cultured; Deoxyuracil Nucleotides; Embryo, Mammalian; Female; Mice; MicroRNAs; Molecular Sequence Data; Nucleic Acid Conformation; RNA Editing; RNA Nucleotidyltransferases; RNA Stability; RNA, Messenger; RNA, Small Untranslated

Novel microRNA candidates and miRNA-mRNA pairs in embryonic stem (ES) cells. - Gu, Peili; Reid, Jeffrey G; Gao, Xiaolian; Shaw, Chad A; Creighton, Chad; Tran, Peter L; Zhou, Xiaochuan; Drabek, Rafal B; Steffen, David L; Hoang, David M; Weiss, Michelle K; Naghavi, Arash O; et al. (PLoS One, 2008)
BACKGROUND: MicroRNAS (miRNAS: a class of short non-coding RNAs) are emerging as important agents of post transcriptional gene regulation and integral components of gene networks. MiRNAs have been strongly linked to stem cells, which have a remarkable dual role in development. They can either continuously replenish themselves (self-renewal), or differentiate into cells that execute a limited number of specific actions (pluripotence). METHODOLOGY/PRINCIPAL FINDINGS: In order to identify novel miRNAs from narrow windows of development we carried out an in silico search for micro-conserved elements (MCE) in adult tissue progenitor transcript sequences. A plethora of previously unknown miRNA candidates were revealed including 545 small RNAs that are enriched in embryonic stem (ES) cells over adult cells. Approximately 20% of these novel candidates are down-regulated in ES (Dicer(-/-)) ES cells that are impaired in miRNA maturation. The ES-enriched miRNA candidates exhibit distinct and opposite expression trends from mmu-mirs (an abundant class in adult tissues) during retinoic acid (RA)-induced ES cell differentiation. Significant perturbation of trends is found in both miRNAs and novel candidates in ES (GCNF(-/-)) cells, which display loss of repression of pluripotence genes upon differentiation. CONCLUSION/SIGNIFICANCE: Combining expression profile information with miRNA target prediction, we identified miRNA-mRNA pairs that correlate with ES cell pluripotence and differentiation. Perturbation of these pairs in the ES (GCNF(-/-)) mutant suggests a role for miRNAs in the core regulatory networks underlying ES cell self-renewal, pluripotence and differentiation.
Keywords: Algorithms; Animals; Blotting, Northern; Cell Differentiation; Computational Biology; Conserved Sequence; Embryonic Stem Cells; False Positive Reactions; Humans; MicroRNAs; Models, Biological; Models, Genetic; RNA, Messenger; Time Factors; Tretinoin

PDX-1 acts as a potential molecular target for treatment of human pancreatic cancer. - Liu, Shihe; Ballian, Nikiforos; Belaguli, Narasimhaswamy S; Patel, Sanjeet; Li, Min; Templeton, Nancy Smyth; Marie-Claude Gingras; Richard A Gibbs; Fisher, William; Brunicardi, F Charles (Pancreas, 2008)
OBJECTIVES: The purpose of this study was to investigate whether pancreatic and duodenal homeobox factor 1 (PDX-1) could serve as a potential molecular target for the treatment of pancreatic cancer. METHODS: Cell proliferation, invasion capacity, and protein levels of cell cycle mediators were determined in human pancreatic cancer cells transfected with mouse PDX-1 (mPDX-1) alone or with mPDX-1 short hairpin RNA (shRNA) and/or human PDX-1 shRNA (huPDX-1 shRNA). Tumor cell growth and apoptosis were also evaluated in vivo in PANC-1 tumor-bearing severe combined immunodeficient mice receiving multiple treatments of intravenous liposomal huPDX-1 shRNA. RESULTS: mPDX-1 overexpression resulted in the significant increase of cell proliferation and invasion in MIA PaCa2, but not PANC-1 cells. This effect was blocked by knocking down mPDX-1 expression with mPDX-1 shRNA. Silencing of huPDX-1 expression in PANC-1 cells inhibited cell proliferation in vitro and suppressed tumor growth in vivo which was associated with increased tumor cell apoptosis. PDX-1 overexpression resulted in dysregulation of the cell cycle with up-regulation of cyclin D, cyclin E, and Cdk2 and down-regulation of p27. CONCLUSIONS: PDX-1 regulates cell proliferation and invasion in human pancreatic cancer cells. Down-regulation of PDX-1 expression inhibits pancreatic cancer cell growth in vitro and in vivo, implying its use as a potential therapeutic target for the treatment of pancreatic cancer.
Keywords: Animals; Base Sequence; Biomarkers, Tumor; Cell Line, Tumor; Cell Proliferation; Homeodomain Proteins; Humans; Islets of Langerhans; Male; Mice; Mice, SCID; Molecular Sequence Data; Neoplasm Invasiveness; Neoplasm Transplantation; Pancreatic Neoplasms; RNA Interference; RNA, Small Interfering; Trans-Activators; Transfection; Transplantation, Heterologous

Pulmonary alveolar proteinosis caused by deletion of the GM-CSFRalpha gene in the X chromosome pseudoautosomal region 1. - Martinez-Moczygemba, Margarita; Doan, Minh L; Elidemir, Okan; Fan, Leland L; Cheung, Sau Wai; Lei, Jonathan T; Moore, James P; Tavana, Ghamartaj; Lewis, Lora R; Zhu, Yiming; Donna M Muzny; Richard A Gibbs; et al. (J Exp Med, 2008)
Pulmonary alveolar proteinosis (PAP) is a rare lung disorder in which surfactant-derived lipoproteins accumulate excessively within pulmonary alveoli, causing severe respiratory distress. The importance of granulocyte/macrophage colony-stimulating factor (GM-CSF) in the pathogenesis of PAP has been confirmed in humans and mice, wherein GM-CSF signaling is required for pulmonary alveolar macrophage catabolism of surfactant. PAP is caused by disruption of GM-CSF signaling in these cells, and is usually caused by neutralizing autoantibodies to GM-CSF or is secondary to other underlying diseases. Rarely, genetic defects in surfactant proteins or the common beta chain for the GM-CSF receptor (GM-CSFR) are causal. Using a combination of cellular, molecular, and genomic approaches, we provide the first evidence that PAP can result from a genetic deficiency of the GM-CSFR alpha chain, encoded in the X-chromosome pseudoautosomal region 1.
Keywords: Animals; CD11b Antigen; Child, Preschool; Chromosomes, Human, X; Exons; Female; Genotype; Granulocyte-Macrophage Colony-Stimulating Factor; Humans; In Situ Hybridization, Fluorescence; Karyotyping; Male; Mice; Monocytes; Pulmonary Alveolar Proteinosis; Pulmonary Surfactants; Receptors, Granulocyte-Macrophage Colony-Stimulating Factor; Signal Transduction; Turner Syndrome

Rats in the genomic era. - Kim C Worley; Weinstock, G M; Richard A Gibbs (Physiol Genomics, 2008)
The rat genome project and the resources that it has generated are transforming the translation of rat biology to human medicine. The rat genome was sequenced to a high quality "draft," the structure and location of the genes were predicted, and a global assessment was published (Gibbs RA et al., Nature 428: 493-521, 2004). Since that time, researchers have made use of the genome sequence and annotations and related resources. We take this opportunity to review the currently available rat genome resources and to discuss the progress and future plans for the rat genome.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Female; Genome; Genomic Library; Genomics; Humans; Mice; National Heart, Lung, and Blood Institute (U.S.); National Human Genome Research Institute (U.S.); Polymorphism, Single Nucleotide; Rats; United States

Somatic mutations affect key pathways in lung adenocarcinoma. - Ding, Li; Getz, Gad; Wheeler, David A; Mardis, Elaine R; McLellan, Michael D; Cibulskis, Kristian; Sougnez, Carrie; Greulich, Heidi; Donna M Muzny; Morgan, Margaret B; Fulton, Lucinda; Fulton, Robert S; et al. (Nature, 2008)
Determining the genetic basis of cancer requires comprehensive analyses of large collections of histopathologically well-classified primary tumours. Here we report the results of a collaborative study to discover somatic mutations in 188 human lung adenocarcinomas. DNA sequencing of 623 genes with known or potential relationships to cancer revealed more than 1,000 somatic mutations across the samples. Our analysis identified 26 genes that are mutated at significantly high frequencies and thus are probably involved in carcinogenesis. The frequently mutated genes include tyrosine kinases, among them the EGFR homologue ERBB4; multiple ephrin receptor genes, notably EPHA3; vascular endothelial growth factor receptor KDR; and NTRK genes. These data provide evidence of somatic mutations in primary lung adenocarcinoma for several tumour suppressor genes involved in other cancers--including NF1, APC, RB1 and ATM--and for sequence changes in PTPRD as well as the frequently deleted gene LRP1B. The observed mutational profiles correlate with clinical features, smoking status and DNA repair defects. These results are reinforced by data integration including single nucleotide polymorphism array and gene expression array. Our findings shed further light on several important signalling pathways involved in lung adenocarcinoma, and suggest new molecular targets for treatment.
Keywords: Adenocarcinoma, Bronchiolo-Alveolar; Female; Gene Dosage; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Humans; Lung Neoplasms; Male; Mutation; Proto-Oncogenes

What everybody should know about the rat genome and its online resources. - Twigger, Simon N; Pruitt, Kim D; Fernandez-Suarez, Xose M; Karolchik, Donna; Worley, Kim C; Maglott, Donna R; Brown, Garth; Weinstock, George; Richard A Gibbs; Kent, Jim; Birney, Ewan; Jacob, Howard J (Nat Genet, 2008)
It has been four years since the original publication of the draft sequence of the rat genome. Five groups are now working together to assemble, annotate and release an updated version of the rat genome. As the prevailing model for physiology, complex disease and pharmacological studies, there is an acute need for the rat's genomic resources to keep pace with the rat's prominence in the laboratory. In this commentary, we describe the current status of the rat genome sequence and the plans for its impending 'upgrade'. We then cover the key online resources providing access to the rat genome, including the new SNP views at Ensembl, the RefSeq and Genes databases at the US National Center for Biotechnology Information, Genome Browser at the University of California Santa Cruz and the disease portals for cardiovascular disease and obesity at the Rat Genome Database.
Keywords: Animals; Computational Biology; Databases, Genetic; Disease Models, Animal; Genetic Diseases, Inborn; Genetic Variation; Genome; Genomics; Haplotypes; Humans; Internet; Polymorphism, Single Nucleotide; Rats; Rats, Mutant Strains; Sequence Analysis, DNA

28-way vertebrate alignment and conservation track in the UCSC Genome Browser. - Miller, Webb; Rosenbloom, Kate; Hardison, Ross C; Hou, Minmei; Taylor, James; Raney, Brian; Burhans, Richard; King, David C; Baertsch, Robert; Blankenberg, Daniel; Kosakovsky Pond, Sergei L; Nekrutenko, Anton; et al. (Genome Res, 2007)
This article describes a set of alignments of 28 vertebrate genome sequences that is provided by the UCSC Genome Browser. The alignments can be viewed on the Human Genome Browser (March 2006 assembly) at http://genome.ucsc.edu, downloaded in bulk by anonymous FTP from http://hgdownload.cse.ucsc.edu/goldenPath/hg18/multiz28way, or analyzed with the Galaxy server at http://g2.bx.psu.edu. This article illustrates the power of this resource for exploring vertebrate and mammalian evolution, using three examples. First, we present several vignettes involving insertions and deletions within protein-coding regions, including a look at some human-specific indels. Then we study the extent to which start codons and stop codons in the human sequence are conserved in other species, showing that start codons are in general more poorly conserved than stop codons. Finally, an investigation of the phylogenetic depth of conservation for several classes of functional elements in the human genome reveals striking differences in the rates and modes of decay in alignability. Each functional class has a distinctive period of stringent constraint, followed by decays that allow (for the case of regulatory regions) or reject (for coding regions and ultraconserved elements) insertions and deletions.
Keywords: Animals; Base Sequence; Cats; Cattle; Codon, Initiator; Codon, Terminator; Conserved Sequence; Databases, Genetic; Dogs; Genome, Human; Guinea Pigs; Humans; Mice; Molecular Sequence Data; Mutagenesis, Insertional; Rabbits; Rats; Sequence Alignment; Sequence Deletion

Analyses of deep mammalian sequence alignments and constraint predictions for 1% of the human genome. - Margulies, Elliott H; Cooper, Gregory M; Asimenos, George; Thomas, Daryl J; Dewey, Colin N; Siepel, Adam; Birney, Ewan; Keefe, Damian; Schwartz, Ariel S; Hou, Minmei; Taylor, James; Nikolaev, Sergey; et al. (Genome Res, 2007)
A key component of the ongoing ENCODE project involves rigorous comparative sequence analyses for the initially targeted 1% of the human genome. Here, we present orthologous sequence generation, alignment, and evolutionary constraint analyses of 23 mammalian species for all ENCODE targets. Alignments were generated using four different methods; comparisons of these methods reveal large-scale consistency but substantial differences in terms of small genomic rearrangements, sensitivity (sequence coverage), and specificity (alignment accuracy). We describe the quantitative and qualitative trade-offs concomitant with alignment method choice and the levels of technical error that need to be accounted for in applications that require multisequence alignments. Using the generated alignments, we identified constrained regions using three different methods. While the different constraint-detecting methods are in general agreement, there are important discrepancies relating to both the underlying alignments and the specific algorithms. However, by integrating the results across the alignments and constraint-detecting methods, we produced constraint annotations that were found to be robust based on multiple independent measures. Analyses of these annotations illustrate that most classes of experimentally annotated functional elements are enriched for constrained sequences; however, large portions of each class (with the exception of protein-coding sequences) do not overlap constrained regions. The latter elements might not be under primary sequence constraint, might not be constrained across all mammals, or might have expendable molecular functions. Conversely, 40% of the constrained sequences do not overlap any of the functional elements that have been experimentally identified. Together, these findings demonstrate and quantify how many genomic functional elements await basic molecular characterization.
Keywords: Animals; Evolution, Molecular; Genome, Human; Human Genome Project; Humans; Mammals; Open Reading Frames; Phylogeny; Sequence Alignment

Characterizing the cancer genome in lung adenocarcinoma. - Weir, Barbara A; Woo, Michele S; Getz, Gad; Perner, Sven; Ding, Li; Beroukhim, Rameen; Lin, William M; Province, Michael A; Kraja, Aldi; Johnson, Laura A; Shah, Kinjal; Sato, Mitsuo; et al. (Nature, 2007)
Somatic alterations in cellular DNA underlie almost all human cancers. The prospect of targeted therapies and the development of high-resolution, genome-wide approaches are now spurring systematic efforts to characterize cancer genomes. Here we report a large-scale project to characterize copy-number alterations in primary lung adenocarcinomas. By analysis of a large collection of tumours (n = 371) using dense single nucleotide polymorphism arrays, we identify a total of 57 significantly recurrent events. We find that 26 of 39 autosomal chromosome arms show consistent large-scale copy-number gain or loss, of which only a handful have been linked to a specific gene. We also identify 31 recurrent focal events, including 24 amplifications and 7 homozygous deletions. Only six of these focal events are currently associated with known mutations in lung carcinomas. The most common event, amplification of chromosome 14q13.3, is found in approximately 12% of samples. On the basis of genomic and functional analyses, we identify NKX2-1 (NK2 homeobox 1, also called TITF1), which lies in the minimal 14q13.3 amplification interval and encodes a lineage-specific transcription factor, as a novel candidate proto-oncogene involved in a significant fraction of lung adenocarcinomas. More generally, our results indicate that many of the genes that are involved in lung adenocarcinoma remain to be discovered.
Keywords: Adenocarcinoma; Cell Line, Tumor; Chromosome Deletion; Chromosomes, Human, Pair 14; Gene Amplification; Genome, Human; Genomics; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Loss of Heterozygosity; Lung Neoplasms; Neoplasms; Nuclear Proteins; Polymorphism, Single Nucleotide; Proto-Oncogene Mas; RNA Interference; Thyroid Nuclear Factor 1; Transcription Factors

Demographic histories and patterns of linkage disequilibrium in Chinese and Indian rhesus macaques. - Hernandez, Ryan D; Hubisz, Melissa J; David A Wheeler; Smith, David G; Ferguson, Betsy; Jeffrey Rogers; Nazareth, Lynne; Indap, Amit; Bourquin, Traci; McPherson, John; Donna M Muzny; Richard A Gibbs; et al. (Science, 2007)
To understand the demographic history of rhesus macaques (Macaca mulatta) and document the extent of linkage disequilibrium (LD) in the genome, we partially resequenced five Encyclopedia of DNA Elements regions in 9 Chinese and 38 captive-born Indian rhesus macaques. Population genetic analyses of the 1467 single-nucleotide polymorphisms discovered suggest that the two populations separated about 162,000 years ago, with the Chinese population tripling in size since then and the Indian population eventually shrinking by a factor of four. Using coalescent simulations, we confirmed that these inferred demographic events explain a much faster decay of LD in Chinese (r(2) approximately 0.15 at 10 kilobases) versus Indian (r(2) approximately 0.52 at 10 kilobases) macaque populations.
Keywords: Animals; China; Demography; DNA, Mitochondrial; Genetics, Medical; Humans; India; Linkage Disequilibrium; Macaca mulatta; Polymorphism, Single Nucleotide

Direct selection of human genomic loci by microarray hybridization. - Albert, Thomas J; Molla, Michael N; Donna M Muzny; Nazareth, Lynne; Wheeler, David; Song, Xingzhi; Richmond, Todd A; Middle, Chris M; Rodesch, Matthew J; Packard, Charles J; Weinstock, George M; Richard A Gibbs (Nat Methods, 2007)
We applied high-density microarrays to the enrichment of specific sequences from the human genome for high-throughput sequencing. After capture of 6,726 approximately 500-base 'exon' segments, and of 'locus-specific' regions ranging in size from 200 kb to 5 Mb, followed by sequencing on a 454 Life Sciences FLX sequencer, most sequence reads represented selection targets. These direct selection methods supersede multiplex PCR for the large-scale analysis of genomic regions.
Keywords: BRCA1 Protein; Cell Line, Tumor; Gene Library; Genome, Human; Humans; Nucleic Acid Hybridization; Oligodeoxyribonucleotides; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Evolutionary and biomedical insights from the rhesus macaque genome. - Richard A Gibbs; Jeffrey Rogers; Katze, Michael G; Bumgarner, Roger; Weinstock, George M; Mardis, Elaine R; Remington, Karin A; Strausberg, Robert L; Venter, J Craig; Wilson, Richard K; Batzer, Mark A; Bustamante, Carlos D; et al. (Science, 2007)
The rhesus macaque (Macaca mulatta) is an abundant primate species that diverged from the ancestors of Homo sapiens about 25 million years ago. Because they are genetically and physiologically similar to humans, rhesus monkeys are the most widely used nonhuman primate in basic and applied biomedical research. We determined the genome sequence of an Indian-origin Macaca mulatta female and compared the data with chimpanzees and humans to reveal the structure of ancestral primate genomes and to identify evidence for positive selection and lineage-specific expansions and contractions of gene families. A comparison of sequences from individual animals was used to investigate their underlying genetic diversity. The complete description of the macaque genome blueprint enhances the utility of this animal model for biomedical research and improves our understanding of the basic biology of the species.
Keywords: Animals; Biomedical Research; Evolution, Molecular; Female; Gene Duplication; Gene Rearrangement; Genetic Diseases, Inborn; Genetic Variation; Genome; Humans; Macaca mulatta; Male; Multigene Family; Mutation; Pan troglodytes; Sequence Analysis, DNA; Species Specificity

The genome of Apis mellifera: dialog between linkage mapping and sequence assembly. - Solignac, Michel; Zhang, Lan; Mougel, Florence; Li, Bingshan; Vautrin, Dominique; Monnerot, Monique; Cornuet, Jean-Marie; Worley, Kim C; Weinstock, George M; Richard A Gibbs (Genome Biol, 2007)
Two independent genome projects for the honey bee, a microsatellite linkage map and a genome sequence assembly, interactively produced an almost complete organization of the euchromatic genome. Assembly 4.0 now includes 626 scaffolds that were ordered and oriented into chromosomes according to the framework provided by the third-generation linkage map (AmelMap3). Each construct was used to control the quality of the other. The co-linearity of markers in the sequence and the map is almost perfect and argues in favor of the high quality of both.
Keywords: Animals; Base Sequence; Bees; Chromosome Mapping; Genome; Microsatellite Repeats

Genome-wide detection and characterization of positive selection in human populations. - Sabeti, Pardis C; Varilly, Patrick; Fry, Ben; Lohmueller, Jason; Hostetter, Elizabeth; Cotsapas, Chris; Xie, Xiaohui; Byrne, Elizabeth H; McCarroll, Steven A; Gaudet, Rachelle; Schaffner, Stephen F; Lander, Eric S; et al. (Nature, 2007)
With the advent of dense maps of human genetic variation, it is now possible to detect positive natural selection across the human genome. Here we report an analysis of over 3 million polymorphisms from the International HapMap Project Phase 2 (HapMap2). We used 'long-range haplotype' methods, which were developed to identify alleles segregating in a population that have undergone recent selection, and we also developed new methods that are based on cross-population comparisons to discover alleles that have swept to near-fixation within a population. The analysis reveals more than 300 strong candidate regions. Focusing on the strongest 22 regions, we develop a heuristic for scrutinizing these regions to identify candidate targets of selection. In a complementary analysis, we identify 26 non-synonymous, coding, single nucleotide polymorphisms showing regional evidence of positive selection. Examination of these candidates highlights three cases in which two genes in a common biological process have apparently undergone positive selection in the same population:LARGE and DMD, both related to infection by the Lassa virus, in West Africa;SLC24A5 and SLC45A2, both involved in skin pigmentation, in Europe; and EDAR and EDA2R, both involved in development of hair follicles, in Asia.
Keywords: Antiporters; Edar Receptor; Gene Frequency; Genetics, Population; Genome, Human; Geography; Haplotypes; Humans; Models, Molecular; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Selection, Genetic

Identification and analysis of functional elements in 1% of the human genome by the ENCODE pilot project. - Birney, Ewan; Stamatoyannopoulos, John A; Dutta, Anindya; Guigó, Roderic; Gingeras, Thomas R; Margulies, Elliott H; Weng, Zhiping; Snyder, Michael; Dermitzakis, Emmanouil T; Thurman, Robert E; Kuehn, Michael S; Taylor, Christopher M; et al. (Nature, 2007)
We report the generation and analysis of functional data from multiple, diverse experiments performed on a targeted 1% of the human genome as part of the pilot phase of the ENCODE Project. These data have been further integrated and augmented by a number of evolutionary and computational analyses. Together, our results advance the collective knowledge about human genome function in several major areas. First, our studies provide convincing evidence that the genome is pervasively transcribed, such that the majority of its bases can be found in primary transcripts, including non-protein-coding transcripts, and those that extensively overlap one another. Second, systematic examination of transcriptional regulation has yielded new understanding about transcription start sites, including their relationship to specific regulatory sequences and features of chromatin accessibility and histone modification. Third, a more sophisticated view of chromatin structure has emerged, including its inter-relationship with DNA replication and transcriptional regulation. Finally, integration of these new sources of information, in particular with respect to mammalian evolution based on inter- and intra-species sequence comparisons, has yielded new mechanistic and evolutionary insights concerning the functional landscape of the human genome. Together, these studies are defining a path for pursuit of a more comprehensive characterization of human genome function.
Keywords: Chromatin; Chromatin Immunoprecipitation; Conserved Sequence; DNA Replication; Evolution, Molecular; Exons; Genetic Variation; Genome, Human; Genomics; Heterozygote; Histones; Humans; Pilot Projects; Protein Binding; Regulatory Sequences, Nucleic Acid; RNA, Messenger; RNA, Untranslated; Transcription Factors; Transcription Initiation Site; Transcription, Genetic

A second generation human haplotype map of over 3.1 million SNPs. - Frazer, Kelly A; Ballinger, Dennis G; Cox, David R; Hinds, David A; Stuve, Laura L; Richard A Gibbs; Belmont, John W; Boudreau, Andrew; Hardenbol, Paul; Leal, Suzanne M; Pasternak, Shiran; Wheeler, David A; et al. (Nature, 2007)
We describe the Phase II HapMap, which characterizes over 3.1 million human single nucleotide polymorphisms (SNPs) genotyped in 270 individuals from four geographically diverse populations and includes 25-35% of common SNP variation in the populations surveyed. The map is estimated to capture untyped common variation with an average maximum r2 of between 0.9 and 0.96 depending on population. We demonstrate that the current generation of commercial genome-wide genotyping products captures common Phase II SNPs with an average maximum r2 of up to 0.8 in African and up to 0.95 in non-African populations, and that potential gains in power in association studies can be obtained through imputation. These data also reveal novel aspects of the structure of linkage disequilibrium. We show that 10-30% of pairs of individuals within a population share at least one region of extended genetic identity arising from recent ancestry and that up to 1% of all common variants are untaggable, primarily because they lie within recombination hotspots. We show that recombination rates vary systematically around genes and between genes of different function. Finally, we demonstrate increased differentiation at non-synonymous, compared to synonymous, SNPs, resulting from systematic differences in the strength or efficacy of natural selection between populations.
Keywords: Female; Haplotypes; Homozygote; Humans; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide; Racial Groups; Recombination, Genetic; Selection, Genetic

Sequence variation in DOCK9 and heterogeneity in bipolar disorder. - Detera-Wadleigh, Sevilla D; Liu, Chun-yu; Maheshwari, Manjula; Cardona, Imer; Corona, Winston; Akula, Nirmala; Steele, C J M; Badner, Judith A; Kundu, Mukta; Kassem, Layla; Potash, James B; Richard A Gibbs; et al. (Psychiatr Genet, 2007)
BACKGROUND: Linkage of bipolar disorder to a broad region on chromosome 13q has been supported in several studies including a meta-analysis on genome scans. Subsequent reports have shown that variations in the DAOA (G72) locus on 13q33 display association with bipolar disorder but these may not account for all of the linkage evidence in the region. OBJECTIVE: To identify additional susceptibility loci on 13q32-q33 by linkage disequilibrium mapping and explore the impact of phenotypic heterogeneity on association. METHODS: In the initial phase, 98 single nucleotide polymorphism (SNPs) located on 13q32-q33 were genotyped on 285 probands with bipolar disorder and their parents were drawn from families in the NIMH Genetics Initiative consortium for bipolar disorder (NIMH1-4) and two other series. Fine scale mapping using one family series (NIMH1-2) as the test sample was targeted on a gene that displayed the highest evidence of association. A secondary analysis of familial component phenotypes of bipolar disorder was conducted. RESULTS: Three of seven SNPs in DOCK9, a gene that encodes an activator of the Rho-GTPase Cdc42, showed significant excess allelic transmission (P=0.0477-0.00067). Fine scale mapping on DOCK9 yielded evidence of association at nine SNPs in the gene (P=0.02-0.006). Follow-up tests detected excess transmission of the same allele of rs1340 in two out of three other sets of families. The association signals were largely attributable to maternally transmitted alleles (rs1927568: P=0.000083; odds ratio=3.778). A secondary analysis of familial component phenotypes of bipolar disorder detected significant association across multiple DOCK9 markers for racing thoughts, psychosis, delusion during mania and course of illness indicators. CONCLUSION: These results suggest that DOCK9 contributes to both risk and increased illness severity in bipolar disorder. We found evidence for the effect of phenotypic heterogeneity on association. To our knowledge this is the first report to implicate DOCK9 or the Rho-GTPase pathway in the etiology of bipolar disorder.
Keywords: Bipolar Disorder; Family; Female; Genetic Predisposition to Disease; Genetic Variation; Guanine Nucleotide Exchange Factors; Humans; Linkage Disequilibrium; Male; Phenotype; Polymorphism, Single Nucleotide; Severity of Illness Index

Community annotation: procedures, protocols, and supporting tools. - Elsik, Christine G; Worley, Kim C; Zhang, Lan; Milshina, Natalia V; Jiang, Huaiyang; Reese, Justin T; Childs, Kevin L; Venkatraman, Anand; Dickens, C Michael; Weinstock, George M; Richard A Gibbs (Genome Res, 2006)
Investigators at the Baylor College of Medicine Human Genome Sequencing Center (BCM-HGSC) and BeeBase organized a community-wide effort to manually annotate the honey bee (Apis mellifera) genome. Although various strategies for manual annotation have been used in the past, the value of dispersed community annotation has not yet been demonstrated. Here we make a case for the merit of dispersed community annotation. We present annotation procedures, standard protocols, and tools used for sequence analysis, data submission, and data management. We also report lessons learned from this dispersed community annotation effort for a metazoan genome.
Keywords: Animals; Bees; Databases, Genetic; Genome, Human; Genomics; Humans; Models, Genetic; Molecular Sequence Data; Sequence Analysis

Comparative analysis of the bovine MHC class IIb sequence identifies inversion breakpoints and three unexpected genes. - Childers, C P; Newkirk, H L; Honeycutt, D A; Ramlachan, N; Donna M Muzny; Sodergren, E; Richard A Gibbs; Weinstock, G M; Womack, J E; Skow, L C (Anim Genet, 2006)
The bovine major histocompatibility complex (MHC) or BoLA is organized differently from typical mammalian MHCs in that a large portion of the class II region, called class IIb, has been transposed to a position near the centromere on bovine chromosome 23. Gene mapping indicated that the rearrangement resulted from a single inversion, but the boundaries and gene content of the inverted segment have not been fully determined. Here, we report the genomic sequence of BoLA IIb. Comparative sequence analysis with the human MHC revealed that the proximal inversion breakpoint occurred approximately 2.5 kb from the 3' end of the glutamate-cysteine ligase, catalytic subunit (GCLC) locus and that the distal breakpoint occurred about 2 kb from the 5' end from a divergent class IIDRbeta-like sequence designated DSB. Gene content, order and orientation of BoLA IIb are consistent with the single inversion hypothesis when compared with the corresponding region of the human class II MHC (HLA class II). Differences with HLA include the presence of a single histone H2B gene located between the proteasome subunit, beta type, 9 (PSMB9) and DMB loci and a duplicated TAP2 with a variant splice site. BoLA IIb spans approximately 450 kb DNA, with 20 apparently intact genes and no obvious pseudogenes. The region contains 227 simple sequence repeats (SSRs) and approximately 167 kb of retroviral-related repetitive DNA. Nineteen of the 20 genes identified in silico are supported by bovine EST data indicating that the functional gene content of BoLA IIb has not been diminished because it has been transposed from the remainder of BoLA genes.
Keywords: Animals; Cattle; Chromosome Inversion; Chromosomes, Mammalian; Contig Mapping; Evolution, Molecular; Genes, MHC Class II; Histones; Humans; Molecular Sequence Data; Sequence Analysis, DNA

The DNA sequence, annotation and analysis of human chromosome 3. - Donna M Muzny; Steven E Scherer; Kaul, Rajinder; Wang, Jing; Yu, Jun; Sudbrak, Ralf; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; et al. (Nature, 2006)
After the completion of a draft human genome sequence, the International Human Genome Sequencing Consortium has proceeded to finish and annotate each of the 24 chromosomes comprising the human genome. Here we describe the sequencing and analysis of human chromosome 3, one of the largest human chromosomes. Chromosome 3 comprises just four contigs, one of which currently represents the longest unbroken stretch of finished DNA sequence known so far. The chromosome is remarkable in having the lowest rate of segmental duplication in the genome. It also includes a chemokine receptor gene cluster as well as numerous loci involved in multiple human cancers such as the gene encoding FHIT, which contains the most common constitutive fragile site in the genome, FRA3B. Using genomic sequence from chimpanzee and rhesus macaque, we were able to characterize the breakpoints defining a large pericentric inversion that occurred some time after the split of Homininae from Ponginae, and propose an evolutionary history of the inversion.
Keywords: Animals; Base Sequence; Chromosome Breakage; Chromosome Inversion; Chromosomes, Human, Pair 3; Contig Mapping; CpG Islands; DNA, Complementary; Evolution, Molecular; Expressed Sequence Tags; Human Genome Project; Humans; Macaca mulatta; Molecular Sequence Data; Pan troglodytes; Sequence Analysis, DNA; Synteny

The finished DNA sequence of human chromosome 12. - Scherer, Steven E; Donna M Muzny; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; Gunaratne, Preethi; R. Alan Harris; Hawes, Alicia C; Hernandez, Judith; et al. (Nature, 2006)
Human chromosome 12 contains more than 1,400 coding genes and 487 loci that have been directly implicated in human disease. The q arm of chromosome 12 contains one of the largest blocks of linkage disequilibrium found in the human genome. Here we present the finished sequence of human chromosome 12, which has been finished to high quality and spans approximately 132 megabases, representing approximately 4.5% of the human genome. Alignment of the human chromosome 12 sequence across vertebrates reveals the origin of individual segments in chicken, and a unique history of rearrangement through rodent and primate lineages. The rate of base substitutions in recent evolutionary history shows an overall slowing in hominids compared with primates and rodents.
Keywords: Animals; Base Composition; Chromosomes, Human, Pair 12; CpG Islands; Evolution, Molecular; Expressed Sequence Tags; Genes; Humans; Linkage Disequilibrium; Microsatellite Repeats; Molecular Sequence Data; Mutagenesis, Insertional; Pan troglodytes; Sequence Analysis, DNA; Sequence Deletion; Short Interspersed Nucleotide Elements; Synteny

Genetics. No longer de-identified. - McGuire, Amy L; Richard A Gibbs (Science, 2006)
Keywords: Access to Information; Databases, Genetic; Ethics Committees, Research; Genetic Privacy; Genetic Research; Health Insurance Portability and Accountability Act; Humans; Information Dissemination; Informed Consent; Polymorphism, Single Nucleotide; Research Subjects; Sequence Analysis, DNA; United States

The genome of the sea urchin Strongylocentrotus purpuratus. - Sodergren, Erica; Weinstock, George M; Davidson, Eric H; Cameron, R Andrew; Richard A Gibbs; Angerer, Robert C; Angerer, Lynne M; Arnone, Maria Ina; Burgess, David R; Burke, Robert D; Coffman, James A; Dean, Michael; et al. (Science, 2006)
We report the sequence and analysis of the 814-megabase genome of the sea urchin Strongylocentrotus purpuratus, a model for developmental and systems biology. The sequencing strategy combined whole-genome shotgun and bacterial artificial chromosome (BAC) sequences. This use of BAC clones, aided by a pooling strategy, overcame difficulties associated with high heterozygosity of the genome. The genome encodes about 23,300 genes, including many previously thought to be vertebrate innovations or known only outside the deuterostomes. This echinoderm genome provides an evolutionary outgroup for the chordates and yields insights into the evolution of deuterostomes.
Keywords: Animals; Calcification, Physiologic; Cell Adhesion Molecules; Complement Activation; Computational Biology; Embryonic Development; Evolution, Molecular; Gene Expression Regulation, Developmental; Genes; Genome; Immunity, Innate; Immunologic Factors; Male; Nervous System Physiological Phenomena; Proteins; Sequence Analysis, DNA; Signal Transduction; Strongylocentrotus purpuratus; Transcription Factors

Meeting the growing demands of genetic research. - McGuire, Amy L; Richard A Gibbs (J Law Med Ethics, 2006)
Keywords: Databases, Genetic; Genetic Research; Genomics; Health Insurance Portability and Accountability Act; Humans; Informed Consent; United States

Phylogenomic analysis reveals bees and wasps (Hymenoptera) at the base of the radiation of Holometabolous insects. - Savard, Joël; Tautz, Diethard; Richards, Stephen; Weinstock, George M; Richard A Gibbs; Werren, John H; Tettelin, Hervé; Lercher, Martin J (Genome Res, 2006)
Comparative studies require knowledge of the evolutionary relationships between taxa. However, neither morphological nor paleontological data have been able to unequivocally resolve the major groups of holometabolous insects so far. Here, we utilize emerging genome projects to assemble and analyze a data set of 185 nuclear genes, resulting in a fully resolved phylogeny of the major insect model species. Contrary to the most widely accepted phylogenetic hypothesis, bees and wasps (Hymenoptera) are basal to the other major holometabolous orders, beetles (Coleoptera), moths (Lepidoptera), and flies (Diptera). We validate our results by meticulous examination of potential confounding factors. Phylogenomic approaches are thus able to resolve long-standing questions about the phylogeny of insects.
Keywords: Animals; Bees; Biological Evolution; Genome, Insect; Genomics; Insect Proteins; Insecta; Models, Genetic; Phylogeny; Proteomics; Species Specificity; Wasps

Recurrent duplication-driven transposition of DNA during hominoid evolution. - Johnson, Matthew E; Cheng, Ze; Morrison, V Anne; Scherer, Steven; Ventura, Mario; Richard A Gibbs; Green, Eric D; Eichler, Evan E (Proc Natl Acad Sci U S A, 2006)
The underlying mechanism by which the interspersed pattern of human segmental duplications has evolved is unknown. Based on a comparative analysis of primate genomes, we show that a particular segmental duplication (LCR16a) has been the source locus for the formation of the majority of intrachromosomal duplications blocks on human chromosome 16. We provide evidence that this particular segment has been active independently in each great ape and human lineage at different points during evolution. Euchromatic sequence that flanks sites of LCR16a integration are frequently lineage-specific duplications. This process has mobilized duplication blocks (15-200 kb in size) to new genomic locations in each species. Breakpoint analysis of lineage-specific insertions suggests coordinated deletion of repeat-rich DNA at the target site, in some cases deleting genes in that species. Our data support a model of duplication where the probability that a segment of DNA becomes duplicated is determined by its proximity to core duplicons, such as LCR16a.
Keywords: Animals; Base Sequence; Biological Evolution; Chromosomes, Human, Pair 16; DNA; DNA Transposable Elements; Evolution, Molecular; Gene Duplication; Hominidae; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA

Shedding genomic light on Aristotle's lantern. - Sodergren, Erica; Shen, Yufeng; Song, Xingzhi; Zhang, Lan; Richard A Gibbs; Weinstock, George M (Dev Biol, 2006)
Sea urchins have proved fascinating to biologists since the time of Aristotle who compared the appearance of their bony mouth structure to a lantern in The History of Animals. Throughout modern times it has been a model system for research in developmental biology. Now, the genome of the sea urchin Strongylocentrotus purpuratus is the first echinoderm genome to be sequenced. A high quality draft sequence assembly was produced using the Atlas assembler to combine whole genome shotgun sequences with sequences from a collection of BACs selected to form a minimal tiling path along the genome. A formidable challenge was presented by the high degree of heterozygosity between the two haplotypes of the selected male representative of this marine organism. This was overcome by use of the BAC tiling path backbone, in which each BAC represents a single haplotype, as well as by improvements in the Atlas software. Another innovation introduced in this project was the sequencing of pools of tiling path BACs rather than individual BAC sequencing. The Clone-Array Pooled Shotgun Strategy greatly reduced the cost and time devoted to preparing shotgun libraries from BAC clones. The genome sequence was analyzed with several gene prediction methods to produce a comprehensive gene list that was then manually refined and annotated by a volunteer team of sea urchin experts. This latter annotation community edited over 9000 gene models and uncovered many unexpected aspects of the sea urchin genetic content impacting transcriptional regulation, immunology, sensory perception, and an organism's development. Analysis of the basic deuterostome genetic complement supports the sea urchin's role as a model system for deuterostome and, by extension, chordate development.
Keywords: Animals; Chromosomes, Artificial, Bacterial; DNA; Genome; Sea Urchins

Spectrum of CHD7 mutations in 110 individuals with CHARGE syndrome and genotype-phenotype correlation. - Lalani, Seema R; Safiullah, Arsalan M; Fernbach, Susan D; Harutyunyan, Karine G; Thaller, Christina; Peterson, Leif E; McPherson, John D; Richard A Gibbs; White, Lisa D; Hefner, Margaret; Davenport, Sandra L H; Graham, John M; et al. (Am J Hum Genet, 2006)
CHARGE syndrome is a well-established multiple-malformation syndrome with distinctive consensus diagnostic criteria. Characteristic associated anomalies include ocular coloboma, choanal atresia, cranial nerve defects, distinctive external and inner ear abnormalities, hearing loss, cardiovascular malformations, urogenital anomalies, and growth retardation. Recently, mutations of the chromodomain helicase DNA-binding protein gene CHD7 were reported to be a major cause of CHARGE syndrome. We sequenced the CHD7 gene in 110 individuals who had received the clinical diagnosis of CHARGE syndrome, and we detected mutations in 64 (58%). Mutations were distributed throughout the coding exons and conserved splice sites of CHD7. Of the 64 mutations, 47 (73%) predicted premature truncation of the protein. These included nonsense and frameshift mutations, which most likely lead to haploinsufficiency. Phenotypically, the mutation-positive group was more likely to exhibit cardiovascular malformations (54 of 59 in the mutation-positive group vs. 30 of 42 in the mutation-negative group; P=.014), coloboma of the eye (55 of 62 in the mutation-positive group vs. 30 of 43 in the mutation-negative group; P=.022), and facial asymmetry, often caused by seventh cranial nerve abnormalities (36 of 56 in the mutation-positive group vs. 13 of 39 in the mutation-negative group; P=.004). Mouse embryo whole-mount and section in situ hybridization showed the expression of Chd7 in the outflow tract of the heart, optic vesicle, facio-acoustic preganglion complex, brain, olfactory pit, and mandibular component of the first branchial arch. Microarray gene-expression analysis showed a signature pattern of gene-expression differences that distinguished the individuals with CHARGE syndrome with CHD7 mutation from the controls. We conclude that cardiovascular malformations, coloboma, and facial asymmetry are common findings in CHARGE syndrome caused by CHD7 mutation.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Child; Child, Preschool; Coloboma; DNA Helicases; DNA Mutational Analysis; DNA-Binding Proteins; Embryo, Mammalian; Facial Asymmetry; Female; Genotype; Heart Defects, Congenital; Humans; In Situ Hybridization, Fluorescence; Male; Mice; Molecular Sequence Data; Mutation; Pedigree; Phenotype; RNA Splice Sites; RNA, Messenger; Syndrome

Sweetness and light: illuminating the honey bee genome. - Robinson, G E; Evans, J D; Maleszka, R; Robertson, H M; Weaver, D B; Worley, K; Richard A Gibbs; Weinstock, G M (Insect Mol Biol, 2006)
Keywords: Animals; Bees; Genome, Insect; Genomics; Sequence Analysis, DNA

Comparative genome sequencing of Drosophila pseudoobscura: chromosomal, gene, and cis-element evolution. - Richards, Stephen; Liu, Yue; Bettencourt, Brian R; Hradecky, Pavel; Letovsky, Stan; Nielsen, Rasmus; Thornton, Kevin; Hubisz, Melissa J; Rui Chen; Meisel, Richard P; Couronne, Olivier; Hua, Sujun; et al. (Genome Res, 2005)
We have sequenced the genome of a second Drosophila species, Drosophila pseudoobscura, and compared this to the genome sequence of Drosophila melanogaster, a primary model organism. Throughout evolution the vast majority of Drosophila genes have remained on the same chromosome arm, but within each arm gene order has been extensively reshuffled, leading to a minimum of 921 syntenic blocks shared between the species. A repetitive sequence is found in the D. pseudoobscura genome at many junctions between adjacent syntenic blocks. Analysis of this novel repetitive element family suggests that recombination between offset elements may have given rise to many paracentric inversions, thereby contributing to the shuffling of gene order in the D. pseudoobscura lineage. Based on sequence similarity and synteny, 10,516 putative orthologs have been identified as a core gene set conserved over 25-55 million years (Myr) since the pseudoobscura/melanogaster divergence. Genes expressed in the testes had higher amino acid sequence divergence than the genome-wide average, consistent with the rapid evolution of sex-specific proteins. Cis-regulatory sequences are more conserved than random and nearby sequences between the species--but the difference is slight, suggesting that the evolution of cis-regulatory elements is flexible. Overall, a pattern of repeat-mediated chromosomal rearrangement, and high coadaptation of both male genes and cis-regulatory sequences emerges as important themes of genome divergence between these species of Drosophila.
Keywords: Animals; Chromosome Breakage; Chromosome Inversion; Chromosome Mapping; Chromosomes; Conserved Sequence; Drosophila; Drosophila melanogaster; Enhancer Elements, Genetic; Evolution, Molecular; Gene Rearrangement; Genes, Insect; Genetic Variation; Genome; Molecular Sequence Data; Predictive Value of Tests; Repetitive Sequences, Nucleic Acid; Sequence Analysis, DNA

Deeper into the genome. - Richard A Gibbs (Nature, 2005)
Keywords: Genetic Predisposition to Disease; Genome, Human; Genomics; Genotype; Haplotypes; Humans; Phenotype; Polymorphism, Single Nucleotide; Racial Groups

The DNA sequence of the human X chromosome. - Ross, Mark T; Grafham, Darren V; Coffey, Alison J; Scherer, Steven; McLay, Kirsten; Donna M Muzny; Platzer, Matthias; Howell, Gareth R; Burrows, Christine; Bird, Christine P; Frankish, Adam; Lovell, Frances L; et al. (Nature, 2005)
The human X chromosome has a unique biology that was shaped by its evolution as the sex chromosome shared by males and females. We have determined 99.3% of the euchromatic sequence of the X chromosome. Our analysis illustrates the autosomal origin of the mammalian sex chromosomes, the stepwise process that led to the progressive loss of recombination between X and Y, and the extent of subsequent degradation of the Y chromosome. LINE1 repeat elements cover one-third of the X chromosome, with a distribution that is consistent with their proposed role as way stations in the process of X-chromosome inactivation. We found 1,098 genes in the sequence, of which 99 encode proteins expressed in testis and in various tumour types. A disproportionately high number of mendelian diseases are documented for the X chromosome. Of this number, 168 have been explained by mutations in 113 X-linked genes, which in many cases were characterized with the aid of the DNA sequence.
Keywords: Animals; Antigens, Neoplasm; Centromere; Chromosomes, Human, X; Chromosomes, Human, Y; Contig Mapping; Crossing Over, Genetic; Dosage Compensation, Genetic; Evolution, Molecular; Female; Genetic Linkage; Genetics, Medical; Genomics; Humans; Male; Polymorphism, Single Nucleotide; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Testis

Dual regulation and redundant function of two eye-specific enhancers of the Drosophila retinal determination gene dachshund. - Pappu, Kartik S; Ostrin, Edwin J; Middlebrooks, Brooke W; Sili, Beril Tavsanli; Rui Chen; Atkins, Mardelle R; Richard A Gibbs; Mardon, Graeme (Development, 2005)
Drosophila eye development is controlled by a conserved network of retinal determination (RD) genes. The RD genes encode nuclear proteins that form complexes and function in concert with extracellular signal-regulated transcription factors. Identification of the genomic regulatory elements that govern the eye-specific expression of the RD genes will allow us to better understand how spatial and temporal control of gene expression occurs during early eye development. We compared conserved non-coding sequences (CNCSs) between five Drosophilids along the approximately 40 kb genomic locus of the RD gene dachshund (dac). Our analysis uncovers two separate eye enhancers in intron eight and the 3' non-coding regions of the dac locus defined by clusters of highly conserved sequences. Loss- and gain-of-function analyses suggest that the 3' eye enhancer is synergistically activated by a combination of eya, so and dpp signaling, and only indirectly activated by ey, whereas the 5' eye enhancer is primarily regulated by ey, acting in concert with eya and so. Disrupting conserved So-binding sites in the 3' eye enhancer prevents reporter expression in vivo. Our results suggest that the two eye enhancers act redundantly and in concert with each other to integrate distinct upstream inputs and direct the eye-specific expression of dac.
Keywords: 3' Untranslated Regions; Animals; Base Sequence; DNA-Binding Proteins; Drosophila; Drosophila Proteins; Enhancer Elements, Genetic; Eye Proteins; Gene Expression Regulation, Developmental; Genome; Homeodomain Proteins; Homozygote; Introns; Molecular Sequence Data; Mutation; Nuclear Proteins; Organ Specificity; Response Elements; Retina

Evolutionarily conserved elements in vertebrate, insect, worm, and yeast genomes. - Siepel, Adam; Bejerano, Gill; Pedersen, Jakob S; Hinrichs, Angie S; Hou, Minmei; Rosenbloom, Kate; Clawson, Hiram; Spieth, John; Hillier, LaDeana W; Richards, Stephen; Weinstock, George M; Wilson, Richard K; et al. (Genome Res, 2005)
We have conducted a comprehensive search for conserved elements in vertebrate genomes, using genome-wide multiple alignments of five vertebrate species (human, mouse, rat, chicken, and Fugu rubripes). Parallel searches have been performed with multiple alignments of four insect species (three species of Drosophila and Anopheles gambiae), two species of Caenorhabditis, and seven species of Saccharomyces. Conserved elements were identified with a computer program called phastCons, which is based on a two-state phylogenetic hidden Markov model (phylo-HMM). PhastCons works by fitting a phylo-HMM to the data by maximum likelihood, subject to constraints designed to calibrate the model across species groups, and then predicting conserved elements based on this model. The predicted elements cover roughly 3%-8% of the human genome (depending on the details of the calibration procedure) and substantially higher fractions of the more compact Drosophila melanogaster (37%-53%), Caenorhabditis elegans (18%-37%), and Saccharaomyces cerevisiae (47%-68%) genomes. From yeasts to vertebrates, in order of increasing genome size and general biological complexity, increasing fractions of conserved bases are found to lie outside of the exons of known protein-coding genes. In all groups, the most highly conserved elements (HCEs), by log-odds score, are hundreds or thousands of bases long. These elements share certain properties with ultraconserved elements, but they tend to be longer and less perfectly conserved, and they overlap genes of somewhat different functional categories. In vertebrates, HCEs are associated with the 3' UTRs of regulatory genes, stable gene deserts, and megabase-sized regions rich in moderately conserved noncoding sequences. Noncoding HCEs also show strong statistical evidence of an enrichment for RNA secondary structure.
Keywords: 3' Untranslated Regions; Animals; Base Pairing; Base Sequence; Caenorhabditis elegans; Conserved Sequence; DNA, Intergenic; Evolution, Molecular; Genome; Humans; Insecta; Molecular Sequence Data; Saccharomyces; Vertebrates; Yeasts

Genetic testing, biotechnology, and GMOs: A snapshot of public opinion, 2003 through 2004. - Alford, Raye L; Morris, Kelley E; C Michelle Rives; Steven E Scherer; Weinstock, George; Richard A Gibbs; Ghonima, Karim; Belcher, Mark; Valdes, Hayden; Sumners, Carolyn; Law, Colin; Reiff, Patricia (Genet Med, 2005)
Keywords: Adolescent; Adult; Biotechnology; Female; Food, Genetically Modified; Genetic Engineering; Genetic Testing; Humans; Male; Middle Aged; Public Opinion

The genome of the social amoeba Dictyostelium discoideum. - Eichinger, L; Pachebat, J A; Glöckner, G; Rajandream, M-A; Sucgang, R; Berriman, M; Song, J; Olsen, R; Szafranski, K; Xu, Q; Tunggal, B; Kummerfeld, S; et al. (Nature, 2005)
The social amoebae are exceptional in their ability to alternate between unicellular and multicellular forms. Here we describe the genome of the best-studied member of this group, Dictyostelium discoideum. The gene-dense chromosomes of this organism encode approximately 12,500 predicted proteins, a high proportion of which have long, repetitive amino acid tracts. There are many genes for polyketide synthases and ABC transporters, suggesting an extensive secondary metabolism for producing and exporting small molecules. The genome is rich in complex repeats, one class of which is clustered and may serve as centromeres. Partial copies of the extrachromosomal ribosomal DNA (rDNA) element are found at the ends of each chromosome, suggesting a novel telomere structure and the use of a common mechanism to maintain both the rDNA and chromosomal termini. A proteome-based phylogeny shows that the amoebozoa diverged from the animal-fungal lineage after the plant-animal split, but Dictyostelium seems to have retained more of the diversity of the ancestral genome than have plants, animals or fungi.
Keywords: Animals; ATP-Binding Cassette Transporters; Base Composition; Cell Adhesion; Cell Movement; Centromere; Conserved Sequence; Dictyostelium; DNA Transposable Elements; DNA, Ribosomal; Eukaryotic Cells; Gene Duplication; Gene Transfer, Horizontal; Genome; Genomics; Humans; Molecular Sequence Data; Phylogeny; Proteome; Protozoan Proteins; Repetitive Sequences, Nucleic Acid; RNA, Transfer; Sequence Analysis, DNA; Signal Transduction; Social Behavior; Telomere

Highly multiplexed molecular inversion probe genotyping: over 10,000 targeted SNPs genotyped in a single tube assay. - Hardenbol, Paul; Fuli Yu; Belmont, John; Mackenzie, Jennifer; Bruckner, Carsten; Brundage, Tiffany; Boudreau, Andrew; Chow, Steve; Eberle, Jim; Erbilgin, Ayca; Falkowski, Mat; Fitzgerald, Ron; et al. (Genome Res, 2005)
Large-scale genetic studies are highly dependent on efficient and scalable multiplex SNP assays. In this study, we report the development of Molecular Inversion Probe technology with four-color, single array detection, applied to large-scale genotyping of up to 12,000 SNPs per reaction. While generating 38,429 SNP assays using this technology in a population of 30 trios from the Centre d'Etude Polymorphisme Humain family panel as part of the International HapMap project, we established SNP conversion rates of approximately 90% with concordance rates >99.6% and completeness levels >98% for assays multiplexed up to 12,000plex levels. Furthermore, these individual metrics can be "traded off" and, by sacrificing a small fraction of the conversion rate, the accuracy can be increased to very high levels. No loss of performance is seen when scaling from 6,000plex to 12,000plex assays, strongly validating the ability of the technology to suppress cross-reactivity at high multiplex levels. The results of this study demonstrate the suitability of this technology for comprehensive association studies that use targeted SNPs in indirect linkage disequilibrium studies or that directly screen for causative mutations.
Keywords: Chromosome Inversion; Cluster Analysis; DNA Probes; Gene Expression Profiling; Genome, Human; Genotype; Humans; Molecular Probe Techniques; Molecular Probes; Polymorphism, Single Nucleotide; Research Design

Identification of prognosis markers in pediatric high-risk acute lymphoblastic leukemia. - Al-Lamki, Zakia; Wali, Yasser A; Wasifuddin, Shah M; Zachariah, Mathew; Al-Mjeni, Rayhanah; Li, Changping; Muralitharan, Shanmugakonar; Al-Kharusi, Khalsa; Gunaratne, Preethi; Peterson, Leif; Richard A Gibbs; Marie-Claude Gingras; et al. (Pediatr Hematol Oncol, 2005)
Gene expression profiling may improve the understanding of the biology behind relapse in pediatric acute lymphoblastic leukemia. Using suppression subtractive hybridization (SSH), cDNA concatenated sequencing (CCS), and reverse transcriptase real-time quantitative polymerase chain reaction (RT-RQ-PCR) on high-risk patient samples with nondeterminant chromosomal translocation, the authors identified 3 genes that were significantly overexpressed in the nonrelapsed patients: the calcium/calmodulin-dependent serine protein kinase (CASK), subunit 2 of the cofactor required for SP1 transcriptional activation (CRSP2), and granzyme K (GZMK). The level of expression of these biomarkers may help identify patients with potentially good prognosis within a group otherwise at high risk of relapse.
Keywords: Adolescent; Biomarkers, Tumor; Child; Child, Preschool; Female; Gene Expression Profiling; Gene Expression Regulation, Leukemic; Humans; Male; Neoplasm Proteins; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Predictive Value of Tests; Prognosis; Recurrence; Reverse Transcriptase Polymerase Chain Reaction; Risk Factors

Pooled genomic indexing of rhesus macaque. - Milosavljevic, Aleksandar; R. Alan Harris; Sodergren, Erica J; Jackson, Andrew R; Kalafus, Ken J; Hodgson, Anne; Cree, Andrew; Dai, Weilie; Csuros, Miklos; Zhu, Baoli; De Jong, Pieter J; Weinstock, George M; et al. (Genome Res, 2005)
Pooled genomic indexing (PGI) is a method for mapping collections of bacterial artificial chromosome (BAC) clones between species by using a combination of clone pooling and DNA sequencing. PGI has been used to map a total of 3858 BAC clones covering approximately 24% of the rhesus macaque (Macaca mulatta) genome onto 4178 homologous loci in the human genome. A number of intrachromosomal rearrangements were detected by mapping multiple segments within the individual rhesus BACs onto multiple disjoined loci in the human genome. Transversal pooling designs involving shuffled BAC arrays were employed for robust mapping even with modest DNA sequence read coverage. A further innovation, short-tag pooled genomic indexing (ST-PGI), was also introduced to further improve the economy of mapping by sequencing multiple, short, mapable tags within a single sequencing reaction.
Keywords: Animals; Chromosome Aberrations; Chromosomes, Artificial, Bacterial; Contig Mapping; DNA; Genetic Markers; Genome; Genome, Human; Humans; Macaca mulatta; Sequence Alignment; Sequence Analysis, DNA

Positive selection of a pre-expansion CAG repeat of the human SCA2 gene. - Fuli Yu; Sabeti, Pardis C; Hardenbol, Paul; Fu, Qing; Fry, Ben; Lu, Xiuhua; Ghose, Sy; Vega, Richard; Perez, Ag; Pasternak, Shiran; Leal, Suzanne M; Willis, Thomas D; et al. (PLoS Genet, 2005)
A region of approximately one megabase of human Chromosome 12 shows extensive linkage disequilibrium in Utah residents with ancestry from northern and western Europe. This strikingly large linkage disequilibrium block was analyzed with statistical and experimental methods to determine whether natural selection could be implicated in shaping the current genome structure. Extended Haplotype Homozygosity and Relative Extended Haplotype Homozygosity analyses on this region mapped a core region of the strongest conserved haplotype to the exon 1 of the Spinocerebellar ataxia type 2 gene (SCA2). Direct DNA sequencing of this region of the SCA2 gene revealed a significant association between a pre-expanded allele [(CAG)8CAA(CAG)4CAA(CAG)8] of CAG repeats within exon 1 and the selected haplotype of the SCA2 gene. A significantly negative Tajima's D value (-2.20, p < 0.01) on this site consistently suggested selection on the CAG repeat. This region was also investigated in the three other populations, none of which showed signs of selection. These results suggest that a recent positive selection of the pre-expansion SCA2 CAG repeat has occurred in Utah residents with European ancestry.
Keywords: Ataxins; Base Sequence; Chromosome Mapping; Chromosomes, Human, Pair 12; Europe; Exons; Gene Frequency; Humans; Molecular Sequence Data; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Selection, Genetic; Spinocerebellar Degenerations; Trinucleotide Repeats; Utah; White People

Single nucleotide polymorphisms in genes for 2'-5'-oligoadenylate synthetase and RNase L inpatients hospitalized with West Nile virus infection. - Yakub, Imtiaz; Lillibridge, Kristy M; Moran, Ana; Gonzalez, Omar Y; Belmont, John; Richard A Gibbs; Tweardy, David J (J Infect Dis, 2005)
BACKGROUND: Infection with the flavivirus West Nile virus (WNV) is a growing problem across the United States, where there is a case-fatality rate of 15%-29% in individuals >70 years old and no consistently effective treatment. Susceptibility to WNV disease in inbred strains of mice was mapped to a nonsense mutation in the gene encoding the 1b isoform of 2'-5'-oligoadenylate synthetase (OAS), a member of the OAS/RNase L system of innate viral resistance. Genetic susceptibility to severe WNV disease in humans has not been determined. METHODS: We sequenced each exon within all OAS and RNASEL genes in 33 individuals hospitalized with WNV infection in Houston to assess if there is a defect in this system in patients with severe WNV disease. RESULTS: Sequencing did not reveal any insertions, deletions, or nonsense mutations in any OAS or RNASEL gene. However, comparison of the exonic sequences between case patients and control subjects identified 23 single nucleotide polymorphisms (SNPs), including a synonymous SNP in OASL exon 2 (rs3213545), in which the reference allele occurred at a higher frequency in case patients (P < .004). CONCLUSION: Because the reference allele contains a splice enhancer site, our finding suggests that the RNA transcripts generated from this allele may undergo increased splicing, which results in a dominant-negative OASL isozyme similar to the nonsense/truncation mutant form of Oas1b in mice.
Keywords: 2',5'-Oligoadenylate Synthetase; Adult; Aged; Endoribonucleases; Exons; Female; Genetic Predisposition to Disease; Hospitalization; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; West Nile Fever; West Nile virus

SNPdetector: a software tool for sensitive and accurate SNP detection. - Zhang, Jinghui; Wheeler, David A; Yakub, Imtiaz; Wei, Sharon; Sood, Raman; Rowe, William; Liu, Paul P; Richard A Gibbs; Buetow, Kenneth H (PLoS Comput Biol, 2005)
Identification of single nucleotide polymorphisms (SNPs) and mutations is important for the discovery of genetic predisposition to complex diseases. PCR resequencing is the method of choice for de novo SNP discovery. However, manual curation of putative SNPs has been a major bottleneck in the application of this method to high-throughput screening. Therefore it is critical to develop a more sensitive and accurate computational method for automated SNP detection. We developed a software tool, SNPdetector, for automated identification of SNPs and mutations in fluorescence-based resequencing reads. SNPdetector was designed to model the process of human visual inspection and has a very low false positive and false negative rate. We demonstrate the superior performance of SNPdetector in SNP and mutation analysis by comparing its results with those derived by human inspection, PolyPhred (a popular SNP detection tool), and independent genotype assays in three large-scale investigations. The first study identified and validated inter- and intra-subspecies variations in 4,650 traces of 25 inbred mouse strains that belong to either the Mus musculus species or the M. spretus species. Unexpected heterozygosity in CAST/Ei strain was observed in two out of 1,167 mouse SNPs. The second study identified 11,241 candidate SNPs in five ENCODE regions of the human genome covering 2.5 Mb of genomic sequence. Approximately 50% of the candidate SNPs were selected for experimental genotyping; the validation rate exceeded 95%. The third study detected ENU-induced mutations (at 0.04% allele frequency) in 64,896 traces of 1,236 zebra fish. Our analysis of three large and diverse test datasets demonstrated that SNPdetector is an effective tool for genome-scale research and for large-sample clinical studies. SNPdetector runs on Unix/Linux platform and is available publicly (http://lpg.nci.nih.gov).
Keywords: Algorithms; Alleles; Animals; Computational Biology; Gene Frequency; Genome; Genotype; Heterozygote; Humans; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity; Software

Trp modification signals a quorum. - Richard A Gibbs (Nat Chem Biol, 2005)
Keywords: Bacillus subtilis; Bacterial Proteins; Molecular Structure; Protein Conformation; Tryptophan

The Atlas genome assembly system. - Havlak, Paul; Rui Chen; Durbin, K James; Egan, Amy; Ren, Yanru; Song, Xing-Zhi; Weinstock, George M; Richard A Gibbs (Genome Res, 2004)
Atlas is a suite of programs developed for assembly of genomes by a "combined approach" that uses DNA sequence reads from both BACs and whole-genome shotgun (WGS) libraries. The BAC clones afford advantages of localized assembly with reduced computational load, and provide a robust method for dealing with repeated sequences. Inclusion of WGS sequences facilitates use of different clone insert sizes and reduces data production costs. A core function of Atlas software is recruitment of WGS sequences into appropriate BACs based on sequence overlaps. Because construction of consensus sequences is from local assembly of these reads, only small (<0.1%) units of the genome are assembled at a time. Once assembled, each BAC is used to derive a genomic layout. This "sequence-based" growth of the genome map has greater precision than with non-sequence-based methods. Use of BACs allows correction of artifacts due to repeats at each stage of the process. This is aided by ancillary data such as BAC fingerprint, other genomic maps, and syntenic relations with other genomes. Atlas was used to assemble a draft DNA sequence of the rat genome; its major components including overlapper and split-scaffold are also being used in pure WGS projects.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Contig Mapping; Genome; Rats; Software

Complete genome sequence of Rickettsia typhi and comparison with sequences of other rickettsiae. - McLeod, Michael P; Qin, Xiang; Karpathy, Sandor E; Gioia, Jason; Highlander, Sarah K; Fox, George E; McNeill, Thomas Z; Jiang, Huaiyang; Donna M Muzny; Jacob, Leni S; Hawes, Alicia C; Sodergren, Erica; et al. (J Bacteriol, 2004)
Rickettsia typhi, the causative agent of murine typhus, is an obligate intracellular bacterium with a life cycle involving both vertebrate and invertebrate hosts. Here we present the complete genome sequence of R. typhi (1,111,496 bp) and compare it to the two published rickettsial genome sequences: R. prowazekii and R. conorii. We identified 877 genes in R. typhi encoding 3 rRNAs, 33 tRNAs, 3 noncoding RNAs, and 838 proteins, 3 of which are frameshifts. In addition, we discovered more than 40 pseudogenes, including the entire cytochrome c oxidase system. The three rickettsial genomes share 775 genes: 23 are found only in R. prowazekii and R. typhi, 15 are found only in R. conorii and R. typhi, and 24 are unique to R. typhi. Although most of the genes are colinear, there is a 35-kb inversion in gene order, which is close to the replication terminus, in R. typhi, compared to R. prowazekii and R. conorii. In addition, we found a 124-kb R. typhi-specific inversion, starting 19 kb from the origin of replication, compared to R. prowazekii and R. conorii. Inversions in this region are also seen in the unpublished genome sequences of R. sibirica and R. rickettsii, indicating that this region is a hot spot for rearrangements. Genome comparisons also revealed a 12-kb insertion in the R. prowazekii genome, relative to R. typhi and R. conorii, which appears to have occurred after the typhus (R. prowazekii and R. typhi) and spotted fever (R. conorii) groups diverged. The three-way comparison allowed further in silico analysis of the SpoT split genes, leading us to propose that the stringent response system is still functional in these rickettsiae.
Keywords: Chromosome Inversion; DNA, Bacterial; Electron Transport Complex IV; Frameshifting, Ribosomal; Gene Expression Regulation, Bacterial; Gene Rearrangement; Genes, Bacterial; Genes, rRNA; Genome, Bacterial; Genomics; Molecular Sequence Data; Pseudogenes; Rickettsia; Rickettsia conorii; Rickettsia typhi; RNA, Transfer; RNA, Untranslated; Sequence Analysis, DNA; Sequence Homology; Synteny

Dynamic building of a BAC clone tiling path for the Rat Genome Sequencing Project. - Rui Chen; Sodergren, Erica; Weinstock, George M; Richard A Gibbs (Genome Res, 2004)
CLONEPICKER is a software pipeline that integrates sequence data with BAC clone fingerprints to dynamically select a minimal overlapping clone set covering the whole genome. In the Rat Genome Sequencing Project (RGSP), a hybrid strategy of "clone by clone" and "whole genome shotgun" approaches was used to maximize the merits of both approaches. Like the "clone by clone" method, one key challenge for this strategy was to select a low-redundancy clone set that covered the whole genome while the sequencing is in progress. The CLONEPICKER pipeline met this challenge using restriction enzyme fingerprint data, BAC end sequence data, and sequences generated from individual BAC clones as well as WGS reads. In the RGSP, an average of 7.5 clones was identified from each side of a seed clone, and the minimal overlapping clones were reliably selected. Combined with the assembled BAC fingerprint map, a set of BAC clones that covered >97% of the genome was identified and used in the RGSP.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Computational Biology; Contig Mapping; DNA Fingerprinting; Genome; Rats; Sequence Analysis, DNA; Software

Genetics. The critical region in trisomy 21. - Nelson, David L; Richard A Gibbs (Science, 2004)
Keywords: Animals; Chromosome Deletion; Chromosomes, Human, Pair 21; Chromosomes, Mammalian; Craniofacial Abnormalities; Crosses, Genetic; Disease Models, Animal; Down Syndrome; Female; Gene Duplication; Humans; Male; Mice; Recombination, Genetic; Skull; Trisomy

Genome sequence of the Brown Norway rat yields insights into mammalian evolution. - Richard A Gibbs; Weinstock, George M; Metzker, Michael L; Donna M Muzny; Sodergren, Erica J; Scherer, Steven; Scott, Graham; Steffen, David; Worley, Kim C; Burch, Paula E; Okwuonu, Geoffrey; Hines, Sandra; et al. (Nature, 2004)
The laboratory rat (Rattus norvegicus) is an indispensable tool in experimental medicine and drug development, having made inestimable contributions to human health. We report here the genome sequence of the Brown Norway (BN) rat strain. The sequence represents a high-quality 'draft' covering over 90% of the genome. The BN rat sequence is the third complete mammalian genome to be deciphered, and three-way comparisons with the human and mouse genomes resolve details of mammalian evolution. This first comprehensive analysis includes genes and proteins and their relation to human disease, repeated sequences, comparative genome-wide studies of mammalian orthologous chromosomal regions and rearrangement breakpoints, reconstruction of ancestral karyotypes and the events leading to existing species, rates of variation, and lineage-specific and lineage-independent evolutionary events such as expansion of gene families, orthology relations and protein evolution.
Keywords: Animals; Base Composition; Centromere; Chromosomes, Mammalian; CpG Islands; DNA Transposable Elements; DNA, Mitochondrial; Evolution, Molecular; Gene Duplication; Genome; Genomics; Humans; Introns; Male; Mice; Models, Molecular; Mutagenesis; Polymorphism, Single Nucleotide; Rats; Rats, Inbred BN; Regulatory Sequences, Nucleic Acid; Retroelements; RNA Splice Sites; RNA, Untranslated; Sequence Analysis, DNA; Telomere

Genome-wide linkage disequilibrium and haplotype maps. - Belmont, John W; Richard A Gibbs (Am J Pharmacogenomics, 2004)
There is currently a broad effort to produce genome-wide high-density linkage disequilibrium (LD) maps with single nucleotide polymorphisms. The hope is that the resulting maps can be exploited to find genes that affect the onset and severity of at least some common human diseases. These maps may also be useful for identifying genes that affect drug response or the likelihood of drug toxicities. The goal of this review is to provide a broad overview of some of the key concerns motivating the design of a major international project called the International Haplotype Map Project. The process of map production requires the identification of very large numbers of polymorphic sites, implementation of facile, highly accurate and inexpensive genotyping production pipelines, and provision for public access to the genotype data. Great progress has been made recently in genotyping methods and these advances are allowing very large-scale data collection. A major goal of these efforts is to enable the selection of subsets of markers that capture useful genetic information in short genomic intervals, while optimally reducing the number of markers that must be genotyped. Standard measures of LD provide a starting point but may not fully capture the complexity of the information inherent in the data. Extremely dense genotype data in several broadly representative populations (European, Chinese, Japanese, and Yoruba) should yield important insights into the genetic structure of most genes. Further study is required to determine how broadly applicable the data will be to other population groups. Significant challenges lie ahead in determining the best methods for the selection of markers in disease/phenotype studies, large-scale genotyping, and analysis of the resulting genetic data.
Keywords: Animals; Chromosome Mapping; Databases, Genetic; Genetic Markers; Genome; Haplotypes; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Population; Quality Control

Genomic segmental polymorphisms in inbred mouse strains. - Li, Jiangzhen; Jiang, Tao; Mao, Jian-Hua; Balmain, Allan; Peterson, Leif; Harris, Charles; Rao, Pulivarthi H; Havlak, Paul; Richard A Gibbs; Cai, Wei-Wen (Nat Genet, 2004)
By analyzing genomic copy-number differences using high-resolution mouse whole-genome BAC arrays, we uncover substantial differences in regional DNA content between inbred strains of mice. The identification of these apparently common segmental polymorphisms suggests that these differences can contribute to genetic variability and pathologic susceptibility.
Keywords: Animals; Base Sequence; Chromosomes, Artificial, Bacterial; Gene Dosage; In Situ Hybridization, Fluorescence; Mice; Mice, Inbred Strains; Polymorphism, Genetic

Identification of rat genes by TWINSCAN gene prediction, RT-PCR, and direct sequencing. - Wu, Jia Qian; Shteynberg, David; Arumugam, Manimozhiyan; Richard A Gibbs; Brent, Michael R (Genome Res, 2004)
The publication of a draft sequence of a third mammalian genome--that of the rat--suggests a need to rethink genome annotation. New mammalian sequences will not receive the kind of labor-intensive annotation efforts that are currently being devoted to human. In this paper, we demonstrate an alternative approach: reverse transcription-polymerase chain reaction (RT-PCR) and direct sequencing based on dual-genome de novo predictions from TWINSCAN. We tested 444 TWINSCAN-predicted rat genes that showed significant homology to known human genes implicated in disease but that were partially or completely missed by methods based on protein-to-genome mapping. Using primers in exons flanking a single predicted intron, we were able to verify the existence of 59% of these predicted genes. We then attempted to amplify the complete predicted open reading frames of 136 genes that were verified in the single-intron experiment. Spliced sequences were amplified in 46 cases (34%). We conclude that this procedure for elucidating gene structures with native cDNA sequences is cost-effective and will become even more so as it is further optimized.
Keywords: Animals; Computational Biology; Genes; Humans; Introns; Open Reading Frames; Predictive Value of Tests; Rats; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA; Software; Untranslated Regions

Large-scale RT-PCR recovery of full-length cDNA clones. - Wu, Jia Qian; Garcia, Angela M; Hulyk, Steven; Sneed, Anna; Kowis, Carla; Yuan, Ye; Steffen, David; McPherson, John D; Gunaratne, Preethi H; Richard A Gibbs (Biotechniques, 2004)
Pseudogenes, alternative transcripts, noncoding RNA, and polymorphisms each add extensive complexity to the mammalian transcriptome and confound estimation of the total number of genes. Despite advanced algorithms for gene prediction and several large-scale efforts to obtain cDNA clones for all human open reading frames (ORFs), no single collection is complete. To enhance this effort, we have developed a high-throughput pipeline for reverse transcription PCR (RT-PCR) gene recovery. Most importantly, novel molecular strategies for improving RT-PCR yield of transcripts that have been difficult to isolate by other means and computational strategies for clone sequence validation have been developed and optimized. This systematic gene recovery pipeline allows both rescue of predicted human and rat genes and provides insight into the complexity of the transcriptome through comparisons with existing data sets.
Keywords: Automation; Cloning, Molecular; DNA, Complementary; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sequence Analysis, DNA

The status, quality, and expansion of the NIH full-length cDNA project: the Mammalian Gene Collection (MGC). - Gerhard, Daniela S; Wagner, Lukas; Feingold, Elise A; Shenmen, Carolyn M; Grouse, Lynette H; Schuler, Greg; Klein, Steven L; Old, Susan; Rasooly, Rebekah; Good, Peter; Guyer, Mark; Peck, Allison M; et al. (Genome Res, 2004)
The National Institutes of Health's Mammalian Gene Collection (MGC) project was designed to generate and sequence a publicly accessible cDNA resource containing a complete open reading frame (ORF) for every human and mouse gene. The project initially used a random strategy to select clones from a large number of cDNA libraries from diverse tissues. Candidate clones were chosen based on 5'-EST sequences, and then fully sequenced to high accuracy and analyzed by algorithms developed for this project. Currently, more than 11,000 human and 10,000 mouse genes are represented in MGC by at least one clone with a full ORF. The random selection approach is now reaching a saturation point, and a transition to protocols targeted at the missing transcripts is now required to complete the mouse and human collections. Comparison of the sequence of the MGC clones to reference genome sequences reveals that most cDNA clones are of very high sequence quality, although it is likely that some cDNAs may carry missense variants as a consequence of experimental artifact, such as PCR, cloning, or reverse transcriptase errors. Recently, a rat cDNA component was added to the project, and ongoing frog (Xenopus) and zebrafish (Danio) cDNA projects were expanded to take advantage of the high-throughput MGC pipeline.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA Primers; DNA, Complementary; Gene Library; Humans; Mice; National Institutes of Health (U.S.); Open Reading Frames; Rats; United States; Xenopus laevis; Zebrafish

Variation in GRM3 affects cognition, prefrontal glutamate, and risk for schizophrenia. - Egan, Michael F; Straub, Richard E; Goldberg, Terry E; Yakub, Imtiaz; Callicott, Joseph H; Hariri, Ahmad R; Mattay, Venkata S; Bertolino, Alessandro; Hyde, Thomas M; Shannon-Weickert, Cynthia; Akil, Mayada; Crook, Jeremy; et al. (Proc Natl Acad Sci U S A, 2004)
GRM3, a metabotropic glutamate receptor-modulating synaptic glutamate, is a promising schizophrenia candidate gene. In a family-based association study, a common GRM3 haplotype was strongly associated with schizophrenia (P = 0.0001). Within this haplotype, the A allele of single-nucleotide polymorphism (SNP) 4 (hCV11245618) in intron 2 was slightly overtransmitted to probands (P = 0.02). We studied the effects of this SNP on neurobiological traits related to risk for schizophrenia and glutamate neurotransmission. The SNP4 A allele was associated with poorer performance on several cognitive tests of prefrontal and hippocampal function. The physiological basis of this effect was assessed with functional MRI, which showed relatively deleterious activation patterns in both cortical regions in control subjects homozygous for the SNP4 A allele. We next looked at SNP4's effects on two indirect measures of prefrontal glutamate neurotransmission. Prefrontal N-acetylaspartate, an in vivo MRI measure related to synaptic activity and closely correlated with tissue glutamate, was lower in SNP4 AA homozygotes. In postmortem human prefrontal cortex, AA homozygotes had lower mRNA levels of the glial glutamate transporter EAAT2, a protein regulated by GRM3 that critically modulates synaptic glutamate. Effects of SNP4 on prefrontal GRM3 mRNA and protein levels were marginal. Resequencing revealed no missense or splice-site SNPs, suggesting that the intronic SNP4 or related haplotypes may exert subtle regulatory effects on GRM3 transcription. These convergent data point to a specific molecular pathway by which GRM3 genotype alters glutamate neurotransmission, prefrontal and hippocampal physiology and cognition, and thereby increased risk for schizophrenia.
Keywords: Adult; Cognition; Genetic Predisposition to Disease; Genotype; Glutamates; Haplotypes; Hippocampus; Humans; Magnetic Resonance Imaging; Middle Aged; Neuropsychological Tests; Phenotype; Prefrontal Cortex; Receptors, Metabotropic Glutamate; Schizophrenia; Sequence Analysis, DNA

Concatenation cDNA sequencing for transcriptome analysis. - Gunaratne, Preethi H; Wu, Jia Qian; Garcia, Angela M; Hulyk, Steven; Kim C Worley; Margolin, Judith F; Richard A Gibbs (C R Biol, 2003)
We describe a high-throughput cDNA sequencing pipeline (http://www.hgsc.bcm.tmc.edu/projects/cdna) built in response to the emerging need for rapid sequencing of large cDNA collections. Using this strategy cDNA inserts are purified and joined through concatenation into large molecules. These 'pseudo-BACs' are subjected to random shotgun sequencing whereby the majority of cDNA inserts in the pool are sequenced. Using this concatenation cDNA sequencing platform, we have contributed more than 13000 full-length cDNA sequences from human and mouse to the Mammalian Gene Collection (MGC).
Keywords: Cloning, Molecular; DNA, Complementary; DNA, Concatenated; Genetic Techniques; Humans; Sequence Analysis, DNA; Transcription, Genetic

Evolving methods for the assembly of large genomes. - Richard A Gibbs; Weinstock, G M (Cold Spring Harb Symp Quant Biol, 2003)
Keywords: Animals; Chromosomes, Artificial, Bacterial; Cloning, Molecular; Genetic Techniques; Genome; Genomics; Humans; Sequence Analysis, DNA

Human genetics. Primate shadow play. - Richard A Gibbs; Nelson, David L (Science, 2003)
Keywords: Animals; Biological Evolution; Cebidae; Cercopithecidae; Computational Biology; Conserved Sequence; Exons; Genome; Genome, Human; Hominidae; Humans; Models, Statistical; Phylogeny; Primates; Regulatory Sequences, Nucleic Acid; Sequence Analysis, DNA; Species Specificity

Novel potential ALL low-risk markers revealed by gene expression profiling with new high-throughput SSH-CCS-PCR. - Qiu, J; Gunaratne, P; Peterson, L E; Khurana, D; Walsham, N; Loulseged, H; Karni, R J; Roussel, E; Richard A Gibbs; Margolin, J F; Marie-Claude Gingras (Leukemia, 2003)
The current systems of risk grouping in pediatric acute lymphoblastic leukemia (ALL) fail to predict therapeutic success in 10-35% of patients. To identify better predictive markers of clinical behavior in ALL, we have developed an integrated approach for gene expression profiling that couples suppression subtractive hybridization, concatenated cDNA sequencing, and reverse transcriptase real-time quantitative PCR. Using this approach, a total of 600 differentially expressed genes were identified between t(4;11) ALL and pre-B ALL with no determinant chromosomal translocation. The expression of 67 genes was analyzed in different cytogenetic ALL subgroups and B lymphocytes isolated from healthy donors. Three genes, BACH1, TP53BPL, and H2B/S, were consistently expressed as a significant cluster associated with the low-risk ALL subgroups. A total of 42 genes were differentially expressed in ALL vs normal B lymphocytes, with no specific association with any particular ALL subgroups. The remaining 22 genes were part of a specific expression profile associated with the hyperdiploid, t(12;21), or t(4;11) subgroups. Using an unsupervised hierarchical cluster analysis, the discriminating power of these specific expression profiles allowed the clustering of patients according to their subgroups. These genes could help to understand the difference in treatment response and become therapeutical targets to improve ALL clinical outcomes.
Keywords: B-Lymphocytes; Biomarkers, Tumor; Case-Control Studies; DNA Primers; DNA, Complementary; DNA, Neoplasm; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Humans; Neoplasm Proteins; Nucleic Acid Hybridization; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Risk Factors; RNA, Messenger; RNA, Neoplasm; Subtraction Technique

Polymorphisms at the G72/G30 gene locus, on 13q33, are associated with bipolar disorder in two independent pedigree series. - Hattori, Eiji; Liu, Chunyu; Badner, Judith A; Bonner, Tom I; Christian, Susan L; Maheshwari, Manjula; Detera-Wadleigh, Sevilla D; Richard A Gibbs; Gershon, Elliot S (Am J Hum Genet, 2003)
Linkage evidence suggests that chromosome 13 (13q32-33) contains susceptibility genes for both bipolar disorder and schizophrenia. Recently, genes called "G72" and "G30" were identified, and polymorphisms of these overlapping genes were reported to be associated with schizophrenia. We studied two series of pedigrees with bipolar disorder: the Clinical Neurogenetics (CNG) pedigrees (in which linkage to illness had been previously reported at 13q32-33), with 83 samples from 22 multiplex families, and the National Institute of Mental Health (NIMH) Genetics Initiative pedigrees, with 474 samples from 152 families. Sixteen single-nucleotide polymorphisms (SNPs) were genotyped at and around the G72/G30 locus, which covered a 157-kb region encompassing the entire complementary DNA sequences of G72 and G30. We performed transmission/disequilibrium testing (TDT) and haplotype analysis, since a linkage-disequilibrium block was present at this gene locus. In the CNG and NIMH data sets, the results of global TDT of the entire haplotype set were significant and consistent (P=.0004 and P=.008, respectively). In the CNG series, the associated genotypes divided the families into those with linkage and those without linkage (partitioned by the linkage evidence). Analysis of the decay of haplotype sharing gave a location estimate that included G72/G30 in its 95% confidence interval. Although statistically significant association was not detected for individual SNPs in the NIMH data set, the same haplotype was consistently overtransmitted in both series. These data suggest that a susceptibility variant for bipolar illness exists in the vicinity of the G72/G30 genes. Taken together with the earlier report, this is the first demonstration of a novel gene(s), discovered through a positional approach, independently associated with both bipolar illness and schizophrenia.
Keywords: Alternative Splicing; Bipolar Disorder; Carrier Proteins; Chromosomes, Human, Pair 13; DNA, Complementary; Gene Frequency; Genes; Genetic Linkage; Genetic Predisposition to Disease; Haplotypes; Humans; Intracellular Signaling Peptides and Proteins; Likelihood Functions; Linkage Disequilibrium; Molecular Sequence Data; Pedigree; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Sequence and structure of the extrachromosomal palindrome encoding the ribosomal RNA genes in Dictyostelium. - Sucgang, Richard; Chen, Guokai; Liu, Wen; Lindsay, Ryan; Lu, Jing; Donna M Muzny; Shaulsky, Gad; Loomis, William; Richard A Gibbs; Kuspa, Adam (Nucleic Acids Res, 2003)
Ribosomal RNAs (rRNAs) are encoded by multicopy families of identical genes. In Dictyostelium and other protists, the rDNA is carried on extrachromosomal palindromic elements that comprise up to 20% of the nuclear DNA. We present the sequence of the 88 kb Dictyostelium rDNA element, noting that the rRNA genes are likely to be the only transcribed regions. By interrogating a library of ordered YAC clones, we provide evidence for a chromosomal copy of the rDNA on chromosome 4. This locus may provide master copies for the stable transmission of the extrachromosomal elements. The extrachromosomal elements were also found to form chromosome-sized clusters of DNA within nuclei of nocodazole-treated cells arrested in mitosis. These clusters resemble true chromosomes and may allow the efficient segregation of the rDNA during mitosis. These rDNA clusters may also explain the cytological observations of a seventh chromosome in this organism.
Keywords: Animals; Chromosome Mapping; Dictyostelium; DNA, Protozoan; In Situ Hybridization, Fluorescence; Molecular Sequence Data; Plasmids; RNA, Ribosomal; Sequence Analysis, DNA

The beta-globin C-->G mutation at 6 bp 3' to the termination codon causes beta-thalassaemia by decreasing the mRNA level. - Sgourou, Argyro; Papachatzopoulou, Adamandia; Psiouri, Lambrini; Antoniou, Michael; Zoumbos, Nicholas; Richard A Gibbs; Athanassiadou, Aglaia (Br J Haematol, 2002)
We have studied the expression of the silent beta-thalassaemia term+6 (C-->G) mutation, at nucleotide 6 after the stop codon within the human beta-globin 3' untranslated regions (3'UTR), by stable transfection in murine erythroleukaemia (MEL) cells. Steady state mRNA levels from transfected MEL cells containing the term+6 mutant allele were reduced by 52-60%, compared with those obtained from the normal beta-globin gene, in both total and cytoplasmic RNA fractions, showing that the mutation itself is responsible for the similar data obtained from patients. Upon analysis of nuclear RNA, the term+6 mutation was found to also lower the ratio of cleaved/uncleaved transcripts by 22-30%, thus revealing that it interferes with correct 3'-end formation of beta-globin mRNA. The term+6 mutation lies within a polypyrimidine track, similar to that in the beta-intervening sequence II (beta-IVSII), which is known to be an important contributor to the promotion of premRNA 3'-end formation. We propose that the two polypyrimidine tracks flanking the translated region of exon III of the human beta-globin gene may co-operate during beta-globin mRNA biogenesis.
Keywords: beta-Thalassemia; Child; Codon, Terminator; Globins; Humans; Male; Mutation; RNA, Messenger; Transfection

The cloning, genomic organization and tissue expression profile of the human DLG5 gene. - Shah, Gopi; Brugada, Ramon; Gonzalez, Oscar; Czernuszewicz, Grazyna; Richard A Gibbs; Bachinski, Linda; Roberts, Robert (BMC Genomics, 2002)
BACKGROUND: Familial atrial fibrillation, an autosomal dominant disease, was previously mapped to chromosome 10q22. One of the genes mapped to the 10q22 region is DLG5, a member of the MAGUKs (Membrane Associated Gyanylate Kinase) family which mediates intracellular signaling. Only a partial cDNA was available for DLG5. To exclude potential disease inducing mutations, it was necessary to obtain a complete cDNA and genomic sequence of the gene. METHODS: The Northern Blot analysis performed using 3' UTR of this gene indicated the transcript size to be about 7.2 KB. Using race technique and library screening the entire cDNA was cloned. This gene was evaluated by sequencing the coding region and splice functions in normal and affected family members with familial atrial fibrillation. Furthermore, haploid cell lines from affected patients were generated and analyzed for deletions that may have been missed by PCR. RESULTS: We identified two distinct alternately spliced transcripts of this gene. The genomic sequence of the DLG5 gene spanned 79 KB with 32 exons and was shown to have ubiquitous human tissue expression including placenta, heart, skeletal muscle, liver and pancreas. CONCLUSIONS: The entire cDNA of DLG5 was identified, sequenced and its genomic organization determined.

The cloning, genomic organization and tissue expression profile of the human DLG5 gene: Correction. - Shah, Gopi; Brugada, Ramon; Gonzalez, Oscar; Czernuszewicz, Grazyna; Richard A Gibbs; Bachinski, Linda; Roberts, Robert (BMC Genomics, 2002)

Finishing a whole-genome shotgun: release 3 of the Drosophila melanogaster euchromatic genome sequence. - Celniker, Susan E; Wheeler, David A; Kronmiller, Brent; Carlson, Joseph W; Halpern, Aaron; Patel, Sandeep; Adams, Mark; Champe, Mark; Dugan, Shannon P; Frise, Erwin; Hodgson, Ann; George, Reed A; et al. (Genome Biol, 2002)
BACKGROUND: The Drosophila melanogaster genome was the first metazoan genome to have been sequenced by the whole-genome shotgun (WGS) method. Two issues relating to this achievement were widely debated in the genomics community: how correct is the sequence with respect to base-pair (bp) accuracy and frequency of assembly errors? And, how difficult is it to bring a WGS sequence to the accepted standard for finished sequence? We are now in a position to answer these questions. RESULTS: Our finishing process was designed to close gaps, improve sequence quality and validate the assembly. Sequence traces derived from the WGS and draft sequencing of individual bacterial artificial chromosomes (BACs) were assembled into BAC-sized segments. These segments were brought to high quality, and then joined to constitute the sequence of each chromosome arm. Overall assembly was verified by comparison to a physical map of fingerprinted BAC clones. In the current version of the 116.9 Mb euchromatic genome, called Release 3, the six euchromatic chromosome arms are represented by 13 scaffolds with a total of 37 sequence gaps. We compared Release 3 to Release 2; in autosomal regions of unique sequence, the error rate of Release 2 was one in 20,000 bp. CONCLUSIONS: The WGS strategy can efficiently produce a high-quality sequence of a metazoan genome while generating the reagents required for sequence finishing. However, the initial method of repeat assembly was flawed. The sequence we report here, Release 3, is a reliable resource for molecular genetic experimentation and computational analysis.
Keywords: Animals; Drosophila melanogaster; Euchromatin; Genome; Physical Chromosome Mapping; Research Design; Sequence Analysis, DNA; X Chromosome

Generation and initial analysis of more than 15,000 full-length human and mouse cDNA sequences. - Strausberg, Robert L; Feingold, Elise A; Grouse, Lynette H; Derge, Jeffery G; Klausner, Richard D; Collins, Francis S; Wagner, Lukas; Shenmen, Carolyn M; Schuler, Gregory D; Altschul, Stephen F; Zeeberg, Barry; Buetow, Kenneth H; et al. (Proc Natl Acad Sci U S A, 2002)
The National Institutes of Health Mammalian Gene Collection (MGC) Program is a multiinstitutional effort to identify and sequence a cDNA clone containing a complete ORF for each human and mouse gene. ESTs were generated from libraries enriched for full-length cDNAs and analyzed to identify candidate full-ORF clones, which then were sequenced to high accuracy. The MGC has currently sequenced and verified the full ORF for a nonredundant set of >9,000 human and >6,000 mouse genes. Candidate full-ORF clones for an additional 7,800 human and 3,500 mouse genes also have been identified. All MGC sequences and clones are available without restriction through public databases and clone distribution networks (see http:mgc.nci.nih.gov).
Keywords: Algorithms; Animals; DNA, Complementary; Gene Library; Humans; Mice; Open Reading Frames; Sequence Analysis, DNA

Glass bead purification of plasmid template DNA for high throughput sequencing of mammalian genomes. - Dederich, Debra A; Okwuonu, Geoffrey; Garner, Toni; Denn, Amanda; Sutton, Angelica; Escotto, Michael; Martindale, Ashley; Delgado, Oliver; Donna M Muzny; Richard A Gibbs; Metzker, Michael L (Nucleic Acids Res, 2002)
To meet the new challenge of generating the draft sequences of mammalian genomes, we describe the development of a novel high throughput 96-well method for the purification of plasmid DNA template using size-fractionated, acid-washed glass beads. Unlike most previously described approaches, the current method has been designed and optimized to facilitate the direct binding of alcohol-precipitated plasmid DNA to glass beads from alkaline lysed bacterial cells containing the insoluble cellular aggregate material. Eliminating the tedious step of separating the cleared lysate significantly simplifies the method and improves throughput and reliability. During a 4 month period of 96-capillary DNA sequencing of the Rattus norvegicus genome at the Baylor College of Medicine Human Genome Sequencing Center, the average success rate and read length derived from >1 800 000 plasmid DNA templates prepared by the direct lysis/glass bead method were 82.2% and 516 bases, respectively. The cost of this direct lysis/glass bead method in September 2001 was approximately 10 cents per clone, which is a significant cost saving in high throughput genomic sequencing efforts.
Keywords: Animals; DNA; Genome; Glass; Microspheres; Plasmids; Rats; Reproducibility of Results; Sequence Analysis, DNA

Initial sequencing and comparative analysis of the mouse genome. - Waterston, Robert H; Lindblad-Toh, Kerstin; Birney, Ewan; Rogers, Jane; Abril, Josep F; Agarwal, Pankaj; Agarwala, Richa; Ainscough, Rachel; Alexandersson, Marina; An, Peter; Antonarakis, Stylianos E; Attwood, John; et al. (Nature, 2002)
The sequence of the mouse genome is a key informational tool for understanding the contents of the human genome and a key experimental tool for biomedical research. Here, we report the results of an international collaboration to produce a high-quality draft sequence of the mouse genome. We also present an initial comparative analysis of the mouse and human genomes, describing some of the insights that can be gleaned from the two sequences. We discuss topics including the analysis of the evolutionary forces shaping the size, structure and sequence of the genomes; the conservation of large-scale synteny across most of the genomes; the much lower extent of sequence orthology covering less than half of the genomes; the proportions of the genomes under selection; the number of protein-coding genes; the expansion of gene families related to reproduction and immunity; the evolution of proteins; and the identification of intraspecies polymorphism.
Keywords: Animals; Base Composition; Chromosomes, Mammalian; Conserved Sequence; CpG Islands; Evolution, Molecular; Gene Expression Regulation; Genes; Genetic Variation; Genome; Genome, Human; Genomics; Humans; Mice; Mice, Knockout; Mice, Transgenic; Models, Animal; Multigene Family; Mutagenesis; Neoplasms; Physical Chromosome Mapping; Proteome; Pseudogenes; Quantitative Trait Loci; Repetitive Sequences, Nucleic Acid; RNA, Untranslated; Selection, Genetic; Sequence Analysis, DNA; Sex Chromosomes; Species Specificity; Synteny

Loader Lite: a new software tool for the ABI PRISM 3700 DNA sequencer. - Scott, G B I; Steffen, D L; Edgar, D; Warren, J T; Kovár, C L; Steven E Scherer; Havlak, P H; Richard A Gibbs (Biotechniques, 2002)
Here we describe the development of a novel software tool entitled Loader Lite that generates plate records or sample sheetsfor the ABI PRISMs 3700 DNA sequencer. The major advantage of this program is that it enables the ongoing operation of sequencing instruments without reference to external network(s). The autonomous operation of sequencing instruments is critical if sample throughput is to be maintained during periods of network outage. Loader Lite employs a deliberate strategy of inputting anonymous tray barcodes at run time. After sequencing, the barcodes are reconciled with relevant project details by reference to a database. This software takes advantage of barcode scanning technology by creating plate records directly on the local computer, serving an individual sequencer, immediately before importing and linking. This real-time synthesis of the plate records at the point of loading all but eliminates loading errors. Loader Lite is user-friendly, fully configurable, and permits the running of partial or full 384-well sample trays, using any standard combinations of run modules, dye sets, mobility files, analysis modules, etc. The 96-well format is not supported; however, this capability will appear in subsequent versions that are currently under development. This application is designed as an added value, adjunct program to the regular ABI PRISM 3700 Data Collection software. We have successfully used Loader Lite over the past six months to load approximately 7 million sequencing reactions and believe its utility and functionality will prove to be attractive to the wider sequencing community.
Keywords: Sequence Analysis, DNA; Software; Statistics as Topic

Molecular evidence of HIV-1 transmission in a criminal case. - Metzker, Michael L; Mindell, David P; Liu, Xiao-Mei; Ptak, Roger G; Richard A Gibbs; Hillis, David M (Proc Natl Acad Sci U S A, 2002)
A gastroenterologist was convicted of attempted second-degree murder by injecting his former girlfriend with blood or blood-products obtained from an HIV type 1 (HIV-1)-infected patient under his care. Phylogenetic analyses of HIV-1 sequences were admitted and used as evidence in this case, representing the first use of phylogenetic analyses in a criminal court case in the United States. Phylogenetic analyses of HIV-1 reverse transcriptase and env DNA sequences isolated from the victim, the patient, and a local population sample of HIV-1-positive individuals showed the victim's HIV-1 sequences to be most closely related to and nested within a lineage comprised of the patient's HIV-1 sequences. This finding of paraphyly for the patient's sequences was consistent with the direction of transmission from the patient to the victim. Analysis of the victim's viral reverse transcriptase sequences revealed genotypes consistent with known mutations that confer resistance to AZT, similar to those genotypes found in the patient. A priori establishment of the patient and victim as a suspected transmission pair provided a clear hypothesis for phylogenetic testing. All phylogenetic models and both genes examined strongly supported the close relationship between the HIV-1 sequences of the patient and the victim. Resampling of blood from the suspected transmission pair and independent sequencing by different laboratories provided precaution against laboratory error.
Keywords: Base Sequence; Crime; Crime Victims; DNA, Viral; Female; Forensic Medicine; HIV Envelope Protein gp120; HIV Infections; HIV Reverse Transcriptase; HIV-1; Humans; Male; Molecular Sequence Data; Phylogeny; Sequence Analysis, DNA

Mutation screening of two candidate genes from 13q32 in families affected with Bipolar disorder: human peptide transporter (SLC15A1) and human glypican5 (GPC5). - Maheshwari, Manjula; Christian, S L; Liu, C; Badner, J A; Detera-Wadleigh, S; Gershon, E S; Richard A Gibbs (BMC Genomics, 2002)
BACKGROUND: Multiple candidate regions as sites for Schizophrenia and Bipolar susceptibility genes have been reported, suggesting heterogeneity of susceptibility genes or oligogenic inheritance. Linkage analysis has suggested chromosome 13q32 as one of the regions with evidence of linkage to Schizophrenia and, separately, to Bipolar disorder (BP). SLC15A1 and GPC5 are two of the candidate genes within an approximately 10-cM region of linkage on chromosome 13q32. In order to identify a possible role for these candidates as susceptibility genes, we performed mutation screening on the coding regions of these two genes in 7 families (n-20) affected with Bipolar disorder showing linkage to 13q32. RESULTS: Genomic organization revealed 23 exons in SLC15A1 and 8 exons in GPC5 gene respectively. Sequencing of the exons did not reveal mutations in the GPC5 gene in the 7 families affected with BP. Two polymorphic variants were discovered in the SLC15A1 gene. One was T to C substitution in the third position of codon encoding alanine at 1403 position of mRNA in exon 17, and the other was A to G substitution in the untranslated region at position 2242 of mRNA in exon 23. CONCLUSIONS: Mutation analysis of 2 candidate genes for Bipolar disorder on chromosome 13q32 did not identify any potentially causative mutations within the coding regions or splice junctions of the SLC15A1 or GPC5 genes in 7 families showing linkage to 13q32. Further studies of the regulatory regions are needed to completely exclude these genes as causative for Bipolar disorder.

PTPN11 mutations in Noonan syndrome type I: detection of recurrent mutations in exons 3 and 13. - Maheshwari, M; Belmont, J; Fernbach, S; Ho, T; Molinari, L; Yakub, I; Fuli Yu; Combes, A; Towbin, J; Craigen, W J; Richard A Gibbs (Hum Mutat, 2002)
We surveyed 16 subjects with the clinical diagnosis of Noonan Syndrome (NS1) from 12 families and their relevant family members for mutations in PTPN11/SHP2 using direct DNA sequencing. We found three different mutations among five families. Two unrelated subjects shared the same de novo missense substitution in exon 13 (S502T); an additional two unrelated families had a mutation in exon 3 (Y63C); and one subject had the amino acid substitution Y62D, also in exon 3. None of the three mutations were present in ethnically matched controls. In the mature protein model, the exon 3 mutants and the exon 13 mutant amino acids cluster at the interface between the N' SH2 domain and the phosphatase catalytic domain. Six of eight subjects with PTPN11/SHP2 mutations had pulmonary valve stenosis while no mutations were identified in those subjects (N = 4) with hypertrophic cardiomyopathy. An additional four subjects with possible Noonan syndrome were evaluated, but no mutations in PTPN11/SHP2 were identified. These results confirm that mutations in PTPN11/SHP2 underlie a common form of Noonan syndrome, and that the disease exhibits both allelic and locus heterogeneity. The observation of recurrent mutations supports the hypothesis that a special class of gain-of-function mutations in SHP2 give rise to Noonan syndrome.
Keywords: Catalytic Domain; DNA Mutational Analysis; Exons; Female; Humans; Intracellular Signaling Peptides and Proteins; Isoenzymes; Male; Mutation; Noonan Syndrome; Phenotype; Protein Structure, Quaternary; Protein Tyrosine Phosphatase, Non-Receptor Type 11; Protein Tyrosine Phosphatases; Recurrence; SH2 Domain-Containing Protein Tyrosine Phosphatases; src Homology Domains

A clone-array pooled shotgun strategy for sequencing large genomes. - Cai, W W; Chen, R; Richard A Gibbs; Bradley, A (Genome Res, 2001)
A simplified strategy for sequencing large genomes is proposed. Clone-Array Pooled Shotgun Sequencing (CAPSS) is based on pooling rows and columns of arrayed genomic clones, for shotgun library construction. Random sequences are accumulated, and the data are processed by sequential comparison of rows and columns to assemble the sequence of clones at points of intersection. Compared with either a clone-by-clone approach or whole-genome shotgun sequencing, CAPSS requires relatively few library constructions and only minimal computational power for a complete genome assembly. The strategy is suitable for sequencing large genomes for which there are no sequence-ready maps, but for which relatively high resolution STS maps and highly redundant BAC libraries are available. It is immediately applicable to the sequencing of mouse, rat, zebrafish, and other important genomes, and can be managed in a cooperative fashion to take advantage of a distributed international DNA sequencing capacity.
Keywords: Animals; Computer Simulation; Genome; Humans; Mice; Oligonucleotide Array Sequence Analysis; Software

Comparing vertebrate whole-genome shotgun reads to the human genome. - Chen, R; Bouck, J B; Weinstock, G M; Richard A Gibbs (Genome Res, 2001)
Multi-species sequence comparisons are a very efficient way to reveal conserved genes. Because sequence finishing is expensive and time consuming, many genome sequences are likely to stay incomplete. A challenge is to use these fragmented data for understanding the human genome. Methods for using cross-species whole-genome shotgun sequence (WGS) for genome annotation are described in this paper. About one-half million high-quality rat WGS reads (covering 7.5% of the rat genome) generated at the Baylor College of Medicine Human Genome Sequencing Center were compared with the human genome. Using computer-generated random reads as a negative control, a set of parameters was determined for reliable interpretation of BLAST search results. About 10% of the rat reads contain regions that are conserved in the human genomic sequence and about one-third of these include known gene-coding regions. Mapping the conserved regions to human chromosomes showed a 23-fold enrichment for coding regions compared with noncoding regions. This approach can also be applied to other mammalian genomes for gene finding. These data predicted approximately 42,500 genes in the human, slightly more than reported previously.
Keywords: Animals; Base Sequence; Computational Biology; Conserved Sequence; Databases, Genetic; Expressed Sequence Tags; Genome; Genome, Human; Heterochromatin; Humans; Mice; Molecular Sequence Data; Rats; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Species Specificity; Transcription, Genetic

A high-resolution map of human chromosome 12. - Montgomery, K T; Lee, E; Miller, A; Lau, S; Shim, C; Decker, J; Chiu, D; Emerling, S; Sekhon, M; Kim, R; Lenz, J; Han, J; et al. (Nature, 2001)
Our sequence-tagged site-content map of chromosome 12 is now integrated with the whole-genome fingerprinting effort. It provides accurate and nearly complete bacterial clone coverage of chromosome 12. We propose that this integrated mapping protocol serves as a model for constructing physical maps for entire genomes.
Keywords: Chromosomes, Artificial, Bacterial; Chromosomes, Human, Pair 12; Contig Mapping; Genome, Human; Humans; Sequence Tagged Sites

Initial sequencing and analysis of the human genome. - Lander, E S; Linton, L M; Birren, B; Nusbaum, C; Zody, M C; Baldwin, J; Devon, K; Dewar, K; Doyle, M; FitzHugh, W; Funke, R; Gage, D; et al. (Nature, 2001)
The human genome holds an extraordinary trove of information about human development, physiology, medicine and evolution. Here we report the results of an international collaboration to produce and make freely available a draft sequence of the human genome. We also present an initial analysis of the data, describing some of the insights that can be gleaned from the sequence.
Keywords: Animals; Chromosome Mapping; Conserved Sequence; CpG Islands; Databases, Factual; DNA Transposable Elements; Drug Industry; Evolution, Molecular; Forecasting; GC Rich Sequence; Gene Duplication; Genes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Human Genome Project; Humans; Mutation; Private Sector; Proteins; Proteome; Public Sector; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Species Specificity

A physical map of the human genome. - McPherson, J D; Marra, M; Hillier, L; Waterston, R H; Chinwalla, A; Wallis, J; Sekhon, M; Wylie, K; Mardis, E R; Wilson, R K; Fulton, R; Kucaba, T A; et al. (Nature, 2001)
The human genome is by far the largest genome to be sequenced, and its size and complexity present many challenges for sequence assembly. The International Human Genome Sequencing Consortium constructed a map of the whole genome to enable the selection of clones for sequencing and for the accurate assembly of the genome sequence. Here we report the construction of the whole-genome bacterial artificial chromosome (BAC) map and its integration with previous landmark maps and information from mapping efforts focused on specific chromosomal regions. We also describe the integration of sequence data with the map.
Keywords: Chromosomes, Artificial, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Gene Duplication; Genome, Human; Humans; In Situ Hybridization, Fluorescence; Repetitive Sequences, Nucleic Acid

A BAC-based physical map of the major autosomes of Drosophila melanogaster. - Hoskins, R A; Nelson, C R; Berman, B P; Laverty, T R; George, R A; Ciesiolka, L; Naeemuddin, M; Arenson, A D; Durbin, J; David, R G; Tabor, P E; Bailey, M R; et al. (Science, 2000)
We constructed a bacterial artificial chromosome (BAC)-based physical map of chromosomes 2 and 3 of Drosophila melanogaster, which constitute 81% of the genome. Sequence tagged site (STS) content, restriction fingerprinting, and polytene chromosome in situ hybridization approaches were integrated to produce a map spanning the euchromatin. Three of five remaining gaps are in repeat-rich regions near the centromeres. A tiling path of clones spanning this map and STS maps of chromosomes X and 4 was sequenced to low coverage; the maps and tiling path sequence were used to support and verify the whole-genome sequence assembly, and tiling path BACs were used as templates in sequence finishing.
Keywords: Animals; Centromere; Chromatin; Chromosomes, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genetic Markers; Genetic Vectors; Genome; In Situ Hybridization; Repetitive Sequences, Nucleic Acid; Restriction Mapping; Sequence Analysis, DNA; Sequence Tagged Sites; Telomere

Construction of a high-resolution physical map of the chromosome 10q22-q23 dilated cardiomyopathy locus and analysis of candidate genes. - Bowles, K R; Abraham, S E; Brugada, R; Zintz, C; Comeaux, J; Sorajja, D; Tsubata, S; Li, H; Brandon, L; Richard A Gibbs; Steven E Scherer; Bowles, N E; et al. (Genomics, 2000)
Dilated cardiomyopathy (DCM) is a major cause of morbidity and mortality and a leading cause of cardiac transplantation worldwide. Multiple loci and three genes encoding cardiac actin, desmin, and lamin A/C have been described for autosomal dominant DCM. Using recombination analysis, we have narrowed the 10q21-q23 locus to a region of approximately 4.1 cM. In addition, we have constructed a BAC contig, composed of 199 clones, which was used to develop a high-resolution physical map that contains the DCM critical region (approximately 3.9 Mb long). Seven genes, including ANX11, PPIF, DLG5, RPC155, RPS24, SFTPA1, and KCNMA1, have been mapped to the region of interest. RPC155, RPS24, SFTPA1, and KCNMA1 were excluded from further analysis based on their known functions and tissue-specific expression patterns. Mutational analysis of ANX11, DLG5, and PPIF revealed no disease-associated mutations. Multiple ESTs have also been mapped to the critical region.
Keywords: Cardiomyopathy, Dilated; Chromosomes, Bacterial; Chromosomes, Human, Pair 10; DNA Mutational Analysis; Expressed Sequence Tags; Family Health; Female; Genetic Predisposition to Disease; Genomic Library; Humans; Male; Pedigree; Phenotype; Physical Chromosome Mapping; Sequence Analysis, DNA

The genome sequence of Drosophila melanogaster. - Adams, M D; Celniker, S E; Holt, R A; Evans, C A; Gocayne, J D; Amanatides, P G; Steven E Scherer; Li, P W; Hoskins, R A; Galle, R F; George, R A; Lewis, S E; et al. (Science, 2000)
The fly Drosophila melanogaster is one of the most intensively studied organisms in biology and serves as a model system for the investigation of many developmental and cellular processes common to higher eukaryotes, including humans. We have determined the nucleotide sequence of nearly all of the approximately 120-megabase euchromatic portion of the Drosophila genome using a whole-genome shotgun sequencing strategy supported by extensive clone-based sequence and a high-quality bacterial artificial chromosome physical map. Efforts are under way to close the remaining gaps; however, the sequence is of sufficient accuracy and contiguity to be declared substantially complete and to support an initial analysis of genome structure and preliminary gene annotation and interpretation. The genome encodes approximately 13,600 genes, somewhat fewer than the smaller Caenorhabditis elegans genome, but with comparable functional diversity.
Keywords: Animals; Biological Transport; Chromatin; Cloning, Molecular; Computational Biology; Contig Mapping; Cytochrome P-450 Enzyme System; DNA Repair; DNA Replication; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genome; Heterochromatin; Insect Proteins; Nuclear Proteins; Protein Biosynthesis; Sequence Analysis, DNA; Transcription, Genetic

The human transcript database: a catalogue of full length cDNA inserts. - Bouck, J; McLeod, M P; Worley, K; Richard A Gibbs (Bioinformatics, 2000)
SUMMARY: Full length cDNA sequences are an important resource for the research community but are currently intermingled with other sequences. We have identified the human full length insert cDNA sequences in GenBank and placed them in a single location, the Human Transcript Database. AVAILIBILITY: The Human Transcript Database is available at http://www.hgsc.bcm.tms.edu/HTDB/. CONTACT: John Bouck: jbouck@bcm.tmc.edu
Keywords: Databases, Factual; DNA Transposable Elements; DNA, Complementary; Humans; RNA, Messenger

Intranasal immunization with HIV reverse transcriptase: effect of dose in the induction of helper T cell type 1 and 2 immunity. - Pacheco, S E; Richard A Gibbs; Ansari-Lari, A; Rogers, P (AIDS Res Hum Retroviruses, 2000)
HIV reverse transcriptase (RT) is immunologically recognized by the host after natural infection with HIV. To study the immune response to this nonenvelope protein and the effect of the antigen dose and the immunization route on the differential induction of cellular or humoral responses, CB6F1 mice were immunized intranasally with various doses of recombinant RT (0.025-25 microg/dose) in the presence of the mucosal adjuvant cholera toxin (CT). An antigen-specific, dose-dependent, in vitro proliferative response was observed in splenic cells from all mouse groups immunized with RT and CT. Proliferative responses in salivary gland-associated lymph node (SGALN) cells from the same mice were detected only with higher antigen dose immunizations (2.5, 25 microg/dose). IFN-gamma, a Th1-type cytokine, was detected in RT-stimulated culture supernatants from splenic and SGALN cells from all groups of mice immunized with RT and CT in a dose-dependent fashion. IL-4, a Th2-type cytokine, was detected in RT-stimulated culture supernatants from splenic and SGALN cells from mice immunized with higher doses of RT and CT. RT-specific IgG2a, a Th1-type-related antibody, was detected consistently in sera from all animals immunized with RT and CT and was predominant in mice immunized with lower antigen doses (0.025, 0.25 microg/dose). RT-specific IgG1, a Th2-type-related antibody, was detected consistently in mice immunized with higher antigen doses and was predominant in these groups. These studies demonstrate the immunogenicity of recombinant RT and the effect of the antigen dose in the induction of Th1-type and Th2-type immune responses after mucosal immunization.
Keywords: Administration, Intranasal; AIDS Vaccines; Animals; Cytokines; Dose-Response Relationship, Immunologic; Female; HIV Antibodies; HIV Reverse Transcriptase; Immunization; Immunoglobulin G; Lymph Nodes; Lymphocyte Activation; Mice; Recombinant Proteins; Salivary Glands; Spleen; Th1 Cells; Th2 Cells

PipMaker--a web server for aligning two genomic DNA sequences. - Schwartz, S; Zhang, Z; Frazer, K A; Smit, A; Riemer, C; Bouck, J; Richard A Gibbs; Hardison, R; Miller, W (Genome Res, 2000)
PipMaker (http://bio.cse.psu.edu) is a World-Wide Web site for comparing two long DNA sequences to identify conserved segments and for producing informative, high-resolution displays of the resulting alignments. One display is a percent identity plot (pip), which shows both the position in one sequence and the degree of similarity for each aligning segment between the two sequences in a compact and easily understandable form. Positions along the horizontal axis can be labeled with features such as exons of genes and repetitive elements, and colors can be used to clarify and enhance the display. The web site also provides a plot of the locations of those segments in both species (similar to a dot plot). PipMaker is appropriate for comparing genomic sequences from any two related species, although the types of information that can be inferred (e.g., protein-coding regions and cis-regulatory elements) depend on the level of conservation and the time and divergence rate since the separation of the species. Gene regulatory elements are often detectable as similar, noncoding sequences in species that diverged as much as 100-300 million years ago, such as humans and mice, Caenorhabditis elegans and C. briggsae, or Escherichia coli and Salmonella spp. PipMaker supports analysis of unfinished or "working draft" sequences by permitting one of the two sequences to be in unoriented and unordered contigs.
Keywords: Animals; Base Sequence; Caenorhabditis elegans; Computational Biology; DNA; Escherichia coli; Genes, Bacterial; Genes, Helminth; Genes, Protozoan; Humans; Internet; Mice; Molecular Sequence Data; Salmonella typhimurium; Sequence Alignment; Software

Shotgun sample sequence comparisons between mouse and human genomes. - Bouck, J B; Metzker, M L; Richard A Gibbs (Nat Genet, 2000)
A mixed 'clone-by-clone' and 'whole-genome shotgun' strategy will be used to determine the genomic sequence of the mouse. This method will allow a phase of rapid annotation of the contemporaneous human sequence draft, through whole-genome 'sample sequence comparisons'.
Keywords: Animals; Cloning, Molecular; Computational Biology; Female; Genome; Genomic Library; Humans; Mice; Mice, Inbred C57BL; Rats; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid

An allylic/acyclic adenosine nucleoside triphosphate for termination of DNA synthesis by DNA template-dependent polymerases. - Martinez, C I; Thoresen, L H; Richard A Gibbs; Burgess, K (Nucleic Acids Res, 1999)
An allylic adenosine triphosphate analog (AATP) was tested as a substrate for commercially available DNA polymerases. All but one of the enzymes assayed incorporated AATP opposite thymidine (T) with concomitant termination of the elongation reaction. A concentration of only 1 microM was sufficient for complete termination of the polymerization reaction for a short template mediated by Ampli Taq DNA polymerase FS (Taq FS). This result suggests that AATP could be used as a 2',3'-dideoxyadenosine-5'-triphosphate (ddA) surrogate. Kinetics of incorporation revealed that AATP was 48 times less efficiently incorporated than ddA. Furthermore, AATP was used in dye-primer sequencing as a substitute for ddA.
Keywords: Adenosine Triphosphate; Base Sequence; Boron Compounds; DNA; DNA Primers; DNA Replication; DNA-Directed DNA Polymerase; Fluorescent Dyes; Kinetics; Substrate Specificity; Templates, Genetic

Comparison of gene indexing databases. - Bouck, J; Yu, W; Richard A Gibbs; Kim C Worley (Trends Genet, 1999)
Keywords: Abstracting and Indexing; Alternative Splicing; Cluster Analysis; Databases, Factual; DNA, Complementary; Expressed Sequence Tags; Genome, Human; Humans

Somatic sequence variation at the Friedreich ataxia locus includes complete contraction of the expanded GAA triplet repeat, significant length variation in serially passaged lymphoblasts and enhanced mutagenesis in the flanking sequence. - Bidichandani, S I; Purandare, S M; Taylor, E E; Gumin, G; Machkhas, H; Harati, Y; Richard A Gibbs; Ashizawa, T; Patel, P I (Hum Mol Genet, 1999)
The vast majority of Friedreich ataxia patients are homozygous for large GAA triplet repeat expansions in intron 1 of the X25 gene. Instability of the expanded GAA repeat was examined in 23 chromosomes bearing 97-1250 triplets in lymphoblastoid cell lines passaged 20-39 times. Southern analyses revealed 18 events of significant changes in length ranging from 69 to 633 triplets, wherein the de novo allele gradually replaced the original over 1-6 passages. Contractions and expansions occurred with equal frequency and magnitude. This behavior is unique in comparison with other large, non-coding triplet repeat expansions [(CGG)(n)and (CTG)(n)] which remain relatively stable under similar conditions. We also report a rare patient who, having inherited two expanded alleles, showed evidence of contracted GAA repeats ranging from nine to 29 triplets in DNA from two independent peripheral blood samples. The GAA triplet repeat is known to adopt a triplex structure, and triplexes in transcribed templates cause enhanced mutagenesis. The poly(A) tract and a 135 bp sequence, both situated immediately upstream of the GAA triplet repeat, were therefore examined for somatic mutations. The poly(A) tract showed enhanced instability when in cis with the GAA expansion. The 135 bp upstream sequence was found to harbor a 3-fold excess of point mutations in DNA derived from individuals homozygous for the GAA triplet repeat expansion compared with normal controls. These data are likely to have important mechanistic and clinical implications.
Keywords: Base Sequence; Cells, Cultured; DNA Mutational Analysis; Frataxin; Friedreich Ataxia; Humans; Iron-Binding Proteins; Lymphocyte Activation; Lymphocytes; Molecular Sequence Data; Phosphotransferases (Alcohol Group Acceptor); Poly A; Trinucleotide Repeat Expansion

The weed paves the way. - Richard A Gibbs (Nat Genet, 1999)
Keywords: Arabidopsis; Genome, Plant; Physical Chromosome Mapping; Sequence Tagged Sites

Analysis of the quality and utility of random shotgun sequencing at low redundancies. - Bouck, J; Miller, W; Gorrell, J H; Donna M Muzny; Richard A Gibbs (Genome Res, 1998)
The currently favored approach for sequencing the human genome involves selecting representative large-insert clones (100-200 kb), randomly shearing this DNA to construct shotgun libraries, and then sequencing many different isolates from the library. This method, entitled directed random shotgun sequencing, requires highly redundant sequencing to obtain a complete and accurate finished consensus sequence. Recently it has been suggested that a rapidly generated lower redundancy sequence might be of use to the scientific community. Low-redundancy sequencing has been examined previously using simulated data sets. Here we utilize trace data from a number of projects submitted to GenBank to perform reconstruction experiments that mimic low-redundancy sequencing. These low-redundancy sequences have been examined for the completeness and quality of the consensus product, information content, and usefulness for interspecies comparisons. The data presented here suggest three different sequencing strategies, each with different utilities. (1) Nearly complete sequence data can be obtained by sequencing a random shotgun library at sixfold redundancy. This may therefore represent a good point to switch from a random to directed approach. (2) Sequencing can be performed with as little as twofold redundancy to find most of the information about exons, EST hits, and putative exon similarity matches. (3) To obtain contiguity of coding regions, sequencing at three- to fourfold redundancy would be appropriate. From these results, we suggest that a useful intermediate product for genome sequencing might be obtained by three- to fourfold redundancy. Such a product would allow a large amount of biologically useful data to be extracted while postponing the majority of work involved in producing a high quality consensus sequence.
Keywords: Animals; Contig Mapping; Expressed Sequence Tags; Gene Library; Genome, Human; Humans; Mice; Quality Control; Retrospective Studies; Sequence Analysis, DNA

Comparative sequence analysis of a gene-rich cluster at human chromosome 12p13 and its syntenic region in mouse chromosome 6. - Ansari-Lari, M A; Oeltjen, J C; Schwartz, S; Zhang, Z; Donna M Muzny; Lu, J; Gorrell, J H; Chinault, A C; Belmont, J W; Miller, W; Richard A Gibbs (Genome Res, 1998)
The Human Genome Project has created a formidable challenge: the extraction of biological information from extensive amounts of raw sequence. With the increasing availability of genomic sequence from other species, one approach to extracting coding and regulatory element information is through cross-species sequence comparison. To assess the strengths and weaknesses of this methodology for large-scale sequence analysis, 227 kb of mouse sequence syntenic to a gene-rich cluster on human chromosome 12p13 was obtained. Primarily through percent identity plots (PIPs) of SIM comparative sequence alignments, the sequence of coding regions, putative alternative exons, conserved noncoding regions, and correlation in repetitive element insertions were easily determined. The analysis demonstrated that the number, order, and orientation of all 17 genes are conserved between the two species, whereas two human pseudogenes are absent in mouse. In addition, apart from MIRs, no direct correlation of distribution or position of the majority of repetitive elements between the two species is seen. Finally, in examining the synonymous and nonsynonymous substitution rates in the conserved genes, a large variation in nonsynonymous rates is observed indicating that the genes in this region are diverging at different rates. This study indicates the utility and strength of large-scale cross-species sequence comparisons in the extraction of biological information from raw sequence, especially when combined with other computational tools such as GRAIL and BLAST.
Keywords: Amino Acid Sequence; Animals; Chromosome Mapping; Chromosomes; Chromosomes, Human, Pair 12; Conserved Sequence; Humans; Mice; Molecular Sequence Data; Multigene Family; Repetitive Sequences, Nucleic Acid; Sequence Alignment; Sequence Analysis, DNA

DNA deletion confined to the iduronate-2-sulfatase promoter abolishes IDS gene expression. - Timms, K M; Huckett, L E; Belmont, J W; Shapira, S K; Richard A Gibbs (Hum Mutat, 1998)
Deficiency of the enzyme iduronate-2-sulfatase (IDS) results in Hunter syndrome, an X-linked recessive lysosomal storage disorder. In this study, analysis of a patient with features of moderate to severe Hunter syndrome identified a 178-bp deletion upstream of IDS exon 1 spanning a predicted promoter element. Sequencing of all nine IDS exons from this patient failed to identify any additional mutations within the coding regions or in intron-exon boundaries. The 178-bp deletion is flanked by two 13-bp direct repeats and potential DNA topoisomerase II recognition sites. These findings point toward nonhomologous recombination as a possible mechanism for this mutation. Expression studies on this patient do not detect any IDS transcripts, indicating that the deletion spans sequences essential for IDS expression. Complete lack of expression of IDS is consistent with the moderate to severe phenotype observed in this patient.
Keywords: Base Sequence; Child, Preschool; DNA Mutational Analysis; Gene Expression Regulation; Humans; Iduronate Sulfatase; Male; Molecular Sequence Data; Mucopolysaccharidosis II; Pedigree; Phenotype; Promoter Regions, Genetic; Sequence Analysis, DNA; Sequence Deletion

Elimination of residual natural nucleotides from 3'-O-modified-dNTP syntheses by enzymatic mop-up. - Metzker, M L; Raghavachari, R; Burgess, K; Richard A Gibbs (Biotechniques, 1998)
Here, we describe a novel strategy called enzymatic "Mop-Up" that efficiently removes contaminating dNTPs from reverse-phase, high-performance liquid chromatography (RP-HPLC) purified 3'-O-modified dNTP syntheses. Enzymatic mop-up takes advantage of the high selectivity of DNA polymerases for the former nucleoside triphosphates over the latter nucleotide analogs. We demonstrate the selective removal of contaminating dATP and dTTP from RP-HPLC purified 3'-O-methyl-dATP and 3'-O-(2-nitrobenzyl)-dTTP syntheses, respectively. These data highlight the importance of natural nucleotide contamination when interpreting enzymatic incorporation data and provide an alternative hypothesis for the observed property of catalytic editing of DNA polymerases. Moreover, the effective removal of natural nucleotides from 3'-O-modified analogs addresses the important issue of nucleotide read-through for stop-start DNA sequencing strategies, such as the base addition sequencing scheme (BASS).
Keywords: Base Sequence; Chromatography, High Pressure Liquid; Deoxyribonucleotides; DNA; DNA-Directed DNA Polymerase

The genomic organization of Isopeptidase T-3 (ISOT-3), a new member of the ubiquitin specific protease family (UBP). - Timms, K M; Ansari-Lari, M A; Morris, W; Brown, S N; Richard A Gibbs (Gene, 1998)
A novel Isopeptidase T gene (ISOT-3) has been identified on human mosome 3q26.2--q26.3. gene shows 67.3% nucleotide identity and 54.8% amino acid identity to n Isopeptidase (ISOT-1). Northern blot analysis has shown that ISOT-3 is highly essed in ovary and testes, low-level expression in six other tissues tested. In contrast, ISOT-1 is essed at high levels in brain, and there is no detectable expression in ovary. The exonic nization of these two genes highly conserved with only one variant intron position. Intron 15 in -3 is absent in ISOT-1, there is an alternate splice site at the same location. Although the --intron structure has been erved between the two genes, ISOT-3 has significantly larger intronic ons, and the overall of this gene is at least 90 kb compared to 15 kb for ISOT-1. These data suggest that both ISOT-1 and ISOT-3 have descended from a common ancestor. In addition, the low overall sequence identity and different expression patterns may reflect differences in substrate specificity.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Carbon-Nitrogen Lyases; Chromosome Mapping; Chromosomes, Human, Pair 3; Consensus Sequence; DNA, Complementary; Exons; Female; Gene Library; Humans; Male; Mice; Molecular Sequence Data; Organ Specificity; Ovary; Polymerase Chain Reaction; Recombinant Proteins; Saccharomyces cerevisiae; Sequence Alignment; Sequence Homology, Amino Acid; Substrate Specificity; Testis; Ubiquitins

Quantitation of mixed-base populations of HIV-1 variants by automated DNA sequencing with BODIPY dye-labeled primers. - Metzker, M L; Ansari-Lari, M A; Liu, X M; Holder, D J; Richard A Gibbs (Biotechniques, 1998)
Direct DNA sequencing of human immunodeficiency virus type 1 (HIV-1) pol and env gene regions was characterized for accuracy and precision. Restricted maximum likelihood (REML) analysis of molecular clone reconstruction experiments using a primer-walking strategy showed that the BODIPY and BODIPY energy-transfer (BET) dye primers sets were significantly more accurate in quantitating heterogenous base mixtures than the fluorescein/rhodamine dye primers. Of the three sets examined, the BET dye primers were the most accurate. The improved accuracy correlated with the reduced emission band-widths of BODIPY and BET dye primers and the more uniform signal intensities of BET dye primers. However, comparing % coefficients of variation (CV) for the three dye primer sets, revealed that BODIPY dye primers gave better precision than both BET and fluorescein/rhodamine dye primer sets. Several sequence-dependent motifs were identified that showed specific nucleotide-biased incorporation and were determined to be the major variable component of the total %CV. Taken together, these results show that BODIPY and BET direct DNA sequencing can accurately and precisely characterize complex mixed-base populations.
Keywords: Boron Compounds; DNA Primers; DNA, Viral; DNA-Directed DNA Polymerase; Genes, env; Genes, pol; Genetic Heterogeneity; Genetic Variation; Genome, Viral; HIV Envelope Protein gp120; HIV-1; Humans; Reproducibility of Results; Sequence Analysis, DNA

Reassessment of biochemically determined Hunter syndrome carrier status by DNA testing. - Timms, K M; Edwards, F J; Belmont, J W; Yates, J R; Richard A Gibbs (J Med Genet, 1998)
Deficiency of iduronate-2-sulphatase (IDS) results in the X linked recessive lysosomal storage disorder Hunter syndrome. Determination of carrier status in families affected by this disorder has been performed using a variety of enzymatic tests. None of these tests has proved to be 100% effective at identifying carriers. The aim of this study was to perform carrier testing in a family affected by the disorder, where testing was complicated by the fact that no surviving affected subjects were available for study. Direct dye primer sequencing of PCR products was used to identify mixed bases in an obligate carrier. Two mixed bases were observed within exon VIII. The first base change (T-->A) at nucleotide position 1150 results in a missense mutation (H342Q), while the second base change (G-->T) at nucleotide position 1151 results in a nonsense mutation (G343X). Four additional female family members were screened for the same mutation. Using this approach it is possible to provide unambiguous information about a subject's carrier status and, unlike biochemical testing, this approach will be equally effective when applied to families with the mild form of this disorder.
Keywords: DNA; Female; Heterozygote; Humans; Iduronate Sulfatase; Male; Mucopolysaccharidosis II; Pedigree

Using BODIPY dye-primer chemistry in large-scale sequencing. - Donna M Muzny; Metzker, M L; Bouck, J; Gorrell, J H; Ding, Y; Maxim, E; Richard A Gibbs (IEEE Eng Med Biol Mag, 1998)
Keywords: Boron Compounds; Chromosome Mapping; DNA Primers; Drug Storage; Fluorescent Dyes; Humans; Quality Control; Reproducibility of Results; Robotics; Sequence Analysis, DNA

The extent of genetic variation in the CCR5 gene. - Ansari-Lari, M A; Liu, X M; Metzker, M L; Rut, A R; Richard A Gibbs (Nat Genet, 1997)
Keywords: Alleles; Base Composition; Ethnicity; Gene Frequency; Genetic Variation; Heterozygote; Homozygote; Humans; Mutation; Receptors, CCR5; Receptors, Cytokine; Receptors, HIV; Sequence Analysis, DNA

Hares and tortoises in the race to sequence the human genome: expectations and realities. - Richard A Gibbs (Trends Genet, 1997)
Keywords: Human Genome Project; Humans; Polymerase Chain Reaction; Sequence Alignment; Sequence Analysis, DNA; Sequence Tagged Sites; Software

The human COX10 gene is disrupted during homologous recombination between the 24 kb proximal and distal CMT1A-REPs. - Reiter, L T; Murakami, T; Koeuth, T; Richard A Gibbs; James R Lupski (Hum Mol Genet, 1997)
The CMT1A-REPs are two large directly repeating DNA sequences located on chromosome 17p11.2-p12 flanking the region duplicated in patients with Charcot-Marie-Tooth disease type 1A (CMT1A) and deleted in patients with hereditary neuropathy with liability to pressure palsies (HNPP). We have sequenced two cosmids, c74F4 and c15H12, which contain the entire proximal and distal CMT1A-REPs and determined that these repeats are approximately 99% identical across a 24,011 bp region. In addition, both contain an exon of the human heme A:farnesyltransferase gene (COX10). Hybridization studies revealed that COX10 spans the distal CMT1A-REP, while the proximal CMT1A-REP contains an isolated COX10 'pseudo-exon'. There is also a COX10 hybridization signal on chromosome 10 which appears to represent a processed pseudogene. We propose that the distal CMT1A-REP represents the progenitor copy of COX10 exon VI which was duplicated with surrounding intronic sequences during mammalian genome evolution and that the HNPP deletion results in a COX10 null allele.
Keywords: Alkyl and Aryl Transferases; Base Sequence; Blotting, Southern; Centromere; Charcot-Marie-Tooth Disease; Chromosomes, Human, Pair 17; Electron Transport Complex IV; Exons; Humans; Membrane Proteins; Molecular Sequence Data; Nucleic Acid Hybridization; Restriction Mapping; Sequence Homology, Nucleic Acid; Telomere

Large-scale comparative sequence analysis of the human and murine Bruton's tyrosine kinase loci reveals conserved regulatory domains. - Oeltjen, J C; Malley, T M; Donna M Muzny; Miller, W; Richard A Gibbs; Belmont, J W (Genome Res, 1997)
Large-scale genomic DNA sequencing of orthologous and paralogous loci in different species should contribute to a basic understanding of the evolution of both the protein-coding regions and noncoding regulatory elements. We compared 93 kb of human sequence to 89 kb of mouse sequence in the Bruton's tyrosine kinase (BTK) region. In addition to showing the conservation of both position and orientation of the five functionally unrelated genes in the region (BTK, alpha-D-galactosidase A, L44L, FTP-3, and FCI-12), the comparison revealed conservation of clusters of noncoding sequence flanking the first exon of each gene. Furthermore, in the sequence comparison at the BTK locus, the conservation of clusters of noncoding sequence extends throughout the locus; the noncoding sequence is more highly conserved in the BTK locus in comparison to the flanking loci. This suggests a correlation with the complex developmental regulation of expression of btk. To determine whether a highly conserved 3.5-kb segment flanking the first exon of BTK contains transcriptional regulatory signals, we tested various portions of the segment for promoter and expression activity in several appropriate cell lines. The results demonstrate the contribution of the conserved region flanking the first exon to the cell lineage-specific expression pattern of btk. These data show the usefulness of large scale sequence comparisons to focus investigation on regions of noncoding sequence that play essential roles in complex gene regulation.
Keywords: Agammaglobulinaemia Tyrosine Kinase; alpha-Galactosidase; Animals; Base Sequence; Conserved Sequence; Enhancer Elements, Genetic; Genetic Variation; Humans; Mice; Models, Genetic; Molecular Sequence Data; Promoter Regions, Genetic; Protein-Tyrosine Kinases; Recombinant Proteins; Regulatory Sequences, Nucleic Acid; Repetitive Sequences, Nucleic Acid; Sequence Alignment; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Transcription Factors; Transcription, Genetic; Transfection

Large-scale sequencing in human chromosome 12p13: experimental and computational gene structure determination. - Ansari-Lari, M A; Shen, Y; Donna M Muzny; Lee, W; Richard A Gibbs (Genome Res, 1997)
The detailed genomic organization of a gene-dense region at human chromosome 12p13, spanning 223 kb of contiguous sequence, was determined. This region is composed of 20 genes and several other expressed sequences. Experimental tools including RT-PCR and cDNA sequencing, combined with gene prediction programs, were utilized in the analysis of the sequence. Various computer software programs were employed for sequence similarity searches and functional predictions. The high number of genes with diverse functions and complex transcriptional patterns make this region ideal for addressing challenges of gene discovery and genomic characterization amenable to large-scale sequence analysis.
Keywords: Alternative Splicing; Amino Acid Sequence; Chromosome Mapping; Chromosomes, Human, Pair 12; Computational Biology; DNA, Complementary; Exons; Gene Expression; Genomic Library; Glycolysis; Humans; Introns; Molecular Sequence Data; Multigene Family; Nerve Tissue Proteins; Polymerase Chain Reaction; RNA-Directed DNA Polymerase; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Signal Transduction; Software

Molecular and phenotypic variation in patients with severe Hunter syndrome. - Timms, K M; Bondeson, M L; Ansari-Lari, M A; Lagerstedt, K; Donna M Muzny; Dugan-Rocha, S P; Nelson, D L; Pettersson, U; Richard A Gibbs (Hum Mol Genet, 1997)
Severe Hunter syndrome is a fatal X-linked lysosomal storage disorder caused by iduronate-2-sulphatase (IDS) deficiency. Patients with complete deletion of the IDS locus often have atypical phenotypes including ptosis, obstructive sleep apnoea, and the occurrence of seizures. We have used genomic DNA sequencing to identify several new genes in the IDS region. DNA deletion patients with atypical symptoms have been analysed to determine whether these atypical symptoms could be due to involvement of these other loci. The occurrence of seizures in two individuals correlated with a deletion extending proximal of IDS, up to and including part of the FMR2 locus. Other (non-seizure) symptoms were associated with distal deletions. In addition, a group of patients with no variant symptoms, and a characteristic rearrangement involving a recombination between the IDS gene and an adjacent IDS pseudogene (IDS psi), showed normal expression of loci distal to IDS. Together, these results identify FMR2 as a candidate gene for seizures, when mutated along with IDS.
Keywords: Chromosome Mapping; Cloning, Molecular; Electrophoresis, Agar Gel; Gene Deletion; Gene Expression; Gene Rearrangement; Humans; Iduronate Sulfatase; Male; Molecular Sequence Data; Mucopolysaccharidosis II; Nuclear Proteins; Phenotype; Polymerase Chain Reaction; Proteins; Pseudogenes; Recombination, Genetic; Seizures; Trans-Activators; X Chromosome

Sequencing and functional analysis of the SNRPN promoter: in vitro methylation abolishes promoter activity. - Huq, A H; Sutcliffe, J S; Nakao, M; Shen, Y; Richard A Gibbs; Beaudet, A L (Genome Res, 1997)
The gene encoding the small nuclear ribonucleoprotein-associated polypeptide N (SNRPN) maps to the Prader-Willi syndrome critical region on chromosome 15 and is expressed preferentially from the paternal allele. A CpG island encompassing the first exon of SNRPN is methylated on the inactive maternal allele. DNA sequence was determined for a cosmid containing the first three exons of SNRPN and extending 20 kb upstream and 15 kb downstream from the CpG island. This region is extremely rich in Alu elements and other repetitive sequences and contains a single CpG island, which includes numerous short direct repeat sequences. Functional analysis of the first exon revealed strong promoter activity for a 260-bp fragment extending 207 bp upstream from the exon. In vitro methylation of this 260-bp fragment abolished promoter activity completely, suggesting that the silencing of the maternal SNRPN allele may be a direct consequence of methylation of the promoter region.
Keywords: Alleles; Autoantigens; Cells, Cultured; Chromosomes, Human, Pair 15; Cloning, Molecular; CpG Islands; DNA Methylation; DNA-Cytosine Methylases; Exons; Gene Expression; HeLa Cells; Humans; Methylation; Molecular Sequence Data; Polymerase Chain Reaction; Prader-Willi Syndrome; Promoter Regions, Genetic; Repetitive Sequences, Nucleic Acid; Ribonucleoproteins, Small Nuclear; Sequence Analysis, DNA; snRNP Core Proteins; Transfection

Simultaneous shotgun sequencing of multiple cDNA clones. - Andersson, B; Lu, J; Shen, Y; Wentland, M A; Richard A Gibbs (DNA Seq, 1997)
This study describes an efficient method for the rapid sequencing of DNA fragments in the size range 1-5 kb. Individual fragments, here cDNA inserts, are purified by restriction enzyme digestion and gel purification, pooled and concatenated by ligation. The concatamers are sheared and cloned randomly into M13, followed by random sequencing. The sequences of the individual cDNA inserts are obtained at the assembly stage using restriction enzyme sites as "tags' for the ends of each fragment. In this study the sequencing of two libraries containing 7 and 16 cDNA inserts with an average length of 2.5 kb is described. The results show that of the shotgun sequencing of large fragments, and that the method compares favorably to alternative strategies, such as primer walking.
Keywords: Animals; Cloning, Molecular; DNA, Complementary; Drosophila; Gene Expression; Gene Library; Restriction Mapping; Sequence Analysis, DNA

Test of the potential of a dATP surrogate for sequencing via MALDI-MS. - Jacutin, S; Zhang, A J; Russell, D H; Richard A Gibbs; Burgess, K (Nucleic Acids Res, 1997)
1-(2'-Deoxy-beta-d-ribofuranosyl)-3-nitropyrrole phosphate was incorporated into a DNA decamer and analyzed via matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS). The extent and composition of the various fragment peaks were compared with those in the MALDI-MS spectrum of dT4AT5. The nitropyrrole-containing oligomer proved to be more robust. Two different DNA template assays were then used to attempt to identify DNA replicating enzymes that would incorporate the corresponding triphosphate, i.e. 1-(2'-deoxy-beta-d-ribofuranosyl)-3-nitropyrrole triphosphate (dXTP). It was shown that dXTP was not incorporated by some enzymes and it inhibited others. However, DNA polymerase I Klenow fragment and avian myeloblastosis virus reverse transcriptase incorporated dXTP in place of dATP and then replicated the template overhang in the usual way. The potential of dXTP as a surrogate for dATP in DNA sequencing with MALDI-MS analysis is discussed.
Keywords: Deoxyadenine Nucleotides; DNA Polymerase I; DNA-Directed DNA Polymerase; Mass Spectrometry; Nucleotides; Pyrroles; Retroviridae; RNA-Directed DNA Polymerase; Sequence Analysis, DNA; Substrate Specificity; Taq Polymerase; Templates, Genetic

A "double adaptor" method for improved shotgun library construction. - Andersson, B; Wentland, M A; Ricafrente, J Y; Liu, W; Richard A Gibbs (Anal Biochem, 1996)
The efficiency of shotgun DNA sequencing depends to a great extent on the quality of the random-subclone libraries used. We here describe a novel "double adaptor" strategy for efficient construction of high-quality shotgun libraries. In this method, randomly sheared and end-repaired fragments are ligated to oligonucleotide adaptors creating 12-base overhangs. Nonphosphorylated oligonucleotides are used, which prevents formation of adaptor dimers and ensures efficient ligation of insert to adaptor. The vector is prepared from a modified M13 vector, by KpnI/PstI digestion followed by ligation to oligonucleotides with ends complementary to the overhangs created in the digest. These adaptors create 5'-overhangs complementary to those on the inserts. Following annealing of insert to vector, the DNA is directly used for transformation without a ligation step. This protocol is robust and shows three- to fivefold higher yield of clones compared to previous protocols. No chimeric clones can be detected and the background of clones without an insert is <1%. The procedure is rapid and shows potential for automation.
Keywords: Base Sequence; Cloning, Molecular; Genetic Vectors; Genomic Library; Humans; Molecular Sequence Data; Oligonucleotides; Polymerase Chain Reaction; X Chromosome

Duplication of a gene-rich cluster between 16p11.1 and Xq28: a novel pericentromeric-directed mechanism for paralogous genome evolution. - Eichler, E E; Lu, F; Shen, Y; Antonacci, R; Jurecic, V; Doggett, N A; Moyzis, R K; Baldini, A; Richard A Gibbs; Nelson, D L (Hum Mol Genet, 1996)
We have identified a 26.5 kb gene-rich duplication shared by human Xq28 and 16p11.1. Complete comparative sequence analysis of cosmids from both loci has revealed identical Xq28 and 16p11.1 genomic structures for both the human creatine transporter gene (SLC6A8) and five exons of the CDM gene (DXS1357E). Overall nucleotide similarity within the duplication was found to be 94.6%, suggesting that this interchromosomal duplication occurred within recent evolutionary time (7-10 mya). Based on comparisons between genomic and cDNA sequence, both the Xq28 creatine transporter and DXS1357E genes are transcriptionally active. Predicted translation of exons and RT-PCR analysis reveal that chromosome 16 paralogs likely represent pseudogenes. Comparative fluorescent in situ hybridization (FISH) analyses of chromosomes from various primates indicate that this gene-rich segment has undergone several duplications. In gorilla and chimpanzee, multiple pericentromeric localizations on a variety of chromosomes were found using probes from the duplicated region. In other species, such as the orangutan and gibbon, FISH signals were only identified at the distal end of the X chromosome, suggesting that the Xq28 locus represents the ancestral copy. Sequencing of the 16p 11.1/Xq28 duplication breakpoints has revealed the presence of repetitive immunoglobulin-like CAGGG pentamer sequences at or near the paralogy boundaries. The mobilization and dispersal of this gene-rich 27 kb element to the pericentromeric regions of primate chromosomes defines an unprecedented form of recent genome evolution and a novel mechanism for the generation of genetic diversity among closely related species.
Keywords: Animals; Base Sequence; Carrier Proteins; Centromere; Chromosome Mapping; Chromosomes, Human, Pair 16; Cosmids; Creatine; Evolution, Molecular; Exons; Hominidae; Humans; Hylobates; Membrane Proteins; Membrane Transport Proteins; Models, Genetic; Molecular Sequence Data; Multigene Family; Proteins; Repetitive Sequences, Nucleic Acid; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; X Chromosome

Electrophoretically uniform fluorescent dyes for automated DNA sequencing. - Metzker, M L; Lu, J; Richard A Gibbs (Science, 1996)
A class of dyes, BODIPY fluorophores, has been identified for automated DNA sequencing that has improved spectral characteristics compared with conventional fluorescein and rhodamine dyes. Single and double BODIPY dye primers were characterized in commercially available DNA sequencers and showed uniform electrophoretic mobilities and high fluorescence intensities. The improved physical properties of BODIPY dye primers were demonstrated by direct base-calling from the unprocessed fluorescent signals and improved heterozygote analyses of mixed-base populations. The high sensitivity of BODIPY dye primers requires at least 33 percent less reagent consumed per reaction than conventional dye primers, which should affect the costs of large genome-sequencing efforts.
Keywords: Autoanalysis; Base Sequence; Boron Compounds; DNA Primers; Electrophoresis, Polyacrylamide Gel; Fluorescent Dyes; Molecular Sequence Data; Sensitivity and Specificity; Sequence Analysis, DNA; Spectrometry, Fluorescence

Expression of human immunodeficiency virus type 1 reverse transcriptase in trans during virion release and after infection. - Ansari-Lari, M A; Richard A Gibbs (J Virol, 1996)
The normal reverse transcription of retroviral RNA is a complex process which depends on the orchestration of several steps throughout the virus life cycle. During the assembly of retroviruses, reverse transcriptase (RT) is directed into the virion as a component of the Gag-Pol polyprotein. In the maturation of the Gag-Pol polyprotein of human immunodeficiency virus type 1 (HIV-1), cleavage by the viral protease occurs during viral budding. After infection, reverse transcription of viral RNA into double-stranded DNA is completed in the cytoplasm of the infected cell. In this study, the processing and reverse transcription of HIV-1 have been examined by separate expression of mature HIV-1 RT and proviral molecules bearing RT mutations. The effects of RT expression in trans during virion release and after viral entry were investigated. Constitutive expression of HIV-1 RT was established in CD4- and non-CD4-expressing cells via the coexpression of its individual subunits, and three HIV-1 RT mutant constructs were generated. The results indicate that a bona fide RT trans complementation does not occur during virion release or after infection. However, after infection of an RT-expressing cell with a high titer RT-defective virus, intracellular reverse transcription can be detected.
Keywords: Base Sequence; Cell Line; Fusion Proteins, gag-pol; HIV Long Terminal Repeat; HIV Reverse Transcriptase; HIV-1; Molecular Sequence Data; Mutation; Retroelements; RNA-Directed DNA Polymerase; Virion; Virus Assembly

A gene-rich cluster between the CD4 and triosephosphate isomerase genes at human chromosome 12p13. - Ansari-Lari, M A; Donna M Muzny; Lu, J; Lu, F; Lilley, C E; Spanos, S; Malley, T; Richard A Gibbs (Genome Res, 1996)
The genomic sequence of the human CD4 gene and its neighboring region, located at chromosome 12p13, was generated using the large-scale shotgun sequencing strategy. A total of 117 kb of genomic sequence and approximately 11 kb of cDNA sequence were obtained. Six genes, including CD4, triosephosphate isomerase, B3 subunit of G proteins (GNB3), and ubiquitin isopeptidase T (ISOT), with known functions, and two new genes with unknown functions were identified. Using a battery of strategies, the exon/intron boundaries, splice variants, and tissue expression patterns of the genes were determined. Various computer software was utilized for analyses of the DNA and amino acid sequences. The results of the analyses and sequence-based strategies for gene identification are discussed.
Keywords: Alternative Splicing; Amino Acid Sequence; Base Sequence; CD4 Antigens; Chromosome Mapping; Chromosomes, Human, Pair 12; DNA, Complementary; Humans; Molecular Sequence Data; Multigene Family; Sequence Homology, Amino Acid; Triose-Phosphate Isomerase

Genomic organization of the mouse double minute 2 gene. - Jones, S N; Ansari-Lari, M A; Hancock, A R; Jones, W J; Richard A Gibbs; Donehower, L A; Bradley, A (Gene, 1996)
Transfection of the mouse double minute 2 (Mdm2) oncogene has been found to induce immortalization of primary cells and to transform cultured cells. Amplification and/or overexpression of human MDM2 has been documented in a large percentage of human cancers. Mouse and human Mdm2 cDNA have been cloned from transformed cells and the cDNA sequence of both genes have been reported previously. In this report, we present the gene structure of mouse Mdm2. Comparison of the coding sequences of the Mdm2 gene with the previously reported cDNA sequence and with Mdm2 sequences obtained from an Mdm2-bearing cosmid clone capable of inducing transformation revealed that the reported cDNA sequence was in error, and that Mdm2-induced transformation of cells does not require an activating mutation in Mdm2. Ligation-anchor PCR analysis of transcripts produced from the P1 and P2 promoters indicates that transcription initiates at sites upstream of those reported previously for both promoters.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Genome; Mice; Molecular Sequence Data; Nuclear Proteins; Promoter Regions, Genetic; Proto-Oncogene Proteins; Proto-Oncogene Proteins c-mdm2; Proto-Oncogenes; Transcription, Genetic

Identification of FMR2, a novel gene associated with the FRAXE CCG repeat and CpG island. - Gu, Y; Shen, Y; Richard A Gibbs; Nelson, D L (Nat Genet, 1996)
Five folate-sensitive fragile sites have been identified at the molecular level to date. Each is characterized by an expanded and methylated trinucleotide repeat CGG (CCG). Of the three X chromosome sites, FRAXA, FRAXE and FRAXF, the former two are associated with mental retardation in their expanded forms. FRAXA expansion results in fragile X syndrome due to down regulation of expression of the FMR1 gene, which carries the hypermutable CGG repeat in the 5' untranslated portion of its first exon. Mild mental retardation without consistent physical findings has been found associated with expanded CCG repeats at FRAXE. We have identified a large gene (FMR2) transcribed distally from the CpG island at FRAXE, and down-regulated by repeat expansion and methylation. The gene is novel, expressed in adult brain and placenta, and shows similarity with another human protein, MLLT2, expressed from a gene at chromosome 4q21 involved in translocations found in acute lymphoblastic leukaemia (ALL) cells. Identification of this gene will facilitate further studies to determine the role of its product in FRAXE associated mental deficiency.
Keywords: Adult; Amino Acid Sequence; Base Sequence; Brain; Chromosomes, Human, Pair 4; Cloning, Molecular; Dinucleoside Phosphates; DNA Primers; Female; Fragile X Syndrome; Gene Expression; Humans; Intellectual Disability; Molecular Sequence Data; Nuclear Proteins; Organ Specificity; Placenta; Polymerase Chain Reaction; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pregnancy; Protein Biosynthesis; Proteins; Repetitive Sequences, Nucleic Acid; RNA, Messenger; Sequence Homology, Amino Acid; Trans-Activators; Transcription, Genetic; X Chromosome

Improved ligation-anchored PCR strategy for identification of 5' ends of transcripts. - Ansari-Lari, M A; Jones, S N; Timms, K M; Richard A Gibbs (Biotechniques, 1996)
Keywords: Alternative Splicing; Animals; Bacteriophage T4; Biotin; DNA Primers; DNA, Complementary; Exons; Humans; Mice; Nuclear Proteins; Polymerase Chain Reaction; Proto-Oncogene Proteins; Proto-Oncogene Proteins c-mdm2; RNA Ligase (ATP); RNA, Messenger; Thiolester Hydrolases; Ubiquitin Thiolesterase

Method for 96-well M13 DNA template preparations for large-scale sequencing. - Andersson, B; Lu, J; Edwards, K E; Donna M Muzny; Richard A Gibbs (Biotechniques, 1996)
Efficient preparation of DNA templates is an important step in large-scale DNA sequencing. The ensure high-quality sequence data, we have prepared M13 phage DNA templates using a glass fiber-filtration method. We present the adaptation of this protocol to a 96-well format using commercially available filter plates. Two variations are described: one using polyethylene glycol precipitation and a second where the phage particles are disrupted before filtration, thus eliminating the need for precipitation. Using either of these protocols, 96 templates can be prepared in less than 2 h. Sufficient DNA for 1-2 dye primer sequencing reactions is routinely obtained from 1 mL of culture, and the resulting sequence data are of high quality.
Keywords: Bacteriophage M13; DNA, Viral; Genetic Vectors; Polyethylene Glycols; Polymerase Chain Reaction; Sequence Analysis, DNA; Templates, Genetic

A recombination hotspot responsible for two inherited peripheral neuropathies is located near a mariner transposon-like element. - Reiter, L T; Murakami, T; Koeuth, T; Pentao, L; Donna M Muzny; Richard A Gibbs; James R Lupski (Nat Genet, 1996)
The Charcot-Marie Tooth disease type 1A (CMT1A) duplication and hereditary neuropathy with liability to pressure palsies (HNPP) deletion are reciprocal products of an unequal crossing-over event between misaligned flanking CMT1A-REP repeats. The molecular aetiology of this apparently homologous recombination event was examined by sequencing the crossover region. Through the detection of novel junction fragments from the recombinant CMT1A-REPs in both CMT1A and HNPP patients, a 1.7-kb recombination hotspot within the approximately 30-kb CMT1A-REPs was identified. This hotspot is 98% identical between CMT1A-REPs indicating that sequence identity is not likely the sole factor involved in promoting crossover events. Sequence analysis revealed a mariner transposon-like element (MITE) near the hotspot which we hypothesize could mediate strand exchange events via cleavage by a transposase at or near the 3' end of the element.
Keywords: Amino Acid Sequence; Base Sequence; Charcot-Marie-Tooth Disease; DNA; DNA Transposable Elements; Gene Deletion; Humans; Molecular Sequence Data; Multigene Family; Peripheral Nervous System Diseases; Recombination, Genetic; Repetitive Sequences, Nucleic Acid; Restriction Mapping; Sequence Homology, Amino Acid

130 kb of DNA sequence reveals two new genes and a regional duplication distal to the human iduronate-2-sulfate sulfatase locus. - Timms, K M; Lu, F; Shen, Y; Pierson, C A; Donna M Muzny; Gu, Y; Nelson, D L; Richard A Gibbs (Genome Res, 1995)
Deficiency of IDs activity results in Hunter Syndrome (mucopolysaccharidosis type II), a fatal X-linked recessive disorder. We report characterization of 28 cosmids around the IDS locus in Xq28. Four overlapping cosmids have been sequenced in their entirety generating a 130-kb contig. These studies show the fine structure of the IDS gene and identify an IDS pseudogene-like structure located 20 kb distal to the active gene. Two novel genes have also been identified in this sequence, and one of these genes is also locally duplicated. Both homologs are expressed, and a number of alternative transcript products have been characterized. The presence of a highly conserved pseudogene-like structure within a larger duplicated region close to the IDS gene has significant implications for the study of mutations at this locus.
Keywords: Base Sequence; Chromosome Walking; Chromosomes, Artificial, Yeast; Cosmids; Gene Expression; Genes; Genetic Markers; Humans; Iduronate Sulfatase; Male; Mucopolysaccharidosis II; Multigene Family; Polymerase Chain Reaction; Pseudogenes; Repetitive Sequences, Nucleic Acid; RNA, Messenger; Sequence Alignment; Transcription, Genetic; X Chromosome

Accurate determination of DNA in agarose gels using the novel algorithm GelScann(1.0). - Metzker, M L; Allain, K M; Richard A Gibbs (Comput Appl Biosci, 1995)
GelScann(1.0) is a user-friendly program that accurately quantitates DNA from CCD imaged agarose gels. The algorithm automatically locates lanes, locates bands within a given lane, and quantitates the intensity of each band. GelScann (1.0) uses a statistical method to discriminate DNA from local background fluorescence. The sensitivity of the LaneFinder and BandFinder can be adjusted by the user interacting with GelScann (1.0)'s option box. We demonstrate that GelScann(1.0) can accurately determine DNA that GelScann(1.0) can accurately determine DNA concentrations for routine molecular biology applications and determine the relative intensities of PCR amplified fragments for genetic testing.
Keywords: Algorithms; Bacteriophage M13; DNA, Viral; Electrophoresis, Agar Gel; Female; Genetic Carrier Screening; HIV Infections; HIV-1; Humans; Image Processing, Computer-Assisted; Microcomputers; Muscular Dystrophies; Polymerase Chain Reaction

Analysis of human immunodeficiency virus type 1 integrase mutants. - Ansari-Lari, M A; Donehower, L A; Richard A Gibbs (Virology, 1995)
The human immunodeficiency virus type-1 (HIV-1) integrase protein (IN) mediates the insertion of linear double-stranded viral DNA into the host genome. Mutations in IN can have different effects on the virus life cycle. In this study, Gag-Pol polyprotein processing, Tat synthesis, and viral replication were investigated in integrase-defective HIV-1 mutants. In the absence of IN synthesis, the Gag-Pol polyprotein stability, packaging, and/or processing was reduced. There was limited expression of Tat observed in IN mutants, but no viral replication.
Keywords: Base Sequence; Blotting, Western; Cell Line; Defective Viruses; DNA Nucleotidyltransferases; DNA Primers; Gene Products, gag; Gene Products, pol; Genome, Viral; HIV Reverse Transcriptase; HIV-1; Humans; Integrases; Molecular Sequence Data; Point Mutation; Polymerase Chain Reaction; RNA-Directed DNA Polymerase; Transfection; Viral Proteins

Complete sequence of a 38.4-kb human cosmid insert containing the polymorphic marker DXS455 from Xq28. - Andersson, B; Lu, F; Donna M Muzny; Warren, S T; Richard A Gibbs (DNA Seq, 1995)
The complete DNA sequence of a cosmid mapping to human Xq28 (DXS455) has been determined using a shotgun approach (genbank accession number: L31948). The cosmid insert is 38.4 kb in length, and contains several repetitive sequences, including a highly repetitive region located in a fragment previously shown to contain a polymorphic VNTR locus, as well as short di- and tri-nucleotide repeats. In addition to the previously known VNTR locus, a CA-repeat and an unusual 800-bp repetitive region have been found to be polymorphic. The repeated sequence mapping to the site of the VNTR locus spans 480 bp in the cosmid. In addition to several AT-dinucleotide stretches, this repeat has four copies of a 25 bp repeat unit and flanking sequences similar to this 25-mer. No expressed sequences have so far been identified in this cosmid.
Keywords: Bacteriophage M13; Base Sequence; Cosmids; DNA; Gene Library; Genetic Markers; Humans; Minisatellite Repeats; Molecular Sequence Data; Repetitive Sequences, Nucleic Acid; X Chromosome

Detection and genetic analysis of beta-thalassemia mutations by competitive oligopriming. - Athanassiadou, A; Papachatzopoulou, A; Richard A Gibbs (Hum Mutat, 1995)
A new approach for the detection of beta-thalassemia mutations has been applied, based on competitive oligonucleotide priming (COP) of in vitro DNA amplification at the mutation site. This method allows genotyping of the template DNA, through differential labeling of the allele-specific competitive oligoprimers and biotinylation of the common reverse primer. The system provides a basis for rapid, simple, and reliable detection of the numerous known beta-thalassemia mutations, revealing the precise nature of the mismatch in each case, and thereby facilitating the molecular genetic analysis of the disease.
Keywords: Base Sequence; beta-Thalassemia; DNA; DNA Mutational Analysis; DNA Primers; Globins; Humans; Molecular Sequence Data; Oligodeoxyribonucleotides

Pressing ahead with human genome sequencing. - Richard A Gibbs (Nat Genet, 1995)
While waiting for revolutionary techniques to emerge, conventional approaches have been used to generate more than 40 million bases of DNA sequence from large scale projects involving different organisms. About eight megabases are from the human genome. Does this progress signal the time to move ahead for a massive human genomic sequencing effort, or should we bide our time, waiting for more technical developments? The answer is to move ahead now, choosing carefully those strategies that can be easily adapted to future methodologies.
Keywords: Animals; Base Sequence; Caenorhabditis; DNA; Genome, Fungal; Genome, Human; Human Genome Project; Humans; Molecular Sequence Data; Saccharomyces cerevisiae

Sixty-nine kilobases of contiguous human genomic sequence containing the alpha-galactosidase A and Bruton's tyrosine kinase loci. - Oeltjen, J C; Liu, X; Lu, J; Allen, R C; Donna M Muzny; Belmont, J W; Richard A Gibbs (Mamm Genome, 1995)
Several disease loci have been mapped to the Xq21.3-Xq22 region of the human X Chromosome (Chr) including X-linked agammaglobulinemia (XLA), Fabry disease, Alport syndrome, and Pelizaeus Merzbacher disease. Upon cloning of the XLA gene, Bruton's tyrosine kinase (btk), both Fabry disease and XLA were mapped within the same 50- to 70-kb interval. In order to investigate the genomic organization of the region surrounding btk and the Fabry disease gene, alpha-galactosidase A (gla), we constructed a 6-cosmid contig spanning the region from 5' of gla to 3' of btk. Two of these cosmids spanning most of the coding sequence and the upstream region of btk and gla, U237D10 and U230D1, were sequenced by a random shotgun strategy combined with automated sequencing, resulting in 69 kb of contiguous genomic sequence. Sequencing of U237D10 showed btk to be comprised of 19 exons spanning over 35 kb. Sequencing of U230D1 showed that the 3' end of gla is 9 kb from the 5' end of btk and also demonstrated the presence of two additional genes in the region immediately 5' to btk. The surprisingly high gene density is similar to that seen previously only in the human major histocompatibility locus.
Keywords: Agammaglobulinaemia Tyrosine Kinase; alpha-Galactosidase; Amino Acid Sequence; Base Sequence; Cosmids; Fabry Disease; Gene Library; Humans; Introns; Molecular Sequence Data; Protein-Tyrosine Kinases; Repetitive Sequences, Nucleic Acid; X Chromosome

Working on the assembly line. - Richard A Gibbs; Cockerill, M (Trends Biochem Sci, 1995)
Keywords: Base Sequence; DNA; Molecular Sequence Data; Sequence Analysis, DNA; Software

Adaptor-based uracil DNA glycosylase cloning simplifies shotgun library construction for large-scale sequencing. - Andersson, B; Povinelli, C M; Wentland, M A; Shen, Y; Donna M Muzny; Richard A Gibbs (Anal Biochem, 1994)
An improved strategy for the preparation of libraries for the random sequencing of DNA is reported. The protocol is a modification of a previous adaptor-based strategy, and utilizes long (11 base) overhangs, which eliminates the unreliable step of vector-insert ligation. The random inserts are prepared by adaptor ligation, while the M13 vector is prepared as described for uracil DNA glycosylase (UDG) cloning of polymerase chain reaction (PCR) products, using PCR with uracil-containing primers, followed by UDG treatment to produce overhangs. This method has been found to reliably yield large numbers of clones. There is no background due to religation of the vector, and all clones contain inserts. In addition, the method is simple and suitable for export to other investigators. Libraries were constructed from cosmids containing human DNA and from human cDNAs in order to characterize a strategy for shotgun sequencing of multiple shorter fragments.
Keywords: Base Sequence; Cloning, Molecular; DNA Glycosylases; DNA Primers; DNA, Complementary; Genomic Library; Humans; Molecular Sequence Data; N-Glycosyl Hydrolases; Polymerase Chain Reaction; Sequence Analysis, DNA; Uracil-DNA Glycosidase

Analysis of HIV type 1 reverse transcriptase expression in a human cell line. - Ansari-Lari, M A; Richard A Gibbs (AIDS Res Hum Retroviruses, 1994)
The functional analysis of human immunodeficiency virus type-1 (HIV-1) reverse transcriptase (RT) subunits on transient and constitutive expression, in the absence or presence of the HIV-1 protease (PR) expression, in a human cell line is described. HIV-1 RT is a heterodimer composed of a 51-kDa subunit (p51) and a 66-kDa subunit (p66). Cloning and expression of the RT region of the HIV-1 pol gene in the HT-1080 human fibrosarcoma cell line yielded p66 without any detectable p51 and a low level of RT activity could be measured. Transient expression of PR and RT in cis generated p51 and p66, but when RT and PR were expressed in trans only p66 was produced. Attempts to establish a stable cell line expressing the PR-RT region of the pol gene were hampered by an apparent intolerance of HT-1080 cells to the HIV-1 PR expression. Therefore, to generate p51 independent of PR expression, the 51-kDa subunit was cloned separately. p51 lacked detectable RT activity. Coexpression of p51 and p66 resulted in a dramatic increase in RT activity. Stable HT-1080 cells producing both p51 and p66 exhibited on average a 15-fold increase in RT activity compared to the parental cell line. Immunofluorescence revealed a diffuse cytoplasmic localization of p51 and p66. To date, this is the first example of a human cell line that is constitutively expressing HIV-1 RT in the absence of HIV-1 infection.
Keywords: Base Sequence; Cell Line; Cloning, Molecular; DNA Primers; Fibrosarcoma; Fluorescent Antibody Technique; Genes, pol; HIV Protease; HIV Reverse Transcriptase; HIV-1; Humans; Macromolecular Substances; Molecular Sequence Data; Molecular Weight; Polymerase Chain Reaction; Recombinant Proteins; Restriction Mapping; RNA-Directed DNA Polymerase; Transfection; Tumor Cells, Cultured

Fine structure of the human FMR1 gene. - Eichler, E E; Stephen Richards; Richard A Gibbs; Nelson, D L (Hum Mol Genet, 1994)
Keywords: Base Sequence; Exons; Fragile X Mental Retardation Protein; Fragile X Syndrome; Genes; Humans; Molecular Sequence Data; Nerve Tissue Proteins; RNA-Binding Proteins

Multiplex PCR: advantages, development, and applications. - Edwards, M C; Richard A Gibbs (PCR Methods Appl, 1994)
Keywords: Animals; Bacteria; Gene Deletion; Humans; Mutation; Polymerase Chain Reaction; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; Templates, Genetic; Viruses

A novel beta-thalassaemia mutation in the 5' untranslated region of the beta-globin gene. - Athanassiadou, A; Papachatzopoulou, A; Zoumbos, N; Maniatis, G M; Richard A Gibbs (Br J Haematol, 1994)
A thymidine deletion at position +10 of the 5' untranslated region of the beta-globin gene was detected in a beta-thalassaemia intermedia patient carrying a beta(0)39 stop codon mutation on the other chromosome; this new mutation, +10(-T), was detected by automated fluorescent DNA sequencing and verified by dot-blot allele-specific hybridizations. The +10(-T) mutation is a 'silent carrier', is associated with a reduced amount of steady-state beta-globin mRNA, and establishes a connection between the 5' untranslated region of the beta-globin gene and the regulation of its expression.
Keywords: Aged; Base Sequence; beta-Thalassemia; Blotting, Northern; DNA Mutational Analysis; Female; Globins; Humans; Molecular Sequence Data; RNA, Messenger; Sequence Deletion; Thymidine

Termination of DNA synthesis by novel 3'-modified-deoxyribonucleoside 5'-triphosphates. - Metzker, M L; Raghavachari, R; Stephen Richards; Jacutin, S E; Civitello, A; Burgess, K; Richard A Gibbs (Nucleic Acids Res, 1994)
Eight 3'-modified-dNTPs were synthesized and tested in two different DNA template assays for incorporation activity. From this enzymatic screen, two 3'-O-methyl-dNTPs were shown to terminate DNA syntheses mediated by a number of polymerases and may be used as alternative terminators in Sanger sequencing. 3'-O-(2-Nitrobenzyl)-dATP is a UV sensitive nucleotide and was shown to be incorporated by several thermostable DNA polymerases. Base specific termination and efficient photolytic removal of the 3'-protecting group was demonstrated. Following deprotection, DNA synthesis was reinitiated by the incorporation of natural nucleotides into DNA. The identification of this labile terminator and the demonstration of a one cycle stop-start DNA synthesis are initial steps in the development of a novel sequencing strategy.
Keywords: Base Sequence; Chromatography, High Pressure Liquid; Deoxyribonucleotides; DNA; DNA-Directed DNA Polymerase; Molecular Sequence Data; Molecular Structure; Templates, Genetic

Decreased expression of myotonin-protein kinase messenger RNA and protein in adult form of myotonic dystrophy. - Fu, Y H; Friedman, D L; Stephen Richards; Pearlman, J A; Richard A Gibbs; Pizzuti, A; Ashizawa, T; Perryman, M B; Scarlato, G; Fenwick, R G (Science, 1993)
The myotonic dystrophy mutation has recently been identified; however, the molecular mechanism of the disease is still unknown. The sequence of the myotonin-protein kinase gene was determined, and messenger RNA spliced forms were identified in various tissues. Antisera were developed for analytical studies. Quantitative reverse transcription-polymerase chain reaction and radioimmunoassay were used to demonstrate that decreased levels of the messenger RNA and protein expression are associated with the adult form of myotonic dystrophy.
Keywords: Adult; Alternative Splicing; Amino Acid Sequence; Base Sequence; Gene Expression; Humans; Molecular Sequence Data; Molecular Weight; Muscles; Myotonic Dystrophy; Myotonin-Protein Kinase; Polymerase Chain Reaction; Protein Kinases; Protein Serine-Threonine Kinases; RNA, Messenger

Detection and significance of HIV sequences in HIV infection. - Lewis, D E; Richard A Gibbs (Prog Med Virol, 1993)
Keywords: Base Sequence; DNA, Viral; HIV; HIV Infections; Humans; In Situ Hybridization; Molecular Sequence Data; Polymerase Chain Reaction; RNA, Viral; Sequence Analysis, DNA

Fine structure of the human FMR1 gene. - Eichler, E E; Stephen Richards; Richard A Gibbs; Nelson, D L (Hum Mol Genet, 1993)
The fragile X syndrome is due to a CGG triplet expansion in the first exon of FMR1, resulting in hypermethylation and extinction of gene expression. To further our understanding of the gene's involvement in the syndrome, we report the physical structure of this locus. A high resolution restriction map of the FRAX(A) locus has been prepared encompassing approximately 50 kb. Using exon-exon PCR and restriction analysis, the FMR1 gene has been determined to consist of 17 exons spanning 38 kb of Xq27.3. Each intron-exon boundary has been sequenced. In general, the splice donors and acceptors located in the 5' portion of the gene demonstrate greater adherence to consensus than those in the 3' end, providing a possible explanation for the finding of alternative splicing in FMR1. The elucidation of the exon composition of the FMR1 gene and its flanking region will enhance detection of coding sequence mutations possible in fragile X phenocopy individuals.
Keywords: Alternative Splicing; Base Sequence; Cloning, Molecular; Cosmids; Exons; Fragile X Mental Retardation Protein; Fragile X Syndrome; Humans; Introns; Molecular Sequence Data; Nerve Tissue Proteins; Oligodeoxyribonucleotides; Polymerase Chain Reaction; Repetitive Sequences, Nucleic Acid; Restriction Mapping; RNA, Messenger; RNA-Binding Proteins; X Chromosome

Large-scale sequencing library production: an adaptor-based strategy. - Povinelli, C M; Richard A Gibbs (Anal Biochem, 1993)
A significant bottleneck in large-scale DNA sequencing projects is the creation of high-quality random libraries suitable for sequencing. We have utilized an adaptor-based strategy and developed a simple protocol to reliably generate single-insert random subclone M13 libraries yielding uniform coverage and > 10(3) clones per microgram of DNA. Of the resulting white plaques, 95% contained inserts, < 0.5% were due to adaptors with no insert, and none of the clones were found to contain extraneous DNA (0/600) or multiple inserts (0/300).
Keywords: Base Sequence; Biotechnology; CD4 Antigens; Cloning, Molecular; DNA; Evaluation Studies as Topic; Gene Library; Genetic Techniques; Genetic Vectors; Humans; Molecular Sequence Data; Sequence Analysis, DNA; Software Design

Multiplex DNA amplification and solid-phase direct sequencing for mutation analysis at the hprt locus in Chinese hamster cells. - Zu, Z; Yu, Y; Richard A Gibbs; Caskey, C T; Hsie, A W (Mutat Res, 1993)
We report here the development of multiplex in vitro DNA amplification and solid-phase direct exon sequencing for the analysis of mutations at the hypoxanthine-guanine phosphoribosyltransferase (hprt) locus in Chinese hamster cells. 18 representative HPRT-deficient mutants, derived either spontaneously, or after exposure to UV light or ionizing radiation, were analyzed. All 9 hprt exons were simultaneously amplified via the polymerase chain reaction (PCR) for rapid deletion detection. 5 mutants involve single- or multiple-exon deletions. Altered multiplex PCR patterns were detected in mutants Bsp-040, Bsp-065 and BGR-606. Subsequent direct sequence analysis reveals that Bsp-040 and Bsp-065 carry a 52-bp and a 13-bp intragenic DNA deletion in exon 3, respectively. BGR-606 contains a 223-bp insertion accompanied by a 10-bp deletion of intron sequence within exon 4 fragment. Other subtle DNA alterations identified by direct exon sequence analysis include single-base substitutions, small deletions and insertions, and RNA splicing mutations.
Keywords: Animals; Base Sequence; CHO Cells; Chromosome Mapping; Cricetinae; DNA Mutational Analysis; Hypoxanthine Phosphoribosyltransferase; Molecular Sequence Data; Mutation; Polymerase Chain Reaction; Sequence Analysis, DNA

Rapid characterization of HIV-1 sequence diversity using denaturing gradient gel electrophoresis and direct automated DNA sequencing of PCR products. - Andersson, B; Ying, J H; Lewis, D E; Richard A Gibbs (PCR Methods Appl, 1993)
A direct method for visualization and isolation of sequence variants of human immunodeficiency virus type 1 (HIV-1) utilizing denaturing gradient gel electrophoresis (DGGE) combined with automated direct DNA sequencing was developed. Two fragments from the env gene and one from the nef gene of HIV-1, which together constitute approximately 1.0 kb of sequence, were amplified by PCR and analyzed. HIV-1 variants from each region were resolved and excised from the gel; this was followed by direct sequencing of different viral variants. In 9 infected patients, a limited number of dominant sequence variants could be seen in the three regions, together with a faint background of minor variants. The use of DGGE makes it possible to obtain a direct estimate of overall HIV-1 sequence diversity within patient samples without an intermediate DNA cloning step.
Keywords: Base Sequence; DNA, Viral; Electrophoresis; HIV-1; Humans; Molecular Sequence Data; Polymerase Chain Reaction; Sequence Analysis, DNA

Genotypic confirmation from the original dried blood specimens in a neonatal hemoglobinopathy screening program. - Descartes, M; Huang, Y; Zhang, Y H; McCabe, L L; Richard A Gibbs; Therrell, B L; McCabe, E R (Pediatr Res, 1992)
Dried blood spots are used for newborn screening because of ease of sample collection, handling, and shipment. DNA is stable and accessible in the filter paper matrix. Genotypic confirmation using initial specimens is demonstrated for a regional screening program. Seventy-five blinded samples underwent DNA analysis after Hb electrophoresis. DNA was microextracted from a 1/2-inch semicircle (25 microL whole blood equivalent), amplified, and analyzed by four different methods. Direct amplification without microextraction and automated sequencing from microextracted DNA also was performed. All four analyses agreed for the A and S alleles in 70 of 75 specimens. Three disagreements were clarified by the other semicircle from the original sample: two were due to polymerase chain reaction contamination and one to contamination of one of four analytical tests. Two would have required analysis of a second specimen, one because of polymerase chain reaction failure and the second because the patient had S/beta-thalassemia. Direct amplification without microextraction was successful in an additional 77 of 78 specimens for analysis of the A, S, C, and E alleles. Automated direct sequencing from microextracted DNA was demonstrated for the A, S, and C alleles. Analysis of microextracted DNA from dried blood specimens for A and S alleles reduced the need for and costs of obtaining a second specimen for confirmation by 97%. Direct amplification without microextraction for analysis of A, S, and C alleles permits additional reduction in personnel time and costs. We have demonstrated that microextracted DNA is amenable to automated sequencing after asymmetric polymerase chain reaction. Direct genotypic confirmation can facilitate diagnosis and initiation of medical intervention.
Keywords: Alleles; Base Sequence; Blood Specimen Collection; DNA Mutational Analysis; Genotype; Hemoglobinopathies; Hemoglobins, Abnormal; Humans; Infant, Newborn; Mass Screening; Molecular Sequence Data

A human dimorphism resulting from loss of an Alu. - Edwards, M C; Richard A Gibbs (Genomics, 1992)
The molecular phylogeny of Alu and other repeated sequences in the human genome provides clues to events during primate evolution. A subclass of human Alu's has been previously identified as dimorphic insertions within members of the medium reiteration frequency (mer) class of repeats, reflecting the complicated sequence of insertion and radiation events leading to the current human genome structure. One dimorphic Alu is located within a previously unidentified mer family member, in the first intron of the human T4 (CD4) gene. The insertion (Alu+ allele) has a frequency of approximately 70% in Europeans and Africans and is homozygous in 20 Asian samples. Polymerase chain reaction amplification, direct DNA sequencing, and Southern analysis using oligonucleotide probes revealed that the Alu- allele was derived from the Alu+ allele by loss of part of the inserted sequence. Comparison with a tightly linked marker within the human genome and studies of baboon DNA samples revealed that the original insertion was a relatively early event in primate evolution, but that the Alu sequence loss leading to the dimorphism has occurred much more recently. Loss of Alu insertions therefore represents one mechanism for the generation of human Alu dimorphisms.
Keywords: Animals; Base Sequence; Blotting, Southern; CD4 Antigens; DNA; Genetic Linkage; Humans; Molecular Sequence Data; Papio; Polymerase Chain Reaction; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; Retroviruses, Simian; Sequence Homology, Nucleic Acid

Identification of a 2 base pair nonsense mutation causing a cryptic splice site in a DMD patient. - Winnard, A V; Jia-Hsu, Y; Richard A Gibbs; Mendell, J R; Burghes, A H (Hum Mol Genet, 1992)
Keywords: Amino Acid Sequence; Base Sequence; DNA; Female; Humans; Molecular Sequence Data; Muscular Dystrophies; Mutation; Polymerase Chain Reaction; RNA Splicing; RNA, Messenger

Polymerase chain reaction-based comprehensive procedure for the analysis of the mutation spectrum at the hypoxanthine-guanine phosphoribosyltransferase locus in Chinese hamster cells. - Yu, Y J; Xu, Z; Richard A Gibbs; Hsie, A W (Environ Mol Mutagen, 1992)
We have established a comprehensive procedure based on the polymerase chain reaction (PCR) to analyze the molecular spectrum of mutations at the hypoxanthine-guanine phosphoribosyltransferase (hprt) locus in Chinese hamster cells. The procedure includes direct sequencing of PCR-amplified hprt cDNA for locating point mutations in the expressed coding sequences, multiplex PCR amplification of the hprt exons for screening large deletions, and direct sequencing of PCR-amplified hprt exons and their flanking regions for detecting intronic mutations resulting in mRNA splicing errors. Using this procedure, we have identified different types of mutations among a representative collection of spontaneous and induced HPRT-deficient Chinese hamster cell mutants. This procedure is simple, rapid, accurate, and practical for a comprehensive study of the mutation spectrum in a large number of HPRT-deficient Chinese hamster cell mutants.
Keywords: Animals; Base Sequence; CHO Cells; Cricetinae; DNA; Exons; Hypoxanthine Phosphoribosyltransferase; Molecular Sequence Data; Mutation; Polymerase Chain Reaction

A simple protocol for the automation of DNA cycle sequencing reactions and polymerase chain reactions. - Civitello, A B; Stephen Richards; Richard A Gibbs (DNA Seq, 1992)
Automated DNA sequencing methods using robotic workstations have been previously reported, however it is often an arduous task to import these technologies into a laboratory. We describe protocols making use of a Beckman Biomek 1000 robotic workstation to prepare polymerase chain reactions (PCRs) and "cycle sequencing" reactions to be performed in a Perkin Elmer Cetus System 9600 thermocycler. The combination of these two instruments allows a high throughput of PCR and DNA sequencing reactions. The programs described are freely available via anonymous file transfer protocol (FTP).
Keywords: Bacteriophage M13; Base Sequence; DNA, Viral; Electrophoresis, Agar Gel; Molecular Sequence Data; Polymerase Chain Reaction; Robotics; Sequence Analysis, DNA

A transposon-like element in the deletion-prone region of the dystrophin gene. - Pizzuti, A; Pieretti, M; Fenwick, R G; Richard A Gibbs; Caskey, C T (Genomics, 1992)
The central portion of the dystrophin gene locus is a preferential site for deletions causing progressive muscular dystrophy of the Duchenne type (DMD). The nucleotide sequence of a deletion junction fragment from a DMD patient was determined, revealing that the proximal breakpoint of the deletion in intron 43 fell within the sequence of a transposon-like element. This segment, belonging to the THE-1 family of human transposable elements, is normally present in a complete form in intron 43 of the dystrophin gene. The deletion mutation was maternally transmitted and eliminated two-thirds of the THE-1 element. Analysis of DNA from additional DMD patients revealed a second deletion with the proximal breakpoint mapping within the same THE-1 element.
Keywords: Base Sequence; Chromosome Deletion; DNA; DNA Mutational Analysis; DNA Transposable Elements; Dystrophin; Humans; Introns; Male; Molecular Sequence Data; Muscular Dystrophies; Restriction Mapping; Sequence Homology, Nucleic Acid

Alu-primed polymerase chain reaction for regional assignment of 110 yeast artificial chromosome clones from the human X chromosome: identification of clones associated with a disease locus. - Nelson, D L; Ballabio, A; Victoria, M F; Pieretti, M; Bies, R D; Richard A Gibbs; Maley, J A; Chinault, A C; Webster, T D; Caskey, C T (Proc Natl Acad Sci U S A, 1991)
Over 400 yeast artificial chromosome (YAC) clones were isolated from the human X chromosome, and 110 of these were assigned to regions defined by chromosome translocation and deletion breakpoints. Polymerase chain reaction using Alu primers was applied to YAC clones in order to generate probes, to identify overlapping clones, and to derive "fingerprints" and sequence data directly from total yeast DNA. Several clones were identified in regions of medical interest. One set of three overlapping clones was found to cross a chromosomal translocation implicated in Lowe syndrome. The regional assignment of groups of YAC clones provides initiation points for further attempts to develop large cloned contiguous sequences, as well as material for investigation of regions involved in genetic diseases.
Keywords: Base Sequence; Blotting, Southern; Chromosome Mapping; Chromosomes, Fungal; Cloning, Molecular; Deoxyribonucleases, Type II Site-Specific; Gene Library; Genetic Diseases, Inborn; Humans; Molecular Sequence Data; Nucleotide Mapping; Oligonucleotide Probes; Polymerase Chain Reaction; Restriction Mapping; Saccharomyces cerevisiae; X Chromosome

Carrier detection and prenatal diagnosis in Duchenne and Becker muscular dystrophy families, using dinucleotide repeat polymorphisms. - Clemens, P R; Fenwick, R G; Chamberlain, J S; Richard A Gibbs; de Andrade, M; Chakraborty, R; Caskey, C T (Am J Hum Genet, 1991)
To improve carrier detection and prenatal diagnosis for Duchenne and Becker muscular dystrophy families, we determined allele frequencies and measures of variation for four (dC-dA)n.(dG-dT)n loci identified within a deletion-prone region of the human dystrophin gene. The loci are highly polymorphic, with predicted heterozygosities of 71.6%-93.3%. Direct DNA sequence analysis of the (dC-dA)n.(dG-dT)n locus in intron 49 revealed an additional length polymorphism which varies by single-basepair increments, is adjacent to the dinucleotide repeat block, and enhances the polymorphic content of this marker. The four (dC-dA)n.(dG-dT)n loci are each easily amplified by PCR in two diplex reactions. The variability of allele lengths at these loci makes them ideal for carrier detection and prenatal diagnosis, often providing diagnostic information when RFLP analysis is uninformative. These markers have aided in identification of deletion mutations, exclusion of maternal cell contamination of chorionic villus samples, confirmation of paternity, and mapping of gene recombinations. The allele identification of these loci can be performed either with a radiolabel or with an automated, nonradioactive, fluorescent gel detection system.
Keywords: Alleles; Base Sequence; Cells, Cultured; Dystrophin; Female; Gene Frequency; Genetic Carrier Screening; Genetic Markers; Humans; Male; Molecular Sequence Data; Muscular Dystrophies; Pedigree; Polydeoxyribonucleotides; Polymerase Chain Reaction; Polymorphism, Genetic; Pregnancy; Prenatal Diagnosis; Repetitive Sequences, Nucleic Acid

Evolution of human immunodeficiency virus type 1 nucleotide sequence diversity among close contacts. - Burger, H; Weiser, B; Flaherty, K; Gulla, J; Nguyen, P N; Richard A Gibbs (Proc Natl Acad Sci U S A, 1991)
The degree of change in the nucleotide sequence of human immunodeficiency virus type 1 (HIV-1) that occurs when it is transmitted sexually from one individual to another or vertically from mother to child is unknown. Previous studies have shown that most cultured HIV-1 isolates from the same individuals differed in the entire envelope gene nucleotide sequence by up to 2%, although most isolates from unrelated individuals differed by 6-22%. To examine diversity among HIV-1 isolates from close contacts, we determined the nucleotide sequences of viruses from a family with a known epidemiologic profile, in which a woman transmitted HIV-1 heterosexually to her partner and vertically to her daughter. Direct DNA sequence analysis of primary HIV-1 isolates amplified by PCR was used to distinguish the major and minor viral sequences, termed quasispecies, to rapidly determine the predominant sequences and their phylogenetic relationships. The nucleotide sequence diversity of a major portion of the HIV-1 envelope gene was 3.7% between isolates from the woman and her heterosexual partner and 8.5% between isolates from this woman and her daughter, who had been infected for a longer period than the partner. The configuration of the phylogenetic tree demonstrated that the daughter's predominant isolate evolved from a progenitor of her mother's current strain. This study provides evidence of a continuous spectrum of sequence diversity between any two isolates ranging from those derived from the same person to those from close contacts and, ultimately, those from unrelated individuals. These data and methods can be applied to epidemiologic investigations of possible HIV-1 transmission between health care workers and their patients.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; Amino Acid Sequence; Base Sequence; Biological Evolution; DNA, Viral; Female; Genes, env; Genetic Variation; HIV-1; Humans; Male; Molecular Sequence Data; Oligodeoxyribonucleotides; Phylogeny; Polymerase Chain Reaction; Sequence Homology, Nucleic Acid

Fidelity of targeted recombination in human fibroblasts and murine embryonic stem cells. - Zheng, H; Hasty, P; Brenneman, M A; Grompe, M; Richard A Gibbs; Wilson, J H; Bradley, A (Proc Natl Acad Sci U S A, 1991)
Targeted recombination in murine embryonic stem cells promises to be a powerful tool for introducing specific mutations into target genes to study development in mice and to create animal models of human disease. Gene targeting also holds potential for correcting genetic defects as an approach to human gene therapy. To precisely modify target genes, homologous recombination must proceed with high fidelity. However, several results have suggested that targeted recombination may be highly mutagenic. To test the accuracy of gene targeting we analyzed 44 independent targeted recombinants at the hypoxanthine phosphoribosyltransferase (HPRT) locus in a human fibroblast cell line and in mouse embryonic stem cells. We surveyed 80 kilobases around the sites of recombination by using chemical cleavage of mismatches. Only two mutations were found: a T----G transversion and a thymidine deletion. Thus, gene targeting in mammalian cells can be extremely accurate. These results demonstrate the feasibility of generating precise modifications of mammalian genomes by gene targeting.
Keywords: Animals; Base Sequence; Fibroblasts; Genetic Vectors; Humans; Hypoxanthine Phosphoribosyltransferase; In Vitro Techniques; Mice; Molecular Sequence Data; Oligonucleotides; Polymerase Chain Reaction; Recombination, Genetic; Stem Cells

The molecular characterisation of HPRT CHERMSIDE and HPRT COORPAROO: two Lesch-Nyhan patients with reduced amounts of mRNA. - Gordon, R B; Dawson, P A; Sculley, D G; Emmerson, B T; Caskey, C T; Richard A Gibbs (Gene, 1991)
A complete deficiency of the purine salvage enzyme, hypoxanthine phosphoribosyltransferase (HPRT; EC 2.4.2.8), in man results in the Lesch-Nyhan (LN) syndrome. Two unrelated patients with the full LN syndrome showed no evidence of a major alteration to the gene encoding HPRT (HPRT) by restriction endonuclease analysis, but exhibited negligible levels of HPRT mRNA on Northern blots. DNA from these patients was characterised further. Amplification, by the polymerase chain reaction (PCR), of individual HPRT-exon fragments from genomic DNA followed by nucleotide (nt) sequence analysis using automated technology, revealed single-base mutations in each patient. One patient has an insertion of a T within exon-2, which places a stop codon in frame, presumably resulting in premature termination of translation of the HPRT mRNA. The other patient has a G----A base substitution at the 5' end of intron-6, at the junction of exon-6 and intron-6. Although dot blot analysis indicated negligible HPRT mRNA in lymphoblast cells from both patients, we were successful in amplifying HPRT cDNA using PCR. Direct nt sequence analysis of the amplified cDNA confirmed the insertion of a T in exon-2 in the one patient and revealed a complete deletion of exon-6 in the other patient, the latter event presumably arising due to aberrant splicing of primary message. Both mutations were also confirmed by hybridisation of amplified genomic DNA with allele-specific oligodeoxyribonucleotide probes. This study illustrates two approaches for analysing DNA mutations at the molecular level and demonstrates the power of PCR technology in the study of genetic diseases.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Base Sequence; Blotting, Northern; Codon; Exons; Female; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Molecular Sequence Data; Mutation; Polymerase Chain Reaction; Protein Biosynthesis

Pentanucleotide repeat length polymorphism at the human CD4 locus. - Edwards, M C; Clemens, P R; Tristan, M; Pizzuti, A; Richard A Gibbs (Nucleic Acids Res, 1991)
Keywords: Base Sequence; Black People; CD4 Antigens; Chromosomes, Human, Pair 12; Exons; Humans; Molecular Sequence Data; Oligodeoxyribonucleotides; Polymerase Chain Reaction; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; White People

Polymerase chain reaction techniques. - Richard A Gibbs (Curr Opin Biotechnol, 1991)
Keywords: Animals; Base Sequence; Humans; Mutation; Oligonucleotides; Polymerase Chain Reaction

DNA amplification by the polymerase chain reaction. - Richard A Gibbs (Anal Chem, 1990)
The polymerase chain reaction (PCR) is a technique involving enzymatic amplification of nucleic acid sequences via repeated cycles of denaturation, oligonucleotide annealing, and DNA polymerase extension. PCR has revolutionized the practice of DNA technology as it allows virtually any nucleic acid sequence to be readily generated in vitro in relatively great abundance, so that subsequent analyses are not confounded by the presence of other DNA fragments or a lack of material with which to work. PCR also enables the sequence of individual DNA fragments to be altered. The method has advantages over conventional procedures for DNA cloning and analysis in many circumstances because it is faster, simpler, and more flexible. The total range and number of applications that have evolved in the short time since the first report of PCR are enormous. This review describes some of the history of PCR, the principle of the method, practical considerations for performing PCR, and a variety of applications.
Keywords: Gene Amplification; Genetic Engineering; Polymerase Chain Reaction

Long HIV-1 incubation periods and dynamics of transmission within a family. - Burger, H; Belman, A L; Grimson, R; Kaell, A; Flaherty, K; Gulla, J; Richard A Gibbs; Nguyun, P N; Weiser, B (Lancet, 1990)
The incubation period of human immunodeficiency virus type 1 (HIV-1) infection was studied in a family of five in which vertical and heterosexual transmission occurred from one index case. This investigation documented incubation periods of longer than 12 years in a mother and her daughter; although neither has symptoms, both are definitely infected and have very low CD4(+)-lymphocyte counts. The study confirmed the predictions of incubation periods longer than 10 years in a small proportion of infected individuals. It provides evidence that vertically HIV-1-infected teenagers can be expected to appear in the population.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; CD4-Positive T-Lymphocytes; Child; DNA, Viral; Family; Family Health; Female; HIV Antibodies; HIV Seropositivity; HIV-1; Humans; Leukocyte Count; Male; Sexual Behavior; Substance Abuse, Intravenous; Time Factors

Multiplex DNA deletion detection and exon sequencing of the hypoxanthine phosphoribosyltransferase gene in Lesch-Nyhan families. - Richard A Gibbs; Nguyen, P N; Edwards, A; Civitello, A B; Caskey, C T (Genomics, 1990)
The Lesch-Nyhan (LN) syndrome is a genetically lethal human neurological disease that results from mutations that inactivate the hypoxanthine phosphoribosyltransferase (HPRT) gene. The elucidation of the complete DNA sequence of the human HPRT gene locus has enabled the construction of multiple oligonucleotide primer sets for the simultaneous in vitro amplification of all nine HPRT exons. The multiplex polymerase chain reaction provides a facile assay for the detection of HPRT exon deletions and the reaction products can be analyzed by direct automated fluorescent DNA sequencing to identify subtle alterations in the gene. Alterations have been identified in the HPRT genes from 15 independent LN cases, and 10 LN family studies were performed. The sequencing method uses solid supports and is sufficiently simple and sensitive to be a favored approach for LN diagnosis. LN heterozygotes can be diagnosed without reference to the affected male. In addition, these procedures will be useful for somatic mutagenesis studies.
Keywords: Base Sequence; Chromosome Deletion; DNA; Exons; Female; Genes; Genetic Carrier Screening; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Male; Molecular Sequence Data; Pedigree; Polymerase Chain Reaction

PCR test for cystic fibrosis deletion. - Ballabio, A; Richard A Gibbs; Caskey, C T (Nature, 1990)
Keywords: Base Sequence; Chromosome Deletion; Cystic Fibrosis; Humans; Molecular Sequence Data; Nucleic Acid Amplification Techniques; Oligonucleotide Probes; Polymerase Chain Reaction

The use of primers from highly conserved pol regions to identify uncharacterized retroviruses by the polymerase chain reaction. - Donehower, L A; Bohannon, R C; Ford, R J; Richard A Gibbs (J Virol Methods, 1990)
Two degenerate oligonucleotide primers derived from regions of pol conserved among retroviruses have been synthesized. Polymerase chain reactions utilizing these primers amplify a 135-bp pol fragment in every retrovirus DNA tested to date. The polymerase chain reaction has been linked to a reverse transcriptase step so that a pol-specific DNA fragment can be obtained from a moderate amount of a purified retrovirus or viral RNA. The identity of an unknown retrovirus can be determined by sequencing of the amplified fragment following molecular cloning. This procedure was tested on an unidentified (non-HIV) retrovirus expressed by a B-cell lymphoma line obtained from an AIDS patient. Our PCR assay identified the retrovirus as being highly similar to Mason-Pfizer monkey virus (MPMV) and simian retrovirus 1, which are closely related immunosuppressive type D viruses that cause simian AIDS.
Keywords: Amino Acid Sequence; Base Sequence; DNA, Viral; Gene Amplification; Genes, pol; Humans; Molecular Sequence Data; Oligonucleotides; Polymerase Chain Reaction; Retroviridae; Retroviruses, Simian; RNA-Directed DNA Polymerase; Sequence Homology, Nucleic Acid; Simian Immunodeficiency Virus; Templates, Genetic

Automated DNA sequencing methods for detection and analysis of mutations: applications to the Lesch-Nyhan syndrome. - Edwards, A; Richard A Gibbs; Nguyen, P N; Ansorge, W; Caskey, C T (Trans Assoc Am Physicians, 1989)
Keywords: Base Sequence; Chromosome Deletion; DNA; Female; Genetic Carrier Screening; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Male; Mutation; Pedigree; Polymerase Chain Reaction; Polymorphism, Genetic; Pregnancy; Prenatal Diagnosis; Repetitive Sequences, Nucleic Acid; Restriction Mapping

Deletion screening at the hypoxanthine-guanine phosphoribosyltransferase locus in Chinese hamster cells using the polymerase chain reaction. - Xu, Z D; Yu, Y J; Hsie, A W; Caskey, C T; Rossiter, B; Richard A Gibbs (Teratog Carcinog Mutagen, 1989)
We have developed a rapid screening method using the polymerase chain reaction (PCR) for detecting deletion mutations at the hypoxanthine-guanine phosphoribosyltransferase (hprt) locus in Chinese hamster cells. DNA was extracted from spontaneous and ultraviolet (UV) light- and X-ray-induced hprt-deficient mutants. Two primer sets were used to amplify 276 bp and 344 bp fragments containing the entire exon 3 and exon 9 coding sequence, respectively. The PCR was performed using Taq DNA polymerase for 40 cycles, and the PCR product was directly analyzed for the presence of the respective amplified DNA using electrophoresis on agarose gels stained with ethidium bromide. With this assay, we have analyzed 39 independently derived hprt-deficient mutants. Four of ten spontaneous mutants were found to have deletions in exon 9. UV light produced mutants with predominantly wild-type amplification patterns (10/14). X-ray induced mostly deletion patterns (11/15); six of these occurred only in exon 9, and five occurred in both exons 3 and 9. These observations are consistent with the classical notion that UV light induces predominantly missense mutations and X-ray produces a high proportion of deletion mutations. Deletion mutations occurred most frequently at the 3' end of the hprt gene, suggesting the possible existence of hot spots for deletions in this region. The PCR assay for deletion detection has the advantage that it can be completed in less than 4 hr without using radioisotopes. This assay should be useful for routine deletion screening.
Keywords: Animals; Cells, Cultured; Chromosome Deletion; DNA; DNA-Directed DNA Polymerase; Electrophoresis, Agar Gel; Exons; Gene Amplification; Hypoxanthine Phosphoribosyltransferase; Ultraviolet Rays; X-Rays

Detection of single DNA base differences by competitive oligonucleotide priming. - Richard A Gibbs; Nguyen, P N; Caskey, C T (Nucleic Acids Res, 1989)
Synthetic DNA oligonucleotides can serve as efficient primers for DNA synthesis even when there is a single base mismatch between the primers and the corresponding DNA template. However, when the primer-template annealing is carried out with a mixture of primers and at low stringency the binding of a perfectly matched primer is strongly favored relative to a primer differing by a single base. This primer competition is observed over a range of oligonucleotide sizes from twelve to sixteen bases and with a variety of base mismatches. When coupled with the polymerase chain reaction, for the amplification of specific DNA sequences, competitive oligonucleotide priming provides a simple general strategy for the detection of single DNA base differences.
Keywords: Animals; Base Sequence; Binding, Competitive; DNA; DNA, Single-Stranded; DNA-Directed DNA Polymerase; Gene Amplification; Mice; Mice, Mutant Strains; Molecular Sequence Data; Mutation; Oligonucleotides; Taq Polymerase; Templates, Genetic

Identification of mutations leading to the Lesch-Nyhan syndrome by automated direct DNA sequencing of in vitro amplified cDNA. - Richard A Gibbs; Nguyen, P N; McBride, L J; Koepf, S M; Caskey, C T (Proc Natl Acad Sci U S A, 1989)
The Lesch-Nyhan (LN) syndrome is a severe X chromosome-linked disease that results from a deficiency of the purine salvage enzyme hypoxanthine phosphoribosyltransferase (HPRT). The mutations leading to the disease are heterogeneous and frequently arise as de novo events. We have identified nucleotide alterations in 15 independently arising HPRT-deficiency cases by direct DNA sequencing of in vitro amplified HPRT cDNA. We also demonstrate that the direct DNA sequence analysis can be automated, further simplifying the detection of new mutations at this locus. The mutations include DNA base substitutions, small DNA deletions, a single DNA base insertion, and errors in RNA splicing. The application of these procedures allows DNA diagnosis and carrier identification by the direct detection of the mutant alleles within individual families affected by LN.
Keywords: Alleles; Autoanalysis; Base Sequence; DNA; DNA-Directed DNA Polymerase; Gene Amplification; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Mutation; Nucleic Acid Hybridization; Oligonucleotide Probes; Pedigree; RNA Splicing; Software

Deletion screening of the Duchenne muscular dystrophy locus via multiplex DNA amplification. - Chamberlain, J S; Richard A Gibbs; Ranier, J E; Nguyen, P N; Caskey, C T (Nucleic Acids Res, 1988)
The application of recombinant DNA technology to prenatal diagnosis of many recessively inherited X-linked diseases is complicated by a high frequency of heterogeneous, new mutations (1). Partial gene deletions account for more than 50% of Duchenne muscular dystrophy (DMD) lesions, and approximately one-third of all cases result from a new mutation (2-5). We report the isolation and DNA sequence of several deletion prone exons from the human DMD gene. We also describe a rapid method capable of detecting the majority of deletions in the DMD gene. This procedure utilizes simultaneous genomic DNA amplification of multiple widely separated sequences and should permit deletion scanning at any hemizygous locus. We demonstrate the application of this multiplex reaction for prenatal and postnatal diagnosis of DMD.
Keywords: Base Sequence; Chromosome Deletion; Cloning, Molecular; DNA; Female; Gene Amplification; Humans; Male; Molecular Sequence Data; Muscular Dystrophies; Prenatal Diagnosis

Diagnosis of human heritable defects by recombinant DNA methods. - Caskey, C T; Richard A Gibbs; Witkowski, J A; Hejtmancik, J F (Philos Trans R Soc Lond B Biol Sci, 1988)
Recombinant DNA methods provide highly sensitive means for the detection of DNA alterations that lead to human disease mutations. In this paper I shall illustrate the approaches currently available and discuss new technologies that show promise of replacing the present methods. Medical diagnosis by means of recombinant DNA methods has an expanding role in clinical medicine.
Keywords: DNA, Recombinant; Female; Genetic Diseases, Inborn; Genetic Engineering; Genetic Techniques; Humans; Mutation; Pregnancy; Prenatal Diagnosis

Expression of the murine Duchenne muscular dystrophy gene in muscle and brain. - Chamberlain, J S; Pearlman, J A; Donna M Muzny; Richard A Gibbs; Ranier, J E; Caskey, C T; Reeves, A A (Science, 1988)
Complementary DNA clones were isolated that represent the 5' terminal 2.5 kilobases of the murine Duchenne muscular dystrophy (Dmd) messenger RNA (mRNA). Mouse Dmd mRNA was detectable in skeletal and cardiac muscle and at a level approximately 90 percent lower in brain. Dmd mRNA is also present, but at much lower than normal levels, in both the muscle and brain of three different strains of dystrophic mdx mice. The identification of Dmd mRNA in brain raises the possibility of a relation between human Duchenne muscular dystrophy (DMD) gene expression and the mental retardation found in some DMD males. These results also provide evidence that the mdx mutations are allelic variants of mouse Dmd gene mutations.
Keywords: Animals; Brain; DNA; DNA, Recombinant; Gene Expression Regulation; Intellectual Disability; Mice; Mice, Inbred ICR; Mice, Mutant Strains; Muscles; Muscular Dystrophy, Animal; Mutation; Nucleic Acid Hybridization; Ribonuclease, Pancreatic; RNA, Messenger

Generation of cDNA probes directed by amino acid sequence: cloning of urate oxidase. - Lee, C C; Wu, X W; Richard A Gibbs; Cook, R G; Donna M Muzny; Caskey, C T (Science, 1988)
Urate oxidase (E.C. 1.7.3.3) catalyzes the oxidation of uric acid to allantoin in most mammals except humans and certain primates. The amino-terminal amino acid sequence for porcine urate oxidase was determined and used in a novel procedure for generating complementary DNA (cDNA) probes to this amino acid sequence. The procedure is based on the polymerase chain reaction and utilizes mixed oligonucleotide primers complementary to the reverse translation products of an amino acid sequence. This rapid and simple cDNA cloning procedure is generally applicable and requires only a partial amino acid sequence. A cDNA probe developed by this procedure was used to isolate a full-length porcine urate oxidase cDNA and to demonstrate the presence of homologous genomic sequences in humans.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Cloning, Molecular; DNA; Gene Amplification; Liver; Mice; Molecular Sequence Data; Nucleic Acid Hybridization; Swine; Urate Oxidase

Identification and localization of mutations at the Lesch-Nyhan locus by ribonuclease A cleavage. - Richard A Gibbs; Caskey, C T (Science, 1987)
Many mutations leading to human disease are the result of single DNA base pair changes that cannot be identified by Southern analysis. This has prompted the development of alternative assays for point mutation detection. The recently described ribonuclease A cleavage procedure, with a polyuridylic acid-paper affinity chromatography step, has been used to identify the mutational lesions in the hypoxanthine phosphoribosyltransferase (HPRT) messenger RNAs of patients with Lesch-Nyhan syndrome. Distinctive ribonuclease A cleavage patterns were identified in messenger RNA from 5 of 14 Lesch-Nyhan patients who were chosen because no HPRT Southern or Northern blotting pattern changes had been found. This approach now allows HPRT mutation detection in 50 percent of the cases of Lesch-Nyhan syndrome. The polyuridylic acid-paper affinity procedure provides a general method for analysis of low abundance messenger RNAs.
Keywords: Cell Line; Chromosome Deletion; HeLa Cells; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Mutation; Nucleic Acid Hybridization; Ribonuclease, Pancreatic; RNA, Messenger

The molecular basis of the sparse fur mouse mutation. - Veres, G; Richard A Gibbs; Steven E Scherer; Caskey, C T (Science, 1987)
The ornithine transcarbamylase-deficient sparse fur mouse is an excellent model to study the most common human urea cycle disorder. The mutation has been well characterized by both biochemical and enzymological methods, but its exact nature has not been revealed. A single base substitution in the complementary DNA for ornithine transcarbamylase from the sparse fur mouse has been identified by means of a combination of two recently described techniques for rapid mutational analysis. This strategy is simpler than conventional complementary DNA library construction, screening, and sequencing, which has often been used to find a new mutation. The ornithine transcarbamylase gene in the sparse fur mouse contains a C to A transversion that alters a histidine residue to an asparagine residue at amino acid 117.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Disease Models, Animal; DNA; Genes; Mice; Mice, Mutant Strains; Mutation; Ornithine Decarboxylase; RNA, Messenger

Molecular characterization of 125I decay and X-ray-induced HPRT mutants in CHO cells. - Richard A Gibbs; Camakaris, J; Hodgson, G S; Martin, R F (Int J Radiat Biol Relat Stud Phys Chem Med, 1987)
The predominant initial lesion induced by 125I decay in DNa is a double-strand DNA break comprising a 'mini deletion' of up to several base pairs (bp). However, Southern analysis of the structure of 125I decay-induced HPRT mutants in Chinese hamster ovary cells revealed that most of the mutants are deletions of thousands of bps. A similar predominance of substantial deletions was also found in X-ray-induced mutants.
Keywords: Animals; Chromosome Deletion; Cricetinae; DNA Repair; Gamma Rays; Hypoxanthine Phosphoribosyltransferase; Iodine Radioisotopes; Mutation; Polymorphism, Restriction Fragment Length; X-Rays